Biosynthesis of highly pure poly-γ-glutamic acid for biomedical applications - Pereira, C.L.; Antunes, J.C.; Gonçalves, R.M.; Ferreira-da-Silva, F.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2012)
The remarkable properties of poly-aminoacids, mainly their biocompatibility and biodegradability, have prompted an increasing interest in these polymers for biomedical applications. Poly-γ-glutamic acid (γ-PGA) is one of the most interesting poly-aminoacids with potential applications as a biomaterial. Here we describe the production and characterization of γ-PGA by Bacillus subtilis natto. The γ-PGA was produced with low molecular weight (10-50 kDa), high purity grade (>99 %) and a D-/L-glutamate ratio of 50-60/50-40 %. To evaluate the feasibility of using this γ-PGA as a biomaterial, chitosan (Ch)/γ-PGA nanoparticles were prepared by the coacervation method at pH ranging from 3.0 to 5.0, with dimensions in the interval 214-221 nm with a poly-dispersion index of ca. 0.2. The high purity of γ-PGA produced by this method, which is firstly described here, renders this biopolymer suitable for biomedical applications. Moreover, the Ch/γ-PGA nanocomplexes developed in this investigation can be combined with biologically active substances for their delivery in the organism. The fact that the assembly between Ch and γ-PGA relies on electrostatic interactions enables addition of other molecules that can be released into the medium through changes from acidic to physiological pH, without loss in biological activity. © Springer Science+Business Media, LLC 2012.
Keywords: Amino acids; animal cell; article; Bacillus subtilis; Bacillus subtilis natto; Bioactivity; Biocompatibility; Biocompatible Materials; biodegradability; Biodegradable polymers; Biodegradation; Biologically active substances; biomaterial; Biomedical applications; biomedicine; biosynthesis; chitosan; circular dichroism; complex formation; controlled study; dispersion; Electrophoresis, Polyacrylamide Gel; feasibility study; Functional polymers; gamma polyglutamic acid; Glutamic acid; High purity; Low molecular weight; Medical applications; molecular interaction; molecular weight; Nanocomplexes; nanoparticle; nonhuman; pH; Physiological pH; polyglutamic acid; Potential applications; priority journal; purification; Spectroscopy, Fourier Transform Infrared; static electricity; Stereoisomerism; unclassified drug

E-cadherin dysfunction in gastric cancer - Cellular consequences, clinical applications and open questions - Carneiro, P.; Fernandes, M.S.; Figueiredo, J.; Caldeira, J.; Carvalho, J.; Pinheiro, H.; Leite, M.; Melo, S.; Oliveira, P.; Simões-Correia, J.; Oliveira, M.J.; Carneiro, F.; et al. (FEBS LettersFEBS Lett., 2012)
E-cadherin plays a major role in cell-cell adhesion and inactivating germline mutations in its encoding gene predispose to hereditary diffuse gastric cancer. Evidence indicates that aside from its recognized role in early tumourigenesis, E-cadherin is also pivotal for tumour progression, including invasion and metastization. Herein, we discuss E-cadherin alterations found in a cancer context, associated cellular effects and signalling pathways, and we raise new key questions that will impact in the management of GC patients and families. © 2012 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: Adhesion; Cadherins; cancer growth; cancer invasion; cancer patient; cancer susceptibility; cell adhesion; complex formation; conference paper; E-cadherin; embryo development; endocytosis; epigenetics; epithelial mesenchymal transition; Gastric cancer; gene mutation; gene silencing; genetic susceptibility; Germ-Line Mutation; HDGC; Helicobacter infection; Helicobacter Infections; Helicobacter pylori; histone deacetylase inhibitor; human; Humans; Invasion; metastasis; molecular pathology; nonhuman; priority journal; protein analysis; protein depletion; protein expression; protein function; protein structure; regulatory mechanism; signal transduction; Signalling; stomach cancer; stomach carcinogenesis; Stomach Neoplasms; Tumour; uvomorulin

The effect of adsorbed fibronectin and osteopontin on macrophage adhesion and morphology on hydrophilic and hydrophobic model surfaces - Maciel, J.; Oliveira, M.I.; Gonalves, R.M.; Barbosa, M.A. (Acta BiomaterialiaActa Biomater., 2012)
Macrophages play a crucial role in the host response to biomaterials. Here we investigated the effect of adsorbed fibronectin (FN) and osteopontin (OPN), two important proteins for tissue repair, on macrophage adhesion and morphology. Since cell-biomaterial interactions are modulated via proteins adsorbed onto biomaterial surfaces, FN and OPN were adsorbed on model self-assembled monolayers (SAMs) of alkanethiols on gold with different functional terminal groups (CH 3, OH and tetra(ethylene-glycol)). The initial interaction of inflammatory cells with a biomaterial is crucial for the ensuing phases of an inflammatory reaction. For this reason short-term cultures of primary human macrophages were performed. To account for the competitive adsorption of other proteins serum was added to the culture medium and the effect compared with serum-free medium cultures. In the presence of serum hydrophilic surfaces increased macrophage adhesion. In particular, FN induced a higher cell density, while OPN tended to decrease it. In serum-free medium cell adhesion was greater on hydrophobic surfaces, except for OPN-coated SAMs. Importantly, FN no longer enhanced macrophage adhesion, while OPN maintained its inhibitory effect. Cell polarization studies indicated that macrophage morphology variations induced by surface chemistry are overcome by pre-adsorbed OPN. Taken together our results show that in the presence of serum macrophage adhesion is promoted by FN hydrophilic surfaces, but impaired on OPN-coated surfaces. The effects of inhibited macrophage adhesion on macrophage fusion, and its relevance to the initial stages of the inflammatory response to biomaterials are discussed. © 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: alkane; article; biomaterial; Biomaterials; cell adhesion; cell density; cell interaction; cell structure; controlled study; culture medium; cytoskeleton; Fibronectin; functional group; gold; human; human cell; hydrophilicity; hydrophobicity; inflammatory cell; macrophage; Macrophages; nanomaterial; Osteopontin; priority journal; self assembled monolayer; Self-assembled monolayers; Tetra; thiol; tissue repair

The effect of octadecyl chain immobilization on the hemocompatibility of poly (2-hydroxyethyl methacrylate) - Fischer, M.; Baptista, C.P.; Gonçalves, I.C.; Ratner, B.D.; Sperling, C.; Werner, C.; Martins, C.L.; Barbosa, M.A. (BiomaterialsBiomaterials, 2012)
Albumin-scavenging surfaces decorated with n-alkyl chains represent an established strategy for blood-contacting applications. To evaluate this concept, a set of poly (2-hydroxyethyl methacrylate) (pHEMA) films modified with different amounts of octadecyl isocyanate (C18) was investigated in an in vitro hemocompatibility assay using freshly drawn human whole blood. In addition, the hydrogel materials were thoroughly characterized with respect to changes in wettability and elasticity, which accompanied the gradual chemical modification of pHEMA. An increase of the surface C18 content induced enhanced hydrophobicity and stiffness. Immobilization of C18 chains was found to substantially reduce the coagulation activation and the complement activation by the pHEMA films. Platelet adhesion and degranulation (PF4 release) were similar on the modified and the unmodified pHEMA. Platelet adhesion to pHEMA hydrogels was lower than the polytetrafluoroethylene reference. We conclude that the immobilization of octadecyl chains improved the hemocompatibility of pHEMA materials under conditions that might be encountered in low shear blood flow. © 2012 Elsevier Ltd.
Keywords: Adhesion; Albumin; article; Biological materials; Biomaterials; Blood; Blood flow; Chemical modification; Coagulation; controlled study; Degranulation; Elasticity; Haemocompatibility; Hemocompatibility; human; hydrogel; in vitro study; In-vitro; isocyanate; Octadecyl; octadecyl isocyanate; PHEMA; Platelet adhesion; Platelets; Poly(2-hydroxyethyl methacrylate); PolyHEMA; polymacon; priority journal; Protein adsorption; thrombocyte adhesion; unclassified drug; wettability; Whole blood

Epithelial E- and P-cadherins: Role and clinical significance in cancer - Paredes, J.; Figueiredo, J.; Albergaria, A.; Oliveira, P.; Carvalho, J.; Ribeiro, A.S.; Caldeira, J.; Costa, A.M.; Simões-Correia, J.; Oliveira, M.J.; Pinheiro, H.; Pinho, S.S.; et al. (Biochimica et Biophysica Acta - Reviews on CancerBiochim. Biophys. Acta Rev. Cancer, 2012)
E-cadherin and P-cadherin are major contributors to cell-cell adhesion in epithelial tissues, playing pivotal roles in important morphogenetic and differentiation processes during development, and in maintaining integrity and homeostasis in adult tissues. It is now generally accepted that alterations in these two molecules are observed during tumour progression of most carcinomas. Genetic or epigenetic alterations in E- and P-cadherin-encoding genes (CDH1 and CDH3, respectively), or alterations in their proteins expression, often result in tissue disorder, cellular de-differentiation, increased invasiveness of tumour cells and ultimately in metastasis. In this review, we will discuss the major properties of E- and P-cadherin molecules, its regulation in normal tissue, and their alterations and role in cancer, with a specific focus on gastric and breast cancer models. © 2012 Elsevier B.V.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: BBACEdoi: 10.1016/j.bbcan.2012.05.002Language of Original Document: EnglishCorrespondence Address: Seruca, R.; IPATIMUP, Institute of Molecular Pathology and Immunology, University of Porto, Rua Dr. Roberto Frias s/n, 4200-465 Porto, Portugal; email: rseruca@ipatimup.ptChemicals/CAS: uvomorulin, 112956-45-3Tradenames: pf 03732010References: Cavallaro, U., Christofori, G., Cell adhesion and signalling by cadherins and Ig-CAMs in cancer (2004) Nat. Rev. Cancer, 4, pp. 118-132;Gerrow, K., El-Husseini, A., Cell adhesion molecules at the synapse (2006) Front. Biosci., 11, pp. 2400-2419; Nollet, F., Kools, P., van Roy, F., Phylogenetic analysis of the cadherin superfamily allows identification of six major subfamilies besides several solitary members (2000) J. Mol. Biol., 299, pp. 551-572; Takeichi, M., Cadherins in cancer: implications for invasion and metastasis (1993) Curr. Opin. Cell Biol., 5, pp. 806-811; Pignatelli, M., Bodmer, W.F., Genetics and biochemistry of collagen binding-triggered glandular differentiation in a human colon carcinoma cell line (1988) Proc. Natl. Acad. Sci. U. S. A., 85, pp. 5561-5565; Takeichi, M., Morphogenetic roles of classic cadherins (1995) Curr. Opin. Cell Biol., 7, pp. 619-627; Shapiro, L., Fannon, A.M., Kwong, P.D., Thompson, A., Lehmann, M.S., Grubel, G., Legrand, J.F., Hendrickson, W.A., Structural basis of cell-cell adhesion by cadherins (1995) Nature, 374, pp. 327-337; Ozawa, M., Ringwald, M., Kemler, R., Uvomorulin-catenin complex formation is regulated by a specific domain in the cytoplasmic region of the cell adhesion molecule (1990) Proc. Natl. Acad. Sci. U. S. A., 87, pp. 4246-4250; Blaschuk, O.W., Sullivan, R., David, S., Pouliot, Y., Identification of a cadherin cell adhesion recognition sequence (1990) Dev. Biol., 139, pp. 227-229; Ozawa, M., Baribault, H., Kemler, R., The cytoplasmic domain of the cell adhesion molecule uvomorulin associates with three independent proteins structurally related in different species (1989) EMBO J., 8, pp. 1711-1717; Gumbiner, B.M., McCrea, P.D., Catenins as mediators of the cytoplasmic functions of cadherins (1993) J. Cell Sci. Suppl., 17, pp. 155-158; Yap, A.S., Niessen, C.M., Gumbiner, B.M., The juxtamembrane region of the cadherin cytoplasmic tail supports lateral clustering, adhesive strengthening, and interaction with p120ctn (1998) J. Cell Biol., 141, pp. 779-789; Van Aken, E., De Wever, O., Correia da Rocha, A.S., Mareel, M., Defective E-cadherin/catenin complexes in human cancer (2001) Virchows Arch., 439, pp. 725-751; Mareel, M., Oliveira, M.J., Madani, I., Cancer invasion and metastasis: interacting ecosystems (2009) Virchows Arch., 454, pp. 599-622; Makrilia, N., Kollias, A., Manolopoulos, L., Syrigos, K., Cell adhesion molecules: role and clinical significance in cancer (2009) Cancer Invest., 27, pp. 1023-1037; Bussemakers, M.J., van Bokhoven, A., Voller, M., Smit, F.P., Schalken, J.A., The genes for the calcium-dependent cell adhesion molecules P- and E-cadherin are tandemly arranged in the human genome (1994) Biochem. Biophys. Res. Commun., 203, pp. 1291-1294; Berx, G., Staes, K., van Hengel, J., Molemans, F., Bussemakers, M.J., van Bokhoven, A., van Roy, F., Cloning and characterization of the human invasion suppressor gene E-cadherin (CDH1) (1995) Genomics, 26, pp. 281-289; Jarrard, D.F., Paul, R., van Bokhoven, A., Nguyen, S.H., Bova, G.S., Wheelock, M.J., Johnson, K.R., Isaacs, W.B., P-cadherin is a basal cell-specific epithelial marker that is not expressed in prostate cancer (1997) Clin. Cancer Res., 3, pp. 2121-2128; Hubbard, T.J., Aken, B.L., Ayling, S., Ballester, B., Beal, K., Bragin, E., Brent, S., Flicek, P., Ensembl 2009 (2009) Nucleic Acids Res., 37, pp. D690-D697; Faraldo, M.L., Cano, A., The 5' flanking sequences of the mouse P-cadherin gene. Homologies to 5' sequences of the E-cadherin gene and identification of a first 215 base-pair intron (1993) J. Mol. Biol., 231, pp. 935-941; van Roy, F., Berx, G., The cell-cell adhesion molecule E-cadherin (2008) Cell. Mol. Life Sci., 65, pp. 3756-3788; Stemmler, M.P., Cadherins in development and cancer (2008) Mol. Biosyst., 4, pp. 835-850; Paredes, J., Albergaria, A., Oliveira, J.T., Jeronimo, C., Milanezi, F., Schmitt, F.C., P-cadherin overexpression is an indicator of clinical outcome in invasive breast carcinomas and is associated with CDH3 promoter hypomethylation (2005) Clin. Cancer Res., 11, pp. 5869-5877; Sakharkar, K.R., Chow, V.T., PPD-proteome profile database (2004) In Silico Biol., 4, pp. 219-223; Thomas, D.J., Rosenbloom, K.R., Clawson, H., Hinrichs, A.S., Trumbower, H., Raney, B.J., Karolchik, D., Kent, W.J., The ENCODE Project at UC Santa Cruz (2007) Nucleic Acids Res., 35, pp. D663-D667; Oliveira, P., Sanges, R., Huntsman, D., Stupka, E., Oliveira, C., Characterization of the intronic portion of cadherin superfamily members, common cancer orchestrators (2012) Eur. J. Hum. Genet.; Hosono, S., Gross, I., English, M.A., Hajra, K.M., Fearon, E.R., Licht, J.D., E-cadherin is a WT1 target gene (2000) J. Biol. Chem., 275, pp. 10943-10953; Liu, Y.N., Lee, W.W., Wang, C.Y., Chao, T.H., Chen, Y., Chen, J.H., Regulatory mechanisms controlling human E-cadherin gene expression (2005) Oncogene, 24, pp. 8277-8290; Behrens, J., Lowrick, O., Klein-Hitpass, L., Birchmeier, W., The E-cadherin promoter: functional analysis of a G.C-rich region and an epithelial cell-specific palindromic regulatory element (1991) Proc. Natl. Acad. Sci. U. S. A., 88, pp. 11495-11499; Cano, A., Perez-Moreno, M.A., Rodrigo, I., Locascio, A., Blanco, M.J., del Barrio, M.G., Portillo, F., Nieto, M.A., The transcription factor snail controls epithelial-mesenchymal transitions by repressing E-cadherin expression (2000) Nat. Cell Biol., 2, pp. 76-83; Hajra, K.M., Chen, D.Y., Fearon, E.R., The SLUG zinc-finger protein represses E-cadherin in breast cancer (2002) Cancer Res., 62, pp. 1613-1618; Perez-Moreno, M.A., Locascio, A., Rodrigo, I., Dhondt, G., Portillo, F., Nieto, M.A., Cano, A., A new role for E12/E47 in the repression of E-cadherin expression and epithelial-mesenchymal transitions (2001) J. Biol. Chem., 276, pp. 27424-27431; Comijn, J., Berx, G., Vermassen, P., Verschueren, K., van Grunsven, L., Bruyneel, E., Mareel, M., van Roy, F., The two-handed E box binding zinc finger protein SIP1 downregulates E-cadherin and induces invasion (2001) Mol. Cell, 7, pp. 1267-1278; Eger, A., Aigner, K., Sonderegger, S., Dampier, B., Oehler, S., Schreiber, M., Berx, G., Foisner, R., DeltaEF1 is a transcriptional repressor of E-cadherin and regulates epithelial plasticity in breast cancer cells (2005) Oncogene, 24, pp. 2375-2385; Peinado, H., Olmeda, D., Cano, A., Snail, Zeb and bHLH factors in tumour progression: an alliance against the epithelial phenotype? (2007) Nat. Rev. Cancer, 7, pp. 415-428; Shi, Y., Sawada, J., Sui, G., Affar el, B., Whetstine, J.R., Lan, F., Ogawa, H., Nakatani, Y., Coordinated histone modifications mediated by a CtBP co-repressor complex (2003) Nature, 422, pp. 735-738; Jamora, C., DasGupta, R., Kocieniewski, P., Fuchs, E., Links between signal transduction, transcription and adhesion in epithelial bud development (2003) Nature, 422, pp. 317-322; Vandewalle, C., Comijn, J., De Craene, B., Vermassen, P., Bruyneel, E., Andersen, H., Tulchinsky, E., Berx, G., SIP1/ZEB2 induces EMT by repressing genes of different epithelial cell-cell junctions (2005) Nucleic Acids Res., 33, pp. 6566-6578; Aigner, K., Dampier, B., Descovich, L., Mikula, M., Sultan, A., Schreiber, M., Mikulits, W., Eger, A., The transcription factor ZEB1 (deltaEF1) promotes tumour cell dedifferentiation by repressing master regulators of epithelial polarity (2007) Oncogene, 26, pp. 6979-6988; Spaderna, S., Schmalhofer, O., Wahlbuhl, M., Dimmler, A., Bauer, K., Sultan, A., Hlubek, F., Brabletz, T., The transcriptional repressor ZEB1 promotes metastasis and loss of cell polarity in cancer (2008) Cancer Res., 68, pp. 537-544; Graff, J.R., Herman, J.G., Lapidus, R.G., Chopra, H., Xu, R., Jarrard, D.F., Isaacs, W.B., Baylin, S.B., E-cadherin expression is silenced by DNA hypermethylation in human breast and prostate carcinomas (1995) Cancer Res., 55, pp. 5195-5199; Shimomura, Y., Wajid, M., Shapiro, L., Christiano, A.M., P-cadherin is a p63 target gene with a crucial role in the developing human limb bud and hair follicle (2008) Development, 135, pp. 743-753; Carroll, D.K., Carroll, J.S., Leong, C.O., Cheng, F., Brown, M., Mills, A.A., Brugge, J.S., Ellisen, L.W., P63 regulates an adhesion programme and cell survival in epithelial cells (2006) Nat. Cell Biol., 8, pp. 551-561; Faraldo, M.M., Teuliere, J., Deugnier, M.A., Birchmeier, W., Huelsken, J., Thiery, J.P., Cano, A., Glukhova, M.A., Beta-catenin regulates P-cadherin expression in mammary basal epithelial cells (2007) FEBS Lett., 581, pp. 831-836; Le, T.L., Yap, A.S., Stow, J.L., Recycling of E-cadherin: a potential mechanism for regulating cadherin dynamics (1999) J. Cell Biol., 146, pp. 219-232; Bryant, D.M., Stow, J.L., The ins and outs of E-cadherin trafficking (2004) Trends Cell Biol., 14, pp. 427-434; Hinck, L., Nathke, I.S., Papkoff, J., Nelson, W.J., Dynamics of cadherin/catenin complex formation: novel protein interactions and pathways of complex assembly (1994) J. Cell Biol., 125, pp. 1327-1340; Chen, Y.T., Stewart, D.B., Nelson, W.J., Coupling assembly of the E-cadherin/beta-catenin complex to efficient endoplasmic reticulum exit and basal-lateral membrane targeting of E-cadherin in polarized MDCK cells (1999) J. Cell Biol., 144, pp. 687-699; Lock, J.G., Stow, J.L., Rab11 in recycling endosomes regulates the sorting and basolateral transport of E-cadherin (2005) Mol. Biol. Cell, 16, pp. 1744-1755; Bryant, D.M., Kerr, M.C., Hammond, L.A., Joseph, S.R., Mostov, K.E., Teasdale, R.D., Stow, J.L., EGF induces macropinocytosis and SNX1-modulated recycling of E-cadherin (2007) J. Cell Sci., 120, pp. 1818-1828; Ling, K., Bairstow, S.F., Carbonara, C., Turbin, D.A., Huntsman, D.G., Anderson, R.A., Type I gamma phosphatidylinositol phosphate kinase modulates adherens junction and E-cadherin trafficking via a direct interaction with mu 1B adaptin (2007) J. Cell Biol., 176, pp. 343-353; Mosesson, Y., Mills, G.B., Yarden, Y., Derailed endocytosis: an emerging feature of cancer (2008) Nat. Rev. Cancer, 8, pp. 835-850; Ireton, R.C., Davis, M.A., van Hengel, J., Mariner, D.J., Barnes, K., Thoreson, M.A., Anastasiadis, P.Z., Reynolds, A.B., A novel role for p120 catenin in E-cadherin function (2002) J. Cell Biol., 159, pp. 465-476; Davis, M.A., Ireton, R.C., Reynolds, A.B., A core function for p120-catenin in cadherin turnover (2003) J. Cell Biol., 163, pp. 525-534; Xiao, K., Garner, J., Buckley, K.M., Vincent, P.A., Chiasson, C.M., Dejana, E., Faundez, V., Kowalczyk, A.P., P120-Catenin regulates clathrin-dependent endocytosis of VE-cadherin (2005) Mol. Biol. Cell, 16, pp. 5141-5151; Taniuchi, K., Nakagawa, H., Hosokawa, M., Nakamura, T., Eguchi, H., Ohigashi, H., Ishikawa, O., Nakamura, Y., Overexpressed P-cadherin/CDH3 promotes motility of pancreatic cancer cells by interacting with p120ctn and activating rho-family GTPases (2005) Cancer Res., 65, pp. 3092-3099; Paredes, J., Stove, C., Stove, V., Milanezi, F., Van Marck, V., Derycke, L., Mareel, M., Schmitt, F., P-cadherin is up-regulated by the antiestrogen ICI 182,780 and promotes invasion of human breast cancer cells (2004) Cancer Res., 64, pp. 8309-8317; Palacios, F., Price, L., Schweitzer, J., Collard, J.G., D'Souza-Schorey, C., An essential role for ARF6-regulated membrane traffic in adherens junction turnover and epithelial cell migration (2001) EMBO J., 20, pp. 4973-4986; Figueiredo, J., Simoes-Correia, J., Soderberg, O., Suriano, G., Seruca, R., ADP-ribosylation factor 6 mediates E-cadherin recovery by chemical chaperones (2011) PLoS One, 6, pp. e23188; Palacios, F., Schweitzer, J.K., Boshans, R.L., D'Souza-Schorey, C., ARF6-GTP recruits Nm23-H1 to facilitate dynamin-mediated endocytosis during adherens junctions disassembly (2002) Nat. Cell Biol., 4, pp. 929-936; Otsuki, Y., Tanaka, M., Yoshii, S., Kawazoe, N., Nakaya, K., Sugimura, H., Tumor metastasis suppressor nm23H1 regulates Rac1 GTPase by interaction with Tiam1 (2001) Proc. Natl. Acad. Sci. U. S. A., 98, pp. 4385-4390; Morishige, M., Hashimoto, S., Ogawa, E., Toda, Y., Kotani, H., Hirose, M., Wei, S., Sabe, H., GEP100 links epidermal growth factor receptor signalling to Arf6 activation to induce breast cancer invasion (2008) Nat. Cell Biol., 10, pp. 85-92; Daniel, J.M., Reynolds, A.B., Tyrosine phosphorylation and cadherin/catenin function (1997) Bioessays, 19, pp. 883-891; Palacios, F., Tushir, J.S., Fujita, Y., D'Souza-Schorey, C., Lysosomal targeting of E-cadherin: a unique mechanism for the down-regulation of cell-cell adhesion during epithelial to mesenchymal transitions (2005) Mol. Cell. Biol., 25, pp. 389-402; Fujita, Y., Krause, G., Scheffner, M., Zechner, D., Leddy, H.E., Behrens, J., Sommer, T., Birchmeier, W., Hakai, a c-Cbl-like protein, ubiquitinates and induces endocytosis of the E-cadherin complex (2002) Nat. Cell Biol., 4, pp. 222-231; Pinho, S.S., Seruca, R., Gartner, F., Yamaguchi, Y., Gu, J., Taniguchi, N., Reis, C.A., Modulation of E-cadherin function and dysfunction by N-glycosylation (2011) Cell. Mol. Life Sci., 68, pp. 1011-1020; Zhu, W., Leber, B., Andrews, D.W., Cytoplasmic O-glycosylation prevents cell surface transport of E-cadherin during apoptosis (2001) EMBO J., 20, pp. 5999-6007; Zhou, F., Su, J., Fu, L., Yang, Y., Zhang, L., Wang, L., Zhao, H., Zha, X., Unglycosylation at Asn-633 made extracellular domain of E-cadherin folded incorrectly and arrested in endoplasmic reticulum, then sequentially degraded by ERAD (2008) Glycoconj. J., 25, pp. 727-740; Liwosz, A., Lei, T., Kukuruzinska, M.A., N-glycosylation affects the molecular organization and stability of E-cadherin junctions (2006) J. Biol. Chem., 281, pp. 23138-23149; Pinho, S.S., Reis, C.A., Paredes, J., Magalhaes, A.M., Ferreira, A.C., Figueiredo, J., Xiaogang, W., Seruca, R., The role of N-acetylglucosaminyltransferase III and V in the post-transcriptional modifications of E-cadherin (2009) Hum. Mol. Genet., 18, pp. 2599-2608; Pinho, S.S., Oliveira, P., Cabral, J., Carvalho, S., Huntsman, D., Gartner, F., Seruca, R., Oliveira, C., Loss and recovery of Mgat3 and GnT-III mediated E-cadherin N-glycosylation is a mechanism involved in epithelial-mesenchymal-epithelial transitions (2012) PLoS One, 7, pp. e33191; Osumi, D., Takahashi, M., Miyoshi, E., Yokoe, S., Lee, S.H., Noda, K., Nakamori, S., Taniguchi, N., Core fucosylation of E-cadherin enhances cell-cell adhesion in human colon carcinoma WiDr cells (2009) Cancer Sci., 100, pp. 888-895; Takeichi, M., Functional correlation between cell adhesive properties and some cell surface proteins (1977) J. Cell Biol., 75, pp. 464-474; Hyafil, F., Morello, D., Babinet, C., Jacob, F., A cell surface glycoprotein involved in the compaction of embryonal carcinoma cells and cleavage stage embryos (1980) Cell, 21, pp. 927-934; Ogou, S., Okada, T.S., Takeichi, M., Cleavage stage mouse embryos share a common cell adhesion system with teratocarcinoma cells (1982) Dev. Biol., 92, pp. 521-528; Takeichi, M., The cadherins: cell-cell adhesion molecules controlling animal morphogenesis (1988) Development, 102, pp. 639-655; Fleming, T.P., Javed, Q., Hay, M., Epithelial differentiation and intercellular junction formation in the mouse early embryo (1992) Dev. Suppl., pp. 105-112; Aplin, J.D., Jones, C.J., Harris, L.K., Adhesion molecules in human trophoblast-a review. I. Villous trophoblast (2009) Placenta, 30, pp. 293-298; Nose, A., Takeichi, M., A novel cadherin cell adhesion molecule: its expression patterns associated with implantation and organogenesis of mouse embryos (1986) J. Cell Biol., 103, pp. 2649-2658; Larue, L., Ohsugi, M., Hirchenhain, J., Kemler, R., E-cadherin null mutant embryos fail to form a trophectoderm epithelium (1994) Proc. Natl. Acad. Sci. U. S. A., 91, pp. 8263-8267; Riethmacher, D., Brinkmann, V., Birchmeier, C., A targeted mutation in the mouse E-cadherin gene results in defective preimplantation development (1995) Proc. Natl. Acad. Sci. U. S. A., 92, pp. 855-859; Radice, G.L., Ferreira-Cornwell, M.C., Robinson, S.D., Rayburn, H., Chodosh, L.A., Takeichi, M., Hynes, R.O., Precocious mammary gland development in P-cadherin-deficient mice (1997) J. Cell Biol., 139, pp. 1025-1032; Frebourg, T., Oliveira, C., Hochain, P., Karam, R., Manouvrier, S., Graziadio, C., Vekemans, M., Seruca, R., Cleft lip/palate and CDH1/E-cadherin mutations in families with hereditary diffuse gastric cancer (2006) J. Med. Genet., 43, pp. 138-142; Kjaer, K.W., Hansen, L., Schwabe, G.C., Marques-de-Faria, A.P., Eiberg, H., Mundlos, S., Tommerup, N., Rosenberg, T., Distinct CDH3 mutations cause ectodermal dysplasia, ectrodactyly, macular dystrophy (EEM syndrome) (2005) J. Med. Genet., 42, pp. 292-298; Sprecher, E., Bergman, R., Richard, G., Lurie, R., Shalev, S., Petronius, D., Shalata, A., Szargel, R., Hypotrichosis with juvenile macular dystrophy is caused by a mutation in CDH3, encoding P-cadherin (2001) Nat. Genet., 29, pp. 134-136; Nelson, W.J., Epithelial cell polarity from the outside looking in (2003) News Physiol. Sci., 18, pp. 143-146; Hirai, Y., Nose, A., Kobayashi, S., Takeichi, M., Expression and role of E- and P-cadherin adhesion molecules in embryonic histogenesis. II. Skin morphogenesis (1989) Development, 105, pp. 271-277; Berx, G., Van Roy, F., The E-cadherin/catenin complex: an important gatekeeper in breast cancer tumorigenesis and malignant progression (2001) Breast Cancer Res., 3, pp. 289-293; Shimoyama, Y., Hirohashi, S., Expression of E- and P-cadherin in gastric carcinomas (1991) Cancer Res., 51, pp. 2185-2192; Hines, M.D., Jin, H.C., Wheelock, M.J., Jensen, P.J., Inhibition of cadherin function differentially affects markers of terminal differentiation in cultured human keratinocytes (1999) J. Cell Sci., 112 (PART 24), pp. 4569-4579; Ribeiro, A.S., Albergaria, A., Sousa, B., Correia, A.L., Bracke, M., Seruca, R., Schmitt, F.C., Paredes, J., Extracellular cleavage and shedding of P-cadherin: a mechanism underlying the invasive behaviour of breast cancer cells (2010) Oncogene, 29, pp. 392-402; Moll, R., Mitze, M., Frixen, U.H., Birchmeier, W., Differential loss of E-cadherin expression in infiltrating ductal and lobular breast carcinomas (1993) Am. J. Pathol., 143, pp. 1731-1742; Gamallo, C., Palacios, J., Suarez, A., Pizarro, A., Navarro, P., Quintanilla, M., Cano, A., Correlation of E-cadherin expression with differentiation grade and histological type in breast carcinoma (1993) Am. J. Pathol., 142, pp. 987-993; Reis-Filho, J.S., Cancela Paredes, J., Milanezi, F., Schmitt, F.C., Clinicopathologic implications of E-cadherin reactivity in patients with lobular carcinoma in situ of the breast (2002) Cancer, 94, pp. 2114-2115; author reply 2115-2116Weigelt, B., Geyer, F.C., Natrajan, R., Lopez-Garcia, M.A., Ahmad, A.S., Savage, K., Kreike, B., Reis-Filho, J.S., The molecular underpinning of lobular histological growth pattern: a genome-wide transcriptomic analysis of invasive lobular carcinomas and grade- and molecular subtype-matched invasive ductal carcinomas of no special type (2010) J. Pathol., 220, pp. 45-57; Simpson, P.T., Reis-Filho, J.S., Lambros, M.B., Jones, C., Steele, D., Mackay, A., Iravani, M., Lakhani, S.R., Molecular profiling pleomorphic lobular carcinomas of the breast: evidence for a common molecular genetic pathway with classic lobular carcinomas (2008) J. Pathol., 215, pp. 231-244; Mahler-Araujo, B., Savage, K., Parry, S., Reis-Filho, J.S., Reduction of E-cadherin expression is associated with non-lobular breast carcinomas of basal-like and triple negative phenotype (2008) J. Clin. Pathol., 61, pp. 615-620; Lopes, N., Carvalho, J., Duraes, C., Sousa, B., Gomes, M., Costa, J.L., Oliveira, C., Schmitt, F., 1Alpha,25-dihydroxyvitamin D3 induces de novo E-cadherin expression in triple-negative breast cancer cells by CDH1-promoter demethylation (2012) Anticancer. Res., 32, pp. 249-257; Berx, G., Cleton-Jansen, A.M., Strumane, K., de Leeuw, W.J., Nollet, F., van Roy, F., Cornelisse, C., E-cadherin is inactivated in a majority of invasive human lobular breast cancers by truncation mutations throughout its extracellular domain (1996) Oncogene, 13, pp. 1919-1925; Keller, G., Vogelsang, H., Becker, I., Hutter, J., Ott, K., Candidus, S., Grundei, T., Hofler, H., Diffuse type gastric and lobular breast carcinoma in a familial gastric cancer patient with an E-cadherin germline mutation (1999) Am. J. Pathol., 155, pp. 337-342; Schrader, K.A., Masciari, S., Boyd, N., Wiyrick, S., Kaurah, P., Senz, J., Burke, W., Huntsman, D.G., Hereditary diffuse gastric cancer: association with lobular breast cancer (2008) Fam. Cancer, 7, pp. 73-82; Becker, K.F., Atkinson, M.J., Reich, U., Becker, I., Nekarda, H., Siewert, J.R., Hofler, H., E-cadherin gene mutations provide clues to diffuse type gastric carcinomas (1994) Cancer Res., 54, pp. 3845-3852; Becker, K.F., Kremmer, E., Eulitz, M., Becker, I., Handschuh, G., Schuhmacher, C., Muller, W., Hofler, H., Analysis of E-cadherin in diffuse-type gastric cancer using a mutation-specific monoclonal antibody (1999) Am. J. Pathol., 155, pp. 1803-1809; Machado, J.C., Carneiro, F., Beck, S., Rossi, S., Lopes, J., Taveira-Gomes, A., Cardoso-Oliveira, M., E-cadherin expression is correlated with the isolated cell/diffuse histotype and with features of biological aggressiveness of gastric carcinoma (1998) Int. J. Surg. Pathol., 6, pp. 135-144; Carneiro, F., Machado, J.C., Seruca, R., Sobrinho-Simoes, M., E-cadherin changes in gastric carcimona (1999) Histopathology, 35, pp. 477-478; Carvalho, J., van Grieken, N.C., Pereira, P.M., Sousa, S., Tijssen, M., Buffart, T.E., Diosdado, B., Oliveira, C., Lack of microRNA-101 causes E-cadherin functional deregulation through EZH2 upregulation in intestinal gastric cancer (2012) J. Pathol.; Machado, J.C., Oliveira, C., Carvalho, R., Soares, P., Berx, G., Caldas, C., Seruca, R., Sobrinho-Simoes, M., E-cadherin gene (CDH1) promoter methylation as the second hit in sporadic diffuse gastric carcinoma (2001) Oncogene, 20, pp. 1525-1528; Guilford, P., Hopkins, J., Harraway, J., McLeod, M., McLeod, N., Harawira, P., Taite, H., Reeve, A.E., E-cadherin germline mutations in familial gastric cancer (1998) Nature, 392, pp. 402-405; Oliveira, C., Senz, J., Kaurah, P., Pinheiro, H., Sanges, R., Haegert, A., Corso, G., Huntsman, D., Germline CDH1 deletions in hereditary diffuse gastric cancer families (2009) Hum. Mol. Genet., 18, pp. 1545-1555; Pinheiro, H., Bordeira-Carrico, R., Seixas, S., Carvalho, J., Senz, J., Oliveira, P., Inacio, P., Oliveira, C., Allele-specific CDH1 downregulation and hereditary diffuse gastric cancer (2010) Hum. Mol. Genet., 19, pp. 943-952; Guilford, P., Humar, B., Blair, V., Hereditary diffuse gastric cancer: translation of CDH1 germline mutations into clinical practice (2010) Gastric Cancer, 13, pp. 1-10; Suriano, G., Seixas, S., Rocha, J., Seruca, R., A model to infer the pathogenic significance of CDH1 germline missense variants (2006) J. Mol. Med., 84, pp. 1023-1031; Suriano, G., Oliveira, C., Ferreira, P., Machado, J.C., Bordin, M.C., De Wever, O., Bruyneel, E.A., Seruca, R., Identification of CDH1 germline missense mutations associated with functional inactivation of the E-cadherin protein in young gastric cancer probands (2003) Hum. Mol. Genet., 12, pp. 575-582; Suriano, G., Oliveira, M.J., Huntsman, D., Mateus, A.R., Ferreira, P., Casares, F., Oliveira, C., Seruca, R., E-cadherin germline missense mutations and cell phenotype: evidence for the independence of cell invasion on the motile capabilities of the cells (2003) Hum. Mol. Genet., 12, pp. 3007-3016; Brooks-Wilson, A.R., Kaurah, P., Suriano, G., Leach, S., Senz, J., Grehan, N., Butterfield, Y.S., Huntsman, D., Germline E-cadherin mutations in hereditary diffuse gastric cancer: assessment of 42 new families and review of genetic screening criteria (2004) J. Med. Genet., 41, pp. 508-517; Kaurah, P., MacMillan, A., Boyd, N., Senz, J., De Luca, A., Chun, N., Suriano, G., Huntsman, D., Founder and recurrent CDH1 mutations in families with hereditary diffuse gastric cancer (2007) JAMA, 297, pp. 2360-2372; Corso, G., Roviello, F., Paredes, J., Pedrazzani, C., Novais, M., Correia, J., Marrelli, D., Suriano, G., Characterization of the P373L E-cadherin germline missense mutation and implication for clinical management (2007) Eur. J. Surg. Oncol., 33, pp. 1061-1067; More, H., Humar, B., Weber, W., Ward, R., Christian, A., Lintott, C., Graziano, F., Guilford, P., Identification of seven novel germline mutations in the human E-cadherin (CDH1) gene (2007) Hum. Mutat., 28, p. 203; Oliveira, C., de Bruin, J., Nabais, S., Ligtenberg, M., Moutinho, C., Nagengast, F.M., Seruca, R., Carneiro, F., Intragenic deletion of CDH1 as the inactivating mechanism of the wild-type allele in an HDGC tumour (2004) Oncogene, 23, pp. 2236-2240; Barber, M., Murrell, A., Ito, Y., Maia, A.T., Hyland, S., Oliveira, C., Save, V., Fitzgerald, R.C., Mechanisms and sequelae of E-cadherin silencing in hereditary diffuse gastric cancer (2008) J. Pathol., 216, pp. 295-306; Oliveira, C., Sousa, S., Pinheiro, H., Karam, R., Bordeira-Carrico, R., Senz, J., Kaurah, P., Seruca, R., Quantification of epigenetic and genetic 2nd hits in CDH1 during hereditary diffuse gastric cancer syndrome progression (2009) Gastroenterology, 136, pp. 2137-2148; Grady, W.M., Willis, J., Guilford, P.J., Dunbier, A.K., Toro, T.T., Lynch, H., Wiesner, G., Markowitz, S., Methylation of the CDH1 promoter as the second genetic hit in hereditary diffuse gastric cancer (2000) Nat. Genet., 26, pp. 16-17; Peinado, H., Ballestar, E., Esteller, M., Cano, A., Snail mediates E-cadherin repression by the recruitment of the Sin3A/histone deacetylase 1 (HDAC1)/HDAC2 complex (2004) Mol. Cell. Biol., 24, pp. 306-319; Fujii, S., Ochiai, A., Enhancer of zeste homolog 2 downregulates E-cadherin by mediating histone H3 methylation in gastric cancer cells (2008) Cancer Sci., 99, pp. 738-746; Cao, Q., Yu, J., Dhanasekaran, S.M., Kim, J.H., Mani, R.S., Tomlins, S.A., Mehra, R., Chinnaiyan, A.M., Repression of E-cadherin by the polycomb group protein EZH2 in cancer (2008) Oncogene, 27, pp. 7274-7284; Pena, C., Garcia, J.M., Silva, J., Garcia, V., Rodriguez, R., Alonso, I., Millan, I., Bonilla, F., E-cadherin and vitamin D receptor regulation by SNAIL and ZEB1 in colon cancer: clinicopathological correlations (2005) Hum. Mol. Genet., 14, pp. 3361-3370; Liu, Y., Hong, Y., Zhao, Y., Ismail, T.M., Wong, Y., Eu, K.W., Histone H3 (lys-9) deacetylation is associated with transcriptional silencing of E-cadherin in colorectal cancer cell lines (2008) Cancer Invest., 26, pp. 575-582; von Burstin, J., Eser, S., Paul, M.C., Seidler, B., Brandl, M., Messer, M., von Werder, A., Saur, D., E-cadherin regulates metastasis of pancreatic cancer in vivo and is suppressed by a SNAIL/HDAC1/HDAC2 repressor complex (2009) Gastroenterology, 137, pp. 361-371. , (371 e361-365); Herranz, N., Pasini, D., Diaz, V.M., Franci, C., Gutierrez, A., Dave, N., Escriva, M., Peiro, S., Polycomb complex 2 is required for E-cadherin repression by the Snail1 transcription factor (2008) Mol. Cell. Biol., 28, pp. 4772-4781; Ambros, V., The functions of animal microRNAs (2004) Nature, 431, pp. 350-355; He, L., Hannon, G.J., MicroRNAs: small RNAs with a big role in gene regulation (2004) Nat. Rev. Genet., 5, pp. 522-531; Hurteau, G.J., Carlson, J.A., Spivack, S.D., Brock, G.J., Overexpression of the microRNA hsa-miR-200c leads to reduced expression of transcription factor 8 and increased expression of E-cadherin (2007) Cancer Res., 67, pp. 7972-7976; Korpal, M., Lee, E.S., Hu, G., Kang, Y., The miR-200 family inhibits epithelial-mesenchymal transition and cancer cell migration by direct targeting of E-cadherin transcriptional repressors ZEB1 and ZEB2 (2008) J. Biol. Chem., 283, pp. 14910-14914; Gregory, P.A., Bert, A.G., Paterson, E.L., Barry, S.C., Tsykin, A., Farshid, G., Vadas, M.A., Goodall, G.J., The miR-200 family and miR-205 regulate epithelial to mesenchymal transition by targeting ZEB1 and SIP1 (2008) Nat. Cell Biol., 10, pp. 593-601; Park, S.M., Gaur, A.B., Lengyel, E., Peter, M.E., The miR-200 family determines the epithelial phenotype of cancer cells by targeting the E-cadherin repressors ZEB1 and ZEB2 (2008) Genes Dev., 22, pp. 894-907; Tan, H.X., Wang, Q., Chen, L.Z., Huang, X.H., Chen, J.S., Fu, X.H., Cao, L.Q., Zhang, L.J., MicroRNA-9 reduces cell invasion and E-cadherin secretion in SK-Hep-1 cell (2010) Med. Oncol., 27, pp. 654-660; Ma, L., Young, J., Prabhala, H., Pan, E., Mestdagh, P., Muth, D., Teruya-Feldstein, J., Weinberg, R.A., MiR-9, a MYC/MYCN-activated microRNA, regulates E-cadherin and cancer metastasis (2010) Nat. Cell Biol., 12, pp. 247-256; Oki, Y., Issa, J.P., Epigenetic mechanisms in AML-a target for therapy (2010) Cancer Treat. Res., 145, pp. 19-40; Simoes-Correia, J., Figueiredo, J., Oliveira, C., van Hengel, J., Seruca, R., van Roy, F., Suriano, G., Endoplasmic reticulum quality control: a new mechanism of E-cadherin regulation and its implication in cancer (2008) Hum. Mol. Genet., 17, pp. 3566-3576; Sitia, R., Braakman, I., Quality control in the endoplasmic reticulum protein factory (2003) Nature, 426, pp. 891-894; Meusser, B., Hirsch, C., Jarosch, E., Sommer, T., ERAD: the long road to destruction (2005) Nat. Cell Biol., 7, pp. 766-772; van Hengel, J., van Roy, F., Diverse functions of p120ctn in tumors (2007) Biochim. Biophys. Acta, 1773, pp. 78-88; Jawhari, A.U., Noda, M., Pignatelli, M., Farthing, M., Up-regulated cytoplasmic expression, with reduced membranous distribution, of the src substrate p120(ctn) in gastric carcinoma (1999) J. Pathol., 189, pp. 180-185; Karayiannakis, A.J., Syrigos, K.N., Alexiou, D., Kalahanis, N., Rosenberg, T., Bastounis, E., Pignatelli, M., Expression patterns of the novel catenin p120cas in gastrointestinal cancers (1999) Anticancer. Res., 19, pp. 4401-4405; Karatzas, G., Karayiannakis, A.J., Syrigos, K.N., Chatzigianni, E., Papanikolaou, S., Simatos, G., Papanikolaou, D., Bogris, S., Expression patterns of the E-cadherin-catenin cell-cell adhesion complex in gastric cancer (2000) Hepatogastroenterology, 47, pp. 1465-1469; Apweiler, R., Hermjakob, H., Sharon, N., On the frequency of protein glycosylation, as deduced from analysis of the SWISS-PROT database (1999) Biochim. Biophys. Acta, 1473, pp. 4-8; Dube, D.H., Bertozzi, C.R., Glycans in cancer and inflammation-potential for therapeutics and diagnostics (2005) Nat. Rev. Drug Discov., 4, pp. 477-488; Pinho, S.S., Osorio, H., Nita-Lazar, M., Gomes, J., Lopes, C., Gartner, F., Reis, C.A., Role of E-cadherin N-glycosylation profile in a mammary tumor model (2009) Biochem. Biophys. Res. Commun., 379, pp. 1091-1096; Iijima, J., Zhao, Y., Isaji, T., Kameyama, A., Nakaya, S., Wang, X., Ihara, H., Gu, J., Cell-cell interaction-dependent regulation of N-acetylglucosaminyltransferase III and the bisected N-glycans in GE11 epithelial cells. Involvement of E-cadherin-mediated cell adhesion (2006) J. Biol. Chem., 281, pp. 13038-13046; Yoshimura, M., Ihara, Y., Matsuzawa, Y., Taniguchi, N., Aberrant glycosylation of E-cadherin enhances cell-cell binding to suppress metastasis (1996) J. Biol. Chem., 271, pp. 13811-13815; Giles, R.H., van Es, J.H., Clevers, H., Caught up in a Wnt storm: Wnt signaling in cancer (2003) Biochim. Biophys. Acta, 1653, pp. 1-24; Reynolds, A.B., Roczniak-Ferguson, A., Emerging roles for p120-catenin in cell adhesion and cancer (2004) Oncogene, 23, pp. 7947-7956; Christofori, G., Changing neighbours, changing behaviour: cell adhesion molecule-mediated signalling during tumour progression (2003) EMBO J., 22, pp. 2318-2323; Gottardi, C.J., Wong, E., Gumbiner, B.M., E-cadherin suppresses cellular transformation by inhibiting beta-catenin signaling in an adhesion-independent manner (2001) J. Cell Biol., 153, pp. 1049-1060; Stockinger, A., Eger, A., Wolf, J., Beug, H., Foisner, R., E-cadherin regulates cell growth by modulating proliferation-dependent beta-catenin transcriptional activity (2001) J. Cell Biol., 154, pp. 1185-1196; Suriano, G., Mulholland, D., de Wever, O., Ferreira, P., Mateus, A.R., Bruyneel, E., Nelson, C.C., Seruca, R., The intracellular E-cadherin germline mutation V832 M lacks the ability to mediate cell-cell adhesion and to suppress invasion (2003) Oncogene, 22, pp. 5716-5719; Sahai, E., Marshall, C.J., RHO-GTPases and cancer (2002) Nat. Rev. Cancer, 2, pp. 133-142; Deplazes, J., Fuchs, M., Rauser, S., Genth, H., Lengyel, E., Busch, R., Luber, B., Rac1 and Rho contribute to the migratory and invasive phenotype associated with somatic E-cadherin mutation (2009) Hum. Mol. Genet., 18, pp. 3632-3644; Mateus, A.R., Seruca, R., Machado, J.C., Keller, G., Oliveira, M.J., Suriano, G., Luber, B., EGFR regulates RhoA-GTP dependent cell motility in E-cadherin mutant cells (2007) Hum. Mol. Genet., 16, pp. 1639-1647; Mateus, A.R., Simoes-Correia, J., Figueiredo, J., Heindl, S., Alves, C.C., Suriano, G., Luber, B., Seruca, R., E-cadherin mutations and cell motility: a genotype-phenotype correlation (2009) Exp. Cell Res., 315, pp. 1393-1402; Crepaldi, T., Pollack, A.L., Prat, M., Zborek, A., Mostov, K., Comoglio, P.M., Targeting of the SF/HGF receptor to the basolateral domain of polarized epithelial cells (1994) J. Cell Biol., 125, pp. 313-320; Pece, S., Gutkind, J.S., Signaling from E-cadherins to the MAPK pathway by the recruitment and activation of epidermal growth factor receptors upon cell-cell contact formation (2000) J. Biol. Chem., 275, pp. 41227-41233; Thiery, J.P., Epithelial-mesenchymal transitions in tumour progression (2002) Nat. Rev. Cancer, 2, pp. 442-454; Qian, X., Karpova, T., Sheppard, A.M., McNally, J., Lowy, D.R., E-cadherin-mediated adhesion inhibits ligand-dependent activation of diverse receptor tyrosine kinases (2004) EMBO J., 23, pp. 1739-1748; Takahashi, K., Suzuki, K., Density-dependent inhibition of growth involves prevention of EGF receptor activation by E-cadherin-mediated cell-cell adhesion (1996) Exp. Cell Res., 226, pp. 214-222; Mook, O.R., Frederiks, W.M., Van Noorden, C.J., The role of gelatinases in colorectal cancer progression and metastasis (2004) Biochim. Biophys. Acta, 1705, pp. 69-89; Munshi, H.G., Ghosh, S., Mukhopadhyay, S., Wu, Y.I., Sen, R., Green, K.J., Stack, M.S., Proteinase suppression by E-cadherin-mediated cell-cell attachment in premalignant oral keratinocytes (2002) J. Biol. Chem., 277, pp. 38159-38167; Lochter, A., Galosy, S., Muschler, J., Freedman, N., Werb, Z., Bissell, M.J., Matrix metalloproteinase stromelysin-1 triggers a cascade of molecular alterations that leads to stable epithelial-to-mesenchymal conversion and a premalignant phenotype in mammary epithelial cells (1997) J. Cell Biol., 139, pp. 1861-1872; Davies, G., Jiang, W.G., Mason, M.D., Matrilysin mediates extracellular cleavage of E-cadherin from prostate cancer cells: a key mechanism in hepatocyte growth factor/scatter factor-induced cell-cell dissociation and in vitro invasion (2001) Clin. Cancer Res., 7, pp. 3289-3297; Noe, V., Fingleton, B., Jacobs, K., Crawford, H.C., Vermeulen, S., Steelant, W., Bruyneel, E., Mareel, M., Release of an invasion promoter E-cadherin fragment by matrilysin and stromelysin-1 (2001) J. Cell Sci., 114, pp. 111-118; Ryniers, F., Stove, C., Goethals, M., Brackenier, L., Noe, V., Bracke, M., Vandekerckhove, J., Bruyneel, E., Plasmin produces an E-cadherin fragment that stimulates cancer cell invasion (2002) Biol. Chem., 383, pp. 159-165; Comoglio, P.M., Boccaccio, C., Trusolino, L., Interactions between growth factor receptors and adhesion molecules: breaking the rules (2003) Curr. Opin. Cell Biol., 15, pp. 565-571; Ferreira, P., Oliveira, M.J., Beraldi, E., Mateus, A.R., Nakajima, T., Gleave, M., Yokota, J., Suriano, G., Loss of functional E-cadherin renders cells more resistant to the apoptotic agent taxol in vitro (2005) Exp. Cell Res., 310, pp. 99-104; Ferreira, A.C., Suriano, G., Mendes, N., Gomes, B., Wen, X., Carneiro, F., Seruca, R., Machado, J.C., E-cadherin impairment increases cell survival through Notch-dependent upregulation of Bcl-2 (2012) Hum. Mol. Genet., 21, pp. 334-343; Huang, F.Y., Chan, A.O., Rashid, A., Wong, D.K., Cho, C.H., Yuen, M.F., Helicobacter pylori induces promoter methylation of E-cadherin via interleukin-1beta activation of nitric oxide production in gastric cancer cells (2012) Cancer; Chan, A.O., Lam, S.K., Wong, B.C., Wong, W.M., Yuen, M.F., Yeung, Y.H., Hui, W.M., Kwong, Y.L., Promoter methylation of E-cadherin gene in gastric mucosa associated with Helicobacter pylori infection and in gastric cancer (2003) Gut, 52, pp. 502-506; Leung, W.K., Man, E.P., Yu, J., Go, M.Y., To, K.F., Yamaoka, Y., Cheng, V.Y., Sung, J.J., Effects of Helicobacter pylori eradication on methylation status of E-cadherin gene in noncancerous stomach (2006) Clin. Cancer Res., 12, pp. 3216-3221; Perri, F., Cotugno, R., Piepoli, A., Merla, A., Quitadamo, M., Gentile, A., Pilotto, A., Andriulli, A., Aberrant DNA methylation in non-neoplastic gastric mucosa of H. pylori infected patients and effect of eradication (2007) Am. J. Gastroenterol., 102, pp. 1361-1371; Chan, A.O., Peng, J.Z., Lam, S.K., Lai, K.C., Yuen, M.F., Cheung, H.K., Kwong, Y.L., Wong, B.C., Eradication of Helicobacter pylori infection reverses E-cadherin promoter hypermethylation (2006) Gut, 55, pp. 463-468; Schirrmeister, W., Gnad, T., Wex, T., Higashiyama, S., Wolke, C., Naumann, M., Lendeckel, U., Ectodomain shedding of E-cadherin and c-Met is induced by Helicobacter pylori infection (2009) Exp. Cell Res., 315, pp. 3500-3508; Hoy, B., Lower, M., Weydig, C., Carra, G., Tegtmeyer, N., Geppert, T., Schroder, P., Wessler, S., Helicobacter pylori HtrA is a new secreted virulence factor that cleaves E-cadherin to disrupt intercellular adhesion (2010) EMBO Rep., 11, pp. 798-804; O'Connor, P.M., Lapointe, T.K., Jackson, S., Beck, P.L., Jones, N.L., Buret, A.G., Helicobacter pylori activates calpain via toll-like receptor 2 to disrupt adherens junctions in human gastric epithelial cells (2011) Infect. Immun., 79, pp. 3887-3894; Conlin, V.S., Curtis, S.B., Zhao, Y., Moore, E.D., Smith, V.C., Meloche, R.M., Finlay, B.B., Buchan, A.M., Helicobacter pylori infection targets adherens junction regulatory proteins and results in increased rates of migration in human gastric epithelial cells (2004) Infect. Immun., 72, pp. 5181-5192; Suzuki, M., Mimuro, H., Suzuki, T., Park, M., Yamamoto, T., Sasakawa, C., Interaction of CagA with Crk plays an important role in Helicobacter pylori-induced loss of gastric epithelial cell adhesion (2005) J. Exp. Med., 202, pp. 1235-1247; Franco, A.T., Israel, D.A., Washington, M.K., Krishna, U., Fox, J.G., Rogers, A.B., Neish, A.S., Peek, R.M., Activation of beta-catenin by carcinogenic Helicobacter pylori (2005) Proc. Natl. Acad. Sci. U. S. A., 102, pp. 10646-10651; Murata-Kamiya, N., Kurashima, Y., Teishikata, Y., Yamahashi, Y., Saito, Y., Higashi, H., Aburatani, H., Hatakeyama, M., Helicobacter pylori CagA interacts with E-cadherin and deregulates the beta-catenin signal that promotes intestinal transdifferentiation in gastric epithelial cells (2007) Oncogene, 26, pp. 4617-4626; Sokolova, O., Bozko, P.M., Naumann, M., Helicobacter pylori suppresses glycogen synthase kinase 3beta to promote beta-catenin activity (2008) J. Biol. Chem., 283, pp. 29367-29374; Ogden, S.R., Wroblewski, L.E., Weydig, C., Romero-Gallo, J., O'Brien, D.P., Israel, D.A., Krishna, U.S., Peek, R.M., P120 and Kaiso regulate Helicobacter pylori-induced expression of matrix metalloproteinase-7 (2008) Mol. Biol. Cell, 19, pp. 4110-4121; Bebb, J.R., Leach, L., Zaitoun, A., Hand, N., Letley, D.P., Thomas, R., Atherton, J.C., Effects of Helicobacter pylori on the cadherin-catenin complex (2006) J. Clin. Pathol., 59, pp. 1261-1266; Oliveira, M.J., Costa, A.M., Costa, A.C., Ferreira, R.M., Sampaio, P., Machado, J.C., Seruca, R., Figueiredo, C., CagA associates with c-Met, E-cadherin, and p120-catenin in a multiproteic complex that suppresses Helicobacter pylori-induced cell-invasive phenotype (2009) J. Infect. Dis., 200, pp. 745-755; Oliveira, M.J., Costa, A.C., Costa, A.M., Henriques, L., Suriano, G., Atherton, J.C., Machado, J.C., Figueiredo, C., Helicobacter pylori induces gastric epithelial cell invasion in a c-Met and type IV secretion system-dependent manner (2006) J. Biol. Chem., 281, pp. 34888-34896; Jang, A.C., Starz-Gaiano, M., Montell, D.J., Modeling migration and metastasis in Drosophila (2007) J. Mammary Gland Biol. Neoplasia, 12, pp. 103-114; Pereira, P.S., Teixeira, A., Pinho, S., Ferreira, P., Fernandes, J., Oliveira, C., Seruca, R., Casares, F., E-cadherin missense mutations, associated with hereditary diffuse gastric cancer (HDGC) syndrome, display distinct invasive behaviors and genetic interactions with the Wnt and Notch pathways in Drosophila epithelia (2006) Hum. Mol. Genet., 15, pp. 1704-1712; Caldeira, J., Pereira, P.S., Suriano, G., Casares, F., Using fruitflies to help understand the molecular mechanisms of human hereditary diffuse gastric cancer (2009) Int. J. Dev. Biol., 53, pp. 1557-1561; Humar, B., Blair, V., Charlton, A., More, H., Martin, I., Guilford, P., E-cadherin deficiency initiates gastric signet-ring cell carcinoma in mice and man (2009) Cancer Res., 69, pp. 2050-2056; Mbalaviele, G., Dunstan, C.R., Sasaki, A., Williams, P.J., Mundy, G.R., Yoneda, T., E-cadherin expression in human breast cancer cells suppresses the development of osteolytic bone metastases in an experimental metastasis model (1996) Cancer Res., 56, pp. 4063-4070; Perl, A.K., Wilgenbus, P., Dahl, U., Semb, H., Christofori, G., A causal role for E-cadherin in the transition from adenoma to carcinoma (1998) Nature, 392, pp. 190-193; Kuwabara, Y., Yamada, T., Yamazaki, K., Du, W.L., Banno, K., Aoki, D., Sakamoto, M., Establishment of an ovarian metastasis model and possible involvement of E-cadherin down-regulation in the metastasis (2008) Cancer Sci., 99, pp. 1933-1939; Shimoyama, Y., Hirohashi, S., Hirano, S., Noguchi, M., Shimosato, Y., Takeichi, M., Abe, O., Cadherin cell-adhesion molecules in human epithelial tissues and carcinomas (1989) Cancer Res., 49, pp. 2128-2133; Sanders, D.S., Bruton, R., Darnton, S.J., Casson, A.G., Hanson, I., Williams, H.K., Jankowski, J., Sequential changes in cadherin-catenin expression associated with the progression and heterogeneity of primary oesophageal squamous carcinoma (1998) Int. J. Cancer, 79, pp. 573-579; Rocha, A.S., Soares, P., Machado, J.C., Maximo, V., Fonseca, E., Franssila, K., Sobrinho-Simoes, M., Mucoepidermoid carcinoma of the thyroid: a tumour histotype characterised by P-cadherin neoexpression and marked abnormalities of E-cadherin/catenins complex (2002) Virchows Arch., 440, pp. 498-504; Kim, M.A., Jung, E.J., Lee, H.S., Lee, H.E., Yang, H.K., Oh, D.Y., Bang, Y.J., Kim, W.H., P-cadherin expression in gastric carcinoma: its regulation mechanism and prognostic significance (2010) Hum. Pathol., 41, pp. 877-885; Imai, K., Hirata, S., Irie, A., Senju, S., Ikuta, Y., Yokomine, K., Harao, M., Nishimura, Y., Identification of a novel tumor-associated antigen, cadherin 3/P-cadherin, as a possible target for immunotherapy of pancreatic, gastric, and colorectal cancers (2008) Clin. Cancer Res., 14, pp. 6487-6495; Lo Muzio, L., Campisi, G., Farina, A., Rubini, C., Pannone, G., Serpico, R., Laino, G., Carinci, F., P-cadherin expression and survival rate in oral squamous cell carcinoma: an immunohistochemical study (2005) BMC Cancer, 5, p. 63; Han, A.C., Edelson, M.I., Peralta Soler, A., Knudsen, K.A., Lifschitz-Mercer, B., Czernobilsky, B., Rosenblum, N.G., Salazar, H., Cadherin expression in glandular tumors of the cervix (2000) Cancer, 89, pp. 2053-2058; Longatto Filho, A., Albergaria, A., Paredes, J., Moreira, M.A., Milanezi, F., Schmitt, F.C., P-cadherin expression in glandular lesions of the uterine cervix detected by liquid-based cytology (2005) Cytopathology, 16, pp. 88-93; Stefansson, I.M., Salvesen, H.B., Akslen, L.A., Prognostic impact of alterations in P-cadherin expression and related cell adhesion markers in endometrial cancer (2004) J. Clin. Oncol., 22, pp. 1242-1252; Moreno-Bueno, G., Hardisson, D., Sarrio, D., Sanchez, C., Cassia, R., Prat, J., Herman, J.G., Palacios, J., Abnormalities of E- and P-cadherin and catenin (beta-, gamma-catenin, and p120ctn) expression in endometrial cancer and endometrial atypical hyperplasia (2003) J. Pathol., 199, pp. 471-478; Quattrocchi, L., Green, A.R., Martin, S., Durrant, L., Deen, S., The cadherin switch in ovarian high-grade serous carcinoma is associated with disease progression (2011) Virchows Arch., 459, pp. 21-29; Sarrio, D., Moreno-Bueno, G., Sanchez-Estevez, C., Banon-Rodriguez, I., Hernandez-Cortes, G., Hardisson, D., Palacios, J., Expression of cadherins and catenins correlates with distinct histologic types of ovarian carcinomas (2006) Hum. Pathol., 37, pp. 1042-1049; Soler, A.P., Harner, G.D., Knudsen, K.A., McBrearty, F.X., Grujic, E., Salazar, H., Han, A.C., Keshgegian, A.A., Expression of P-cadherin identifies prostate-specific-antigen-negative cells in epithelial tissues of male sexual accessory organs and in prostatic carcinomas. Implications for prostate cancer biology (1997) Am. J. Pathol., 151, pp. 471-478; Bryan, R.T., Atherfold, P.A., Yeo, Y., Jones, L.J., Harrison, R.F., Wallace, D.M., Jankowski, J.A., Cadherin switching dictates the biology of transitional cell carcinoma of the bladder: ex vivo and in vitro studies (2008) J. Pathol., 215, pp. 184-194; Matos, I., Dufloth, R., Alvarenga, M., Zeferino, L.C., Schmitt, F., P63, cytokeratin 5, and P-cadherin: three molecular markers to distinguish basal phenotype in breast carcinomas (2005) Virchows Arch., 447, pp. 688-694; Arnes, J.B., Brunet, J.S., Stefansson, I., Begin, L.R., Wong, N., Chappuis, P.O., Akslen, L.A., Foulkes, W.D., Placental cadherin and the basal epithelial phenotype of BRCA1-related breast cancer (2005) Clin. Cancer Res., 11, pp. 4003-4011; Palacios, J., Benito, N., Pizarro, A., Suarez, A., Espada, J., Cano, A., Gamallo, C., Anomalous expression of P-cadherin in breast carcinoma. Correlation with E-cadherin expression and pathological features (1995) Am. J. Pathol., 146, pp. 605-612; Peralta Soler, A., Knudsen, K.A., Salazar, H., Han, A.C., Keshgegian, A.A., P-cadherin expression in breast carcinoma indicates poor survival (1999) Cancer, 86, pp. 1263-1272; Paredes, J., Milanezi, F., Reis-Filho, J.S., Leitao, D., Athanazio, D., Schmitt, F., Aberrant P-cadherin expression: is it associated with estrogen-independent growth in breast cancer? (2002) Pathol. Res. Pract., 198, pp. 795-801; Kovacs, A., Dhillon, J., Walker, R.A., Expression of P-cadherin, but not E-cadherin or N-cadherin, relates to pathological and functional differentiation of breast carcinomas (2003) Mol. Pathol., 56, pp. 318-322; Gamallo, C., Moreno-Bueno, G., Sarrio, D., Calero, F., Hardisson, D., Palacios, J., The prognostic significance of P-cadherin in infiltrating ductal breast carcinoma (2001) Mod. Pathol., 14, pp. 650-654; Paredes, J., Correia, A.L., Ribeiro, A.S., Milanezi, F., Cameselle-Teijeiro, J., Schmitt, F.C., Breast carcinomas that co-express E- and P-cadherin are associated with p120-catenin cytoplasmic localisation and poor patient survival (2008) J. Clin. Pathol., 61, pp. 856-862; Foulkes, W.D., Stefansson, I.M., Chappuis, P.O., Begin, L.R., Goffin, J.R., Wong, N., Trudel, M., Akslen, L.A., Germline BRCA1 mutations and a basal epithelial phenotype in breast cancer (2003) J. Natl. Cancer Inst., 95, pp. 1482-1485; Lakhani, S.R., Reis-Filho, J.S., Fulford, L., Penault-Llorca, F., van der Vijver, M., Parry, S., Bishop, T., Easton, D.F., Prediction of BRCA1 status in patients with breast cancer using estrogen receptor and basal phenotype (2005) Clin. Cancer Res., 11, pp. 5175-5180; Palacios, J., Honrado, E., Osorio, A., Cazorla, A., Sarrio, D., Barroso, A., Rodriguez, S., Benitez, J., Immunohistochemical characteristics defined by tissue microarray of hereditary breast cancer not attributable to BRCA1 or BRCA2 mutations: differences from breast carcinomas arising in BRCA1 and BRCA2 mutation carriers (2003) Clin. Cancer Res., 9, pp. 3606-3614; Palacios, J., Honrado, E., Osorio, A., Cazorla, A., Sarrio, D., Barroso, A., Rodriguez, S., Benitez, J., Phenotypic characterization of BRCA1 and BRCA2 tumors based in a tissue microarray study with 37 immunohistochemical markers (2005) Breast Cancer Res. Treat., 90, pp. 5-14; Gorski, J.J., James, C.R., Quinn, J.E., Stewart, G.E., Staunton, K.C., Buckley, N.E., McDyer, F.A., Harkin, D.P., BRCA1 transcriptionally regulates genes associated with the basal-like phenotype in breast cancer (2010) Breast Cancer Res. Treat., 122, pp. 721-731; Albergaria, A., Ribeiro, A.S., Pinho, S., Milanezi, F., Carneiro, V., Sousa, B., Sousa, S., Schmitt, F., ICI 182,780 induces P-cadherin overexpression in breast cancer cells through chromatin remodelling at the promoter level: a role for C/EBPbeta in CDH3 gene activation (2010) Hum. Mol. Genet., 19, pp. 2554-2566; Sato, N., Fukushima, N., Maitra, A., Matsubayashi, H., Yeo, C.J., Cameron, J.L., Hruban, R.H., Goggins, M., Discovery of novel targets for aberrant methylation in pancreatic carcinoma using high-throughput microarrays (2003) Cancer Res., 63, pp. 3735-3742; Milicic, A., Harrison, L.A., Goodlad, R.A., Hardy, R.G., Nicholson, A.M., Presz, M., Sieber, O., Jankowski, J.A., Ectopic expression of P-cadherin correlates with promoter hypomethylation early in colorectal carcinogenesis and enhanced intestinal crypt fission in vivo (2008) Cancer Res., 68, pp. 7760-7768; Van Marck, V., Stove, C., Van Den Bossche, K., Stove, V., Paredes, J., Vander Haeghen, Y., Bracke, M., P-cadherin promotes cell-cell adhesion and counteracts invasion in human melanoma (2005) Cancer Res., 65, pp. 8774-8783; Sarrio, D., Palacios, J., Hergueta-Redondo, M., Gomez-Lopez, G., Cano, A., Moreno-Bueno, G., Functional characterization of E- and P-cadherin in invasive breast cancer cells (2009) BMC Cancer, 9, p. 74; Bauer, K., Dowejko, A., Bosserhoff, A.K., Reichert, T.E., Bauer, R.J., P-cadherin induces an epithelial-like phenotype in oral squamous cell carcinoma by GSK-3beta-mediated Snail phosphorylation (2009) Carcinogenesis, 30, pp. 1781-1788; Bauer, K., Dowejko, A., Bosserhoff, A.K., Reichert, T.E., Bauer, R., Slit-2 facilitates interaction of P-cadherin with Robo-3 and inhibits cell migration in an oral squamous cell carcinoma cell line (2011) Carcinogenesis, 32, pp. 935-943; Mandeville, J.A., Silva Neto, B., Vanni, A.J., Smith, G.L., Rieger-Christ, K.M., Zeheb, R., Loda, M., Summerhayes, I.C., P-cadherin as a prognostic indicator and a modulator of migratory behaviour in bladder carcinoma cells (2008) BJU Int., 102, pp. 1707-1714; Cheung, L.W., Leung, P.C., Wong, A.S., Cadherin switching and activation of p120 catenin signaling are mediators of gonadotropin-releasing hormone to promote tumor cell migration and invasion in ovarian cancer (2010) Oncogene, 29, pp. 2427-2440; Reynolds, A.B., Daniel, J.M., Mo, Y.Y., Wu, J., Zhang, Z., The novel catenin p120cas binds classical cadherins and induces an unusual morphological phenotype in NIH3T3 fibroblasts (1996) Exp. Cell Res., 225, pp. 328-337; Baki, L., Marambaud, P., Efthimiopoulos, S., Georgakopoulos, A., Wen, P., Cui, W., Shioi, J., Robakis, N.K., Presenilin-1 binds cytoplasmic epithelial cadherin, inhibits cadherin/p120 association, and regulates stability and function of the cadherin/catenin adhesion complex (2001) Proc. Natl. Acad. Sci. U. S. A., 98, pp. 2381-2386; Jacobs, K., Van Gele, M., Forsyth, R., Brochez, L., Vanhoecke, B., De Wever, O., Bracke, M., P-cadherin counteracts myosin II-B function: implications in melanoma progression (2010) Mol. Cancer, 9, p. 255; Radice, G.L., Sauer, C.L., Kostetskii, I., Peralta Soler, A., Knudsen, K.A., Inappropriate P-cadherin expression in the mouse mammary epithelium is compatible with normal mammary gland function (2003) Differentiation, 71, pp. 361-373; Gregory, D.J., Mikhaylova, L., Fedulov, A.V., Selective DNA demethylation by fusion of TDG with a sequence-specific DNA-binding domain (2012) Epigenetics, 7; Zhang, C.C., Yan, Z., Zhang, Q., Kuszpit, K., Zasadny, K., Qiu, M., Painter, C.L., VanArsdale, T., PF-03732010: a fully human monoclonal antibody against P-cadherin with antitumor and antimetastatic activity (2010) Clin. Cancer Res., 16, pp. 5177-5188
Keywords: antineoplastic activity; antineoplastic agent; Breast; breast cancer; Cancer; cancer chemotherapy; cancer model; cancer survival; drug effect; E-cadherin; Gastric; gene expression regulation; gene function; gene location; gene overexpression; gene structure; genetic association; genetic code; Helicobacter infection; Hereditary diffuse gastric cancer; human; in vivo study; loss of function mutation; lymph node metastasis; malignant neoplastic disease; molecular dynamics; molecular pathology; molecularly targeted therapy; nonhuman; P cadherin; P cadherin gene; P-cadherin; pf 03732010; priority journal; protein expression; protein function; protein inhibitor; protein processing; review; signal transduction; stomach cancer; transcription regulation; tumor gene; unclassified drug; uvomorulin; uvomorulin gene; vasculotropin inhibitor

Methamphetamine mimics the neurochemical profile of aging in rats and impairs recognition memory - Melo, P.; Magalhães, A.; Alves, C.J.; Tavares, M.A.; De Sousa, L.; Summavielle, T.; Moradas-Ferreira, P. (NeuroToxicologyNeuroToxicology, 2012)
Brain neurochemistry and cognition performance are thought to decline with age. Accumulating data indicate that similar events occur after prolonged methamphetamine (MA) exposure. Using the rat as a model, the present study was designed to uncover common alteration patterns in brain neurochemistry and memory performance between aging and prolonged MA exposure. To this end, animals were treated with a chronic binge MA administration paradigm (20. mg/kg/day from postnatal day 91 to 100). Three-age control groups received isovolumetric saline treatment and were tested at the MA age-matched period, and at 12 and 20 months. We observed that both MA and aged animals presented a long, but not short, time impairment in novelty preference and an increased anxiety-like behavior. Neurochemical analysis indicated similar MA- and age-related impairments in dopamine, serotonin and metabolites in the striatum, prefrontal cortex and hippocampus. Thus, the present data illustrate that MA may be used to mimic age-related effects on neurotransmitter systems and advocate MA treatment as a feasible animal model to study neuronal processes associated with aging. © 2012 Elsevier Inc.
Keywords: Accelerated aging; Age Factors; aging; animal behavior; animal experiment; animal model; animal tissue; Animalia; Animals; anxiety; article; behavior change; Behavior, Animal; Brain; Brain Chemistry; controlled study; corpus striatum; dopamine; Exploratory Behavior; hippocampus; Hydroxyindoleacetic Acid; long term exposure; male; Memory Disorders; mental performance; Methamphetamine; Neurochemistry; neurotransmission; nonhuman; perinatal drug exposure; prefrontal cortex; priority journal; rat; Rats; Rats, Wistar; Rattus; recognition; Recognition (Psychology); Recognition memory; serotonin; sodium chloride; Time Factors

Poor reliability of visual analysis of fetal heart rate tracings: What should be done about it? - Bernardes, J.; Ayres-de-Campos, D. (American Journal of Obstetrics and GynecologyAm. J. Obstet. Gynecol., 2012)
Keywords: accuracy; Cardiotocography; clinical decision making; clinical practice; computer analysis; fetus blood sampling; fetus electrocardiography; fetus heart rate; Heart Rate, Fetal; human; Humans; letter; medical education; metabolic acidosis; newborn disease; priority journal; reliability; visual acuity

Tumor cell-educated periprostatic adipose tissue acquires an aggressive cancer-promoting secretory profile - Ribeiro, R.J.T.; Monteiro, C.P.D.; Cunha, V.F.P.M.; Azevedo, A.S.M.; Oliveira, M.J.; Monteiro, R.; Fraga, A.M.; Príncipe, P.; Lobato, C.; Lobo, F.; Morais, A.; Silva, V.; et al. (Cellular Physiology and BiochemistryCell. Physiol. Biochem., 2012)
Background/Aims: The microenvironment produces important factors that are crucial to prostate cancer (PCa) progression. However, the extent to which the cancer cells stimulate periprostatic adipose tissue (PPAT) to produce these proteins is largely unknown. Our purpose was to determine whether PCa cell-derived factors influence PPAT metabolic activity. Methods: Primary cultures of human PPAT samples from PCa patients (adipose tissue organotypic explants and primary stromal vascular fraction, SVF) were stimulated with conditioned medium (CM) collected from prostate carcinoma (PC3) cells. Cultures without CM were used as control. We used multiplex analysis and ELISA for protein quantification, qPCR to determine mitochondrial DNA (mtDNA) copy number and zymography for matrix metalloproteinase activity, in order to evaluate the response of adipose tissue explants and SVFs to PC3 CM. Results: Stimulation of PPAT explants with PCa PC3 CM induced adipokines associated with cancer progression (osteopontin, tumoral necrosis factor alpha and interleukin-6) and reduced the expression of the protective adipokine adiponectin. Notably, osteopontin protein expression was 13-fold upregulated. Matrix metalloproteinase 9 activity and mitochondrial DNA copy number were higher after stimulation with cancer CM. Stromovascular cells from PPAT in culture were not influenced by tumor-derived factors. Conclusion: The modulation of adipokine expression by tumor CM indicates the pervasive extent to which tumor cells command PPAT to produce factors favorable to their aggressiveness. © 2012 S. Karger AG, Basel.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: CEPBEdoi: 10.1159/000337604PubMed ID: 22415092Language of Original Document: EnglishCorrespondence Address: Ribeiro, R.J.T.; Portuguese Institute of Oncology, Porto Centre Molecular Oncology Group -CI, Edifício Laboratórios -Piso 4, Rua Dr. António Bernardino Almeida, 4200-072 Porto, Portugal; email: oriebir.r@gmail.comChemicals/CAS: adiponectin, 283182-39-8; gelatinase B, 146480-36-6; osteopontin, 106441-73-0; Adiponectin; Culture Media, Conditioned; Cytokines; DNA, Mitochondrial; Interleukin-6; Matrix Metalloproteinase 2, 3.4.24.24; Matrix Metalloproteinase 9, 3.4.24.35; Osteopontin, 106441-73-0; Tumor Necrosis Factor-alphaReferences: Hsing, A.W., Sakoda, L.C., Chua Jr., S., Obesity, metabolic syndrome, and prostate cancer (2007) Am J Clin Nutr, 86, pp. s843-857;Cao, Y., Ma, J., Body mass index, prostate cancer-specific mortality, and biochemical recurrence: A systematic review and meta-analysis (2011) Cancer Prev Res (Phila), 4, pp. 486-501; Baillargeon, J., Rose, D.P., Obesity, adipokines, and prostate cancer (review) (2006) Int J Oncol, 28, pp. 737-745; Mistry, T., Digby, J.E., Desai, K.M., Randeva, H.S., Obesity and Prostate Cancer: A Role for Adipokines (2007) European Urology, 52 (1), pp. 46-53. , DOI 10.1016/j.eururo.2007.03.054, PII S0302283807004307; Hirano, T., Morii, H., Nakazawa, K., Murakami, D., Yamashita, A., Asahi, J., Orimo, H., Tokura, Y., Enhancement of adipogenesis induction by conditioned media obtained from cancer cells (2008) Cancer Lett, 268, pp. 286-294; Andarawewa, K.L., Motrescu, E.R., Chenard, M.-P., Gansmuller, A., Stoll, I., Tomasetto, C., Rio, M.-C., Stromelysin-3 is a potent negative regulator of adipogenesis participating to cancer cell-adipocyte interaction/crosstalk at the tumor invasive front (2005) Cancer Research, 65 (23), pp. 10862-10871. , DOI 10.1158/0008-5472.CAN-05-1231; Jotzu, C., Alt, E., Welte, G., Li, J., Hennessy, B.T., Devarajan, E., Krishnappa, S., Song, Y.H., Adipose tissue derived stem cells differentiate into carcinoma-associated fibroblast-like cells under the influence of tumor derived factors (2011) Cell Oncol (Dordr), 34, pp. 55-67; Dolinkova, M., Dostalova, I., Lacinova, Z., Michalsky, D., Haluzikova, D., Mraz, M., The endocrine profile of subcutaneous and visceral adipose tissue of obese patients (2008) Mol Cell Endocrinol, 291, pp. 63-70; Van Roermund, J.G., Hinnen, K.A., Tolman, C.J., Bol, G.H., Witjes, J.A., Bosch, J.L., Kiemeney, L.A., Van Vulpen, M., Periprostatic fat correlates with tumour aggressiveness in prostate cancer patients (2011) BJU Int, 107, pp. 1775-1779; Sumitomo, M., Asakuma, J., Yoshii, H., Sato, A., Horiguchi, A., Ito, K., Nagakura, K., Asano, T., Anterior perirectal fat tissue thickness is a strong predictor of recurrence after high-intensity focused ultrasound for prostate cancer (2010) Int J Urol, 17, pp. 776-782; Finley, D.S., Calvert, V.S., Inokuchi, J., Lau, A., Narula, N., Petricoin, E.F., Zaldivar, F., Ornstein, D.K., Periprostatic adipose tissue as a modulator of prostate cancer aggressiveness (2009) J Urol, 182, pp. 1621-1627; Thalmann, S., Juge-Aubry, C.E., Meier, C.A., Explant cultures of white adipose tissue (2008) Methods Mol Biol, 456, pp. 195-199; Song, G.J., Lewis, V., Mitochondrial DNA integrity and copy number in sperm from infertile men (2008) Fertil Steril, 90, pp. 2238-2244; Park, J., Euhus, D.M., Scherer, P.E., Paracrine and Endocrine Effects of Adipose Tissue on Cancer Development and Progression (2011) Endocr Rev, 32, pp. 550-570; George, D.J., Halabi, S., Shepard, T.F., Sanford, B., Vogelzang, N.J., Small, E.J., Kantoff, P.W., The prognostic significance of plasma interleukin-6 levels in patients with metastatic hormone-refractory prostate cancer: Results from cancer and leukemia group B 9480 (2005) Clinical Cancer Research, 11 (5), pp. 1815-1820. , DOI 10.1158/1078-0432.CCR-04-1560; Michalaki, V., Syrigos, K., Charles, P., Waxman, J., Serum levels of IL-6 and TNF-α correlate with clinicopathological features and patient survival in patients with prostate cancer (2004) British Journal of Cancer, 90 (12), pp. 2312-2316; Dirat, B., Bochet, L., Dabek, M., Daviaud, D., Dauvillier, S., Majed, B., Wang, Y.Y., Muller, C., Cancerassociated adipocytes exhibit an activated phenotype and contribute to breast cancer invasion (2011) Cancer Res, 71, pp. 2455-2465; Culig, Z., New insights into the role of interleukin-6 in human prostate cancer (2009) J Urol, 182, pp. 1255-1256; Chun, J.Y., Nadiminty, N., Dutt, S., Lou, W., Yang, J.C., Kung, H.J., Evans, C.P., Gao, A.C., Interleukin-6 regulates androgen synthesis in prostate cancer cells (2009) Clin Cancer Res, 15, pp. 4815-4822; Weber, G.F., Lett, G.S., Haubein, N.C., Osteopontin is a marker for cancer aggressiveness and patient survival (2010) Br J Cancer, 103, pp. 861-869; Thalmann, G.N., Sikes, R.A., Devoll, R.E., Kiefer, J.A., Markwalder, R., Klima, I., Farach-Carson, C.M., Chung, L.W.K., Osteopontin: Possible role in prostate cancer progression (1999) Clinical Cancer Research, 5 (8), pp. 2271-2277; McAllister, S.S., Gifford, A.M., Greiner, A.L., Kelleher, S.P., Saelzler, M.P., Ince, T.A., Reinhardt, F., Weinberg, R.A., Systemic Endocrine Instigation of Indolent Tumor Growth Requires Osteopontin (2008) Cell, 133 (6), pp. 994-1005. , DOI 10.1016/j.cell.2008.04.045, PII S0092867408006211; Balkwill, F., TNF-alpha in promotion and progression of cancer (2006) Cancer Metastasis Rev, 25, pp. 409-416; Yan, B., Wang, H., Rabbani, Z.N., Zhao, Y., Li, W., Yuan, Y., Li, F., Li, C.-Y., Tumor necrosis factor-α is a potent endogenous mutagen that promotes cellular transformation (2006) Cancer Research, 66 (24), pp. 11565-11570. , DOI 10.1158/0008-5472.CAN-06-2540; Bates, R.C., Mercurio, A.M., Tumor necrosis factor-α stimulates the epithelial-tomesenchymal transition of human colonic organoids (2003) Molecular Biology of the Cell, 14 (5), pp. 1790-1800. , DOI 10.1091/mbc.E02-09-0583; Yamauchi, T., Kamon, J., Waki, H., Terauchi, Y., Kubota, N., Hara, K., Mori, Y., Kadowaki, T., The fat-derived hormone adiponectin reverses insulin resistance associated with both lipoatrophy and obesity (2001) Nature Medicine, 7 (8), pp. 941-946. , DOI 10.1038/90984; Li, H., Stampfer, M.J., Mucci, L., Rifai, N., Qiu, W., Kurth, T., Ma, J., A 25-year prospective study of plasma adiponectin and leptin concentrations and prostate cancer risk and survival (2010) Clin Chem, 56, pp. 34-43; Ribeiro, R., Lopes, C., Medeiros, R., The link between obesity and prostate cancer: The leptin pathway and therapeutic perspectives (2006) Prostate Cancer and Prostatic Diseases, 9 (1), pp. 19-24. , DOI 10.1038/sj.pcan.4500844, PII 4500844; Vaday, G.G., Peehl, D.M., Kadam, P.A., Lawrence, D.M., Expression of CCL5 (RANTES) and CCR5 in prostate cancer (2006) Prostate, 66 (2), pp. 124-134. , DOI 10.1002/pros.20306; Kessenbrock, K., Plaks, V., Werb, Z., Matrix metalloproteinases: Regulators of the tumor microenvironment (2010) Cell, 141, pp. 52-67; Bouloumie, A., Sengenes, C., Portolan, G., Galitzky, J., Lafontan, M., Adipocyte Produces Matrix Metalloproteinases 2 and 9 Involvement in Adipose Differentiation (2001) Diabetes, 50 (9), pp. 2080-2086; Bergers, G., Brekken, R., McMahon, G., Vu, T.H., Itoh, T., Tamaki, K., Tanzawa, K., Hanahan, D., Matrix metalloproteinase-9 triggers the angiogenic switch during carcinogenesis (2000) Nat Cell Biol, 2, pp. 737-744; Lin, C.Y., Tsai, P.H., Kandaswami, C.C., Lee, P.P., Huang, C.J., Hwang, J.J., Lee, M.T., Matrix metalloproteinase-9 cooperates with transcription factor Snail to induce epithelial-mesenchymal transition (2011) Cancer Sci, 102, pp. 815-827; Chakrabarti, S., Patel, K.D., Matrix metalloproteinase-2 (MMP-2) and MMP-9 in pulmonary pathology (2005) Experimental Lung Research, 31 (6), pp. 599-621. , DOI 10.1080/019021490944232; Sehgal, G., Hua, J., Bernhard, E.J., Sehgal, I., Thompson, T.C., Muschel, R.J., Requirement for matrix metalloproteinase-9 (Gelatinase B) expression in metastasis by murine prostate carcinoma (1998) American Journal of Pathology, 152 (2), pp. 591-596; Johnson, T.R., Koul, S., Kumar, B., Khandrika, L., Venezia, S., Maroni, P.D., Meacham, R.B., Koul, H.K., Loss of PDEF, a prostatederived Ets factor is associated with aggressive phenotype of prostate cancer: Regulation of MMP 9 by PDEF (2010) Mol Cancer, 9, p. 148; Trudel, D., Fradet, Y., Meyer, F., Tetu, B., Matrix metalloproteinase 9 is associated with Gleason score in prostate cancer but not with prognosis (2010) Hum Pathol, 41, pp. 1694-1701; Zhang, L., Shi, J., Feng, J., Klocker, H., Lee, C., Zhang, J., Type IV collagenase (matrix metalloproteinase-2 and -9) in prostate cancer (2004) Prostate Cancer and Prostatic Diseases, 7 (4), pp. 327-332. , DOI 10.1038/sj.pcan.4500750, PII 4500750; Zhong, W.D., Han, Z.D., He, H.C., Bi, X.C., Dai, Q.S., Zhu, G., Ye, Y.K., Chen, Z.N., CD147, MMP-1, MMP-2 and MMP-9 protein expression as significant prognostic factors in human prostate cancer (2008) Oncology, 75, pp. 230-236; Sauer, C.G., Kappeler, A., Spath, M., Kaden, J.J., Michel, M.S., Mayer, D., Bleyl, U., Grobholz, R., Expression and activity of matrix metalloproteinases-2 and -9 in serum, core needle biopsies and tissue specimens of prostate cancer patients (2004) Virchows Archiv, 444 (6), pp. 518-526; Opdenakker, G., Masure, S., Grillet, B., Van Damme, J., Cytokine-mediated regulation of human leukocyte gelatinases and role in arthritis (1991) Lymphokine Cytokine Res, 10, pp. 317-324; Unal, R., Yao-Borengasser, A., Varma, V., Rasouli, N., Labbate, C., Kern, P.A., Ranganathan, G., Matrix metalloproteinase-9 is increased in obese subjects and decreases in response to pioglitazone (2010) J Clin Endocrinol Metab, 95, pp. 2993-3001; Catalan, V., Gomez-Ambrosi, J., Rodriguez, A., Ramirez, B., Silva, C., Rotellar, F., Gil, M.J., Frühbeck, G., Increased adipose tissue expression of lipocalin-2 in obesity is related to inflammation and matrix metalloproteinase-2 and metalloproteinase-9 activities in humans (2009) J Mol Med (Berl), 87, pp. 803-813; Villarroya, J., Giralt, M., Villarroya, F., Mitochondrial DNA: An up-and-coming actor in white adipose tissue pathophysiology (2009) Obesity (Silver Spring), 17, pp. 1814-1820; Robin, E.D., Wong, R., Mitochondrial DNA molecules and virtual number of mitochondria per cell in mammalian cells (1988) J Cell Physiol, 136, pp. 507-513; Kaaman, M., Sparks, L.M., Van Harmelen, V., Smith, S.R., Sjolin, E., Dahlman, I., Arner, P., Strong association between mitochondrial DNA copy number and lipogenesis in human white adipose tissue (2007) Diabetologia, 50 (12), pp. 2526-2533. , DOI 10.1007/s00125-007-0818-6; Yamauchi, T., Kamon, J., Waki, H., Murakami, K., Motojima, K., Komeda, K., Ide, T., Kadowaki, T., The mechanisms by which both heterozygous peroxisome proliferator- activated receptor gamma (PPARgamma) deficiency and PPARgamma agonist improve insulin resistance (2001) J Biol Chem, 276, pp. 41245-41254; Wilson-Fritch, L., Burkart, A., Bell, G., Mendelson, K., Leszyk, J., Nicoloro, S., Czech, M., Corvera, S., Mitochondrial biogenesis and remodeling during adipogenesis and in response to the insulin sensitizer rosiglitazone (2003) Molecular and Cellular Biology, 23 (3), pp. 1085-1094. , DOI 10.1128/MCB.23.3.1085-1094.2003; Ducluzeau, P.H., Priou, M., Weitheimer, M., Flamment, M., Duluc, L., Iacobazi, F., Soleti, R., Malthièry, Y., Dynamic regulation of mitochondrial network and oxidative functions during 3T3-L1 fat cell differentiation (2011) J Physiol Biochem, 67, pp. 285-296; Bogacka, I., Ukropcova, B., McNeil, M., Gimble, J.M., Smith, S.R., Structural and functional consequences of mitochondrial biogenesis in human adipocytes in vitro (2005) Journal of Clinical Endocrinology and Metabolism, 90 (12), pp. 6650-6656. , http://jcem.endojournals.org/cgi/reprint/90/12/6650, DOI 10.1210/jc.2005-1024; Toda, S., Uchihashi, K., Aoki, S., Sonoda, E., Yamasaki, F., Piao, M., Ootani, A., Sugihara, H., Adipose tissueorganotypic culture system as a promising model for studying adipose tissue biology and regeneration (2009) Organogenesis, 5, pp. 50-56; Tuxhorn, J.A., Ayala, G.E., Rowley, D.R., Reactive stroma in prostate cancer progression (2001) Journal of Urology, 166 (6), pp. 2472-2483
Keywords: Adipokines; adiponectin; adipose tissue; adult; article; cancer cell; cancer growth; Cells, Cultured; clinical article; controlled study; Culture Media, Conditioned; culture medium; Cytokines; DNA, Mitochondrial; enzyme activity; enzyme linked immunosorbent assay; explant; gelatinase B; human; human cell; human tissue; Humans; interleukin 6; Interleukin-6; male; Matrix Metalloproteinase 2; Matrix Metalloproteinase 9; Middle Aged; mitochondrial DNA; Osteopontin; Periprostatic adipose tissue; priority journal; Prostate cancer; Prostatic Neoplasms; protein expression; protein induction; protein secretion; quantitative analysis; stroma cell; tissue metabolism; tumor necrosis factor alpha; Tumor Necrosis Factor-alpha

Complexity and categorical analysis may improve the interpretation of agreement studies using continuous variables - Costa-Santos, C.; Bernardes, J.; Antunes, L.; Ayres-de-Campos, D. (Journal of Evaluation in Clinical PracticeJ. Eval. Clin. Pract., 2011)
Rationale Complex clinical scenarios involving a high degree of uncertainty frequently lead to a poor agreement over diagnosis and management. However, inconsistent results can be found with the most widely used measures of agreement for continuous variables - the limits of agreement and the intraclass correlation coefficient. Aims and objectives We aim to improve the interpretation of agreement studies using continues variables. Methods and results Evaluation of agreement may be improved by complexity analysis and by categorization of variables, followed by the use of the proportions of agreement. Conclusions The average never characterizes a complex phenomenon and the methods used to access agreement in continuous variables are based on the mean. For future agreement studies, involving complex continuous variables, we recommend a complexity and categorical analysis. © 2011 Blackwell Publishing Ltd.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JECPFdoi: 10.1111/j.1365-2753.2011.01668.xPubMed ID: 21489051Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Department of Biostatistics and Medical Informatics, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: Costa Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) BJOG: An International Journal of Obstetrics and Gynaecology, 112 (5), pp. 667-669. , DOI 10.1111/j.1471-0528.2004.00505.x;Khan, K.S., Chien, P.F., Evaluation of a clinical test. I: Assessment of reliability (2001) BJOG, 108, pp. 562-567; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2005) Journal of Clinical Epidemiology, 58 (3), pp. 215-216. , DOI 10.1016/j.jclinepi.2004.07.007; Costa-Santos, C., Bernardes, J., Ayres-De-Campos, D., Costa, A., Costa, C., The limits of agreement and the intraclass correlation coefficient may be inconsistent in the interpretation of agreement (2011) Journal of Clinical Epidemiology, 64 (3), pp. 264-269; Costa-Santos, C., Antunes, L., Souto, A., Bernardes, J., Assessment of disagreement: A new information-based approach (2010) Annals of Epidemiology, 20, pp. 555-561; Luiz, R.R., Costa, A.J.L., Kale, P.L., Werneck, G.L., Assessment of agreement of a quantitative variable: A new graphical approach (2003) Journal of Clinical Epidemiology, 56 (10), pp. 963-967. , DOI 10.1016/S0895-4356(03)00164-1; Plsek, P.E., Greenhalgh, T., The challenge of complexity in health care (2001) British Medical Journal, 323 (7313), pp. 625-628; Shiell, A., Hawe, P., Gold, L., Complex interventions or complex systems? Implications for health economic evaluation (2008) BMJ, 336 (7656), pp. 1281-1283; Wilson, T., Holt, T., Complexity science: Complexity and clinical care (2001) British Medical Journal, 323 (7314), pp. 685-688; Miles, A., Complexity in medicine and healthcare: People and systems, theory and practice (2009) Journal of Evaluation in Clinical Practice, 15 (3), pp. 409-410; Shannon, Î., A mathematical theory of communication (1948) Bell System Technical Journal, 27, pp. 379-423. , 623- 656; Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) International Journal of Gynecology and Obstetrics, 57 (1), pp. 33-37. , DOI 10.1016/S0020-7292(97)02846-4, PII S0020729297028464; Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) British Journal of Obstetrics and Gynaecology, 106, pp. 1307-1310; Rooth, G., Guidelines for the use of fetal monitoring (1987) International Journal of Gynaecology and Obstetrics, 25, pp. 159-167; Grant, J.M., The fetal heart rate is normal, isn't it? Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Müller, R., Büttner, P., A critical discussion of intraclass correlation coefficients (1994) Statistics in Medicine, 13, pp. 2465-2476; Byrt, T., Bishop, J., Carlin, J.B., Bias, prevalence and kappa (1993) Journal of Clinical Epidemiology, 46 (5), pp. 423-429. , DOI 10.1016/0895-4356(93)90018-V; West, B.J., Homeostasis and Gauss statistics: Barriers to understanding natural variability (2010) Journal of Evaluation in Clinical Practice, 16, pp. 403-408; Goncalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Medical and Biological Engineering and Computing, 44 (10), pp. 847-855. , DOI 10.1007/s11517-006-0105-6; Costa Santos, C., Vitanyi, P.M.B., Bernardes, J., Antunes, L., Clustering fetal heart rate tracings by compression (2006) Proceedings - IEEE Symposium on Computer-Based Medical Systems, 2006, pp. 685-690. , DOI 10.1109/CBMS.2006.68, 1647650, Proceedings - 19th IEEE International Symposium on Computer-Based Medical Systems, CBMS 2006
Keywords: article; Biomedical research; Cardiotocography; clinical decision making; clinical practice; complexity; Data Interpretation, Statistical; Decision Making; entropy; Female; fetus heart rate; Heart Rate, Fetal; human; Humans; observer variation; Pregnancy; Pregnancy Outcome; priority journal; Reproducibility of Results; statistical data interpretation; Uncertainty

Covalent immobilization of antimicrobial peptides (AMPs) onto biomaterial surfaces - Costa, F.; Carvalho, I.F.; Montelaro, R.C.; Gomes, P.; Martins, M.C.L. (Acta BiomaterialiaActa Biomater., 2011)
Bacterial adhesion to biomaterials remains a major problem in the medical devices field. Antimicrobial peptides (AMPs) are well-known components of the innate immune system that can be applied to overcome biofilm-associated infections. Their relevance has been increasing as a practical alternative to conventional antibiotics, which are declining in effectiveness. The recent interest focused on these peptides can be explained by a group of special features, including a wide spectrum of activity, high efficacy at very low concentrations, target specificity, anti-endotoxin activity, synergistic action with classical antibiotics, and low propensity for developing resistance. Therefore, the development of an antimicrobial coating with such properties would be worthwhile. The immobilization of AMPs onto a biomaterial surface has further advantages as it also helps to circumvent AMPs' potential limitations, such as short half-life and cytotoxicity associated with higher concentrations of soluble peptides. The studies discussed in the current review report on the impact of covalent immobilization of AMPs onto surfaces through different chemical coupling strategies, length of spacers, and peptide orientation and concentration. The overall results suggest that immobilized AMPs may be effective in the prevention of biofilm formation by reduction of microorganism survival post-contact with the coated biomaterial. Minimal cytotoxicity and long-term stability profiles were obtained by optimizing immobilization parameters, indicating a promising potential for the use of immobilized AMPs in clinical applications. On the other hand, the effects of tethering on mechanisms of action of AMPs have not yet been fully elucidated. Therefore, further studies are recommended to explore the real potential of immobilized AMPs in health applications as antimicrobial coatings of medical devices. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 24Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2010.11.005PubMed ID: 21056701Language of Original Document: EnglishCorrespondence Address: Martins, M. C. L.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: amoxicillin, 26787-78-0, 34642-77-8, 61336-70-7; ampicillin, 69-52-3, 69-53-4, 7177-48-2, 74083-13-9, 94586-58-0; carbenicillin, 17230-86-3, 4697-36-3, 4800-94-6; cefazolin, 25953-19-9, 27164-46-1; gentamicin, 1392-48-9, 1403-66-3, 1405-41-0; penicillin G, 1406-05-9, 61-33-6; teicoplanin, 61036-62-2, 61036-64-4; tobramycin, 32986-56-4; vancomycin, 1404-90-6, 1404-93-9; Antimicrobial Cationic Peptides; Biocompatible Materials; Coated Materials, Biocompatible; Immobilized ProteinsReferences: Glinel, K., Jonas, A.M., Jouenne, T., Leprince, J., Galas, L., Huck, W.T., Antibacterial and antifouling polymer brushes incorporating antimicrobial peptide (2009) Bioconj Chem, 20 (1), pp. 71-77;Vila, J., Soriano, A., Mensa, J., Molecular basis of microbial adherence to prosthetic materials. Role of biofilms in prosthesis-associated infection (2008) Enferm Infecc Microbiol Clin, 26 (1), pp. 48-54; Hetrick, E.M., Schoenfisch, M.H., Reducing implant-related infections: Active release strategies (2006) Chemical Society Reviews, 35 (9), pp. 780-789. , DOI 10.1039/b515219b; Darouiche, R.O., Treatment of Infections Associated with Surgical Implants (2004) New England Journal of Medicine, 350 (14), pp. 1422-1429. , DOI 10.1056/NEJMra035415; Zhao, L., Chu, P.K., Zhang, Y., Wu, Z., Antibacterial coatings on titanium implants (2009) J Biomed Mater Res B Appl Biomater, 91 (1), pp. 470-480; Dee, K.C., Puleo, D.A., Bizios, R., (2002) An Introduction to Tissue-biomaterial Interactions, , Wiley-Liss New York; Subramani, K., Jung, R.E., Molenberg, A., Hammerle, C.H., Biofilm on dental implants: A review of the literature (2009) Int J Oral Maxillofac Implants, 24 (4), pp. 616-626; Fey, P.D., Olson, M.E., Current concepts in biofilm formation of Staphylococcus epidermidis (2010) Future Microbiol, 5 (6), pp. 917-933; De Carvalho, C.C., Biofilms: Recent developments on an old battle (2007) Recent Pat Biotechnol, 1 (1), pp. 49-57; Costerton, J.W., Stewart, P.S., Greenberg, E.P., Bacterial biofilms: A common cause of persistent infections (1999) Science, 284 (5418), pp. 1318-1322. , DOI 10.1126/science.284.5418.1318; Willcox, M.D., Hume, E.B., Aliwarga, Y., Kumar, N., Cole, N., A novel cationic-peptide coating for the prevention of microbial colonization on contact lenses (2008) J Appl Microbiol, 105 (6), pp. 1817-1825; Lewis, K., Riddle of biofilm resistance (2001) Antimicrobial Agents and Chemotherapy, 45 (4), pp. 999-1007. , DOI 10.1128/AAC.45.4.999-1007.2001; Monteiro, D.R., Gorup, L.F., Takamiya, A.S., Ruvollo-Filho, A.C., De Camargo, E.R., Barbosa, D.B., The growing importance of materials that prevent microbial adhesion: Antimicrobial effect of medical devices containing silver (2009) Int J Antimicrob Agents, 34 (2), pp. 103-110; Gooderham, W.J., Bains, M., McPhee, J.B., Wiegand, I., Hancock, R.E., Induction by cationic antimicrobial peptides and involvement in intrinsic polymyxin and antimicrobial peptide resistance, biofilm formation, and swarming motility of PsrA in Pseudomonas aeruginosa (2008) J Bacteriol, 190 (16), pp. 5624-5634; Bagge, N., Schuster, M., Hentzer, M., Ciofu, O., Givskov, M., Greenberg, E.P., Hoiby, N., Pseudomonas aeruginosa Biofilms Exposed to Imipenem Exhibit Changes in Global Gene Expression and β-Lactamase and Alginate Production (2004) Antimicrobial Agents and Chemotherapy, 48 (4), pp. 1175-1187. , DOI 10.1128/AAC.48.4.1175-1187.2004; Ahmed, N.A., Petersen, F.C., Scheie, A.A., AI-2/LuxS is involved in increased biofilm formation by Streptococcus intermedius in the presence of antibiotics (2009) Antimicrob Agents Chemother, 53 (10), pp. 4258-4263; Hoffman, L.R., D'Argenio, D.A., MacCoss, M.J., Zhang, Z., Jones, R.A., Miller, S.I., Aminoglycoside antibiotics induce bacterial biofilm formation (2005) Nature, 436 (7054), pp. 1171-1175. , DOI 10.1038/nature03912; Harbers, G.M., Emoto, K., Greef, C., Metzger, S.W., Woodward, H.N., Mascali, J.J., Grainger, D.W., Lochhead, M.J., Functionalized poly(ethylene glycol)-based bioassay surface chemistry that facilitates bio-immobilization and inhibits nonspecific protein, bacterial, and mammalian cell adhesion (2007) Chemistry of Materials, 19 (18), pp. 4405-4414. , DOI 10.1021/cm070509u; Chapman, R.G., Ostuni, E., Liang, M.N., Meluleni, G., Kim, E., Yan, L., Pier, G., Whitesides, G.M., Polymeric thin films that resist the adsorption of proteins and the adhesion of bacteria (2001) Langmuir, 17 (4), pp. 1225-1233. , DOI 10.1021/la001222d; Goncalves, I.C., Martins, M.C., Barbosa, M.A., Naeemi, E., Ratner, B.D., Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands (2009) J Biomed Mater Res A, 89 (3), pp. 642-653; Chung, D., Papadakis, S.E., Yam, K.L., Evaluation of a polymer coating containing triclosan as the antimicrobial layer for packaging materials (2003) International Journal of Food Science and Technology, 38 (2), pp. 165-169. , DOI 10.1046/j.1365-2621.2003.00657.x; Leung, D., Spratt, D.A., Pratten, J., Gulabivala, K., Mordan, N.J., Young, A.M., Chlorhexidine-releasing methacrylate dental composite materials (2005) Biomaterials, 26 (34), pp. 7145-7153. , DOI 10.1016/j.biomaterials.2005.05.014, PII S0142961205003881; Ravikumar, T., Murata, H., Koepsel, R.R., Russell, A.J., Surface-active antifungal polyquaternary amine (2006) Biomacromolecules, 7 (10), pp. 2762-2769. , DOI 10.1021/bm060476w; Bach, A., Darby, D., Bottiger, B., Bohrer, H., Motsch, J., Martin, E., Retention of the antibiotic teicoplanin on a hydromer-coated central venous catheter to prevent bacterial colonization in postoperative surgical patients (1996) Intensive Care Medicine, 22 (10), pp. 1066-1069. , DOI 10.1007/s001340050214; Jose, B., Antoci Jr., V., Zeiger, A.R., Wickstrom, E., Hickok, N.J., Vancomycin covalently bonded to titanium beads kills Staphylococcus aureus (2005) Chemistry and Biology, 12 (9), pp. 1041-1048. , DOI 10.1016/j.chembiol.2005.06.013, PII S1074552105002309; Kilic, D., Agalar, C., Ozturk, E., Denkbas, E.B., Cime, A., Agalar, F., Antimicrobial activity of cefazolin-impregnated mesh grafts (2007) ANZ Journal of Surgery, 77 (4), pp. 256-260. , DOI 10.1111/j.1445-2197.2007.04029.x; Gallardo-Moreno, A.M., Pacha-Olivenza, M.A., Saldana, L., Perez-Giraldo, C., Bruque, J.M., Vilaboa, N., In vitro biocompatibility and bacterial adhesion of physico-chemically modified Ti6Al4V surface by means of UV irradiation (2009) Acta Biomater, 5 (1), pp. 181-192; Jansen, B., Kohnen, W., Prevention of biofilm formation by polymer modification (1995) Journal of Industrial Microbiology, 15 (4), pp. 391-396. , DOI 10.1007/BF01569996; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., Albumin and fibrinogen adsorption on Cibacron blue F3G-A immobilised onto PU-PHEMA (polyurethane-poly (hydroxyethylmethacrylate)) surfaces (2003) Journal of Biomaterials Science, Polymer Edition, 14 (5), pp. 439-455. , DOI 10.1163/156856203766652057; Zhang, F., Zhang, Z., Zhu, X., Kang, E.T., Neoh, K.G., Silk-functionalized titanium surfaces for enhancing osteoblast functions and reducing bacterial adhesion (2008) Biomaterials, 29 (36), pp. 4751-4759; Flemming, R.G., Capelli, C.C., Cooper, S.L., Proctor, R.A., Bacterial colonization of functionalized polyurethanes (2000) Biomaterials, 21 (3), pp. 273-281; Singla, A.K., Chawla, M., Chitosan: Some pharmaceutical and biological aspects - An update (2001) Journal of Pharmacy and Pharmacology, 53 (8), pp. 1047-1067. , DOI 10.1211/0022357011776441; Murata, H., Koepsel, R.R., Matyjaszewski, K., Russell, A.J., Permanent, non-leaching antibacterial surfaces-2: How high density cationic surfaces kill bacterial cells (2007) Biomaterials, 28 (32), pp. 4870-4879. , DOI 10.1016/j.biomaterials.2007.06.012, PII S0142961207004681; Aumsuwan, N., Danyus, R.C., Heinhorst, S., Urban, M.W., Attachment of ampicillin to expanded poly(tetrafluoroethylene): Surface reactions leading to inhibition of microbial growth (2008) Biomacromolecules, 9 (7), pp. 1712-1718; Cevher, E., Orhan, Z., Mulazimoglu, L., Sensoy, D., Alper, M., Yildiz, A., Characterization of biodegradable chitosan microspheres containing vancomycin and treatment of experimental osteomyelitis caused by methicillin-resistant Staphylococcus aureus with prepared microspheres (2006) Int J Pharm, 317 (2), pp. 127-135; Faber, C., Stallmann, H.P., Lyaruu, D.M., Joosten, U., Von Eiff, C., Van Nieuw Amerongen, A., Wuisman, P.I.J.M., Comparable efficacies of the antimicrobial peptide human lactoferrin 1-11 and gentamicin in a chronic methicillin-resistant Staphylococcus aureus osteomyelitis model (2005) Antimicrobial Agents and Chemotherapy, 49 (6), pp. 2438-2444. , DOI 10.1128/AAC.49.6.2438-2444.2005; Aumsuwan, N., Heinhorst, S., Urban, M.W., Antibacterial surfaces on expanded polytetrafluoroethylene; penicillin attachment (2007) Biomacromolecules, 8 (2), pp. 713-718. , DOI 10.1021/bm061050k; Palumbi, S.R., Humans as the world's greatest evolutionary force (2001) Science, 293 (5536), pp. 1786-1790. , DOI 10.1126/science.293.5536.1786; Andreu, D., Rivas, L., Animal antimicrobial peptides: An overview (1998) Biopolymers, 47 (6), pp. 415-433; Rivas, L., Luque-Ortega, J.R., Andreu, D., Amphibian antimicrobial peptides and Protozoa: Lessons from parasites (2009) Biochim Biophys Acta, 1788 (8), pp. 1570-1581; Gordon, Y.J., Romanowski, E.G., McDermott, A.M., Mini review: A review of antimicrobial peptides and their therapeutic potential as anti-infective drugs (2005) Current Eye Research, 30 (7), pp. 505-515. , DOI 10.1080/02713680590968637; Guani-Guerra, E., Santos-Mendoza, T., Lugo-Reyes, S.O., Teran, L.M., Antimicrobial peptides: General overview and clinical implications in human health and disease (2010) Clin Immunol, 135 (1), pp. 1-11; Perron, G.G., Zasloff, M., Bell, G., Experimental evolution of resistance to an antimicrobial peptide (2006) Proceedings of the Royal Society B: Biological Sciences, 273 (1583), pp. 251-256. , DOI 10.1098/rspb.2005.3301; Reddy, K.V.R., Yedery, R.D., Aranha, C., Antimicrobial peptides: Premises and promises (2004) International Journal of Antimicrobial Agents, 24 (6), pp. 536-547. , DOI 10.1016/j.ijantimicag.2004.09.005, PII S092485790400322X; Van 'T Hof, W., Veerman, E.C.I., Heimerhorst, E.J., Nieuw Amerongen, A.V., Antimicrobial peptides: Properties and applicability (2001) Biological Chemistry, 382 (4), pp. 597-619. , DOI 10.1515/BC.2001.072; Li, M., Cha, D.J., Lai, Y., Villaruz, A.E., Sturdevant, D.E., Otto, M., The antimicrobial peptide-sensing system aps of Staphylococcus aureus (2007) Molecular Microbiology, 66 (5), pp. 1136-1147. , DOI 10.1111/j.1365-2958.2007.05986.x; Li, M., Lai, Y., Villaruz, A.E., Cha, D.J., Sturdevant, D.E., Otto, M., Gram-positive three-component antimicrobial peptide-sensing system (2007) Proceedings of the National Academy of Sciences of the United States of America, 104 (22), pp. 9469-9474. , DOI 10.1073/pnas.0702159104; Otto, M., Bacterial sensing of antimicrobial peptides (2009) Contrib Microbiol, 16, pp. 136-149; Peschel, A., Vincent Collins, L., Staphylococcal resistance to antimicrobial peptides of mammalian and bacterial origin (2001) Peptides, 22 (10), pp. 1651-1659. , DOI 10.1016/S0196-9781(01)00500-9, PII S0196978101005009; Peschel, A., Jack, R.W., Otto, M., Collins, L.V., Staubitz, P., Nicholson, G., Kalbacher, H., Van Strijp, J.A.G., Staphylococcus aureus resistance to human defensins and evasion of neutrophil killing via the novel virulence factor MprF is based on modification of membrane lipids with L-lysine (2001) Journal of Experimental Medicine, 193 (9), pp. 1067-1076. , DOI 10.1084/jem.193.9.1067; Cao, M., Helmann, J.D., The Bacillus subtilis Extracytoplasmic-Function σ X Factor Regulates Modification of the Cell Envelope and Resistance to Cationic Antimicrobial Peptides (2004) Journal of Bacteriology, 186 (4), pp. 1136-1146. , DOI 10.1128/JB.186.4.1136-1146.2004; Clarke, S.R., Foster, S.J., IsdA protects Staphylococcus aureus against the bactericidal protease activity of apolactoferrin (2008) Infection and Immunity, 76 (4), pp. 1518-1526. , DOI 10.1128/IAI.01530-07; Vuong, C., Voyich, J.M., Fischer, E.R., Braughton, K.R., Whitney, A.R., DeLeo, F.R., Otto, M., Polysaccharide intercellular adhesin (PIA) protects Staphylococcus epidermidis against major components of the human innate immune system (2004) Cellular Microbiology, 6 (3), pp. 269-275. , DOI 10.1046/j.1462-5822.2004.00367.x; Zasloff, M., Antimicrobial peptides of multicellular organisms (2002) Nature, 415 (6870), pp. 389-395. , DOI 10.1038/415389a; Hancock, R.E.W., Peptide antibiotics (1997) Lancet, 349 (9049), pp. 418-422. , DOI 10.1016/S0140-6736(97)80051-7; Cho, W.-M., Joshi, B.P., Cho, H., Lee, K.-H., Design and synthesis of novel antibacterial peptide-resin conjugates (2007) Bioorganic and Medicinal Chemistry Letters, 17 (21), pp. 5772-5776. , DOI 10.1016/j.bmcl.2007.08.056, PII S0960894X0701013X; Statz, A.R., Park, J.P., Chongsiriwatana, N.P., Barron, A.E., Messersmith, P.B., Surface-immobilised antimicrobial peptoids (2008) Biofouling, 24 (6), pp. 439-448; Deslouches, B., Gonzalez, I.A., DeAlmeida, D., Islam, K., Steele, C., Montelaro, R.C., Mietzner, T.A., De novo-derived cationic antimicrobial peptide activity in a murine model of Pseudomonas aeruginosa bacteraemia (2007) Journal of Antimicrobial Chemotherapy, 60 (3), pp. 669-672. , DOI 10.1093/jac/dkm253; Novak, K.F., Diamond, W.J., Kirakodu, S., Peyyala, R., Anderson, K.W., Montelaro, R.C., Mietzner, T.A., Efficacy of the de novo-derived antimicrobial peptide WLBU2 against oral bacteria (2007) Antimicrobial Agents and Chemotherapy, 51 (5), pp. 1837-1839. , DOI 10.1128/AAC.00924-06; Deslouches, B., Islam, K., Craigo, J.K., Paranjape, S.M., Montelaro, R.C., Mietzner, T.A., Activity of the de novo engineered antimicrobial peptide WLBU2 against Pseudomonas aeruginosa in human serum and whole blood: Implications for systemic applications (2005) Antimicrobial Agents and Chemotherapy, 49 (8), pp. 3208-3216. , DOI 10.1128/AAC.49.8.3208-3216.2005; Deslouches, B., Phadke, S.M., Lazarevic, V., Cascio, M., Islam, K., Montelaro, R.C., Mietzner, T.A., De novo generation of cationic antimicrobial peptides: Influence of length and tryptophan substitution on antimicrobial activity (2005) Antimicrobial Agents and Chemotherapy, 49 (1), pp. 316-322. , DOI 10.1128/AAC.49.1.316-322.2005; Levin, M., Quint, P.A., Goldstein, B., Barton, P., Bradley, J.S., Shemie, S.D., Recombinant bactericidal/permeability-increasing protein (rBPI21) as adjunctive treatment for children with severe meningococcal sepsis: A randomised trial. rBPI21 Meningococcal Sepsis Study Group (2000) Lancet, 356 (9234), pp. 961-967; Giroir, B.P., Scannon, P.J., Levin, M., Bactericidal/permeability-increasing protein-lessons learned from the phase III, randomized, clinical trial of rBPI21 for adjunctive treatment of children with severe meningococcemia (2001) Crit Care Med, 29 (7 SUPPL.), pp. 130-135; Brogden, K.A., Antimicrobial peptides: Pore formers or metabolic inhibitors in bacteria? (2005) Nature Reviews Microbiology, 3 (3), pp. 238-250. , DOI 10.1038/nrmicro1098; Bastos, M., Bai, G., Gomes, P., Andreu, D., Goormaghtigh, E., Prieto, M., Energetics and partition of two cecropin-melittin hybrid peptides to model membranes of different composition (2008) Biophys J, 94 (6), pp. 2128-2141; Melo, M.N., Ferre, R., Castanho, M.A., Antimicrobial peptides: Linking partition, activity and high membrane-bound concentrations (2009) Nat Rev Microbiol, 7 (3), pp. 245-250; Haynie, S.L., Crum, G.A., Doele, B.A., Antimicrobial activities of amphiphilic peptides covalently bonded to a water-insoluble resin (1995) Antimicrob Agents Chemother, 39 (2), pp. 301-307; Humblot, V., Yala, J.F., Thebault, P., Boukerma, K., Hequet, A., Berjeaud, J.M., The antibacterial activity of Magainin i immobilized onto mixed thiols self-assembled monolayers (2009) Biomaterials, 30 (21), pp. 3503-3512; Bagheri, M., Beyermann, M., Dathe, M., Immobilization reduces the activity of surface-bound cationic antimicrobial peptides with no influence upon the activity spectrum (2009) Antimicrob Agents Chemother, 53 (3), pp. 1132-1141; Gabriel, M., Nazmi, K., Veerman, E.C., Nieuw Amerongen, A.V., Zentner, A., Preparation of LL-37-grafted titanium surfaces with bactericidal activity (2006) Bioconj Chem, 17 (2), pp. 548-550; Hilpert, K., Elliott, M., Jenssen, H., Kindrachuk, J., Fjell, C.D., Korner, J., Screening and characterization of surface-tethered cationic peptides for antimicrobial activity (2009) Chem Biol, 16 (1), pp. 58-69; Batista, M.K.S., Gallemi, M., Adeva, A., Gomes, C.A.R., Gomes, P., Facile regioselective synthesis of a novel chitosan-pexiganan conjugate with potential interest for the treatment of infected skin lesions (2009) Synthetic Commun, 39 (7), pp. 1228-1240; Venter, J.C., Immobilized and insolubilized drugs, hormones, and neurotransmitters: Properties, mechanisms of action and applications (1982) Pharmacological Reviews, 34 (2), pp. 153-187; Endo, Y., Tani, T., Kodama, M., Antimicrobial activity of tertiary amine covalently bonded to a polystyrene fiber (1987) Appl Environ Microbiol, 53 (9), pp. 2050-2055; Chuang, H.F., Shukla, A., Loose, C.R., Hammond-Cunningham, P.T., Stephanopoulos, G., (2009) Structures Including Antimicrobial Peptides, , United States; Chen, R., Cole, N., Willcox, M.D., Park, J., Rasul, R., Carter, E., Synthesis, characterization and in vitro activity of a surface-attached antimicrobial cationic peptide (2009) Biofouling, 25 (6), pp. 517-524; Steven, M.D., Hotchkiss, J.H., Covalent immobilization of an antimicrobial peptide on poly(ethylene) film (2008) J Appl Polym Sci, 110 (5), pp. 2665-2670; Appendini, P., Hotchkiss, J.H., Surface modification of poly(styrene) by the attachment of an antimicrobial peptide (2001) J Appl Polym Sci, 81 (3), pp. 609-616; Fields, G.B., Noble, R.L., Solid phase peptide synthesis utilizing 9-fluorenylmethoxycarbonyl amino acids (1990) International Journal of Peptide and Protein Research, 35 (3), pp. 161-214; Rostovtsev, V.V., Green, L.G., Fokin, V.V., Sharpless, K.B., A stepwise huisgen cycloaddition process: Copper(I)-catalyzed regioselective "ligation" of azides and terminal alkynes (2002) Angewandte Chemie - International Edition, 41 (14), pp. 2596-2599. , DOI 10.1002/1521-3773(20020715)41: 14<2596::AID-ANIE2596>3.0.CO;2-4; Abad, J.M., Velez, M., Santamaria, C., Guisan, J.M., Matheus, P.R., Vazquez, L., Gazaryan, I., Fernandez, V.M., Immobilization of peroxidase glycoprotein on gold electrodes modified with mixed epoxy-boronic acid monolayers (2002) Journal of the American Chemical Society, 124 (43), pp. 12845-12853. , DOI 10.1021/ja026658p; Lee, M.-R., Shin, I., Fabrication of chemical microarrays by efficient immobilization of hydrazide-linked substances on epoxide-coated glass surfaces (2005) Angewandte Chemie - International Edition, 44 (19), pp. 2881-2884. , DOI 10.1002/anie.200462720; Hudalla, G.A., Murphy, W.L., Immobilization of peptides with distinct biological activities onto stem cell culture substrates using orthogonal chemistries (2010) Langmuir, 26 (9), pp. 6449-6456; Cole, N., Hume, E.B., Vijay, A.K., Sankaridurg, P., Kumar, N., Willcox, M.D., In vivo performance of melimine as an antimicrobial coating for contact lenses in models of CLARE and CLPU (2010) Invest Ophthalmol Vis Sci, 51 (1), pp. 390-395
Keywords: Amino Acid Sequence; amoxicillin; ampicillin; Animals; antibiotic agent; antibiotic resistance; Antimicrobial Cationic Peptides; Antimicrobial peptides; Bacteria (microorganisms); Bacterial adhesion; bacterial survival; Biocompatible Materials; biofilm; Biofilms; biomaterial; carbenicillin; cefazolin; Coated Materials, Biocompatible; Cytotoxicity; drug activity; drug half life; drug solubility; drug stability; drug targeting; gentamicin; human; Humans; Immobilized Proteins; Molecular Sequence Data; mouth inflammation; Nanostructured surfaces; nonhuman; penicillin G; polypeptide antibiotic agent; priority journal; review; sepsis; skin infection; soft tissue infection; Surface functionalization; Surface Properties; teicoplanin; tobramycin; vancomycin

Gene delivery into mesenchymal stem cells: A biomimetic approach using rgd nanoclusters based on poly(amidoamine) dendrimers - Pandita, D.; Santos, J.L.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (BiomacromoleculesBiomacromolecules, 2011)
Poly(amidoamine) dendrimers (generations 5 and 6) with amine termini were conjugated with peptides containing the arginine-glycine-aspartic acid (RGD) sequence having in view their application as gene delivery vectors. The idea behind the work was to take advantage of the cationic nature of dendrimers and of the integrin targeting capabilities of the RGD motif to improve gene delivery. Dendrimers were used as scaffolds for RGD clustering and, by controlling the number of peptides (4, 8, and 16) linked to each dendrimer, it was possible to evaluate the effect of RGD density on the gene delivery process. The new vectors were characterized in respect to their ability to neutralize and compact plasmid DNA (pDNA). The complexes formed by the vectors and pDNA were studied concerning their size, zeta potential, capacity of being internalized by cells and ability of transferring genes. Transfection efficiency was analyzed, first, by using a pDNA encoding for Enhanced Green Fluorescent Protein and Firefly Luciferase and, second, by using a pDNA encoding for Bone Morphogenetic Protein-2. Gene expression in mesenchymal stem cells was enhanced using the new vectors in comparison to native dendrimers and was shown to be dependent on the electrostatic interaction established between the dendrimer moiety and the cell surface, as well as on the RGD density of nanoclusters. The use of dendrimer scaffolds for RGD cluster formation is a new approach that can be extended beyond gene delivery applications, whenever RGD clustering is important for modulating cellular responses. © 2011 American Chemical Society.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm1012647PubMed ID: 21210673Language of Original Document: EnglishCorrespondence Address: Tomás, H.; CQM-Centro de Química da Madeira, MMRG, Universidade da Madeira, 9000-390 Funchal, Portugal; email: lenat@uma.ptChemicals/CAS: arginylglycylaspartic acid, 99896-85-2; firefly luciferase, 61970-00-1; Dendrimers; Oligopeptides; Poly(amidoamine); Polyamines; arginyl-glycyl-aspartic acid, 99896-85-2References: Pierschbacher, M.D., Ruoslahti, E., (1984) Nature, 309, pp. 30-33;Ruoslahti, E., (1996) Annu. Rev. Cell Dev. Biol., 12, pp. 697-715; Schaffn, P., Dard, M.M., (2003) Cell. Mol. Life Sci., 60, pp. 119-132; Arosio, D., Manzoni, L., Araldi, E.M.V., Caprini, A., Monferini, E., Scolastico, C., (2009) Bioconjugate Chem., 20, pp. 1611-1617; Cai, W., Chen, X., (2008) Nat. Protoc., 3, pp. 89-96; Cai, W., Wu, Y., Chen, K., Cao, Q., Tice, D.A., Chen, X., (2006) Cancer Res., 66, pp. 9673-9681; Gaillard, C., Cellot, G., Li, S., Toma, F.M., Dumortier, H., Spalluto, G., Cacciari, B., Bianco, A., (2009) Adv. Mater., 21, pp. 1-6; Green, J.J., Chiu, E., Leshchiner, E.S., Shi, J., Langer, R., Anderson, D.G., (2007) Nano Lett., 7, pp. 874-879; Hwang, D.S., Sim, S.B., Cha, H.J., (2007) Biomaterials, 28, pp. 4039-4046; Irvine, D.J., Mayes, A.M., Griffith, L.G., (2001) Biomacromolecules, 2, pp. 85-94; Kong, H.J., Hsiong, S., Mooney, D.J., (2007) Nano Lett., 7, pp. 161-166; Lesniak, W.G., Kariapper, M.S., Nair, B.M., Tan, W., Hutson, A., Balogh, L.P., Khan, M.K., (2007) Bioconjugate Chem., 18, pp. 1148-1154; Ng, Q.K., Sutton, M.K., Soonsawad, P., Xing, L., Cheng, H., Segura, T., (2009) Mol. Ther., 17, pp. 828-836; Suk, J.S., Suh, J., Choy, K., Lai, S.K., Fu, J., Hanes, J., (2006) Biomaterials, 27, pp. 5143-5150; Sun, Y.X., Zeng, X., Meng, Q.F., Zhang, X.Z., Cheng, S.X., Zhuo, R.X., (2008) Biomaterials, 29, pp. 4356-4365; Yang, H., Kao, W.J., (2007) Int. J. Nanomed., 2, pp. 89-99; Yoshimoto, M., Ogawa, K., Washiyama, K., Shikano, N., Mori, H., Amano, R., Kawai, K., (2008) Int. J. Cancer, 123, pp. 709-715; Bidarra, S.J., Barrias, C.C., Barbosa, M.A., Soares, R., Granja, P.L., (2010) Biomacromolecules, 11, pp. 1956-1964; Grellier, M., Granja, P.L., Fricain, J.-C., Bidarra, S.J., Renard, M., Bareille, R., Bourget, C., Barbosa, M.A., (2009) Biomaterials, 30, pp. 3271-8; Evangelista, M.B., Hsiong, S., Fernandes, R., Sampaio, P., Kong, H.J., Barrias, C.C., Salema, R., Granja, P.L., (2007) Biomaterials, 28, pp. 3644-55; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., (2001) J. Dental Res., 80, pp. 2025-9; Rowley, J.A., Madlambayan, G., Mooney, D.J., (1999) Biomaterials, 20, pp. 45-53; Hynes, R.O., (2002) Cell, 110, pp. 673-687; Qin, J., Vinogradova, O., Plow, E.F., (2004) PLoS Biol., 2, pp. e169; Medina-Kauwe, L.K., (2003) Adv. Drug Delivery Rev., 55, pp. 1485-1496; Stewart, P.L., Chiu, C.Y., Huang, S., Muir, T., Zhao, Y., Chait, B., Mathias, P., Nemerow, G.R., (1997) EMBO J., 16, pp. 1189-1198; Dufès, C., Uchegbu, I.F., Schätzlein, A.G., (2005) Adv. Drug Delivery Rev., 57, pp. 2177-2202; Mintzer, M.A., Simanek, E.E., (2009) Chem. Rev., 109, pp. 259-302; Smith, D.K., (2008) Curr. Top. Med. Chem., 8, pp. 1187-1203; Svenson, S., Tomalia, D.A., (2005) Adv. Drug Delivery Rev., 57, pp. 2106-2129; Dennig, J., Duncan, E., (2002) J. Biotechnol., 90, pp. 339-347; Sokolova, V.V., Radtke, I., Heumann, R., Epple, M., (2006) Biomaterials, 27, pp. 3147-3153; Kukowska-Latallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker Jr., J.R., (1996) Proc. Natl. Acad. Sci. U.S.A., 93, pp. 4897-4902; Santos, J.L., Oramas, E., Pêgo, A.P., Granja, P.L., Tomás, H., (2009) J. Controlled Release, 134, pp. 141-148; Prockop, D.J., (2009) Mol. Ther., 17, pp. 939-946; Väänänen, H.K., (2005) Ann. Med., 37, pp. 469-479; Gronthos, S., Simmons, P.J., Graves, S.E., Robey, P.G., (2001) Bone, 28, pp. 174-181; Snyder, S.L., Sobocinski, P.Z., (1975) Anal. Biochem., 64, pp. 284-288; Haensler, J., Szoka Jr., F.C., (1993) Bioconjugate Chem, 4, pp. 372-379; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., (1985) Anal. Biochem., 150, pp. 76-85; Perrot, S., Dutertre-Catella, H., Martin, C., Rat, P., Warnet, J.M., (2003) Toxicol. Sci., 72, pp. 122-129; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Hiraoka, Y., Inoue, S., Shimokawa, H., Tabata, Y., (2006) Biomaterials, 27, pp. 1387-1398; Zhang, S., Li, J., Lykotrafitis, G., Bao, G., Suresh, S., (2009) Adv. Mater., 21, pp. 419-424; Tang, M.X., Szoka, F.C., (1997) Gene Ther., 4, pp. 823-32; Santos, J.L., Pandita, D., Rodrigues, J., Pêgo, A.P., Granja, P.L., Balian, G., Tomás, H., (2010) Mol. Pharm., 7, pp. 763-774; Santos, J.L., Oliveira, H., Pandita, D., Rodrigues, J., Pêgo, A.P., Granja, P.L., Tomás, H., (2010) J. Controlled Release, 144, pp. 55-64; Kunath, K., Merdan, T., Hegener, O., Häberlein, H., Kissel, T., (2003) J. Gene Med., 5, pp. 588-599; Lechardeur, D., Verkman, A.S., Lukacs, G.L., (2005) Adv. Drug Delivery Rev., 57, pp. 755-767; Ryoo, H.M., Lee, M.H., Kim, Y.J., (2006) Gene, 366, pp. 51-57
Keywords: Amino Acid Sequence; Amino acids; animal cell; animal experiment; Animals; Arginine-glycine-aspartic acids; arginylglycylaspartic acid; article; Biomimetics; bone morphogenetic protein 2; Bone morphogenetic protein-2; Cell culture; Cell membranes; cell surface; Cell surfaces; cell survival; Cellular response; Cluster formations; Complexation; controlled study; dendrimer; Dendrimers; Electrostatic interactions; electrostatic precipitation; Encoding (symbols); Enhanced green fluorescent protein; Firefly luciferase; Functional polymers; Gene delivery; Gene delivery vectors; gene expression; gene targeting; Gene therapy; Gene transfer; Gene Transfer Techniques; gene vector; integrin; Integrins; male; Mesenchymal stem cell; Mesenchymal Stem Cells; Molecular Structure; Nanoclusters; Nanostructures; New approaches; nonhuman; Oligopeptides; Organic acids; Peptides; plasmid DNA; Plasmid DNA (pDNA); polyamidoamine; Polyamidoamine dendrimers; Polyamines; priority journal; rat; Rats; Rats, Wistar; RGD motif; Scaffolds; Stem cells; Structure-Activity Relationship; Targeting capability; Transfection efficiency; Vectors; Zeta potential

Interactions of leukocytes and platelets with poly(lysine/leucine) immobilized on tetraethylene glycol-terminated self-assembled monolayers - Martins, M.C.L.; Ochoa-Mendes, V.; Ferreira, G.; Barbosa, J.N.; Curtin, S.A.; Ratner, B.D.; Barbosa, M.A. (Acta BiomaterialiaActa Biomater., 2011)
Surfaces that bind heparin are important for biomaterials for blood deheparinization. In our recent work it was demonstrated that a polypeptide composed of l-lysine and l-leucine (pKL), after immobilization onto tetra(ethylene glycol) terminated self-assembled monolayers (EG4-SAMs), can bind heparin from blood plasma in a selective, concentration-dependent way. During this work the effect of this peptide on platelet adhesion and activation and leukocyte adhesion was studied. The surface charge of these nanostructured surfaces was evaluated in order to correlate the effect of positively charged amine groups and hydrophobic methyl groups on the behavior of platelets and leukocyte adhesion. The results demonstrated that the presence of pKL decreased leukocyte adhesion to EG4-SAMs at all concentrations used. This effect is even more pronounced when surfaces were pre-immersed in heparinized plasma. In contrast, there is an increase in platelet adhesion and activation with increased percentage immobilized pKL. This effect is enhanced when surfaces were pre-immersed in heparinized plasma. However, adsorbed pKL in very low amounts does not induce platelet adhesion and activation compared with EG4, even when pre-immersed in plasma. Since only low pKL amounts are necessary to induce heparin selectivity, these results are promising for the development of heparin-binding biomaterials for blood deheparinization. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2011.01.013PubMed ID: 21237292Language of Original Document: EnglishCorrespondence Address: Martins, M. C. L.; Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; leucine, 61-90-5, 7005-03-0; polylysine, 25104-18-1, 25988-63-0, 33960-24-6, 38000-06-5, 73565-56-7; Ethylene Glycol, 107-21-1; Imidazoles; Immobilized Proteins; N,N-carbonyldiimidazole, 530-62-1; Polyethylene Glycols; Polylysine, 25104-18-1; ProteinsReferences: Dailey, J., (1998) Blood, , 2nd ed. Ipswich (MA, USA): Medical Consulting Group;Section V: Chronic intermittent haemodialysis and prevention of clotting in the extracorporal system (2002) Nephrol Dial Transplant, 17 (SUPPL. 7), pp. 63-71. , European Best Practice Guidelines Working Group; Martins, M.C., Curtin, S.A., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88, pp. 162-173; Love, J.C., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chemical Reviews, 105 (4), pp. 1103-1169. , DOI 10.1021/cr0300789; Cardin, A.D., Weintraub, H.J.R., Molecular modeling of protein-glycosaminoglycan interactions (1989) Arteriosclerosis, 9 (1), pp. 21-32; Prime, K.L., Whitesides, G.M., Adsorption of proteins onto surfaces containing end-attached oligo(ethylene oxide) - A model system using self-assembled monolayers (1993) J Am Chem Soc, 115, pp. 10714-10721; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) Journal of Biomedical Materials Research - Part A, 67 (1), pp. 158-171; Werner, C., Konig, U., Augsburg, A., Arnhold, C., Korber, H., Zimmermann, R., Jacobasch, H.-J., Electrokinetic surface characterization of biomedical polymers - A survey (1999) Colloids and Surfaces A: Physicochemical and Engineering Aspects, 159 (2-3), pp. 519-529. , DOI 10.1016/S0927-7757(99)00290-3, PII S0927775799002903; Frank, R.D., Dresbach, H., Thelen, H., Sieberth, H.-G., Glutardialdehyde induced fluorescence technique (GIFT): A new method for the imaging of platelet adhesion on biomaterials (2000) Journal of Biomedical Materials Research, 52 (2), pp. 374-381. , DOI 10.1002/1097-4636(200011)52:2<374::AID-JBM18>3.0.CO;2-Z; Chan, Y.H.M., Schweiss, R., Werner, C., Grunze, M., Electrokinetic characterization of oligo- and poly(ethylene glycol)-terminated self-assembled monolayers on gold and glass surfaces (2003) Langmuir, 19, pp. 7380-7385; Schweiss, R., Welzel, P.B., Werner, C., Knoll, W., Dissociation of surface functional groups and preferential adsorption of ions on self-assembled monolayers assessed by streaming potential and streaming current measurements (2001) Langmuir, 17 (14), pp. 4304-4311. , DOI 10.1021/la001741g; Rodrigues, S.N., Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27 (31), pp. 5357-5367. , DOI 10.1016/j.biomaterials.2006.06.010, PII S0142961206005515; Goncalves, I.C., Martins, M.C., Barbosa, M.A., Naeemi, E., Ratner, B.D., Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands (2009) J Biomed Mater Res, 89 A, pp. 642-653; Prime, K.L., Whitesides, G.M., Self-assembled organic monolayers: Model systems for studying adsorption of proteins at surfaces (1991) Science, 252 (5009), pp. 1164-1167; Mrksich, M., Using self-assembled monolayers to model the extracellular matrix (2009) Acta Biomater, 5, pp. 832-841; Sagnella, S., Mai-Ngam, K., Chitosan based surfactant polymers designed to improve blood compatibility on biomaterials (2005) Colloids Surf B Biointerfaces, 42, pp. 147-155; Chuang, W.H., Lin, J.C., Surface characterization and platelet adhesion studies for the mixed self-assembled monolayers with amine and carboxylic acid terminated functionalities (2007) J Biomed Mater Res A, 82, pp. 820-830; Chen, S., Yu, F., Yu, Q., He, Y., Jiang, S., Strong resistance of a thin crystalline layer of balanced charged groups to protein adsorption (2006) Langmuir, 22 (19), pp. 8186-8191. , DOI 10.1021/la061012m; Chen, S.F., Jiang, S.Y., A new avenue to nonfouling materials (2008) Adv Mater, 20, p. 335; Li, D., Chen, H., Glenn McClung, W., Brash, J.L., Lysine-PEG-modified polyurethane as a fibrinolytic surface. effect of PEG chain length on protein interactions, platelet interactions and clot lysis (2009) Acta Biomater, 5, pp. 1864-1871; Tsai, W.-B., Grunkemeier, J.M., Horbett, T.A., Variations in the ability of adsorbed fibrinogen to mediate platelet adhesion to polystyrene-based materials: A multivariate statistical analysis of antibody binding to the platelet binding sites of fibrinogen (2003) Journal of Biomedical Materials Research - Part A, 67 (4), pp. 1255-1268; Weisel, J.W., Nagaswami, C., Vilaire, G., Bennett, J.S., Examination of the platelet membrane glycoprotein IIb-IIIa complex and its interaction with fibrinogen and other ligands by electron microscopy (1992) J Biol Chem, 267 (23), pp. 16637-16643; Gorbet, M.B., Sefton, M.V., Biomaterial-associated thrombosis: Roles of coagulation factors, complement, platelets and leukocytes (2004) Biomaterials, 25 (26), pp. 5681-5703. , DOI 10.1016/j.biomaterials.2004.01.023, PII S0142961204000687; Brash, J.L., Tenhove, P., Protein adsorption studies on standard polymeric materials (1993) J Biomater Sci Polym Ed, 4, pp. 591-599; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) Journal of the American Chemical Society, 120 (14), pp. 3464-3473. , DOI 10.1021/ja970819l; Silin, V., Weetall, H., Vanderah, D.J., SPR studies of the nonspecific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) Journal of Colloid and Interface Science, 185 (1), pp. 94-103. , DOI 10.1006/jcis.1996.4586; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (2000) Journal of Biomedical Materials Research, 49 (4), pp. 435-447. , DOI 10.1002/(SICI)1097-4636(20000315)49:4<435::AID-JBM2>3.0.CO;2-Y; Werthen, M., Sellborn, A., Kalltorp, M., Elwing, H., Thomsen, P., In vitro study of monocyte viability during the initial adhesion to albumin- and fibrinogen-coated surfaces (2001) Biomaterials, 22, pp. 827-832; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) Journal of Biomedical Materials Research, 50 (3), pp. 291-301. , DOI 10.1002/(SICI)1097-4636(20000605)50:3<291::AID-JBM2>3.0.CO;2-1; Barbosa, J.N., Martins, M.C.L., Freitas, S.C., Goncalves, I.C., Aguas, A.P., Barbosa, M.A., Adhesion of human leucocytes on mixtures of hydroxyl- and methyl-terminated self-assembled monolayers: Effect of blood protein adsorption (2010) J Biomed Mater Res, 93 A, pp. 12-19; Sperling, C., Schweiss, R.B., Streller, U., Werner, C., In vitro hemocompatibility of self-assembled monolayers displaying various functional groups (2005) Biomaterials, 26, pp. 6547-6557; Toda, M., Kitazawa, T., Hirata, I., Hirano, Y., Iwata, H., Complement activation on surfaces carrying amino groups (2008) Biomaterials, 29 (4), pp. 407-417. , DOI 10.1016/j.biomaterials.2007.10.005, PII S014296120700796X
Keywords: article; Blood Platelets; Cell Communication; Cell Shape; Ethylene Glycol; heparin; heparin binding protein; Humans; hydrophobicity; Imidazoles; Immobilized Proteins; leucine; leukocyte; leukocyte adherence; Leukocytes; methyl group; nanomaterial; plasma; Platelet Adhesiveness; Platelets; Polyethylene Glycols; polylysine; polypeptide; priority journal; Proteins; self assembled monolayer; Self-assembled monolayers; static electricity; Surface charge; Surface Properties; Tetra; thrombocyte; thrombocyte adhesion

Knowledge of adverse neonatal outcome alters clinicians' interpretation of the intrapartum cardiotocograph - Ayres-de-Campos, D.; Arteiro, D.; Costa-Santos, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2011)
Objective: To evaluate the impact of knowledge of neonatal outcome on clinicians' interpretation of the intrapartum cardiotocograph (CTG). Design: Prospective evaluation of pre-recorded cases. Setting: Five maternity hospitals. Population: From a database of intrapartum CTGs acquired with a scalp electrode in singleton near-term fetuses, 20 tracings were sequentially selected from cases with newborn umbilical artery pH < 7.05 and 20 from cases with pH > 7.20. Methods: Five experienced obstetricians practising in different maternity hospitals were asked to analyse the 40 tracings individually, according to the International Federation of Gynaecology and Obstetrics guidelines. In a first round, clinicians were given no information on neonatal outcome. In a second round, carried out 2 months later, clinicians were asked to analyse the same tracings, but the order was randomly altered and information on the newborn's arterial pH was provided. Clinicians were not informed of the purpose of the study or whether the tracings were the same. Main outcome measures: The incidence of individual fetal heart rate feature identification and tracing classification, before and after neonatal outcome was made available. Results: In the group with pH < 7.05, repetitive decelerations and reduced variability were more common in the second round (P < 0.001 and P = 0.001, respectively), as was a pathological classification (P = 0.002); variable decelerations were less common (P = 0.008). In the group with normal pH, less tracings in the second round had prolonged decelerations (P = 0.013) and no accelerations (P = 0.013), but more had pronounced decelerations (P = 0.031) and reduced variability (P = 0.007); there was a reduction in pathological classifications, but this difference failed to reach statistical significance (P = 0.051). Conclusions: A knowledge of adverse neonatal outcome leads to a more severe classification of the intrapartum CTG, which derives mainly from the evaluation of decelerations and variability. © 2011 The Authors BJOG An International Journal of Obstetrics and Gynaecology © 2011 RCOG.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: BIOGFdoi: 10.1111/j.1471-0528.2011.03003.xPubMed ID: 21609381Language of Original Document: EnglishCorrespondence Address: Ayres-de-Campos, D.; Departmento de Ginecologia e Obstetrícia, Faculdade de Medicina do Porto, 4200-309 Porto, Portugal; email: dcampos@med.up.ptReferences: (2006) Perinatal Mortality Surveillance 2004: England, Wales and Northern Ireland, , CEMACH - Centre for Maternal and Child Enquiries (previously Confidential Enquiries into Maternal and Child Health). London: CEMACH;(1997) CESDI - Confidential Enquiry into Stillbirths and Deaths in Infancy, , 4th Annual Report. London: CESDI; Wood, C., Renou, P., Oats, J., A controlled trial of fetal heart rate monitoring in a low-risk obstetric population (1981) American Journal of Obstetrics and Gynecology, 141 (5), pp. 527-534; MacDonald, D., Grant, A., Sheridan-Pereira, M., The Dublin randomized controlled trial of intrapartum fetal heart rate monitoring (1985) American Journal of Obstetrics and Gynecology, 152 (5), pp. 524-539; Shy, K.K., Luthy, D.A., Bennett, F.C., Whitfield, M., Larson, E.B., Van Belle, G., Hughes, J.P., Stenchever, M.A., Effects of electronic fetal-heart-rate monitoring, as compared with periodic auscultation, on the neurologic development of premature infants (1990) New England Journal of Medicine, 322 (9), pp. 588-593; Dillner, L., Babies' deaths linked to suboptimal care (1995) Br Med J, 310, p. 757; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Palomaki, O., Luukkaala, T., Luoto, R., Tuimala, R., Intrapartum cardiotocography - The dilemma of interpretational variation (2006) Journal of Perinatal Medicine, 34 (4), pp. 298-302. , DOI 10.1515/JPM.2006.057, PII JPME344298; Westerhuis, M., Van Horen, E., Kwee, A., Van Der Tweel, I., Visser, G., Moons, K., Inter- and intra-observer agreement of intrapartum ST analysis of the fetal electrocardiogram in women monitored by STAN (2009) BJOG, 116, pp. 545-551; Caplan, R.A., Posner, K.L., Cheney, F.W., Effect of outcome on physician judgment of appropriateness of care (1991) J Am Med Assoc, 265, pp. 1957-1960; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, pp. 159-167. , FIGO News; Amer-Wahlin, I., Hellsten, C., Noren, H., Hagberg, H., Herbst, A., Kjellmer, I., Lilja, H., Marsal, K., Cardiotocography only versus cardiotocography plus ST analysis of fetal electrocardiogram for intrapartum fetal monitoring: A Swedish randomised controlled trial (2001) Lancet, 358 (9281), pp. 534-538. , DOI 10.1016/S0140-6736(01)05703-8; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: A time for quality data (1994) British Journal of Obstetrics and Gynaecology, 101 (12), pp. 1054-1063; Figueras, F., Albela, S., Bonino, S., Palacio, M., Barrau, E., Hernandez, S., Casellas, C., Cararach, V., Visual analysis of antepartum fetal heart rate tracings: Inter- and intra-observer agreement and impact of knowledge of neonatal outcome (2005) Journal of Perinatal Medicine, 33 (3), pp. 241-245. , http://www.extenza-eps.com/extenza/loadPDF?objectIDValue=64432, DOI 10.1515/JPM.2005.044; Zain, H.A., Wright, J.W., Parrish, G.E., Diehl, S.J., Interpreting the fetal heart rate tracing: Effect of knowledge of neonatal outcome (1998) Journal of Reproductive Medicine for the Obstetrician and Gynecologist, 43 (4), pp. 367-370; Almström, H., Axelsson, O., Ekman, G., Ingemarsson, I., Maesel, A., Arström, K., Umbilical artery velocimetry may influence clinical interpretation of intrapartum cardiotocograms (1995) Acta Obstet Gynecol Scand, 74, pp. 526-529; Spencer, J.A.D., Clinical overview of cardiotocography (1993) British Journal of Obstetrics and Gynaecology, Supplement, 100 (9), pp. 4-7; Ayres-de-Campos, D., Bernardes, J., Early, variable and late decelerations: Can a consensus be reached in their identification? (1999) Int J Gynecol Obstet, 65, pp. 305-306; Capstick, J.B., Edwards, P.J., Trends in obstetric malpractice claims (1990) Lancet, 336 (8720), pp. 931-932. , DOI 10.1016/0140-6736(90)92291-O; Symonds, E.M., Litigation and the cardiotocogram (1993) British Journal of Obstetrics and Gynaecology, Supplement, 100 (9), pp. 8-9; Williams, B., Arulkumaran, S., Cardiotocography and medicolegal issues (2004) Best Practice and Research: Clinical Obstetrics and Gynaecology, 18 (3), pp. 457-466. , DOI 10.1016/j.bpobgyn.2004.02.005, PII S1521693404000318
Keywords: adverse outcome; Agreement; article; bradycardia; Cardiotocography; clinical competence; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus heart rate; fetus outcome; health practitioner; Heart rate; Heart Rate, Fetal; human; Humans; Hydrogen-Ion Concentration; incidence; Infant, Newborn; intrapartum care; Labor, Obstetric; medical practice; pH; practice guideline; Practice Guidelines as Topic; Pregnancy; Pregnancy Outcome; priority journal; Prospective Studies; Questionnaires; Reference Standards; Reproducibility of Results; Research Design; Risk Factors; Sweden; tachycardia; umbilical artery

Layer-by-layer self-assembly of chitosan and poly(γ-glutamic acid) into polyelectrolyte complexes - Antunes, J.C.; Pereira, C.L.; Molinos, M.; Ferreira-da-Silva, F.; Dessi, M.; Gloria, A.; Ambrosio, L.; Gonca̧lves, R.M.; Barbosa, M.A. (BiomacromoleculesBiomacromolecules, 2011)
Chitosan (Ch) is a nontoxic and biocompatible polysaccharide extensively used in biomedical applications. Ch, as a polycation, can be combined with anionic polymers by layer-bylayer (LbL) self-assembly, giving rise to multilayered complexed architectures. These structures can be used in tissue engineering strategies, as drug delivery systems, or artificial matrices mimicking the extracellular microenvironment. In this work, Ch was combined with poly(γ-glutamic acid) (γ-PGA). γ-PGA is a polyanion, which was microbially produced, and is known for its low immunogenic reaction and low cytotoxicity. Multilayered ultrathin films were assembled by LbL, with a maximum of six layers. The interaction between both polymers was analyzed by: ellipsometry, quartz crystal microbalance with dissipation, Fourier transform infrared spectroscopy, atomic force microscopy, and zeta potential measurements. Ch/γ-PGA polyelectrolyte multilayers (PEMs) revealed no cytotoxicity according to ISO 10993-5. Overall, this study demonstrates that Ch can interact electrostatically with γ-PGA forming multilayered films. Furthermore, this study provides a comprehensive characterization of Ch/γ-PGA PEM structures, elucidating the contribution of each layer for the nanostructured films. These model surfaces can be useful substrates to study cell-biomaterial interactions in tissue regeneration. © 2011 American Chemical Society.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm2008235PubMed ID: 22032302Language of Original Document: EnglishCorrespondence Address: Antunes, J.C.; INEB - Instituto de Engenharia Biomédica, Porto, Portugal; email: joana.antunes@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; glutamic acid, 11070-68-1, 138-15-8, 56-86-0, 6899-05-4; Biocompatible Materials; Chitosan, 9012-76-4; Electrolytes; Polyglutamic Acid, 25513-46-6; Viscoelastic Substances; poly(gamma-glutamic acid)References: Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., Ultrathin polymer coatings by complexation of polyelectrolytes at interfaces: Suitable materials, structure and properties (2000) Macromol. Rapid Commun., 21, pp. 319-348;Schonhoff, M., Layered polyelectrolyte complexes: Physics of formation and molecular properties (2003) J. Phys.: Condens. Matter, 15, pp. R1781-R1808; Von Klitzing, R., Internal structure of polyelectrolyte multilayer assemblies (2006) Phys. Chem. Chem. Phys., 8, pp. 5012-5033; Iler, R.K., Multilayers of colloidal particles (1966) J. Colloid Interface Sci., 21, pp. 569-594; Zhang, X., Chen, H., Zhang, H., Layer-by-layer assembly: From conventional to unconventional methods (2007) Chemical Communications, (14), pp. 1395-1405. , DOI 10.1039/b615590a; Decher, G., Hong, J.D., Schmitt, J., Buildup of ultrathin multilayer films by a self-assembly process. 3. Consecutively alternating adsorption of anionic and cationic polyelectrolytes on charged surfaces (1992) Thin Solid Films, 210, pp. 831-835; Boudou, T., Crouzier, T., Ren, K.F., Blin, G., Picart, C., Multiple functionalities of polyelectrolyte multilayer films: New biomedical applications (2010) Adv. Mater., 22, pp. 441-467; Schlenoff, J.B., Retrospective on the future of polyelectrolyte multilayers (2009) Langmuir, 25, pp. 14007-14010; Ariga, K., Hill, J.P., Ji, Q.M., Layer-by-layer assembly as a versatile bottom-up nanofabrication technique for exploratory research and realistic application (2007) Phys. Chem. Chem. Phys., 9, pp. 2319-2340; Meng, S., Liu, Z., Shen, L., Guo, Z., Chou, L.L., Zhong, W., Du, Q., Ge, J., The effect of a layer-by-layer chitosan-heparin coating on the endothelialization and coagulation properties of a coronary stent system (2009) Biomaterials, 30, pp. 2276-2283; De Geest, B.G., Jonas, A.M., Demeester, J., De Smedt, S.C., Glucose-responsive polyelectrolyte capsules (2006) Langmuir, 22 (11), pp. 5070-5074. , DOI 10.1021/la053368o; Dimitrova, M., Affolter, C., Meyer, F., Nguyen, I., Richard, D.G., Schuster, C., Bartenschlager, R., Baumert, T.F., Sustained delivery of siRNAs targeting viral infection by celldegradable multilayered polyelectrolyte films (2008) Proc. Natl. Acad. Sci. U.S.A., 105, pp. 16320-16325; Crouzier, T., Ren, K., Nicolas, C., Roy, C., Picart, C., Layer-bylayer films as a biomimetic reservoir for rhBMP-2 delivery: Controlled differentiation of myoblasts to osteoblasts (2009) Small, 5, pp. 598-608; He, L., Dexter, A.F., Middelberg, A.P.J., Biomolecular engineering at interfaces (2006) Chemical Engineering Science, 61 (3), pp. 989-1003. , DOI 10.1016/j.ces.2005.05.064, PII S000925090500518X, Biomolecular Engineering; Chua, P.H., Neoh, K.G., Shi, Z., Kang, E.T., Structural stability and bioapplicability assessment of hyaluronic acid-chitosan polyelectrolyte multilayers on titanium substrates (2008) J. Biomed. Mater. Res., Part A, 87 A, pp. 1061-1074; Decher, G., Fuzzy nanoassemblies: Toward layered polymeric multicomposites (1997) Science, 277 (5330), pp. 1232-1237. , DOI 10.1126/science.277.5330.1232; Ozin, G.A., Hou, K., Lotsch, B.V., Cademartiri, L., Puzzo, D.P., Scotognella, F., Ghadimi, A., Thomson, J., Nanofabrication by selfassembly (2009) Mater. Today, 12, pp. 12-23; Dubas, S.T., Schlenoff, J.B., Factors controlling the growth of polyelectrolyte multilayers (1999) Macromolecules, 32 (24), pp. 8153-8160. , DOI 10.1021/ma981927a; Kumar, M.N.V.R., Muzzarelli, R.A.A., Muzzarelli, C., Sashiwa, H., Domb, A.J., Chitosan chemistry and pharmaceutical perspectives (2004) Chemical Reviews, 104 (12), pp. 6017-6084. , DOI 10.1021/cr030441b; Yi, H., Wu, L.-Q., Bentley, W.E., Ghodssi, R., Rubloff, G.W., Culver, J.N., Payne, G.F., Biofabrication with chitosan (2005) Biomacromolecules, 6 (6), pp. 2881-2894. , DOI 10.1021/bm050410l; Berger, J., Reist, M., Mayer, J.M., Felt, O., Gurny, R., Structure and interactions in chitosan hydrogels formed by complexation or aggregation for biomedical applications (2004) European Journal of Pharmaceutics and Biopharmaceutics, 57 (1), pp. 35-52. , DOI 10.1016/S0939-6411(03)00160-7; Rinaudo, M., Chitin and chitosan: Properties and applications (2006) Progress in Polymer Science (Oxford), 31 (7), pp. 603-632. , DOI 10.1016/j.progpolymsci.2006.06.001, PII S0079670006000530; Sogias, I.A., Khutoryanskiy, V.V., Williams, A.C., Exploring the factors affecting the solubility of chitosan in water (2010) Macromol. Chem. Phys., 211, pp. 426-433; Sorlier, P., Denuziere, A., Viton, C., Domard, A., Relation between the degree of acetylation and the electrostatic properties of chitin and chitosan (2001) Biomacromolecules, 2 (3), pp. 765-772. , DOI 10.1021/bm015531+; Krayukhina, M.A., Samoilova, N.A., Yamskov, I.A., Polyelectrolyte complexes of chitosan: Formation, properties, and applications (2008) Usp. Khim., 77, pp. 854-869; Buescher, J.M., Margaritis, A., Microbial biosynthesis of polyglutamic acid biopolymer and applications in the biopharmaceutical, biomedical and food industries (2007) Critical Reviews in Biotechnology, 27 (1), pp. 1-19. , DOI 10.1080/07388550601166458, PII 773236840; Shih, I.L., Van, Y.T., Shen, M.H., Biomedical applications of chemically and microbiologically synthesized poly(glutamic acid) and poly(lysine) (2004) Mini-Rev. Med. Chem., 4, pp. 179-188; Nelson, D.L., Cox, M.M., Amino acids peptides and proteins (2005) Lehninger Principles of Biochemistry, pp. 78-79. , 4th ed.; W. H. Freeman and Company: New York; Edde, B., Rossier, J., Lecaer, J.P., Desbruyeres, E., Gros, F., Denoulet, P., Posttranslational glutamylation of alpha-tubulin (1990) Science, 247, pp. 83-85; Candela, T., Fouet, A., Poly-γ-glutamate in bacteria (2006) Mol. Microbiol., 60, pp. 1091-1098; Rhie, G.-E., Roehrl, M.H., Mourez, M., Collier, R.J., Mekalanos, J.J., Wang, J.Y., A dually active anthrax vaccine that confers protection against both bacilli and toxins (2003) Proceedings of the National Academy of Sciences of the United States of America, 100 (19), pp. 10925-10930. , DOI 10.1073/pnas.1834478100; Schneerson, R., Kubler-Kielb, J., Liu, T.-Y., Dai, Z.-D., Leppla, S.H., Yergey, A., Backlund, P., Robbins, J.B., Poly(γ-D-glutamic acid) protein conjugates induce IgG antibodies in mice to the capsule of Bacillus anthracis: A potential addition to the anthrax vaccine (2003) Proceedings of the National Academy of Sciences of the United States of America, 100 (15), pp. 8945-8950. , DOI 10.1073/pnas.1633512100; Prescott, A.G., Stock II, L.R., (2005) Method for Producing Medical and Commercial Grade Poly-γ-glutamic Acid of High Molecular Weight, , U. S. Patent 20050095679; Prodhomme, E.J.F., Tutt, A.L., Glennie, M.J., Bugg, T.D.H., Multivalent Conjugates of Poly-γ-D-glutamic Acid from Bacillus licheniformis with Antibody F(abβ) and Glycopeptide Ligands (2003) Bioconjugate Chemistry, 14 (6), pp. 1148-1155. , DOI 10.1021/bc020019m; Sutherland, M.D., Thorkildson, P., Parks, S.D., Kozel, T.R., In vivo fate and distribution of poly-γ-D-glutamic acid, the capsular antigen from Bacillus anthracis (2008) Infection and Immunity, 76 (3), pp. 899-906. , DOI 10.1128/IAI.01176-07; Serizawa, T., Goto, H., Kishida, A., Endo, T., Akashi, M., Improved alternate deposition of biodegradable naturally occurring polymers onto a quartz crystal microbalance (1999) J. Polym. Sci., Part A: Polym. Chem., 37, pp. 801-804; Tachaboonyakiat, W., Serizawa, T., Endo, T., Akashi, M., The influence of molecular weight over the ultrathin films of biodegradable polyion complexes between chitosan and poly(γ-glutamic acid) (2000) Polym. J., 32, pp. 481-485; Hsieh, C.Y., Tsai, S.P., Wang, D.M., Chang, Y.N., Hsieh, H.J., Preparation of γ-PGA/chitosan composite tissue engineering matrices (2005) Biomaterials, 26, pp. 5617-5623; Kang, H.S., Park, S.H., Lee, Y.G., Son, T.I., Polyelectrolyte complex hydrogel composed of chitosan and poly(γ-glutamic acid) for biological application: Preparation, physical properties, and cytocompatibility (2007) J. Appl. Polym. Sci., 103, pp. 386-394; Tsao, C.T., Chang, C.H., Lin, Y.Y., Wu, M.F., Wang, J.L., Han, J.L., Hsieh, K.H., Antibacterial activity and biocompatibility of a chitosan-γ- poly(glutamic acid) polyelectrolyte complex hydrogel (2010) Carbohydr. Res., 345, pp. 1774-1780; Hajdu, I., Bodnar, M., Filipcsei, G., Hartmann, J.F., Daroczi, L., Zrinyi, M., Borbely, J., Nanoparticles prepared by self-assembly of chitosan and poly-γ-glutamic acid (2008) Colloid Polym. Sci., 286, pp. 343-350; Lin, Y.H., Chung, C.K., Chen, C.T., Liang, H.F., Chen, S.C., Sung, H.W., Preparation of nanoparticles composed of chitosan/poly-γ-glutamic acid and evaluation of their permeability through Caco-2 cells (2005) Biomacromolecules, 6, pp. 1104-1112; Imoto, T., Kida, T., Matsusaki, M., Akashi, M., Preparation and unique pH-responsive properties of novel biodegradable nanocapsules composed of poly(γ-glutamic acid) and chitosan as weak polyelectrolytes (2010) Macromol. Biosci., 10, pp. 271-277; Crompton, K.E., Goud, J.D., Bellamkonda, R.V., Gengenbach, T.R., Finkelstein, D.I., Horne, M.K., Forsythe, J.S., Polylysine-functionalised thermoresponsive chitosan hydrogel for neural tissue engineering (2007) Biomaterials, 28 (3), pp. 441-449. , DOI 10.1016/j.biomaterials.2006.08.044, PII S0142961206007642; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydrate Polymers, 29 (1), pp. 63-68. , DOI 10.1016/0144-8617(95)00147-6; Kunioka, M., Goto, A., Biosynthesis of poly(γ-glutamic acid) from L-glutamic acid, citric acid, and ammonium sulfate in Bacillus subtilis IFO3335 (1994) Applied Microbiology and Biotechnology, 40 (6), pp. 867-872. , DOI 10.1007/s002530050082; Kubota, H., Matsunobu, T., Uotani, K., Takebe, H., Satoh, A., Tanaka, T., Taniguchi, M., Production of poly(γ-glutamic acid) by Bacillus subtilis F-2-01 (1993) Biosci., Biotechnol., Biochem., 57, pp. 1212-1213; Ashiuchi, M., Soda, K., Misono, H., A poly-γ-glutamate synthetic system of Bacillus subtilis IFO 3336: Gene cloning and biochemical analysis of poly-γ-glutamate produced by Escherichia coli clone cells (1999) Biochemical and Biophysical Research Communications, 263 (1), pp. 6-12. , DOI 10.1006/bbrc.1999.1298; Yamaguchi, F., Ogawa, Y., Kikuchi, M., Yuasa, K., Motai, H., Detection of γ-polyglutamic acid (γ-PGA) by SDS-PAGE (1996) Biosci., Biotechnol., Biochem., 60, pp. 255-258; Scolnik, Y., Portnaya, I., Cogan, U., Tal, S., Haimovitz, R., Fridkin, M., Elitzur, A.C., Shinitzky, M., Subtle differences in structural transitions between poly-L-and poly-D-amino acids of equal length in water (2006) Phys. Chem. Chem. Phys., 8, pp. 333-339; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) Journal of Biomedical Materials Research - Part A, 67 (1), pp. 158-171; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Da Silva, M.F., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Transactions on Magnetics, 35 (5 PART 3), pp. 4361-4367. , DOI 10.1109/20.799086; Ambrosio, L., Borzacchiello, A., Netti, P.A., Nicolais, L., Properties of new materials: Rheological study on hyaluronic acid and its derivative solutions (1999) Journal of Macromolecular Science - Pure and Applied Chemistry, 36 A (7-8), pp. 991-1000; Horcas, I., Fernandez, R., Gomez-Rodriguez, J.M., Colchero, J., Gomez-Herrero, J., Baro, A.M., WSXM: A software for scanning probe microscopy and a tool for nanotechnology (2007) Rev. Sci. Instrum., 78, p. 1; Martins, M.C.L., Ochoa-Mendes, V., Ferreira, G., Barbosa, J.N., Curtin, S.A., Ratner, B.D., Barbosa, M.A., Interactions of leukocytes and platelets with poly(lysine/leucine) immobilized on tetraethylene glycol-terminated self-assembled monolayers (2011) Acta Biomater., 7, pp. 1949-1955; Werner, C., Konig, U., Augsburg, A., Arnhold, C., Korber, H., Zimmermann, R., Jacobasch, H.-J., Electrokinetic surface characterization of biomedical polymers - A survey (1999) Colloids and Surfaces A: Physicochemical and Engineering Aspects, 159 (2-3), pp. 519-529. , DOI 10.1016/S0927-7757(99)00290-3, PII S0927775799002903; Fairbrother, F., Mastin, H., Studies in electro-endosmosis part I (1924) J. Chem. Soc., 125, pp. 2319-2330; Voinova, M.V., Rodahl, M., Jonson, M., Kasemo, B., Viscoelastic acoustic response of layered polymer films at fluid-solid interfaces: Continuum mechanics approach (1999) Phy. Scr., 59, pp. 391-396; Hook, F., Kasemo, B., Variations in coupled water, viscoelastic properties, and film thickness of a Mefp-1 protein film during adsorption and cross-linking: A quartz crystal microbalance with dissipation monitoring, ellipsometry, and surface plasmon resonance study (2001) Analytical Chemistry, 73 (24), pp. 5796-5804. , DOI 10.1021/ac0106501; Hook, F., Rodahl, M., Brzezinski, P., Kasemo, B., Measurements using the quartz crystal microbalance technique of ferritin monolayers on methyl-thiolated gold: Dependence of energy dissipation and saturation coverage on salt concentration (1998) Journal of Colloid and Interface Science, 208 (1), pp. 63-67. , DOI 10.1006/jcis.1998.5774; Larsson, C., Rodahl, M., Hook, F., Characterization of DNA immobilization and subsequent hybridization on a 2D arrangement of streptavidin on a biotin-modified lipid bilayer supported on SiO 2 (2003) Analytical Chemistry, 75 (19), pp. 5080-5087. , DOI 10.1021/ac034269n; Sauerbrey, G., Verwendung von schwingquarzen zur wagung dunner schichten und zur mikrowagung (1959) Z. Phys., 155, pp. 206-222; Schlenoff, J.B., Dubas, S.T., Mechanism of polyelectrolyte multilayer growth: Charge overcompensation and distribution (2001) Macromolecules, 34 (3), pp. 592-598. , DOI 10.1021/ma0003093; Kim, D.K., Han, S.W., Kim, C.H., Hong, J.D., Kim, K., Morphology of multilayers assembled by electrostatic attraction of oppositely charged model polyelectrolytes (1999) Thin Solid Films, 350, pp. 153-160; Picart, C., Lavalle, Ph., Hubert, P., Cuisinier, F.J.G., Decher, G., Schaaf, P., Voegel, J.-C., Buildup mechanism for poly(L-lysine)/hyaluronic acid films onto a solid surface (2001) Langmuir, 17 (23), pp. 7414-7424. , DOI 10.1021/la010848g; Richert, L., Lavalle, P., Payan, E., Shu, X.Z., Prestwich, G.D., Stoltz, J.F., Schaaf, P., Picart, C., Layer by layer buildup of polysaccharide films: Physical chemistry and cellular adhesion aspects (2004) Langmuir, 20, pp. 448-458; Tsao, C.T., Hang, C.H., Lin, Y.Y., Wu, M.F., Wang, J.L., Young, T.H., Han, J.L., Hsieh, K.H., Evaluation of chitosan/γ-poly(glutamic acid) polyelectrolyte complex for wound dressing materials (2011) Carbohydr. Polym., 84, pp. 812-819; Bonazzola, C., Calvo, E.J., A Fourier transform infrared reflection-absorption spectroscopy study of redox polyelectrolyte films (2003) Langmuir, 19, pp. 5279-5286; Boulmedais, F., Ball, V., Schwinte, P., Frisch, B., Schaaf, P., Voegel, J.C., Buildup of exponentially growing multilayer polypeptide films with internal secondary structure (2003) Langmuir, 19, pp. 440-445; Boulmedais, F., Bozonnet, M., Schwinte, P., Voegel, J.C., Schaaf, P., Multilayered polypeptide films: Secondary structures and effect of various stresses (2003) Langmuir, 19, pp. 9873-9882; He, L.M., Neu, M.P., Vanderberg, L.A., Bacillus lichenformis γ-glutamyl exopolymer: Physicochemical characterization and U(VI) interaction (2000) Environmental Science and Technology, 34 (9), pp. 1694-1701. , DOI 10.1021/es991119e; Chan, Y.H.M., Schweiss, R., Werner, C., Grunze, M., Electrokinetic characterization of oligo-and poly(ethylene glycol)-terminated self-assembled monolayers on gold and glass surfaces (2003) Langmuir, 19, pp. 7380-7385; Giesbers, M., Kleijn, J.M., Cohen Stuart, M.A., The electrical double layer on gold probed by electrokinetic and surface force measurements (2002) Journal of Colloid and Interface Science, 248 (1), pp. 88-95. , DOI 10.1006/jcis.2001.8144; Schlenoff, J.B., Ly, H., Li, M., Charge and mass balance in polyelectrolyte multilayers (1998) Journal of the American Chemical Society, 120 (30), pp. 7626-7634. , DOI 10.1021/ja980350+; Rodahl, M., Hook, F., Fredriksson, C., Keller, C.A., Krozer, A., Brzezinski, P., Voinova, M., Kasemo, B., Simultaneous frequency and dissipation factor QCM measurements of biomolecular adsorption and cell adhesion (1997) Faraday Discussions, 107, pp. 229-246; Guzman, E., San Miguel, V., Peinado, C., Ortega, F., Rubio, R.C., Polyelectrolyte multilayers containing triblock copolymers of different charge ratio (2010) Langmuir, 26, pp. 11494-11502; Salomaki, M., Laiho, T., Kankare, J., Counteranion-controlled properties of polyelectrolyte multilayers (2004) Macromolecules, 37 (25), pp. 9585-9590. , DOI 10.1021/ma048701u; Dutta, A.K., Nayak, A., Belfort, G., Viscoelastic properties of adsorbed and cross-linked polypeptide and protein layers at a solidliquid interface (2008) J. Colloid Interface Sci., 324, pp. 55-60
Keywords: Amino acids; Anionic polymers; article; Atomic force microscopy; Atomic spectroscopy; Biocompatible Materials; Biocompatible polysaccharides; Biomaterials; Biomedical applications; Cell-biomaterial interactions; chemical interaction; chitosan; controlled study; Cytotoxicity; Drug delivery; drug delivery system; Drug Delivery Systems; Electrolytes; ellipsometry; enzyme activity; Extracellular; Fourier transform infrared spectroscopy; Glutamic acid; immunogenicity; infrared spectroscopy; Layer by layer self assembly; Medical applications; microenvironment; Microenvironments; Microscopy, Atomic Force; Model surface; Models, Molecular; Multi-layered; Multi-layered films; Multilayers; nanofilm; Nanostructured Films; polyanion; Polyanions; Polycations; polyelectrolyte; Polyelectrolyte complexes; Polyelectrolyte multilayer; Polyelectrolytes; Polyethylenes; polyglutamic acid; Polymers; priority journal; Programmed control systems; Quartz; quartz crystal microbalance; Quartz crystal microbalance with dissipation; Self assembly; Tissue; Tissue engineering; Tissue regeneration; Ultrathin films; Viscoelastic Substances; Zeta potential; Zeta potential measurements

The limits of agreement and the intraclass correlation coefficient may be inconsistent in the interpretation of agreement - Costa-Santos, C.; Bernardes, J.; Ayres-de-Campos, D.; Costa, A.; Costa, C. (Journal of Clinical EpidemiologyJ. Clin. Epidemiol., 2011)
Objective: To compare the interpretation of agreement in the prediction of neonatal outcome variables, using the limits of agreement (LA) and the intraclass correlation coefficient (ICC). Study Design and Setting: Three obstetricians were asked to predict neonatal outcomes independently based on the evaluation of intrapartum cardiotocographic tracings. Interobserver agreement was assessed with the LA and the ICC, and the results obtained were interpreted by six clinicians and six statisticians on a scale that established agreement as very poor, poor, fair, good, or very good. Results: Interpretation of the LA results was less consensual than the ICC results, with proportions of agreement of 0.36 (95% confidence interval [CI]: 0.28-0.44) vs. 0.63 (95% CI: 0.54-0.73), respectively. LA results suggested a fair to good agreement among obstetricians, whereas interpretation of ICC results suggested a poor to fair agreement. LA results were more plausible with reality, suggesting that obstetricians predicted neonatal outcomes better than randomly generated values, whereas it was not always the case with the ICC. Conclusions: LA and ICC can provide inconsistent results in agreement studies. Accordingly, in the absence of better strategies to assess agreement, both should be used for this purpose, but their results need to be interpreted with caution keeping their respective limitations in mind. © 2011 Elsevier Inc. All rights reserved.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JCEPEdoi: 10.1016/j.jclinepi.2009.11.010PubMed ID: 20189765Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Biostatistics and Medical Informatics Department, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: De Vet, H., Observer reliability and agreement (1999) Encyclopedia of Biostatistics, pp. 3123-3127;Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Santos, C.C., Pereira, C.A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) Br J Obstet Gynaecol, 112, pp. 667-669; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2003) J Clin Epidemiol, 56, pp. 963-967; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 1, pp. 307-310; Bartko, J.J., The intraclass correlation coefficient as a measure of reliability (1966) Psychol Rep, 19, pp. 3-11; Muller, R., Buttner, P., A critical discussion of intraclass correlation coefficients (1994) Stat Med, 13, pp. 2465-2476; Burdock, E., Fleiss, J.L., Hardesty, A.S., A new view of interobserver agreement (1963) Person Psychol, 16, pp. 373-384; Casey, B.M., McLntire, D.D., Leveno, K.J., The continuing value of the Apgar score for the assessment of newborn infants (2001) N Engl J Med, 344, pp. 467-471; Van De Riet, J.E., Vandenbussche, F.P., Le Cessie, S., Keirse, M.J., Newborn assessment and long-term adverse outcome: A systematic review (1999) Am J Obstet Gynecol, 180, pp. 1024-1029; Shrout, P.E., Fleiss, J.L., Intraclass correlations: Uses in assessing rater reliability (1979) Psychol Bull, 86, pp. 420-427; Fleiss, J.U., Davies, M., Measuring nominal scale agreement among many raters (1971) Psychol Bull, 76, pp. 378-382; Carpenter, J., Bithell, J., Bootstrap confidence intervals: When, which, what? A practical guide for medical statisticians (2000) Stat Med, 19, pp. 1141-1164; Landis, J.R., Koch, G.G., The measurement of observer agreement for categorical data (1977) Biometrics, 33, pp. 159-174
Keywords: Agreement; Apgar score; Cardiotocography; correlation coefficient; Female; Fetal Blood; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; intrapartum care; limit of agreement; newborn assessment; normal human; observer variation; Obstetrics; outcome variable; Pregnancy; Pregnancy Outcome; priority journal; reproducibility; Reproducibility of Results; review; statistical data interpretation; statistical parameters; Umbilical Arteries; Umbilical artery blood pH; umbilical cord blood

Molecularly designed alginate hydrogels susceptible to local proteolysis as three-dimensional cellular microenvironments - Fonseca, K.B.; Bidarra, S.J.; Oliveira, M.J.; Granja, P.L.; Barrias, C.C. (Acta BiomaterialiaActa Biomater., 2011)
The development of sophisticated three-dimensional (3-D) cell culture microenvironments that recreate some of the complexity of the natural extracellular matrix (ECM) remains a challenging task. Here, the modification of alginate through partial crosslinking with a matrix metalloproteinase (MMP) cleavable peptide (proline-valine-glycine-leucine-isoleucine-glycine, PVGLIG) is described, and its use in the preparation of injectable, in situ crosslinkable hydrogel-like matrices is proposed. PVGLIG-grafted alginates were synthesized by carbodiimide chemistry and characterized. Their biological performance was evaluated by comparing the response of 3-D cultured mesenchymal stem cells (MSCs) to alginate hydrogels containing only cell-adhesion peptides (RGD-alginate) or both peptides (PVGLIG/RGD-alginate). After 1 week, cells remained essentially round within RGD-alginate, while they exhibited an elongated morphology within PVGLIG/RGD-alginate hydrogels, forming cellular networks. This suggests that cells were able to structurally reorganize the matrix, through enzymatic hydrolysis of PVGLIG residues, overcoming biophysical hydrogel resistance. As shown by gelatine-zymography, MSC presented higher activity of MMP-2 when cultured within alginate functionalized with MMP-sensitive peptide, suggesting that the cell's proteolytic phenotype was modulated by the matrix composition. Additionally, PVGLIG/RGD-alginate hydrogels were clearly degraded in cell culture. Taken together, the results demonstrate that the co-incorporation of MMP-labile peptides in cell-adhesive RGD-alginate hydrogels improved their performance as ECM analogues, providing a more dynamic and physiological 3-D cellular microenvironment. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2010.12.029PubMed ID: 21193068Language of Original Document: EnglishCorrespondence Address: Barrias, C. C.; INEB, Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; gelatin, 9000-70-8; gelatinase A, 146480-35-5; Alginates; Glucuronic Acid, 576-37-4; Hexuronic Acids; Hydrogels; Matrix Metalloproteinases, 3.4.24.-; Peptides; alginic acid, 9005-32-7References: Lukashev, M.E., Werb, Z., ECM signalling: Orchestrating cell behaviour and misbehaviour (1998) Trends in Cell Biology, 8 (11), pp. 437-441. , DOI 10.1016/S0962-8924(98)01362-2, PII S0962892498013622;Bosman, F.T., Stamenkovic, I., Functional structure and composition of the extracellular matrix (2003) Journal of Pathology, 200 (4), pp. 423-428. , DOI 10.1002/path.1437; Lutolf, M.P., Hubbell, J.A., Synthetic biomaterials as instructive extracellular microenvironments for morphogenesis in tissue engineering (2005) Nature Biotechnology, 23 (1), pp. 47-55. , DOI 10.1038/nbt1055; Lutolf, M.P., Gilbert, P.M., Blau, H.M., Designing materials to direct stem-cell fate (2009) Nature, 462 (7272), pp. 433-441; Tibbitt, M.W., Anseth, K.S., Hydrogels as extracellular matrix mimics for 3D cell culture (2009) Biotechnol Bioeng, 103 (4), pp. 655-663; Augst, A.D., Kong, H.J., Mooney, D.J., Alginate hydrogels as biomaterials (2006) Macromolecular Bioscience, 6 (8), pp. 623-633. , DOI 10.1002/mabi.200600069; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H.-J., Barrias, C.C., Salema, R., Granja, P.L., Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix (2007) Biomaterials, 28 (25), pp. 3644-3655. , DOI 10.1016/j.biomaterials.2007.04.028, PII S014296120700347X; Grellier, M., Granja, P.L., Fricain, J.C., Bidarra, S.J., Renard, M., Bareille, R., The effect of the co-immobilization of human osteoprogenitors and endothelial cells within alginate microspheres on mineralization in a bone defect (2009) Biomaterials, 30 (19), pp. 3271-3278; Bidarra, S.J., Barrias, C.C., Barbosa, M.A., Soares, R., Granja, P.L., Immobilization of human mesenchymal stem cells within RGD-grafted alginate microspheres and assessment of their angiogenic potential (2010) Biomacromolecules, 11 (8), pp. 1956-1964; West, J.L., Hubbell, J.A., Polymeric biomaterials with degradation sites for proteases involved in cell migration (1999) Macromolecules, 32 (1), pp. 241-244; Page-Mccaw, A., Ewald, A.J., Werb, Z., Matrix metalloproteinases and the regulation of tissue remodelling (2007) Nat Rev Mol Cell Biol, 8 (3), pp. 221-233; Murphy, G., Nagase, H., Progress in matrix metalloproteinase research (2008) Mol Aspects Med, 29 (5), pp. 290-308; Chau, Y., Luo, Y., Cheung, A.C.Y., Nagai, Y., Zhang, S., Kobler, J.B., Incorporation of a matrix metalloproteinase-sensitive substrate into self-assembling peptides - A model for biofunctional scaffolds (2008) Biomaterials, 29 (11), pp. 1713-1719; Chau, Y., Tan, F.E., Langer, R., Synthesis and characterization of dextran-peptide-methotrexate conjugates for tumor targeting via mediation by matrix metalloproteinase II and matrix metalloproteinase IX (2004) Bioconjugate Chemistry, 15 (4), pp. 931-941. , DOI 10.1021/bc0499174; Turk, B.E., Huang, L.L., Piro, E.T., Cantley, L.C., Determination of protease cleavage site motifs using mixture-based oriented peptide libraries (2001) Nature Biotechnology, 19 (7), pp. 661-667. , DOI 10.1038/90273; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24 (22), pp. 4023-4029. , DOI 10.1016/S0142-9612(03)00295-3; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20 (1), pp. 45-53. , DOI 10.1016/S0142-9612(98)00107-0, PII S0142961298001070; Lorenzen, A., Kennedy, S.W., A fluorescence-based protein assay for use with a microplate reader (1993) Analytical Biochemistry, 214 (1), pp. 346-348. , DOI 10.1006/abio.1993.1504; Kuo, C.K., Ma, P.X., Ionically crosslinked alginate hydrogels as scaffolds for tissue engineering: Part 1. Structure, gelation rate and mechanical properties (2001) Biomaterials, 22 (6), pp. 511-521. , DOI 10.1016/S0142-9612(00)00201-5, PII S0142961200002015; Oliveira, S.M., Barrias, C.C., Almeida, I.F., Costa, P.C., Pena Ferreira, M.R., Bahia, M.F., Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gel-forming ability (2008) J Biomed Mater Res B Appl Biomater, 87 (1), pp. 49-58; Kavimandan, N.J., Losi, E., Wilson, J.J., Brodbelt, J.S., Peppas, N.A., Synthesis and characterization of insulin-transferrin conjugates (2006) Bioconjugate Chemistry, 17 (6), pp. 1376-1384. , DOI 10.1021/bc050344k; Lee, K.Y., Rowley, J.A., Eiselt, P., Moy, E.M., Bouhadir, K.H., Mooney, D.J., Controlling mechanical and swelling properties of alginate hydrogels independently by cross-linker type and cross-linking density (2000) Macromolecules, 33 (11), pp. 4291-4294; Dent, A., Aslam, M., The functional chemistry of proteins and protein coupling (1998) Bioconjugation: Protein Coupling Techniques for the Biomedical Sciences, pp. 50-100; Werb, Z., ECM and cell surface proteolysis: Regulating cellular ecology (1997) Cell, 91 (4), pp. 439-442; Friedl, P., Brocker, E.-B., The biology of cell locomotion within three-dimensional extracellular matrix (2000) Cellular and Molecular Life Sciences, 57 (1), pp. 41-64. , DOI 10.1007/s000180050498; Drury, J.L., Boontheeku, T., Mooney, D.J., Cellular cross-linking of peptide modified hydrogels (2005) Journal of Biomechanical Engineering, 127 (2), pp. 220-228. , DOI 10.1115/1.1865194; Boontheekul, T., Kong, H.-J., Mooney, D.J., Controlling alginate gel degradation utilizing partial oxidation and bimodal molecular weight distribution (2005) Biomaterials, 26 (15), pp. 2455-2465. , DOI 10.1016/j.biomaterials.2004.06.044, PII S0142961204006064; Ries, C., Egea, V., Karow, M., Kolb, H., Jochum, M., Neth, P., MMP-2, MT1-MMP, and TIMP-2 are essential for the invasive capacity of human mesenchymal stem cells: Differential regulation by inflammatory cytokines (2007) Blood, 109 (9), pp. 4055-4063. , http://bloodjournal.hematologylibrary.org/cgi/reprint/109/9/4055, DOI 10.1182/blood-2006-10-051060; Seiki, M., The cell surface: The stage for matrix metalloproteinase regulation of migration (2002) Current Opinion in Cell Biology, 14 (5), pp. 624-632. , DOI 10.1016/S0955-0674(02)00363-0; Will, H., Atkinson, S.J., Butler, G.S., Smith, B., Murphy, G., The soluble catalytic domain of membrane type 1 matrix metalloproteinase cleaves the propeptide of progelatinase A and initiates autoproteolytic activation. Regulation by TIMP-2 and TIMP-3 (1996) Journal of Biological Chemistry, 271 (29), pp. 17119-17123. , DOI 10.1074/jbc.271.29.17119; Itoh, Y., Seiki, M., MT1-MMP: A potent modifier of pericellular microenvironment (2006) Journal of Cellular Physiology, 206 (1), pp. 1-8. , DOI 10.1002/jcp.20431; Barbolina, M.V., Adley, B.P., Ariztia, E.V., Liu, Y., Stack, M.S., Microenvironmental regulation of membrane type 1 matrix metalloproteinase activity in ovarian carcinoma cells via collagen-induced EGR1 expression (2007) Journal of Biological Chemistry, 282 (7), pp. 4924-4931. , http://www.jbc.org/cgi/reprint/282/7/4924, DOI 10.1074/jbc.M608428200
Keywords: 3-D Cell culture; Alginate; Alginates; alginic acid; Amino Acid Sequence; article; cell adhesion; cell composition; Cell Count; Cell culture; Cell Culture Techniques; Cell Shape; cell structure; cell survival; cell viability; Cells, Cultured; controlled study; Enzyme Activation; enzyme activity; extracellular matrix; Extracellular matrix (ECM); gelatin; gelatinase A; Glucuronic Acid; Hexuronic Acids; human; human cell; Humans; hydrogel; Hydrogels; hydrolysis; matrix metalloproteinase; Matrix Metalloproteinases; Matrix metalloproteinases (MMPs); Mesenchymal stem cell; Mesenchymal Stem Cells; Molecular Sequence Data; morphology; peptide derivative; Peptides; phenotype; priority journal; prolylvalylglycylleucylisoleucylglycine; Protease-sensitive; protein cleavage; protein degradation; Protein Processing, Post-Translational; Subcellular Fractions; tumor microenvironment; unclassified drug; zymography

Observer reliability and agreement: Differences, difficulties, and controversies - Costa Santos, C.; Bernardes, J.; Ayres-de-Campos, D. (Journal of Clinical EpidemiologyJ. Clin. Epidemiol., 2011)
Keywords: consensus; correlation coefficient; letter; methodology; organization; priority journal; reliability; research; scientific literature; validity

Pectin-based injectable biomaterials for bone tissue engineering - Munarin, F.; Guerreiro, S.G.; Grellier, M.A.; Tanzi, M.C.; Barbosa, M.A.; Petrini, P.; Granja, P.L. (BiomacromoleculesBiomacromolecules, 2011)
A variety of natural polymers and proteins are considered to be 3D cell culture structures able to mimic the extracellular matrix (ECM) to promote bone tissue regeneration. Pectin, a natural polysaccharide extracted from the plant cell walls and having a chemical structure similar to alginate, provides interesting properties as artificial ECM. In this work, for the first time, pectin, modified with an RGD-containing oligopeptide or not, is used as an ECM alternative to immobilize cells for bone tissue regeneration. The viability, metabolic activity, morphology, and osteogenic differentiation of immobilized MC3T3-E1 preosteoblats demonstrate the potential of this polysaccharide to keep immobilized cells viable and differentiating. Preosteoblasts immobilized in both types of pectin microspheres maintained a constant viability up to 29 days and were able to differentiate. The grafting of the RGD peptide on pectin backbone induced improved cell adhesion and proliferation within the microspheres. Furthermore, not only did cells grow inside but also theywere able to spread out from themicrospheres and to organize themselves in 3D structures producing a mineralized extracellular matrix. These promising results suggest that pectin can be proposed as an injectable cell vehicle for bone tissue regeneration. © 2011 American Chemical Society.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm101110xPubMed ID: 21302960Language of Original Document: EnglishCorrespondence Address: Munarin, F.; Biomatlab, Bioengineering Department, Politecnico di Milano, Piazza Leonardo da Vinci 32, 20133, Milan, Italy; email: fabiola.munarin@mail.polimi.itChemicals/CAS: arginylglycylaspartic acid, 99896-85-2; osteocalcin, 136461-80-8; pectin, 9000-69-5; Biocompatible Materials; Oligopeptides; Pectins; arginyl-glycyl-aspartic acid, 99896-85-2; pectin, 9000-69-5References: Brown, M.J., Lester, J.N., (1980) Appl. Environ. Microbiol., 40, pp. 179-185;Knox, J.P., (2008) Curr. Opin. Plant Biol., 1, pp. 308-313; Jarvis, M.C., (1984) Plant, Cell Environ, 7, pp. 153-164; Thom, D., Grant, G.T., Morris, E.R., Rees, D.A., (1982) Carbohydr. Res., 100, pp. 29-42; Fang, Y., Al-Assaf, S., Phillips, G.O., Nishinari, K., Funami, T., Williams, P.A., (2008) Carbohydr. Polym., 72, pp. 334-341; Rowley, J.A., Madlambayan, G., Mooney, D.J., (1999) Biomaterials, 20, pp. 45-53; Price, L.S., (1997) Bioessays, 19, pp. 941-943; Dee, K.C., Andersen, T.T., Bizios, R., (1999) Biomaterials, 20, pp. 221-227; Pierschbacher, M.D., Ruoslahti, E., (1984) Nature, 309, pp. 30-33; Ruoslahti, E., Pierschbacher, M., (1987) Science, 238, pp. 491-497; Hynes, R.O., (1992) Cell, 69, pp. 11-25; Yamada, K.M., (1997) Matrix Biol., 16, pp. 137-141; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H., Barrias, C.C., Salema, R., Granja, P.L., (2007) Biomaterials, 28, pp. 3644-3655; Grellier, M., Granja, P.L., Fricain, J., Bidarra, S.J., Renard, M., Bareille, R., Bourget, C., Barbosa, M.A., (2009) Biomaterials, 30, pp. 3271-3278; Liu, L., Fishman, M.L., Kost, J., Hicks, K.B., (2003) Biomaterials, 24, pp. 3333-3343; Rao, K.P., Prabhashankar, B., Kumar, A., Khan, A., Biradar, S.S., Srishail, S.P., Satyanath, B., (2003) Yale J. Biol. Med., 76, pp. 149-154; Jackson, C.L., Dreaden, T.M., Theobald, L.K., Tran, N.M., Beal, T.L., Eid, M., Gao, M.Y., Mohnen, D., (2007) Glycobiology, 17, pp. 805-819; Glinsky, V.V., Raz, A., (2009) Carbohydr. Res., 344, pp. 1788-1791; Vayssade, M., Sengkhamparn, N., Verhoef, R., Delaigue, C., Goundiam, O., Vigneron, P., Voragen, A.G., Nagel, M.D., (2010) Phytother. Res., 24, pp. 982-989; Katav, T., Liu, L., Traitel, T., Goldbart, R., Wolfson, M., Kost, J., (2008) J. Controlled Release, 130, pp. 183-191; Opanasopit, P., Apirakaramwong, A., Ngawhirunpat, T., Rojanarata, T., Ruktanonchai, U., (2008) AAPS PharmSciTech, 9, pp. 67-74; Morra, M., Cassinelli, C., Cascardo, G., Nagel, M., Della Volpe, C., Siboni, S., Maniglio, D., Ulvskov, P., (2004) Biomacromolecules, 5, pp. 2094-2104; Bussy, C., Verhoef, R., Haeger, A., Morra, M., Duval, J., Vigneron, P., Bensoussan, A., Nagel, M.D., (2008) J. Biomed. Mater. Res. A, 86, pp. 597-606; Kokkonen, H.E., Ilvesaro, J.M., Morra, M., Schols, H.A., Tuukkanen, J., (2007) Biomacromolecules, 8, pp. 509-515; Munarin, F., Giuliano, L., Bozzini, S., Tanzi, M.C., Petrini, P., (2010) Mater. Sci. Eng. C, 30, pp. 491-496; Karageorgiou, V., Kaplan, D., (2005) Biomaterials, 26, pp. 5474-5491; Volkmer, E., Drosse, I., Otto, S., Stangelmayer, A., Stengele, M., Kallukalam, B.C., Mutschler, W., Schieker, M., (2008) Tissue Eng., Part A, 14, pp. 1331-1340; Anselme, K., (2000) Biomaterials, 21, pp. 667-681; Hersel, U., Dahmen, C., Kessler, H., (2003) Biomaterials, 24, pp. 4385-4415; Stains, J.P., Civitelli, R., (2005) Birth Defects Res., Part C, 75, pp. 72-80; Ichibouji, T., Miyazaki, T., Ishida, E., Ashizuka, M., Sugino, A., Ohtsuki, C., Kuramoto, K., (2008) J. Ceram. Soc. Jpn., 116, pp. 74-78
Keywords: 3-D Cell culture; 3D Structure; 3T3 Cells; Adhesion; Alginate; animal cell; Animals; arginylglycylaspartic acid; article; Biocompatible Materials; Biopolymers; Bone; Bone and Bones; Bone Regeneration; bone tissue; Bone tissue engineering; Bone tissue regeneration; carbohydrate analysis; cell adhesion; Cell culture; cell differentiation; cell growth; cell metabolism; cell proliferation; cell spreading; cell structure; cell viability; Cells; Chemical modification; Chemical structure; controlled study; Cryoelectron Microscopy; Extracellular matrices; extracellular matrix; gene expression; immobilized cell; Immobilized cells; Injectable biomaterials; Injections; MC3T3-E1; Metabolic activity; Mice; Microscopy, Electron, Scanning; microsphere; Microspheres; Mineralized extracellular matrixes; mouse; Natural polysaccharide; nonhuman; Oligopeptides; osteoblast; osteocalcin; Osteogenic differentiation; pectin; Pectins; Plant cell culture; Plant cell wall; Preosteoblasts; priority journal; RGD peptide; Three dimensional; Tissue engineering

Scientists perception of ethical issues in nanomedicine: A case study - Silva Costa, H.; Sethe, S.; Pêgo, A.P.; Olsson, I.A.S. (NanomedicineNanomedicine, 2011)
Aim: Research and development in nanomedicine has been accompanied by the consideration of ethical issues; however, little is known about how researchers working in this area perceive such issues. This case-study explores scientists attitude towards and knowledge of ethical issues. Method: Data were collected by semi-structured interviews with 22 nanomedicine practitioners and subject to content analysis. Results: We found that scientists reflect with ambiguity on the reputed novelty of nanomedicine and what the ethical issues and risks are in their work. Respondents see no necessity for a paradigm shift in ethical considerations, but view ethical issues in nanomedicine as overlapping with those of other areas of biomedical research. Most respondents discuss ethical issues they faced in scientific work with their colleagues, but expect benefit from additional information and training on ethics. Conclusion: Our findings that scientists are motivated to reflect on ethical issues in their work, can contribute to the design of new strategies, including training programs, to engage scientists in ethical discussion and stimulate their responsibility as nanomedicine practitioners. © 2011 Future Medicine Ltd.
Keywords: adult; ambiguity; article; attitude; case study; clinical article; empirical research; ethics; Female; human; Humans; information; knowledge; male; medical ethics; medical research; Middle Aged; Models, Theoretical; nanomedicine; Nanotechnology; perception; priority journal; professional practice; qualitative study; Research Personnel; responsibility; risks; scientist; scientists perception; semi structured interview; training; Young Adult

Simulations of the NK cell immune synapse reveal that activation thresholds can be established by inhibitory receptors acting locally - Kaplan, A.; Kotzer, S.; Almeida, C.R.; Kohen, R.; Halpert, G.; Salmon-Divon, M.; Köhler, K.; Höglund, P.; Davis, D.M.; Mehr, R. (Journal of ImmunologyJ. Immunol., 2011)
NK cell activation is regulated by a balance between activating and inhibitory signals. To address the question of how these signals are spatially integrated, we created a computer simulation of activating and inhibitory NK cell immunological synapse (NKIS) assembly, implementing either a "quantity-based" inhibition model or a "distance-based" inhibition model. The simulations mimicked the observed molecule distributions in inhibitory and activating NKIS and yielded several new insights. First, the total signal is highly influenced by activating complex dissociation rates but not by adhesion and inhibitory complex dissociation rates. Second, concerted motion of receptors in clusters significantly accelerates NKIS maturation. Third, when the potential of a cis interaction between Ly49 receptors and MHC class I on murine NK cells was added to the model, the integrated signal as a function of receptor and ligand numbers was only slightly increased, at least up to the level of 50% cis-bound Ly49 receptors reached in the model. Fourth, and perhaps most importantly, the integrated signal behavior obtained when using the distance-based inhibition signal model was closer to the experimentally observed behavior, with an inhibition radius of the order 3-10 molecules. Microscopy to visualize Vav activation in NK cells on micropatterned surfaces of activating and inhibitory strips revealed that Vav is only locally activated where activating receptors are ligated within a single NK cell contact. Taken together, these data are consistent with a model in which inhibitory receptors act locally; that is, that every bound inhibitory receptor acts on activating receptors within a certain radius around it. Copyright © 2011 by The American Association of Immunologists, Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JOIMAdoi: 10.4049/jimmunol.1002208PubMed ID: 21690326Language of Original Document: EnglishCorrespondence Address: Mehr, R.; Mina and Everard Goodman Faculty of Life Sciences, Bar-Ilan University, Ramat-Gan 52900, Israel; email: ramit.mehr@biu.ac.ilChemicals/CAS: Vav protein, 282122-55-8; intercellular adhesion molecule 1, 126547-89-5; H-2 Antigens; Histocompatibility Antigens Class I; Intercellular Adhesion Molecule-1, 126547-89-5; KLRK1 protein, human; Lymphocyte Function-Associated Antigen-1; MHC class I-related chain A; NK Cell Lectin-Like Receptor Subfamily A; NK Cell Lectin-Like Receptor Subfamily K; Receptors, KIRReferences: Burgess, S.J., Maasho, K., Masilamani, M., Narayanan, S., Borrego, F., Coligan, J.E., The NKG2D receptor: Immunobiology and clinical implications (2008) Immunol. Res., 40, pp. 18-34;González, S., López-Soto, A., Suarez-Alvarez, B., López-Vázquez, A., López-Larrea, C., NKG2D ligands: Key targets of the immune response (2008) Trends Immunol., 29, pp. 397-403; Vyas, Y.M., Maniar, H., Dupont, B., Cutting edge: Differential segregation of the Src homology 2-containing protein tyrosine phosphatase-1 within the early NK cell immune synapse distinguishes noncytolytic from cytolytic interactions (2002) Journal of Immunology, 168 (7), pp. 3150-3154; Long, E.O., Negative signaling by inhibitory receptors: The NK cell paradigm (2008) Immunol. Rev., 224, pp. 70-84; Ljunggren, H.G., Kärre, K., In search of the 'missing self': MHC molecules and NK cell recognition (1990) Immunol. Today, 11, pp. 237-244; Kane, K.P., Silver, E.T., Hazes, B., Specificity and function of activating Ly-49 receptors (2001) Immunol. Rev., 181, pp. 104-114; Lanier, L.L., Up on the tightrope: Natural killer cell activation and inhibition (2008) Nat. Immunol., 9, pp. 495-502; Radaev, S., Sun, P.D., Structure and function of natural killer cell surface receptors (2003) Annu. Rev. Biophys. Biomol. Struct., 32, pp. 93-114; Vivier, E., Nunes, J.A., Vely, F., Natural killer cell signaling pathways (2004) Science, 306 (5701), pp. 1517-1519. , DOI 10.1126/science.1103478; Yokoyama, W.M., Plougastel, B.F., Immune functions encoded by the natural killer gene complex (2003) Nat. Rev. Immunol., 3, pp. 304-316; Stebbins, C.C., Watzl, C., Billadeau, D.D., Leibson, P.J., Burshtyn, D.N., Long, E.O., Vav1 dephosphorylation by the tyrosine phosphatase SHP-1 as amechanism for inhibition of cellular cytotoxicity (2003) Mol. Cell. Biol., 23, pp. 6291-6299; Bryceson, Y.T., Long, E.O., Line of attack: NK cell specificity and integration of signals (2008) Curr. Opin. Immunol., 20, pp. 344-352; McCann, F.E., Suhling, K., Carlin, L.M., Eleme, K., Taner, S.B., Yanagi, K., Vanherberghen, B., Davis, D.M., Imaging immune surveillance by T cells and NK cells (2002) Immunol. Rev., 189, pp. 179-192; Davis, D.M., Assembly of the immunological synapse for T cells and NK cells (2002) Trends in Immunology, 23 (7), pp. 356-363. , DOI 10.1016/S1471-4906(02)02243-3, PII S1471490602022433; Vyas, Y.M., Mehta, K.M., Morgan, M., Maniar, H., Butros, L., Jung, S., Burkhardt, J.K., Dupont, B., Spatial organization of signal transduction molecules in the NK cell immune synapses during MHC class I-regulated noncytolytic and cytolytic interactions (2001) Journal of Immunology, 167 (8), pp. 4358-4367; Vyas, Y.M., Maniar, H., Lyddane, C.E., Sadelain, M., Dupont, B., Ligand binding to inhibitory killer cell Ig-like receptors induce colocalization with Src homology domain 2-containing protein tyrosine phosphatase 1 and interruption of ongoing activation signals (2004) Journal of Immunology, 173 (3), pp. 1571-1578; Orange, J.S., Formation and function of the lytic NK-cell immunological synapse (2008) Nat. Rev. Immunol., 8, pp. 713-725; Eleme, K., Taner, S.B., Onfelt, B., Collinson, L.M., McCann, F.E., Chalupny, N.J., Cosman, D., Davis, D.M., Cell surface organization of stress-inducible proteins ULBP and MICA that stimulate human NK cells and T cells via NKG2D (2004) J. Exp. Med., 199, pp. 1005-1010; Cebo, C., Da, R.S., Wittnebel, S., Turhan, A.G., Abdelali, J., Caillat-Zucman, S., Bourhis, J.H., Caignard, A., The decreased susceptibility of Bcr/Abl targets to NK cell-mediated lysis in response to imatinib mesylate involves modulation of NKG2D ligands, GM1 expression, and synapse formation (2006) Journal of Immunology, 176 (2), pp. 864-872; Burack, W.R., Lee, K.H., Holdorf, A.D., Dustin, M.L., Shaw, A.S., Cutting edge: Quantitative imaging of raft accumulation in the immunological synapse (2002) J. Immunol., 169, pp. 2837-2841; Harder, T., Engelhardt, K.R., Membrane domains in lymphocytes - From lipid rafts to protein scaffolds (2004) Traffic, 5, pp. 265-275; Laude, A.J., Prior, I.A., Plasma membrane microdomains: Organization, function and trafficking (2004) Mol. Membr. Biol., 21, pp. 193-205; Lou, Z., Jevremovic, D., Billadeau, D.D., Leibson, P.J., A balance between positive and negative signals in cytotoxic lymphocytes regulates the polarization of lipid rafts during the development of cell-mediated killing (2000) J. Exp. Med., 191, pp. 347-354; Pike, L.J., Lipid rafts: Bringing order to chaos (2003) Journal of Lipid Research, 44 (4), pp. 655-667. , DOI 10.1194/jlr.R200021-JLR200; Pizzo, P., Viola, A., Lymphocyte lipid rafts: Structure and function (2003) Curr. Opin. Immunol., 15, pp. 255-260; Rodgers, W., Farris, D., Mishra, S., Merging complexes: Properties of membrane raft assembly during lymphocyte signaling (2005) Trends Immunol., 26, pp. 97-103; Schmitz, G., Grandl, M., Update on lipid membrane microdomains (2008) Curr. Opin. Clin. Nutr. Metab. Care, 11, pp. 106-112; Wright, M.D., Moseley, G.W., Van Spriel, A.B., Tetraspanin microdomains in immune cell signalling and malignant disease (2004) Tissue Antigens, 64 (5), pp. 533-542. , DOI 10.1111/j.1399-0039.2004.00321.x; Vogt, A.B., Spindeldreher, S., Kropshofer, H., Clustering of MHCpeptide complexes prior to their engagement in the immunological synapse: Lipid raft and tetraspan microdomains (2002) Immunol. Rev., 189, pp. 136-151; Lee, S.J.E., Hori, Y., Groves, J.T., Dustin, M.L., Chakraborty, A.K., Correlation of a dynamic model for immunological synapse formation with effector functions: Two pathways to synapse formation (2002) Trends Immunol., 23, pp. 492-499; Giagulli, C., Scarpini, E., Ottoboni, L., Narumiya, S., Butcher, E.C., Constantin, G., Laudanna, C., RhoA and zeta PKC Control Distinct Modalities of LFA-1 Activation by Chemokines: Critical Role of LFA-1 Affinity Triggering in Lymphocyte In Vivo Homing (2004) Immunity, 20 (1), pp. 25-35. , DOI 10.1016/S1074-7613(03)00350-9; Masilamani, M., Nguyen, C., Kabat, J., Borrego, F., Coligan, J.E., CD94/NKG2A inhibits NK cell activation by disrupting the actin network at the immunological synapse (2006) J. Immunol., 177, pp. 3590-3596; Weikl, T.R., Lipowsky, R., Pattern formation during T-cell adhesion (2004) Biophysical Journal, 87 (6), pp. 3665-3678. , DOI 10.1529/biophysj.104.045609; Kotzer, S., Salmon-Divon, M., Kaplan, A., Almeida, C.R., Hoglund, P., Davis, D.M., Mehr, R., Modeling the influence of molecule and cell surface micro-domain distribution on the formation of T cell immunological synapses (2007) Life Science Systems and Applications Workshop, 2007. LISA 2007. IEEE/NIH. 8-9 November, , http://ieeexplore.ieee.org/xpl/freeabs_all.jsp?arnumber=4400878, Available at; Culley, F.J., Johnson, M., Evans, J.H., Kumar, S., Crilly, R., Casasbuenas, J., Schnyder, T., Ushakov, D.S., Natural killer cell signal integration balances synapse symmetry and migration (2009) PLoS Biol., 7, pp. e1000159; Treanor, B., Lanigan, P.M.P., Kumar, S., Dunsby, C., Munro, I., Auksorius, E., Culley, F.J., Neil, M.A.A., Microclusters of inhibitory killer immunoglobulin-like receptor signaling at natural killer cell immunological synapses (2006) J. Cell Biol., 174, pp. 153-161; Back, J., Chalifour, A., Scarpellino, L., Held, W., Stable masking by H-2Dd cis ligand limits Ly49A relocalization to the site of NK cell/target cell contact (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 3978-3983; Back, J., Scarpellino, L., Held, W., Probing the interactions of NK cell receptors with ligand expressed in trans and cis (2010) MethodsMol. Biol., 612, pp. 313-323; Chalifour, A., Scarpellino, L., Back, J., Brodin, P., Devèvre, E., Gros, F., Lévy, F., Held, W., A role for cis interaction between the inhibitory Ly49A receptor and MHC class I for natural killer cell education (2009) Immunity, 30, pp. 337-347; Doucey, M.A., Scarpellino, L., Zimmer, J., Guillaume, P., Luescher, I.F., Bron, C., Held, W., Cis association of Ly49A with MHC class I restricts natural killer cell inhibition (2004) Nat. Immunol., 5, pp. 328-336; Held, W., Mariuzza, R.A., Cis interactions of immunoreceptors with MHC and non-MHC ligands (2008) Nat. Rev. Immunol., 8, pp. 269-278; Scarpellino, L., Oeschger, F., Guillaume, P., Coedert, J.D., Levy, F., Leclercq, G., Held, W., Interactions of Ly49 family receptors with MHC class I ligands in trans and cis (2007) Journal of Immunology, 178 (3), pp. 1277-1284; Saffman, P.G., Delbrück, M., Brownian motion in biological membranes (1975) Proc. Natl. Acad. Sci. USA, 72, pp. 3111-3113; Raychaudhuri, S., Chakraborty, A.K., Kardar, M., Effective membrane model of the immunological synapse (2003) Phys. Rev. Lett., 91, p. 208101; Burroughs, N.J., Wülfing, C., Differential segregation in a cell-cell contact interface: The dynamics of the immunological synapse (2002) Biophys. J., 83, pp. 1784-1796; Coombs, D., Goldstein, B., Effects of the geometry of the immunological synapse on the delivery of effector molecules (2004) Biophysical Journal, 87 (4), pp. 2215-2220. , DOI 10.1529/biophysj.104.045674; Köhler, K., Xiong, S., Brzostek, J., Mehrabi, M., Eissmann, P., Harrison, A., Cordoba, S.P., Gould, K., Matched sizes of activating and inhibitory receptor/ligand pairs are required for optimal signal integration by human natural killer cells (2010) PLoS ONE, 5, pp. e15374; Dykstra, M., Cherukuri, A., Sohn, H.W., Tzeng, S.J., Pierce, S.K., Location is everything: Lipid rafts and immune cell signaling (2003) Annu. Rev. Immunol., 21, pp. 457-481; Horejsí, V., The roles of membrane microdomains (rafts) in T cell activation (2003) Immunol. Rev., 191, pp. 148-164; Fujiwara, T., Ritchie, K., Murakoshi, H., Jacobson, K., Kusumi, A., Phospholipids undergo hop diffusion in compartmentalized cell membrane (2002) Journal of Cell Biology, 157 (6), pp. 1071-1081. , DOI 10.1083/jcb.200202050; Giurisato, E., McIntosh, D.P., Tassi, M., Gamberucci, A., Benedetti, A., T cell receptor can be recruited to a subset of plasma membrane rafts, independently of cell signaling and attendantly to raft clustering (2003) J. Biol. Chem., 278, pp. 6771-6778; Kusumi, A., Koyama-Honda, I., Suzuki, K., Molecular dynamics and interactions for creation of stimulation-induced stabilized rafts from small unstable steady-state rafts (2004) Traffic, 5 (4), pp. 213-230. , DOI 10.1111/j.1600-0854.2004.0178.x; Marwali, M.R., MacLeod, M.A., Muzia, D.N., Takei, F., Lipid rafts mediate association of LFA-1 and CD3 and formation of the immunological synapse of CTL (2004) Journal of Immunology, 173 (5), pp. 2960-2967; Montixi, C., Langlet, C., Bernard, A.M., Thimonier, J., Dubois, C., Wurbel, M.A., Chauvin, J.P., He, H.T., Engagement of T cell receptor triggers its recruitment to low-density detergent-insoluble membrane domains (1998) EMBO J., 17, pp. 5334-5348; Munro, S., Lipid rafts: Elusive or illusive? (2003) Cell, 115, pp. 377-388; Pizzo, P., Giurisato, E., Bigsten, A., Tassi, M., Tavano, R., Shaw, A., Viola, A., Physiological T cell activation starts and propagates in lipid rafts (2004) Immunol. Lett., 91, pp. 3-9; Xavier, R., Brennan, T., Li, Q., McCormack, C., Seed, B., Membrane compartmentation is required for efficient T cell activation (1998) Immunity, 8, pp. 723-732; Filipp, D., Julius, M., Lipid rafts: Resolution of the "fyn problem"? (2004) Mol. Immunol., 41, pp. 645-656; Schade, A.E., Levine, A.D., Lipid raft heterogeneity in human peripheral blood T lymphoblasts: A mechanism for regulating the initiation of TCR signal transduction (2002) J. Immunol., 168, pp. 2233-2239; Janes, P.W., Ley, S.C., Magee, A.I., Aggregation of lipid rafts accompanies signaling via the T cell antigen receptor (1999) J. Cell Biol., 147, pp. 447-461; Hiltbold, E.M., Poloso, N.J., Roche, P.A., MHC class II-peptide complexes and APC lipid rafts accumulate at the immunological synapse (2003) J. Immunol., 170, pp. 1329-1338; Wülfing, C., Tskvitaria-Fuller, I., Burroughs, N., Sjaastad, M.D., Klem, J., Schatzle, J.D., Interface accumulation of receptor/ligand couples in lymphocyte activation: Methods, mechanisms, and significance (2002) Immunol. Rev., 189, pp. 64-83; Poloso, N.J., Roche, P.A., Association of MHC class II-peptide complexes with plasma membrane lipid microdomains (2004) Curr. Opin. Immunol., 16, pp. 103-107; Anderson, H.A., Hiltbold, E.M., Roche, P.A., Concentration of MHC class II molecules in lipid rafts facilitates antigen presentation (2000) Nat. Immunol., 1, pp. 156-162; Meyer Zum Bueschenfelde, C.O., Unternaehrer, J., Mellman, I., Bottomly, K., Regulated recruitment of MHC class II and costimulatory molecules to lipid rafts in dendritic cells (2004) J. Immunol., 173, pp. 6119-6124; Szollosi, J., Horejsi, V., Bene, L., Angelisova, P., Damjanovich, S., Supramolecular Complexes of MHC Class I, MHC Class II, CD20, and Tetraspan Molecules (CD53, CD81, and CD82) at the Surface of a B Cell Line JY (1996) Journal of Immunology, 157 (7), pp. 2939-2946; Leitinger, B., Hogg, N., The involvement of lipid rafts in the regulation of integrin function (2002) Journal of Cell Science, 115 (5), pp. 963-972; Cherukuri, A., Cheng, P.C., Pierce, S.K., The role of the CD19/CD21 complex in B cell processing and presentation of complement-tagged antigens (2001) J. Immunol., 167, pp. 163-172; Sheets, E.D., Holowka, D., Baird, B., Critical role for cholesterol in Lyn-mediated tyrosine phosphorylation of FcepsilonRI and their association with detergent-resistant membranes (1999) Journal of Cell Biology, 145 (4), pp. 877-887. , DOI 10.1083/jcb.145.4.877; Jordan, S., Rodgers, W., T cell glycolipid-enriched membrane domains are constitutively assembled as membrane patches that translocate to immune synapses (2003) Journal of Immunology, 171 (1), pp. 78-87; Kaizuka, Y., Douglass, A.D., Vardhana, S., Dustin, M.L., Vale, R.D., The coreceptor CD2 uses plasma membrane microdomains to transduce signals in T cells (2009) J. Cell Biol., 185, pp. 521-534; Dustin, M.L., Membrane domains and the immunological synapse: Keeping T cells resting and ready (2002) J. Clin. Invest., 109, pp. 155-160; Almeida, C.R., Davis, D.M., Segregation of HLA-C from ICAM-1 at NK cell immune synapses is controlled by its cell surface density (2006) J. Immunol., 177, pp. 6904-6910; Delon, J., The immunological synapse (2000) Curr. Biol., 10, pp. R214; Anton Van Der Merwe, P., Davis, S.J., Shaw, A.S., Dustin, M.L., Cytoskeletal polarization and redistribution of cell-surface molecules during T cell antigen recognition (2000) Semin. Immunol., 12, pp. 5-21; Bossi, G., Trambas, C., Booth, S., Clark, R., Stinchcombe, J., Griffiths, G.M., The secretory synapse: The secrets of a serial killer (2002) Immunol. Rev., 189, pp. 152-160; Endt, J., McCann, F.E., Almeida, C.R., Urlaub, D., Leung, R., Pende, D., Davis, D.M., Watzl, C., Inhibitory receptor signals suppress ligation-induced recruitment of NKG2D to GM1-rich membrane domains at the human NK cell immune synapse (2007) Journal of Immunology, 178 (9), pp. 5606-5611; Gasser, S., Raulet, D.H., Activation and self-tolerance of natural killer cells (2006) Immunol. Rev., 214, pp. 130-142; Rubio, G., Férez, X., Sánchez-Campillo, M., Gálvez, J., Martí, S., Verdú, R., Hernández-Caselles, T., García-Peñarrubia, P., Cross-linking of MHC class I molecules on human NK cells inhibits NK cell function, segregates MHC I from the NK cell synapse, and induces intracellular phosphotyrosines (2004) J. Leukoc. Biol., 76, pp. 116-124; Kaizuka, Y., Douglass, A.D., Varma, R., Dustin, M.L., Vale, R.D., Mechanisms for segregating T cell receptor and adhesion molecules during immunological synapse formation in Jurkat T cells (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 20296-20301; Brodin, P., Lakshmikanth, T., Mehr, R., Johansson, M.H., Duru, A.D., Achour, A., Salmon-Divon, M., Johansson, S., Natural killer cell tolerance persists despite significant reduction of self MHC class I on normal target cells in mice (2010) PLoS ONE, 5, pp. e1317; Carlin, L.M., Eleme, K., McCann, F.E., Davis, D.M., Intercellular transfer and supramolecular organization of human leukocyte antigen C at inhibitory natural killer cell immune synapses (2001) J. Exp. Med., 194, pp. 1507-1517; Fassett, M.S., Davis, D.M., Valter, M.M., Cohen, G.B., Strominger, J.L., Signaling at the inhibitory natural killer cell immune synapse regulates lipid raft polarization but not class I MHC clustering (2001) Proc. Natl. Acad. Sci. USA, 98, pp. 14547-14552; Faure, M., Barber, D.F., Takahashi, S.M., Jin, T., Long, E.O., Spontaneous clustering and tyrosine phosphorylation of NK cell inhibitory receptor induced by ligand binding (2003) J. Immunol., 170, pp. 6107-6114; Standeven, L.J., Carlin, L.M., Borszcz, P., Davis, D.M., Burshtyn, D.N., The actin cytoskeleton controls the efficiency of killer Ig-like receptor accumulation at inhibitory NK cell immune synapses (2004) J. Immunol., 173, pp. 5617-5625; Abeyweera, T.P., Merino, E., Huse, M., Inhibitory signaling blocks activating receptor clustering and induces cytoskeletal retraction in natural killer cells (2011) J. Cell Biol., 192, pp. 675-690; Labadia, M.E., Jeanfavre, D.D., Caviness, G.O., Morelock, M.M., Molecular regulation of the interaction between leukocyte function-associated antigen-1 and soluble ICAM-1 by divalent metal cations (1998) J. Immunol., 161, pp. 836-842; Tominaga, Y., Kita, Y., Satoh, A., Asai, S., Kato, K., Ishikawa, K., Horiuchi, T., Takashi, T., Affinity and kinetic analysis of the molecular interaction of ICAM-1 and leukocyte function-associated antigen-1 (1998) Journal of Immunology, 161 (8), pp. 4016-4022; Maenaka, K., Van Der Merwe, P.A., Stuart, D.I., Jones, E.Y., Sondermann, P., The human low affinity Fcgamma receptors IIa, IIb, and III bind IgG with fast kinetics and distinct thermodynamic properties (2001) J. Biol. Chem., 276, pp. 44898-44904; Dustin, M.L., Ferguson, L.M., Chan, P.Y., Springer, T.A., Golan, D.E., Visualization of CD2 interaction with LFA-3 and determination of the twodimensional dissociation constant for adhesion receptors in a contact area (1996) J. Cell Biol., 132, pp. 465-474; Sloan-Lancaster, J., Presley, J., Ellenberg, J., Yamazaki, T., Lippincott-Schwartz, J., Samelson, L.E., ZAP-70 association with T cell receptor zeta (TCRzeta): Fluorescence imaging of dynamic changes upon cellular stimulation (1998) J. Cell Biol., 143, pp. 613-624; Von Essen, M., Bonefeld, C.M., Siersma, V., Rasmussen, A.B., Lauritsen, J.P.H., Nielsen, B.L., Geisler, C., Constitutive and ligand-induced TCR degradation (2004) Journal of Immunology, 173 (1), pp. 384-393; Groves, J.T., Wulfing, C., Boxer, S.G., Electrical manipulation of glycan-phosphatidyl inositol-tethered proteins in planar supported bilayers (1996) Biophys. J., 71, pp. 2716-2723; Krogsgaard, M., Li, Q.J., Sumen, C., Huppa, J.B., Huse, M., Davis, M.M., Agonist/endogenous peptide-MHC heterodimers drive T cell activation and sensitivity (2005) Nature, 434, pp. 238-243; Dimasi, N., Sawicki, M.W., Reineck, L.A., Li, Y., Natarajan, K., Margulies, D.H., Mariuzza, R.A., Crystal structure of the Ly49I natural killer cell receptor reveals variability in dimerization mode within the Ly49 family (2002) J. Mol. Biol., 320, pp. 573-585; Natarajan, K., Boyd, L.F., Schuck, P., Yokoyama, W.M., Eliat, D., Margulies, D.H., Interaction of the NK cell inhibitory receptor Ly49A with H-2Dd: Identification of a site distinct from the TCR site (1999) Immunity, 11, pp. 591-601; O'Callaghan, C.A., Cerwenka, A., Willcox, B.E., Lanier, L.L., Bjorkman, P.J., Molecular competition for NKG2D: H60 and RAE1 compete unequally for NKG2D with dominance of H60 (2001) Immunity, 15, pp. 201-211; Borrego, F., Masilamani, M., Marusina, A.I., Tang, X., Coligan, J.E., The CD94/NKG2 family of receptors: From molecules and cells to clinical relevance (2006) Immunol. Res., 35, pp. 263-278
Keywords: animal cell; animal experiment; Animals; antigen recognition; article; cell maturation; cell membrane; Computer simulation; controlled study; dissociation; H-2 Antigens; Histocompatibility Antigens Class I; HLA antigen; HLA C antigen; Humans; immunological synapse; Immunological Synapses; intercellular adhesion molecule 1; Intercellular Adhesion Molecule-1; killer cell immunoglobulin like receptor 2DL1; Killer Cells, Natural; lymphocyte activation; lymphocyte function associated antigen 1; Lymphocyte Function-Associated Antigen-1; major histocompatibility antigen class 1; Membrane Microdomains; Mice; Models, Immunological; mouse; natural killer cell; natural killer cell receptor NKG2D; NK Cell Lectin-Like Receptor Subfamily A; NK Cell Lectin-Like Receptor Subfamily K; nonhuman; priority journal; protein assembly; Receptors, KIR; signal transduction; steady state; Vav protein

Access to computerised analysis of intrapartum cardiotocographs improves clinicians' prediction of newborn umbilical artery blood pH - Costa, A.; Santos, C.; Ayres-de-Campos, D.; Costa, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2010)
Objective To evaluate the impact of access to computerised cardiotocograph (CTG) analysis on reproducibility and accuracy of clinicians' predictions of umbilical artery blood pH (UAB pH) and 5-minute Apgar score. Design Prospective evaluation of pre-recorded cases. Setting A tertiary-care university hospital. Population From databases of intrapartum CTGs acquired in singleton term pregnancies, 204 tracings with low signal loss and short time interval to delivery were consecutively selected. Methods Tracings were randomly assigned to computer analysis by the Omniview-SisPorto 3.5 ® system (study group n = 104) or to no analysis (control group n = 100). Three experienced clinicians evaluated all tracing printouts independently and were asked to predict the newborns' UAB pH and 5-minute Apgar scores from them. Main outcome measures Interobserver agreement (measured by the intraclass correlation coefficient [ICC]) and accuracy in prediction of neonatal outcomes with 95% CI. Results Agreement on prediction of UAB pH was significantly higher in the study group (ICC = 0.70; 95% CI 0.61-0.77) than in the control group (ICC = 0.43; 95% CI 0.21-0.60), and a trend towards better agreement was also seen in estimation of 5-minute Apgar scores (ICC = 0.55; 95% CI 0.38-0.68 versus ICC = 0.43; 95% CI 0.25-0.57). Observers predicted UAB pH values correctly within a 0.10 margin in 70% of cases in the study group (95% CI 0.61-0.79) versus 46% in the control group (95% CI 0.35-0.56). They predicted 5-minute Apgar scores within a margin of one in 81% of cases in the study group (95% CI 0.73-0.88) and in 70% of cases in the control group (95% CI 0.61-0.79). Conclusions Prediction of UAB pH is more reproducible and accurate when clinicians have access to computerised analysis of CTGs. © RCOG 2010 BJOG An International Journal of Obstetrics and Gynaecology.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BIOGFdoi: 10.1111/j.1471-0528.2010.02645.xPubMed ID: 20618316Language of Original Document: EnglishCorrespondence Address: Costa, A.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina da Universidade Do Porto, Alameda Hernani Monteiro, 4200-319 Porto, Portugal; email: cosantonia@gmail.comReferences: Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-10;Donker, D.K., Van Geijn, H.P., Hasman, A., Interobserver variation in the assessment of fetal heart rate recordings (1993) Eur J Obstet Gynecol Reprod Biol, 52, pp. 21-8; Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-65; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-5; Ayres-De-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto ® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis (2008) J Perinat Med, 36, pp. 260-4; Costa, A., Ayres-De-Campos, D., Costa, F., Santos, C., Bernardes, J., Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals (2009) Am J Obstet Gynecol, 201, pp. 464e1-6. , Jun 17. [Epub ahead of print]; Westerhuis, M., Van Horen, E., Kwee, A., Van Dertweel, I., Visser, G., Moons, K., Inter- and intra-observer agreement of intrapartum ST analysis of the fetal electrocardiogram in women monitored by STAN (2009) BJOG, 116, pp. 545-51; Ayres-De-Campos, D., Bernardes, J., Marsalb, K., Nickelsen, C., Makarainend, L., Banfield, P., Can the reproducibility of fetal heart rate baseline estimation be improved? (2004) Eur J Obstet Gynecol Reprod Biol, 112, pp. 49-54; Huch, A., Huch, C., Rooth, G., Guidelines for blood sampling and measurement of pH and blood gas values in Obstetrics (1994) Eur J Obstet Gynecol Reprod Biol, 54, pp. 165-75; Umbilical artery blood acid-base analysis (1996) Int J Gynecol Obstet, 52, pp. 305-10. , ACOG technical bulletin; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: A time for quality data (1994) Br J Obstet Gynaecol, 101, pp. 1054-63; Costa-Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) BJOG, 112, pp. 667-9; Bland, J.M., Altman, D.G., Agreement between methods of measurement with multiple observations per individual (2007) J Biopharm Stat, 17, pp. 571-82; Chauhan, S.P., Klauser, C.K., Woodring, T.C., Sanderson, M., Magann, E.F., Morrison, J.C., Intrapartum nonreassuring fetal heart rate tracing and prediction of adverse outcomes: Interobserver variability (2008) Am J Obstet Gynecol, 199, pp. 623e1-e5; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., The value of computer assessment compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464
Keywords: access to information; Apgar score; arterial pH; article; Cardiotocography; clinical competence; computer analysis; computerised analysis; controlled study; delivery; Diagnosis, Computer-Assisted; diagnostic accuracy; Female; Fetal Blood; Fetal heart rate; Fetal monitoring; Gestational Age; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; male; neonatal acidaemia; Neonatology; newborn; observer variation; outcome assessment; prediction; Pregnancy; priority journal; Prospective Studies; prospective study; reproducibility; Umbilical Arteries; umbilical artery; university hospital

Analysis of heart rate variability in a rat model of induced pulmonary hypertension - Gonçalves, H.; Henriques-Coelho, T.; Bernardes, J.; Rocha, A.P.; Brandão-Nogueira, A.; Leite-Moreira, A. (Medical Engineering and PhysicsMed. Eng. Phys., 2010)
Monocrotaline (MCT) is commonly used to experimentally induce pulmonary hypertension (PH), which might lead to chronic heart failure. In this study, linear and non-linear heart rate (HR) dynamics were weekly assessed in MCT-treated and non-treated Wistar rats.The HR of 10 adult Wistar rats injected with MCT (MCT group) and of 10 similar rats injected with vehicle (non-MCT group), anesthetized with Ketamine, was weekly recorded during 4 weeks. The first four segments of 1-min length of each HR recording were analysed using linear, time and frequency domains, and approximate (ApEn) and sample (SampEn) entropy indices, considering recently proposed values for the threshold parameter of ApEn and SampEn. Statistical analysis was performed using 95% confidence intervals and statistical tests.Along the study period, an overall weekly maintenance of HR indices, or a decrease, namely in weeks 1-2, was manifest, in the MCT group, except for LF and LF/HF, in week 1, denoting a short-term increase in sympathetic activity without any other changes. On the other hand, a maintenance of HR indices, or an increase, namely on week 4, was observed in the non-MCT group, except for LF/HF, denoting a long-term increase of the overall activity of HR control systems, with a parasympathetic like dominance.Studies on long-term HR dynamics should be performed in very carefully controlled experimental settings, as significant weekly changes may occur, both among anesthetized MCT-treated and non-treated rats. © 2010 IPEM.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: MEPHEdoi: 10.1016/j.medengphy.2010.04.018PubMed ID: 20547091Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Geociências, Ambiente e Ordenamento do Território, Faculdade de Ciências, Universidade do Porto, Rua do Campo Alegre 687, 4169-007 Porto, Portugal; email: hernani.goncalves@fc.up.ptChemicals/CAS: monocrotaline, 315-22-0, 8051-27-2; Ketamine, 6740-88-1; Monocrotaline, 315-22-0References: (2005), ACOG, American College of Obstetricians and Gynecologists. ACOG Practice Bulletin. Clinical Management Guidelines for Obstetrician-Gynecologists, Number 70, December 2005. Obstet Gynecol 106(6):1453-60Akhavein, F., St.-Michel, E.J., Seifert, E., Rohlicek, C.V., Decreased left ventricular function, myocarditis, and coronary arteriolar medial thickening following monocrotaline administration in adult rats (2007) J Appl Physiol, 103 (1), pp. 287-295;Beckers, F., Verheyden, B., Aubert, A.E., Aging and nonlinear heart rate control in a healthy population (2006) Am J Physiol Heart Circ Physiol, 290 (6), pp. H2560-H2570; Bernardes, J., Costa-Pereira, A., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Bernardes, J., Gonçalves, H., Ayres-de-Campos, D., Rocha, A.P., Linear and complex heart rate dynamics vary with sex in relation to fetal behavioural states (2008) Early Hum Dev, 84, pp. 433-439; Bruijnzeel, A.W., Stam, R., Croiset, G., Wiegant, G.M., Long-term sensitization of cardiovascular stress responses after a single stressful experience (2001) Physiol Behav, 73 (1-2), pp. 81-86; Cerutti, C., Gustin, M.P., Paultre, C.Z., Lo, M., Julien, C., Vincent, M., Autonomic nervous-systempulmonary-edema and cardiovascular variability in rats-a spectral-analysis approach (1991) Am J Physiol, 261 (84), pp. H1292-H1299; Court, D.J., Parer, J.T., Nathanielsz, P.W., Parer, J.T., (1984) Experimental studies of fetal asphyxia and fetal heart rate interpretation Research in Perinatal Medicine, pp. 113-169. , Perinatology Press, New York; Dudewicz, E., Mishra, S., (1988) Modern mathematical statistics, , Jonh Wiley and Sons, Inc; Falcao-Pires, I., Gonçalves, N., Henriques-Coelho, T., Roncon-Albuquerque, R., Moreira-Gonçalves, D., Leite-Moreira, A.F., Administration of Apelin modulates myocardial. expression of Apelin-APJ and improves right ventricular performance in MCT-induced pulmonary hypertension (2008) Circulation, 118, pp. S285; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: the effect on linear and nonlinear parameters (2006) Physiol Meas, 27 (3), pp. 307-319; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med Biol Eng Comput, 44 (10), pp. 847-855; Gonçalves, H., Bernardes, J., Rocha, A.P., Ayres-de-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Hum Dev, 83, pp. 585-591; Gonçalves, H., Henriques-Coelho, T., Bernardes, J., Rocha, A.P., Nogueira, A., Leite-Moreira, A., Linear and nonlinear heart rate analysis in a rat model of acute anoxia (2008) Physiol Meas, 29, pp. 1133-1143; Henriques-Coelho, T., Correia-Pinto, J., Roncon-Albuquerque, R., Baptista, M.J., Lourenco, A.P., Oliveira, S.M., Endogenous production of ghrelin and beneficial effects of its exogenous administration in monocrotaline-induced pulmonary hypertension (2004) Am J Physiol Heart Circ Physiol, 287 (6), pp. H2885-H2890; Henriques-Coelho, T., Oliveira, S.M., Moura, R.S., Roncon-Albuquerque, R., Neves, A.L., Santos, M., Thymulin inhibits monocrotaline-induced pulmonary hypertension modulating interleukin-6 expression and suppressing p38 pathway (2008) Endocrinology, 149 (9), pp. 4367-4373; Hessel, M.H.M., Steendijk, P., den Adel, B., Schutte, C.I., van der Laarse, A., Characterization of right ventricular function after monocrotaline-induced pulmonary hypertension in the intact rat (2006) Am J Physiol Heart Circ Physiol, 291 (5), pp. H2424-H2430; Kuwahara, M., Yayou, K., Ishii, K., Hashimoto, S., Tsubone, H., Sugano, S., Power spectral analysis of heart rate variability as a new method for assessing autonomic activity in the rat (1994) J Electrocardiol, 27 (4), pp. 333-337; Leineweber, K., Brandt, K., Wludyka, B., Beilfuss, A., Ponicke, K., Heinroth-Hoffmann, I., Ventricular hypertrophy plus neurohumoral activation is necessary to alter the cardiac beta-adrenoceptor system in experimental heart failure (2002) Circ Res, 91 (11), pp. 1056-1062; Lourenço, A.P., Roncon-Albuquerque, R., Bras-Silva, C., Faria, B., Wieland, J., Henriques-Coelho, T., Myocardial dysfunction and neurohumoral activation without remodeling in left ventricle of monocrotaline-induced pulmonary hypertensive rats (2006) Am J Physiol Heart Circ Physiol, 291 (4), pp. H1587-H1594; Magenes, G., Signorini, M.G., Arduini, D., Cerutti, S., Fetal heart rate variability due to vibroacoustic stimulation: linear and nonlinear contribution (2004) Methods Inf Med, 43 (1), pp. 47-51; Marshall, B.E., Longnecker, D.E., General anesthetics (1996) Goodman & Gilman's. The pharmacological basis of therapeutics, , McGraw-Hill, New York, J.G. Hardman, A.G. Gilman, L.E. Limbird (Eds.); Martinez, W.L., Martinez, A.R., (2002) Computational statistics handbook with MATLAB, , CRC Press; Miller, W.C., Rice, D.L., Kreusel, R.G., Bedrossian, C.W.M., Monocrotaline model of noncardiogenic pulmonary-edema in dogs (1978) J Appl Physiol, 45 (6), pp. 962-965; Montenegro, N., Bernardes, J., Ayres-de-Campos, D., Matias, A., Areias, J.C., Monitoring of cardiac-extracardiac haemodynamics and automated fetal heart rate preceding intrauterine death (1996) Eur J Obstet Gynecol Reprod Biol, 64 (1), pp. 3-6; Moraru, L., Cimponeriu, L., Tong, S., Thakor, N., Bezerianos, A., Characterization of heart rate variability changes following asphyxia in rats (2004) Methods Inf Med, 43 (1), pp. 118-121; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Baillieres Clin Obstet Gynaecol, 8 (3), pp. 643-661; Parati, G., Mancia, G., Di Rienzo, M., Castiglioni, P., Taylor, J.A., Studinger, P., Point: Counterpoint: Cardiovascular variability is/is not an index of autonomic control of circulation (2006) J Appl Physiol, 101 (2), pp. 676-682; Pincus, S., Viscarello, R., Approximate Entropy: A regularity measure for fetal heart rate analysis (1992) Obstet Gynecol, 79, pp. 249-255; Pincus, S., Aproximate entropy (ApEn) as a complexity measure (1995) Chaos, 5, pp. 110-117; Pincus, S.M., Gevers, E.F., Robinson, I.C.A.F., VanDenBerg, G., Roelfsema, F., Hartman, M.L., Females secrete growth hormone with more process irregularity than males in both humans and rats (1996) Am J Physiol-Endocrinol Metab, 270 (1), pp. E107-E115; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Sanyal, S.N., Ono, K., Derangement of autonomic nerve control in rat with right ventricular failure (2002) Pathophysiology, 8 (3), pp. 197-203; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans Biomed Eng, 50, pp. 365-373; (1996), Task force, Heart rate variability - standards of measurement, physiological interpretation and clinical use Circulation 93 1043-65 Task force of the European Society of Cardiology and the North American Society of Pacing and ElectrophysiologyTaylor, J.A., Studinger, P., Cardiovascular variability is/is not an index of autonomic control of circulation (2006) J Appl Physiol, 101 (2), pp. 690-691; Welch, P.D., The use of Fast Fourier Transform for the estimation of power spectra: a method based on time averaging over short, modified periodograms (1967) IEEE Trans Audio Electroacous, AU-15 (2), pp. 70-73; Yum, M.K., Park, E.Y., Kim, C.R., Hwang, J.H., Alterations in irregular and fractal heart rate behavior in growth restricted fetuses (2001) Eur J Obstet Gynecol, 94, pp. 51-58
Keywords: adrenergic activity; Amines; animal experiment; animal model; Animals; article; cholinergic activity; Chronic heart failures; Confidence interval; controlled study; Disease Models, Animal; Electrocardiography; entropy; Female; Frequency domain analysis; Frequency domains; Heart; heart electrophysiology; Heart rate; Heart rate variability; Heart rate variability (HRV); Heart rates; Hypertension, Pulmonary; Injections, Subcutaneous; Ketamine; Maintenance; Monocrotaline; Non-linear; nonhuman; priority journal; Pulmonary hypertension; rat; Rat model; Rats; Rats, Wistar; Statistical analysis; statistical parameters; Sympathetic activities; Threshold parameters; Time and frequency domain analysis; Time domain analysis; Time Factors; Wistar rat; Wistar rats

Anti-adhesion and antiproliferative cellulose triacetate membrane for prevention of biomaterial-centred infections associated with Staphylococcus epidermidis - Extremina, C.I.; Fonseca, A.F.d.; Granja, P.L.; Fonseca, A.P. (International Journal of Antimicrobial AgentsInt. J. Antimicrob. Agents, 2010)
The initial step in preventing biomaterial-associated infections consists of preventing bacterial adhesion to the device surface. One possible approach is the design of antibiotic-releasing biomaterials. Cellulose triacetate (CTA) membranes with the antibiotic imipenem (IPM) entrapped (CTA-IPM) were prepared. The material was characterised in terms of surface morphology by scanning electron microscopy, surface free energy of interaction and X-ray photoelectron spectroscopy (XPS). Antibiotic release studies were also performed. In vitro adhesion of Staphylococcus epidermidis RP62A to CTA-IPM was investigated using a modified microtitre plate assay, and the antibacterial activity of the CTA-IPM membrane was assessed by a modified Kirby-Bauer test, which showed effective entrapment of the antibiotic as confirmed by XPS and hydrophilicity assays. Release studies showed that this drug-polymer conjugate serves as an adequate reservoir for sustained release of IPM over a period of 71 h at an effective bacteriostatic concentration. Moreover, bacterial adhesion tests showed a statistically significant decrease in the adhesion of S. epidermidis RP62A to CTA-IPM compared with its adhesion to CTA alone. The present innovative approach is capable of providing a membrane with anti-adhesive and antiproliferative properties, thus encouraging in vivo studies to provide a better simulation of the clinical situation. © 2009 Elsevier B.V. and the International Society of Chemotherapy.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: IAAGEdoi: 10.1016/j.ijantimicag.2009.09.017PubMed ID: 19942411Language of Original Document: EnglishCorrespondence Address: Extremina, C.I.; REQUIMTE, Faculdade de Farmácia, Universidade do Porto, Rua Aníbal Cunha 164, 4050-047 Porto, Portugal; email: extremina@gmail.comChemicals/CAS: cellulose triacetate, 9012-09-3; cilastatin plus imipenem, 92309-29-0; Anti-Bacterial Agents; Biocompatible Materials; Cellulose, 9004-34-6; Imipenem, 74431-23-5; cellulose triacetate, 9012-09-3Tradenames: tienam, Merck Sharp and Dohme, GermanyManufacturers: Eastman Kodak, Netherlands; Merck Sharp and Dohme, GermanyReferences: Darouiche, R.O., Treatment of infections associated with surgical implants (2004) N Engl J Med, 350, pp. 1422-1429;Fonseca, A.P., Extremina, C., Fonseca, A.F., Sousa, J.C., Effect of subinhibitory concentration of piperacillin/tazobactam on Pseudomonas aeruginosa (2004) J Med Microbiol, 53, pp. 903-910; Donelli, G., Francolini, I., Piozzi, A., Di Rosa, R., Marconi, W., New polymer-antibiotic systems to inhibit bacterial biofilm formation: a suitable approach to prevent central venous catheter-associated infections (2002) J Chemother, 14, pp. 501-507; Akiyama, H., Okamoto, S., Prophylaxis of indwelling urethral catheter infection: clinical experience with a modified Foley catheter and drainage system (1979) J Urol, 121, pp. 40-42; Granja, P.L., Baquey, C., Pouységu, L., Bareille, R., De Jéso, B., Barbosa, M.A., Cellulose-based biomaterials for bone regeneration: hemi-synthesis and characterisation (1996) Proceedings of polymers in medicine and surgery-PIMS'96, pp. 73-80. , Glasgow, UK; Elam, J.H., Karlsson, C.H., Nygren, H., Pre-adsorption of cellulose ether onto polymer surfaces: adsorption of adhesins and platelet activation (1992) Biomaterials, 14, pp. 233-237; Fonseca, A.P., Granja, P.L., Nogueira, J.A., Oliveira, D.R., Barbosa, M.A., Staphylococcus epidermidis RP62A adhesion to chemically modified cellulose derivatives (2001) J Mater Sci Mater Med, 12, pp. 543-548; Performance standards for antimicrobial susceptibility testing (2006) Sixteenth informational supplement. Document M100-S16. Wayne, PA: CLSI, , Clinical and Laboratory Standards Institute; Vacheethasanee, K., Temenoff, J.S., Higashi, J.M., Gary, A., Anderson, J.M., Bayston, R., Bacterial surface properties of clinically isolated Staphylococcus epidermidis strains determine adhesion on polyethylene (1998) J Biomed Mater Res, 42, pp. 425-432; Bhat, N.V., Wavhal, D.S., Preparation of cellulose triacetate pervaporation membrane by ammonia plasma treatment (2000) J Appl Polym Sci, 76, pp. 258-265; Amaral, I.F., Granja, P.L., Melo Luis, V., Saramago, B., Barbosa, M.A., Functionalization of chitosan membranes through phosphorylation: atomic force microscopy, wettability, and cytotoxicity studies (2006) J Appl Polym Sci, 102, pp. 276-284; Thomas, M.J.K., Ando, D.J., (1996) Ultraviolet and visible spectroscopy: analytical chemistry by open learning, , Wiley, New York, NY; (1992) High resolution XPS of organic polymers: the Scienta ESCA300 database, , Beamson G., and Briggs D. (Eds), John Wiley & Sons Ltd, Chichester, UK; Yigong Ge, Wikler, M.A., Sahm, D.F., Blosser-Middleton, R.S., Karlowsky, J.A., In vitro antimicrobial activity of doripenem, a new carbapenem (2004) Antimicrob Agents Chemother, 48, pp. 1384-1396; Martínez-Martínez, L., Pascual, A., Giglio, M.I., Perea, E.J., Effect of subinhibitory concentrations of β-lactams on the production of slime, surface hydrophobicity and adhesion of Staphylococcus epidermidis [in Spanish] (1991) Enferm Infecc Microbiol Clin, 9, pp. 543-546
Keywords: Adhesion; Anti-Bacterial Agents; antibacterial activity; Antimicrobial agents; article; Bacterial adhesion; bacterial growth; bacteriostasis; bacterium adherence; Biocompatible Materials; biomaterial; Cellulose; Cellulose triacetate; cilastatin plus imipenem; controlled study; device infection; drug screening; Equipment and Supplies; growth inhibition; Humans; hydrophilicity; Imipenem; in vitro study; infection prevention; Membranes; Microbial Sensitivity Tests; microtiter plate assay; nonhuman; priority journal; Prosthesis-Related Infections; Scanning electron microscopy; Staphylococcus epidermidis; surface property; sustained drug release; X ray photoelectron spectroscopy

Assessment of Disagreement: A New Information-Based Approach - Costa-Santos, C.; Antunes, L.; Souto, A.; Bernardes, J. (Annals of EpidemiologyAnn. Epidemiol., 2010)
Purpose: Disagreement on the interpretation of diagnostic tests and clinical decisions remains an important problem in medicine. As no strategy to assess agreement seems to be fail-safe to compare the degree of agreement, or disagreement, we propose a new information-based approach to assess disagreement. Methods: The sum over all logarithms of possible outcomes of a variable is a valid measure of the amount of information contained in the variable. The proposed measure is based on the amount of information contained in the differences between two observations. This measure is normalized and satisfies the flowing properties: it is a metric, scaled invariant and it has differential weighting. Results: Two real examples and a simulation were used to illustrate the usefulness of the proposed measure to compare the degree of disagreement. Conclusions: Used as complement to the existing methods, we believe our approach can be useful to compare the degree of disagreement among different populations. © 2010 Elsevier Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: ANNPEdoi: 10.1016/j.annepidem.2010.02.011Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Biostatistics and Medical Informatics Department, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: Bland, M., (2000) An introduction to medical statistics, , Oxford University Press, Oxford;Costa Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynecology: inappropriateness, controversies and consequences (2005) Br J Obstet Gynaecol, 112, pp. 667-669; Gow, R.M., Barrowman, N.J., Lai, L., Moher, D., A review of five cardiology journals found that observer variability of measured variables was infrequently reported (2008) J Clin Epidemiol, 61, pp. 394-401; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2005) J Clin Epidemiol, 58, pp. 215-216; de Vet, H., Observer reliability and agreement (1999) Encyclopedia of Biostatistics, pp. 3123-3127. , Wiley, Chichester, P. Armitage, T. Colton (Eds.); Shrout, P.E., Fleiss, J.L., Intraclass correlation: uses in assessing rater reliability (1979) Psychol Bull, 88, pp. 420-428; Burdock, E.I., Fleiss, J.L., Hardesty, A.S., A new view of interobserver agreement (1963) Psychol Bull, 16, pp. 373-384; McGraw, K.O., Wong, S.P., Forming inferences about some intraclass correlation coefficients (1996) Psychol Methods, 1, pp. 30-46; Muller, R., Buttner, P., A critical discussion of intraclass correlation coefficients (1994) Stat Med, 13, pp. 2465-2476; Steiner, D.L., Norman, G.R., (2003) Health measurements scales. A practical guide to their development and use, , Oxford University Press, Oxford; Lee, D., Koh, D., Ong, C.N., Statistical evaluation of the agreement between two methods for measuring a quantitative variable (1989) Comput Biol Med, 19, pp. 61-70; Lin, L.K., A concordance correlation coefficient to evaluate reproducibility (1989) Biometrics, 45, pp. 255-268; Nickerson, C.A.E., A note on " A Concordance Correlation Coefficient to Evaluate Reproducibility" (1997) Biometrics, 53, pp. 1503-1507; Atkinson, G., Nevill, A., Comment on the " Use of Concordance Correlation to Assess the Agreement between Two Variables" (1997) Biometrics, 53, pp. 775-777; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 1, pp. 307-310; Luiz, R.R., Costa, A.J., Kale, P.L., Werneck, G.L., Assessment of agreement of a quantitative variable: a new graphical approach (2003) J Clin Epidemiol, 56, pp. 963-967; Monti, K.L., Folded empirical distribution function curves-mountain plots (1995) Am Stat, 33, pp. 525-527; Shannon, I., A mathematical theory of communication (1948) Bell System Tech J, 27, pp. 379-423. , 623-656; Bland, J.M., Altaman, D.G., Measuring agreement in method comparison studies (1999) Stat Methods Med Res, 8, pp. 135-160
Keywords: analysis of variance; Apgar score; article; Blood Pressure Determination; blood pressure measurement; correlation coefficient; human; Humans; information science; Information Theory; intermethod comparison; mathematical computing; measurement error; medical research; metric system; Models, Statistical; observer variation; priority journal; probability; process model; reliability; Reproducibility of Results; scale up; standard; Statistical analysis; statistical model; statistics; Statistics as Topic; systolic blood pressure; validity; variance

Biocompatibility and calcification of bovine pericardium employed for the construction of cardiac bioprostheses treated with different chemical crosslink methods - Jorge-Herrero, E.; Fonseca, C.; Barge, A.P.; Turnay, J.; Olmo, N.; Fernández, P.; Lizarbe, M.A.; García Páez, J.M. (Artificial OrgansArtif. Organs, 2010)
The use of biological materials in the construction of bioprostheses requires the application of different chemical procedures to improve the durability of the material without producing any undesirable effects. A number of crosslinking methods have been tested in biological tissues composed mainly of collagen. The aim of this study was to evaluate the in vitro biocompatibility, the mechanical properties, and in vivo calcification of chemically modified bovine pericardium using glutaraldehyde acetals (GAAs) in comparison with glutaraldehyde (GA) treatment. Homsy's tests showed that the most cytotoxic treatment is GA whereas GAA treatments showed lower cytotoxicity. Regarding the mechanical properties of the modified materials, no significant differences in stress at rupture were detected among the different treatments. Zeta-Potential showed higher negative values for GA treatment (-4.9 ± 0.6 mV) compared with GAA-0.625% (-2.2 ± 0.5 mV) and GAA-1% (-2.2 ± 0.4 mV), which presented values similar to native tissue. Similar results were obtained for calcium permeability coefficients which showed the highest values for GA treatment (0.12 ± 0.02 mm 2/min), being significantly lower for GAA treatments or non-crosslinked pericardium. These results confirmed the higher propensity of the GA-treated tissues for attraction of calcium cations and were in good agreement with the calcification degree obtained after 60 days implantation into young rats, which was significantly higher for the GA group (22.70 ± 20.80 mg/g dry tissue) compared with GAA-0.625% and GAA-1% groups (0.49 ± 0.28 mg/g dry tissue and 3.51 ± 3.27 mg/g dry tissue, respectively; P < 0.001). In conclusion, GAA treatments can be considered a promising alternative to GA treatment. © 2010, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: ARORDdoi: 10.1111/j.1525-1594.2009.00978.xPubMed ID: 20633147Language of Original Document: EnglishCorrespondence Address: Jorge-Herrero, E.; Biomateriales y Telemedicina, Hospital Universitario Puerta de Hierro Majadahonda, Peine 7, planta 0, c/ Manuel de Falla 2, 28222Majadahonda, Madrid, Spain; email: ejorge.herrero@bioing.cph.esChemicals/CAS: calcium, 14092-94-5, 7440-70-2; glutaraldehyde, 111-30-8, 37245-61-7; Calcium, 7440-70-2; Cross-Linking Reagents; Glutaral, 111-30-8References: Grunkemeier, G.L., Rahimtoola, S.H., Artificial heart valves (1990) Annu Rev Med, 41, pp. 251-263;Vongpatanasin, W., Hillis, L.D., Lange, R.A., Prosthetic heart valves (1996) N Engl J Med, 335, pp. 407-416; Zilla, P., Brink, J., Human, P., Bezuidenhout, D., Prosthetic heart valves: Catering for the few (2008) Biomaterials, 29, pp. 385-406; Schoen, F.J., Levy, R.J., Heart valve bioprostheses: Antimineralization (1992) Eur J Cardiothorac Surg, 6 (1), pp. 91-3. , Suppl; Schoen, F.J., Cardiac valve prostheses: Review of clinical status and contemporary biomaterials issues (1987) J Biomed Mater Res, 21 (A1), pp. 91-117. , Suppl; Thubrikar, M.J., Deck, J.D., Aouad, J., Nolan, S.P., Role of mechanical stress in calcification of aortic bioprosthetic valves (1983) J Thorac Cardiovasc Surg, 86, pp. 115-125; Schoen, F.J., Kujovich, J.L., Levy, R.J., Sutton, M.S., Bioprosthetic valve failure (1988) Cardiovasc Clin, 18, pp. 289-317; Schoen, F.J., Tsao, J.W., Levy, R.J., Calcification of bovine pericardium used in cardiac valve bioprostheses. Implications for the mechanisms of bioprosthetic tissue mineralization (1986) Am J Pathol, 123, pp. 134-145; Ishihara, T., Ferrans, V.J., Boyce, S.W., Jones, M., Roberts, W.C., Structure and classification of cuspal tears and perforations in porcine bioprosthetic cardiac valves implanted in patients (1981) Am J Cardiol, 48, pp. 665-678; Gendler, E., Gendler, S., Nimni, M.E., Toxic reactions evoked by glutaraldehyde-fixed pericardium and cardiac valve tissue bioprosthesis (1984) J Biomed Mater Res, 18, pp. 727-736; Chanda, J., Kondoh, K., Ijima, K., Matsukawa, M., Kuribayashi, R., In vitro and in vivo calcification of vascular bioprostheses (1998) Biomaterials, 19, pp. 1651-1656; Biedrzycki, L.M., Lerner, E., Levy, R.J., Schoen, F.J., Differential calcification of cusps and aortic wall failed stented porcine bioprosthetic valves (1997) J Biomed Mater Res, 34, pp. 411-415; Jorge, H.E., Fernandez, P., Gutierrez, M., Castillo, O.J., Study of the calcification of bovine pericardium: Analysis of the implication of lipids and proteoglycans (1991) Biomaterials, 12, pp. 683-689; Arenaz, B., Maestro, M.M., Fernandez, P., Effects of periodate and chondroitin 4-sulfate on proteoglycan stabilization of ostrich pericardium. Inhibition of calcification in subcutaneous implants in rats (2004) Biomaterials, 25, pp. 3359-3368; Calero, P., Jorge-Herrero, E., Turnay, J., Gelatinases in soft tissue biomaterials. Analysis of different crosslinking agents (2002) Biomaterials, 23, pp. 3473-3478; Simionescu, A., Simionescu, D., Deac, R.F., Matrix metalloproteinases in the pathology of natural and bioprosthetic cardiac valves (1996) Cardiovasc Pathol, 5, pp. 323-332; Griffiths, L.G., Choe, L.H., Reardon, K.F., Dow, S.W., Christopher, O.E., Immunoproteomic identification of bovine pericardium xenoantigens (2008) Biomaterials, 29, pp. 3514-3520; Vesely, I., Barber, J.E., Ratliff, N.B., Tissue damage and calcification may be independent mechanisms of bioprosthetic heart valve failure (2001) J Heart Valve Dis, 10, pp. 471-477; Vesely, I., The evolution of bioprosthetic heart valve design and its impact on durability (2003) Cardiovasc Pathol, 12, pp. 277-286; Jorge-Herrero, E., Fernandez, P., De La Torre, N., Inhibition of the calcification of porcine valve tissue by selective lipid removal (1994) Biomaterials, 15, pp. 815-820; Pettenazzo, E., Valente, M., Thiene, G., Octanediol treatment of glutaraldehyde fixed bovine pericardium: Evidence of anticalcification efficacy in the subcutaneous rat model (2008) Eur J Cardiothorac Surg, 34, pp. 418-422; Nimni, M.E., Myers, D., Ertl, D., Han, B., Factors which affect the calcification of tissue-derived bioprostheses (1997) J Biomed Mater Res, 35, pp. 531-537; Jayakrishnan, A., Jameela, S.R., Glutaraldehyde as a fixative in bioprostheses and drug delivery matrices (1996) Biomaterials, 17, pp. 471-484; Eybl, E., Griesmacher, A., Grimm, M., Wolner, E., Toxic effects of aldehydes released from fixed pericardium on bovine aortic endothelial cells (1989) J Biomed Mater Res, 23, pp. 1355-1365; Levy, R.J., Schoen, F.J., Sherman, F.S., Nichols, J., Hawley, M.A., Lund, S.A., Calcification of subcutaneously implanted type i collagen sponges. Effects of formaldehyde and glutaraldehyde pretreatments (1986) Am J Pathol, 122, pp. 71-82; Golomb, G., Schoen, F.J., Smith, M.S., Linden, J., Dixon, M., Levy, R.J., The role of glutaraldehyde-induced cross-links in calcification of bovine pericardium used in cardiac valve bioprostheses (1987) Am J Pathol, 127, pp. 122-130; Huang-Lee, L.L., Cheung, D.T., Nimni, M.E., Biochemical changes and cytotoxicity associated with the degradation of polymeric glutaraldehyde derived crosslinks (1990) J Biomed Mater Res, 24, pp. 1185-1201; Southern, L.J., Hughes, H., Lawford, P.V., Clench, M.R., Manning, N.J., Glutaraldehyde-induced cross-links: A study of model compounds and commercial bioprosthetic valves (2000) J Heart Valve Dis, 9, pp. 241-248; Goissis, G., Yoshioka, S.A., Braile, D.M., Ramirez, V.D., The chemical protecting group concept applied in crosslinking of natural tissues with glutaraldehyde acetals (1998) Artif Organs, 22, pp. 210-214; Yoshioka, S.A., Goissis, G., Thermal and spectrophotometric studies of new crosslinking method for collagen matrix with glutaraldehyde acetals (2008) J Mater Sci Mater Med, 19, pp. 1215-1223; Vyavahare, N.R., Hirsch, D., Lerner, E., Prevention of calcification of glutaraldehyde-crosslinked porcine aortic cusp by ethanol preincubation: Mechanistic studies of protein structure and water-biomaterial relationship (1998) J Biomed Mater Res, 40, pp. 577-585; Triglia, D., Braa, S.S., Yonan, C., Naughton, G.K., In vitro toxicity of various classes of test agents using the neutral red assay on a human three-dimensional physiologic skin model (1991) Vitro Cell Dev Biol, 27, pp. 239-244; Plumb, J.A., Milroy, R., Kaye, S.B., Effects of the pH dependence of 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyl-tetrazolium bromide-formazan absorption on chemosensitivity determined by a novel tetrazolium-based assay (1989) Cancer Res, 49, pp. 4435-4440; Garcia Paez, J.M., Carrera, A., Cordon, A., Uniaxial and biaxial tensile strength of calf pericardium used in the construction of bioprostheses: Biomaterial selection criteria (2000) J Biomater Appl, 15, pp. 47-64; Kirby, B.J., Hasselbrink, Jr.E.F., Zeta potential of microfluidic substrates: 2. Data for polymers (2004) Electrophoresis, 25, pp. 203-213; Jorge-Herrero, E., Turnay, J., Calero, P., Calcification and identification of metalloproteinases in bovine pericardium after subcutaneous implantation in rats (2001) J Mater Sci Mater Med, 12, pp. 1013-1017; Van Wachem, P.B., Van Luyn, M.J.A., Damink, L.H.H.O., Dijkstra, P.J., Feijen, J., Nieuwenhuis, P., Tissue regenerating capacity of carbodiimide-crosslinked dermal sheep collagen during repair of the abdominal wall (1994) International Journal of Artificial Organs, 17 (4), pp. 230-239; Olde Damink, L.H.H., Dijkstra, P.J., Van Luyn, M.J.A., Van Wachem, P.B., Nieuwenhuis, P., Feijen, J., In vitro degradation of dermal sheep collagen cross-linked using a water-soluble carbodiimide (1996) Biomaterials, 17 (7), pp. 679-684. , DOI 10.1016/0142-9612(96)86737-8; Olde Damink, L.H., Dijkstra, P.J., Van Luyn, M.J., Van Wachem, P.B., Nieuwenhuis, P., Feijen, J., Cross-linking of dermal sheep collagen using a water-soluble carbodiimide (1996) Biomaterials, 17, pp. 765-773; Olde Damink, L.H.H., Dijkstra, P.J., Van Luyn, M.J.A., Van Wachem, P.B., Nieuwenhuis, P., Feijen, J., In vitro degradation of dermal sheep collagen cross-linked using a water-soluble carbodiimide (1996) Biomaterials, 17 (7), pp. 679-684. , DOI 10.1016/0142-9612(96)86737-8; Anselme, K., Petite, H., Herbage, D., Inhibition of calcification in vivo by acyl azide cross-linking of a collagen-glycosaminoglycan sponge (1992) Matrix, 12, pp. 264-273; Petite, H., Frei, V., Huc, A., Herbage, D., Use of diphenylphosphorylazide for cross-linking collagen-based biomaterials (1994) J Biomed Mater Res, 28, pp. 159-165; Petite, H., Duval, J.L., Frei, V., Abdul-Malak, N., Sigot-Luizard, M.F., Herbage, D., Cytocompatibility of calf pericardium treated by glutaraldehyde and by the acyl azide methods in an organotypic culture model (1995) Biomaterials, 16, pp. 1003-1008; Marinucci, L., Lilli, C., Guerra, M., Biocompatibility of collagen membranes crosslinked with glutaraldehyde or diphenylphosphoryl azide: An in vitro study (2003) J Biomed Mater Res, 67, pp. 504-509; Naimark, W.A., Pereira, C.A., Tsang, K., Lee, J.M., HMDC crosslinking of bovine pericardial tissue: A potential role of the solvent environment in the design of bioprosthetic materials (1995) J Mater Sci Mater Med, 6, pp. 235-241; Khouw, I.M., Van Wachem, P.B., Molema, G., Plantinga, J.A., De Leij, L.F., Van Luyn, M.J., The foreign body reaction to a biodegradable biomaterial differs between rats and mice (2000) J Biomed Mater Res, 52, pp. 439-446; Huma, P., Bezuidenhout, D., Torrianni, M., Hendriks, M., Zilla, P., Optimization of diamine bridges in glutaraldehyde treated bioprosthetic aortic wall tissue (2002) Biomaterials, 23, pp. 2099-2103; Jorge-Herrero, E., Fernandez, P., Turnay, J., Influence of different chemical cross-linking treatments on the properties of bovine pericardium and collagen (1999) Biomaterials, 20, pp. 539-545
Keywords: acetal derivative; animal cell; animal experiment; animal tissue; Animals; article; Biocompatibility; Bioprostheses; Bioprosthesis; Bovinae; Calcification; Calcification, Physiologic; Calcium; cation; Cattle; Chemical modification; controlled study; Cross-Linking Reagents; Crosslinking; Cytotoxicity; Glutaral; glutaraldehyde; heart valve bioprosthesis; Heart, Artificial; in vitro study; materials testing; mechanical stress; nonhuman; pericardium; permeability; priority journal; rat; Rats; Rattus; Subcutaneous implantation; Tissue engineering; Zeta potential

Characterization of polymeric solutions as injectable vehicles for hydroxyapatite microspheres - Oliveira, S.M.; Almeida, I.F.; Costa, P.C.; Barrias, C.C.; Ferreira, M.R.P.; Bahia, M.F.; Barbosa, M.A. (AAPS PharmSciTechAAPS PharmSciTech, 2010)
A polymeric solution and a reinforcement phase can work as an injectable material to fill up bone defects. However, the properties of the solution should be suitable to enable the transport of that extra phase. Additionally, the use of biocompatible materials is a requirement for tissue regeneration. Thus, we intended to optimize a biocompatible polymeric solution able to carry hydroxyapatite microspheres into bone defects using an orthopedic injectable device. To achieve that goal, polymers usually regarded as biocompatible were selected, namely sodium carboxymethylcellulose, hydroxypropylmethylcellulose, and Na-alginate (ALG). The rheological properties of the polymeric solutions at different concentrations were assessed by viscosimetry before and after moist heat sterilization. In order to correlate rheological properties with injectability, solutions were tested using an orthopedic device applied for minimal invasive surgeries. Among the three polymers, ALG solutions presented the most suitable properties for our goal and a non-sterile ALG 6% solution was successfully used to perform preliminary injection tests of hydroxyapatite microspheres. Sterile ALG 7.25% solution was found to closely match non-sterile ALG 6% properties and it was selected as the optimal vehicle. Finally, sterile ALG 7.25% physical stability was studied at different temperatures over a 3-month period. It was observed that its rheological properties presented minor changes when stored at 25°C or at 4°C. © 2010 American Association of Pharmaceutical Scientists.
Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1208/s12249-010-9447-3PubMed ID: 20490958Language of Original Document: EnglishCorrespondence Address: Oliveira, S. M.; Dep. de Eng. Mecânica e Gestão Industrial, Escola Superior de Tecnologia e Gestão de Viseu, Campus Politécnico de Repeses, 3504-510, Viseu, Portugal; email: soliveira@estv.ipv.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; carboxymethylcellulose, 8050-38-2, 9000-11-7, 9004-32-4, 9050-04-8; hydroxyapatite, 1306-06-5, 51198-94-8; hydroxypropylmethylcellulose, 9004-65-3; Biocompatible Materials; Capsules; Durapatite, 1306-06-5; Excipients; Polymers; Solutions; VehiclesReferences: Verlaan, J.J., Oner, F.C., Dhert, W.J., Anterior spinal column augmentation with injectable bone cements (2006) Biomat, 27 (3), pp. 290-301;Chenite, A., Chaput, C., Wang, D., Combes, C., Buschmann, M.D., Hoemann, C.D., Novel injectable neutral solutions of chitosan form biodegradable gels in situ (2000) Biomat, 21 (21), pp. 2155-2161; Hoemann, C.D., Sun, J., Legare, A., McKee, M.D., Buschmann, M.D., Tissue engineering of cartilage using an injectable and adhesive chitosan-based cell-delivery vehicle (2005) Osteoarthritis Cart., 13 (4), pp. 318-329; Balakrishnan, B., Jayakrishnan, A., Self-cross-linking biopolymers as injectable in situ forming biodegradable scaffolds (2005) Biomat, 26 (18), pp. 3941-3951; Shu, X.Z., Ghosh, K., Liu, Y., Palumbo, F.S., Luo, Y., Clark, R.A., Attachment and spreading of fibroblasts on an RGD peptidemodified injectable hyaluronan hydrogel (2004) J. Biomed. Mater. Res., 68 A (2), pp. 365-375; Shu, X.Z., Ahmad, S., Liu, Y., Prestwich, G.D., Synthesis and evaluation of injectable, in situ crosslinkable synthetic extracellular matrices for tissue engineering (2006) J. Biomed. Mater. Res. A, 79 (4), pp. 902-912; Weiss, P., Gauthier, O., Bouler, J.-M., Grimandi, G., Daculsi, G., Injectable bone substitute using a hydrophilic polymer (1999) Bone, 25 (SUPPL. 1), pp. 67S-70S. , DOI 10.1016/S8756-3282(99)00146-5, PII S8756328299001465; Trojani, C., Weiss, P., Michiels, J.F., Vinatier, C., Guicheux, J., Daculsi, G., Three-dimensional culture and differentiation of human osteogenic cells in an injectable hydroxypropylmethylcellulose hydrogel (2005) Biomat, 26 (27), pp. 5509-5517; Virto, M.R., Frutos, P., Torrado, S., Frutos, G., Gentamicin release from modified acrylic bone cements with lactose and hydroxypropylmethylcellulose (2003) Biomat, 24 (1), pp. 79-87; Bodic, F., Amouriq, Y., Gayet-Delacroix, M., Gauthier, O., Bouler, J.-M., Daculsi, G., Méthode nom invasive d'evaluation d'un substitut osseux injectable/Non-invasive evaluation of an injectable bone substitute (2002) C R Biologies, 325, pp. 345-353; Andrews, G.P., Gorman, S.P., Jones, D.S., Rheological characterisation of primary and binary interactive bioadhesive gels composed of cellulose derivatives designed as ophthalmic viscosurgical devices (2005) Biomat, 26 (5), pp. 571-580; He, S., Yaszemski, M.J., Yasko, A.W., Engel, P.S., Mikos, A.G., Injectable biodegradable polymer composites based on poly (propylene fumarate) crosslinked with poly (ethylene glycol) dimethacrylate (2000) Biomat, 21 (23), pp. 2389-2394; Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomat, 21 (23), pp. 2405-2412; Iooss, P., Le Ray, A.M., Grimandi, G., Daculsi, G., Merle, C., A new injectable bone substitute combining poly (epsilon-caprolactone) microparticles with biphasic calcium phosphate granules (2001) Biomat, 22 (20), pp. 2785-2794; Uda, H., Sugawara, Y., Nakasu, M., Experimental studies on hydroxyapatite powder-carboxymethyl chitin composite: Injectable material for bone augmentation (2006) J. Plast. Reconstr. Aesthet. Surg., 59 (2), pp. 188-196; Carrodeguas, R.G., Lasa, B.V., Barrio, J.S.D., Injectable acrylic bone cements for vertebroplasty with improved properties (2004) J. Biomed. Mater. Res. B-Appl. Biomat., 68 (1), pp. 94-104; Oliveira, S.M., Barrias, C.C., Ribeiro, C.C., Almeida, I.F., Bahia, M.F., Barbosa, M.A., Morphology and mechanical properties of injectable ceramic microspheres (2009) Key Engineering Mat., 396-398, pp. 691-694; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Key Engineering Mat., 254-256, pp. 877-880; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Preparation and characterisation of calcium-phosphate porous microspheres with a uniform size for biomedical applications (2006) J. Mater. Sci. Mater. Med., 17 (5), pp. 455-463; Oliveira, S.M., Barrias, C.C., Almeida, I.F., Costa, P.C., Ferreira, M.P., Bahia, M.F., Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gelforming ability (2008) J. Biomed. Mater. Res. B-Appl. Biomat., 87 B, pp. 49-58; Barnes, H.A., Hutton, J.F., Walters, K., (1998) An Introduction to Rheology, , Amsterdam: Elsevier Science; Leo, W.J., McLoughlin, A.J., Malone, D.M., Effects of sterilization treatments on some properties of alginate solutions and gels (1990) Biotech. Progress, 6 (1), pp. 51-53; Holme, H.K., Lindmo, K., Kristiansen, A., Smidsrød, O., Thermal depolymerization of alginate in the solid state (2003) Carbohydrate Polym., 54 (4), pp. 431-438; Bohner, M., Baroud, G., Injectability of calcium phosphate pastes (2005) Biomat, 26 (13), pp. 1553-1563; Hide, I.G., Gangi, A., Percutaneous vertebroplasty: History, technique and current perspectives (2004) Clin. Radiol., 59 (6), pp. 461-467; Lewis, G., Injectable bone cements for use in vertebroplasty and kyphoplasty: State-of-the-art review (2006) J. Biomed. Mat. Res. B-Appl. Biomat., 76 B (2), pp. 456-468; Baumann, A., Tauss, J., Baumann, G., Tomka, M., Hessinger, M., Tiesenhausen, K., Cement embolization into the vena cava and pulmonal arteries after vertebroplasty: Interdisciplinary management (2006) Europ J. Vasc. and End Surg., 31 (5), pp. 558-561; Mathis, J.M., Wong, W., Percutaneous vertebroplasty: Technical considerations (2003) J. Vasc. and Intervent Rad., 14 (8), pp. 953-960; Xu, H.H., Weir, M.D., Burguera, E.F., Fraser, A.M., Injectable and macroporous calcium phosphate cement scaffold (2006) Biomat, 27 (24), pp. 4279-4287; Gisep, A., Curtis, R., Hanni, M., Suhm, N., Augmentation of implant purchase with bone cements: An in vitro study of injectability and dough distribution (2006) J. Biomed. Mater. Res. B-Appl. Biomat., 77 (1), pp. 114-119; Krebs, J., Ferguson, S.J., Bohner, M., Baroud, G., Steffen, T., Heini, P.F., Clinical measurements of cement injection pressure during vertebroplasty (2005) Spine, 30 (5), pp. E118-E122; Draget, K.I., Skjak-Braek, G., Smidsrod, O., Alginate-based new materials (1997) Int. J. Biol. Macromol., 21 (1-2), pp. 47-55
Keywords: Alginate; alginic acid; article; Biocompatibility; Biocompatible Materials; Capsules; Carboxymethylcellulose; Drug Compounding; Durapatite; Excipients; hydroxyapatite; Hydroxypropylmethylcellulose; Injectability; injection; Injections; instrument sterilization; microsphere; Microspheres; minimally invasive surgery; molecular weight; orthopedic equipment; Polymers; priority journal; Solutions; Vehicles; viscometry

De novo expression of CD44 variants in sporadic and hereditary gastric cancer - Da Cunha, C.B.; Oliveira, C.; Wen, X.; Gomes, B.; Sousa, S.; Suriano, G.; Grellier, M.; Huntsman, D.G.; Carneiro, F.; Granja, P.L.; Seruca, R. (Laboratory InvestigationLab. Invest., 2010)
CD44 is the major ubiquitously expressed cell surface receptor for hyaluronate. The CD44 gene encodes several protein isoforms due to extensive alternative splicing and post-translational modifications. Some of these CD44 variable isoforms have been foreseen as key players in malignant transformation and their expression is highly restricted and highly specific, unlike the canonical CD44 standard isoform. In this study, we aimed at dissecting the mRNA splicing pattern of CD44 in normal stomach and gastric cancer (GC) cell lines (n9) using cloning and quantitative mRNA amplification assays. Moreover, we assessed the RNA levels and protein expression pattern of relevant splicing forms in distinct premalignant and malignant gastric lesions (sporadic (n43) and hereditary (n3) forms) using real-time RT-PCR and immunohistochemistry. We also explored the association of CD44 and E-cadherin expression by immunohistochemistry, as E-cadherin has a pivotal functional role in GC. We established the pattern of CD44 variant forms in normal stomach and gastric malignancy. We observed that although exon v6-containing isoforms were rarely expressed in normal gastric mucosa, they became increasingly expressed both in gastric premalignant (hyperplastic polyps, complete and incomplete intestinal metaplasia, low- and high-grade dysplasia) and malignant lesions (cell lines derived from GCs, primary sporadic GCs and hereditary diffuse GCs (HDGCs)). Moreover, we verified that whenever E-cadherin expression was absent, exon v6-containing CD44 isoforms were overexpressed. The lack of expression of CD44 isoforms containing exon v6 in the surface and foveolar epithelia of normal stomach and, its de novo expression in premalignant, as well as in sporadic and hereditary malignant lesions of the stomach, pinpoint CD44 v6-containg isoforms as potential biomarkers for early transformation of the gastric mucosa. Further, our results raise the hypothesis of using CD44v6 as a marker of early invasive intramucosal carcinoma in HDGC CDH1 mutation carriers that lack CDH1 expression in their tumors. © 2010 USCAP, Inc All rights reserved.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: LAINAdoi: 10.1038/labinvest.2010.155PubMed ID: 20856229Language of Original Document: EnglishCorrespondence Address: Da Cunha, C. B.; IPATIMUP, Institute of Molecular Pathology and Immunology, University of Porto, Rua Dr. Roberto Frias s/n, 4200-465 Porto, Portugal; email: rseruca@ipatimup.ptChemicals/CAS: uvomorulin, 112956-45-3; Antigens, CD44; CD44 protein, human; CD44v6 antigen; Cadherins; RNA, MessengerReferences: Aruffo, A., Stamenkovic, I., Melnick, M., CD44 is the principal cell surface receptor for hyaluronate (1990) Cell, 61, pp. 1303-1313;Screaton, G.R., Bell, M.V., Jackson, D.G., Genomic structure of DNA encoding the lymphocyte homing receptor CD44 reveals at least 12 alternatively spliced exons (1992) Proc Natl Acad Sci USA, 89, pp. 12160-12164; Ponta, H., Wainwright, D., Herrlich, P., Molecules in focus the CD44 protein family (1998) Int J Biochem Cell Biol, 30, pp. 299-305; Rudzki, Z., Jothy, S., CD44 and the adhesion of neoplastic cells (1997) Mol Pathol, 50, pp. 57-71; Shtivelman, E., Bishop, J.M., Expression of CD44 is repressed in neuroblastoma cells (1991) Mol Cell Biol, 11, pp. 5446-5453; De Marzo, A.M., Bradshaw, C., Sauvageot, J., CD44 and CD44v6 downregulation in clinical prostatic carcinoma: Relation to Gleason grade and cytoarchitecture (1998) Prostate, 34, pp. 162-168; Joensuu, H., Klemi, P.J., Toikkanen, S., Glycoprotein CD44 expression and its association with survival in breast cancer (1993) Am J Pathol, 143, pp. 867-874; Friedrichs, K., Kugler, G., Franke, F., CD44 isoforms in prognosis of breast cancer (1995) Lancet, 345, p. 1237; Kaufmann, M., Heider, K.H., Sinn, H.P., CD44 variant exon epitopes in primary breast cancer and length of survival (1995) Lancet, 345, pp. 615-619; Mulder, J.W., Kruyt, P.M., Sewnath, M., Colorectal cancer prognosis and expression of exon-v6-containing CD44 proteins (1994) Lancet, 344, pp. 1470-1472; Wielenga, V.J., Heider, K.H., Offerhaus, G.J., Expression of CD44 variant proteins in human colorectal cancer is related to tumor progression (1993) Cancer Res, 53, pp. 4754-4756; Terpe, H.J., Koopmann, R., Imhof, B.A., Expression of integrins and CD44 isoforms in non-Hodgkin's lymphomas: CD44 variant isoforms are preferentially expressed in high-grade malignant lymphomas (1994) J Pathol, 174, pp. 89-100; Takaishi, S., Okumura, T., Tu, S., Identification of gastric cancer stem cells using the cell surface marker CD44 (2009) Stem Cells, 27, pp. 1006-1020; Heider, K.-H., Dammrich, J., Skroch-Angel, P., Differential EXpression of CD44 splice variants in intestinal-and diffuse-type human gastric carcinomas and normal gastric mucosa (1993) Cancer Res, 53, pp. 4197-4203; Mayer, B., Jauch, K.W., Gunthert, U., De-novo expression of CD44 and survival in gastric cancer (1993) Lancet, 342, pp. 1019-1022; Muller, W., Schneiders, A., Heider, K.H., Expression and prognostic value of the CD44 splicing variants v5 and v6 in gastric cancer (1997) J Pathol, 183, pp. 222-227; Mirecka, J., Marx, D., Schauer, A., Immunohistochemical localization of CD44 variants 5 and 6 in human gastric mucosa and gastric cancer (1995) Anticancer Res, 15, pp. 1459-1465; Heider, K.H., Dammrich, J., Skroch-Angel, P., Differential expression of CD44 splice variants in intestinal-and diffuse-type human gastric carcinomas and normal gastric mucosa (1993) Cancer Res, 53, pp. 4197-4203; Hong, R.L., Lee, W.J., Shun, C.T., Expression of CD44 and its clinical implication in diffuse-type and intestinal-type gastric adenocarcinomas (1995) Oncology, 52, pp. 334-339; Ghaffarzadehgan, K., Jafarzadeh, M., Raziee, H.R., Expression of cell adhesion molecule CD44 in gastric adenocarcinoma and its prognostic importance (2008) World J Gastroenterol, 14, pp. 6376-6381; Carneiro, F., Huntsman, D.G., Smyrk, T.C., Model of the early development of diffuse gastric cancer in E-cadherin mutation carriers and its implications for patient screening (2004) J Pathol, 203, pp. 681-687; Suriano, G., Mulholland, D., De Wever, O., The intracellular E-cadherin germline mutation V832M lacks the ability to mediate cell-cell adhesion and to suppress invasion (2003) Oncogene, 22, pp. 5716-5719; Suriano, G., Oliveira, C., Ferreira, P., Identification of CDH1 germline missense mutations associated with functional inactivation of the E-cadherin protein in young gastric cancer probands (2003) Hum Mol Genet, 12, pp. 575-582; Suriano, G., Oliveira, M.J., Huntsman, D., E-cadherin germline missense mutations and cell phenotype: Evidence for the independence of cell invasion on the motile capabilities of the cells (2003) Hum Mol Genet, 12, pp. 3007-3016; Oliveira, C., Bordin, M.C., Grehan, N., Screening E-cadherin in gastric cancer families reveals germline mutations only in hereditary diffuse gastric cancer kindred (2002) Hum Mutat, 19, pp. 510-517; MacHado, J.C., Oliveira, C., Carvalho, R., E-cadherin gene (CDH1) promoter methylation as the second hit in sporadic diffuse gastric carcinoma (2001) Oncogene, 20, pp. 1525-1528; Huntsman, D.G., Carneiro, F., Lewis, F.R., Early gastric cancer in young, asymptomatic carriers of germ-line E-cadherin mutations (2001) N Engl J Med, 344, pp. 1904-1909; Carneiro, F., MacHado, J.C., Seruca, R., E-cadherin changes in gastric carcimona (1999) Histopathology, 35, pp. 477-478; Mateus, A.R., Simoes-Correia, J., Figueiredo, J., E-cadherin mutations and cell motility: A genotype-phenotype correlation (2009) Exp Cell Res, 315, pp. 1393-1402; Oliveira, C., Senz, J., Kaurah, P., Germline CDH1 deletions in hereditary diffuse gastric cancer families (2009) Hum Mol Genet, 18, pp. 1545-1555; Oliveira, C., Sousa, S., Pinheiro, H., Quantification of epigenetic and genetic second hits in CDH1 during hereditary diffuse gastric cancer syndrome progression (2009) Gastroenterology, 136, pp. 2137-2148; Lynch, H.T., Grady, W., Suriano, G., Gastric cancer: New genetic developments (2005) J Surg Oncol, 90, pp. 114-133. , discussion 133; Lauren, P., The two histological main types of gastric carcinoma: Diffuse and so-called intestinal-type carcinoma. An attempt at a histo-clinical classification (1965) Acta Pathol Microbiol Scand, 64, pp. 31-49; Filipe, M.I., Jass, J.R., Intestinal metaplasia subtypes and cancer risk (1986) Gastric Carcinoma, pp. 87-115. , Filipe MI, Jass JR (eds). Churchill Livingstone, London; Sato, S., Yokozaki, H., Yasui, W., Silencing of the CD44 gene by CpG methylation in a human gastric carcinoma cell line (1999) Jpn J Cancer Res, 90, pp. 485-489; Guilford, P.H.J., Harraway, J., McLeod, M., E-cadherin germline mutations in familial gastric cancer (1998) Nature, 26, p. 6674; Günthert, U., Hofmann, M., Rudy, W., A new variant of glycoprotein CD44 confers metastatic potential to rat carcinoma cells (1991) Cell, 65, pp. 13-24; Vr, O., Chen, L., Sleeman, J.P., CD44 is required for two consecutive steps in HGF/c-Met signaling (2002) Genes Dev, 16, pp. 3074-3086; Spk, D., Stefan, M., Wels, C., HGF-Promoted Motility in Primary Melanocytes Depends on CD44v6 Regulated via NF-kappa B, Egr-1, and C/EBP-beta (2010) J Investig Dermatol, 130, pp. 1893-1903; Mielgo, A., Van Driel, M., Bloem, A., A novel antiapoptotic mechanism based on interference of Fas signaling by CD44 variant isoforms (2006) Cell Death Differ, 13, pp. 465-477; Marhaba, R., Bourouba, M., Zoller, M., CD44v6 promotes proliferation by persisting activation of MAP kinases (2005) Cell Signal, 17, pp. 961-973; Bates, R.C., Edwards, N.S., Burns, G.F., A CD44 survival pathway triggers chemoresistance via lyn kinase and phosphoinositide 3-kinase/Akt in colon carcinoma cells (2001) Cancer Res, 61, pp. 5275-5283; Carvalho, R., Milne, A.N., Polak, M., A novel region of amplification at 11p12-13 in gastric cancer, revealed by representational difference analysis, is associated with overexpression of CD44v6, especially in early-onset gastric carcinomas (2006) Genes Chromosomes Cancer, 45, pp. 967-975; Heider, K.H., Hofmann, M., Hors, E., A human homologue of the rat metastasis-associated variant of CD44 is expressed in colorectal carcinomas and adenomatous polyps (1993) J Cell Biol, 120, pp. 227-233; Gulmann, C., Grace, A., Leader, M., CD44v6: A potential marker of malignant transformation in intestinal metaplasia of the stomach? An immunohistochemical study using tissue microarrays (2003) Eur J Gastroenterol Hepatol, 15, pp. 981-986; Wimmel, A., Kogan, E., Ramaswamy, A., Variant expression of CD44 in preneoplastic lesions of the lung (2001) Cancer, 92, pp. 1231-1236; Afify, A.M., Craig, S., Paulino, A.F., Expression of hyaluronic acid and its receptors, CD44s and CD44v6, in normal, hyperplastic, and neoplastic endometrium (2005) Ann Diagn Pathol, 9, pp. 312-318; Soon Cheol, H., Jae Yun, S., Jae Kwan, L., Significance of CD44v6 expression in gynecologic malignancies (2006) J Obstet Gynaecol Res, 32, pp. 379-386; Afify, A., Ma, M., Braggin, J., Expression of CD44s, CD44v6, and hyaluronan across the spectrum of normal-hyperplasia-carcinoma in breast (2008) Appl Immunohistochem Mol Morphol, 16, pp. 121-127; Judd, L.M., Andriga, A., Rubio, C.A., Gastric achlorhydria in H/K-ATPase-deficient (Atp4a(-/-)) mice causes severe hyperplasia, muco-cystic metaplasia and upregulation of growth factors (2005) J Gastroenterol Hepatol, 20, pp. 1266-1278; Liu, Y.J., Yan, P.S., Li, J., Expression and significance of CD44 s, CD44v6, and nm23 mRNA in human cancer (2005) World J Gastroenterol, 11, pp. 6601-6606; Polkowski, W.P., Skomra, D.G., Mielko, J., E-cadherin expression as predictive marker of proximal resection line involvement for advanced carcinoma of the gastric cardia (2004) E J Surg Oncol, 30, pp. 1084-1092; Seiter, S.A.R., Reber, S., Komitowski, D., Prevention of tumor metastasis formation by anti-variant CD44 (1993) J Experiment Med, 177, pp. 443-455; Reeder, J.A., Gotley, D.C., Walsh, M.D., Expression of ANTisense CD44 variant 6 inhibits colorectal tumor metastasis and tumor growth in a wound environment (1998) Cancer Res, 58, pp. 3719-3726; Nishii, T., Yashiro, M., Shinto, O., Cancer stem cell-like SP cells have a high adhesion ability to the peritoneum in gastric carcinoma (2009) Cancer Sci, 100, pp. 1397-1402; Carneiro, F., Huntsman, D.G., Smyrk, T.C., Model of the early development of diffuse gastric cancer in E-cadherin mutation carriers and its implications for patient screening (2004) J Pathol, 203, pp. 681-687; Pdp, P., Guilford, P., Caldas, C., The International Gastric Cancer Linkage C. Incidence of gastric cancer and breast cancer in CDH1 (E-cadherin) mutation carriers from hereditary diffuse gastric cancer families (2001) Gastroenterology, 121, pp. 1348-1353; Humar, B., Fukuzawa, R., Blair, V., Destabilized adhesion in the gastric proliferative zone and c-Src kinase activation mark the development of early diffuse gastric cancer (2007) Cancer Res, 67, pp. 2480-2489; Ferrari, M., Cancer nanotechnology: Opportunities and challenges (2005) Nat Rev Cancer, 5, pp. 161-171; Yww, W., Chen, Y., Huang, K., The investigation of polymer-siRNA nanoparticle for gene therapy of gastric cancer in vitro (2010) Int J Nanomed, 5, pp. 129-136
Keywords: Alternative Splicing; Antigens, CD44; article; Cadherins; CD44; CD44v6; CD44v6 antigen; CD44v7 antigen; Cell Line, Tumor; clinical article; controlled study; E-cadherin; familial cancer; Gastric Mucosa; Germ-Line Mutation; HDGC; Hermes antigen; human; human tissue; Humans; immunohistochemistry; intestine metaplasia; messenger RNA; Neoplasm Metastasis; priority journal; protein expression; real time polymerase chain reaction; reverse transcription polymerase chain reaction; RNA splicing; RNA, Messenger; splicing; sporadic GC; stomach; stomach cancer; stomach mucosa; Stomach Neoplasms; stomach polyp; tumor marker; unclassified drug; uvomorulin

Dynamic cell-cell interactions between cord blood haematopoietic progenitors and the cellular niche are essential for the expansion of CD34 +, CD34 +CD38 - Da Silva, C.L.; Gonçalves, R.; Dos Santos, F.; Andrade, P.Z.; Almeida-Porada, G.; Cabral, J.M.S. (Journal of Tissue Engineering and Regenerative MedicineJ. Tissue Eng. Regenerative Med., 2010)
Most clinical applications of haematopoietic stem/progenitor cells (HSCs) would benefit from their ex vivo expansion to obtain a therapeutically significant amount of cells from the available donor samples. We studied the impact of cellular interactions between umbilical cord blood (UCB) haematopoietic cells and bone marrow (BM)-derived mesenchymal stem cells (MSCs) on the ex vivo expansion and differentiative potential of UCB CD34 +-enriched cells. UCB cells were cultured: (a) directly in contact with BM MSC-derived stromal layers (contact); (b) separated by a microporous membrane (non-contact); or (c) without stroma (no stroma). Highly dynamic culture events occurred in HSC-MSC co-cultures, involving cell-cell interactions, which preceded HSC expansion. Throughout the time in culture [18 days], total cell expansion was significantly higher in contact (fold increase of 280 ± 37 at day 18) compared to non-contact (85 ± 25). No significant cell expansion was observed in stroma-free cultures. CD34 + cell expansion was also clearly favoured by direct contact with BM MSCs (35 ± 5- and 7 ± 3-fold increases at day 18 for contact and non-contact, respectively). Moreover, a higher percentage of CD34 +CD38
Cited By (since 1996): 8Export Date: 21 November 2012Source: Scopusdoi: 10.1002/term.226PubMed ID: 19937912Language of Original Document: EnglishCorrespondence Address: Da Silva, C. L.; IBB-Institute for Biotechnology and Bioengineering, Centre for Biological and Chemical Engineering, Instituto Superior Técnico, Avenida Rovisco Pais, 1049-001 Lisbon, Portugal; email: claudialobato@ist.utl.ptChemicals/CAS: Antigens, CD34; Antigens, CD38, 3.2.2.5; Antigens, CD7; SuspensionsReferences: Alakel, N., Jing, D., Muller, K., Direct contact with mesenchymal stromal cells affects migratory behavior and gene expression profile of CD133 + hematopoietic stem cells during ex vivo expansion (2009) Exp Hematol, 37 (4), pp. 504-513;Almeida-Porada, G., Brown, R.L., MacKintosh, F.R., Evaluation of serum-free culture conditions able to support the ex vivo expansion and engraftment of human hematopoietic stem cells in the human-to-sheep xenograft model (2000) J Hematother Stem Cell Res, 9 (5), pp. 683-693; Ando, K., Nakamura, Y., Chargui, J., Extensive generation of human cord blood CD34 + stem cells from Lin -CD34 - cells in a long-term in vitro system (2000) Exp Hematol, 28 (6), pp. 690-699; Bernstein, I.D., Boyd, R.L., van den Brink, M.R., Clinical strategies to enhance posttransplant immune reconstitution (2008) Biol Blood Marrow Transpl, 14 (1 and SUPPL. 1), pp. 94-99; Bilko, N.M., Votyakova, I.A., Vasylovska, S.V., Characterization of the interactions between stromal and haematopoietic progenitor cells in expansion cell culture models (2005) Cell Biol Int, 29 (1), pp. 83-86; Breems, D.A., Blokland, E.A., Siebel, K.E., Stroma contact prevents loss of hematopoietic stem cell quality during ex vivo expansion of CD34 + mobilized peripheral blood stem cells (1998) Blood, 91 (1), pp. 111-117; Cheng, X., Macvittie, T., Meisenberg, B., Human brain endothelial cells (HUBEC) promote SCID repopulating cell expansion through direct contact (2007) Growth Factors, 25 (3), pp. 141-150; Corre, J., Planat-Benard, V., Corberand, J., Human bone marrow adipocytes support complete myeloid and lymphoid differentiation from human CD34 + cells (2004) Br J Haematol, 127 (3), pp. 344-347; da Silva, C.L., Goncalves, R., Crapnell, K.B., A human stromal-based serum-free culture system supports the ex vivo expansion/maintenance of bone marrow and cord blood hematopoietic stem/progenitor cells (2005) Exp Hematol, 33 (7), pp. 828-835; da Silva, C.L., Goncalves, R., Porada, C.D., Differences amid bone marrow and cord blood hematopoietic stem/progenitor cell division kinetics (2009) J Cell Physiol, , DOI: 10.1002/jcp.21736; de Lima, M., Shpall, E., Strategies for widening the use of cord blood in hematopoietic stem cell transplantation (2006) Haematologica, 91 (5), pp. 584-587; Foguenne, J., Di Stefano, I., Giet, O., Ex vivo expansion of hematopoietic progenitor cells is associated with downregulation of α4 integrin- and CXCR4-mediated engraftment in NOD/SCID β2-microglobulin-null mice (2009) Haematologica, 94 (2), pp. 185-194; Freund, D., Bauer, N., Boxberger, S., Polarization of human hematopoietic progenitors during contact with multipotent mesenchymal stromal cells: Effects on proliferation and clonogenicity (2006) Stem Cells Dev, 15 (6), pp. 815-829; Frias, A.M., Porada, C.D., Crapnell, K.B., Generation of functional natural killer and dendritic cells in a human stromal-based serum-free culture system designed for cord blood expansion (2008) Exp Hematol, 36 (1), pp. 61-68; Goncalves, R., Lobato da Silva, C., Cabral, J.M.S., A Stro-1 + human universal stromal feeder layer to expand/maintain human bone marrow hematopoietic stem/progenitor cells in a serum-free culture system (2006) Exp Hematol, 34 (10), pp. 1353-1359; Gordon, M.Y.M.S., Davidson, R.J., Grand, F.H., Contact-mediated inhibition of human hematopoietic progenitor cell proliferationmay be conferred by stem cell antigen, CD34 (2000) Hematol J, 1, pp. 77-86; Hao, Q.L., Zhu, J., Price, M.A., Identification of a novel, human multilymphoid progenitor in cord blood (2001) Blood, 97 (12), pp. 3683-3690; Haylock, D.N., Nilsson, S.K., Osteopontin: A bridge between bone and blood (2006) Br J Haematol, 134 (5), pp. 467-474; Hidalgo, A., Robledo, M.M., Teixido, J., CD44-mediated hematopoietic progenitor cell adhesion and its complex role in myelopoiesis (2002) J Hematother Stem Cell Res, 11 (3), pp. 539-547; Hofmeister, C.C., Zhang, J., Knight, K.L., Ex vivo expansion of umbilical cord blood stem cells for transplantation: Growing knowledge from the hematopoietic niche (2007) Bone Marrow Transpl, 39 (1), pp. 11-23; Jones, P., May, G., Healy, L., Stromal expression of Jagged 1 promotes colony formation by fetal hematopoietic progenitor cells (1998) Blood, 92 (5), pp. 1505-1511; Katayama, Y., Frenette, P.S., Galactocerebrosides are required postnatally for stromal-dependent bone marrow lymphopoiesis (2003) Immunity, 18 (6), pp. 789-800; Kawada, H., Ando, K., Tsuji, T., Rapid ex vivo expansion of human umbilical cord hematopoietic progenitors using a novel culture system (1999) Exp Hematol, 27 (5), pp. 904-915; Kilroy, G.E., Foster, S.J., Wu, X., Cytokine profile of human adipose-derived stem cells: Expression of angiogenic, hematopoietic, and pro-inflammatory factors (2007) J Cell Physiol, 212 (3), pp. 702-709; Kim, J.A., Kang, Y.J., Park, G., Identification of a stromamediated Wnt/β-catenin signal promoting self-renewal of hematopoietic stem cells in the stem cell niche (2009) Stem Cells, 27 (6), pp. 1318-1329; Koller, M.R., Oxender, M., Jensen, T.C., Direct contact between CD34 +lin - cells and stroma induces a soluble activity that specifically increases primitive hematopoietic cell production (1999) Exp Hematol, 27 (4), pp. 734-741; Lewis, I.D., Almeida-Porada, G., Du, J., Umbilical cord blood cells capable of engrafting in primary, secondary, and tertiary xenogeneic hosts are preserved after ex vivo culture in a noncontact system (2001) Blood, 97 (11), pp. 3441-3449; Li, N., Feugier, P., Serrurrier, B., Human mesenchymal stem cells improve ex vivo expansion of adult human CD34 + peripheral blood progenitor cells and decrease their allostimulatory capacity (2007) Exp Hematol, 35 (3), pp. 507-515; Li, Y.P., Paczesny, S., Lauret, E., Human mesenchymal stem cells license adult CD34 + hemopoietic progenitor cells to differentiate into regulatory dendritic cells through activation of the Notch pathway (2008) J Immunol, 180 (3), pp. 1598-1608; Loeuillet, C., Bernard, G., Remy-Martin, J., Distinct hematopoietic support by two human stromal cell lines (2001) Exp Hematol, 29 (6), pp. 736-745; Mayani, H., Lansdorp, P.M., Biology of human umbilical cord blood-derived hematopoietic stem/progenitor cells (1998) Stem Cells, 16 (3), pp. 153-165; McKenzie, J.L., Gan, O.I., Doedens, M., Reversible cell surface expression of CD38 on CD34-positive human hematopoietic repopulating cells (2007) Exp Hematol, 35 (9), pp. 1429-1436; Moore, K.A., Lemischka, I.R., Stem cells and their niches (2006) Science, 311 (5769), pp. 1880-1885; Nolta, J.A., Smogorzewska, E.M., Kohn, D.B., Analysis of optimal conditions for retroviral-mediated transduction of primitive human hematopoietic cells (1995) Blood, 86 (1), pp. 101-110; Oostendorp, R.A., Robin, C., Steinhoff, C., Long-term maintenance of hematopoietic stem cells does not require contact with embryo-derived stromal cells in cocultures (2005) Stem Cells, 23 (6), pp. 842-851; Oritani, K., Wu, X., Medina, K., Antibody ligation of CD9 modifies production of myeloid cells in long-term cultures (1996) Blood, 87 (6), pp. 2252-2261; Sadlon, T.J., Lewis, I.D., D'Andrea, R.J., BMP4: Its role in development of the hematopoietic system and potential as a hematopoietic growth factor (2004) Stem Cells, 22 (4), pp. 457-474; Shih, C.C., Hu, M.C.T., Hu, J., Long-term ex vivo maintenance and expansion of transplantable human hematopoietic stem cells (1999) Blood, 94 (5), pp. 1623-1636; Shpall, E.J., Quinones, R., Giller, R., Transplantation of ex vivo expanded cord blood (2002) Biol Blood Marrow Transpl, 8 (7), pp. 368-376; Suzuki, T., Yokoyama, Y., Kumano, K., Highly efficient ex vivo expansion of human hematopoietic stem cells using Δ1-Fc chimeric protein (2006) Stem Cells, 24 (11), pp. 2456-2465; Verfaillie, C.M., Direct contact between human primitive hematopoietic progenitors and bone marrow stroma is not required for long-term in vitro hematopoiesis (1992) Blood, 79 (11), pp. 2821-2826; Wagner, W., Wein, F., Roderburg, C., Adhesion of hematopoietic progenitor cells to human mesenchymal stem cells as a model for cell-cell interaction (2007) Exp Hematol, 35 (2), pp. 314-325; Yin, T., Li, L., The stem cell niches in bone (2006) J Clin Invest, 116 (5), pp. 1195-1201; Zhang, C.C., Kaba, M., Iizuka, S., Angiopoietin-like 5 and IGFBP2 stimulate ex vivo expansion of human cord blood hematopoietic stem cells as assayed by NOD/SCID transplantation (2008) Blood, 111 (7), pp. 3415-3423; Zhang, Y., Chai, C., Jiang, X.S., Co-culture of umbilical cord blood CD34 + cells with human mesenchymal stem cells (2006) Tissue Eng, 12 (8), pp. 2161-2170
Keywords: Antigens, CD34; Antigens, CD38; Antigens, CD7; article; Bone marrow microenvironment; CD34 antigen; CD38 antigen; CD7 antigen; cell adhesion; Cell Communication; cell contact; Cell culture; cell differentiation; cell interaction; cell proliferation; Cells, Cultured; cellular distribution; clonogenic assay; coculture; Coculture Techniques; Colony-Forming Units Assay; controlled study; Ex vivo expansion; ex vivo study; Fetal Blood; flow cytometry; Haematopoietic stem/progenitor cells; hematopoietic stem cell; Hematopoietic Stem Cells; human; human cell; Humans; Lymphocytes; lymphoid cell; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Electron, Scanning; phenotype; priority journal; Scanning electron microscopy; somatic gene therapy; stem cell expansion; Stem Cell Niche; stroma cell; Suspensions; umbilical cord blood

The effect of immobilization of thrombin inhibitors onto self-assembled monolayers on the adsorption and activity of thrombin - Freitas, S.C.; Barbosa, M.A.; Martins, M.C.L. (BiomaterialsBiomaterials, 2010)
Thrombus formation is the major problem associated with biomaterials for blood contact medical devices. The immobilization of inhibitors to thrombin, a serine protease that plays a central role on the coagulation system, on the surface of biomaterials should be a good strategy to avoid blood clotting and increase their hemocompatibility. The aim of this work is the design of a nanostructured surface with capacity to adsorb and inactivate thrombin. The pentapeptide sequence d-Phenylalanine-Proline-Arginine-Proline-Glycine (fPRPG), that was described as a thrombin inhibitor, was immobilized onto tetra(ethylene glycol) terminated self-assembled monolayers (EG4-SAMs). Surface containing different amounts of fPRPG were prepared using different concentrations of N,N′-Carbonyldiimidazole (CDI) during immobilization. The efficiency of fPRPG immobilization was followed using ellipsometry, contact angle measurements, Infrared reflection absorption spectroscopy (IRRAS) and X-ray photoelectron spectroscopy (XPS). Thrombin adsorption was quantified using radiolabelled thrombin and its activity in solution and after adsorption on the developed surfaces was assessed using a chromogenic assay. It was found that, although the immobilization of fPRPG on to EG4-SAMs does not increase its selectivity to thrombin, the activity of the adsorbed thrombin was inhibited in a peptide concentration dependent way. We concluded that SAMs with fPRPG immobilized in high amounts can be used as thrombin-inhibitor surfaces, which is a good step on the development of new surfaces for blood contact devices. © 2010 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2010.01.097PubMed ID: 20153046Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: thrombin, 9002-04-4; Albumins; Gold, 7440-57-5; Immobilized Proteins; Iodine Radioisotopes; Peptides; Solutions; Thrombin, 3.4.21.5References: Gorbet, M.B., Sefton, M.V., Biomaterial-associated thrombosis: roles of coagulation factors, complement, platelets and leukocytes (2004) Biomaterials, 25 (26), pp. 5681-5703;Ratner, B.D., Hoffman, A.F., Schoen, F.J., Lemons, J.L., (2004) Biomaterials science - an introduction to materials in medicine. 2nd ed., , Elsevier Academic Press, San Diego, CA, USA; Bode, W., Structure and interaction modes of thrombin (2006) Blood Cells Mol Dis, 36 (2), pp. 122-130; Huntington, J.A., Molecular recognition mechanisms of thrombin (2005) J Thromb Haemost, 3 (8), pp. 1861-1872; Schwienhorst, A., Direct thrombin inhibitors - a survey of recent developments (2006) Cell Mol Life Sci, 63 (23), pp. 2773-2791; Tseng, P.-Y., Rele, S.S., Sun, X.-L., Chaikof, E.L., Membrane-mimetic films containing thrombomodulin and heparin inhibit tissue factor-induced thrombin generation in a flow model (2006) Biomaterials, 27 (12), pp. 2637-2650; Sperling, C., Salchert, K., Streller, U., Werner, C., Covalently immobilized thrombomodulin inhibits coagulation and complement activation of artificial surfaces in vitro (2004) Biomaterials, 25 (21), pp. 5101-5113; Lin, J.C., Tseng, S.M., Surface characterization and platelet adhesion studies on polyethylene surface with hirudin immobilization (2001) J Mater Sci Mater Med, 12 (9), pp. 827-832; Wendel, H.P., Ziemer, G., Coating-techniques to improve the hemocompatibility of artificial devices used for extracorporeal circulation (1999) Eur J Cardiothorac Surg, 16 (3), pp. 342-350; Werner, C., Maitz, M.F., Sperling, C., Current strategies towards hemocompatible coatings (2007) J Mater Chem, 17 (32), pp. 3376-3384; Weitz, J.I., Crowther, M., Direct thrombin inhibitors (2002) Thromb Res, 106 (3), pp. V275-V284; Di Nisio, M., Middeldorp, S., Büller, H.R., Direct thrombin inhibitors (2005) N Engl J Med, 353 (10), pp. 1028-1040; Stone, S.R., Hofsteenge, J., Kinetics of the inhibition of thrombin by hirudin (1986) Biochemistry, 25 (16), pp. 4622-4628; Grutter, M.G., Priestle, J., Rahuel, J., Grossenbacher, H., Bode, W., Hofsteenge, J., Crystal structure of the thrombin-hirudin complex: a novel mode of serine protease inhibition (1990) EMBO J, 9 (8), pp. 2361-2365; Lahann, J., Plüster, W., Klee, D., Gattner, H.G., Höcker, H., Immobilization of the thrombin inhibitor r-hirudin conserving its biological activity (2001) J Mater Sci Mater Med, 12 (9), pp. 807-810; Phaneuf, M.D., Berceli, S.A., Bide, M.J., Quist, W.C., LoGerfo, F.W., Covalent linkage of recombinant hirudin to poly(ethylene terephthalate) (Dacron): creation of a novel antithrombin surface (1997) Biomaterials, 18 (10), pp. 755-765; Wyers, M.C., Phaneuf, M.D., Rzucidlo, E.M., Contreras, M.A., Logerfo, F.W., Quist, W.C., In vivo assessment of a novel Dacron surface with covalently bound recombinant hirudin (1999) Cardiovasc Pathol, 8 (3), pp. 153-159; Maraganore, J.M., Bourdon, P., Jablonski, J., Ramachandran, K.L., Fenton Ii, J.W., Design and characterization of hirulogs: a novel class of bivalent peptide inhibitors of thrombin (1990) Biochemistry, 29 (30), pp. 7095-7101; Maraganore, J.M., Chao, B., Joseph, M.L., Jablonski, J., Ramachandran, K.L., Anticoagulant activity of synthetic hirudin peptides (1989) J Biol Chem, 264 (15), pp. 8692-8698; Sun, X., Sheardown, H., Tengvall, P., Brash, J.L., Peptide modified gold-coated polyurethanes as thrombin scavenging surfaces (2000) J Biomed Mater Res, 49 (1), pp. 66-78; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111 (1), pp. 321-335; Herrwerth, S., Eck, W., Reinhardt, S., Grunze, M., Factors that determine the protein resistance of oligoether self-assembled monolayers - internal hydrophilicity, terminal hydrophilicity, and lateral packing density (2003) J Am Chem Soc, 125 (31), pp. 9359-9366; Lottenberg, R., Christensen, U., Jackson, C.M., Coleman, P.L., Assay of coagulation proteases using peptide chromogenic and fluorogenic substrates (1981) Meth Enzymol, 80 (PART C), pp. 341-361; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) J Biomed Mater Res A, 67 A (1), pp. 158-171; Martins, M.C.L., Curtin, S.A., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88 (1), pp. 162-173; (1993) Iodine-125. A guide to radioiodination techniques, , Amersham Life Science, Little Chalfort; Rahmelow, K., Hubner, W., Ackermann, T., Infrared absorbances of protein side chains (1998) Anal Biochem, 257 (1), pp. 1-11; Barth, A., The infrared absorption of amino acid side chains (2000) Prog Biophys Mol Biol, 74 (3-5), pp. 141-173; Li, L., Chen, S., Zheng, J., Ratner, B.D., Jiang, S., Protein adsorption on oligo(ethylene glycol)-terminated alkanethiolate self-assembled monolayers: the molecular basis for nonfouling behavior (2005) J Phys Chem B, 109 (7), pp. 2934-2941; Beamson, G., Briggs, D., (1992) High resolution XPS of organic polymers, , John Wiley and Sons, Ltd;, New York; Adden, N., Gamble, L.J., Castner, D.G., Hoffmann, A., Gross, G., Menzel, H., Phosphonic acid monolayers for binding of bioactive molecules to titanium surfaces (2006) Langmuir, 22 (19), pp. 8197-8204; Sousa, S.R., Moradas-Ferreira, P., Saramago, B., Viseu Melo, L., Barbosa, M.A., Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma (2004) Langmuir, 20 (22), pp. 9745-9754; Di Cera, E., Thrombin interactions (2003) Chest, 124 (SUPPL. 3), pp. 11S-17S; Markwardt, F., Historical perspective of the development of thrombin inhibitors (2002) Pathophysiol Haemost Thromb, 32 (SUPPL. 3), pp. 15-22; Hearn, M.T., 1,1′-Carbonyldiimidazole-mediated immobilization of enzymes and affinity ligands (1987) Methods Enzymol, 135, pp. 102-117; Stöllner, D., Scheller, F.W., Warsinke, A., Activation of cellulose membranes with 1,1′-carbonyldiimidazole or 1-cyano-4-dimethylaminopyridinium tetrafluoroborate as a basis for the development of immunosensors (2002) Anal Biochem, 304 (2), pp. 157-165; Martins, M.C.L., Naeemi, E., Ratner, B.D., Barbosa, M.A., Albumin adsorption on Cibacron Blue F3G-A immobilized onto oligo(ethylene glycol)- terminated self-assembled monolayers (2003) J Mater Sci Mater Med, 14 (11), pp. 945-954; Dee, K.C., Puleo, D.A., Bizios, R., (2002) An introduction to tissue-biomaterial interactions, , Wiley-Liss, Inc; Malmsten, M., Lassen, B., Competitive adsorption at hydrophobic surfaces from binary protein systems (1994) J Colloid Interface Sci, 166 (2), pp. 490-498
Keywords: Absorption spectroscopy; Adsorption; adsorption kinetics; Albumins; Amino Acid Sequence; Amino acids; Angle measurement; article; Biomaterials; Blood; Blood clotting; Blood contact; Carbonyldiimidazole; Coagulation; Coagulation system; concentration (parameters); Concentration-dependent; Contact angle; D-phenylalanine; ellipsometry; Ethylene; Ethylene Glycol; ethylene glycol derivative; gold; Hemocompatibility; Humans; imidazole derivative; Immobilized Proteins; Infrared reflection absorption spectroscopy; infrared spectroscopy; Iodine Radioisotopes; isotope labeling; Medical Devices; monolayer culture; nanoanalysis; Nanostructured surface; peptide; Peptide immobilization; Peptides; phenylalanylprolylarginylprolylglycine; Phosphatases; priority journal; Protein adsorption; protein assembly; protein function; protein immobilization; quantitative study; Sams; Self assembled monolayers; Self-assembled monolayers; Serine protease; Solubility; Solutions; Spectroscopy, Fourier Transform Infrared; Surface functionalization; Surface Properties; Tetra; tetra(ethylene glycol); Thrombin; thrombin inhibitor; Thrombin inhibitors; Thrombus formation; unclassified drug; X ray photoelectron spectroscopy

Effect of nanoscale topography on fibronectin adsorption, focal adhesion size and matrix organisation - González-García, C.; Sousa, S.R.; Moratal, D.; Rico, P.; Salmerón-Sánchez, M. (Colloids and Surfaces B: BiointerfacesColloids Surf. B Biointerfaces, 2010)
Phase separation of PLLA/PS (50/50, w/w) solutions during a spin-casting process gives rise to well-defined nanotopographies of 14, 29 and 45. nm deep pits depending on the concentration of the solution. Their influence on the biological activity of fibronectin (FN) was investigated. FN adsorption was quantified by radiolabelling the protein. The amount of adsorbed FN was higher on the 14. nm deep pit nanotopography than on the other two surfaces. FN distribution between valleys and peaks was investigated by AFM combined with image analysis. FN tends to adsorb preferentially on the valleys of the nanotopography only for the 14. nm system and when adsorbed from solutions of concentration lower than 10μg/ml. Higher concentration of the FN solution leads to evenly distribution of the protein throughout the surface; moreover, there is no difference in the distribution of the protein between valleys and peaks for the other two systems (29 and 45. nm) irrespective of the concentration of the FN solution. The biological activity of the adsorbed protein layer was assessed by investigating MC3T3 osteoblast-like cells adhesion, FN reorganisation and late matrix formation on the different substrates. Even if initial cell adhesion is excellent for every substrate, the size of the focal adhesion plaques increases as the size of the pits in the nanotopography does. This is correlated to FN reorganisation, which only takes places on the 29 and 45. nm deep pits surfaces, where enhanced late matrix production was also found. © 2010 Elsevier B.V.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: CSBBEdoi: 10.1016/j.colsurfb.2010.01.021PubMed ID: 20185279Language of Original Document: EnglishCorrespondence Address: Rico, P.; Center for Biomaterials and Tissue Engineering, Universidad Politécnica de Valencia, 46022 Valencia, Spain; email: parico@upvnet.upv.esChemicals/CAS: fibronectin, 86088-83-7; polylactic acid, 26100-51-6; polystyrene, 9003-53-6; Fibronectins; ProteinsReferences: Spie, J., (2002) Ann. N. Y. Acad. Sci., 961, p. 1;Griffin, L., Naughton, G., (2002) Science, 259, p. 1009; Grinnell, F., (1986) J. Cell Biol., 103, p. 2697; Hynes, R.O., (2002) Cell, 110, p. 673; Wong, J.Y., Leach, J.B., Brown, X.Q., (2004) Surf. Sci., 570, p. 119; Schwarz, U.S., Bischofs, I.B., (2005) Med. Eng. Phys., 27, p. 763; Ohara, P.T., Buck, R.C., (1979) Exp. Cell Res., 121, p. 235; Lim, J.Y., Donahue, H.J., (2007) Tissue Eng., 13, p. 1879; Affrossman, S., Jerome, R., O'Neill, S.A., Schmitt, T., Stamm, M., (2000) Colloid Polym. Sci., 278, p. 888; Denis, F.A., Hanarp, P., Sutherland, D.S., Dufrene, Y.F., (2002) Nanoletters, 2, p. 1419; Vieu, C., Carcenac, F., Pepin, A., Chen, Y., Mejias, M., Lebib, A., Manin-Ferlazzo, L., Launois, H., (2000) Appl. Surf. Sci., 164, p. 111; Kriparamanan, R., Aswath, P., Zhou, A., Tang, L., Nguyen, K.T., (2006) J. Nanosci. Nanotechnol., 6, p. 1905; Dalby, M.J., Giannaras, D., Riehle, M.O., Gadegaard, N., Affrossman, S., Curtis, A.S.G., (2004) Biomaterials, 25, p. 77; Lim, J.Y., Dreiss, D., Zhou, Z., Hansen, J.C., Siedlecki, C.A., Hengstebeck, R.W., Cheng, J., Donahue, H.J., (2007) Biomaterials, 28, p. 1787; Dalby, M.J., Hart, A., Yarwood, S.J., (2008) Biomaterials, 29, p. 282; Zinger, O., Zhao, G., Schwartz, Z., Simpson, J., Wieland, M., Landlolt, D., Boyan, B., (2005) Biomaterials, 26, p. 1837; Dalby, M.J., Gadegaard, N., Tare, R., Andar, A., Riehle, M.O., Herzyk, P., Wilkinson, C.D.W., Oreffo, R.O.C., (2007) Nat. Mater., 9, p. 997; Dalby, M.J., McCloy, D., Robertson, M., Wilkinson, C.D.W., Oreffo, R.O.C., (2006) Biomaterials, 27, p. 1306; Pirouz-Dolatshahi, A., Rechendorff, K., Hovgaard, M.B., Foss, M., Chevallier, J., Besenbacher, F., (2008) Colloid Surf. B, 66, p. 53; Khor, H.L., Kukula, H., Tamada, K., Knoll, W., Moeller, M., Hutmacher, D.W., (2007) Biomacromolecules, 8, p. 1530; Cai, K., Bossert, J., Jandt, K., (2006) Colloid Surf. B, 49, p. 136; (1993), p. 64. , Iodine-125, Amersham International, Little Chalfont, Buckinghamshire, U.K.Sousa, S.R., Brás, M., Moradas-Ferreira, P., Barbosa, M.A., (2007) Langmuir, 23, p. 7046; Otsu, N.A., (1979) IEEE Trans. Syst. Man Cybern., 9, p. 62; Gonzalez, R.C., Woods, R.E., Eddins, S.L., (2003) Digital Image Processing Using MATLAB, , Prentice-Hall, Upper Saddle River, NJ; Gonzalez, R.C., Woods, R.E., (2007) Digital Image Processing, , Prentice-Hall, Upper Saddle River, NJ; (2006), MATLAB Image Processing Toolbox User's Guide, The MathWorks, Inc., Natick, MAAllen, L.T., Tosetto, M., Miller, I.S., O'Connor, D.P., Penney, S.C., Lynch, I., Keenan, A.K., Gallagher, W.M., (2006) Biomaterials, 27, p. 3096; Gugutkov, D., Altankov, G., Rodríguez Hernández, J.C., Monleón Pradas, M., Salmerón Sánchez, M., (2010) J. Biomed. Mater. Res. A, 92, p. 322; Rico, P., Rodríguez Hernández, J.C., Moratal, D., Monleón Pradas, M., Salmerón Sánchez, M., (2009) Macromol. Biosci., 9, p. 766; Keselowsky, B.G., Collard, D.M., García, A.J., (2003) J. Biomed. Mater. Res. A, 66, p. 247; Lee, M.H., Ducheyne, P., Lynch, L., Boettiger, D., Composto, R.J., (2006) Biomaterials, 27, p. 1907; Costa Martínez, E., Rodríguez Hernández, J.C., Machado, M., Mano, J., Gómez Ribelles, J.L., Monleón Pradas, M., Salmerón Sánchez, M., (2008) Tissue Eng., 14, p. 1751; Lim, J.Y., Hansen, J.C., Siedlecki, C.A., Hengstebeck, R.A., Cheng, J., Winograd, N., (2005) Biomacromolecules, 6, p. 3319; Liu, X., Lim, J.Y., Donahue, H.J., Dhurjati, R., Maestro, A.M., Vogler, E.A., (2007) Biomaterials, 28, p. 4535; Dalby, M.J., Yarwood, S.J., Riehle, M.O., Johnstone, H.J., Affressman, S., Curtis, A.S., (2002) Exp. Cell Res., 276, p. 1; Dalby, M.J., Childs, S., Riehle, M.O., Johnston, H.J.H., Affrossman, S., (2003) Biomaterials, 24, p. 927; Dalby, M.J., McCloy, D., Robertson, M., Agheli, H., Sutherland, D., Affrossman, S., Oreffo, R.O.C., (2006) Biomaterials, 27, p. 2980; Dalby, M.J., (2005) Med. Eng. Phys., 27, p. 730; Galbraith, C.G., Yamada, K.M., Sheetz, M.P., (2002) J. Cell Biol., 159, p. 695; Balaban, N.Q., Schwarz, U.S., Riveline, D., Goichberg, P., Tzur, G., Sabanay, I., (2001) Nat. Cell Biol., 3, p. 466; Pegueroles, M., Aparicio, C., Bosio, M., Engel, E., Gil, F.J., Planell, J.A., Altankov, G., Acta Biomater. (). doi:10.1016/j.actbio.2009.07.030Altankov, G., Groth, T., (1994) J. Mater. Sci. Mater. Med., 5, p. 732; Altankov, G., Groth, T., (1996) J. Mater. Sci. Mater. Med., 7, p. 425; Altankov, G., Grinnell, F., Groth, T., (1996) J. Biomed. Mater. Res., 30, p. 385; Tzoneva, R., Groth, T., Altankov, G., Paul, D., (2002) J. Mater. Sci. Mater. Med., 13, p. 1235; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., (2005) Biomaterials, 26, p. 3891; Luthen, F., Lange, R., Becker, P., Rychly, J., Beck, U., Nebe, J.G.B., (2005) Biomaterials, 26, p. 2423; Geiger, B., Bershadsky, A., Pankov, R., Yamada, K.M., (2001) Nat. Rev. Mol. Cell Biol., 2, p. 793; Altankov, G., Groth, T., (1996) J. Biomater. Sci. Polym. Ed., 8, p. 299
Keywords: 3T3 Cells; Adhesion; Adsorption; AFM; animal cell; Animals; article; Atomic force microscopy; Bioactivity; Biological activities; biological activity; Casting process; cell adhesion; Cell Line; concentration (parameters); Concentration (process); Concentration of; Deep pit; Different substrates; Electric currents; extracellular matrix; Fibronectin; Fibronectin adsorption; Fibronectins; focal adhesion; Focal adhesion plaques; Focal adhesions; Humans; Image analysis; Image Processing, Computer-Assisted; isotope labeling; Landforms; matrix; Matrix formation; Mice; Microscopy, Atomic Force; nanomaterial; Nanoscale topography; Nanotechnology; Nanotopographies; Nanotopography; nonhuman; osteoblast; Osteoblast-like cells; Osteoblasts; Phase separation; polylactic acid; polystyrene; priority journal; Protein adsorption; Protein layers; protein localization; Proteins; Radiolabelling; Reorganisation; Substrates; Surface Properties

Functionalization of poly(amidoamine) dendrimers with hydrophobic chains for improved gene delivery in mesenchymal stem cells - Santos, J.L.; Oliveira, H.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Journal of Controlled ReleaseJ. Control. Release, 2010)
A new family of gene delivery vectors is synthesized consisting of a medium-size generation PAMAM dendrimer (generation 5, with amine termini) core randomly linked at the periphery to hydrophobic chains that vary in length (12 to 16 carbon alkyl chains) and number (from 4.2 to 9.7 in average). The idea subjacent to the present work is to join the advantages of the cationic nature of the dendrimer with the capacity of lipids to interact with biological membranes. Unlike other amphiphilic systems designed for the same purpose, where the hydrophobic and hydrophilic moieties coexist in opposite sides, the present vectors have a hydrophilic interior and a hydrophobic corona. The vectors are characterized in respect to their ability to neutralize, bind and compact plasmid DNA (pDNA). The complexes formed between the vectors and pDNA are analyzed concerning their size, ζ-potential, resistance to serum nucleases, capacity of being internalized by cells and transfection efficiency. These new vectors show a remarkable capacity for mediating the internalization of pDNA with minimum cytotoxicity, being this effect positively correlated with the -CH 2- content present in the hydrophobic corona. Gene expression in MSCs, a cell type with relevancy in the regenerative medicine clinical context, is also enhanced using the new vectors but, in this case, the higher efficiency is shown by the vectors containing the smallest hydrophobic chains. © 2010 Elsevier B.V.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JCREEdoi: 10.1016/j.jconrel.2010.01.034PubMed ID: 20138937Language of Original Document: EnglishCorrespondence Address: Tomás, H.; CQM - Centro de Química da Madeira, MMRG, Departamento de Química, Universidade da Madeira, Campus Universitário da Penteada, 9000-390 Funchal, Portugal; email: lenat@uma.ptChemicals/CAS: lipid, 66455-18-3; nuclease, 9026-81-7; Cations; DNA, 9007-49-2; Dendrimers; Lipids; PAMAM StarburstReferences: Segura, T., Shea, L.D., Materials for non-viral gene delivery (2001) Annu. Rev. Mat. Res., 31, pp. 25-46;Mastrobattista, E., Bravo, S.A., van der Aa, M., Crommelin, D.J.A., Nonviral gene delivery systems: from simple transfection agents to artificial viruses (2005) Drug Discov. Today Technol., 2, pp. 103-109; Colella, P., Cotugno, G., Auricchio, A., Ocular gene therapy: current progress and future prospects (2009) Trends Mol. Med., 15, pp. 23-31; Scanlon, K.J., Cancer gene therapy: challenges and opportunities (2004) Anticancer Res., 24, pp. 501-504; Gersbach, C.A., Phillips, J.E., Garcia, A.J., Genetic engineering for skeletal regenerative medicine (2007) Annu. Rev. Biomed. Eng., 9, pp. 87-119; Heyde, M., Partridge, K.A., Oreffo, R.O., Howdle, S.M., Shakesheff, K.M., Garnett, M.C., Gene therapy used for tissue engineering applications (2007) J. Pharm. Pharmacol., 59, pp. 329-350; Gafni, Y., Turgeman, G., Liebergal, M., Pelled, G., Gazit, Z., Gazit, D., Stem cells as vehicles for orthopedic gene therapy (2004) Gene Ther., 11, pp. 417-426; Vaananen, H.K., Mesenchymal stem cells (2005) Ann. Med., 37, pp. 469-479; Phillips, J.E., Gersbach, C.A., Garcia, A.J., Virus-based gene therapy strategies for bone regeneration (2007) Biomaterials, 28, pp. 211-229; Lundstrom, K., Latest development in viral vectors for gene therapy (2003) Trends Biotechnol., 21, pp. 117-122; Noel, D., Gazit, D., Bouquet, C., Apparailly, F., Bony, C., Plence, P., Millet, V., Jorgensen, C., Short-term BMP-2 expression is sufficient for in vivo osteochondral differentiation of mesenchymal stem cells (2004) Stem Cells, 22, pp. 74-85; Mintzer, M.A., Simanek, E.E., Nonviral vectors for gene delivery (2009) Chem. Rev., 109, pp. 259-302; Hamm, A., Krott, N., Breibach, I., Blindt, R., Bosserhoff, A.K., Efficient transfection method for primary cells (2002) Tissue Eng., 8, pp. 235-245; McMahon, J.M., Conroy, S., Lyons, M., Greiser, U., O'Shea, C., Strappe, P., Howard, L., O'Brien, T., Gene transfer into rat mesenchymal stem cells: a comparative study of viral and nonviral vectors (2006) Stem Cells Dev., 15, pp. 87-96; Jang, W.-D., Selim, K.M.K., Lee, C.-H., Kang, I.-K., Bioinspired application of dendrimers: from bio-mimicry to biomedical applications (2009) Prog. Polym. Sci., 34, pp. 1-23; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications-reflections on the field (2005) Adv. Drug Deliv. Rev., 57, pp. 2106-2129; Caminade, A.M., Turrin, C.O., Majoral, J.P., Dendrimers and DNA: combinations of two special topologies for nanomaterials and biology (2008) Chemistry, 14, pp. 7422-7432; Dufes, C., Uchegbu, I.F., Schatzlein, A.G., Dendrimers in gene delivery (2005) Adv. Drug Deliv. Rev., 57, pp. 2177-2202; Guillot, M., Eisler, S., Diederich, F., Dendritic vectors for gene transfection (2007) New J. Chem., 31, pp. 1111-1127; Lechardeur, D., Verkman, A.S., Lukacs, G.L., Intracellular routing of plasmid DNA during non-viral gene transfer (2005) Adv. Drug Deliv. Rev., 57, pp. 755-767; Smith, D.K., Dendrimers and the double helix - from DNA binding towards gene therapy (2008) Curr. Top. Med. Chem., 8, pp. 1187-1203; Dobrovolskaia, M.A., McNeil, S.E., Immunological properties of engineered nanomaterials (2007) Nat. Nanotechnol., 2, pp. 469-478; Kukowska-Latallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker, J.R., Efficient transfer of genetic material into mammalian cells using Starburst polyamidoamine dendrimers (1996) Proc. Natl. Acad. Sci. U.S.A., 93, pp. 4897-4902; Santos, J.L., Oramas, E., Pego, A.P., Granja, P.L., Tomas, H., Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene delivery vectors (2009) J. Control. Release, 134, pp. 141-148; Dennig, J., Duncan, E., Gene transfer into eukaryotic cells using activated polyamidoamine dendrimers (2002) J. Biotechnol., 90, pp. 339-347; Kono, K., Akiyama, H., Takahashi, T., Takagishi, T., Harada, A., Transfection activity of polyamidoamine dendrimers having hydrophobic amino acid residues in the periphery (2005) Bioconjug. Chem., 16, pp. 208-214; Takahashi, T., Harada, A., Emi, N., Kono, K., Preparation of efficient gene carriers using a polyamidoamine dendron-bearing lipid: improvement of serum resistance (2005) Bioconjug. Chem., 16, pp. 1160-1165; Takahashi, T., Kojima, C., Harada, A., Kono, K., Alkyl chain moieties of polyamidoamine dendron-bearing lipids influence their function as a nonviral gene vector (2007) Bioconjug. Chem., 18, pp. 1349-1354; Takahashi, T., Kono, K., Itoh, T., Emi, N., Takagishi, T., Synthesis of novel cationic lipids having polyamidoamine dendrons and their transfection activity (2003) Bioconjug. Chem., 14, pp. 764-773; Jones, S.P., Gabrielson, N.P., Pack, D.W., Smith, D.K., Synergistic effects in gene delivery - a structure-activity approach to the optimisation of hybrid dendritic-lipidic transfection agents (2008) Chem. Commun., 39, pp. 4700-4702; Shah, D.S., Sakthivel, T., Toth, I., Florence, A.T., Wilderspin, A.F., DNA transfection and transfected cell viability using amphipathic asymmetric dendrimers (2000) Int. J. Pharm., 208, pp. 41-48; Ahmad, A., Evans, H.M., Ewert, K., George, C.X., Samuel, C.E., Safinya, C.R., New multivalent cationic lipids reveal bell curve for transfection efficiency versus membrane charge density: lipid-DNA complexes for gene delivery (2005) J. Gene Med., 7, pp. 739-748; Ewert, K.K., Evans, H.M., Zidovska, A., Bouxsein, N.F., Ahmad, A., Safinya, C.R., A columnar phase of dendritic lipid-based cationic liposome-DNA complexes for gene delivery: hexagonally ordered cylindrical micelles embedded in a DNA honeycomb lattice (2006) J. Am. Chem. Soc., 128, pp. 3998-4006; Guillot, M., Eisler, S., Weller, K., Merkle, H.P., Gallani, J.L., Diederich, F., Effects of structural modification on gene transfection and self-assembling properties of amphiphilic dendrimers (2006) Org. Biomol. Chem., 4, pp. 766-769; Joester, D., Losson, M., Pugin, R., Heinzelmann, H., Walter, E., Merkle, H.P., Diederich, F., Amphiphilic dendrimers: novel self-assembling vectors for efficient gene delivery (2003) Angew. Chem. Int. Ed., 42, pp. 1486-1490; Alvarez, E., Girones, N., Davis, R.J., Inhibition of the receptor-mediated endocytosis of diferric transferrin is associated with the covalent modification of the transferrin receptor with palmitic acid (1990) J. Biol. Chem., 265, pp. 16644-16655; Jevprasesphant, R., Penny, J., Attwood, D., McKeown, N.B., D'Emanuele, A., Engineering of dendrimer surfaces to enhance transepithelial transport and reduce cytotoxicity (2003) Pharm. Res., 20, pp. 1543-1550; Snyder, S.L., Sobocinski, P.Z., An improved 2,4,6-trinitrobenzenesulfonic acid method for the determination of amines (1975) Anal. Biochem., 64, pp. 284-288; Lapidot, Y., Rappoport, S., Wolman, Y., Use of esters of N-hydroxysuccinimide in the synthesis of N-acylamino acids (1967) J. Lipid. Res., 8, pp. 142-145; Gao, X., Huang, L., Potentiation of cationic liposome-mediated gene delivery by polycations (1996) Biochemistry, 35, pp. 1027-1036; Aubin, J.E., Osteoprogenitor cell frequency in rat bone marrow stromal populations: role for heterotypic cell-cell interactions in osteoblast differentiation (1999) J. Cell Biochem., 72, pp. 396-410; Perrot, S., Dutertre-Catella, H., Martin, C., Rat, P., Warnet, J.M., Resazurin metabolism assay is a new sensitive alternative test in isolated pig cornea (2003) Toxicol. Sci., 72, pp. 122-129; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Hiraoka, Y., Inoue, S., Shimokawa, H., Tabata, Y., Enhanced ectopic bone formation using a combination of plasmid DNA impregnation into 3-D scaffold and bioreactor perfusion culture (2006) Biomaterials, 27, pp. 1387-1398; Wong, S.Y., Pelet, J.M., Putnam, D., Polymer systems for gene delivery - past, present, and future (2007) Prog. Polym. Sci., 32, pp. 799-837; Abbasi, M., Uludag, H., Incani, V., Hsu, C.Y., Jeffery, A., Further investigation of lipid-substituted poly(L-lysine) polymers for transfection of human skin fibroblasts (2008) Biomacromolecules, 9, pp. 1618-1630; Sorgi, F.L., Bhattacharya, S., Huang, L., Protamine sulfate enhances lipid-mediated gene transfer (1997) Gene Ther., 4, pp. 961-968; Lampela, P., Soininen, P., Urtti, A., Männistö, P.T., Raasmaja, A., Synergism in gene delivery by small PEIs and three different nonviral vectors (2004) Int. J. Pharm., 270, pp. 175-184; Brito, L., Little, S., Langer, R., Amiji, M., Poly(β-amino ester) and cationic phospholipid-based lipopolyplexes for gene delivery and transfection in human aortic endothelial and smooth muscle cells (2008) Biomacromolecules, 9, pp. 1179-1187; Hardy, J.G., Love, C.S., Gabrielson, N.P., Pack, D.W., Smith, D.K., Synergistic effects on gene delivery - co-formulation of small disulfide-linked dendritic polycations with Lipofectamine 2000TM (2009) Org. Biomol. Chem., 7, pp. 789-793; Callow, P., Fragneto, G., Cubitt, R., Barlow, D.J., Lawrence, M.J., Timmins, P., Interaction of cationic lipid vesicles with model cell membranes - as determined by neutron reflectivity (2005) Langmuir, 21, pp. 7912-7920; Malik, N., Wiwattanapatapee, R., Klopsch, R., Lorenz, K., Frey, H., Weener, J.W., Meijer, E.W., Duncan, R., Dendrimers: relationship between structure and biocompatibility in vitro, and preliminary studies on the biodistribution of 125I-labelled polyamidoamine dendrimers in vivo (2000) J. Control. Release, 65, pp. 133-148
Keywords: amphophile; animal cell; animal experiment; article; Biological membranes; Biomedical applications; cation; Cations; Cell culture; cell membrane transport; cell type; Cellular uptake; controlled study; Cytotoxicity; dendrimer; Dendrimers; DNA; DNA binding; Dyes; Functional polymers; Gene delivery; gene delivery system; gene expression; Gene therapy; Gene transfer; Gene Transfer Techniques; gene vector; Genes; genetic transfection; Genetic Vectors; Humans; Hydrocarbons; hydrophilicity; hydrophobicity; internalization; lipid; Lipids; male; Mesenchymal stem cell; Mesenchymal Stem Cells; nonhuman; nuclease; Nucleic acids; plasmid DNA; Plasmids; Poly(amidoamine) dendrimers; polyamidoamine; Polyamidoamine dendrimers; priority journal; rat; Regenerative Medicine; Stem cells; Transfection; Vectors; Zeta potential

Heparinized hydroxyapatite/collagen three-dimensional scaffolds for tissue engineering - Teixeira, S.; Yang, L.; Dijkstra, P.J.; Ferraz, M.P.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2010)
Currently, in bone tissue engineering research, the development of appropriate biomaterials for the regeneration of bony tissues is a major concern. Bone tissue is composed of a structural protein, collagen type I, on which calcium phosphate crystals are enclosed. For tissue engineering, one of the most applied strategies consists on the development and application of three dimensional porous scaffolds with similar composition to the bone. In this way, they can provide a physical support for cell attachment, proliferation, nutrient transport and new bone tissue infiltration. Hydroxyapatite is a calcium phosphate with a similar composition of bone and widely applied in several medical/dentistry fields. Therefore, in this study, hydroxyapatite three dimensional porous scaffolds were produced using the polymer replication method. Next, the porous scaffolds were homogeneously coated with a film of collagen type I by applying vacuum force. Yet, due to collagen degradability properties, it was necessary to perform an adequate crosslinking method. As a result, N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) was employed as an efficient and non-toxic crosslinking method in this research. The composites were characterized by means of SEM, DSC and TNBS. Furthermore, heparin was incorporated in order to accomplish sustained delivery of a growth factor of interest namely, bone morphogenetic proteins (BMP-2). BMP-2 binding and release of non-heparinized and heparinized scaffolds was evaluated at specific time points. The incorporation of heparin leads to a reduced initial burst phase when compared to the non heparinized materials. The results show a beneficial effect with the incorporation of heparin and its potential as a localized drug delivery system for the sustained release of growth factors. © 2010 Springer Science+Business Media, LLC.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-010-4097-2PubMed ID: 20596760Language of Original Document: EnglishCorrespondence Address: Teixeira, S.; Divisão de Biomateriais, INEB-Instituto de Engenharia Biomédica, Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: sandra_teixeira3@yahoo.comChemicals/CAS: collagen, 9007-34-5; cyanamide, 151-51-9, 420-04-2; heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; hydroxyapatite, 1306-06-5, 51198-94-8; n hydroxysuccinimide, 6066-82-6; trinitrobenzenesulfonic acid, 16655-63-3, 2508-19-2; Biocompatible Materials; Bone Substitutes; Collagen, 9007-34-5; Cross-Linking Reagents; Durapatite, 1306-06-5; Heparin, 9005-49-6; PolymersReferences: Rose, F.R., Cyster, L.A., Grant, D.M., Scotchford, C.A., Howdle, S.M., Shakesheff, K.M., In vitro assessment of cell penetration into porous hydroxyapatite scaffolds with a central aligned channel (2004) Biomaterials, 25 (24), pp. 5507-5514. , DOI 10.1016/j.biomaterials.2004.01.012, PII S0142961204000134;Hong, Z., Zhang, P., He, C., Qiu, X., Liu, A., Chen, L., Chen, X., Jing, X., Nano-composite of poly(L-lactide) and surface grafted hydroxyapatite: Mechanical properties and biocompatibility (2005) Biomaterials, 26 (32), pp. 6296-6304. , DOI 10.1016/j.biomaterials.2005.04.018, PII S0142961205003297; Ignjatovic, N., Tomic, S., Dakic, M., Miljkovic, M., Plavsic, M., Uskokovic, D., Synthesis and properties of hydroxyapatite/poly-L-lactide composite biomaterials (1999) Biomaterials, 20 (9), pp. 809-816. , DOI 10.1016/S0142-9612(98)00234-8, PII S0142961298002348; Kothapalli, C.R., Shaw, M.T., Wei, M., Biodegradable HA-PLA 3-D porous scaffolds: Effect of nano-sized filler content on scaffold properties (2005) Acta Biomaterialia, 1 (6), pp. 653-662. , DOI 10.1016/j.actbio.2005.06.005, PII S1742706105000978; Liao, S., Wang, W., Uo, M., Ohkawa, S., Akasaka, T., Tamura, K., Cui, F., Watari, F., A three-layered nano-carbonated hydroxyapatite/collagen/PLGA composite membrane for guided tissue regeneration (2005) Biomaterials, 26 (36), pp. 7564-7571. , DOI 10.1016/j.biomaterials.2005.05.050, PII S0142961205004199; Maeda, H., Kasuga, T., Hench, L.L., Preparation of poly(L-lactic acid)-polysiloxane-calcium carbonate hybrid membranes for guided bone regeneration (2006) Biomaterials, 27 (8), pp. 1216-1222. , DOI 10.1016/j.biomaterials.2005.08.010, PII S0142961205007829; Kong, L., Gao, Y., Cao, W., Gong, Y., Zhao, N., Zhang, X., Preparation and characterization of nano-hydroxyapatite/chitosan composite scaffolds (2005) Journal of Biomedical Materials Research - Part A, 75 (2), pp. 275-282. , DOI 10.1002/jbm.a.30414; Li, X.M., Feng, Q.L., Cui, F.Z., In vitro degradation of porous nano-hydroxyapatite/collagen/PLLA scaffold reinforced by chitin fibres (2006) Mater Sci Eng C-Biomim Supramol Syst, 26 (4), pp. 716-720. , 1:CAS:528:DC%2BD28XjvFyntr4%3D; Sachlos, E., Gotora, D., Czernuszka, J.T., Collagen scaffolds reinforced with biomimetic composite nano-sized carbonate-substituted hydroxyapatite crystals and shaped by rapid prototyping to contain internal microchannels (2006) Tissue Engineering, 12 (9), pp. 2479-2487. , DOI 10.1089/ten.2006.12.2479; Zhu, X., Eibl, O., Scheideler, L., Geis-Gerstorfer, J., Characterization of nano hydroxyapatite/collagen surfaces and cellular behaviors (2006) Journal of Biomedical Materials Research - Part A, 79 (1), pp. 114-127. , DOI 10.1002/jbm.a.30706; Pieper, J.S., Hafmans, T., Veerkamp, J.H., Van Kuppevelt, T.H., Development of tailor-made collagen-glycosaminoglycan matrices: EDC/NHS crosslinking, and ultrastructural aspects (2000) Biomaterials, 21 (6), pp. 581-593. , DOI 10.1016/S0142-9612(99)00222-7, PII S0142961299002227; Pieper, J.S., Oosterhof, A., Dijkstra, P.J., Veerkamp, J.H., Van Kuppevelt, T.H., Preparation and characterization of porous crosslinked collagenous matrices containing bioavailable chondroitin sulphate (1999) Biomaterials, 20 (9), pp. 847-858. , DOI 10.1016/S0142-9612(98)00240-3, PII S0142961298002403; Pieper, J.S., Van Wachem, P.B., Van Luyn, M.J.A., Brouwer, L.A., Hafmans, T., Veerkamp, J.H., Van Kuppevelt, T.H., Attachment of glycosaminoglycans to collagenous matrices modulates the tissue response in rats (2000) Biomaterials, 21 (16), pp. 1689-1699. , DOI 10.1016/S0142-9612(00)00052-1, PII S0142961200000521; Pieper, J.S., Hafmans, T., Van Wachem, P.B., Van Luyn, M.J.A., Brouwer, L.A., Veerkamp, J.H., Van Kuppevelt, T.H., Loading of collagen-heparan sulfate matrices with bFGF promotes angiogenesis and tissue generation in rats (2002) Journal of Biomedical Materials Research, 62 (2), pp. 185-194. , DOI 10.1002/jbm.10267; Wissink, M.J.B., Beernink, R., Pieper, J.S., Poot, A.A., Engbers, G.H.M., Beugeling, T., Immobilization of heparin to EDC/NHS-crosslinked collagen. Characterization and in vitro evaluation (2001) Biomaterials, 22 (2), pp. 151-163. , 10.1016/S0142-9612(00)00164-2 1:CAS:528:DC%2BD3cXovFGnu7g%3D 11101159; Wissink, M.J.B., Beernink, R., Poot, A.A., Engbers, G.H.M., Beugeling, T., Van Aken, W.G., Feijen, J., Improved endothelialization of vascular grafts by local release of growth factor from heparinized collagen matrices (2000) Journal of Controlled Release, 64 (1-3), pp. 103-114. , DOI 10.1016/S0168-3659(99)00145-5, PII S0168365999001455; Wissink, M.J.B., Beernink, R., Scharenborg, N.M., Poot, A.A., Engbers, G.H.M., Beugeling, T., Van Aken, W.G., Feijen, J., Endothelial cell seeding of (heparinized) collagen matrices: Effects of bFGF pre-loading on proliferation (after low density seeding) and pro-coagulant factors (2000) Journal of Controlled Release, 67 (2-3), pp. 141-155. , DOI 10.1016/S0168-3659(00)00202-9, PII S0168365900002029; Gcm, S., Yao, C., Prevel, P., Markowicz, M., Schenck, P., Noah, E.M., Modulation of angiogenic potential of collagen matrices by covalent incorporation of heparin and loading with vascular endothelial growth factor (2004) Tissue Eng, pp. 1502-9; Yao, C., Markowicz, M., Pallua, N., Magnus Noah, E., Steffens, G., The effect of cross-linking of collagen matrices on their angiogenic capability (2008) Biomaterials, 29 (1), pp. 66-74. , DOI 10.1016/j.biomaterials.2007.08.049, PII S0142961207007284; Jiao, Y.Y., Ubrich, N., Hoffart, V., Marchand-Arvier, M., Vigneron, C., Hoffman, M., Preparation and characterization of heparin-loaded polymeric microparticles (2002) Drug Dev Ind Pharm, 28 (8), pp. 1033-1041. , 10.1081/DDC-120014740 1:CAS:528:DC%2BD38XnslGnt7c%3D 12378958; Jiao, Y., Ubrich, N., Marchand-Arvier, M., Vigneron, C., Hoffman, M., Lecompte, T., Maincent, P., In vitro and in vivo evaluation of oral heparin-loaded polymeric nanoparticles in rabbits (2002) Circulation, 105 (2), pp. 230-235. , DOI 10.1161/hc0202.101988; Lee, K.W., Yoon, J.J., Lee, J.H., Kim, S.Y., Jung, H.J., Kim, S.J., Joh, J.W., Lee, S.K., Sustained release of vascular endothelial growth factor from calcium-induced alginate hydrogels reinforced by heparin and chitosan (2004) Transplantation Proceedings, 36 (8), pp. 2464-2465. , DOI 10.1016/j.transproceed.2004.08.078, PII S0041134504009480; Schroeder-Tefft, J.A., Bentz, H., Estridge, T.D., Collagen and heparin matrices for growth factor delivery (1997) Journal of Controlled Release, 48 (1), pp. 29-33. , DOI 10.1016/S0168-3659(97)00055-2, PII S0168365997000552; Teixeira, S., Ferraz, M.P., Monteiro, F.J., Biocompatibility of highly macroporous ceramic scaffolds: Cell adhesion and morphology studies (2008) J Mater Sci, 19 (2), pp. 855-859. , 1:CAS:528:DC%2BD1cXhs1Wktb8%3D; Edlund, U., Danmark, S., Albertsson, A.-C., A strategy for the covalent functionalization of resorbable polymers with heparin and osteoinductive growth factor (2008) Biomacromolecules, 9 (3), pp. 901-905. , DOI 10.1021/bm701267u; Teixeira, S., Oliveira, S., Ferraz, M., Monteiro, F.J., Three dimensional macroporous calcium phosphates scaffolds for bone tissue engineering (2008) Key Eng Mater Trans Tech, pp. 947-50; Yamamoto, M., Tabata, Y., Hong, L., Miyamoto, S., Hashimoto, N., Ikada, Y., Bone regeneration by transforming growth factor β1 released from a biodegradable hydrogel (2000) Journal of Controlled Release, 64 (1-3), pp. 133-142. , DOI 10.1016/S0168-3659(99)00129-7, PII S0168365999001297; Teixeira, S., Rodriguez, M.A., Pena, P., De Aza, A.H., De Aza, S., Ferraz, M.P., Monteiro, F.J., Physical characterization of hydroxyapatite porous scaffolds for tissue engineering (2009) Mater Sci Eng C, 29 (5), pp. 1510-1514. , 10.1016/j.msec.2008.09.052 1:CAS:528:DC%2BD1MXmtVarurg%3D
Keywords: Achilles Tendon; Animals; Apatite; article; Beneficial effects; Binding and release; Biocompatible Materials; Biological materials; Biomaterials; Bone; Bone and Bones; bone morphogenetic protein 2; Bone morphogenetic proteins; Bone Substitutes; bone tissue; Bone tissue engineering; Bony tissue; Calcium; calcium phosphate; Calcium phosphate crystals; Cattle; Cell attachments; Collagen; collagen degradation; collagen type 1; Collagen type I; controlled study; cross linking; Cross-Linking Reagents; Crosslinking; cyanamide; Degradability; differential scanning calorimetry; Drug delivery; drug delivery system; Durapatite; Grafts; Growth factor; heparin; Hydrogels; hydroxyapatite; Microscopy, Electron, Scanning; n (3 dimethyllaminopropyl) n' ethylcarbodiimide; n hydroxysuccinimide; N-hydroxysuccinimide; Nutrient transport; Peptides; polymer; Polymer replication; Polymers; Polysaccharides; porosity; Porous scaffold; priority journal; protein binding; Scaffolds; Scanning electron microscopy; SEM; Specific time; Structural proteins; Sustained release; Three dimensional; Three-dimensional porous scaffolds; Three-dimensional scaffolds; Tissue engineering; tissue scaffold; Tissue Scaffolds; trinitrobenzenesulfonic acid; unclassified drug; vacuum; Vacuum force

Immobilization of human mesenchymal stem cells within RGD-grafted alginate microspheres and assessment of their angiogenic potential - Bidarra, S.J.; Barrias, C.C.; Barbosa, M.A.; Soares, R.; Granja, P.L. (BiomacromoleculesBiomacromolecules, 2010)
In this work, human mesenchymal stem cells (hMSC) immobilized in RGD-coupled alginate microspheres, with a binary composition of high and low molecular weight alginate, were investigated. Cells immobilized within RGD-alginate microspheres (during 21 days) showed metabolic activity, with an overall viability higher than 90%, short cell extensions, and, when induced, they were able to differentiate into the osteogenic lineage. In osteogenic conditions (comparing to basal conditions), immobilized cells presented alkaline phosphatase (ALP) activity and an upregulation of ALP, collagen type I, and Runx 2 expression. Moreover, mineralization was also detected in immobilized cells under osteogenic stimulus. In addition, it was demonstrated for the first time that MSCs immobilized in this 3D matrix were able to enhance the ability of neighboring endothelial cells to form tubelike structures. Overall, these findings represent a step forward in the development of injectable stem cell carriers for bone tissue engineering. © 2010 American Chemical Society.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm100264aPubMed ID: 20690708Language of Original Document: EnglishCorrespondence Address: Granja, P. L.; INEB-Instituto de Engenharia Biomédica, Rua do Campo Alegre No. 823, 4150-180 Porto, Portugal; email: pgranja@ineb.up.ptMolecular Sequence Numbers: GENBANK: BC021289, NM_000088, NM_002046;Chemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; alkaline phosphatase, 9001-78-9; arginylglycylaspartic acid, 99896-85-2; Alginates; Alkaline Phosphatase, 3.1.3.1; Collagen Type I; DNA Primers; Oligopeptides; arginyl-glycyl-aspartic acid, 99896-85-2References: Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomaterials, 21, pp. 2405-2412;Barralet, J.E., Wang, L., Lawson, M., Triffitt, J.T., Cooper, P.R., Shelton, R.M., Comparison of bone marrow cell growth on 2D and 3D alginate hydrogels (2005) J. Mater. Sci.: Mater. Med., 16, pp. 515-519; Ma, H.L., Hung, S.C., Lin, S.Y., Chen, Y.L., Lo, W.H., Chondrogenesis of human mesenchymal stem cells encapsulated in alginate beads (2003) J. Biomed. Mater. Res., 64, pp. 273-281; Augst, A.D., Kong, H.J., Mooney, D.J., Alginate hydrogels as biomaterials (2006) Macromol. Biosci., 6, pp. 623-633; Smidsrod, O., Skjak-Braek, G., Alginate as immobilization matrix for cells (1990) Trends Biotechnol., 8, pp. 71-78; Jen, A.C., Wake, M.C., Mikos, A.G., Review: Hydrogels for cell immobilization (1996) Biotechnol. Bioeng., 50, pp. 357-364; Oliveira, S.M., Barrias, C.C., Almeida, I.F., Costa, P.C., Ferreira, M.R.P., Bahia, M.F., Barbosa R. M, A., Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gel-forming ability (2008) J. Biomed. Mater. Res. B, 87, pp. 49-8; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H.-J., Barrias, C.C., Salema, R., Granja, P.L., Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix (2007) Biomaterials, 28, pp. 3644-3655; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20, pp. 45-53; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24, pp. 4023-4029; Grellier, M., Granja, P.L., Fricain, J.-C., Bidarra, S.J., Renard, M., Bareille, R., Bourget, C., Barbosa, M.A., The effect of the co-immobilization of human osteoprogenitors and endothelial cells within alginate microspheres on mineralization in a bone defect (2009) Biomaterials, 30, pp. 3271-3278; Caplan, A.I., Adult mesenchymal stem cells for tissue engineering versus regenerative medicine (2007) J. Cell. Physiol., 213, pp. 341-347; Horwitz, E.M., MSC: A coming of age in regenerative medicine (2006) Cytotherapy, 8, pp. 194-195; Sumanasinghe, R.D., Bernacki, S.H., Loboa, E.G., Osteogenic differentiation of human mesenchymal stem cells in collagen matrices: Effect of uniaxial cyclic tensile strain on bone morphogenetic protein (BMP-2) mRNA expression (2006) Tissue Eng., 12, pp. 3459-3465; Granero-Molto, F., Weis, J.A., Longobardi, L., Spagnoli, A., Role of mesenchymal stem cells in regenerative medicine: Application to bone and cartilage repair (2008) Expert Opin. Biol. Ther., 8, pp. 255-268; Markusen, J.F., Mason, C., Hull, D.A., Town, M.A., Tabor, A.B., Clements, M., Boshoff, C.H., Dunnill, P., Behavior of adult human mesenchymal stem cells entrapped in alginate-GRGDY beads (2006) Tissue Eng., 12, pp. 821-830; Duggal, S., Fronsdal, K.B., Szoke, K., Shahdadfar, A., Melvik, J.E., Brinchmann, J.E., Phenotype and gene expression of human mesenchymal stem cells in alginate scaffolds (2009) Tissue Eng., Part A, 15, pp. 1763-1773; Kasper, G., Dankert, N., Tuischer, J., Hoeft, M., Gaber, T., Glaeser, J.D., Zander, D., Duda, G.N., Mesenchymal stem cells regulate angiogenesis according to their mechanical environment (2007) Stem Cells, 25, pp. 903-910; Gruber, R., Kandler, B., Holzmann, P., Vogele-Kadletz, M., Losert, U., Fischer, M.B., Watzek, G., Bone marrow stromal cells can provide a local environment that favors migration and formation of tubular structures of endothelial cells (2005) Tissue Eng., 11, pp. 896-903; Valarmathi, M.T., Yost, M.J., Goodwin, R.L., Potts, J.D., A three-dimensional tubular scaffold that modulates the osteogenic and vasculogenic differentiation of rat bone marrow stromal cells (2008) Tissue Eng., Part A, 14, pp. 491-504; Potapova, I.A., Gaudette, G.R., Brink, P.R., Robinson, R.B., Rosen, M.R., Cohen, I.S., Doronin, S.V., Mesenchymal stem cells support migration, extracellular matrix invasion, proliferation, and survival of endothelial cells in vitro (2007) Stem Cells, 25, pp. 1761-1768; Moon, J.J., West, J.L., Vascularization of engineered tissues: Approaches to promote angiogenesis in biomaterials (2008) Curr. Top. Med. Chem., 8, pp. 300-310; Carano, R.A.D., Filvaroff, E.H., Angiogenesis and bone repair (2003) Drug Discovery Today, 8, pp. 980-989; Eriksen, E.F., Eghbali-Fatourechi, G.Z., Khosla, S., Remodeling and vascular spaces in bone (2007) J. Bone Miner. Res., 22, pp. 1-6; Schroeder, T.M., Jensen, E.D., Westendorf, J.J., Runx2: A master organizer of gene transcription in developing and maturing osteoblasts (2005) Birth Defects Res., Part C, 75, pp. 213-225; Soares, R., Guo, S., Ga'rtner, F., Schmitt, F., Russo, J., 17β-Estradiol-mediated vessel assembly and stabilization in tumor angiogenesis requires TGFβ and EGFR crosstalk (2003) Angiogenesis, 6, pp. 271-281; Kubota, Y., Kleinman, H.K., Martin, G.R., Lawley, T.J., Role of laminin and basement membrane in the morphological differentiation of human endothelial cells into capillary-like structures (1988) J. Cell Biol., 107, pp. 1589-1598; Kaully, T., Kaufman-Francis, K., Lesman, A., Levenberg, S., Vascularization-The conduit to viable engineered tissues (2009) Tissue Eng., Part B, 15, pp. 159-169; Silva, E.A., Mooney, D.J., Spatiotemporal control of vascular endothelial growth factor delivery from injectable hydrogels enhances angiogenesis (2007) J. Thromb. Haemost., 5, pp. 590-598; Fuchs, S., Jiang, X., Schmidt, H., Dohle, E., Ghanaati, S., Orth, C., Hofmann, A., Kirkpatrick, C.J., Dynamic processes involved in the pre-vascularization of silk fibroin constructs for bone regeneration using outgrowth endothelial cells (2009) Biomaterials, 30, pp. 1329-1338; Hsiong, S.X., Mooney, D.J., Regeneration of vascularized bone (2006) Periodontol. 2000, 41, pp. 109-122; Abbah, S., Lu, W., Chan, D., Cheung, K., Liu, W., Zhao, F., Li, Z., Luk, K., Osteogenic behavior of alginate encapsulated bone marrow stromal cells: An in vitro study (2008) J. Mater. Sci.: Mater. Med., 19, pp. 2113-2119; Moioli, E.K., Hong, L., Mao, J.J., Inhibition of osteogenic differentiation of human mesenchymal stem cells (2007) Wound Repair Regen., 15, pp. 413-421; Healy, K.E., Guldberg, R.E., Bone tissue engineering (2007) J. Musculoskelet. Neuronal Interact., 7, pp. 328-330; Stein, G.S., Lian, J.B., Owen, T.A., Relationship of cell growth to the regulation of tissue-specific gene expression during osteoblast differentiation (1990) FASEB J., 4, pp. 3111-3123; Lian, J.B., Stein, G.S., Concepts of osteoblast growth and differentiation: Basis for modulation of bone cell development and tissue formation (1992) Crit. Rev. Oral Biol. Med., 3, pp. 269-305; Huang, Y.-C., Kaigler, D., Rice, K.G., Krebsbach, P.H., Mooney, D.J., Combined angiogenic and osteogenic factor delivery enhances bone marrow stromal cell-driven bone regeneration (2005) J. Bone Miner. Res., 20, pp. 848-857; Fang, T.D., Salim, A., Xia, W., Nacamuli, R.P., Guccione, S., Song, H.M., Carano, R.A., Longaker, M.T., Angiogenesis is required for successful bone induction during distraction osteogenesis (2005) J. Bone Miner. Res., 20, pp. 1114-1124; Villars, F., Bordenave, L., Bareille, R., Amédée, J., Effect of human endothelial cells on human bone marrow stromal cell phenotype: Role of VEGF (2000) J. Cell. Biochem., 79, pp. 672-685; Kaigler, D., Krebsbach, P.H., Polverini, P.J., Mooney, D.J., Role of vascular endothelial growth factor in bone marrow stromal cell modulation of endothelial cells (2003) Tissue Eng., 9, pp. 95-103; Grellier, M., Ferreira-Tojais, N., Bourget, C., Bareillke, R., Guillemot, F., Amédée, J., Role of vascular endothelial growth factor in the communication between human osteoprogenitors and endothelial cells (2009) J. Cell. Biochem., 106, pp. 390-398; Yu, J., Gu, Y., Du, K.T., Mihardja, S., Sievers, R.E., Lee, R.J., The effect of injected RGD modified alginate on angiogenesis and left ventricular function in a chronic rat infarct model (2009) Biomaterials, 30, pp. 751-756
Keywords: Alginate; Alginates; alginic acid; alkaline phosphatase; Alkaline phosphatase activity; angiogenesis; arginylglycylaspartic acid; article; Basal conditions; Base Sequence; Binary composition; bone development; Bone tissue engineering; Cell culture; cell differentiation; Cell extension; Cell immobilization; cell metabolism; cell structure; cell viability; collagen type 1; Collagen type I; controlled study; DNA Primers; Endothelial Cells; endothelium cell; enzyme activity; human; human cell; Human mesenchymal stem cells; Humans; immobilized cell; Immobilized cells; Low molecular weight; matrix; Mesenchymal stem cell; Mesenchymal Stem Cells; Metabolic activity; Microscopy, Electron, Scanning; microsphere; Microspheres; molecular weight; Neovascularization, Physiologic; nucleotide sequence; Oligopeptides; osteoblast; Osteogenic; Phosphatases; priority journal; protein expression; quantitative analysis; Reverse Transcriptase Polymerase Chain Reaction; stem cell; Stem cells; three dimensional imaging; Tissue engineering; transcription factor RUNX2; umbilical vein; Up-regulation; upregulation

In vitro study of the proliferation and growth of human bone marrow cells on apatite-wollastonite-2M glass ceramics - Magallanes-Perdomo, M.; De Aza, A.H.; Mateus, A.Y.; Teixeira, S.; Monteiro, F.J.; De Aza, S.; Pena, P. (Acta BiomaterialiaActa Biomater., 2010)
This study concerns the preparation and in vitro characterization of an apatite-wollastonite-2M bioactive glass ceramic which is intended to be used for the regeneration of hard tissue (i.e. in dental and craniomaxillofacial surgery). This bioglass ceramic has been obtained by appropriate thermal treatment through the devitrification (crystallization) of a glass with a stoichiometric eutectic composition within the Ca 3(PO 4)2-CaSiO 3 binary system. Crack-free specimens of the bioglass ceramic were immersed in human bone marrow cell cultures for 3, 7, 14 and 21 days, in order to study biocompatibility. Cell morphology, proliferation and colonization were assessed by scanning electron microscopy and confocal laser scanning microscopy. A total protein content assay was used to evaluate the viability and proliferation of cultured bone marrow cells. The results showed that the cells were able to adhere and proliferate on the designed material due to the essentiality of silicon and calcium as accessory factors for cell activity stimulation. © 2009 Acta Materialia Inc. All rights reserved.
Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2009.12.027Language of Original Document: EnglishCorrespondence Address: De Aza, A. H.; Instituto de Cerámica y Vidrio, CSIC, C/Kelsen 5, 28049 Madrid, Spain; email: aaza@icv.csic.esChemicals/CAS: apatite, 64476-38-6; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; calcium silicate, 1344-95-2, 13983-17-0; silicate, 12627-13-3; Apatites; Bone Substitutes; Calcium Compounds; Ceramics; Silicates; calcium silicate, 1344-95-2References: Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics, , London: World Scientific;Hench, L.L., Bioceramics: From concept to clinic (1991) J. Am. Ceram. Soc., 74, pp. 1487-1510; Best, S.M., Porter, A.E., Thian, E.S., Huan, J., Bioceramics: Past, present and for the future (2008) J. Eur. Ceram. Soc., 28, pp. 1319-1327; Chevalier, J., Gremillard, L., Ceramics for medical applications: A picture for the next 20 years (2009) J. Eur. Ceram. Soc., 29, pp. 1245-1255; Teixeira, S., Oliveira, S., Ferraz, M.P., Monteiro, F.J., Mesenchymal stem cell proliferation and morphological analysis on interconnected macroporous structures (2007) Key Eng. Mater., 330-332, pp. 1129-1132; Temenoff, J.S., Mikos, A.G., (2008) Biomaterials: The Intersection of Biology and Materials Science, p. 471. , London: Pearson International; Carlisle, E.M., Biochemical and morphological changes associated with long bone abnormalities in silicon deficiency (1980) J. Nutr., 110, pp. 1046-1055; Carlisle, E.M., A silicon requirement for normal skull formation (1980) J. Nutr., 110, pp. 352-359; Reffitt, M., Ogston, N., Jugdaohsingh, R., Cheung, H.F., Evans, B.A., Thompson, R.P., Orthosilicic acid stimulates collagen type 1 synthesis and osteoblastic differentiation in human osteoblast-like cells in vitro (2003) Bone, 32, pp. 127-135; Brown, L., Luklinska, Z., De Aza, P.N., De Aza, S., Anseau, M., Hughes, F.J., Mechanism of osteoinduction by pseudowollastonite (psW) ceramic (2004) 7th World Biomaterials Congress, , Paper presented at the, Sydney; De Aza, P.N., De Aza, A.H., De Aza, S., Crystalline bioceramic materials (2005) Bol Soc. Esp. Ceram. V, 44, pp. 135-145; De Aza, P.N., De Aza, A.H., Pena, P., De Aza, S., Bioactive glasses and glass-ceramics (2007) Bol Soc. Esp. Ceram. V, 46, pp. 45-55; Kokubo, T., Ito, S., Sakka, S., Formation of a high-strength bioactive glass-ceramic in the system MgO-CaO-SiO 2-P 2O 5 (1986) J. Mat. Sci., 21, pp. 536-540; De Aza, P.N., Guitián, F., De Aza, S., Bioeutectic: A new ceramic material for human bone replacement (1997) Biomaterials, 18, pp. 1285-1291; De Aza, P.N., Guitián, F., De Aza, S., A new bioactive material which transforms in situ into hydroxyapatite (1998) Act Mater., 46, pp. 2541-2549; De Aza, P.N., Guitián, F., De Aza, S., Bioeutectics (1994) Internacional Trademark, 780 (1), p. 697. , Universidad de Santiago de Compostela; De Aza, P.N., Guitián, F., De Aza, S., Bioeutectics: New bioceramic materials (1999) Advances in Science and Technology, 28, pp. 25-32. , Vicenzini P, editor, Materials in clinical applications, Faenza: Publi Techna Italia; De Aza, P.N., Luklinska, Z.B., Anseau, M.R., Guitian, F., De Aza, S., Reactivity of wollastonite-tricalcium phosphate ceramic (Bioeutectic ®) in parotid human saliva (2000) Biomaterials, 21, pp. 1735-1741; De Aza, A.H., Velasquez, P., Alemany, M.I., Pena, P., De Aza, P.N., In situ bone-like apatite formation from a Bioeutectic ceramic in SBF dynamic flow (2007) J. Am. Ceram. Soc., 90, pp. 1200-1207; Sánchez, F.M., Díaz-Güemes, I., Enciso, S., Moreno, B., De Aza, A.H., Carrodeguas, R.G., Evaluación de una cerámica bioactiva de p-wollastonita como sustituto óseo en el modelo ovino (2009) XVII Congreso Internacional de la Sociedad Española de Cirugía Veterinaria, , Cáceres; 6-8 November, Paper Presented at the; Llorca, J., Orera, V., Directionally solidified eutectic ceramic oxides (2006) Prog. Mater. Sci., 51, pp. 711-809; Magallanes-Perdomo, M., Carrodeguas, R.G., Pena, P., De Aza, P.N., De Aza, S., De Aza, A.H., Non-isothermal devitrification study of wollastonite-tricalcium phosphate Bioeutectic ® glass (2009) Key Eng. Mat., 396-398, pp. 127-130; Magallanes-Perdomo, M., Pena, P., De Aza, P.N., Carrodeguas, R.G., Rodriguez, M.A., Turrillas, X., Devitrification studies of wollastonite-tricalcium phosphate eutectic glass (2009) Acta Biomater, 5, pp. 3057-3066; De Aza, P.N., Guitián, F., De Aza, S., Phase diagram of wollastonite-tricalcium phosphate (1995) J. Am. Ceram. Soc., 78, pp. 1653-1656; Young, R.A., (1993) The Rietveld Method, p. 336. , Oxford: Oxford University Press; Larson, A.C., Von Dreele, R.B., (1994) Los Alamos National Laboratory Report No. LA-UR-86-748, , Los Alamos, NM: Los Alamos National Laboratory; Finger, L.W., Cox, D.E., Jephcoat, A.P., A correction for powder diffraction peak asymmetry due to axial divergence (1994) J. Appl. Cryst., 27, pp. 892-900; Wilson, R.M., Elliott, J.C., Dowker, S.E., Rodriguez-Lorenzo, L.M., Rietveld refinements and spectroscopic studies of the structure of Ca-deficient apatite (2005) Biomaterials, 26, pp. 1317-1327; Wilson, R.M., Elliott, J.C., Dowker, S.E., Rodriguez-Lorenzo, L.M., Ca 9.303 (PO 4) 6 (OH) 0.6061.97 (H 2O) (2005) ICSD Collection Code 152190, Inorganic Crystal Structure Database, , Karlsruhe: Fachonformationszentrum; Trojer, F.J., The crystal structure of parawollastonite (1968) Zeitschrift fur Kristallographie Kristallgeometrie Kristallphysik Kristallchemie, 127, pp. 291-308; Trojer, F.J., CaSiO 3-wollastonite-2M (1968) ICSD Collection Code 34908, Inorganic Crystal Structure Database, , Karlsruhe: Fachonformationszentrum; De La, T.A.G., Bruque, S., Aranda, M.A.G., Rietveld quantitative amorphous content analysis (2001) J. Appl. Cryst., 34, pp. 196-202; De Aza, A.H., De La Torre, A.G., Aranda, M.A.G., Valle, F.J., De Aza, S., Rietveld quantitative analysis of Buen Retiro porcelains (2004) J. Am. Ceram. Soc., 87, pp. 449-454; Magallanes-Perdomo, M., Luklinska, Z.B., De Aza, A.H., Carrodeguas, R.G., De Aza, S., Pena, P., Bone like apatite forming ability of apatite-wollastonite glass ceramic (2009) 11th International Conference and Exhibition of the European Ceramic Society, , Krakow, Poland; 21-25 June, Paper Presented at the; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and double-layer HA-P 2O 3/CaO glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behavior (2001) J. Mater. Sci. Mater. Med., 12, pp. 629-638; Meseguer-Olmo, L., Bernabeu-Esclapez, A., Ros-Martinez, E., Sanchez-Salcedo, S., Padilla, S., Martin, A.I., In vitro behaviour of adult mesenchymal stem cells seeded on a bioactive glass ceramic in the SiO 2-CaO-P 2O 5 system (2008) Acta Biomater, 4, pp. 1104-1113; Muller, P., Bulnheim, U., Diener, A., Luthen, F., Teller, M., Klinkenberg, E.D., Calcium phosphate surfaces promote osteogenic differentiation of mesenchymal stem cells (2008) J. Cell. Mol. Med., 12, pp. 281-291; Saldana, L., Sanchez-Salcedo, S., Izquierdo-Barba, I., Bensiamar, F., Munuera, L., Vallet-Regi, M., Calcium phosphate-based particles influence osteogenic maturation of human mesenchymal stem cells (2009) Acta Biomater, 5, pp. 1294-1305; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Effect of titanium surface-roughness on proliferation, differentiation, and protein-synthesis of human osteoblast-like cells (MG63) (1995) J. Biomed. Mater. Res., 29, pp. 389-401; Bowers, K.T., Keller, J.C., Randolph, B.A., Wick, D.G., Michaels, C.M., Optimization of surface micromorphology for enhanced osteoblast responses in vitro (1992) Int. J. Oral. Maxillofac. Implants, 7, pp. 302-310; Boyan, B.D., Batzer, R., Kieswetter, K., Liu, Y., Cochran, D.L., Szmuckler-Moncler, S., Titanium surface roughness alters responsiveness of MG63 osteoblastlike cells to 1 alpha, 25-(OH) (2) D-3 (1998) J. Biomed. Mater. Res., 39, pp. 77-85; Mateus, A.Y.P., Barrias, C.C., Ribeiro, C., Ferraz, M.P., Monteiro, F.J., Comparative study of nanohydroxyapatite microspheres for medical applications (2008) J. Biomed. Mater. Res. A, 86, pp. 483-493; Ni, S.Y., Chang, J., Chou, L., Zhai, W.Y., Comparison of osteoblast-like cell responses to calcium silicate and tricalcium phosphate ceramics in vitro (2007) J. Biomed. Mater. Res. B. Appl. Biomater, 80, pp. 174-183; Sarmento, C., Luklinska, Z.B., Brown, L., Anseau, M., De Aza, P.N., De Aza, S., In vitro behavior of osteoblastic cells cultured in the presence of pseudowollastonite ceramic (2004) J. Biomed. Mater. Res. A, 69 A, pp. 351-358
Keywords: Apatite; Apatites; article; Bioceramics; Biocompatibility; bone marrow cell; bone prosthesis; Bone Substitutes; Calcium Compounds; calcium derivative; calcium phosphate; calcium silicate; cell activity; cell adhesion; Cell culture; cell differentiation; cell enlargement; cell growth; cell proliferation; cell structure; cell viability; Cells, Cultured; ceramics; chemistry; confocal laser microscopy; crystal structure; Crystallization; cytology; glass; Glass ceramics; human; human cell; Humans; in vitro study; materials testing; Mesenchymal stem cell; Mesenchymal Stem Cells; methodology; osteoblast; Osteoblasts; physiology; priority journal; protein content; Scanning electron microscopy; silicate; Silicates; Surface Properties; surface property; Tissue regeneration; Wollastonite; X ray fluorescence

Influence of crystallite size of nanophased hydroxyapatite on fibronectin and osteonectin adsorption and on MC3T3-E1 osteoblast adhesion and morphology - Ribeiro, N.; Sousa, S.R.; Monteiro, F.J. (Journal of Colloid and Interface ScienceJ. Colloid Interface Sci., 2010)
The characteristic topographical features (crystallite dimensions, surface morphology and roughness) of bioceramics may influence the adsorption of proteins relevant to bone regeneration. This work aims at analyzing the influence of two distinct nanophased hydroxyapatite (HA) ceramics, HA725 and HA1000 on fibronectin (FN) and osteonectin (ON) adsorption and MC3T3-E1 osteoblast adhesion and morphology. Both substrates were obtained using the same hydroxyapatite nanocrystals aggregates and applying the sintering temperatures of 725°C and 1000°C, respectively. The two proteins used in this work, FN as an adhesive glycoprotein and ON as a counter-adhesive protein, are known to be involved in the early stages of osteogenesis (cell adhesion, mobility and proliferation). The properties of the nanoHA substrates had an important role in the adsorption behavior of the two studied proteins and clearly affected the MC3T3-E1 morphology, distribution and metabolic activity. HA1000 surfaces presenting slightly larger grain size, higher root-mean-square roughness (Rq), lower surface area and porosity, allowed for higher amounts of both proteins adsorbed. These substrates also revealed increased number of exposed FN cell-binding domains as well as higher affinity for osteonectin. Regarding the osteoblast adhesion results, improved viability and cell number were found for HA1000 surfaces as compared to HA725 ones, independently of the presence or type of adsorbed protein. Therefore the osteoblast adhesion and metabolic activity seemed to be more sensitive to surfaces morphology and roughness than to the type of adsorbed proteins. © 2010 Elsevier Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JCISAdoi: 10.1016/j.jcis.2010.08.013PubMed ID: 20810127Language of Original Document: EnglishCorrespondence Address: Ribeiro, N.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: nribeiro@ineb.up.ptChemicals/CAS: fibronectin, 86088-83-7; hydroxyapatite, 1306-06-5, 51198-94-8; osteonectin, 104052-78-0; protein, 67254-75-5; Ceramics; Durapatite, 1306-06-5; Fibronectins; OsteonectinReferences: Griffith, L.G., Naughton, G., (2002) Science, 295, p. 1009;Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., (2000) J. Biomed. Mater. Res., 51, pp. 475-483; Webster, T.J., Siegel, R.W., Bizios, R., (1999) Biomaterials, 20, pp. 1221-1227; Jun, I.K., Jang, J.H., Kim, H.W., Kim, H.E., (2005) J. Mater. Sci., 40, pp. 2891-2895; Geiger, B., Bershadsky, A., Pankov, R., Yamada, K.M., (2001) Nat. Rev. Mol. Cell Biol., 2, pp. 793-805; Globus, R.K., Doty, S.B., Lull, J.C., Holmuhamedov, E., Humphries, M.J., Damsky, C.H., (1998) J. Cell Sci., 111, pp. 1385-1393; Moursi, A.M., Damsky, C.H., Lull, J., Zimmerman, D., Doty, S.B., Aota, S.I., Globus, R.K., (1996) J. Cell Sci., 109, pp. 1369-1380; Garcia, A.J., Vega, M.D., Boettiger, D., (1999) Mol. Biol. Cell, 10, pp. 785-798; Petrie, T.A., Capadona, J.R., Reyes, C.D., Garcia, A.J., (2006) Biomaterials, 27, pp. 5459-5470; Dolatshahi-Pirouz, A., Jensen, T., Foss, M., Chevallier, J., Besenbacher, F., (2009) Langmuir, 25, pp. 2971-2978; Shen, J.-W., Wu, T., Wang, Q., Pan, H.-H., (2008) Biomaterials, 29, pp. 513-532; Brekken, R.A., Sage, E.H., (2000) Matrix Biol., 19, pp. 569-580; Termine, J.D., Kleinman, H.K., Whitson, S.W., Conn, K.M., McGarvey, M.L., Martin, G.R., (1981) Cell, 26, pp. 99-105; Liao, S., Ngiam, M., Chan, C.K., Ramakrishna, S., (2009) Biomed. Mater., 4; Sarvestani, A.S., He, X., Jabbari, E., (2008) Eur. Biophys. J. Biophys. Lett., 37, pp. 229-234; Majeska, R.J., Cell Biology of Bone (1934), pp. 2-3. , in: S.C. Cowin (Ed.), Bone Mechanics HandbookKoblinski, J.E., Wu, M., Demeler, B., Jacob, K., Kleinman, H.K., (2005) J. Cell Sci., 118, pp. 2965-2974; O'Brien, J., Wilson, I., Orton, T., Pognan, F., (2000) Eur. J. Biochem., 267, pp. 5421-5426; Ribeiro, C.C., Gibson, I., Barbosa, M.A., (2006) Biomaterials, 27, pp. 1749-1761; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., (1999) J. Biomed. Mater. Res., 45, pp. 370-375; Suzuki, T., Nishizawa, K., Yokogawa, Y., Nagata, F., Kawamoto, Y., Kameyama, T., (1996) J. Ferment. Bioeng., 81, pp. 226-232; Suzuki, T., Yamamoto, T., Toriyama, M., Nishizawa, K., Yokogawa, Y., Mucalo, M.R., Kawamoto, Y., Kameyama, T., (1997) J. Biomed. Mater. Res., 34, pp. 507-517; Holland, N.B., Marchant, R.E., (2000) J. Biomed. Mater. Res., 51, pp. 307-315; Kothapalli, C., Wei, M., Vasiliev, A., Shaw, M.T., (2004) Acta Mater., 52, pp. 5655-5663; Sousa, S.R., Manuela Bras, M., Moradas-Ferreira, P., Barbosa, M.A., (2007) Langmuir, 23, pp. 7046-7054; Rouahi, M., Champion, E., Gallet, O., Jada, A., Anselme, K., (2006) Colloids Surf., B - Biointerfaces, 47, pp. 10-19; dos Santos, E.A., Farina, M., Soares, G.A., Anselme, K., (2008) J. Mater. Sci. - Mater. Med., 19, pp. 2307-2316; Amaral, I.F., Unger, R.E., Fuchs, S., Mendonca, A.M., Sousa, S.R., Barbosa, M.A., Pego, A.P., Kirkpatrick, C.J., (2009) Biomaterials, 30, pp. 5465-5475; Sousa, S.R., Moradas-Ferreira, P., Barbosa, M.A., (2005), pp. 1173-1178. , TiO2 type influences fibronectin adsorption, in: 19th Conference of the European-Society-for-Biomaterials, Springer, Sorrento, ItalyGoldstein, A.S., DiMilla, P.A., (2002) J. Biomed. Mater. Res., 59, pp. 665-675; Michael, K.E., Vernekar, V.N., Keselowsky, B.G., Meredith, J.C., Latour, R.A., Garcia, A.J., (2003) Langmuir, 19, pp. 8033-8040; Anselme, K., Bigerelle, M., (2005) Acta Biomater., 1, pp. 211-222; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., (2000) J. Biomed. Mater. Res., 49, pp. 155-166; Wang, C., Duan, Y., Markovic, B., Barbara, J., Rolfe Howlett, C., Zhang, X., Zreiqat, H., (2004) Biomaterials, 25, pp. 2949-2956; Smith, I.O., McCabe, L.R., Baumann, M.J., (2006) Int. J. Nanomed., 1, pp. 189-194; Bernards, M.T., Qin, C.L., Jiang, S.Y., Bone osteopontin, and bovine serum albumin (2008) Colloids Surf., B - Biointerfaces, 64, pp. 236-247; Durrieu, M.C., Pallu, S., Guillemot, F., Bareille, R., Amedee, J., Baquey, C., Labrugere, C., Dard, M., (2004) J. Mater. Sci. - Mater. Med., 15, pp. 779-786; Itoh, D., Yoneda, S., Kuroda, S., Kondo, H., Umezawa, A., Ohya, K., Ohyama, T., Kasugai, S., (2002) J. Biomed. Mater. Res., 62, pp. 292-298; Funk, S.E., Sage, E.H., (1993) J. Cell. Physiol., 154, pp. 53-63; Hagan, S., Hiscott, P., Sheridan, C., Wong, D., Grierson, I., McGalliard, J., (2003) Mol. Vis., 9, pp. 87-92; Deligianni, D., Korovessis, P., Porte-Derrieu, M.C., Amedee, J., (2005) J. Spinal Disord. Technol., 18, pp. 257-262; Nelson, M., Balasundaram, G., Webster, T.J., (2006) Int. J. Nanomed., 1, pp. 339-349
Keywords: Adhesion; Adhesive proteins; Adsorption; Adsorption behavior; Animals; Apatite; article; Bioceramics; Biological materials; Biomaterials; bone development; Bone Regeneration; cell adhesion; Cell Count; cell metabolism; cell motility; Cell number; cell proliferation; cell strain 3T3; cell structure; Cell-binding domain; Cells, Cultured; cellular distribution; ceramics; controlled study; Crystallite dimension; Crystallite size; Crystallization; Durapatite; Fibronectin; Fibronectin adsorption; Fibronectins; glycoprotein; grain; Grain size; human; human cell; hydroxyapatite; Hydroxyapatite nanocrystals; MC3T3-E1; Metabolic activity; metabolism; Mice; morphology; Nano-HA; nanocrystal; nanoparticles; Nanophased hydroxyapatite; osteoblast; Osteoblast adhesion; Osteoblast morphology; Osteoblasts; Osteogenesis; osteonectin; Osteonectin adsorption; Particle Size; porosity; priority journal; protein; Proteins; Root mean square roughness; Sintering; Sintering temperatures; Surface area; Surface Properties; surface property; Surface roughness; temperature; Topographical features

An intrauterine pressure generator for educational simulation of labour and delivery - Bastos, L.F.; Lobo, M.F.; van Meurs, W.L.; Ayres-de-Campos, D. (Medical Engineering and PhysicsMed. Eng. Phys., 2010)
Simulation provides a risk free and controllable environment for training of healthcare providers. The limited realism of available simulators and training programs impedes immersive training in obstetric emergencies. In developed countries, intrapartum monitoring in high-risk cases involves continuous evaluation of foetal heart rate and uterine contractions signals. We present an essential component of a high-fidelity simulator for normal and critical situations in labour and delivery, namely an intrauterine pressure generator. The signal model behind the generator consists of a truncated Gaussian curve with the programmable features: amplitude, frequency, duration, and resting tone. Through analysis of 44. h of physiological data, we demonstrate that the natural variability of these features and of the baseline pressure can be approximated by deterministic trends and stationary stochastic processes. Signal parameters can be controlled by simulation instructors, scripts, or other models to reflect different patients, pathologies, and evolving clinical situations. Twelve 40-min tracings reflecting three different patients in labour were presented to three clinical experts, who attributed similar realism scores to simulated and to real tracings. © 2010 IPEM.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: MEPHEdoi: 10.1016/j.medengphy.2010.04.015PubMed ID: 20494606Language of Original Document: EnglishCorrespondence Address: Bastos, L.F.; Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Rua Dr. Roberto Frias, s/n, I302, 4200-465 Porto, Portugal; email: lbastos@fe.up.ptReferences: Carlin, A., Alfirevic, Z., Intrapartum foetal emergencies (2006) Semin Foetal Neonatal Med, 11, pp. 150-157;Draycott, T., Sibanda, T., Owen, L., Akande, V., Winter, C., Reading, S., Does training in obstetric emergencies improve neonatal outcome? (2006) BJOG, 113, pp. 177-182; Daniels, K., Lipman, S., Harney, K., Arafeh, J., Druzin, M., Use of simulation based team training for obstetric crises in resident education (2008) Simul Healthc, 3, pp. 154-160; Gardner, R., Walzer, T.B., Simon, R., Raemer, D.B., Obstetric simulation as a risk control strategy: course design and evaluation (2008) Simul Healthc, 3, pp. 119-127; Pliego, J.F., Wehbe-Janek, H., Rajab, M.H., Browning, J.L., Fothergill, R.E., Ob/Gyn boot camp using high-fidelity human simulators: enhancing residents' perceived competency, confidence in taking a leadership role, and stress hardiness (2008) Simul Healthc, 3, pp. 82-89; Crofts, J.F., Bartlett, C., Ellis, D., Hunt, L.P., Fox, R., Draycott, T.J., Training for shoulder dystocia: a trial of simulation using low-fidelity and high-fidelity mannequins (2006) Obstet Gynecol (New York, 1953), 108, pp. 1477-1485; Gardner, R., Raemer, D.B., Simulation in obstetrics and gynecology (2008) Obstet Gynecol Clin North Am, 35, pp. 97-127; (2001) The use of electronic foetal monitoring: the use and interpretation of cardiotocography in intrapartum foetal surveillance, , Royal-College-of-Obstetricians-and-Gynaecologists, RCOG, London; (2006) Intrapartum foetal surveillance: clinical guidelines, , Royal-Australian-and-New-Zealand-College-of-Obstetricians-and-Gynaecologists, RANZCOG, Melbourne; Bracero, L.A., Roshanfekr, D., Byrne, D.W., Analysis of antepartum foetal heart rate tracing by physician and computer (2000) J Matern Foetal Med, 9, pp. 181-185; Doyle, C., Angelotti, T., Diagnosis of an unsuspected maternal hemorrhage via foetal heart rate tracing (2004) J Clin Anesth, 16, pp. 465-468; Donn, S.M., Sinha, S.K., Chiswick, M.L., (2002) Birth asphyxia and the brain: basic science and clinical implications, , Blackwell Publishing; Laros, J.R.K., Presidential address: medical-legal issues in obstetrics and gynecology (2005) Am J Obstet Gynecol, 192, pp. 1883-1889; Cusick, W., Smulian, J.C., Vintzileos, A.M., Intrapartum use of foetal heart rate monitoring, contraction monitoring, and amnioinfusion (1995) Clin Perinatol, 22, pp. 875-906; Vanner, T., Gardosi, J., Intrapartum assessment of uterine activity (1996) Baillieres Clin Obstet Gynaecol, 10, pp. 243-257; Bakker, P.C.A.M., Van Rijswijk, S., Van Rijsiwijk, S., van Geijn, H.P., Uterine activity monitoring during labor (2007) J Perinat Med, 35, pp. 468-477; Bakker, P.C.A.M., van Geijn, H.P., Uterine activity: implications for the condition of the foetus (2008) J Perinat Med, 36, pp. 30-37; Andersen, H.F., Barclay, M.L., A computer-model of uterine contractions based on discrete contractile elements (1995) Obstet Gynecol, 86, pp. 108-111. , J; Young, R.C., A computer model of uterine contractions based on action potential propagation and intercellular calcium waves (1997) Obstet Gynecol, 89, pp. 604-608. , A; Wray, S., Uterine contraction and physiological mechanisms of modulation (1993) Am J Physiol, 264, pp. C1-C18. , J; Wray, S., Kupittayanant, S., Shmygol, A., Smith, R.D., Burdyga, T., The physiological basis of uterine contractility: a short review (2001) Exp Physiol, 86, pp. 239-246; Vauge, C., Carbonne, B., Papiernik, E., Ferre, F., A mathematical model of uterine dynamics and its application to human parturition (2000) Acta Biotheor, 48, pp. 95-105. , J; Moreau, R., Pham, M.T., Redarce, T., Dupuis, O., Simulation of forceps extraction on a childbirth simulator (2008) Proceedings of the IEEE International Conference on Robotics and Automation (ICRA), pp. 1100-1105; Klavan, M., Laver, A.T., Boscola, M.A., (1977) Clinical concepts of foetal heart rate monitoring, , Hewlett-Packard Waltham, Mass; Parer, J.T., (1997) Handbook of foetal heart rate monitoring, , W.B. Saunders Company, Philadelphia; Maul, H., Maner, W.L., Olson, G., Saade, G.R., Garfield, R.E., Non-invasive transabdominal uterine electromyography correlates with the strength of intrauterine pressure and is predictive of labor and delivery (2004) J Matern Foetal Neonatal Med, 15, pp. 297-301; Cobo, E., Quintero, C.A., Strada, G., Zambrana, M.A., Uterine behavior in abruptio placentae. I. Contraction patterns and their reactivity to oxytocin (1965) Am J Obstet Gynecol, 93, pp. 1151-1156; Seitchik, J., Quantitating uterine contractility in clinical context (1981) Obstet Gynecol, 57, pp. 453-457; Burchell, H.J., Odendaal, H.J., de Wet, J.I., Badenhorst, P.N., Uterine contraction patterns in abruptio placentae (1985) S Afr Med J, 67, pp. 48-50; Harbert, G.M., Assessment of uterine contractility and activity (1992) Clin Obstet Gynecol, 35, pp. 546-558; Bruce, E.N., (2001) Biomedical signal processing and signal modeling, , Wiley-Interscience; Levinson, N., The Wiener RMS (root mean square) error criterion in filter design and prediction (1947) J Math Phys, 25, pp. 261-278; Paul, M.J., Smeltzer, J.S., Relationship of measured external tocodynamometry with measured internal uterine activity (1991) Am J Perinatol, 8, pp. 417-420; Miles, A.M., Monga, M., Richeson, K.S., Correlation of external and internal monitoring of uterine activity in a cohort of term patients (2001) Am J Perinatol, 18, pp. 137-140; van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit Comput, 13, pp. 317-324; van Meurs, W.L., Nikkelen, E., Good, M.L., Pharmacokinetic-pharmacodynamic model for educational simulations (1998) IEEE Trans Biomed Eng, 45, pp. 582-590
Keywords: article; Clinical situations; Computer simulation; delivery; Delivery, Obstetric; Developed countries; Educational simulations; Essential component; Female; Fetal monitoring; Gaussian curves; generator; Health care providers; Heart Rate, Fetal; Heart rates; High-fidelity simulators; Humans; Immersive; intrauterine pressure; labor; Labor, Obstetric; Labour and delivery; medical education; Medical educational simulation; muscle tone; Natural variability; normal distribution; Obstetrics; Physiological data; Pregnancy; Prenatal Diagnosis; Pressure; Pressure generators; priority journal; Random processes; Risk free; Signal generator; Signal generators; Signal models; Signal parameters; Signal Processing, Computer-Assisted; simulation; Stationary stochastic process; statistical model; statistical parameters; statistics; Stochastic Processes; Time Factors; Training program; Uterine activities; Uterine activity; Uterine Contraction; Uterine Monitoring; uterus contraction

A model for educational simulation of hemodynamic transitions at birth - Sá-Couto, C.D.; Andriessen, P.; van Meurs, W.L.; Ayres-de-Campos, D.; Sá-Couto, P.M. (Pediatric ResearchPediatr. Res., 2010)
Birth is characterized by swift and complex transitions in hemodynamic and respiratory variables. Unrecognized pathologies or incidents may quickly become fatal or cause permanent damage. This article introduces an essential component of an acute perinatal care simulator, namely a model for educational simulation of normal hemodynamic transitions seen during and shortly after birth. We explicitly formulate educational objectives and adapt a preexisting model for the simulation of neonatal cardiovascular physiology to include essential aspects of fetal hemodynamics. From the scientific literature, we obtain model parameters that characterize these aspects quantitatively. The fetal model is controlled by a time-and event-based script of changes occurring at birth, such as onset of breathing and cord clamping, and the transitory phase up to 24 h after birth. Comparison of simulation results with published target data confirms that realistic simulated hemodynamic vital signs are achieved. Copyright © 2010 International Pediatric Research Foundation, Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: PEREBdoi: 10.1203/PDR.0b013e3181c2def3Language of Original Document: EnglishCorrespondence Address: Van Meurs, W. L.; INEB-Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: wvanmeurs@ineb.up.ptReferences: Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324;Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., A model for educational simulation of neonatal cardiovascular pathophysiology (2006) Simul Healthc, 1, pp. 4-9; Zijlmans, M., Sá-Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., Corrected and improved model for educational simulation of neonatal cardiovascular pathophysiology (2009) Simul Healthc, 4, pp. 49-53; Goodwin, J.A., Van Meurs, W.L., Sá Couto, C.D., Beneken, J.E., Graves, S.A., A model for educational simulation of infant cardiovascular physiology (2004) Anesth Analg, 99, pp. 1655-1664; Ménigault, E., Vieyres, P., Lepoivre, B., Durand, A., Pourcelot, L., Berson, M., Fetal heart modelling based on a pressure-volume relationship (1997) Med Biol Eng Comput, 35, pp. 715-721; Pennati, G., Bellotti, M., Fumero, R., Mathematical modeling of the human foetal cardiovascular system based on Doppler ultrasound data (1997) Med Eng Phys, 19, pp. 327-335; Huikeshoven, F., Coleman, T.G., Jongsma, H.W., Mathematical model of the fetal cardiovascular system: The uncontrolled case (1980) Am J Physiol, 239, pp. R317-R325; Mielke, G., Benda, N., Cardiac output and central distribution of blood flow in the human fetus (2001) Circulation, 103, pp. 1662-1668; Cunningham, G., Leveno, K., MacDonald, P., Gilstrap III, L., Gant, N., Hankins, G., Clark, S., The morphological and functional development of the fetus (1996) Williams Obstetrics, pp. 151-190. , Cunningham G, Leveno K, MacDonald P, Gilstrap III L, Gant N, Hankins G, Clark S (eds) 20th Ed. Appleton & Lange, CT; Huikeshoven, F.J., Hope, I.D., Power, G.G., Gilbert, R.D., Longo, L.D., Mathematical model of fetal circulation and oxygen delivery (1985) Am J Physiol, 249, pp. R192-R202; Rasanen, J., Wood, D.C., Weiner, S., Ludomirski, A., Huhta, J.C., Role of the pulmonary circulation in the distribution of human fetal cardiac output during the second half of pregnancy (1996) Circulation, 94, pp. 1068-1073; Assali, N.S., Morris, J.A., Beck, R., Cardiovascular hemodynamics in the fetal lamb before and after lung expansion (1965) Am J Physiol, 208, pp. 122-129; Vilos, G.A., Liggins, G.C., Intrathoracic pressures in fetal sheep (1982) J Dev Physiol, 4, pp. 247-256; Hooper, S.B., Wallace, M.J., Role of the physicochemical environment in lung development (2006) Clin Exp Pharmacol Physiol, 33, pp. 273-279; Greenspan, J.S., Shaffer, T.H., Fox, W.W., Spitzer, A.R., Assisted ventilation: Physiologic implications and complications (1998) Fetal and Neonatal Physiology, 2. , Polin RA, Fox WW (eds) W.B. Saunders Company, Philadelphia, PA; Friedman, A.H., Fahey, J.T., The transitions from fetal to neonatal circulation: Normal responses and implications for infants with heart disease (1993) Semin Perinatol, 17, pp. 106-121; Ghanayem, N.S., Gordon, J.B., Modulation of pulmonary vasomotor tone in the fetus and neonate (2001) Respir Res, 2, pp. 139-144; Dawes, G.S., Mott, J.C., Widdicombe, J.G., Wyatt, D.G., Changes in the lungs of the new-born lamb (1953) J Physiol, 121, pp. 141-162; Brook, M.M., Heymann, M.A., Teitel, D.F., The heart (2001) Care of the High-Risk, , Klaus MH, Fanaroff AA (eds) 5th ed. W.B. Saunders Company, Philadelphia, PA; Gutyon, A.C., Fetal and neonatal physiology (1991) Textbook of Medical Physiology, , Guyton AC (ed) 8th ed. W.B. Saunders Company Philadelphia, PA; Lagercrantz, H., Bistoletti, P., Catecholamine release in the newborn infant at birth (1977) Pediatr Res, 11, pp. 889-893; Padbury, J.F., Diakomanolis, E.S., Hobel, C.J., Perelman, A., Fisher, D.A., Neonatal adaptation: Sympatho-adrenal response to umbilical cord cutting (1981) Pediatr Res, 15, pp. 1483-1487; Minoura, S., Gilbert, R.D., Postnatal change of cardiac function in lambs: Effects of ganglionic block and afterload (1987) J Dev Physiol, 9, pp. 123-135; Coskun, S., Yüksel, H., Bilgi, Y., Lacin, S., Tansug, N., Onag, A., Non-invasive evaluation of the adaptations of cardiac function in the neonatal period: A comparison of healthy infants delivered by vaginal route and caesarean section (2001) Acta Med Okayama, 55, pp. 213-218; Kishkurno, S., Takahashi, Y., Harada, K., Ishida, A., Tamura, M., Takada, G., Postnatal changes in left ventricular volume and contractility in healthy term infants (1997) Pediatric Cardiology, 18 (2), pp. 91-95. , DOI 10.1007/s002469900123; Shiota, T., Harada, K., Takada, G., Left ventricular systolic and diastolic function during early neonatal period using transthoracic echocardiography (2002) Tohoku J Exp Med, 197, pp. 151-158; Walther, F.J., Benders, M.J., Leighton, J.O., Early changes in the neonatal circulatory transition (1993) J Pediatr, 123, pp. 625-632; Hiraishi, S., Misawa, H., Oguchi, K., Kadoi, N., Saito, K., Fujino, N., Hojo, M., Yashiro, K., Two-dimensional Doppler echocardiographic assessment of closure of the ductus arteriosus in normal newborn infants (1987) J Pediatr, 111, pp. 755-760; Migliavacca, F., Dubini, G., Pennati, G., Pietrabissa, R., Fumero, R., Hsia, T.Y., De Leval, M.R., Computational model of the fluid dynamics in systemic-to-pulmonary shunts (2000) J Biomech, 33, pp. 549-557; Teitel, D.F., Iwamoto, H.S., Rudolph, A.M., Effects of birth-related events on central blood flow patterns (1987) Pediatr Res, 22, pp. 557-566; Anderson, D.F., Bissonnette, J.M., Faber, J.J., Thornburg, K.L., Central shunt flows and pressures in the mature fetal lamb (1981) Am J Physiol, 241, pp. H60-H66; Agata, Y., Hiraishi, S., Oguchi, K., Misawa, H., Horiguchi, Y., Fujino, N., Yashiro, K., Shimada, N., Changes in left ventricular output from fetal to early neonatal life (1991) J Pediatr, 119, pp. 441-445; Harada, K., Shiota, T., Takahashi, Y., Tamura, M., Takada, G., Changes in the volume and performance of the left ventricle in the early neonatal period (1994) Early Hum Dev, 39, pp. 201-209; Moss, A.J., Emmanouilides, G.C., Adams, F.H., Chuang, K., Response of ductus arteriosus and pulmonary and systemic arterial pressure to changes in oxygen environment in newborn infants (1964) Pediatrics, 33, pp. 937-944; Emmanouilides, G.C., Moss, A.J., Monset-Couchard, M., Marcano, B.A., Rzeznic, B., Cardiac output in newborn infants (1970) Biol Neonate, 15, pp. 186-197; Emmanouilides, G.C., Moss, A.J., Duffie Jr., E.R., Adams, F.H., Pulmonary arterial pressure changes in human newborn infants from birth to 3 days of age (1964) J Pediatr, 65, pp. 327-333; Soni, N., Williams, P., Positive pressure ventilation: What is the real cost? (2008) Br J Anaesth, 101, pp. 446-457; Moss, A.J., Emmanouilides, G.C., Duffie Jr., E.R., Closure of the ductus arteriosus in the newborn infant (1963) Pediatrics, 32, pp. 25-30
Keywords: article; artificial ventilation; biological model; birth; Blood flow; blood flow velocity; blood pressure; breathing; breathing mechanics; cardiovascular function; clamp; comparative study; Computer simulation; Constriction; education; evaluation; fetus; hemodynamics; human; Humans; Infant, Newborn; ligation; Models, Cardiovascular; newborn; Parturition; perinatal care; priority journal; Regional Blood Flow; reproducibility; Reproducibility of Results; Respiration, Artificial; Respiratory Mechanics; scientific literature; simulator; stimulation; time; Time Factors; umbilical cord; vascularization; vital sign

Neuropeptide y and osteoblast differentiation - The balance between the neuro-osteogenic network and local control: Review Article - Franquinho, F.; Liz, M.A.; Nunes, A.F.; Neto, E.; Lamghari, M.; Sousa, M.M. (FEBS JournalFEBS J., 2010)
Accumulating evidence has contributed to a novel view in bone biology: bone remodeling, specifically osteoblast differentiation, is under the tight control of the central and peripheral nervous systems. Among other players in this neuro-osteogenic network, the neuropeptide Y (NPY) system has attracted particular attention. At the central nervous system level, NPY exerts its function in bone homeostasis through the hypothalamic Y2 receptor. Locally in the bone, NPY action is mediated by its Y1 receptor. Besides the presence of Y1, a complex network exists locally: not only there is input of the peripheral nervous system, as the bone is directly innervated by NPY-containing fibers, but there is also input from non-neuronal cells, including bone cells capable of NPY expression. The interaction of these distinct players to achieve a multilevel control system of bone homeostasis is still under debate. In this review, we will integrate the current knowledge on the impact of the NPY system in bone biology, and discuss the mechanisms through which the balance between central and the peripheral NPY action might be achieved. © 2010 FEBS.
Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1111/j.1742-4658.2010.07774.xPubMed ID: 20681986Language of Original Document: EnglishCorrespondence Address: Sousa, M. M.; IBMC, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: msousa@ibmc.up.ptChemicals/CAS: neuropeptide Y, 82785-45-3, 83589-17-7; Leptin; Neuropeptide Y; Protein Isoforms; Receptors, Neuropeptide YReferences: Bellido, T., Ali, A.A., Gubrij, I., Plotkin, L.I., Fu, Q., O'Brien, C.A., Manolagas, S.C., Jilka, R.L., Chronic elevation of parathyroid hormone in mice reduces expression of sclerostin by osteocytes: A novel mechanism for hormonal control of osteoblastogenesis (2005) Endocrinology, 146, pp. 4577-4583;Keller, H., Kneissel, M., SOST is a target gene for PTH in bone (2005) Bone, 37, pp. 148-158; O'Brien, C.A., Plotkin, L.I., Galli, C., Goellner, J.J., Gortazar, A.R., Allen, M.R., Robling, A.G., Turner, C.H., Control of bone mass and remodeling by PTH receptor signaling in osteocytes (2008) PLoS ONE, 3, p. 2942; Robling, A.G., Niziolek, P.J., Baldridge, L.A., Condon, K.W., Allen, M.R., Alam, I., Mantila, S.M., Harris, S.E., Mechanical stimulation of bone in vivo reduces osteocyte expression of Sost/sclerostin (2008) J Biol Chem, 283, pp. 5866-5875; Tatsumi, S., Ishii, K., Amizuka, N., Li, M., Kobayashi, T., Kohno, K., Ito, M., Ikeda, K., Targeted ablation of osteocytes induces osteoporosis with defective mechanotransduction (2007) Cell Metab, 5, pp. 464-475; McDonald, A.C., Schuijers, J.A., Shen, P.J., Gundlach, A.L., Grills, B.L., Expression of galanin and galanin receptor-1 in normal bone and during fracture repair in the rat (2003) Bone, 33, pp. 788-797; Pacifici, R., Cytokines, estrogen, and postmenopausal osteoporosis - The second decade (1998) Endocrinology, 139, pp. 2659-2661; You, L., Temiyasathit, S., Lee, P., Kim, C.H., Tummala, P., Yao, W., Kingery, W., Jacobs, C.R., Osteocytes as mechanosensors in the inhibition of bone resorption due to mechanical loading (2008) Bone, 42, pp. 172-179; Lerner, U.H., The role of skeletal nerve fibers in bone metabolism (2000) Endocrinologist, 10, pp. 377-382; Sherman, M.S., The nerves of bone (1963) J Bone Joint Surg Am, 45, pp. 522-528; Kuntz, A., Richins, C.A., Innervation of the bone marrow (1945) J Comp Neurol, 83, pp. 213-222; Miller, M.R., Kasahara, M., Observations on innervation of human long bones (1963) Anat Rec, 145, pp. 13-23; Thurston, T.J., Distribution of nerves in long bones as shown by silver impregnation (1982) J Anat, 134, pp. 719-728; Calvo, W., Fortezav, J., On development of bone marrow innervation in new-born rats as studied with silver impregnation and electron microscopy (1969) Am J Anat, 126, pp. 355-371; Sisask, G., Bjurholm, A., Ahmed, M., Kreicbergs, A., The development of autonomic innervation in bone and joints of the rat (1996) J Auton Nerv Syst, 59, pp. 27-33; Gajda, M., Litwin, J.A., Cichocki, T., Timmermans, J.P., Adriaensen, D., Development of sensory innervation in rat tibia: Co-localization of CGRP and substance P with growth-associated protein 43 (GAP-43) (2005) J Anat, 207, pp. 135-144; Jackman, A., Fitzgerald, M., Development of peripheral hindlimb and central spinal cord innervation by subpopulations of dorsal root ganglion cells in the embryonic rat (2000) J Comp Neurol, 418, pp. 281-298; Kosaras, B., Jakubowski, M., Kainz, V., Burstein, R., Sensory innervation of the calvarial bones of the mouse (2009) J Comp Neurol, 515, pp. 331-348; Jones, K.B., Mollano, A.V., Morcuende, J.A., Cooper, R.R., Saltzman, C.L., Bone and brain: A review of neural, hormonal, and musculoskeletal connections (2004) Iowa Orthop J, 24, pp. 123-132; Alberius, P., Skagerberg, G., Adrenergic innervation of the calvarium of the neonatal rat. Its relationship to the sagittal suture and developing parietal bones (1990) Anat Embryol (Berl), 182, pp. 493-498; Herskovits, M.S., Hallas, B.H., Singh, I.J., Study of sympathetic innervation of cranial bones by axonal transport of horseradish peroxidase in the rat: Preliminary findings (1993) Acta Anat (Basel), 147, pp. 178-183; Hill, E.L., Elde, R., Distribution of CGRP-, VIP-, D beta H-, SP-, and NPY-immunoreactive nerves in the periosteum of the rat (1991) Cell Tissue Res, 264, pp. 469-480; Kruger, L., Silverman, J.D., Mantyh, P.W., Sternini, C., Brecha, N.C., Peripheral patterns of calcitonin-gene-related peptide general somatic sensory innervation: Cutaneous and deep terminations (1989) J Comp Neurol, 280, pp. 291-302; Silverman, J.D., Kruger, L., Calcitonin-gene-related-peptide-immunoreactive innervation of the rat head with emphasis on specialized sensory structures (1989) J Comp Neurol, 280, pp. 303-330; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., Leptin inhibits bone formation through a hypothalamic relay: A central control of bone mass (2000) Cell, 100, pp. 197-207; Robertson, S.A., Leinninger, G.M., Myers, Jr.M.G., Molecular and neural mediators of leptin action (2008) Physiol Behav, 94, pp. 637-642; Ahima, R.S., Flier, J.S., Leptin (2000) Annu Rev Physiol, 62, pp. 413-437; Tartaglia, L.A., Dembski, M., Weng, X., Deng, N., Culpepper, J., Devos, R., Richards, G.J., Deeds, J., Identification and expression cloning of a leptin receptor, OB-R (1995) Cell, 83, pp. 1263-1271; Zhang, Y., Proenca, R., Maffei, M., Barone, M., Leopold, L., Friedman, J.M., Positional cloning of the mouse obese gene and its human homologue (1994) Nature, 372, pp. 425-432; Takeda, S., Elefteriou, F., Levasseur, R., Liu, X., Zhao, L., Parker, K.L., Armstrong, D., Karsenty, G., Leptin regulates bone formation via the sympathetic nervous system (2002) Cell, 111, pp. 305-317; Stephens, T.W., Basinski, M., Bristow, P.K., Bue-Valleskey, J.M., Burgett, S.G., Craft, L., Hale, J., Kriauciunas, A., The role of neuropeptide y in the antiobesity action of the obese gene product (1995) Nature, 377, pp. 530-532; Chronwall, B.M., Dimaggio, D.A., Massari, V.J., Pickel, V.M., Ruggiero, D.A., O'Donohue, T.L., The anatomy of neuropeptide-Y-containing neurons in rat brain (1985) Neuroscience, 15, pp. 1159-1181; Tatemoto, K., Carlquist, M., Mutt, V., Neuropeptide y - A novel brain peptide with structural similarities to peptide YY and pancreatic polypeptide (1982) Nature, 296, pp. 659-660; Pedrazzini, T., Pralong, F., Grouzmann, E., Neuropeptide Y: The universal soldier (2003) Cell Mol Life Sci, 60, pp. 350-377; Erickson, J.C., Hollopeter, G., Palmiter, R.D., Attenuation of the obesity syndrome of ob/ob mice by the loss of neuropeptide y (1996) Science, 274, pp. 1704-1707; Allison, S.J., Baldock, P.A., Herzog, H., The control of bone remodeling by neuropeptide y receptors (2007) Peptides, 28, pp. 320-325; Bjurholm, A., Kreicbergs, A., Terenius, L., Goldstein, M., Schultzberg, M., Neuropeptide Y-, tyrosine hydroxylase- and vasoactive intestinal polypeptide-immunoreactive nerves in bone and surrounding tissues (1988) J Auton Nerv Syst, 25, pp. 119-125; Ahmed, M., Bjurholm, A., Kreicbergs, A., Schultzberg, M., Neuropeptide Y, tyrosine hydroxylase and vasoactive intestinal polypeptide-immunoreactive nerve fibers in the vertebral bodies, discs, dura mater, and spinal ligaments of the rat lumbar spine (1993) Spine, 18, pp. 268-273; Hill, E.L., Turner, R., Elde, R., Effects of neonatal sympathectomy and capsaicin treatment on bone remodeling in rats (1991) Neuroscience, 44, pp. 747-755; Lindblad, B.E., Nielsen, L.B., Jespersen, S.M., Bjurholm, A., Bunger, C., Hansen, E.S., Vasoconstrictive action of neuropeptide y in bone. The porcine tibia perfused in vivo (1994) Acta Orthop Scand, 65, pp. 629-634; Ahmad, T., Ugarph-Morawski, A., Li, J., Bileviciute-Ljungar, I., Finn, A., Ostenson, C.G., Kreicbergs, A., Bone and joint neuropathy in rats with type-2 diabetes (2004) Regul Pept, 119, pp. 61-67; Ericsson, A., Schalling, M., McIntyre, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., Detection of neuropeptide y and its mRNA in megakaryocytes: Enhanced levels in certain autoimmune mice (1987) Proc Natl Acad Sci USA, 84, pp. 5585-5589; Ahmed, M., Srinivasan, G.R., Theodorsson, E., Bjurholm, A., Kreicbergs, A., Extraction and quantitation of neuropeptides in bone by radioimmunoassay (1994) Regul Pept, 51, pp. 179-188; Bjurholm, A., Neuroendocrine peptides in bone (1991) Int Orthop, 15, pp. 325-329; Bjurholm, A., Kreicbergs, A., Schultzberg, M., Lerner, U.H., Neuroendocrine regulation of cyclic AMP formation in osteoblastic cell lines (UMR-106-01, ROS 17/2.8, MC3T3-E1, and Saos-2) and primary bone cells (1992) J Bone Miner Res, 7, pp. 1011-1019; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Simmons, P., Greater bone formation of Y2 knockout mice is associated with increased osteoprogenitor numbers and altered Y1 receptor expression (2007) J Biol Chem, 282, pp. 19082-19091; Nakamura, M., Sakanaka, C., Aoki, Y., Ogasawara, H., Tsuji, T., Kodama, H., Matsumoto, T., Noma, M., Identification of two isoforms of mouse neuropeptide Y-Y1 receptor generated by alternative splicing. Isolation, genomic structure, and functional expression of the receptors (1995) J Biol Chem, 270, pp. 30102-30110; Togari, A., Arai, M., Mizutani, S., Koshihara, Y., Nagatsu, T., Expression of mRNAs for neuropeptide receptors and beta-adrenergic receptors in human osteoblasts and human osteogenic sarcoma cells (1997) Neurosci Lett, 233, pp. 125-128; Igwe, J.C., Jiang, X., Paic, F., Ma, L., Adams, D.J., Baldock, P.A., Pilbeam, C.C., Kalajzic, I., Neuropeptide y is expressed by osteocytes and can inhibit osteoblastic activity (2009) J Cell Biochem, 108, pp. 621-630; Nunes, A.F., Liz, M.A., Franquinho, F., Teixeira, L., Sousa, V., Chenu, C., Lamghari, M., Sousa, M.M., Neuropeptide y expression and function during osteoblast differentiation - Insights from transthyretin knockout mice (2010) FEBS J, 277, pp. 263-275; Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Thomas, G.P., Gardiner, E.M., Herzog, H., Hypothalamic Y2 receptors regulate bone formation (2002) J Clin Invest, 109, pp. 915-921; Ducy, P., Schinke, T., Karsenty, G., The osteoblast: A sophisticated fibroblast under central surveillance (2000) Science, 289, pp. 1501-1504; Allison, S.J., Baldock, P., Sainsbury, A., Enriquez, R., Lee, N.J., Lin, E.J., Klugmann, M., Li, M., Conditional deletion of hypothalamic Y2 receptors reverts gonadectomy-induced bone loss in adult mice (2006) J Biol Chem, 281, pp. 23436-23444; Clegg, D.J., Brown, L.M., Zigman, J.M., Kemp, C.J., Strader, A.D., Benoit, S.C., Woods, S.C., Geary, N., Estradiol-dependent decrease in the orexigenic potency of ghrelin in female rats (2007) Diabetes, 56, pp. 1051-1058; Zengin, A., Zhang, L., Herzog, H., Baldock, P.A., Sainsbury, A., Neuropeptide y and sex hormone interactions in humoral and neuronal regulation of bone and fat (2010) Trends Endocrinol Metab, 21, pp. 411-418; Hosaka, H., Nagata, A., Yoshida, T., Shibata, T., Nagao, T., Tanaka, T., Saito, Y., Tatsuno, I., Pancreatic polypeptide is secreted from and controls differentiation through its specific receptors in osteoblastic MC3T3-E1 cells (2008) Peptides, 29, pp. 1390-1395; Teixeira, L., Sousa, D.M., Nunes, A.F., Sousa, M.M., Herzog, H., Lamghari, M., NPY revealed as a critical modulator of osteoblast function in vitro: New insights into the role of Y1 and Y2 receptors (2009) J Cell Biochem, 107, pp. 908-916; Sainsbury, A., Schwarzer, C., Couzens, M., Herzog, H., Y2 receptor deletion attenuates the type 2 diabetic syndrome of ob/ob mice (2002) Diabetes, 51, pp. 3420-3427; Wilding, J.P., Gilbey, S.G., Bailey, C.J., Batt, R.A., Williams, G., Ghatei, M.A., Bloom, S.R., Increased neuropeptide-Y messenger ribonucleic acid (mRNA) and decreased neurotensin mRNA in the hypothalamus of the obese (ob/ob) mouse (1993) Endocrinology, 132, pp. 1939-1944; Baldock, P.A., Allison, S., McDonald, M.M., Sainsbury, A., Enriquez, R.F., Little, D.G., Eisman, J.A., Herzog, H., Hypothalamic regulation of cortical bone mass: Opposing activity of Y2 receptor and leptin pathways (2006) J Bone Miner Res, 21, pp. 1600-1607; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., Hypothalamic control of bone formation: Distinct actions of leptin and y2 receptor pathways (2005) J Bone Miner Res, 20, pp. 1851-1857; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., During, M.J., Novel role of Y1 receptors in the coordinated regulation of bone and energy homeostasis (2007) J Biol Chem, 282, pp. 19092-19102; Lee, N.J., Doyle, K.L., Sainsbury, A., Enriquez, R.F., Hort, Y.J., Riepler, S.J., Baldock, P.A., Herzog, H., Critical role for Y1 receptors in mesenchymal progenitor cell differentiation and osteoblast activity (2010) J Bone Miner Res, , doi:; Allison, S.J., Baldock, P.A., Enriquez, R.F., Lin, E., During, M., Gardiner, E.M., Eisman, J.A., Herzog, H., Critical interplay between neuropeptide y and sex steroid pathways in bone and adipose tissue homeostasis (2009) J Bone Miner Res, 24, pp. 294-304; Sainsbury, A., Baldock, P.A., Schwarzer, C., Ueno, N., Enriquez, R.F., Couzens, M., Inui, A., Gardiner, E.M., Synergistic effects of Y2 and Y4 receptors on adiposity and bone mass revealed in double knockout mice (2003) Mol Cell Biol, 23, pp. 5225-5233; Elefteriou, F., Takeda, S., Liu, X., Armstrong, D., Karsenty, G., Monosodium glutamate-sensitive hypothalamic neurons contribute to the control of bone mass (2003) Endocrinology, 144, pp. 3842-3847; Baldock, P.A., Lee, N.J., Driessler, F., Lin, S., Allison, S., Stehrer, B., Lin, E.J., Wong, I.P., Neuropeptide y knockout mice reveal a central role of NPY in the coordination of bone mass to body weight (2009) PLoS ONE, 4, p. 8415; Sainsbury, A., Cusin, I., Doyle, P., Rohner-Jeanrenaud, F., Jeanrenaud, B., Intracerebroventricular administration of neuropeptide y to normal rats increases obese gene expression in white adipose tissue (1996) Diabetologia, 39, pp. 353-356; Sainsbury, A., Herzog, H., Inhibitory effects of central neuropeptide y on the somatotropic and gonadotropic axes in male rats are independent of adrenal hormones (2001) Peptides, 22, pp. 467-471; Nunes, A.F., Saraiva, M.J., Sousa, M.M., Transthyretin knockouts are a new mouse model for increased neuropeptide y (2006) FASEB J, 20, pp. 166-168; Prigge, S.T., Mains, R.E., Eipper, B.A., Amzel, L.M., New insights into copper monooxygenases and peptide amidation: Structure, mechanism and function (2000) Cell Mol Life Sci, 57, pp. 1236-1259; Eipper, B.A., Stoffers, D.A., Mains, R.E., The biosynthesis of neuropeptides: Peptide alpha-amidation (1992) Annu Rev Neurosci, 15, pp. 57-85; Marques, F., Sousa, J.C., Oliveira, P., Oliveira, H.C., Palha, J.A., The absence of transthyretin does not impair regulation of lipid and glucose metabolism (2007) Horm Metab Res, 39, pp. 529-533
Keywords: Animals; Bone and Bones; bone cell; bone innervation; bone mass; cell differentiation; Homeostasis; Humans; immunoreactivity; leptin; Nerve Net; neuropeptide Y; neuropeptide Y receptor; neuropeptide Y2 receptor; nonhuman; NPY; NPY receptors; osteoblast; Osteoblasts; phenotype; priority journal; protein expression; protein interaction; Protein Isoforms; Receptors, Neuropeptide Y; review

Neuropeptide y expression and function during osteoblast differentiation - Insights from transthyretin knockout mice - Nunes, A.F.; Liz, M.A.; Franquinho, F.; Teixeira, L.; Sousa, V.; Chenu, C.; Lamghari, M.; Sousa, M.M. (FEBS JournalFEBS J., 2010)
To better understand the role of neuropeptide Y (NPY) in bone homeostasis, as its function in the regulation of bone mass is unclear, we assessed its expression in this tissue. By immunohistochemistry, we demonstrated, both at embryonic stages and in the adult, that NPY is synthesized by osteoblasts, osteocytes, and chondrocytes. Moreover, peptidylglycine α-amidating monooxygenase, the enzyme responsible for NPY activation by amidation, was also expressed in these cell types. Using transthyretin (TTR) KO mice as a model of augmented NPY levels, we showed that this strain has increased NPY content in the bone, further validating the expression of this neuropeptide by bone cells. Moreover, the higher amidated neuropeptide levels in TTR KO mice were related to increased bone mineral density and trabecular volume. Additionally, RT-PCR analysis established that NPY is not only expressed in MC3T3-E1 osteoblastic cells and bone marrow stromal cells (BMSCs), but is also detectable by RIA in BMSCs undergoing osteoblastic differentiation. In agreement with our in vivo observations, in vitro, TTR KO BMSCs differentiated in osteoblasts had increased NPY levels and exhibited enhanced competence in undergoing osteoblastic differentiation. In summary, this work contributes to a better understanding of the role of NPY in the regulation of bone formation by showing that this neuropeptide is expressed in bone cells and that increased amidated neuropeptide content is related to increased bone mass. © 2009 FEBS.
Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1111/j.1742-4658.2009.07482.xPubMed ID: 19954489Language of Original Document: EnglishCorrespondence Address: Sousa, M. M.; IBMC, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: msousa@ibmc.up.ptChemicals/CAS: neuropeptide Y, 82785-45-3, 83589-17-7; Amides; DNA Primers; Neuropeptide Y; Prealbumin; RNA, MessengerReferences: McDonald, A.C., Schuijers, J.A., Shen, P.J., Gundlach, A.L., Grills, B.L., Expression of galanin and galanin receptor-1 in normal bone and during fracture repair in the rat (2003) Bone, 33, pp. 788-797;Pacifici, R., Cytokines, estrogen, and postmenopausal osteoporosis - The second decade (1998) Endocrinology, 139, pp. 2659-2661; You, L., Temiyasathit, S., Lee, P., Kim, C.H., Tummala, P., Yao, W., Kingery, W., Jacobs, C.R., Osteocytes as mechanosensors in the inhibition of bone resorption due to mechanical loading (2008) Bone, 42, pp. 172-179; Chenu, C., Marenzana, M., Sympathetic nervous system and bone remodeling (2005) Joint Bone Spine, 72 (6), pp. 481-483. , DOI 10.1016/j.jbspin.2005.10.007, PII S1297319X05001661; Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Thomas, G.P., Gardiner, E.M., Herzog, H., Hypothalamic Y2 receptors regulate bone formation (2002) J Clin Invest, 109, pp. 915-921; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., During, M.J., Novel role of Y1 receptors in the coordinated regulation of bone and energy homeostasis (2007) J Biol Chem, 282, pp. 19092-19102; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., Leptin inhibits bone formation through a hypothalamic relay: A central control of bone mass (2000) Cell, 100, pp. 197-207; Elefteriou, F., Takeda, S., Liu, X., Armstrong, D., Karsenty, G., Monosodium glutamate-sensitive hypothalamic neurons contribute to the control of bone mass (2003) Endocrinology, 144, pp. 3842-3847; Elefteriou, F., Neuronal signaling and the regulation of bone remodeling (2005) Cell Mol Life Sci, 62, pp. 2339-2349; Bjurholm, A., Kreicbergs, A., Terenius, L., Goldstein, M., Schultzberg, M., Neuropeptide Y-, tyrosine hydroxylase- and vasoactive intestinal polypeptide-immunoreactive nerves in bone and surrounding tissues (1988) J Auton Nerv Syst, 25, pp. 119-125; Hill, E.L., Elde, R., Distribution of CGRP-, VIP-, D beta H-, SP-, and NPY-immunoreactive nerves in the periosteum of the rat (1991) Cell Tissue Res, 264, pp. 469-480; Tabarowski, Z., Gibson-Berry, K., Felten, S.Y., Noradrenergic and peptidergic innervation of the mouse femur bone marrow (1996) Acta Histochem, 98, pp. 453-457; Ahmed, M., Srinivasan, G.R., Theodorsson, E., Bjurholm, A., Kreicbergs, A., Extraction and quantitation of neuropeptides in bone by radioimmunoassay (1994) Regul Pept, 51, pp. 179-188; Ericsson, A., Schalling, M., McIntyre, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., Detection of neuropeptide y and its mRNA in megakaryocytes: Enhanced levels in certain autoimmune mice (1987) Proc Natl Acad Sci USA, 84, pp. 5585-5589; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Simmons, P., Greater bone formation of y2 knockout mice is associated with increased osteoprogenitor numbers and altered y1 receptor expression (2007) J Biol Chem, 282, pp. 19082-19091; Stephens, T.W., Basinski, M., Bristow, P.K., Bue-Valleskey, J.M., Burgett, S.G., Craft, L., Hale, J., Kriauciunas, A., The role of neuropeptide y in the antiobesity action of the obese gene product (1995) Nature, 377, pp. 530-532; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., Hypothalamic control of bone formation: Distinct actions of leptin and y2 receptor pathways (2005) J Bone Miner Res, 20, pp. 1851-1857; Allison, S., Baldock, P., Enriquez, R., Lin, E., During, M., Gardiner, E., Eisman, J., Herzog, H., Critical interplay between neuropeptide y and sex steroid pathways in bone and adipose tissue homeostasis (2008) J Bone Miner Res, 24, pp. 294-304; Nunes, A.F., Saraiva, M.J., Sousa, M.M., Transthyretin knockouts are a new mouse model for increased neuropeptide y (2006) FASEB J, 20, pp. 166-168; Mains, R.E., Cullen, E.I., May, V., Eipper, B.A., The role of secretory granules in peptide biosynthesis (1987) Ann NY Acad Sci, 493, pp. 278-291; Prigge, S.T., Mains, R.E., Eipper, B.A., Amzel, L.M., New insights into copper monooxygenases and peptide amidation: Structure, mechanism and function (2000) Cell Mol Life Sci, 57, pp. 1236-1259; Eipper, B.A., Stoffers, D.A., Mains, R.E., The biosynthesis of neuropeptides: Peptide alpha-amidation (1992) Annu Rev Neurosci, 15, pp. 57-85; Teixeira, L., Sousa, D.M., Nunes, A.F., Sousa, M.M., Herzog, H., Lamghari, M., NPY revealed as a critical modulator of osteoblast function in vitro: New insights into the role of Y1 and Y2 receptors (2009) J Cell Biochem, 107, pp. 908-916; Amano, S., Arai, M., Goto, S., Togari, A., Inhibitory effect of NPY on isoprenaline-induced osteoclastogenesis in mouse bone marrow cells (2007) Biochim Biophys Acta, 1770, pp. 966-973; Baldock, P.A., Allison, S., McDonald, M.M., Sainsbury, A., Enriquez, R.F., Little, D.G., Eisman, J.A., Herzog, H., Hypothalamic regulation of cortical bone mass: Opposing activity of Y2 receptor and leptin pathways (2006) J Bone Miner Res, 21, pp. 1600-1607; Saper, C.B., Loewy, A.D., Swanson, L.W., Cowan, W.M., Direct hypothalamo-autonomic connections (1976) Brain Res, 117, pp. 305-312; Navia, J.M., Harris, S.S., Vitamin A influence on calcium metabolism and calcification (1980) Ann NY Acad Sci, 355, pp. 45-57; Wang, A., Ding, X., Sheng, S., Yao, Z., Retinoic acid inhibits osteogenic differentiation of rat bone marrow stromal cells (2008) Biochem Biophys Res Commun, 375, pp. 435-439; Takahashi, T., Kamiya, N., Kawabata, N., Takagi, M., The effect of retinoic acid on a zinc finger transcription factor, AJ18, during differentiation of a rat clonal preosteoblastic cell line, ROB-C20, into osteoblasts (2008) Arch Oral Biol, 53, pp. 87-94; Grouzmann, E., Comoy, E., Walker, P., Burnier, M., Bohuon, C., Waeber, B., Brunner, H., Production and characterization of four anti-neuropeptide y monoclonal antibodies (1992) Hybridoma, 11, pp. 409-424; Wei, S., Episkopou, V., Piantedosi, R., Maeda, S., Shimada, K., Gottesman, M.E., Blaner, W.S., Studies on the metabolism of retinol and retinol-binding protein in transthyretin-deficient mice produced by homologous recombination (1995) J Biol Chem, 270, pp. 866-870; Karga, H., Papapetrou, P.D., Korakovouni, A., Papandroulaki, F., Polymeris, A., Pampouras, G., Bone mineral density in hyperthyroidism (2004) Clin Endocrinol, 61, pp. 466-472; Episkopou, V., Maeda, S., Nishiguchi, S., Shimada, K., Gaitanaris, G.A., Gottesman, M.E., Robertson, E.J., Disruption of the transthyretin gene results in mice with depressed levels of plasma retinol and thyroid hormone (1993) Proc Natl Acad Sci USA, 90, pp. 2375-2379; Palha, J.A., Episkopou, V., Maeda, S., Shimada, K., Gottesman, M.E., Saraiva, M.J., Thyroid hormone metabolism in a transthyretin-null mouse strain (1994) J Biol Chem, 269, pp. 33135-33139; Palha, J.A., Hays, M.T., Morreale De Escobar, G., Episkopou, V., Gottesman, M.E., Saraiva, M.J., Transthyretin is not essential for thyroxine to reach the brain and other tissues in transthyretin-null mice (1997) Am J Physiol, 272, pp. 485-E493; Palha, J.A., Fernandes, R., De Escobar, G.M., Episkopou, V., Gottesman, M., Saraiva, M.J., Transthyretin regulates thyroid hormone levels in the choroid plexus, but not in the brain parenchyma: Study in a transthyretin-null mouse model (2000) Endocrinology, 141, pp. 3267-3272; Kingery, W.S., Offley, S.C., Guo, T.Z., Davies, M.F., Clark, J.D., Jacobs, C.R., A substance P receptor (NK1) antagonist enhances the widespread osteoporotic effects of sciatic nerve section (2003) Bone, 33, pp. 927-936; Hosaka, H., Nagata, A., Yoshida, T., Shibata, T., Nagao, T., Tanaka, T., Saito, Y., Tatsuno, I., Pancreatic polypeptide is secreted from and controls differentiation through its specific receptors in osteoblastic MC3T3-E1 cells (2008) Peptides, 29, pp. 1390-1395; Fleming, C.E., Saraiva, M.J., Sousa, M.M., Transthyretin enhances nerve regeneration (2007) J Neurochem, 103, pp. 831-839; Sainsbury, A., Cusin, I., Doyle, P., Rohner-Jeanrenaud, F., Jeanrenaud, B., Intracerebroventricular administration of neuropeptide y to normal rats increases obese gene expression in white adipose tissue (1996) Diabetologia, 39, pp. 353-356; Sainsbury, A., Herzog, H., Inhibitory effects of central neuropeptide y on the somatotropic and gonadotropic axes in male rats are independent of adrenal hormones (2001) Peptides, 22, pp. 467-471; Marques, F., Sousa, J.C., Oliveira, P., Oliveira, H.C., Palha, J.A., The absence of transthyretin does not impair regulation of lipid and glucose metabolism (2007) Horm Metab Res, 39, pp. 529-533; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Salingcarnboriboon, R., Tsuji, K., Komori, T., Nakashima, K., Ezura, Y., Noda, M., Runx2 is a target of mechanical unloading to alter osteoblastic activity and bone formation in vivo (2006) Endocrinology, 147, pp. 2296-2305
Keywords: 3T3 Cells; alpha amidating enzyme; Amidated neuropeptide; amidation; Amides; animal cell; animal tissue; Animals; article; Base Sequence; Bone Density; bone development; bone marrow cell; Bone Marrow Cells; Bone marrow stromal cells; bone mass; cartilage cell; cell differentiation; Cells, Cultured; Chondrocytes; controlled study; developmental stage; DNA Primers; embryo; embryo development; Homeostasis; immunohistochemistry; male; Mice; Mice, Knockout; mouse; Mus; neuropeptide Y; nonhuman; NPY; ossification; osteoblast; Osteoblastic differentiation; Osteoblasts; osteocyte; Osteocytes; peptide synthesis; prealbumin; priority journal; protein expression; protein function; radioimmunoassay; regulatory mechanism; reverse transcription polymerase chain reaction; RNA, Messenger; stroma cell; Stromal Cells; trabecular bone

Protein matrices for improved wound healing: Elastase inhibition by a synthetic peptide model - Vasconcelos, A.; Pêgo, A.P.; Henriques, L.; Lamghari, M.; Cavaco-Paulo, A. (BiomacromoleculesBiomacromolecules, 2010)
The unique properties of silk fibroin were combined with keratin to develop new wound-dressing materials. Silk fibroin/keratin (SF/K) films were prepared to reduce high levels of elastase found on chronic wounds. This improved biological function was achieved by the incorporation of a small peptide synthesized based on the reactive-site loop of the Bowman-Birk Inhibitor (BBI) protein. In vitro degradation and release were evaluated using porcine pancreatic elastase (PPE) solution as a model of wound exudate. It was found that biological degradation and release rate are highly dependent on film composition. Furthermore, the level of PPE activity can be tuned by changing the film composition, thus showing an innovative way of controlling the elastase-antielastase imbalance found on chronic wounds. © 2010 American Chemical Society.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm100537bPubMed ID: 20690591Language of Original Document: EnglishCorrespondence Address: Vasconcelos, A.; Universidade Do Minho, Departamento de Engenharia Têxtil, Campus de Azurém, 4800-058 Guimarães, Portugal; email: andreiav@det.uminho.ptChemicals/CAS: Bowman Birk inhibitor, 37330-34-0; Fibroins, 9007-76-5; Keratins, 68238-35-7; Pancreatic Elastase, 3.4.21.36; Peptide Fragments; Trypsin Inhibitor, Bowman-Birk Soybean; Trypsin Inhibitors; fibroin, silkwormReferences: Boateng, J.S., Matthews, K.H., Stevens, H.N.E., Eccleston, G.M., Wound healing dressings and drug delivery systems: A review (2008) J. Pharm. Sci., 97, pp. 2892-2923;Rothe, M., Falanga, V., Growth factors: Their biology and promise in dermatologic diseases and tissue repair (1989) AMA Arch. Dermatol., 125, pp. 1390-1398; Shakespeare, P., Burn wound healing and skin substitutes (2001) Burns, 27, pp. 517-522; Martin, C.R., Wound infection: A failure of wound healing caused by an imbalance of bacteria (1997) Surg. Clin. North Am., 77, pp. 637-650; Stadelmann, W.K., Digenis, A.G., Tobin, G.R., Physiology and healing dynamics of chronic cutaneous wounds (1998) Am. J. Surg., 176, pp. 26S-38S; Eaglstein Wh, F.V., Chronic wounds (1997) Surg. Clin. North Am., 77, pp. 689-700; Gray, D.W.R., The wound exudate continuum: An aid to wound assessment (2004) Wounds U.K.: Appl. Wound Manageme. Suppl., pp. 19-21; Chen, W.Y.J., Rogers, A.A., Lydon, M.J., Characterization of biologic properties of wound fluid collected during early stages of wound healing (1992) J. Invest. Dermatol., 99, pp. 559-564; Brooke, B., Edward, J.C., Caroline, A.O., Leukocyte proteinases in wound healing: Roles in physiologic and pathologic processes (1999) Wound Repair Regener., 7, pp. 410-422; Dorne, R.Y., Benedict, C.N., The proteolytic environment of chronic wounds (1999) Wound Repair Regener., 7, pp. 433-441; Naomi, J.T., Michael, C.S., Shawn, M., Neil, B., Jane, G., Frank, B., Gillian, M., Gregory, S., Analysis of the acute and chronic wound environments: The role of proteases and their inhibitors (1999) Wound Repair Regener., 7, pp. 442-452; Enoch, S., Leaper, D.J., Basic science of wound healing (2008) Surgery (Oxford), 26, pp. 31-37; Chufa, H., Margaret, A.H., George, W.C., Frank, A., Effects of chronic wound fluid on the bioactivity of platelet-derived growth factor in serum-free medium and its direct effect on fibroblast growth (1999) Wound Repair Regener., 7, pp. 97-105; Chen, P., Rose, J., Love, R., Wei, C.H., Wang, B.C., Reactive sites of an anticarcinogenic Bowman-Birk proteinase inhibitor are similar to other trypsin inhibitors (1992) J. Biol. Chem., 267, pp. 1990-1994; Werner, M.H., Wemmer, D.E., Three-dimensional structure of soybean trypsin/chymotrypsin Bowman-Birk inhibitor in solution (1992) Biochemistry, 31, pp. 999-1010; Guangda, L.I.N., Wolfram, B., Robert, H., Chengwu, C.H.I., Richard, A.E., The 0.25-nm X-ray structure of the Bowman-Birk-type inhibitor from mung bean in ternary complex with porcine trypsin (1993) Eur. J. Biochem., 212, pp. 549-555; Voss, R.-H., Ulrich, E., Lars-Oliver, E., Gabriele, W., Young-Mi, K., Peter, F., Crystal structure of the bifunctional soybean Bowman-Birk inhibitor at 0.28-nm resolution (1996) Eur. J. Biochem., 242, pp. 122-131; Wolfram, B., Robert, H., Natural protein proteinase inhibitors and their interaction with proteinases (1992) Eur. J. Biochem., 204, pp. 433-451; Laskowski, M., Qasim, M.A., What can the structures of enzyme-inhibitor complexes tell us about the structures of enzyme substrate complexes (2000) Biochim. Biophys. Acta, Protein Struct. Mol. Enzymol., 1477, pp. 324-337; McBride, J.D., Leatherbarrow, R.J., Synthetic peptide mimics of the Bowman-Birk inhibitor protein (2001) Curr. Med. Chem., 8, pp. 909-917; Jeffrey, D.M., Emma, M.W., Arnd, B.E.B., Agnès, M.J., Robin, J.L., Peptide mimics of the Bowman-Birk inhibitor reactive site loop (2002) Pept. Sci., 66, pp. 79-92; Vasconcelos, A., Freddi, G., Cavaco-Paulo, A., Biodegradable materials based on silk fibroin and keratin (2008) Biomacromolecules, 9, pp. 1299-1305; Ritger, P.L., Peppas, N.A., A simple equation for description of solute release II. Fickian and anomalous release from swellable devices (1987) J. Controlled Release, 5, pp. 37-42; Tanaka, H., Shimazu, T., Sugimoto, H., Yoshioka, T., Sugimoto, T., A sensitive and specific assay for granulocyte elastase in inflammatory tissue fluid using l-pyroglutamyl-l-prolyl-l-valine-p-nitroanilide (1990) Clin. Chim. Acta, 187, pp. 173-180; Yamauchi, K., Maniwa, M., Mori, T., Cultivation of fibroblast cells on keratin-coated substrata (1998) J. Biomater. Sci., Polym. Ed., 9, pp. 259-270; Li, M., Ogiso, M., Minoura, N., Enzymatic degradation behavior of porous silk fibroin sheets (2003) Biomaterials, 24, pp. 357-365; Minoura, N., Aiba, S., Higuchi, M., Gotoh, Y., Tsukada, M., Imai, Y., (1995) Biochem. Biophys. Res. Commun., 208, p. 511; Yamauchi, K., Hojo, H., Yamamoto, Y., Tanabe, T., Enhanced cell adhesion on RGDS-carrying keratin film (2003) Mater. Sci. Eng., C, 23, pp. 467-472; Roh, D.-H., Kang, S.-Y., Kim, J.-Y., Kwon, Y.-B., Young Kweon, H., Lee, K.-G., Park, Y.-H., Lee, J.-H., Wound healing effect of silk fibroin/alginate-blended sponge in full thickness skin defect of rat (2006) J. Mater. Sci.: Mater. Med., 17, pp. 547-552; Lu, S., Wang, X., Lu, Q., Hu, X., Uppal, N., Omenetto, F.G., Kaplan, D.L., Stabilization of Enzymes in Silk Films (2009) Biomacromolecules, 10, pp. 1032-1042; Hofmann, S., Wong Po Foo, C.T., Rossetti, F., Textor, M., Vunjak-Novakovic, G., Kaplan, D.L., Merkle, H.P., Meinel, L., Silk fibroin as an organic polymer for controlled drug delivery (2006) J. Controlled Release, 111, pp. 219-227; Numata, K., Cebe, P., Kaplan, D.L., Mechanism of enzymatic degradation of beta-sheet crystals (2010) Biomaterials, 31, pp. 2926-2933; Shudong, W., Youzhu, Z., Guibo, Y., Hongwei, W., Zhihui, D., Electrospun polylactide/silk fibroin-gelatin composite tubular scaffolds for small-diameter tissue engineering blood vessels (2009) J. Appl. Polym. Sci., 113, pp. 2675-2682; Motta, A., Migliaresi, C., Faccioni, F., Torricelli, P., Fini, M., Giardino, R., Fibroin hydrogels for biomedical applications: Preparation, characterization and in vitro cell culture studies (2004) J. Biomater. Sci., Polym. Ed., 15, p. 851; Bondar, B., Fuchs, S., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Functionality of endothelial cells on silk fibroin nets: Comparative study of micro-and nanometric fibre size (2008) Biomaterials, 29, pp. 561-572; Fuchs, S., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Outgrowth endothelial cells isolated and expanded from human peripheral blood progenitor cells as a potential source of autologous cells for endothelialization of silk fibroin biomaterials (2006) Biomaterials, 27, pp. 5399-5408; Unger, R.E., Wolf, M., Peters, K., Motta, A., Migliaresi, C., James Kirkpatrick, C., Growth of human cells on a non-woven silk fibroin net: A potential for use in tissue engineering (2004) Biomaterials, 25, pp. 1069-1075; Huang, Y., Yu, H., Xiao, C., PH-sensitive cationic guar gum/poly(acrylic acid) polyelectrolyte hydrogels: Swelling and in vitro drug release (2007) Carbohydr. Polym., 69, pp. 774-783; Edwards, J.V., Alvin, F.B., Sarah, B., Abul, J.U., Kelman, C.I., Robert, F.D., Steven, J.M., Inhibition of elastase by a synthetic cotton-bound serine protease inhibitor: In vitro kinetics and inhibitor release (1999) Wound Repair Regener., 7, pp. 106-118; Schneider, A., Wang, X.Y., Kaplan, D.L., Garlick, J.A., Egles, C., Biofunctionalized electrospun silk mats as a topical bioactive dressing for accelerated wound healing (2009) Acta Biomater., 5, pp. 2570-2578; Gariani, T., McBride, J.D., Leatherbarrow, R.J., The role of the P2′ position of Bowman-Birk proteinase inhibitor in the inhibition of trypsin: Studies on P2′ variation in cyclic peptides encompassing the reactive site loop (1999) Biochim. Biophys. Acta, Protein Struct. Mol. Enzymol., 1431, pp. 232-237; Zablotna, E., Kazmierczak, K., Jaskiewicz, A., Stawikowski, M., Kupryszewski, G., Rolka, K., Chemical synthesis and kinetic study of the smallest naturally occurring trypsin inhibitor SFTI-1 isolated from sunflower seeds and its analogues (2002) Biochem. Biophys. Res. Commun., 292, pp. 855-859
Keywords: animal cell; Animals; article; Atomic force microscopy; Biodegradation; Biological degradation; Biological functions; biomaterial; Bombyx; Bowman Birk inhibitor; Bowman-Birk inhibitors; cell proliferation; Chronic wounds; controlled study; Cytotoxicity test; Degradation; Elastase; elastase inhibitor; enzyme activity; Enzyme inhibition; Fibroins; Film composition; In-vitro; keratin; Keratins; mass spectrometry; materials testing; Mice; Microscopy, Atomic Force; NIH 3T3 Cells; nonhuman; pancreatic elastase; Peptide Fragments; Peptides; priority journal; protein binding; Protein matrices; Release rate; Silk; Silk fibroin; Spectrometry, Mass, Electrospray Ionization; Sus; Swine; Synthetic peptide; Trypsin Inhibitor, Bowman-Birk Soybean; Trypsin Inhibitors; wound fluid; Wound healing

Receptor-mediated gene delivery using PAMAM dendrimers conjugated with peptides recognized by mesenchymal stem cells - Santos, J.L.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Balian, G.; Tomás, H. (Molecular PharmaceuticsMol. Pharm., 2010)
As mesenchymal stem cells (MSCs) can differentiate into multiple cell types, the delivery of exogenous genes to this type of cell can be an important tool in tissue regeneration and engineering. However transfection of MSCs using nonviral gene delivery vectors is difficult, the development of more efficient and safe DNA vehicles being necessary. Moreover, specific transfection of MSCs may be required to avoid unwanted side effects in other tissues. In this study, a novel family of gene delivery vectors based on poly(amidoamine) (PAMAM) dendrimers functionalized with peptides displaying high affinity toward MSCs was prepared. The vectors were characterized with respect to their ability to neutralize, bind and compact plasmid DNA (pDNA). The complexes formed between the vectors and pDNA were analyzed concerning their size, -potential, capacity of being internalized by cells and transfection efficiency. These new vectors exhibited low cytotoxicity, receptor-mediated gene delivery into MSCs and transfection efficiencies superior to those presented by native dendrimers and by partially degraded dendrimers. © 2010 American Chemical Society.
Cited By (since 1996): 17Export Date: 21 November 2012Source: Scopusdoi: 10.1021/mp9002877PubMed ID: 20230026Language of Original Document: EnglishCorrespondence Address: Balian, G.; Orthopaedic Research Laboratories, Department of Orthopaedics and Biochemistry and Molecular Genetics, University of Virginia Health System, Charlottesville, VA 22908, United States; email: lenat@uma.ptChemicals/CAS: Dendrimers; Green Fluorescent Proteins, 147336-22-9; PAMAM Starburst; Peptides; enhanced green fluorescent proteinReferences: Väänänen, H.K., Mesenchymal stem cells (2005) Ann. Med., 37, pp. 469-479;Caplan, A.I., Adult mesenchymal stem cells for tissue engineering versus regenerative medicine (2007) J. Cell Physiol., 213, pp. 341-347; Kay, M.A., Glorioso, J.C., Naldini, L., Viral vectors for gene therapy: The art of turning infectious agents into vehicles of therapeutics (2001) Nat. Med., 7, pp. 33-40; Mastrobattista, E., Bravo, S.A., Van Der Aa, M., Crommelin, D.J.A., Nonviral gene delivery systems: From simple transfection agents to artificial viruses (2005) Drug Discovery Today: Technol., 2, pp. 103-109; Merdan, T., Kopecek, J., Kissel, T., Prospects for cationic polymers in gene and oligonucleotide therapy against cancer (2002) Adv. Drug Delivery Rev., 54, pp. 715-758; Hamm, A., Krott, N., Breibach, I., Blindt, R., Bosserhoff, A.K., Efficient transfection method for primary cells (2002) Tissue Eng., 8, pp. 235-245; McMahon, J.M., Conroy, S., Lyons, M., Greiser, U., O'Shea, C., Strappe, P., Howard, L., O'Brien, T., Gene transfer into rat mesenchymal stem cells: A comparative study of viral and nonviral vectors (2006) Stem Cells Dev., 15, pp. 87-96; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications-reflections on the field (2005) Adv. Drug Delivery Rev., 57, pp. 2106-2129; Duf-s, C., Uchegbu, I.F., Schatzlein, A.G., Dendrimers in gene delivery (2005) Adv. Drug Delivery Rev., 57, pp. 2177-2202; Guillot, M., Eisler, S., Diederich, F., Dendritic vectors for gene transfection (2007) New J. Chem., 31, pp. 1111-1127; Smith, D.K., Dendrimers and the double helix-from DNA binding towards gene therapy (2008) Curr. Top. Med. Chem., 8, pp. 1187-1203; Kukowska-Latallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker Jr., J.R., Efficient transfer of genetic material into mammalian cells using Starburst polyamidoamine dendrimers (1996) Proc. Natl. Acad. Sci. U.S.A., 93, pp. 4897-4902; Santos, J.L., Oramas, E., Pêgo, A.P., Granja, P.L., Tomás, H., Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene delivery vectors (2009) J. Controlled Release, 134, pp. 141-148; Balian, G., (2008), Bone Targeting Peptides. In United States Patent 7,323,542, issued January 29Snyder, S.L., Sobocinski, P.Z., An improved 2,4,6-trinitrobenzenesulfonic acid method for the determination of amines (1975) Anal. Biochem., 64, pp. 284-288; Haensler, J., Szoka Jr., F.C., Polyamidoamine cascade polymers mediate efficient transfection of cells in culture (1993) Bioconjugate Chem., 4, pp. 372-379; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Hiraoka, Y., Inoue, S., Shimokawa, H., Tabata, Y., Enhanced ectopic bone formation using a combination of plasmid DNA impregnation into 3-D scaffold and bioreactor perfusion culture (2006) Biomaterials, 27, pp. 1387-1398; Perrot, S., Dutertre-Catella, H., Martin, C., Rat, P., Warnet, J.M., Resazurin metabolism assay is a new sensitive alternative test in isolated pig cornea (2003) Toxicol. Sci., 72, pp. 122-129; Wood, K.C., Little, S.R., Langer, R., Hammond, P.T., A family of hierarchically self-assembling linear-dendritic hybrid polymers for highly efficient targeted gene delivery (2005) Angew. Chem., Int. Ed., 44, pp. 6704-6708; Dan Luo, K.H., Belcheva, N., Han, E., Mark Saltzman, W., Poly(ethylene glycol)-conjugated PAMAM dendrimer for biocompatible, high-efficiency dna delivery (2002) Macromolecules, 35, pp. 3456-3462; Schaffer, D.V., Lauffenburger, D.A., Optimization of cell surface binding enhances efficiency and specificity of molecular conjugate gene delivery (1998) J. Biol. Chem., 273, pp. 28004-28009; Santos, J.L., Oliveira, H., Pandita, D., Pêgo, A.P., Granja, P.L., Tomás, H., Functionalization of poly(amidoamine) dendrimers with hydrophobic chains for improved gene delivery in mesenchymal stem cells (2010) J. Controlled Release, , doi: 10.1016/j.jconrel.2010.01.034
Keywords: animal cell; animal experiment; animal tissue; Animals; article; asparaginylserylmethionylisoleucylalanylhistidylasparaginyllysylthreonylarginylmethionylhistidylglycylglycylglycylserylcysteine; Cell recognition; cell survival; Cells, Cultured; controlled study; Cytotoxicity; dendrimer; Dendrimers; DNA; DNA binding; Electrophoresis, Agar Gel; flow cytometry; Gene delivery; gene targeting; Gene Transfer Techniques; gene vector; genetic transfection; Genetic Vectors; Green Fluorescent Proteins; male; Mesenchymal stem cell; Mesenchymal Stem Cells; Models, Theoretical; multigene family; nonhuman; PAMAM dendrimers; peptide; Peptides; plasmid DNA; polyamidoamine; priority journal; rat; Rats; Rats, Wistar; serylglycylhistidylglutaminylleucylleucylleucylasparaginyllysylmethionylprolylasparaginylglycylglycylglycylserylcysteine; unclassified drug; Zeta potential

Synthesis and characterization of HAp nanorods from a cationic surfactant template method - Coelho, J.M.; Moreira, J.A.; Almeida, A.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2010)
Hydroxyapatite (HAp) [Ca 10(PO 4) 6(OH) 2] nanorods were synthesized using a surfactant templating method, with cetyltrimethylammonium bromide (CTAB) micelles acting as template for HAp growth. The effects of the sintering temperature on the morphological and crystallographic characteristics and on chemical composition of the "as-prepared" structures are discussed. The experimental results show that low heat-treatment temperatures are preferred in order to obtain high quality nanorods, with diameters ranging between 20 and 50 nm. High heat-treatment temperatures enhance the thermal decomposition of HAp into other calcium phosphate compounds, and the sintering of particles into micrometer ball-like structures. The stability of aqueous suspensions of HAp nanorods is also discussed. © 2010 Springer Science+Business Media, LLC.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-010-4122-5PubMed ID: 20623177Language of Original Document: EnglishCorrespondence Address: Moreira, J. A.; IFIMUP, IN-Institute of Nanoscience and Nanotechnology, Universidade Do Porto, Rua do Campo Alegre 687, Porto 4169-007, Portugal; email: jamoreir@fc.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; Cations; Cetrimonium Compounds; Surface-Active Agents; cetrimonium, 6899-10-1References: Rao, C.N.R., Cheetham, A.K., Materials science at the nanoscale (2006) Nanomaterials Handbook, pp. 1-2. , Y. Gogotsi (eds). CRC Press, Taylor & Francis Group New York;Guo, Y., Shi, D., Lian, J., Zdw, W., Cho, H., Liu, G., Quantum dot conjugated hydroxylapatite nanoparticles for in vivo imaging (2008) Nanotechnology, 19, 6p. , 175102; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., Production of porous hydroxyapatite with potential for controlled drug delivery (2004) Mater Sci Forum, 455-456, pp. 358-360. , 10.4028/www.scientific.net/MSF.455-456.358; Vallet-Regi, M., Ceramics for medical applications (2001) Journal of the Chemical Society, Dalton Transactions, (2), pp. 97-108. , DOI 10.1039/b007852m; Dorozhkin, S.V., Epple, M., Biological and medical significance of calcium phosphates (2002) Angewandte Chemie - International Edition, 41 (17), pp. 3130-3146. , DOI 10.1002/1521-3773(20020902)41:17<3130::AID-ANIE3130>3.0.CO;2-1; Ferraz, M.P., Monteiro, F.J., Manuel, C.M., Hydroxyapatite nanoparticles: A review of preparation methodologies (2004) J Appl Biomater Biomech, 2, pp. 74-80. , 1:CAS:528:DC%2BD2cXnvFWiurk%3D; Cengiz, B., Gokce, Y., Yildiz, N., Aktas, Z., Calimi, A., Synthesis and characterization of hydroxyapatite nanoparticles (2008) Colloids Surf A Physichochem Eng Aspects, 322, pp. 29-33. , 1:CAS:528:DC%2BD1cXmt1OqtbY%3D 10.1016/j.colsurfa.2008.02.011; Ying, J.Y., Mehnert, P.C., Wong, M.S., Synthesis and application of supramolecular-templated mesoporous materials (1999) Angew Chem Int Ed, 38, pp. 56-77. , 1:CAS:528:DyaK1MXpsValtg%3D%3D 10.1002/(SICI)1521-3773(19990115)38:1/ 2<56::AID-ANIE56>3.0.CO;2-E; Cates, M.E., Fielding, S.M., Rheology of giant micelles (2006) Advances in Physics, 55 (7-8), pp. 799-879. , DOI 10.1080/00018730601082029, PII T6J4U87W3G5RTN2J; Nagarajan, R., Molecular thermodynamics of giant micelles (2007) Giant Micelles-properties and Applications, pp. 2-5. , R. Zana E.W. Kaler (eds). CRC Pess, Taylor & Francis Group New York; Li, Y., Tjandra, W., Tam, K.C., Synthesis of nanoporous hydroxyapatite using cationic surfactants as templates (2008) Mater Res Bull, 43, pp. 2318-2326. , 1:CAS:528:DC%2BD1cXnsVSrtr4%3D 10.1016/j.materresbull.2007.08.008; Yao, J., Tjandra, W., Chen, Y.Z., Tam, K.C., Mab, J., Soh, B., Hydroxyapatite nanostructure material derived using cationic surfactant as a template (2003) J Mater Chem, 13, pp. 3053-3057. , 1:CAS:528:DC%2BD3sXptlemsro%3D 10.1039/b308801d; Berret, J.F., Rheology of wormlike micelles: Equilibrium properties and shear banding transition (2006) Molecular Gels. Materials with Self-assembled Fibrillar Networks, pp. 667-720. , R.G. Weiss P. Terech (eds). Springer Dordrecht; Kresge, C.T., Leonowicz, M.E., Roth, W.J., Vartuli, J.C., Beck, J.S., Ordered mesoporous molecular sieves synthesized by a liquid-crystal template mechanism (1992) Nature, 359 (6397), pp. 710-712. , DOI 10.1038/359710a0; Beck, J.S., Vartuli, J.C., Roth, W.J., Leonowicz, M.E., Kresge, C.T., Schmitt, K.D., A new family of mesoporous molecular sieves prepared with liquid crystal templates (1992) J Am Chem Soc, 114, pp. 10834-10843. , 1:CAS:528:DyaK38Xms1entr8%3D 10.1021/ja00053a020; Li, Y.Y., Li, J., Nakajima, B., Nanostructured porous biomaterials for controlled drug release systems (2008) Biomaterials-fabrication and Processing, pp. 196-206. , K.C. Paul L. Xuanyong (eds). CRC Press, Taylor & Francis Group New York. 10.1201/9780849379741; Herzberg, G., (1945) The Infrared and Raman Spectra of Poliatomic Molecules, , D van Nostrand Company, Inc. New York; Awonusi, A., Morris, M.D., Tecklenburg, M.M.J., Carbonate assignment and calibration in the Raman spectrum of apatite (2007) Calcified Tissue International, 81 (1), pp. 46-52. , DOI 10.1007/s00223-007-9034-0; Fowler, B.O., Infrared studies of apatites. I. Vibrational assignments for calcium, strontium, and barium hydroxyapatites utilizing isotopic substitution (1974) Inorg Chem, 13, pp. 194-207. , 1:CAS:528:DyaE2cXlsVWktw%3D%3D 10.1021/ic50131a039; Aza, P.N., Santos, C., Pazo, A., Aza, S., Cuscó, R., Artus, L., Vibrational properties of calcium phospate coumpounds. 1. Raman spectrum of β-tricalcium phosphate (1997) Chem Mater, 9, pp. 912-915. , 10.1021/cm960425d
Keywords: Ammonium compounds; Aqueous suspensions; article; Bromine compounds; Calcium; calcium phosphate; cationic surfactant; Cationic surfactants; Cations; Cetrimonium Compounds; Cetyltrimethylammonium bromide; chemical composition; Chemical compositions; Chemical structure; Crystallographic characteristics; Dyes; Heat treatment temperature; High quality; hydroxyapatite; Microscopy, Electron, Scanning; Microscopy, Electron, Transmission; nanorod; Nanorods; Nanotubes; Phosphate compounds; priority journal; Pyrolysis; Scanning electron microscopy; Sintering; Sintering temperatures; Surface-Active Agents; Surfactant template method; Surfactant templating; Suspensions (fluids); synthesis; Synthesis and characterizations; Thermal decompositions; X-Ray Diffraction

Targeted gene delivery into peripheral sensorial neurons mediated by self-assembled vectors composed of poly(ethylene imine) and tetanus toxin fragment c - Oliveira, H.; Fernandez, R.; Pires, L.R.; Martins, M.C.L.; Simões, S.; Barbosa, M.A.; Pêgo, A.P. (Journal of Controlled ReleaseJ. Control. Release, 2010)
A simple, safe and efficient system that can specifically transfect peripheral sensorial neurons can bring new answers to address peripheral neuropathies. A multi-component non-viral gene delivery vector targeted to peripheral nervous system cells was developed, using poly(ethylene imine) (PEI) as starting material. A binary DNA/polymer complex based on thiolated PEI (PEISH) was optimized, considering complex size and zeta potential and the ability to transfect a sensorial neuron cell line (ND7/23). The 50. kDa non-toxic fragment from tetanus toxin (HC), which has been previously shown to interact specifically with peripheral neurons and to undergo retrograde transport, was grafted to the complex core via a bifunctional PEG (HC-PEG) reactive for the thiol moieties present in the complex surface. Several formulations of HC-PEG ternary complexes were tested for targeting, by assessing the extent of cellular internalization and levels of transfection, in both the ND7/23 and NIH 3 T3 (fibroblast) cell lines. Targeted gene transfer to the neuronal cell line was observed for the complex formulations containing 5 and 7.5. Μg of HC-PEG. Finally, our results demonstrate that the developed ternary vectors are able to transfect primary cultures of dorsal root ganglion dissociated neurons in a targeted manner and elicit the expression of a relevant neurotrophic factor. © 2010 Elsevier B.V.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JCREEdoi: 10.1016/j.jconrel.2010.01.018PubMed ID: 20093157Language of Original Document: EnglishCorrespondence Address: Pêgo, A.P.; INEB-Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: apego@ineb.up.ptChemicals/CAS: DNA, 9007-49-2; macrogol, 25322-68-3; polyethyleneimine, 74913-72-7; DNA, 9007-49-2; Imines; Peptide Fragments; Polyethylenes; Tetanus Toxin; poly(ethylene imine); tetanus toxin fragment CReferences: Rodriguez, F.J., Valero-Cabre, A., Navarro, X., Regeneration and functional recovery following peripheral nerve injury (2004) Drug Discov. Today, 1 (2), pp. 177-185;Sahenk, Z., Neurotrophins and peripheral neuropathies (2006) Brain Pathol., 16 (4), pp. 311-319; Apfel, S.C., Kessler, J.A., Neurotrophic factors in the therapy of peripheral neuropathy (1995) Baillieres Clin. Neurol., 4 (3), pp. 593-606; Apfel, S.C., Is the therapeutic application of neurotrophic factors dead? (2002) Ann. Neurol., 51 (1), pp. 8-11; Glorioso, J.C., Mata, M., Fink, D.J., Therapeutic gene transfer to the nervous system using viral vectors (2003) J. Neurovirol., 9 (2), pp. 165-172; Boussif, O., Lezoualc'h, F., Zanta, M.A., Mergny, M.D., Scherman, D., Demeneix, B., A versatile vector for gene and oligonucleotide transfer into cells in culture and in vivo: polyethylenimine (1995) Proc. Natl. Acad. Sci. U.S.A., 92 (16), pp. 7297-7301; Coll, J.L., Chollet, P., Brambilla, E., Desplanques, D., Behr, J.P., Favrot, M., In vivo delivery to tumors of DNA complexed with linear polyethylenimine (1999) Hum. Gene Ther., 10 (10), pp. 1659-1666; Schaffer, D.V., Lauffenburger, D.A., Optimization of cell surface binding enhances efficiency and specificity of molecular conjugate gene delivery (1998) J. Biol. Chem., 273 (43), pp. 28004-28009; Zanta, M.A., Boussif, O., Adib, A., Behr, J.P., In vitro gene delivery to hepatocytes with galactosylated polyethylenimine (1997) Bioconjug. Chem., 8 (6), pp. 839-844; Diebold, S.S., Lehrmann, H., Kursa, M., Wagner, E., Cotten, M., Zenke, M., Efficient gene delivery into human dendritic cells by adenovirus polyethylenimine and mannose polyethylenimine transfection (1999) Hum. Gene Ther., 10 (5), pp. 775-786; Blessing, T., Kursa, M., Holzhauser, R., Kircheis, R., Wagner, E., Different strategies for formation of PEGylated EGF-conjugated PEI/DNA complexes for targeted gene delivery (2001) Bioconjug. Chem., 12 (4), pp. 529-537; Erbacher, P., Remy, J.S., Behr, J.P., Gene transfer with synthetic virus-like particles via the integrin-mediated endocytosis pathway (1999) Gene Ther., 6 (1), pp. 138-145; Kircheis, R., Kichler, A., Wallner, G., Kursa, M., Ogris, M., Felzmann, T., Coupling of cell-binding ligands to polyethylenimine for targeted gene delivery (1997) Gene Ther., 4 (5), pp. 409-418; Park, I.K., Lasiene, J., Chou, S.H., Horner, P.J., Pun, S.H., Neuron-specific delivery of nucleic acids mediated by Tet1-modified poly(ethylenimine) (2007) J. Gene Med., 9 (8), pp. 691-702; Kwon, E.J., Bergen, J.M., Park, I.K., Pun, S.H., Peptide-modified vectors for nucleic acid delivery to neurons (2008) J. Control. Release, 132 (3), pp. 230-235; Price, D.L., Griffin, J., Young, A., Peck, K., Stocks, A., Tetanus toxin: direct evidence for retrograde intraaxonal transport (1975) Science, 188 (4191), pp. 945-947; Figueiredo, D.M., Hallewell, R.A., Chen, L.L., Fairweather, N.F., Dougan, G., Savitt, J.M., Delivery of recombinant tetanus-superoxide dismutase proteins to central nervous system neurons by retrograde axonal transport (1997) Exp. Neurol., 145 (2 PART 1), pp. 546-554; Fishman, P.S., Savitt, J.M., Farrand, D.A., Enhanced CNS uptake of systemically administered proteins through conjugation with tetanus C-fragment (1990) J. Neurol. Sci., 98 (2-3), pp. 311-325; Coen, L., Osta, R., Maury, M., Brulet, P., Construction of hybrid proteins that migrate retrogradely and transynaptically into the central nervous system (1997) Proc. Natl. Acad. Sci. U.S.A., 94 (17), pp. 9400-9405; Knight, A., Carvajal, J., Schneider, H., Coutelle, C., Chamberlain, S., Fairweather, N., Non-viral neuronal gene delivery mediated by the HC fragment of tetanus toxin (1999) Eur. J. Biochem., 259 (3), pp. 762-769; Carlisle, R.C., Etrych, T., Briggs, S.S., Preece, J.A., Ulbrich, K., Seymour, L.W., Polymer-coated polyethylenimine/DNA complexes designed for triggered activation by intracellular reduction (2004) J. Gene Med., 6 (3), pp. 337-344; Goula, D., Remy, J.S., Erbacher, P., Wasowicz, M., Levi, G., Abdallah, B., Size, diffusibility and transfection performance of linear PEI/DNA complexes in the mouse central nervous system (1998) Gene Ther., 5 (5), pp. 712-717; Sinha, K., Box, M., Lalli, G., Schiavo, G., Schneider, H., Groves, M., Analysis of mutants of tetanus toxin Hc fragment: ganglioside binding, cell binding and retrograde axonal transport properties (2000) Mol. Microbiol., 37 (5), pp. 1041-1051; Ellman, G.L., Tissue sulfhydryl groups (1959) Arch. Biochem. Biophys., 82 (1), pp. 70-77; (1993) Iodine-125, a Guide to Radioionation Techniques, , Amersham Life Science; O'brien, J., Wilson, I., Orton, T., Pognan, F., Investigation of the Alamar Blue (resazurin) fluorescent dye for the assessment of mammalian cell cytotoxicity (2000) Eur. J. Biochem., 267 (17), pp. 5421-5426; Pollard, H., Remy, J.S., Loussouarn, G., Demolombe, S., Behr, J.P., Escande, D., Polyethylenimine but not cationic lipids promotes transgene delivery to the nucleus in mammalian cells (1998) J. Biol. Chem., 273 (13), pp. 7507-7511; Neu, M., Fischer, D., Kissel, T., Recent advances in rational gene transfer vector design based on poly(ethylene imine) and its derivatives (2005) J. Gene Med., 7 (8), pp. 992-1009; Moffatt, S., Papasakelariou, C., Wiehle, S., Cristiano, R., Successful in vivo tumor targeting of prostate-specific membrane antigen with a highly efficient J591/PEI/DNA molecular conjugate (2006) Gene Ther., 13 (9), pp. 761-772; Kircheis, R., Ostermann, E., Wolschek, M.F., Lichtenberger, C., Magin-Lachmann, C., Wightman, L., Tumor-targeted gene delivery of tumor necrosis factor-alpha induces tumor necrosis and tumor regression without systemic toxicity (2002) Cancer Gene Ther., 9 (8), pp. 673-680; Bellomo, G., Vairetti, M., Stivala, L., Mirabelli, F., Richelmi, P., Orrenius, S., Demonstration of nuclear compartmentalization of glutathione in hepatocytes (1992) Proc. Natl. Acad. Sci. U.S.A., 89 (10), pp. 4412-4416; Liu, H.S., Jan, M.S., Chou, C.K., Chen, P.H., Ke, N.J., Is green fluorescent protein toxic to the living cells? (1999) Biochem. Biophys. Res. Commun., 260 (3), pp. 712-717; Baens, M., Noels, H., Broeckx, V., Hagens, S., Fevery, S., Billiau, A.D., The dark side of EGFP: defective polyubiquitination (2006) PLoS One, 1, pp. e54; Taghizadeh, R.R., Sherley, J.L., CFP and YFP, but not GFP, provide stable fluorescent marking of rat hepatic adult stem cells (2008) J. Biomed. Biotechnol., 2008. , 453590; Liu, J.K., Tenga, Q.S., Garrity-Moses, M., Federici, T., Tanase, D., Imperiale, M.J., A novel peptide defined through phage display for therapeutic protein and vector neuronal targeting (2005) Neurobiol. Dis., 19 (3), pp. 407-418; Fishman, P.S., Carrigan, D.R., Retrograde transneuronal transfer of the C-fragment of tetanus toxin (1987) Brain Res., 406 (1-2), pp. 275-279
Keywords: Aberrations; animal cell; Animals; article; Bifunctional; Cell culture; Cell Line, Tumor; Cell lines; cell strain 3T3; Cells, Cultured; Cellular internalization; Chemical modification; Complex cores; Complex formulations; Complex surface; controlled study; DNA; DNA protein complex; Dorsal root ganglia; Efficient systems; embryo; Ethylene; Female; Gene transfer; genetic transfection; Imines; internalization; macrogol; Mice; mouse; Multicomponents; nanoparticle; nanoparticles; neuroblastoma cell; Neuronal cell; Neurons; neurotrophic factor; Neurotrophic factors; NIH 3T3 Cells; Nitrogen compounds; Non-viral; Non-viral gene delivery; nonhuman; Nonviral; nonviral gene delivery system; Nucleic acids; Particle Size; Peptide Fragments; Peripheral nervous system; Peripheral neuropathy; Plasmids; Polyethylene Glycols; Polyethylene oxides; Polyethyleneimine; Polyethylenes; Primary culture; priority journal; process optimization; protein expression; rat; Rats; Rats, Wistar; Regenerative Medicine; Self-assembled; sensory nerve cell; spinal ganglion; Starting materials; Targeted; Targeted gene delivery; Ternary complex; Ternary vectors; Tetanus toxin; tetanus toxin fragment c; Transfection; unclassified drug; Zeta potential

Automated Arabidopsis plant root cell segmentation based on SVM classification and region merging - Marcuzzo, M.; Quelhas, P.; Campilho, A.; Maria Mendonça, A.; Campilho, A. (Computers in Biology and MedicineComput. Biol. Med., 2009)
To obtain development information of individual plant cells, it is necessary to perform in vivo imaging of the specimen under study, through time-lapse confocal microscopy. Automation of cell detection/marking process is important to provide research tools in order to ease the search for special events, such as cell division. In this paper we discuss an automatic cell detection approach for Arabidopsis thaliana based on segmentation, which selects the best cell candidates from a starting watershed-based image segmentation and improves the result by merging adjacent regions. The selection of individual cells is obtained using a support vector machine (SVM) classifier, based on a cell descriptor constructed from the shape and edge strength of the cells' contour. In addition we proposed a novel cell merging criterion based on edge strength along the line that connects adjacent cells' centroids, which is a valuable tool in the reduction of cell over-segmentation. The result is largely pruned of badly segmented and over-segmented cells, thus facilitating the study of cells. When comparing the results after merging with the basic watershed segmentation, we obtain 1.5% better coverage (increase in F-measure) and up to 27% better precision in correct cell segmentation. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: CBMDAdoi: 10.1016/j.compbiomed.2009.06.008PubMed ID: 19604506Language of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, Portugal; email: marcuzzo@fe.up.ptReferences: Baeza-Yates, R., Ribeiro-Neto, B., (1999) Modern Information Retrieval, , ACM Press;Bleau, A., Leon, L., Watershed-based segmentation and region merging (2000) Computer Vision and Image Understanding, 77 (3), pp. 317-370; M. Brown, W. Grundy, L.D.N. Cristianini, C. Sugnet, T. Furey, M. Ares, D. Haussler, Knowledge-based analysis of microarray gene expression data using support vector machines, in: Proceedings of the National Academy of Sciences, 97 (1), 1999, pp. 262-267Burges, C., A tutorial on support vector machines for pattern recognition (1998) Data Mining and Knowledge Discovery, 2 (2), pp. 121-167; Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the Arabidopsis thaliana root meristem (2006) Plant Journal, 48, pp. 619-627; Chang, C., Lin, C., (2001) Libsvm: A library for support vector machines, , http://www.csie.ntu.edu.tw/∼cjlin/libsvm/faq.html#f203, Software available online at; Chen, X., Zhou, X., Wong, S.T.C., Automated segmentation classification, and tracking of cancer cell nuclei in time-lapse microscopy (2006) IEEE Transactions on Biomedical Engineering, 53 (4), pp. 762-766; Dabov, K., Foi, A., Katkovnik, V., Egiazarian, K., Image denoising by sparse 3d transform-domain collaborative filtering (2007) IEEE Transactions on Image Processing, 16 (8), pp. 2080-2095; (2004) Kernel Methods in Computational Biology, Computational Molecular Biology, , B. Schölkopf, K. Tsuda, J.-P. Vert, Eds, MIT Press, Cambridge, MA; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic tracking of Arabidopsis thaliana root meristem in confocal microscopy (2004) Springer Lecture Notes in Computer Science, 3212, pp. 166-174. , Proceedings of the International Conference on Image Analysis and Recognition, Springer, Berlin; Grandjean, O., Vernoux, T., Laufs, P., Belcram, K., Mizukami, Y., Traas, J., In vivo analysis of cell division, cell growth, and differentiation at the shoot apical meristem in Arabidopsis (2004) Plant Cell, 16 (1), pp. 74-87; Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in Arabidopsis thaliana provided by a simple mathematical model (2006) Journal of Plant Research, 119, pp. 85-93; Kittler, J., Hatef, M., Duin, R.P.W., Matas, J., On combining classifiers (1998) IEEE Transactions on Pattern Analysis and Machine Intelligence, 20 (3), pp. 226-239; P. Kovesi, Symmetry and asymmetry from local phase, in: Proceedings of the 10th Australian Joint Conference on Artificial Intelligence, December 1997, pp. 185-190P. Kovesi, Edges are not just steps, in: Proceedings of the Fifth Asian Conference on Computer Vision, January 2002, pp. 822-827Liao, L., Noble, W.S., Combining pairwise sequence similarity and support vector machines for remote protein homology detection (2002) Proceedings of the Sixth Annual International Conference on Computational Molecular Biology, pp. 225-232. , ACM Press; Luc, V., Soille, P., Watersheds in digital spaces: an efficient algorithm based on immersion simulations (1991) IEEE Transactions on Pattern Analysis and Machine Intelligence, 13 (6), pp. 583-598; Mao, K., Zhao, P., Tan, P.-H., Supervised learning-based cell image segmentation for p53 immunohistochemistry (2006) IEEE Transactions on Biomedical Engineering, 53 (6), pp. 1153-1163; M. Marcuzzo, P. Quelhas, A. Campilho, A.M. Mendonça, A.C. Campilho, Automatic cell segmentation from confocal microscopy images of the Arabidopsis root, in: IEEE International Symposium on Biomedical Imaging, May 2008, pp. 712-715Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A.C., A hybrid approach for cell image segmentation (2008) Springer Lecture Notes in Computer Science, 5112, pp. 739-749. , Proceedings of the International Conference on Image Analysis and Recognition, Springer, Berlin; Meyer, F., Beucher, S., Morphological segmentation (1990) Journal of Visual Communication and Image Representation, 1 (1), pp. 21-46; Perona, P., Malik, J., Scale-space and edge detection using anisotropic diffusion (1990) IEEE Transactions on Pattern Analysis and Machine Intelligence, 7 (12), pp. 629-639; T. Roberts, S. Mckenna, N. Wuyts, T. Valentine, A. Bengough, Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo, in: IEEE Workshop on Motion & Video Computing, February 2007, pp. 13-21Sathiya Keerthi, S., Lin, C.-J., Asymptotic behaviors of support vector machines with Gaussian kernel (2003) Neural Computation, 15 (7), pp. 1667-1689; Vapnik, V., (1998) Statistical Learning Theory, , Wiley, New York
Keywords: accuracy; Arabidopsis; Arabidopsis plant; Arabidopsis thaliana; article; artificial intelligence; automation; Bioinformatics; Biological cells; Biomedical image processing; Cell detection; Cell divisions; Cell membranes; Cell merging; cell proliferation; Cell segmentation; Cell Shape; Cell Wall; Computer simulation; confocal microscopy; controlled study; Descriptor; F-measure; Image analysis; image processing; Image Processing, Computer-Assisted; Image segmentation; Imaging systems; In-Vivo imaging; Individual cells; Landforms; Merging; Models, Biological; nonhuman; Over segmentation; Plant cells; plant root; Plant roots; Plants (botany); priority journal; Region-merging; Research tools; root morphology; Segmented cell; signal noise ratio; support vector machine; Support vector machines; SVM classification; Watershed segmentation; Watersheds

Cancer cell angiogenic capability is regulated by 3D culture and integrin engagement - Fischbach, C.; Hyun, J.K.; Hsiong, S.X.; Evangelista, M.B.; Yuen, W.; Mooney, D.J. (Proceedings of the National Academy of Sciences of the United States of AmericaProc. Natl. Acad. Sci. U. S. A., 2009)
Three-dimensional culture alters cancer cell signaling; however, the underlying mechanisms and importance of these changes on tumor vascularization remain unclear. A hydrogel system was used to examine the role of the transition from 2D to 3D culture, with and without integrin engagement, on cancer cell angiogenic capability. Three-dimensional culture recreated tumor microenvironmental cues and led to enhanced interleukin 8 (IL-8) secretion that depended on integrin engagement with adhesion peptides coupled to the polymer. In contrast, vascular endothelial growth factor (VEGF) secretion was unaffected by 3D culture with or without substrate adhesion. IL-8 diffused greater distances and was present in higher concentrations in the systemic circulation, relative to VEGF. Implantation of a polymeric IL-8 delivery system into GFP bone marrow-transplanted mice revealed that localized IL-8 up-regulation was critical to both the local and systemic control of tumor vascularization in vivo. In summary, 3D integrin engagement within tumor microenvironments regulates cancer cell angiogenic signaling, and controlled local and systemic blockade of both IL-8 and VEGF signaling may improve antiangiogenic therapies. © 2009 by The National Academy of Sciences of the USA.
Cited By (since 1996): 48Export Date: 21 November 2012Source: ScopusCODEN: PNASAdoi: 10.1073/pnas.0808932106PubMed ID: 19126683Language of Original Document: EnglishCorrespondence Address: Mooney, D. J.; School of Engineering and Applied Sciences, Harvard University, 40 Oxford Street, Cambridge, MA 02138, United States; email: mooneyd@seas.harvard.eduChemicals/CAS: arginylglycylaspartic acid, 99896-85-2; interleukin 8, 114308-91-7; vasculotropin, 127464-60-2; Hydrogels; Integrins; Interleukin-8; Vascular Endothelial Growth Factor AReferences: Debnath, J., Brugge, J.S., Modelling glandular epithelial cancers in 3-dimensional cultures (2005) Nat Rev Cancer, 5, pp. 675-688;Wang, F., Reciprocal interactions between β1-integrin and epidermal growth factor receptor in 3-dimensional basement membrane breast cultures: A different perspective in epithelial biology (1998) Proc Natl Acad Sci USA, 95, pp. 14821-14826; Fischbach, C., Engineering tumors with 3D scaffolds (2007) Nat Methods, 4, pp. 855-860; Paszek, M.J., Tensional homeostasis and the malignant phenotype (2005) Cancer Cell, 8, pp. 241-254; Hanahan, D., Weinberg, R.A., The hallmarks of cancer (2000) Cell, 100, pp. 57-70; De, S., VEGF-integrin interplay controls tumor growth and vascularization (2005) Proc Natl Acad Sci USA, 102, pp. 7589-7594; Lowrie, A.G., Salter, D.M., Ross, J.A., Latent effects of fibronectin, α5β1 integrin, αvβ5 integrin, and the cytoskeleton regulate pancreatic carcinoma cell IL-8 secretion (2004) Br J Cancer, 91, pp. 1327-1334; Cukierman, E., Pankov, R., Stevens, D.R., Yamada, K.M., Taking cell matrix adhesions to the third dimension (2001) Science, 294, pp. 1708-1712; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20, pp. 45-53; Lingen, M.W., Angiogenesis in the development of head and neck cancer and its inhibition by chemopreventive agents (1999) Crit Rev Oral Biol Med, 10, pp. 153-164; Fischbach, C., Mooney, D., Polymeric systems for bioinspired delivery of angiogenic molecules (2006) Adv Polym Sci, 203, pp. 191-221; Ruoslahti, E., Pierschbacher, M.D., New perspectives in cell adhesion: RGD and integrins (1987) Science, 238, pp. 491-497; Kong, H.J., Boontheekul, T., Mooney, D.J., Quantifying the relation between adhesion ligand-receptor bond formation and cell phenotype (2006) Proc Natl Acad Sci USA, 103, pp. 18534-18539; Harris, A.L., Hypoxia: A key regulatory factor in tumour growth (2002) Nat Rev Cancer, 2, pp. 38-47; Xu, L., Hypoxia-induced elevation in interleukin-8 expression by human ovarian carcinoma cells (1999) Cancer Res, 59, pp. 5822-5829; Weaver, V.M., Reversion of the malignant phenotype of human breast cells in three-dimensional cultureandin vivo by integrin-blocking antibodies (1997) J Cell Biol, 137, pp. 231-245; Chung, J., Hypoxia-induced vascular endothelial growth factor transcription and protection from apoptosis are dependent on α6β1 integrin in breast carcinoma cells (2004) Cancer Res, 64, pp. 4711-4716; Ghosh, S., Three-dimensional culture of melanoma cells profoundly affects gene expression profile: A high density oligonucleotide array study (2005) J Cell Physiol, 204, pp. 522-531; De Larco, J.E., A potential role for interleukin-8 in the metastatic phenotype of breast carcinoma cells (2001) Am J Pathol, 158, pp. 639-646; Nemeth, Z.H., Disruption of the actin cytoskeleton results in nuclear factor-κB activation and inflammatory mediator production in cultured human intestinal epithelial cells (2004) J Cell Physiol, 200, pp. 71-81; Xie, K., Interleukin-8 and human cancer biology (2001) Cytokine Growth Factor Rev, 12, pp. 375-391; Casanovas, O., Hicklin, D.J., Bergers, G., Hanahan, D., Drug resistance by evasion of antiangiogenic targeting of VEGF signaling in late-stage pancreatic islet tumors (2005) Cancer Cell, 8, pp. 299-309; Mizukami, Y., Induction of interleukin-8 preserves the angiogenic response in HIF-1α-deficient colon cancer cells (2005) Nat Med, 11, pp. 992-997; Esposito, I., Inflammatory cells contribute to the generation of an angiogenic phenotype in pancreatic ductal adenocarcinoma (2004) J Clin Pathol, 57, pp. 630-636; Ferrara, N., Henzel, W.J., Pituitary follicular cells secrete a novel heparin-binding growth factor specific for vascular endothelial cells (1989) Biochem Biophys Res Commun, 161, pp. 851-858; Gaertner, H.F., Offord, R.E., Site-specific attachment of functionalized poly(ethylene glycol) to the amino terminus of proteins (1996) Bioconjug Chem, 7, pp. 38-44; Goerges, A.L., Nugent, M.A., Regulation of vascular endothelial growth factor binding and activity by extracellular pH (2003) J Biol Chem, 278, pp. 19518-19525; Kuschert, G.S., Identification of a glycosaminoglycan binding surface on human interleukin-8 (1998) Biochemistry, 37, pp. 11193-11201; Kerbel, R., Folkman, J., Clinical translation of angiogenesis inhibitors (2002) Nat Rev Cancer, 2, pp. 727-739; Fischbach, C., Mooney, D.J., Polymers for pro- and antiangiogenic therapy (2007) Biomaterials, 28, pp. 2069-2076; Alsberg, E., Engineering growing tissues (2002) Proc Natl Acad Sci USA, 99, pp. 12025-12030; Simmons, C.A., Dual growth factor delivery and controlled scaffold degradation enhance in vivo bone formation by transplanted bone marrow stromal cells (2004) Bone, 35, pp. 562-569; Comisar, W.A., Kazmers, N.H., Mooney, D.J., Linderman, J.J., Engineering RGD nanopatterned hydrogels to control preosteoblast behavior: A combined computational and experimental approach (2007) Biomaterials, 28, pp. 4409-4417; Alsberg, E., Regulating bone formation via controlled scaffold degradation (2003) J Dent Res, 82, pp. 903-908; Richardson, T.P., Peters, M.C., Ennett, A.B., Mooney, D.J., Polymeric system for dual growth factor delivery (2001) Nat Biotechnol, 19, pp. 1029-1034
Keywords: animal experiment; animal model; Animals; arginylglycylaspartic acid; article; bone marrow transplantation; cancer cell; cancer cell culture; Cell Culture Techniques; concentration (parameters); controlled study; cytokine release; Diffusion; Drug delivery; ECM; Humans; hydrogel; Hydrogels; IL-8; implantation; in vivo study; integrin; Integrins; interleukin 8; Interleukin-8; Mice; microenvironment; Models, Biological; mouse; Mus; Neoplasms; Neovascularization, Pathologic; nonhuman; polymer; priority journal; signal transduction; systemic circulation; Tumor vascularization; upregulation; Vascular Endothelial Growth Factor A; vasculotropin

Cancer invasion and metastasis: Interacting ecosystems - Mareel, M.; Oliveira, M.J.; Madani, I. (Virchows ArchivVirchows Arch., 2009)
Malignant tumors invade and metastasize. They consist of cancer cells, evolving through genetic and epigenetic modulation, mixed with tumor-associated host cells, emerging from resident or bone marrow-derived precursors. These cells establish ecosystems to activate cellular programs for local invasion and distant metastasis. Characteristic of such malignancy-related activities is communication inside ecosystems between cells, ligands, receptor protein complexes, and signaling pathways as well as between ecosystems comprising the primary tumor, lymph node and distant metastasis, bone marrow and blood and lymph circulation. Complexity is another characteristic, resulting from: heterogeneity of the cell populations; the numbers of promoter and suppressor genes, their levels of regulation, and the pleiotropic activities of their products; biological redundancy of the molecular mechanisms underpinning invasion-related activities. Clinical attention is paid to putative new targets, namely host cells, individual molecules and their signaling pathways, as well as the effects of current treatment on invasion and metastasis. © 2009 Springer-Verlag.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: VARCEdoi: 10.1007/s00428-009-0784-0PubMed ID: 19471961Language of Original Document: EnglishCorrespondence Address: Madani, I.; Department of Radiotherapy, Ghent University Hospital, De Pintelaan 185, 9000 Ghent, Belgium; email: indira.madani@ugent.beReferences: Tarin, D., New insights into the pathogenesis of breast cancer metastasis (2006) Breast Disease, 26 (1), pp. 13-25;Stafford, L.J., Vaidya, K.S., Welch, D.R., Metastasis suppressors genes in cancer (2008) Int J Biochem Cell Biol, 40, pp. 874-891; Oliveira, M.J., (2004) The Effect of Bacteria on Colon Cancer Cell Invasion: Molecular Mechanisms Associated, , Faculty of Medicine and Health Sciences. Ghent University. PhD thesis; Madani, I., De Neve, W., Mareel, M., Does ionizing radiation stimulate cancer invasion and metastasis? (2008) Bull Cancer, 95, pp. 292-300; De Wever, O., Mareel, M., Role of tissue stroma in cancer cell invasion (2003) Journal of Pathology, 200 (4), pp. 429-447. , DOI 10.1002/path.1398; Bracke, M.E., Vanhoecke, B.W.A., Derycke, L., Bolca, S., Possemiers, S., Heyerick, A., Stevens, C.V., Parmar, V.S., Plant polyphenolics as anti-invasive cancer agents (2008) Anti-Cancer Agents in Medicinal Chemistry, 8 (2), pp. 171-185. , http://www.ingentaconnect.com/content/ben/acamc/2008/00000008/00000002/ art00004, DOI 10.2174/187152008783497037; Ottewell, P.D., Coleman, R.E., Holen, I., From genetic abnormality to metastases: Murine models of breast cancer and their use in the development of anticancer therapies (2006) Breast Cancer Res Treat, 96, pp. 101-113; Langley, R.R., Fidler, I.J., Tumor cell-organ microenvironment interactions in the pathogenesis of cancer metastasis (2007) Endocrine Reviews, 28 (3), pp. 297-321. , http://edrv.endojournals.org/cgi/reprint/28/3/297.pdf, DOI 10.1210/er.2006-0027; Kuperwasser, C., Chavarria, T., Wu, M., Magrane, G., Gray, J.W., Carey, L., Richardson, A., Weinberg, R.A., Reconstruction of functionally normal and malignant human breast tissues in mice (2004) Proceedings of the National Academy of Sciences of the United States of America, 101 (14), pp. 4966-4971. , DOI 10.1073/pnas.0401064101; Hoffman, R.M., Real-time subcellular imaging in live animals: New visible targets for cancer drug discovery (2006) IDrugs, 9 (9), pp. 632-635; Fomchenko, E.I., Holland, E.C., Mouse models of brain tumors and their applications in preclinical trials (2006) Clinical Cancer Research, 12 (18), pp. 5288-5297. , DOI 10.1158/1078-0432.CCR-06-0438; Gingrich, J.R., Barrios, R.J., Morton, R.A., Boyce, B.F., DeMayo, F.J., Finegold, M.J., Angelopoulou, R., Greenberg, N.M., Metastatic prostate cancer in a transgenic mouse (1996) Cancer Research, 56 (18), pp. 4096-4102; Peri, A.-K., Wilgenbus, P., Dahl, U., Semb, H., Christofori, G., A causal role for E-cadherin in the transition from adenoma to carcinoma (1998) Nature, 392 (6672), pp. 190-193. , DOI 10.1038/32433; Ambartsumian, N., Grigorian, M., Lukanidin, E., Genetically modified mouse models to study the role of metastasis-promoting S100A4(mts1) protein in metastatic mammary cancer (2005) Journal of Dairy Research, 72 (SPEC. ISS.), pp. 27-33. , DOI 10.1017/S0022029905001093; Scherer, R.L., McIntyre, J.O., Matrisian, L.M., Imaging matrix metalloproteinases in cancer (2008) Cancer Metastasis Rev, 27, pp. 679-690; Espina, V., Heiby, M., Pierobon, M., Liotta, L.A., Laser capture microdissection technology (2007) Expert Review of Molecular Diagnostics, 7 (5), pp. 647-657. , http://www.future-drugs.com/doi/pdf/10.1586/14737159.7.5.647, DOI 10.1586/14737159.7.5.647; Eccles, S.A., Welch, D.R., Metastasis: recent discoveries and novel treatment strategies (2007) Lancet, 369 (9574), pp. 1742-1757. , DOI 10.1016/S0140-6736(07)60781-8, PII S0140673607607818; Brenton, J.D., Carey, L.A., Ahmed, A., Caldas, C., Molecular classification and molecular forecasting of breast cancer: Ready for clinical application? (2005) Journal of Clinical Oncology, 23 (29), pp. 7350-7360. , DOI 10.1200/JCO.2005.03.3845; Montel, V., Huang, T.-Y., Mose, E., Pestonjamasp, K., Tarin, D., Expression profiling of primary tumors and matched lymphatic and lung metastases in a xenogeneic breast cancer model (2005) American Journal of Pathology, 166 (5), pp. 1565-1579; Karpf, A.R., Jones, D.A., Reactivating the expression of methylation silenced genes in human cancer (2002) Oncogene, 21 (35 REV. ISS. 3), pp. 5496-5503. , DOI 10.1038/sj.onc.1205602; Feng, Y., Sun, B., Li, X., Zhang, L., Niu, Y., Xiao, C., Ning, L., Hao, X., Differentially expressed genes between primary cancer and paired lymph node metastases predict clinical outcome of node-positive breast cancer patients (2007) Breast Cancer Research and Treatment, 103 (3), pp. 319-329. , DOI 10.1007/s10549-006-9385-7; Van't Veer, L.J., Dai, H., Van De Vijver, M.J., He, Y.D., Hart, A.A.M., Mao, M., Peterse, H.L., Friend, S.H., Gene expression profiling predicts clinical outcome of breast cancer (2002) Nature, 415 (6871), pp. 530-536. , DOI 10.1038/415530a; Wang, W., Klijn, J.G., Zhang, Y., Gene-expression profiles to predict distant metastasis of lymph-node-negative primary breast cancer (2005) Lancet, 415, pp. 530-536; Eckhardt, B.L., Parker, B.S., Van Laar, R.K., Restall, C.M., Natoli, A.L., Tavaria, M.D., Stanley, K.L., Anderson, R.L., Genomic analysis of a spontaneous model of breast cancer metastasis to bone reveals a role for the extracellular matrix (2005) Molecular Cancer Research, 3 (1), pp. 1-13; Adib, T.R., Henderson, S., Perrett, C., Hewitt, D., Bourmpoulia, D., Ledermann, J., Boshoff, C., Predicting biomarkers for ovarian cancer using gene-expression microarrays (2004) British Journal of Cancer, 90 (3), pp. 686-692. , DOI 10.1038/sj.bjc.6601603; Suzuki, M., Tarin, D., Gene expression profiling of human lymph node metastases and matched primary breast carcinomas: Clinical implications (2007) Molecular Oncology, 1 (2), pp. 172-180. , DOI 10.1016/j.molonc.2007.03.005, PII S1574789107000154; Chang, H.Y., Nuyten, D.S.A., Sneddon, J.B., Hastie, T., Tibshirani, R., Sorlie, T., Dai, H., Van De Vijver, M.J., Robustness, scalability, and integration of a wound-response gene expression signature in predicting breast cancer survival (2005) Proceedings of the National Academy of Sciences of the United States of America, 102 (10), pp. 3738-3743. , DOI 10.1073/pnas.0409462102; Finak, G., Bertos, N., Pepin, F., Sadekova, S., Souleimanova, M., Zhao, H., Chen, H., Park, M., Stromal gene expression predicts clinical outcome in breast cancer (2008) Nature Medicine, 14 (5), pp. 518-527. , DOI 10.1038/nm1764, PII NM1764; Clark, I.M., Swingler, T.E., Sampieri, C.L., The regulation of matrix metalloproteinases and their inhibitors (2008) Int J Biochem Cell Biol, 40, pp. 1362-1378; Li, Y., Liang, J., Kang, S., Dong, Z., Wang, N., Xing, H., Zhou, R., Zhao, X., E-cadherin gene polymorphisms and haplotype associated with the occurrence of epithelial ovarian cancer in Chinese (2008) Gynecologic Oncology, 108 (2), pp. 409-414. , DOI 10.1016/j.ygyno.2007.10.024, PII S0090825807008517; Brendle, A., Lei, H., Brandt, A., Polymorphisms in predicted microRNA-binding sites in integrin genes and breast cancer: ITGB4 as prognostic marker (2008) Carcinogenesis, 29, pp. 1394-1399; Hunter, K.W., Crawford, N.P., Germ line polymorphism in metastatic progression (2006) Cancer Research, 66 (3), pp. 1251-1254. , DOI 10.1158/0008-5472.CAN-05-3705; Crawford, N.P., Ziogas, A., Peel, D.J., Germline polymorphisms in SIPA1 are associated with metastasis and other indicators of poor prognosis in breast cancer (2006) Breast Cancer Res, 8, p. 16; Van Roy, F., Berx, G., The cell-cell adhesion molecule E-cadherin (2008) Cell Mol Life Sci, 65, pp. 3756-3788; Bartel, D.P., Chen, C.-Z., Micromanagers of gene expression: The potentially widespread influence of metazoan microRNAs (2004) Nature Reviews Genetics, 5 (5), pp. 396-400; Ma, L., Weinberg, R.A., Micromanagers of malignancy: Role of microRNAs in regulating metastasis (2008) Trends Genet, 24, pp. 448-456; Graff, J.R., Zimmer, S.G., Translational control and metastatic progression: Enhanced activity of the mRNA cap-binding protein eIF-4E selectively enhances translation of metastasis-related mRNAs (2003) Clinical and Experimental Metastasis, 20 (3), pp. 265-273. , DOI 10.1023/A:1022943419011; Hao, X., Sun, B., Hu, L., Lahdesmaki, H., Dunmire, V., Feng, Y., Zhang, S.-W., Zhang, W., Differential Gene and Protein Expression in Primary Breast Malignancies and Their Lymph Node Metastases as Revealed by Combined cDNA Microarray and Tissue Microarray Analysis (2004) Cancer, 100 (6), pp. 1110-1122. , DOI 10.1002/cncr.20095; Hakomori, S.-I., Tumor malignancy defined by aberrant glycosylation and sphingo(glyco)lipid metabolism (1996) Cancer Research, 56 (23), pp. 5309-5318; Yoshimura, M., Ihara, Y., Matsuzawa, Y., Taniguchi, N., Aberrant glycosylation of E-cadherin enhances cell-cell binding to suppress metastasis (1996) Journal of Biological Chemistry, 271 (23), pp. 13811-13815. , DOI 10.1074/jbc.271.23.13811; McLachlan, R.W., Yap, A.S., Not so simple: The complexity of phosphotyrosine signaling at cadherin adhesive contacts (2007) Journal of Molecular Medicine, 85 (6), pp. 545-554. , DOI 10.1007/s00109-007-0198-x, Special Topic: Tumor Cell Invasion and Metastasis; Wipff, P.J., Hinz, B., Integrins and the activation of latent transforming growth factor beta1-an intimate relationship (2008) Eur J Cell Biol, 87, pp. 601-615; Paredes, J., Correia, A.L., Ribeiro, A.S., P-cadherin expression in breast cancer: A review (2007) Breast Cancer Res, 9, p. 214; Van Marck, V., Stove, C., Van Den Bossche, K., Stove, V., Paredes, J., Vander Haeghen, Y., Bracke, M., P-cadherin promotes cell-cell adhesion and counteracts invasion in human melanoma (2005) Cancer Research, 65 (19), pp. 8774-8783. , DOI 10.1158/0008-5472.CAN-04-4414; Wheelock, M.J., Shintani, Y., Maeda, M., Fukumoto, Y., Johnson, K.R., Cadherin switching (2008) Journal of Cell Science, 121 (6), pp. 727-735. , DOI 10.1242/jcs.000455; De Wever, O., Westbroek, W., Verloes, A., Bloemen, N., Bracke, M., Gespach, C., Bruyneel, E., Mareel, M., Critical role of N-cadherin in myofibroblast invasion and migration in vitro stimulated by colon-cancer-cell-derived TGF-β or wounding (2004) Journal of Cell Science, 117 (20), pp. 4691-4703. , DOI 10.1242/jcs.01322; Alexander, N.R., Tran, N.L., Rekapally, H., N-cadherin gene expression in prostate carcinoma is modulated by integrin-dependent nuclear translocation of Twist1 (2006) Cancer Res, 66, pp. 3365-3369; Stove, C., Bracke, M., Roles for neuregulins in human cancer (2005) Clinical and Experimental Metastasis, 21 (8), pp. 665-684. , DOI 10.1007/s10585-004-6917-6; Kerbel, R.S., Tumor angiogenesis (2008) New England Journal of Medicine, 358 (19), pp. 2039-2049. , http://content.nejm.org/cgi/reprint/358/19/2039.pdf, DOI 10.1056/NEJMra0706596; Chabottaux, V., Noel, A., Breast cancer progression: Insights into multifaceted matrix metalloproteinases (2007) Clinical and Experimental Metastasis, 24 (8), pp. 647-656. , DOI 10.1007/s10585-007-9113-7; Noel, A., Jost, M., Maquoi, E., Matrix metalloproteinases at cancer tumor-host interface (2008) Seminars in Cell and Developmental Biology, 19 (1), pp. 52-60. , DOI 10.1016/j.semcdb.2007.05.011, PII S1084952107000821, Matrix Metalloproteinases; Jones, R.B., Gordus, A., Krall, J.A., MacBeath, G., A quantitative protein interaction network for the ErbB receptors using protein microarrays (2006) Nature, 439 (7073), pp. 168-174. , DOI 10.1038/nature04177, PII NATURE04177; Pawson, T., Nash, P., Assembly of cell regulatory systems through protein interaction domains (2003) Science, 300 (5618), pp. 445-452. , DOI 10.1126/science.1083653; Kopfstein, L., Christofori, G., Metastasis: Cell-autonomous mechanisms versus contributions by the tumor microenvironment (2006) Cell Mol Life Sci, 63, pp. 449-468; Paget, S., The distribution of secondary growths in cancer of the breast (1889) Lancet, 1, pp. 571-573; Mareel, M.M., Behrens, J., Birchmeier, W., Down-regulation of E-cadherin expression in Madin Darby canine kidney (MDCK) cells inside tumors of nude mice (1991) Int J Cancer, 47, pp. 922-928; Creighton, C.J., Bromberg-White, J.L., Misek, D.E., Monsma, D.J., Brichory, F., Kuick, R., Giordano, T.J., Hanash, S.M., Analysis of tumor-host interactions by gene expression profiling of lung adenocarcinoma xenografts identifies genes involved in tumor formation (2005) Molecular Cancer Research, 3 (3), pp. 119-129. , DOI 10.1158/1541-7786.MCR-04-0189; Dimanche-Boitrel, M.T., Vakaet Jr., L., Pujuguet, P., Chauffert, B., Martin, M.S., Hammann, A., Van Roy, F., Martin, F., In vivo and in vitro invasiveness of a rat colon-cancer cell line maintaining E-cadherin expression: An enhancing role of tumor-associated myofibroblasts (1994) International Journal of Cancer, 56 (4), pp. 512-521; Lin, E.Y., Pollard, J.W., Tumor-associated macrophages press the angiogenic switch in breast cancer (2007) Cancer Research, 67 (11), pp. 5064-5066. , http://cancerres.aacrjournals.org/cgi/reprint/67/11/5064, DOI 10.1158/0008-5472.CAN-07-0912; Korc, M., Pancreatic cancer-associated stroma production (2007) Am J sur, 194 (4 SUPPL.), pp. 84-S86; He, Y., Rajantie, I., Pajusola, K., Jeltsch, M., Holopainen, T., Yla-Herttuala, S., Harding, T., Alitalo, K., Vascular endothelial cell growth factor receptor 3-mediated activation of lymphatic endothelium is crucial for tumor cell entry and spread via lymphatic vessels (2005) Cancer Research, 65 (11), pp. 4739-4746. , DOI 10.1158/0008-5472.CAN-04-4576; Mahabeleshwar, G.H., Byzova, T.V., Angiogenesis in Melanoma (2007) Seminars in Oncology, 34 (6), pp. 555-565. , DOI 10.1053/j.seminoncol.2007.09.009, PII S0093775407001832, Malignant Melanoma; Benoy, I.H., Salgado, R., Elst, H., Relative microvessel area of the primary tumour, and not lymph node status, predicts the presence of bone marrow micrometastases detected by reverse transcriptase polymerase chain reaction in patients with clinically non-metastatic breast cancer (2005) Breast Cancer Res, 7, pp. 210-R219; Hicklin, D.J., Ellis, L.M., Role of the vascular endothelial growth factor pathway in tumor growth and angiogenesis (2005) Journal of Clinical Oncology, 23 (5), pp. 1011-1027. , DOI 10.1200/JCO.2005.06.081; Schoppmann, S.F., Bayer, G., Aumayr, K., Taucher, S., Geleff, S., Rudas, M., Kubista, E., Horvat, R., Prognostic value of lymphangiogenesis and lymphovascular invasion in invasive breast cancer (2004) Annals of Surgery, 240 (2), pp. 306-312. , DOI 10.1097/01.sla.0000133355.48672.22; Tobler, N.E., Detmar, M., Tumor and lymph node lymphangiogenesis - Impact on cancer metastasis (2006) Journal of Leukocyte Biology, 80 (4), pp. 691-696. , http://www.jleukbio.org/cgi/reprint/80/4/691, DOI 10.1189/jlb.1105653; Nathanson, S.D., Leong, S., Preclinical models of regional lymph node tumor metastasis (2007) Cancer Metastasis and the Lymphvascular System: Basis for Rational Therapy, pp. 129-156. , Springer New York; Wissmann, C., Detmar, M., Pathways targeting tumor lymphangiogenesis (2006) Clinical Cancer Research, 12 (23), pp. 6865-6868. , DOI 10.1158/1078-0432.CCR-06-1800; Rafii, D.C., Psaila, B., Butler, J., Jin, D.K., Lyden, D., Regulation of vasculogenesis by platelet-mediated recruitment of bone marrow-derived cells (2008) Arteriosclerosis, Thrombosis, and Vascular Biology, 28 (2), pp. 217-222. , DOI 10.1161/ATVBAHA.107.151159, PII 0004360520080200000004; Mantovani, A., Sica, A., Sozzani, S., Allavena, P., Vecchi, A., Locati, M., The chemokine system in diverse forms of macrophage activation and polarization (2004) Trends in Immunology, 25 (12), pp. 677-686. , DOI 10.1016/j.it.2004.09.015, PII S1471490604002959; Mantovani, A., Romero, P., Palucka, A.K., Tumour immunity: Effector response to tumour and role of the microenvironment (2008) Lancet, 371, pp. 771-783; Talmadge, J.E., Donkor, M., Scholar, E., Inflammatory cell infiltration of tumors: Jekyll or Hyde (2007) Cancer and Metastasis Reviews, 26 (3-4), pp. 373-400. , DOI 10.1007/s10555-007-9072-0, Forty Years of Metastasis Research: A Tribute to Dr. Isaiah J. Fidler; Lewis, C.E., Pollard, J.W., Distinct role of macrophages in different tumor microenvironments (2006) Cancer Research, 66 (2), pp. 605-612. , DOI 10.1158/0008-5472.CAN-05-4005; Condeelis, J., Pollard, J.W., Macrophages: Obligate partners for tumor cell migration, invasion, and metastasis (2006) Cell, 124 (2), pp. 263-266. , DOI 10.1016/j.cell.2006.01.007, PII S0092867406000559; Wyckoff, J.B., Wang, Y., Lin, E.Y., Li, J.-F., Goswami, S., Stanley, E.R., Segall, J.E., Condeelis, J., Direct visualization of macrophage-assisted tumor cell intravasation in mammary tumors (2007) Cancer Research, 67 (6), pp. 2649-2656. , DOI 10.1158/0008-5472.CAN-06-1823; Mahadevan, D., Von Hoff, D.D., Tumor-stroma interactions in pancreatic ductal adenocarcinoma (2007) Molecular Cancer Therapeutics, 6 (4), pp. 1186-1197. , DOI 10.1158/1535-7163.MCT-06-0686; De Wever, O., Demetter, P., Mareel, M., Stromal myofibroblasts are drivers of invasive cancer growth (2008) Int J Cancer, 123, pp. 2229-2238; Massaguè, J., TGFbeta in cancer (2008) Cell, 134, pp. 215-230; Hu, M., Yao, J., Carroll, D.K., Weremowicz, S., Chen, H., Carrasco, D., Richardson, A., Polyak, K., Regulation of In Situ to Invasive Breast Carcinoma Transition (2008) Cancer Cell, 13 (5), pp. 394-406. , DOI 10.1016/j.ccr.2008.03.007, PII S1535610808000913; Lerwill, M.F., Current practical applications of diagnostic immunohistochemistry in breast pathology (2004) American Journal of Surgical Pathology, 28 (8), pp. 1076-1091. , DOI 10.1097/01.pas.0000126780.10029.f0; Allinen, M., Beroukhim, R., Cai, L., Brennan, C., Lahti-Domenici, J., Huang, H., Porter, D., Polyak, K., Molecular characterization of the tumor microenvironment in breast cancer (2004) Cancer Cell, 6 (1), pp. 17-32. , DOI 10.1016/j.ccr.2004.06.010, PII S1535610804001783; Hu, M., Yao, J., Cai, L., Bachman, K.E., Van Den Brule, F., Velculescu, V., Polyak, K., Distinct epigenetic changes in the stromal cells of breast cancers (2005) Nature Genetics, 37 (8), pp. 899-905. , DOI 10.1038/ng1596; Barsky, S.H., Karlin, N.J., Myoepithelial cells: Autocrine and paracrine suppressors of breast cancer progression (2005) J Mammary Gland Biol Neoplasia, 10, pp. 249-260; Polyak, K., Hu, M., Do myoepithelial cells hold the key for breast tumor progression? (2005) J Mammary Gland Biol Neoplasia, 10, pp. 231-247; Mantyh, P.W., Clohisy, D.R., Koltzenburg, M., Hunt, S.P., Molecular mechanisms of cancer pain (2002) Nature Reviews Cancer, 2 (3), pp. 201-209; Ayala, G.E., Dai, H., Powell, M., Cancer-related axonogenesis and neurogenesis in prostate cancer (2008) Clin Cancer Res, 14, pp. 7593-7603; Wang, W., Zhao, H., Zhang, S., Al, E., Patterns of expression and function of the p75(NGFR) protein in pancreatic cancer cells and tumours (2008) Eur J Surg Oncol, , Nov 26 (in press); Marchesi, F., Piemonti, L., Fedele, G., The chemokine receptor CX3CR1 is involved in the neural tropism and malignant behavior of pancreatic ductal adenocarcinoma (2008) Cancer Res, 68, pp. 9060-9069; Zhang, S., Qi, L., Li, M., Chemokine CXCL12 and its receptor CXCR4 expression are associated with perineural invasion of prostate cancer (2008) J Exp Clin Cancer Res, 27, p. 62; Andarawewa, K.L., Motrescu, E.R., Chenard, M.-P., Gansmuller, A., Stoll, I., Tomasetto, C., Rio, M.-C., Stromelysin-3 is a potent negative regulator of adipogenesis participating to cancer cell-adipocyte interaction/crosstalk at the tumor invasive front (2005) Cancer Research, 65 (23), pp. 10862-10871. , DOI 10.1158/0008-5472.CAN-05-1231; Caers, J., Van Valckenborgh, E., Menu, E., Unraveling the biology of multiple myeloma disease: Cancer stem cells, acquired intracellular changes and interactions with the surrounding micro-environment (2008) Bull Cancer, 95, pp. 301-313; Vona-Davis, L., Rose, D.P., Adipokines as endocrine, paracrine, and autocrine factors in breast cancer risk and progression (2007) Endocrine-Related Cancer, 14 (2), pp. 189-206. , DOI 10.1677/ERC-06-0068; Kunduzova, O., Alet, N., Delesque-Touchard, N., Apelin/APJ signaling system: A potential link between adipose tissue and endothelial angiogenic processes (2008) FASEB J, 22, pp. 4146-4153; Cirillo, D., Rachiglio, A.M., La Montagna, R., Leptin signaling in breast cancer: An overview (2008) J Cell Biochem, 105, pp. 956-964; Jaffe, T., Schwartz, B., Leptin promotes motility and invasiveness in human colon cancer cells by activating multiple signal-transduction pathways (2008) Int J Cancer, 123, pp. 2543-2556; Horiguchi, A., Sumitomo, M., Asakuma, J., Asano, T., Zheng, R., Asano, T., Nanus, D.M., Hayakawa, M., Leptin Promotes Invasiveness of Murine Renal Cancer Cells Via Extracellular Signal-Regulated Kinases and Rho Dependent Pathway (2006) Journal of Urology, 176 (4), pp. 1636-1641. , DOI 10.1016/j.juro.2006.06.040, PII S0022534706014169; Bussard, K.M., Gay, C.V., Mastro, A.M., The bone microenvironment in metastasis; What is special about bone? (2008) Cancer Metastasis Rev, 27, pp. 41-55; Vakaet, L.A.M.-L., Boterberg, T., Pain control by ionizing radiation of bone metastasis (2004) International Journal of Developmental Biology, 48 (5-6), pp. 599-606. , DOI 10.1387/ijdb.041817lv, Invasion in Cancer and Embryonic Development; Oliveira, M.J., Van Damme, J., Lauwaet, T., De Corte, V., De Bruyne, G., Verschraegen, G., Vaneechoutte, M., Leroy, A., β-casein-derived peptides, produced by bacteria, stimulate cancer cell invasion and motility (2003) EMBO Journal, 22 (22), pp. 6161-6173. , DOI 10.1093/emboj/cdg586; Oliveira, M.J., Costa, A.C., Costa, A.M., Henriques, L., Suriano, G., Atherton, J.C., Machado, J.C., Figueiredo, C., Helicobacter pylori induces gastric epithelial cell invasion in a c-Met and type IV secretion system-dependent manner (2006) Journal of Biological Chemistry, 281 (46), pp. 34888-34896. , http://www.jbc.org/cgi/reprint/281/46/34888, DOI 10.1074/jbc.M607067200; Oliveira, M.J., Costa, A.M., Costa, A.C., Al, E., CagA associates with c-Met, E-cadherin, and p120-catenin in a multiproteic complex that suppresses Helicobacter pylori-induced cell invasive phenotype (2009) J Infect Dis, , in press; Miller, M.J., Wei, S.H., Parker, I., Cahalan, M.D., Two-photon imaging of lymphocyte motility and antigen response in intact lymph node (2002) Science, 296 (5574), pp. 1869-1873. , DOI 10.1126/science.1070051; Mullen, J.T., Wang, H., Yao, J.C., Carcinoid tumors of the duodenum (2005) Surgery, 138, pp. 971-977; Hoon, D.S.B., Kitago, M., Kim, J., Mori, T., Piris, A., Szyfelbein, K., Mihm Jr., M.C., Pantel, K., Molecular mechanisms of metastasis (2006) Cancer and Metastasis Reviews, 25 (2), pp. 203-220. , DOI 10.1007/s10555-006-8500-x; Muller, A., Homey, B., Soto, H., Ge, N., Catron, D., Buchanan, M.E., McClanahan, T., Zlotnik, A., Involvement of chemokine receptors in breast cancer metastasis (2001) Nature, 410 (6824), pp. 50-56. , DOI 10.1038/35065016; Hirakawa, S., Brown, L.F., Kodama, S., Paavonen, K., Alitalo, K., Detmar, M., VEGF-C-induced lymphangiogenesis in sentinel lymph nodes promotes tumor metastasis to distant sites (2007) Blood, 109 (3), pp. 1010-1017. , http://www.bloodjournal.org/cgi/reprint/109/3/1010, DOI 10.1182/blood-2006-05-021758; Van Den Eynden, G.G., Vandenberghe, M.K., Van Dam, P.-J.H., Colpaert, C.G., Van Dam, P., Dirix, L.Y., Vermeulen, P.B., Van Marck, E.A., Increased sentinel lymph node lymphangiogenesis is associated with nonsentinel axillary lymph node involvement in breast cancer patients with a positive sentinel node (2007) Clinical Cancer Research, 13 (18), pp. 5391-5397. , http://clincancerres.aacrjournals.org/cgi/reprint/13/18/5391, DOI 10.1158/1078-0432.CCR-07-1230; Dimeo, T.A., Kuperwasser, C., The evolving paradigm of tissue-specific metastasis (2006) Breast Cancer Res, 8, p. 301; Andre, F., Cabioglu, N., Assi, H., Sabourin, J.C., Delaloge, S., Sahin, A., Broglio, K., Cristofanilli, M., Expression of chemokine receptors predicts the site of metastatic relapse in patients with axillary node positive primary breast cancer (2006) Annals of Oncology, 17 (6), pp. 945-951. , DOI 10.1093/annonc/mdl053; Stessels, F., Van Den Eynden, G., Van Der Auwera, I., Salgado, R., Van Den Heuvel, E., Harris, A.L., Jackson, D.G., Vermeulen, P.B., Breast adenocarcinoma liver metastases, in contrast to colorectal cancer liver metastases, display a non-angiogenic growth pattern that preserves the stroma and lacks hypoxia (2004) British Journal of Cancer, 90 (7), pp. 1429-1436. , DOI 10.1038/sj.bjc.6601727; Mendes, O., Kim, H.-T., Lungu, G., Stoica, G., MMP2 role in breast cancer brain metastasis development and its regulation by TIMP2 and ERK1/2 (2007) Clinical and Experimental Metastasis, 24 (5), pp. 341-351. , DOI 10.1007/s10585-007-9071-0; Kaplan, R.N., Psaila, B., Lyden, D., Bone marrow cells in the 'pre-metastatic niche': Within bone and beyond (2006) Cancer and Metastasis Reviews, 25 (4), pp. 521-529. , DOI 10.1007/s10555-006-9036-9, Special issue on Bone Metastasis and Cancer; Hiratsuka, S., Watanabe, A., Aburatani, H., Maru, Y., Tumour-mediated upregulation of chemoattractants and recruitment of myeloid cells predetermines lung metastasis (2006) Nature Cell Biology, 8 (12), pp. 1369-1375. , DOI 10.1038/ncb1507, PII NCB1507; Kaplan, R.N., Psaila, B., Lyden, D., Niche-to-niche migration of bone-marrow-derived cells (2007) Trends in Molecular Medicine, 13 (2), pp. 72-81. , DOI 10.1016/j.molmed.2006.12.003, PII S1471491406002681; Pantel, K., Brakenhoff, R.H., Dissecting the metastatic cascade (2004) Nature Reviews Cancer, 4 (6), pp. 448-456; Vincent-Salomon, A., Bidard, F.C., Pierga, J.Y., Bone marrow micrometastasis in breast cancer: Review of detection methods, prognostic impact and biological issues (2008) Journal of Clinical Pathology, 61 (5), pp. 570-576. , DOI 10.1136/jcp.2007.046649; Bidard, F.C., Vincent-Salomon, A., Gomme, S., Disseminated tumor cells of breast cancer patients: A strong prognostic factor for distant and local relapse (2008) Clin Cancer Res, 14, pp. 3306-3311. , Institut Curie Breast Cancer Study Group et al; Ceelen, W.P., Bracke, M.E., Peritoneal minimal residual disease in colorectal cancer: Mechanisms, prevention, and treatment (2009) Lancet Oncol, 10, pp. 72-79; Bidard, F.C., Pierga, J.Y., Vincent-Salomon, A., A "class action" against the microenvironment: Do cancer cells cooperate in metastasis? (2008) Cancer Metastasis Rev, 27, pp. 5-10; Bertolini, F., Mancuso, P., Shaked, Y., Kerbel, R.S., Molecular and cellular biomarkers for angiogenesis in clinical oncology (2007) Drug Discovery Today, 12 (19-20), pp. 806-812. , DOI 10.1016/j.drudis.2007.08.011, PII S1359644607003534; Shields, J.D., Fleury, M.E., Yong, C., Tomei, A.A., Randolph, G.J., Swartz, M.A., Autologous Chemotaxis as a Mechanism of Tumor Cell Homing to Lymphatics via Interstitial Flow and Autocrine CCR7 Signaling (2007) Cancer Cell, 11 (6), pp. 526-538. , DOI 10.1016/j.ccr.2007.04.020, PII S1535610807001456; Nierodzik, M.L., Karpatkin, S., Thrombin induces tumor growth, metastasis, and angiogenesis: Evidence for a thrombin-regulated dormant tumor phenotype (2006) Cancer Cell, 10 (5), pp. 355-362. , DOI 10.1016/j.ccr.2006.10.002, PII S1535610806002868; Podsypanina, K., Du, Y.C., Jechlinger, M., Seeding and propagation of untransformed mouse mammary cells in the lung (2008) Science, 321, pp. 1841-1844; Aguirre-Ghiso, J.A., Models, mechanisms and clinical evidence for cancer dormancy (2007) Nature Reviews Cancer, 7 (11), pp. 834-846. , DOI 10.1038/nrc2256, PII NRC2256; Brackstone, M., Townson, J.L., Chambers, A.F., Tumour dormancy in breast cancer: An update (2007) Breast Cancer Res, 9, p. 208; O'Reilly, M.S., Holmgren, L., Shing, Y., Chen, C., Rosenthal, R.A., Moses, M., Lane, W.S., Folkman, J., Angiostatin: A novel angiogenesis inhibitor that mediates the suppression of metastases by a Lewis lung carcinoma (1994) Cell, 79 (2), pp. 315-328. , DOI 10.1016/0092-8674(94)90200-3; Norton, L., Massague, J., Is cancer a disease of self-seeding? (2006) Nature Medicine, 12 (8), pp. 875-878. , DOI 10.1038/nm0806-875, PII NM0806875; Bidard, F.C., (2008) Interactions en CoopéRations Cellulaires dans le Processus Métastatique, , MSc thesis. L'Université Paris XI; Benvenuti, S., Comoglio, P.M., The MET receptor tyrosine kinase in invasion and metastasis (2007) Journal of Cellular Physiology, 213 (2), pp. 316-325. , DOI 10.1002/jcp.21183; Mareel, M., Leroy, A., Clinical, cellular, and molecular aspects of cancer invasion (2003) Physiological Reviews, 83 (2), pp. 337-376; Christofori, G., New signals from the invasive front (2006) Nature, 441 (7092), pp. 444-450. , DOI 10.1038/nature04872, PII NATURE04872; Sabbah, M., Emami, S., Redeuilh, G., Molecular signature and therapeutic perspective of the epithelial-to-mesenchymal transitions in epithelial cancers (2008) Drug Resist Updat, 11, pp. 123-151; Thiery, J.P., Sleeman, J.P., Complex networks orchestrate epithelial-mesenchymal transitions (2006) Nature Reviews Molecular Cell Biology, 7 (2), pp. 131-142. , DOI 10.1038/nrm1835, PII NRM1835; Yang, J., Weinberg, R.A., Epithelial-Mesenchymal Transition: At the Crossroads of Development and Tumor Metastasis (2008) Developmental Cell, 14 (6), pp. 818-829. , DOI 10.1016/j.devcel.2008.05.009, PII S1534580708002098; Christiansen, J.J., Rajasekaran, A.K., Reassessing epithelial to mesenchymal transition as a prerequisite for carcinoma invasion and metastasis (2006) Cancer Research, 66 (17), pp. 8319-8326. , DOI 10.1158/0008-5472.CAN-06-0410; Brabletz, T., Jung, A., Spaderna, S., Hlubek, F., Kirchner, T., Migrating cancer stem cells - An integrated concept of malignant tumour progression (2005) Nature Reviews Cancer, 5 (9), pp. 744-749. , DOI 10.1038/nrc1694, PII N1694; Tarin, D., The fallacy of epithelial mesenchymal transition in neoplasia (2005) Cancer Research, 65 (14), pp. 5996-6000. , DOI 10.1158/0008-5472.CAN-05-0699; Garber, K., Epithelial-to-mesenchymal transition is important to metastasis, but questions remain (2008) J Natl Cancer Inst, 100, pp. 232-239; De Wever, O., Derycke, L., Hendrix, A., De Meerleer, G., Godeau, F., Depypere, H., Bracke, M., Soluble cadherins as cancer biomarkers (2007) Clinical and Experimental Metastasis, 24 (8), pp. 685-697. , DOI 10.1007/s10585-007-9104-8; Bellahcene, A., Castronovo, V., Ogbureke, K.U.E., Fisher, L.W., Fedarko, N.S., Small integrin-binding ligand N-linked glycoproteins (SIBLINGs): Multifunctional proteins in cancer (2008) Nature Reviews Cancer, 8 (3), pp. 212-226. , DOI 10.1038/nrc2345, PII NRC2345; Gimona, M., Buccione, R., Adhesions that mediate invasion (2006) International Journal of Biochemistry and Cell Biology, 38 (11), pp. 1875-1892. , DOI 10.1016/j.biocel.2006.05.003, PII S1357272506001580; Gimona, M., Buccione, R., Courtneidge, S.A., Assembly and biological role of podosomes and invadopodia (2008) Curr Opin Cell Biol, 20, pp. 235-241; Lopez-Otin, C., Matrisian, L.M., Emerging roles of proteases in tumour suppression (2007) Nature Reviews Cancer, 7 (10), pp. 800-808. , DOI 10.1038/nrc2228, PII NRC2228; Martin, M.D., Matrisian, L.M., The other side of MMPs: Protective roles in tumor progression (2007) Cancer and Metastasis Reviews, 26 (3-4), pp. 717-724. , DOI 10.1007/s10555-007-9089-4, Forty Years of Metastasis Research: A Tribute to Dr. Isaiah J. Fidler; Sahai, E., Mechanisms of cancer cell invasion (2005) Current Opinion in Genetics and Development, 15 (1), pp. 87-96. , DOI 10.1016/j.gde.2004.12.002, PII S0959437X04001881, Oncogenes and Cell Proliferation; Wolf, K., Mazo, I., Leung, H., Engelke, K., Von Andrian, U.H., Deryugina, E.I., Strongin, A.Y., Friedl, P., Compensation mechanism in tumor cell migration: Mesenchymal-amoeboid transition after blocking of pericellular proteolysis (2003) Journal of Cell Biology, 160 (2), pp. 267-277. , DOI 10.1083/jcb.200209006; Wolf, K., Friedl, P., Molecular mechanisms of cancer cell invasion and plasticity (2006) Br J Dermatol, 154 (SUPPL. 1), pp. 11-15; Yilmaz, M., Christofori, G., Lehembre, F., Distinct mechanisms of tumor invasion and metastasis (2007) Trends in Molecular Medicine, 13 (12), pp. 535-541. , DOI 10.1016/j.molmed.2007.10.004, PII S1471491407001888; Wicki, A., Christofori, G., The potential role of podoplanin in tumour invasion (2007) British Journal of Cancer, 96 (1), pp. 1-5. , DOI 10.1038/sj.bjc.6603518, PII 6603518; Yamaguchi, H., Condeelis, J., Regulation of the actin cytoskeleton in cancer cell migration and invasion (2007) Biochimica et Biophysica Acta - Molecular Cell Research, 1773 (5), pp. 642-652. , DOI 10.1016/j.bbamcr.2006.07.001, PII S0167488906001558; Sahai, E., Garcia-Medina, R., Pouyssegur, J., Vial, E., Smurf1 regulates tumor cell plasticity and motility through degradation of RhoA leading to localized inhibition of contractility (2007) Journal of Cell Biology, 176 (1), pp. 35-42. , http://www.jcb.org/cgi/reprint/176/1/35, DOI 10.1083/jcb.200605135; Gentile, A., Trusolino, L., Comoglio, P.M., The Met tyrosine kinase receptor in development and cancer (2008) Cancer Metastasis Rev, 27, pp. 85-94; Lengyel, E., Sawada, K., Salgia, R., Tyrosine kinase mutations in human cancer (2007) Current Molecular Medicine, 7 (1), pp. 77-84. , http://www.ingentaconnect.com/content/ben/cmm/2007/00000007/00000001/ art00007, DOI 10.2174/156652407779940486; Funasaka, T., Raz, A., The role of autocrine motility factor in tumor and tumor microenvironment (2007) Cancer and Metastasis Reviews, 26 (3-4), pp. 725-735. , DOI 10.1007/s10555-007-9086-7, Forty Years of Metastasis Research: A Tribute to Dr. Isaiah J. Fidler; Hehlgans, S., Haase, M., Cordes, N., Signalling via integrins: Implications for cell survival and anticancer strategies (2007) Biochimica et Biophysica Acta - Reviews on Cancer, 1775 (1), pp. 163-180. , DOI 10.1016/j.bbcan.2006.09.001, PII S0304419X06000588; Douma, S., Van Laar, T., Zevenhoven, J., Suppression of anoikis and induction of metastasis by the neurotrophic receptor TrkB (2004) Nature, 430, pp. 1034-1039; Geiger, T.R., Peeper, D.S., The neurotrophic receptor TrkB in anoikis resistance and metastasis: A perspective (2005) Cancer Research, 65 (16), pp. 7033-7036. , DOI 10.1158/0008-5472.CAN-05-0709; Sandri, M.T., Circulating tumor cells (2007) IEO-Scientific Report 2007-ongoing Research 2008, pp. 192-194; Gnerlich, J., Jeffe, D.B., Deshpande, A.D., Beers, C., Zander, C., Margenthaler, J.A., Surgical removal of the primary tumor increases overall survival in patients with metastatic breast cancer: Analysis of the 1988-2003 SEER data (2007) Annals of Surgical Oncology, 14 (8), pp. 2187-2194. , DOI 10.1245/s10434-007-9438-0; Salama, J.K., Chmura, S.J., Mehta, N., An initial report of a radiation dose-escalation trial in patients with one to five sites of metastatic disease (2008) Clin Cancer Res, 14, pp. 5255-5259; Dolle, L., Depypere, H.T., Bracke, M.E., Anti-invasive and anti-metastasis strategies: New roads, new tools and new hopes (2006) Current Cancer Drug Targets, 6 (8), pp. 729-751. , http://docstore.ingenta.com/cgi-bin/ds_deliver/1/u/d/ISIS/33724480.1/ben/ ccdt/2006/00000006/00000008/art00007/9C146EDF9740EFD9116485319359E89FF5E8D1E22C. pdf?link=http://www.ingentaconnect.com/error/delivery&format=pdf, DOI 10.2174/156800906779010263; Fox, S.B., Generali, D.G., Harris, A.L., Breast tumour angiogenesis (2007) Breast Cancer Res, 9, p. 216; Shaked, Y., Kerbel, R.S., Antiangiogenic strategies on defense: On the possibility of blocking rebounds by the tumor vasculature after chemotherapy (2007) Cancer Research, 67 (15), pp. 7055-7058. , http://cancerres.aacrjournals.org/cgi/reprint/67/15/7055, DOI 10.1158/0008-5472.CAN-07-0905; Formenti, S.C., Demaria, S., Local control by radiotherapy: Is that all there is? (2008) Breast Cancer Res, 10, p. 215; Husemann, Y., Geigl, J.B., Schubert, F., Musiani, P., Meyer, M., Burghart, E., Forni, G., Klein, C.A., Systemic Spread Is an Early Step in Breast Cancer (2008) Cancer Cell, 13 (1), pp. 58-68. , DOI 10.1016/j.ccr.2007.12.003, PII S1535610807003728; Denys, H., Derycke, L., Hendrix, A., Differential impact of TGF-beta and EGF on fibroblast differentiation and invasion reciprocally promotes colon cancer cell invasion (2008) Cancer Lett, 266, pp. 263-274; Milas, L., Mason, K., Liao, Z., Nieder, C., Milas, L., Ang, K.K., Role of cyclooxygenase-2 (COX-2) and its inhibition in tumor biology and radiotherapy (2003) Modification of Radiation Response, pp. 241-258. , Springer Berlin; Opdenakker, G., Van Damme, J., The countercurrent principle in invasion and metastasis of cancer cells. Recent insights on the roles of chemokines (2004) International Journal of Developmental Biology, 48 (5-6), pp. 519-527. , DOI 10.1387/ijdb.041796go, Invasion in Cancer and Embryonic Development; Nugent, J.L., Bunn Jr., P.A., Matthews, M.J., CNS metastases in small cell bronchogenic carcinoma. Increasing frequency and changing pattern with lengthening survival (1979) Cancer, 44 (5), pp. 1885-1893; Camphausen, K., Moses, M.A., Beecken, W.-D., Khan, M.K., Folkman, J., O'Reilly, M.S., Radiation therapy to a primary tumor accelerates metastatic growth in mice (2001) Cancer Research, 61 (5), pp. 2207-2211; Ramaswamy, S., Ross, K.N., Lander, E.S., Golub, T.R., A molecular signature of metastasis in primary solid tumors (2003) Nature Genetics, 33 (1), pp. 49-54. , DOI 10.1038/ng1060; Chen, Y.-J., Lin, S.-C., Kao, T., Chang, C.-S., Hong, P.-S., Shieh, T.-M., Chang, K.-W., Genome-wide profiling of oral squamous cell carcinoma (2004) Journal of Pathology, 204 (3), pp. 326-332. , DOI 10.1002/path.1640; Perou, C.M., Sorile, T., Eisen, M.B., Van De Rijn, M., Jeffrey, S.S., Ress, C.A., Pollack, J.R., Botstein, D., Molecular portraits of human breast tumours (2000) Nature, 406 (6797), pp. 747-752. , DOI 10.1038/35021093; LaTulippe, E., Satagopan, J., Smith, A., Scher, H., Scardino, P., Reuter, V., Gerald, W.L., Comprehensive gene expression analysis of prostate cancer reveals distinct transcriptional programs associated with metastatic disease (2002) Cancer Research, 62 (15), pp. 4499-4506; Lapointe, J., Li, C., Giacomini, C.P., Salari, K., Huang, S., Wang, P., Ferrari, M., Pollack, J.R., Genomic profiling reveals alternative genetic pathways of prostate tumorigenesis (2007) Cancer Research, 67 (18), pp. 8504-8510. , http://cancerres.aacrjournals.org/cgi/reprint/67/18/8504, DOI 10.1158/0008-5472.CAN-07-0673; Lips, E.H., Van Eijk, R., De Graaf, E.J., Integrating chromosomal aberrations and gene expression profiles to dissect rectal tumorigenesis (2008) BMC Cancer, 8, p. 314; Cromer, A., Carles, A., Millon, R., Ganguli, G., Chalmel, F., Lemaire, F., Young, J., Wasylyk, B., Identification of genes associated with tumorigenesis and metastatic potential of hypopharyngeal cancer by microarray analysis (2004) Oncogene, 23 (14), pp. 2484-2498. , DOI 10.1038/sj.onc.1207345; Couvelard, A., Hu, J., Steers, G., O'Toole, D., Sauvanet, A., Belghiti, J., Bedossa, P., Pezzella, F., Identification of Potential Therapeutic Targets by Gene-Expression Profiling in Pancreatic Endocrine Tumors (2006) Gastroenterology, 131 (5), pp. 1597-1610. , DOI 10.1053/j.gastro.2006.09.007, PII S0016508506020014; Bertucci, F., Finetti, P., Rougemont, J., Charafe-Jauffret, E., Nasser, V., Loriod, B., Camerlo, J., Viens, P., Gene expression profiling for molecular characterization of inflammatory breast cancer and prediction of response to chemotherapy (2004) Cancer Research, 64 (23), pp. 8558-8565. , DOI 10.1158/0008-5472.CAN-04-2696
Keywords: bone marrow; cancer cell; cancer invasion; carcinogenesis; cell activity; Circulation; ecosystem; epigenetics; extracellular matrix; gene control; host cell; human; Humans; lymph node metastasis; metastasis; Metastatic site; microarray analysis; Molecular biology; molecular imaging; Neoplasm Invasiveness; Neoplasm Metastasis; Neoplasms; nonhuman; pleiotropy; primary tumor; priority journal; Promoter and suppressor genes; promoter region; review; signal transduction; suppressor gene; Therapy guidance; Tumor-associated host cells

Cationic liposome-DNA complexes as gene delivery vectors: Development and behaviour towards bone-like cells - Oliveira, A.C.; Ferraz, M.P.; Monteiro, F.J.; Simões, S. (Acta BiomaterialiaActa Biomater., 2009)
Modulation of the biological pathways responsible for fracture repair and osteogenisis may accelerate regeneration. Gene therapy is an alternative method for the release of osteogenisis-stimulating proteins into tissues. The development of vectors for gene release is still a problem in terms of ethics and techniques. In this work we evaluated whether cationic liposomes constitute a valuable strategy for the release of genetic material into bone tissue cells as non-viral vectors. Liposomes were prepared with 1,2-dioleoyl-3-trimethylammonium propane (DOTAP)-2-dioleoyl-sn-glycero-3-phosphatidylethanolamine and DOTAP-cholesterol, and characterized according to their size, zeta potential, DNA protection capacity and cytotoxicity. Transfection studies were also carried out using pCMVβ-gal plasmid in two osteoblastic cell lines (MG63 and MC3T3-E1) and in the 294T line, varying the charge ratio and the applied DNA dose. Inclusion of transferrin to increase the expression was also tested. The results suggest that there is great dependency between the transfection activity and the lipid formulation, the charge ratios of the complexes, the applied DNA dose and the cell type. There were even some differences concerning both osteoblastic lines under study. The cells of the MC3T3-E1 line present greater expression levels than the cells of the MG-63 line. The conjugation of the transferrin with the complexes contributes to the increase in transfection levels, possibly due to an increase in internalization of complexes. It is thus a good strategy for inducing the expression of specific genes in osteoblast-like cells. © 2009 Acta Materialia Inc.
Cited By (since 1996): 17Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2009.02.019PubMed ID: 19332382Language of Original Document: EnglishCorrespondence Address: Ferraz, M.P.; CEBIMED, Faculdade de Ciências da Saú, Universidade Fernando Pessoa, Rua Carlos da Maia, 296, 4200-150 Porto, Portugal; email: mpferraz@ufp.ptChemicals/CAS: 1,2 dioleoyl 3 trimethylammoniopropane, 144189-73-1; DNA, 9007-49-2; transferrin, 82030-93-1; DNA, 9007-49-2; LiposomesReferences: Luo, J., Sun, M.H., Kang, Q., Peng, Y., Jiang, W., Luu, H.H., Gene therapy for bone regeneration (2005) Curr Gene Ther, 5 (2), pp. 167-179;Oreffo, R.O.C., Triffitt, J.T., Future potentials for using osteogenic stem cells and biomaterials in orthopedics (1999) Bone, 25 (2 SUPPL. 1), pp. 5S-9S; Laurencin, C.T., Attawia, M.A., Lu, L.Q., Borden, M.D., Lu, H.H., Gorum, W.J., Poly(lactide-co-glycolide)/hydroxyapatite delivery of BMP-2-producing cells: a regional gene therapy approach to bone regeneration (2001) Biomaterials, 22 (11), pp. 1271-1277; Katz, J.L., (1996) Applications of materials in medicine and dentistry: orthopedic applications, , Academic Press, San Diego, CA p. 335-46; Bucholz, R., Nonallograft osteoconductive bone grafts substitutes (2002) Clin Orthop, 395, pp. 44-52; Kirker-Head, C.A., Potential applications and delivery strategies of bone morphogenetic proteins (2000) Adv Drug Deliv Rev, 43, pp. 65-92; Chen, Y., Luk, K.D.K., Cheung, K.M.C., Xu, R., Lin, M.C., Lu, W.W., Gene therapy for new bone formation using adeno-associated viral bone morphogenetic protein-2 vectors (2003) Gene Ther, 10 (16), pp. 1345-1353; Tseng, W.-C., Huang, L., Liposome-based gene therapy (1998) Res Focus, 1 (5); Leach, J.K., Mooney, D., Bone engineering by controlled delivery of osteoinductive molecules and cells (2004) Expert Opin, 4 (7); Dragoo, J.L., Choi, J.Y., Lieberman, J.R., Huang, J., Zuk, P.A., Zhang, J., Bone induction by BMP-2 transduced stem cells derived from human fat (2003) J Orthop Res, 21 (4), pp. 622-629; Eliyahu, H., Barenholz, Y., Domb, A.J., Polymers for DNA delivery (2005) Molecules, 10, pp. 34-64; Penque, D., Terapia génica: um objectivo ou uma realidade (2000) Boletim Biotecnol, 66, pp. 16-19; Winn, S.R., Hu, Y., Sfeir, C., Hollinger, J.O., Gene therapy approaches for modulating bone regeneration (2000) Adv Drug Deliv Rev, 42 (1-2), pp. 121-138; Lima, N., Mota, M., (2003) Biotecnologia, fundamentos e aplicações, , Lidel, Lisboa p. 368-73; Luo, D., Saltzman, W.M., Synthetic DNA delivery systems (2000) Nat Biotechnol, 18, pp. 33-37; Kikuchi, H., Suzuki, N., Ebihara, K., Morita, H., Ishii, Y., Kikuchi, A., Gene delivery using liposome technology (1999) J Control Release, 62 (1-2), pp. 269-277; Liu, F., Huang, L., Development of non-viral vectors for systemic gene delivery (2002) J Control Release, 78 (1-3), pp. 259-266; Girao da Cruz, M.T., Simoes, S., Pires, P.P.C., Nir, S., Pedroso de Lima, M.C., Kinetic analysis of the initial steps involved in lipoplex-cell interactions: effect of various factors that influence transfection activity (2001) Biochim Biophys Acta (BBA) - Biomembr, 1510 (1-2), pp. 136-151; Zuidam, N.J., Barenholz, Y., Electrostatic and structural properties of complexes involving plasmid DNA and cationic lipids commonly used for gene delivery (1998) Biochim Biophys Acta (BBA) - Biomembr, 1368 (1), pp. 115-128; Tros de Ilarduya, C., Arangoa, M.A., Moreno-Aliaga, M.J., Duzgunes, N., Enhanced gene delivery in vitro and in vivo by improved transferrin-lipoplexes (2002) Biochim Biophys Acta (BBA) - Biomembr, 1561 (2), pp. 209-221; Simoes, S., Pires, P., Cruz, M.T.G.d., Duzgunes, N., Pedroso de Lima, M.C., Gene delivery by cationic liposome-DNA complexes containing transferrin or serum albumin (2003) Methods Enzymol, 373, pp. 369-383; Woo-Jeong, C., Jin-Ki, K., Sung-Hee, C., Jeong-Sook, P., Woong Shick, A., Kima, C.-K., Low toxicity of cationic lipid-based emulsion for gene transfer (2004) Biomaterials, 25 (27), pp. 5893-5903; Koe, G.S., Way, H.L., Quentingco, G.M., Smith, J.G., Wedeking, T., Niven, R.W., The effect of mixing on the formation of DNA/liposome complexes (1997) Pharmacy, p. 14; Lasic, D.D., Templeton, N.S., Liposomes in gene therapy (1996) Adv Drug Deliv Rev, 20 (2-3), pp. 221-266; Pedroso de Lima, M.C., Simoes, S., Pires, P., Faneca, H., Duzgunes, N., Cationic lipid-DNA complexes in gene delivery: from biophysics to biological applications (2001) Adv Drug Deliv Rev, 47 (2-3), pp. 277-294; Hirsch-Lerner, D., Zhang, M., Eliyahu, H., Ferrari, M.E., Wheeler, C.J., Barenholz, Y., Effect of "helper lipid" on lipoplex electrostatics (2005) Biochim Biophys Acta (BBA) - Biomembr, 1714 (2), pp. 71-84; Torricelli, P., Fini, M., Giavaresi, G., Borsari, V., Carpi, A., Nicolini, A., Comparative interspecies investigation on osteoblast cultures: data on cell viability and synthetic activity (2003) Biomed Pharmacother, 57 (1), pp. 57-62; Corsi, K., Chellat, F., Yahia, L., Fernandes, J.C., Mesenchymal stem cells, MG63 and HEK293 transfection using chitosan-DNA nanoparticles (2003) Biomaterials, 24 (7), pp. 1255-1264; Mislick, K.A., Baldeschwieler, J.D., Evidence for role of proteoglycans in cation-mediated gene transfer (1996) Proc Natl Acad Sci USA, 93 (22), pp. 12349-12354; Duzgunes, N., Nir, S., Mechanisms and kinetics of liposome-cell interactions (1999) Adv Drug Deliv Rev, 40 (1-2), pp. 3-18; Radwan Almofti, M., Harashima, H., Shinohara, Y., Almofti, A., Baba, Y., Kiwada, H., Cationic liposome-mediated gene delivery: biophysical study and mechanism of internalization (2003) Arch Biochem Biophys, 410 (2), pp. 246-253; Simões, S., Filipe, A., Faneca, H., Mano, M., Penacho, N., Duzgunes, N., Cationic liposomes for gene delivery (2005) Expert Opin, 2 (2); Rejman, J., Bragonzi, A., Conese, M., Role of clathrin- and caveolae-mediated endocytosis in gene transfer mediated by lipo- and polyplexes (2005) Mol Ther, 12 (3), pp. 468-474
Keywords: 1,2 dioleoyl 3 trimethylammoniopropane; animal cell; Animals; article; bone cell; bone development; bone tissue; Cationic liposomes; Cell Line; cell type; complex formation; controlled study; Cytotoxicity; DNA; drug mechanism; gene expression regulation; Gene therapy; Gene transfer; genetic transfection; Genetic Vectors; human; human cell; internalization; lipoplex; liposome; Liposomes; materials testing; Mice; nonhuman; nonviral gene delivery system; osteoblast; Osteoblasts; Osteogenesis; Particle Size; plasmid; priority journal; Transfection; transferrin; Zeta potential

Corrected and improved model for educational simulation of neonatal cardiovascular pathophysiology - Zijlmans, M.; Sá-Couto, C.D.; van Meurs, W.L.; Goodwin, J.A.; Andriessen, P. (Simulation in HealthcareSimul. Healthc., 2009)
We identified errors in the software implementation of the mathematical model presented in: Sá Couto CD, van Meurs WL, Goodwin JA, Andriessen P. A model for educational simulation of neonatal cardiovascular pathophysiology. Simul Healthcare 2006;1:4-12. Simulation results obtained with corrected code are presented for future reference. All but one of the simulation results do not differ by more than 9% from the previously published results. The heart rate response to acute loss of 30% of blood volume, simulated with corrected code is stronger than published target data. This modeling error was masked by errors in code implementation. We improved this response and the model by adjusting the gains and adding thresholds and saturations in the baroreflex model. General considerations on identification of model and code errors and model validity are presented. Copyright © 2009 Society for Simulation in Healthcare.
Cited By (since 1996): 4Export Date: 21 November 2012Source: Scopusdoi: 10.1097/SIH.0b013e31818b27a8Language of Original Document: EnglishCorrespondence Address: Zijlmans, M.; INEB-Instituto de Engenharia Biomédica, Porto, PortugalReferences: Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., A model for educational simulation of neonatal cardiovascular pathophysiology (2006) Simul Healthc, 1, pp. 4-12;Goodwin, J.A., Van Meurs, W.L., Sá Couto, C.D., Beneken, J.E.W., Graves, S.A., A model for educational simulation of infant cardiovascular physiology (2004) Anesth Analg, 99, pp. 1655-1664; Beneken, J.E.W., A mathematical approach to cardiovascular function (1965) The Uncontrolled Human System, , Thesis, University of Utrecht, The Netherlands; Andriessen, P., Bambang Oetomo, S., Peters, C., Vermeulen, B., Wijn, P.F.F., Blanco, C.E., Baroreceptor reflex sensitivity in human neonates: The effect of postmenstrual age (2005) J Physiol, 568, pp. 333-341; Segar, J.L., Roghair, R.D., Segar, E.M., Bailey, M.C., Scholz, T.D., Lamb, F.S., Early gestation dexamethasone alters baroreflex and vascular responses in newborn lambs before hypertension (2006) Am J Physiol Regul Integr Comp Physiol, 291, pp. R481-R488; Wallgren, G., Barr, M., Rudhe, U., Hemodynamic studies of induced acute hypo- and hypervolemia in the newborn infant (1964) Acta Paediatr, 53, pp. 1-12
Keywords: aorta coarctation; article; Baroreflex; bleeding; blood pressure; blood volume; Cardiac Output; cardiovascular disease; Cardiovascular Diseases; Cardiovascular physiology; computer program; Computer simulation; Congenital heart defect; congenital heart malformation; diastolic blood pressure; Education, Medical; Erratum; Fallot tetralogy; great vessels transposition; heart output; Heart rate; heart right ventricle pressure; human; Humans; Infant, Newborn; lung pressure; mathematical model; mean arterial pressure; medical education; medical error; methodology; Neonate; Neonatology; newborn; patent ductus arteriosus; pathophysiology; physiology; pressoreceptor reflex; priority journal; simulation; Software Design; systolic blood pressure; Validation; validity; vascular resistance; Verification; vital sign

The correlation between the adsorption of adhesive proteins and cell behaviour on hydroxyl-methyl mixed self-assembled monolayers - Barrias, C.C.; Martins, M.C.L.; Almeida-Porada, G.; Barbosa, M.A.; Granja, P.L. (BiomaterialsBiomaterials, 2009)
The objective of this study was to compare the biological effects of two key cell-adhesive proteins, fibronectin (FN) and vitronectin (VN), upon adsorption onto molecularly-designed model surfaces. Single-component and mixed self-assembled monolayers (SAMs) of alkanethiols on gold with OH and CH 3 terminal groups were prepared at 100%, 65%, 36% and 0% of OH at the surface, to generate a range of surfaces with a simple chemistry and a wettability gradient. FN and VN were adsorbed under non-competitive (single-protein solutions) and competitive (multi-protein solutions) conditions, and compared at different levels: adsorbed amount (radiolabelling), elution, functional presentation of cell-binding domains (ELISA), and role in mediating cell adhesion (antibody-based assay). The observed trends were related to mesenchymal stem cell response in terms of adhesion and overall cell morphology. Under non-competitive conditions, adsorption of both proteins increased with surface hydrophobicity. The presence of competitive proteins significantly decreased the adsorbed amounts, although both proteins were still detected in all SAMs. Adsorption of FN followed a trend similar to that of non-competitive conditions, while adsorption of VN was higher on 100%OH-SAMs. Concerning elution, retention of adsorbed VN was always higher than that of FN. For both proteins, functional presentation of cell-binding domains was more effective on the more hydrophilic 100%OH-SAMs. This fact, coupled to the ability of this type of SAMs to selectively recruit and retain VN in the presence of competitive serum proteins, seems to correlate with the better cell response observed on these surfaces, as compared with hydrophobic 0%OH(100%CH 3)-SAMs. © 2008 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 41Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2008.09.048PubMed ID: 18952279Language of Original Document: EnglishCorrespondence Address: Barrias, C.C.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, R. Campo Alegre 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptChemicals/CAS: fibronectin, 86088-83-7; gold, 7440-57-5; thiol derivative, 13940-21-1; Biocompatible Materials; Fibronectins; VitronectinReferences: Wilson, C.J., Clegg, R.E., Leavesley, D.I., Pearcy, M.J., Mediation of biomaterial-cell interactions by adsorbed proteins: a review (2005) Tissue Eng, 11, pp. 1-18;García, A.J., Vega, M.D., Boettiger, D., Modulation of cell proliferation and differentiation through substrate-dependent changes in fibronectin conformation (1999) Mol Biol Cell, 10, pp. 785-798; Keselowsky, B.G., Collard, D.M., García, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res A, 66, pp. 247-259; Underwood, P.A., Bennett, F.A., A comparison of the biological activities of the cell-adhesive proteins vitronectin and fibronectin (1989) J Cell Sci, 93, pp. 641-649; Steele, J.G., Johnson, G., Underwood, P.A., Role of serum vitronectin and fibronectin in adhesion of fibroblasts following seeding onto tissue culture polystyrene (1992) J Biomed Mater Res, 26, pp. 861-884; Steele, J.G., Dalton, B.A., Johnson, G., Underwood, P.A., Polystyrene chemistry affects vitronectin activity: an explanation for cell attachment to tissue culture polystyrene but not to unmodified polystyrene (1993) J Biomed Mater Res, 27, pp. 927-940; Underwood, P.A., Steele, J.G., Dalton, B.A., Effects of polystyrene surface chemistry on the biological activity of solid phase fibronectin and vitronectin, analysed with monoclonal antibodies (1993) J Cell Sci, 104, pp. 793-803; Suzuki, S., Oldberg, A., Hayman, E.G., Pierschbacher, M.D., Ruoslahti, E., Complete amino acid sequence of human vitronectin deduced from cDNA. Similarity of cell attachment sites in vitronectin and fibronectin (1985) EMBO J, 4, pp. 2519-2524; Lee, M.H., Ducheyne, P., Lynch, L., Boettiger, D., Composto, R.J., Effect of biomaterial surface properties on fibronectin-alpha5beta1 integrin interaction and cellular attachment (2006) Biomaterials, 27, pp. 1907-1916; Grinnell, F., Feld, M.K., Fibronectin adsorption on hydrophilic and hydrophobic surfaces detected by antibody binding and analyzed during cell adhesion in serum-containing medium (1982) J Biol Chem, 257, pp. 4888-4893; Sousa, S.R., Lamghari, M., Sampaio, P., Moradas-Ferreira, P., Barbosa, M.A., Osteoblast adhesion and morphology on TiO 2 depends on the competitive preadsorption of albumin and fibronectin (2008) J Biomed Mater Res A, 84, pp. 281-290; Fabrizius-Homan, D.J., Cooper, S.L., Competitive adsorption of vitronectin with albumin, fibrinogen, and fibronectin on polymeric biomaterials (1991) J Biomed Mater Res, 25, pp. 953-971; Bale, M.D., Wohlfahrt, L.A., Mosher, D.F., Tomasini, B., Sutton, R.C., Identification of vitronectin as a major plasma protein adsorbed on polymer surfaces of different copolymer composition (1989) Blood, 74, pp. 2698-2706; Thomas, C.H., McFarland, C.D., Jenkins, M.L., Rezania, A., Steele, J.G., Healy, K.E., The role of vitronectin in the attachment and spatial distribution of bone-derived cells on materials with patterned surface chemistry (1997) J Biomed Mater Res, 37, pp. 81-93; McFarland, C.D., Thomas, C.H., DeFilippis, C., Steele, J.G., Healy, K.E., Protein adsorption and cell attachment to patterned surfaces (2000) J Biomed Mater Res, 49, pp. 200-210; Love, J.C., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chem Rev, 105, pp. 1103-1169; Mrksich, M., Whitesides, G.M., Using self-assembled monolayers to understand the interactions of man-made surfaces with proteins and cells (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-78; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111, pp. 321-335; Faucheux, N., Schweiss, R., Lützow, K., Werner, C., Groth, T., Self-assembled monolayers with different terminating groups as model substrates for cell adhesion studies (2004) Biomaterials, 25, pp. 2721-2730; Bernards, M.T., Jiang, S., pH-induced conformation changes of adsorbed vitronectin maximize its bovine aortic endothelial cell binding ability (2008) J Biomed Mater Res A; Martins, M.C., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) J Biomed Mater Res A, 67, pp. 158-171; Rodrigues, S.N., Gonçalves, I.C., Martins, M.C., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Chamberlain, J., Yamagami, T., Colletti, E., Theise, N.D., Desai, J., Frias, A., Efficient generation of human hepatocytes by the intrahepatic delivery of clonal human mesenchymal stem cells in fetal sheep (2007) Hepatology, 46, pp. 1935-1945; (1993) Iodine-125. A guide to radioiodination techniques, , Amersham Life Science, Little Chalfort; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, pp. 183-214. , Williams D.F. (Ed), CRC Press Inc., Harcover; Arima, Y., Iwata, H., Effect of wettability and surface functional groups on protein adsorption and cell adhesion using well-defined mixed self-assembled monolayers (2007) Biomaterials, 28, pp. 3074-3082; Capadona, J.R., Collard, D.M., Garcia, A.J., Fibronectin adsorption and cell adhesion to mixed monolayers of tri(ethylene glycol)- and methyl-terminated alkanethiols (2003) Langmuir, 19, pp. 1847-1852; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13, pp. 3404-3413; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (2000) J Biomed Mater Res, 49, pp. 435-447; Wertz, C.F., Santore, M.M., Fibrinogen adsorption on hydrophilic and hydrophobic surfaces: geometrical and energetic aspects of interfacial relaxations (2002) Langmuir, 18, pp. 706-715; Pitt, W.G., Fabrizius-Homan, D.J., Mosher, D.F., Cooper, S.L., Vitronectin adsorption on polystyrene and oxidized polystyrene (1989) J Colloid Interface Sci, 129, pp. 231-239; Seiffert, D., Smith, J.W., The cell adhesion domain in plasma vitronectin is cryptic (1997) J Biol Chem, 272, pp. 13705-13710
Keywords: Adhesion; Adhesiveness; Adsorption; alkane; Animals; article; Biocompatible Materials; Biological Assay; bone marrow; Cattle; cell adhesion; Cell culture; Cell Movement; Cells; Cells, Cultured; cytology; cytoskeleton; Electric currents; Electron energy levels; enzyme linked immunosorbent assay; Fibronectin; Fibronectins; Focal adhesions; Functional groups; Functionalization; gold; human; human cell; Humans; hydrophilicity; hydrophobicity; Hydroxylation; isotope labeling; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Confocal; Missile bases; Molecular interactions; monoclonal antibody; priority journal; Protein adsorption; protein analysis; protein binding; Protein Structure, Tertiary; Proteins; Self assembled monolayers; Self-assembled monolayers; stem cell; Stem cells; Surface Properties; thiol derivative; Vitronectin

Cytotoxicity evaluation of nanocrystalline diamond coatings by fibroblast cell cultures - Amaral, M.; Gomes, P.S.; Lopes, M.A.; Santos, J.D.; Silva, R.F.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2009)
The cytotoxicity profile of nanocrystalline diamond (NCD) coatings on a Si 3N 4 ceramic was investigated. This material is envisaged to have biomedical dental applications such as burrs and surgical instruments. Two fibroblast cell culture systems were used to address the cytotoxicity of NCD-coated samples: L929 cells (a mouse permanent cell line) and human gingival fibroblasts. Cell behavior was evaluated in terms of cell adhesion, cell viability/proliferation (mitochondrial function, MTT assay) and the pattern of cell growth. Fibroblast cell behavior on standard polystyrene culture plates was used as control, as Si 3N 4 substrates have previously been shown to be biocompatible. NCD coatings provided a suitable surface for cell attachment, spreading and proliferation. Human gingival cells showed a homogeneous cytoplasm spreading, a flattened elongated morphology and a typical parallel alignment on confluent cultures. In comparison, L929 cells denoted a lower cytoplasm expansion, a heterogeneous spreading but a higher proliferation rate. For both cells, after few days, the NCD coating was completely covered with continuous cell layers. As compared to standard polystyrene culture plates, no deleterious or cytotoxic responses were observed with L929 and human fibroblast cell cultures, and in both a slight enhancement in cell proliferation was observed. In addition, the seeded NCD film allowed reproduction of the typical features of the two cell culture systems tested, further suggesting the lack of cytotoxicity of this coating. © 2008 Acta Materialia Inc.
Cited By (since 1996): 8Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2008.08.015PubMed ID: 18819854Language of Original Document: EnglishCorrespondence Address: Amaral, M.; CICECO, Department of Ceramics and Glass Engineering, University of Aveiro, 3810-193 Aveiro, Portugal; email: margarida.amaral@ua.ptChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; diamond, 7782-40-3; polystyrene, 9003-53-6; silicon nitride, 12033-89-5; Culture Media; Diamond, 7782-40-3References: Griffin, J., Ray, P.C., Role of inert gas in the low-temperature nano-diamond chemical vapour deposition process (2006) Nanotechnology, 17, pp. 1225-1229;Mitura, S., Mitura, K., Niedzielski, P., Louda, P., Danilenko, V., Nanocrystalline diamond, its synthesis, properties and applications (2006) J Achievements Mater Manuf Eng, 16, pp. 9-16; Okrój, W., Kamińska, M., Klimek, L., Szymański, W., Walkowiak, B., Blood platelets in contact with nanocrystalline diamond surfaces (2006) Diamond Relat Mater, 15, pp. 1535-1539; Xiao, X., Wang, J., Liu, C., Carlisle, J.A., Mech, B., Greenberg, R., In vitro and in vivo evaluation of ultrananocrystalline diamond for coating of implantable retinal microchips (2006) J Biomed Mater Res B: Appl Biomater, 77 B, pp. 273-281; Tang, L., Tsai, C., Gerberich, W.W., Kruckeberg, L., Kania, D.R., Biocompatibility of chemical-vapour-deposited diamond (1995) Biomaterials, 16, pp. 483-488; Steinmueller-Nethl, D., Kloss, F.R., Haq, M.N.U., Rainer, M., Larsson, K., Linsmeier, C., Strong binding of bioactive BMP-2 to nanocrystalline diamond by physisorption (2006) Biomaterials, 27, pp. 4547-4556; Wenmackers, S., Christiaens, P., Daenen, M., Haenen, K., Nesládek, M., Ven, M., DNA attachment to nanocrystalline diamond films (2005) Phys Status Solidi, 202, pp. 2212-2216; Retama, J.R., Hernando, J., Lopez-Ruiz, B., Härtl, A., Steinmüller, D., Stutzmann, M., Synthetic nanocrystalline diamond as a third-generation biosensor support (2006) Langmuir, 22, pp. 5837-5842; Siew, P.S., Loh, K.P., Poh, W.C., Zhang, H., Biosensing properties of nanocrystalline diamond film grown on polycrystalline diamond electrodes (2005) Diamond Relat Mater, 14, pp. 426-431; Jakubowski, W., Bartosz, G., Niedzielski, P., Szymanski, W., Walkowiak, B., Nanocrystalline diamond surface is resistant to bacterial colonization (2004) Diamond Relat Mater, 13, pp. 1761-1763; Trava-Airoldi, V.J., Corat, E.J., Leite, N.F., Nono, M., Ferreira, N.G., Baranauskas, V., CVD diamond burrs-development and applications (1996) Diamond Relat Mater, 5, pp. 857-860; Amar, M., Ahmed, W., Sein, H., Jones, A.N., Rego, C., Chemical vapour deposition of diamond coatings onto molybdenum dental tools (2003) J Phys Condens Matter, 15, pp. S2977-S2982; Tetsumura, A., Honda, E., Sasaki, T., Kino, K., Metallic residues as a source of artifacts in magnetic resonance imaging of the temporomandibular joint (1999) Dentomaxillofac Radiol, 28, pp. 186-190; Carvalho, C.A., Fagundes, T.C., Barata, T.E., Trava-Airoldi, V.J., Navarro, M.L., The use of CVD diamond burrs for ultraconservative cavity preparations: a report of two cases (2007) J Esthet Restor Dent, 19, pp. 19-29; Mitura, K., Niedzielski, P., Grzegorz, B., Moll, J., Walkowiak, B., Pawlowska, Z., Interactions between carbon coatings and tissue (2006) Surf Coat Technol, 201, pp. 2117-2123; Fries, M.D., Vohra, Y.K., Microcrystalline and nanocrystalline diamond film deposition on cobalt chrome alloy (1999) Thin films-stresses and mechanical properties VIII, , Vinci R., Kraft O., Moody N., Besser P., and Shaffer II E. (Eds), MRS Publications, Boston, MA; Fries, M.D., Vohra, Y.K., Properties of nanocrystalline thin films grown by MPCVD for biomedical implant purposes (2004) Diamond Relat Mater, 13, pp. 1740-1743; Papo, M.J., Catledge, S.A., Vohra, Y.K., Mechanical wear behavior of nanocrystalline and multilayer diamond coatings on temporomandibular joint implants (2004) J Mater Sci: Mater Med, 15, pp. 773-777; Sun, F.H., Zhang, Z.M., Ma, Y.P., Chen, M., Synthesis of nanocrystalline diamond films on smooth WC-Co cemented carbide substrates (2007) Int J Abrasive Technol, 1, pp. 161-172; Belmonte, M., Fernandes, A.J.S., Costa, F.M., Oliveira, F.J., Silva, R.F., Adhesion behaviour assessment on diamond coated silicon nitride by acoustic emission (2003) Diamond Relat Mater, 12, pp. 733-737; Petzow, G., Herrmann, M., Silicon nitride ceramics (2002) Struct Bond, 102, pp. 47-167; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23, pp. 4897-4906; Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Popov, C., Kulisch, W., Jelinek, M., Bock, A., Strnad, J., Nanocrystalline diamond/amorphous carbon composite films for applications in tribology, optics and biomedicine (2006) Thin Solid Films, 494, pp. 92-97; Chong, K.F., Loh, K.P., Vedula, S.R., Lim, C.T., Sternschulte, H., Steinmüller, D., Cell adhesion properties on photochemically functionalized diamond (2007) Langmuir, 23, pp. 5615-5621; Bajaj, P., Akin, D., Gupta, A., Sherman, D., Shi, B., Auciello, O., Ultra-nanocrystalline diamond film as an optimal cell interface for biomedical applications (2007) Biomed Microdevices, , [Epub ahead of print]; Arnold, L.F., Baram, B., In vitro culture of periodontal ligament cells (1972) J Dent Res, 51, pp. 953-959; Piche, J.E., Carnes Jr., D.L., Graves, D.T., Initial characterization of cells derived from human periodontia (1989) J Dent Res, 68, pp. 761-767; Trigo Cabral, C., Costa, M.A., Fernandes, M.H., In vitro models of periodontal cells: a comparative study of long-term gingival, periodontal ligament and alveolar bone cell cultures in the presence of β-glycerophosphate and dexamethasone (2007) J Mater Sci: Mater Med, 18, pp. 1079-1088; Bajpai, P.K., Billote, W.G., Ceramic biomaterials (1995) The biomedical engineering handbook, pp. 552-580. , Bronzino J.D. (Ed), CRC Press, Boca Raton, FL; Nishitani-Gamo, M., Ando, T., Watanabe, K., Sekita, M., Dennig, P.A., Yamamoto, K., Interfacial structures of oriented diamond on Si (1 0 0) characterized by confocal Raman spectroscopy (1997) Diamond Relat Mater, 6, pp. 1036-1040; Ferrari, A.C., Robertson, J., Origin of the 1150 cm -1 Raman mode in nanocrystalline diamond (2001) Phys Rev B, 63, pp. 121405-1-121405-4; Pfeiffer, R., Kuzmany, H., Knoll, P., Bokova, S., Salk, N., Günther, B., Evidence for trans-polyacetylene in nano-crystalline diamond films (2003) Diamond Relat Mater, 12, pp. 268-271; Zimmermann, T., Janischowsky, K., Denisenko, A., Guillén, F.J.H., Kubovic, M., Gruen, D.M., Nanocrystalline diamond pn-structure grown by hot-filament CVD (2006) Diamond Relat Mater, 15, pp. 203-206; Krauss, A.R., Auciello, O., Gruen, D.M., Jayatissa, A., Sumant, A., Tucek, J., Ultrananocrystalline diamond thin films for MEMS and moving mechanical assembly devices (2001) Diamond Relat Mater, 10, pp. 1952-1961; Amaral, M., Fernandes, A.J.S., Vila, M., Oliveira, F.J., Silva, R.F., Growth rate improvements in the hot-filament CVD deposition of nanocrystalline diamond (2006) Diamond Relat Mater, 15, pp. 1822-1827; Alberts, B., Johnson, A., Lewis, J., Raff, M., Roberts, K., Walter, P., The cytoskeleton (2002) Molecular biology of the cell. 4th ed., pp. 907-972. , Alberts B., Johnson A., Lewis J., Raff M., Roberts K., and Walter P. (Eds), Garland Publishing, New York; Stamenovic, D., Effects of cytoskeletal prestress on cell rheological behaviour (2005) Acta Biomater, 1, pp. 255-262; Freshney, T.I., Biology of cultured cells (2000) Culture of animal cells. A manual of basic technique, pp. 9-18. , Wiley-Liss, New York; Garguilo, J.M., Davis, B.A., Buddie, M., Köck, F.A.M., Nemanich, R.J., Fibrinogen adsorption onto microwave plasma chemical vapor deposited diamond films (2004) Diamond Relat Mater, 13, pp. 595-599; Ariano, P., Baldellia, P., Carbonea, E., Gilardino, A., Giudicea, A.L., Lovisolo, D., Cellular adhesion and neuronal excitability on functionalised diamond surfaces (2005) Diamond Relat Mater, 14, pp. 669-674; Heinrich, G., Grijgler, T., Rosiwal, S.M., Singer, R.F., CVD diamond coated titanium alloys for biomedical and aerospace applications (1997) Surf Coat Technol, 94-95, pp. 514-520; Müller, R., Adamschik, M., Steidl, D., Kohn, E., Thamasett, S., Stiller, S., Application of CVD-diamond for catheter ablation in the heart (2004) Diamond Relat Mater, 13, pp. 1080-1083; Nordsletten, L., Hogasen, A.K.M., Konttinen, Y.T., Santavirta, S., Aspenberg, P., Aasen, A.O., Human monocytes stimulation by particles of hydroxyapatite, silicon carbide and diamond: in vitro studies of new prosthesis coatings (1996) Biomaterials, 17, pp. 1521-1527; Aspenberg, P., Antilla, A., Konttinen, Y.T., Lappalainen, R., Goodman, S.B., Nordsletten, L., Benign response to particles of diamond and SiC: bone chamber studies of new joint replacement coating materials in rabbits (1996) Biomaterials, 17, pp. 807-812; Specht, C.G., Williams, O.A., Jackman, R.B., Schoepfer, R., Ordered growth of neurons on diamond (2004) Biomaterials, 25, pp. 4073-4078; Schrand, A.M., Huang, H., Carlson, C., Schlager, J.J., Omacr Sawa, E., Hussain, S.M., Are diamond nanoparticles cytotoxic? (2007) J Phys Chem B, 111, pp. 2-7; International Organization for Standardization, ISO 10993-5: biological evaluation of medical devices. Part 5. Tests for cytotoxicity: in vitro methods. Geneva; 1992International Organization for Standardization, ISO 7405: dentistry-preclinical evaluation of biocompatibility of medical devices used in dentistry-test methods for dental materials. Geneva; 1997Kaplan, F.S., Hayes, W.C., Keaveny, T.M., Boskey, A., Einhorn, T.A., Iannotti, J.P., Form and function of bone (1994) Orthopedic basic science, pp. 127-185. , Simon S.P. (Ed), American Academy of Orthopedic Surgeons, Columbus, OH; Webster, T.J., Proteins: structure and interactions patterns to solid surfaces (2004) Encyclopedia of nanoscience and nanotechnology, pp. 3079-3095. , Schwarz J.A., Contescu C., and Putyera K. (Eds), Marcel Dekker, New York; Webster, T.J., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nanophase ceramics (2000) J Biomed Mater Res, 51, pp. 475-483; Shane, A.C., Marc, D.F., Yogesh, K.V., William, R.L., Jack, E.L., Shanna, W., Nanostructured ceramics for biomedical implants (2002) J Nanosci Nanotechnol, 2, pp. 1-20; Price, R.L., Haberstroh, K.M., Webster, T.J., Enhanced functions of osteoblasts on nanostructured surfaces of carbon and alumina (2003) Med Biol Eng Comput, 41, pp. 372-375; Webster, T.J., Siegel, R.W., Bizios, R., Osteoblast adhesion on nanophase ceramics (1999) Biomaterials, 20, pp. 1221-1227; Perla, V., Webster, T.J., Better osteoblast adhesion on nanoparticulate selenium-A promising orthopedic implant material (2005) J Biomed Mater Res, 75 A, pp. 356-364
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; animal cell; Animals; article; Biocompatibility; Biomedical dental applications; biomedicine; cell adhesion; Cell Division; cell function; cell growth; Cell Line; cell proliferation; cell spreading; cell structure; cell surface; cell survival; cell viability; ceramics; controlled study; Culture Media; cytoplasm; Cytotoxicity; dentistry; diamond; Fibroblast cell cultures; fibroblast culture; Fibroblasts; gingiva; human; human cell; Humans; material coating; Mice; Microscopy, Electron, Scanning; mitochondrial respiration; mouse; nanocrystal; Nanocrystalline diamond coating; Nanostructures; nonhuman; polystyrene; priority journal; Silicon nitride; Surgical instrument

The effect of the co-immobilization of human osteoprogenitors and endothelial cells within alginate microspheres on mineralization in a bone defect - Grellier, M.; Granja, P.L.; Fricain, J.-C.; Bidarra, S.J.; Renard, M.; Bareille, R.; Bourget, C.; Amédée, J.; Barbosa, M.A. (BiomaterialsBiomaterials, 2009)
Bone regeneration seems to be dependant on cell communication between osteogenic and endothelial cells arising from surrounding blood vessels. This study aims to determine whether endothelial cells can regulate the osteogenic potential of osteoprogenitor cells in vitro and in vivo, in a long bone defect, when co-immobilized in alginate microspheres. Alginate is a natural polymer widely used as a biomaterial for cell encapsulation. Human osteoprogenitors (HOP) from bone marrow mesenchymal stem cells were immobilized alone or together with human umbilical vein endothelial cells (HUVEC) inside irradiated, oxidized and RGD-grafted alginate microspheres. Immobilized cells were cultured in dynamic conditions and cell metabolic activity increased during three weeks. The gene expression of alkaline phosphatase and osteocalcin, both specific markers of the osteoblastic phenotype, and mineralization deposits were upregulated in co-immobilized HOPs and HUVECs, comparing to the immobilization of monocultures. VEGF secretion was also increased when HOPs were co-immobilized with HUVECs. Microspheres containing co-cultures were further implanted in a bone defect and bone formation was analysed by μCT and histology at 3 and 6 weeks post-implantation. Mineralization was observed inside and around the implanted microspheres containing the immobilized cells. However, when HOPs were co-immobilized with HUVECs, mineralization significantly increased. These findings demonstrate that co-immobilization of osteogenic and endothelial cells within RGD-grafted alginate microspheres provides a promising strategy for bone tissue engineering. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 38Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.02.033PubMed ID: 19299013Language of Original Document: EnglishCorrespondence Address: Grellier, M.; INSERM, U577, Université Victor Segalen Bordeaux 2, UMR-S577, F-33076 Bordeaux Cedex, France; email: maritie.grellier@inserm.frChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; alkaline phosphatase, 9001-78-9; arginylglycylaspartic acid, 99896-85-2; osteocalcin, 136461-80-8; Alginates; Glucuronic Acid, 576-37-4; Hexuronic Acids; alginic acid, 9005-32-7References: Oreffo, R.O., Triffitt, J.T., Future potentials for using osteogenic stem cells and biomaterials in orthopedics (1999) Bone, 25 (2 SUPPL), pp. 5S-9S;Lubiatowski, P., Kruczynski, J., Gradys, A., Trzeciak, T., Jaroszewski, J., Articular cartilage repair by means of biodegradable scaffolds (2006) Transplant Proc, 38 (1), pp. 320-322; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H.J., Barrias, C.C., Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix (2007) Biomaterials, 28 (25), pp. 3644-3655; Gerber, H.P., Ferrara, N., Angiogenesis and bone growth (2000) Trends Cardiovasc Med, 10 (5), pp. 223-228; Carano, R.A., Filvaroff, E.H., Angiogenesis and bone repair (2003) Drug Discov Today, 8 (21), pp. 980-989; Deckers, M.M., Karperien, M., van der Bent, C., Yamashita, T., Papapoulos, S.E., Lowik, C.W., Expression of vascular endothelial growth factors and their receptors during osteoblast differentiation (2000) Endocrinology, 141 (5), pp. 1667-1674; Guillotin, B., Bourget, C., Remy-Zolgadri, M., Bareille, R., Fernandez, P., Conrad, V., Human primary endothelial cells stimulate human osteoprogenitor cell differentiation (2004) Cell Physiol Biochem, 14 (4-6), pp. 325-332; Villars, F., Bordenave, L., Bareille, R., Amedee, J., Effect of human endothelial cells on human bone marrow stromal cell phenotype: role of VEGF? (2000) J Cell Biochem, 79 (4), pp. 672-685; Kaigler, D., Krebsbach, P.H., Wang, Z., West, E.R., Horger, K., Mooney, D.J., Transplanted endothelial cells enhance orthotopic bone regeneration (2006) J Dent Res, 85 (7), pp. 633-637; Sun, H., Qu, Z., Guo, Y., Zang, G., Yang, B., In vitro and in vivo effects of rat kidney vascular endothelial cells on osteogenesis of rat bone marrow mesenchymal stem cells growing on polylactide-glycoli acid (PLGA) scaffolds (2007) Biomed Eng Online, 6, p. 41; Augst, A.D., Kong, H.J., Mooney, D.J., Alginate hydrogels as biomaterials (2006) Macromol Biosci, 6 (8), pp. 623-633; Leal, D., Matsuhiro, B., Rossi, M., Caruso, F., FT-IR spectra of alginic acid block fractions in three species of brown seaweeds (2008) Carbohydr Res, 343 (2), pp. 308-316; Keshaw, H., Forbes, A., Day, R.M., Release of angiogenic growth factors from cells encapsulated in alginate beads with bioactive glass (2005) Biomaterials, 26 (19), pp. 4171-4179; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80 (11), pp. 2025-2029; Abbah, S.A., Lu, W.W., Chan, D., Cheung, K.M., Liu, W.G., Zhao, F., In vitro evaluation of alginate encapsulated adipose-tissue stromal cells for use as injectable bone graft substitute (2006) Biochem Biophys Res Commun, 347 (1), pp. 185-191; Barrias, C.C., Lamghari, M., Granja, P.L., Sa Miranda, M.C., Barbosa, M.A., Biological evaluation of calcium alginate microspheres as a vehicle for the localized delivery of a therapeutic enzyme (2005) J Biomed Mater Res A, 74 (4), pp. 545-552; Durrieu, M.C., Pallu, S., Guillemot, F., Bareille, R., Amedee, J., Baquey, C.H., Grafting RGD containing peptides onto hydroxyapatite to promote osteoblastic cells adhesion (2004) J Mater Sci Mater Med, 15 (7), pp. 779-786; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24 (22), pp. 4023-4029; Bordenave, L., Baquey, C., Bareille, R., Lefebvre, F., Lauroua, C., Guerin, V., Endothelial cell compatibility testing of three different Pellethanes (1993) J Biomed Mater Res, 27 (11), pp. 1367-1381; Rowley, J.A., Mooney, D.J., Alginate type and RGD density control myoblast phenotype (2002) J Biomed Mater Res, 60 (2), pp. 217-223; Villars, F., Guillotin, B., Amedee, T., Dutoya, S., Bordenave, L., Bareille, R., Effect of HUVEC on human osteoprogenitor cell differentiation needs heterotypic gap junction communication (2002) Am J Physiol Cell Physiol, 282 (4), pp. C775-C785; Clarkin, C.E., Emery, R.J., Pitsillides, A.A., Wheeler-Jones, C.P., Evaluation of VEGF-mediated signaling in primary human cells reveals a paracrine action for VEGF in osteoblast-mediated crosstalk to endothelial cells (2007) J Cell Physiol; Cheng, C., Liu, H., Ge, H., Qian, J., Qin, J., Sun, L., Essential role of Src suppressed C kinase substrates in endothelial cell adhesion and spreading (2007) Biochem Biophys Res Commun, 358 (1), pp. 342-348; Gerber, H.P., McMurtrey, A., Kowalski, J., Yan, M., Keyt, B.A., Dixit, V., Vascular endothelial growth factor regulates endothelial cell survival through the phosphatidylinositol 3′-kinase/Akt signal transduction pathway. Requirement for Flk-1/KDR activation (1998) J Biol Chem, 273 (46), pp. 30336-30343; Cross, M.J., Claesson-Welsh, L., FGF and VEGF function in angiogenesis: signalling pathways, biological responses and therapeutic inhibition (2001) Trends Pharmacol Sci, 22 (4), pp. 201-207; Volkmer, E., Drosse, I., Otto, S., Stangelmayer, A., Stengele, M., Kallukalam, B.C., Hypoxia in static and dynamic 3D culture systems for tissue engineering of bone (2008) Tissue Eng Part A, 14 (8), pp. 1331-1340; Stiehler, M., Bunger, C., Baatrup, A., Lind, M., Kassem, M., Mygind, T., Effect of dynamic 3-D culture on proliferation, distribution, and osteogenic differentiation of human mesenchymal stem cells (2008) J Biomed Mater Res A; Mann, V., Huber, C., Kogianni, G., Jones, D., Noble, B., The influence of mechanical stimulation on osteocyte apoptosis and bone viability in human trabecular bone (2006) J Musculoskelet Neuronal Interact, 6 (4), pp. 408-417; Bjerre, L., Bunger, C.E., Kassem, M., Mygind, T., Flow perfusion culture of human mesenchymal stem cells on silicate-substituted tricalcium phosphate scaffolds (2008) Biomaterials, 29 (17), pp. 2616-2627; Bouletreau, P.J., Warren, S.M., Spector, J.A., Peled, Z.M., Gerrets, R.P., Greenwald, J.A., Hypoxia and VEGF up-regulate BMP-2 mRNA and protein expression in microvascular endothelial cells: implications for fracture healing (2002) Plast Reconstr Surg, 109 (7), pp. 2384-2397; Simmons, C.A., Alsberg, E., Hsiong, S., Kim, W.J., Mooney, D.J., Dual growth factor delivery and controlled scaffold degradation enhance in vivo bone formation by transplanted bone marrow stromal cells (2004) Bone, 35 (2), pp. 562-569; Lu, H.H., Vo, J.M., Chin, H.S., Lin, J., Cozin, M., Tsay, R., Controlled delivery of platelet-rich plasma-derived growth factors for bone formation (2008) J Biomed Mater Res A; Yu, H., Vandevord, P.J., Gong, W., Wu, B., Song, Z., Matthew, H.W., Promotion of osteogenesis in tissue-engineered bone by pre-seeding endothelial progenitor cells-derived endothelial cells (2008) J Orthop Res, 26 (8), pp. 1147-1152; Bouhadir, K.H., Lee, K.Y., Alsberg, E., Damm, K.L., Anderson, K.W., Mooney, D.J., Degradation of partially oxidized alginate and its potential application for tissue engineering (2001) Biotechnol Prog, 17 (5), pp. 945-950
Keywords: adult; aged; Alginate; Alginates; alginic acid; alkaline phosphatase; animal tissue; Animals; arginylglycylaspartic acid; article; Bioactivity; Biopolymers; Blood vessel prostheses; Blood Vessels; Bone; Bone and Bones; bone defect; Bone defects; Bone formations; Bone marrow mesenchymal stem cells; bone mineralization; Bone Regeneration; Bone regenerations; bone tissue; Bone tissue engineerings; Calcification, Physiologic; Cell communications; Cell culture; Cell encapsulations; cell function; cell growth; Cell immobilization; Cell membranes; cell metabolism; Cells, Cultured; Co immobilizations; Co-culture; coculture; computer assisted tomography; controlled study; Defects; Dynamic conditions; Endothelial Cells; endothelium cell; gene expression; gene expression regulation; Glucuronic Acid; Grafting (chemical); Hexuronic Acids; histology; human; human cell; Human umbilical vein endothelial cells; Humans; Humulus; immobilized cell; Immobilized cells; in vitro study; in vivo study; In-vitro; In-vivo; irradiation; long bone; Long bones; Mesenchymal stem cell; Metabolic activities; Mice; Mice, Nude; microsphere; Microspheres; Middle Aged; Mineralogy; monoculture; mouse; nonhuman; osteoblast; osteocalcin; Osteogenic; Osteogenic potentials; Osteoprogenitor cells; Osteoprogenitors; Oxidation; Peptides; phenotype; Post implantations; priority journal; Self assembly; Sodium compounds; stem cell transplantation; Stem cells; Tissue engineering; umbilical vein; upregulation; Vascular endothelial growth factor (VEGF); X ray analysis; Young Adult

Engineering endochondral bone: In vitro studies - Oliveira, S.M.; Amaral, I.F.; Barbosa, M.A.; Teixeira, C.C. (Tissue Engineering - Part ATissue Eng. Part A, 2009)
Chitosan scaffolds have been shown to possess biological and mechanical properties suitable for tissue engineering and clinical applications. In the present work, chitosan sponges were evaluated regarding their ability to support cartilage cell proliferation and maturation, which are the first steps in endochondral bone formation. Chitosan sponges were seeded with chondrocytes isolated from chicken embryo sterna. Chondrocyte/chitosan constructs were cultured for 20 days, and treated with retinoic acid (RA) to induce chondrocyte maturation and matrix synthesis. At different time points, samples were collected for microscopic, histological, biochemical, and mechanical analyses. Results show chondrocyte attachment, proliferation, and abundant matrix synthesis, completely obliterating the pores of the sponges. RA treatment caused chondrocyte hypertrophy, characterized by the presence of type X collagen in the extracellular matrix and increased alkaline phosphatase activity. In addition, hypertrophy markedly changed the mechanical properties of the chondrocyte/chitosan constructs. In conclusion, we have developed chitosan sponges with adequate pore structure and mechanical properties to serve as a support for hypertrophic chondrocytes. In parallel studies, we have evaluated the ability of this mature cartilage scaffold to induce endochondral ossification. © Copyright 2009, Mary Ann Liebert, Inc. 2009.
Cited By (since 1996): 19Export Date: 21 November 2012Source: Scopusdoi: 10.1089/ten.tea.2008.0051Language of Original Document: EnglishCorrespondence Address: Teixeira, C. C.; Departments of Basic Science and Craniofacial Biology and of Orthodontics, New York University, College of Dentistry, 345 East 24th St., New York, NY 10010; email: ct40@nyu.eduChemicals/CAS: DNA, 9007-49-2; alkaline phosphatase, 9001-78-9; chitosan, 9012-76-4; retinoic acid, 302-79-4; Alkaline Phosphatase, 3.1.3.1; Chitosan, 9012-76-4; Collagen Type X; DNA, 9007-49-2; Tretinoin, 302-79-4References: Steinemann, S.G., Metal implants and surface reactions (1996) Injury, 27, p. 16;Disegi, J.A., Eschbach, L., Stainless steel in bone surgery (2000) Injury, 31, p. 2; Reitman, R.D., Emerson, R., Higgins, L., Head, W., Thirteen year results of total hip arthroplasty using a tapered titanium femoral component inserted without cement in patients with type C bone (2003) J Arthroplasty, 18, p. 116; Epinette, J.A., Manley, M.T., D'Antonio, J.A., Edidin, A.A., Capello, W.N., A 10-year minimum follow-up of hydroxyapatite-coated threaded cups: Clinical, radiographic and survivorship analyses with comparison to the literature (2003) J Arthroplasty, 18, p. 140; Xynos, I.D., Hukkanen, M.V., Batten, J.J., Buttery, L.D., Hench, L.L., Polak, J.M., Bioglass 45S5 stimulates osteoblast turnover and enhances bone formation in vitro: Implications and applications for bone tissue engineering (2000) Calcif Tissue Int, 67, p. 321; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Bioceramics, 254, p. 877; Saito, N., Takaoka, K., New synthetic biodegradable polymers as BMP carriers for bone tissue engineering (2003) Biomaterials, 24, p. 2287; Suzuki, T., Kawamura, H., Kasahara, T., Nagasaka, H., Resorbable poly-L-lactide plates and screws for the treatment of mandibular condylar process fractures: A clinical and radiologic follow-up study (2004) J Oral Maxillofac Surg, 62, p. 919; Sittinger, M., Reitzel, D., Dauner, M., Hierlemann, H., Hammer, C., Kastenbauer, E., Planck, H., Bujia, J., Resorbable polyesters in cartilage engineering: Affinity and biocompatibility of polymer fiber structures to chondrocytes (1996) J Biomed Mater Res, 33, p. 57; Vaccaro, A.R., Singh, K., Haid, R., Kitchel, S., Wuisman, P., Taylor, W., Branch, C., Garfin, S., The use of bioabsorbable implants in the spine (2003) Spine J, 3, p. 227; Jianqi, H., Hong, H., Lieping, S., Genghua, G., Comparison of calcium alginate film with collagen membrane for guided bone regeneration in mandibular defects in rabbits (2002) J Oral Maxillofac Surg, 60, p. 1449; Chan, C., Thompson, I., Robinson, P., Wilson, J., Hench, L., Evaluation of bioglass/dextran composite as a bone graft substitute (2002) Int J Oral Maxillofac Surg, 31, p. 73; Mukherjee, D.P., Tunkle, A.S., Roberts, R.A., Clavenna, A., Rogers, S., Smith, D., An animal evaluation of a paste of chitosan glutamate and hydroxyapatite as a synthetic bone graft material (2003) J Biomed Mater Res B Appl Biomater, 67 B, p. 603; Sashiwa, H., Aiba, S., Chemically modified chitin and chitosan as biomaterials (2004) Prog Polym Sci, 89, p. 887; Hoekstra, A., Struszczyk, H., Kivekas, O., Percutaneous microcrystalline chitosan application for sealing arterial puncture sites (1998) Biomaterials, 19, p. 1467; Lee, K.Y., Ha, W.S., Park, W.H., Blood compatibility and biodegradability of partially N-acylated chitosan derivatives (1995) Biomaterials, 16, p. 1211; Suh, J.K., Matthew, H.W., Application of chitosan-based polysaccharide biomaterials in cartilage tissue engineering: A review (2000) Biomaterials, 21, p. 2589; Hirano, S., Tsuchida, H., Nagao, N., N-acetylation in chitosan and the rate of its enzymic hydrolysis (1989) Biomaterials, 10, p. 574; Prashanth, K.V.H., Tharanathan, R.N., Chitin/chitosan: Modifications and their unlimited application potential-an overview (2007) Trends Food Sci Technol, 18, p. 117; Chellat, F., Tabrizian, M., Dumitriu, S., Chornet, E., Hilaire, C., Yahia, R., Study of biodegradation behavior of chitosan-xanthan microspheres in simulated physiological media (2000) J Biomed Mater Res, 53, p. 592; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., Chitosan supports the expression of extracellular matrix proteins in human osteoblasts and chondrocytes (2000) J Biomed Mater Res, 51, p. 586; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Eng, 8, p. 1009; Lu, J.X., Prudhommeaux, F., Meunier, A., Sedel, L., Guillemin, G., Effects of chitosan on rat knee cartilages (1999) Biomaterials, 20, p. 1937; Abe, M., Takahashi, M., Tokura, S., Tamura, H., Nagano, A., Cartilage-scaffold composites produced by bioresorbable beta-chitin sponge with cultured rabbit chondrocytes (2004) Tissue Eng, 10, p. 585; Sechriest, V.F., Miao, Y.J., Niyibizi, C., Westerhausen-Larson, A., Matthew, H.W., Evans, C.H., Fu, F.H., Suh, J.K., GAGaugmented polysaccharide hydrogel: A novel biocompatible and biodegradable material to support chondrogenesis (2000) J Biomed Mater Res, 49, p. 534; Rajpurohit, R., Koch, C.J., Tao, Z., Teixeira, C.M., Shapiro, I.M., Adaptation of chondrocytes to low oxygen tension: Relationship between hypoxia and cellular metabolism (1996) J Cell Physiol, 168, p. 424; Maes, C., Carmeliet, P., Moermans, K., Stockmans, I., Smets, N., Collen, D., Bouillon, R., Carmeliet, G., Impaired angiogenesis and endochondral bone formation in mice lacking the vascular endothelial growth factor isoforms VEGF164 and VEGF188 (2002) Mech Dev, 111, p. 61; Petersen, W., Tsokos, M., Pufe, T., Expression of VEGF121 and VEGF165 in hypertrophic chondrocytes of the human growth plate and epiphyseal cartilage (2002) J Anat, 201, p. 153; Pullig, O., Weseloh, G., Ronneberger, D., Kakonen, S., Swoboda, B., Chondrocyte differentiation in human osteoarthritis: Expression of osteocalcin in normal and osteoarthritic cartilage and bone (2000) Calcif Tissue Int, 67, p. 230; Hashimoto, S., Ochs, R.L., Rosen, F., Quach, J., McCabe, G., Solan, J., Seegmiller, J.E., Lotz, M., Chondrocyte-derived apoptotic bodies and calcification of articular cartilage (1998) Proc Natl Acad Sci USA, 95, p. 3094; Pullig, O., Weseloh, G., Gauer, S., Swoboda, B., Osteopontin is expressed by adult human osteoarthritic chondrocytes: Protein andmRNAanalysis of normal and osteoarthritic cartilage (2000) Matrix Biol, 19, p. 245; Eerola, I., Salminen, H., Lammi, P., Lammi, M., von der Mark, K., Vuorio, E., Saamanen, A.M., Type X collagen, a natural component of mouse articular cartilage: Association with growth, aging, and osteoarthritis (1998) Arthritis Rheum, 41, p. 1287; Amaral, I.F., Sampaio, P., Barbosa, M.A., Threedimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation (2006) J Biomed Mater Res A, 76, p. 335; Mow, V.C., Kuei, S.C., Lai, W.M., Armstrong, C.G., Biphasic creep and stress relaxation of articular cartilage in compression? Theory and experiments (1980) J Biomech Eng, 102, p. 73; Iwamoto, M., Shapiro, I.M., Yagami, K., Boskey, A.L., Leboy, P.S., Adams, S.L., Pacifici, M., Retinoic acid induces rapid mineralization and expression of mineralizationrelated genes in chondrocytes (1993) Exp Cell Res, 207, p. 413; Teixeira, C.C., Hatori, M., Leboy, P.S., Pacifici, M., Shapiro, I.M., A rapid and ultrasensitive method for measurement of DNA, calcium and protein content, and alkaline phosphatase activity of chondrocyte cultures (1995) Calcif Tissue Int, 56, p. 252; Nehrer, S., Breinan, H.A., Ramappa, A., Young, G., Shortkroff, S., Louie, L.K., Sledge, C.B., Spector, M., Matrix collagen type and pore size influence behaviour of seeded canine chondrocytes (1997) Biomaterials, 18, p. 769; Karande, T.S., Ong, J.L., Agrawal, C.M., Diffusion in musculoskeletal tissue engineering scaffolds: Design issues related to porosity, permeability, architecture, and nutrient mixing (2004) Ann Biomed Eng, 32, p. 1728; VandeVord, P.J., Matthew, H.W., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J Biomed Mater Res, 59, p. 585; Hong, Y., Song, H., Gong, Y., Mao, Z., Gao, C., Shen, J., Covalently crosslinked chitosan hydrogel: Properties of in vitro degradation and chondrocyte encapsulation (2007) Acta Biomater, 3, p. 23; Ho, M., Wang, D., Hsieh, H., Liu, H.C., Hsien, T.Y., Lai, J.Y., Hou, L.T., Preparation and characterization of RGDimmobilized chitosan scaffolds (2005) Biomaterials, 26, p. 3197; Amaral, I.F., Cordeiro, A.L., Sampaio, P., Barbosa, M.A., Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation (2007) J Biomater Sci Polym Ed, 18, p. 469; Hoemann, C.D., Sun, J., Legare, A., McKee, M.D., Buschmann, M.D., Tissue engineering of cartilage using an injectable and adhesive chitosan-based cell-delivery vehicle (2005) Osteoarthritis Cartilage, 13, p. 318; Griffon, D.J., Sedighi, M.R., Schaeffer, D.V., Eurell, J.A., Johnson, A.L., Chitosan scaffolds: Interconnective pore size and cartilage engineering (2006) Acta Biomater, 2, p. 313; Underhill, T.M., Weston, A.D., Retinoids and their receptors in skeletal development (1998) Microsc Res Tech, 43, p. 137; Cohen, A.J., Lassova, L., Golden, E.B., Niu, Z., Adams, S.L., Retinoids directly activate the collagen X promoter in prehypertrophic chondrocytes through a distal retinoic acid response element (2006) J Cell Biochem, 99, p. 269; Pacifici, M., Golden, E.B., Iwamoto, M., Adams, S.L., Retinoic acid treatment induces type X collagen gene expression in cultured chick chondrocytes (1991) Exp Cell Res, 195, p. 38; Gentili, C., Bianco, P., Neri, M., Malpeli, M., Campanile, G., Castagnola, P., Cancedda, R., Cancedda, F.D., Cellproliferation, extracellular-matrix mineralization, and ovotransferrin transient expression during in-vitro differentiation of chick hypertrophic chondrocytes into osteoblast-like cells (1993) J Cell Biol, 122, p. 703; Naumann, A., Dennis, J.E., Awadallah, A., Carrino, D.A., Mansour, J.M., Kastenbauer, E., Caplan, A.I., Immunochemical and mechanical characterization of cartilage subtypes in rabbit (2002) J Histochem Cytochem, 50, p. 1049; Wang, W., Kirsch, T., Retinoic acid stimulates annexinmediated growth plate chondrocyte mineralization (2002) J Cell Biol, 157, p. 1061; Whyte, M.P., Hypophosphatasia and the role of alkaline phosphatase in skeletal mineralization (1994) Endocr Rev, 15, p. 439; Lewinson, D., Toister, Z., Silbermann, M., Quantitative and distributional changes in the activity of alkaline phosphatase during the maturation of cartilage (1982) J Histochem Cytochem, 30, p. 261; Amaral, I.F., Sampaio, P., Barbosa, M.A., Threedimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation (2005) J Biomed Mater Res A, 76, p. 335; Park, J.H., Park, B.H., Kim, H.K., Park, T.S., Baek, H.S., Hypoxia decreases Runx2/Cbfa1 expression in human osteoblast-like cells (2002) Mol Cell Endocrinol, 192, p. 197; Utting, J.C., Robins, S.P., Brandao-Burch, A., Orriss, I.R., Behar, J., Arnett, T.R., Hypoxia inhibits the growth, differentiation and bone-forming capacity of rat osteoblasts (2006) Exp Cell Res, 312, p. 1693; Warren, S.M., Steinbrech, D.S., Mehrara, B.J., Saadeh, P.B., Greenwald, J.A., Spector, J.A., Bouletreau, P.J., Longaker, M.T., Hypoxia regulates osteoblast gene expression (2001) J Surg Res, 99, p. 147; Salim, A., Nacamuli, R.P., Morgan, E.F., Giaccia, A.J., Longaker, M.T., Transient changes in oxygen tension inhibit osteogenic differentiation and Runx2 expression in osteoblasts (2004) J Biol Chem, 279, p. 40007; Vu, T.H., Shipley, J.M., Bergers, G., Berger, J.E., Helms, J.A., Hanahan, D., Shapiro, S.D., Werb, Z., MMP-9/gelatinase B is a key regulator of growth plate angiogenesis and apoptosis of hypertrophic chondrocytes (1998) Cell, 93, p. 411; Skawina, A., Litwin, J.A., Gorczyca, J., Miodonski, A.J., The vascular system of human fetal long bones: A scanning electron microscope study of corrosion casts (1994) J Anat, 185, p. 369; Pfander, D., Cramer, T., Schipani, E., Johnson, R.S., HIF-1alpha controls extracellular matrix synthesis by epiphyseal chondrocytes (2003) J Cell Sci, 116, p. 1819; Deckers, M.M., Karperien, M., van der Bent, C., Yamashita, T., Papapoulos, S.E., Lowik, C.W., Expression of vascular endothelial growth factors and their receptors during osteoblast differentiation (2000) Endocrinology, 141, p. 1667; Gerber, H.P., Vu, T.H., Ryan, A.M., Kowalski, J., Werb, Z., Ferrara, N., VEGF couples hypertrophic cartilage remodeling, ossification and angiogenesis during endochondral bone formation (1999) Nat Med, 5, p. 623; Nakagawa, M., Kaneda, T., Arakawa, T., Morita, S., Sato, T., Yomada, T., Hanada, K., Hakeda, Y., Vascular endothelial growth factor (VEGF) directly enhances osteoclastic bone resorption and survival of mature osteoclasts (2000) FEBS Lett, 473, p. 161; Pfander, D., Kortje, D., Zimmermann, R., Weseloh, G., Kirsch, T., Gesslein, M., Cramer, T., Swoboda, B., Vascular endothelial growth factor in articular cartilage of healthy and osteoarthritic human knee joints (2001) Ann RheumDis, 60, p. 1070; Oliveira, S.M., Turner, G., Mijares, D., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., (2007) Engineering endochondral bone: In vivo studies
Keywords: alkaline phosphatase; Alkaline phosphatase activity; animal; animal cell; animal tissue; Animals; article; biomechanics; Body fluids; Bone; Bone and Bones; Bone formation; Cartilage; cartilage cell; Cell culture; cell damage; cell hypertrophy; cell isolation; cell maturation; Cell membranes; cell proliferation; Cells, Cultured; chick embryo; Chicken embryo; Chitin; chitosan; Chitosan scaffold; Chondrocyte; Chondrocyte maturation; Chondrocytes; Clinical application; collagen type 10; Collagen Type X; controlled study; cytology; DNA; drug effect; embryo; enchondral ossification; Endochondral ossification; enzyme activity; enzymology; Extracellular matrices; extracellular matrix; gene expression profiling; Hypertrophic chondrocytes; in vitro study; In-vitro; Ligaments; Matrix synthesis; Mechanical analysis; Mechanical properties; metabolism; methodology; nonhuman; Pathology; physiology; Porifera; porosity; priority journal; retinoic acid; Retinoic acids; Scaffolds; sponge (Porifera); Sterna; sternum; synthesis; Time points; Tissue engineering; tissue scaffold; Tissue Scaffolds; Tretinoin; Type X collagen

Engineering endochondral bone: In vivo studies - Oliveira, S.M.; Mijares, D.Q.; Turner, G.; Amaral, I.F.; Barbosa, M.A.; Teixeira, C.C. (Tissue Engineering - Part ATissue Eng. Part A, 2009)
The use of biomaterials to replace lost bone has been a common practice for decades. More recently, the demands for bone repair and regeneration have pushed research into the use of cultured cells and growth factors in association with these materials. Here we report a novel approach to engineer new bone using a transient cartilage scaffold to induce endochondral ossification. Chondrocyte/chitosan scaffolds (both a transient cartilage scaffold- experimental-and a permanent cartilage scaffold-control) were prepared and implanted subcutaneously in nude mice. Bone formation was evaluated over a period of 5 months. Mineralization was assessed by Faxitron, micro computed tomography, backscatter electrons, and Fourier transform infrared spectroscopy analyses. Histological analysis provided further information on tissue changes in and around the implanted scaffolds. The deposition of ectopic bone was detected in the surface of the experimental implants as early as 1 month after implantation. After 3 months, bone trabeculae and bone marrow cavities were formed inside the scaffolds. The bone deposited was similar to the bone of the mice vertebra. Interestingly, no bone formation was observed in control implants. In conclusion, an engineered transient cartilage template carries all the signals necessary to induce endochondral bone formation in vivo. © Copyright 2009, Mary Ann Liebert, Inc. 2009.
Cited By (since 1996): 14Export Date: 21 November 2012Source: Scopusdoi: 10.1089/ten.tea.2008.0052Language of Original Document: EnglishCorrespondence Address: Teixeira, C. C.; Department of Basic Science and Craniofacial Biology, College of Dentistry, New York University, 345 East. 24th St., New York, NY 10010; email: ct40@nyu.eduChemicals/CAS: chitosan, 9012-76-4; Chitosan, 9012-76-4; MineralsReferences: Yelin, E., Callahan, L.F., The economic cost and social and psychological impact of musculoskeletal conditions. National Arthritis Data Work Groups (1995) Arthritis Rheum, 38, p. 1351;Service, R.F. Tissue engineers build new bone. Science 289,1498, 2000Dupraz, A., Delecrin, J., Moreau, A., Pilet, P., Passuti, N., Long-term bone response to particulate injectable ceramic (1998) J Biomed Mater Res, 42, p. 368; Gauthier, O., Khairoun, I., Bosco, J., Obadia, L., Bourges, X., Rau, C., Magne, D., Daculsi, G., Noninvasive bone replacement with a new injectable calcium phosphate biomaterial (2003) J Biomed Mater Res, 66 A, p. 47; Maroudas, A., Bayliss, M.T., Uchitel-Kaushansky, N., Schneiderman, R., Gilav, E., Aggrecan turnover in human articular cartilage: Use of aspartic acid racemization as a marker of molecular age (1998) Arch Biochem Biophys, 350, p. 61; Ferguson, C., Alpern, E., Miclau, T., Helms, J.A., Does adult fracture repair recapitulate embryonic skeletal formation? (1999) Mech Dev, 87, p. 57; Iwamoto, M., Higuchi, Y., Enomoto-Iwamoto, M., Kurisu, K., Koyama, E., Yeh, H., Rosenbloom, J., Pacifici, M., The role of ERG (ets related gene) in cartilage development (2001) Osteoarthr Cartil, 9 (SUPPL. A), pp. S41; Montufar-Solis, D., Nguyen, H.C., Nguyen, H.D., Horn, W.N., Cody, D.D., Duke, P.J., Using cartilage to repair bone: An alternative approach in tissue engineering (2004) Ann Biomed Eng, 32, p. 504; Pountos, I., Jones, E., Tzioupis, C., McGonagle, D., Giannoudis, P.V., Growing bone and cartilage: The role of mesenchymal stem cells (2006) J Bone Joint Surg Br, 88, p. 421; Valimaki, V.V., Yrjans, J.J., Vuorio, E.I., Aro, H.T., Molecular biological evaluation of bioactive glass microspheres and adjunct bone morphogenetic protein 2 gene transfer in the enhancement of new bone formation (2005) Tissue Eng, 11, p. 387; Huang, Y.C., Simmons, C., Kaigler, D., Rice, K.G., Mooney, D.J., Bone regeneration in a rat cranial defect with delivery of PEI-condensed plasmid DNA encoding for bone morphogenetic protein-4 (BMP-4) (2005) Gene Ther, 12, p. 418; Bikram, M., Fouletier-Dilling, C., Hipp, J.A., Gannon, F., Davis, A.R., Olmsted-Davis, E.A., West, J.L., Endochondral bone formation from hydrogel carriers loaded with BMP2-transduced cells (2007) Ann Biomed Eng, 35, p. 796; Alsberg, E., Anderson, K.W., Albeiruti, A., Rowley, J.A., Mooney, D.J., Engineering growing tissues (2002) Proc Natl Acad Sci USA, 99, p. 12025; Deckers, M.M., Karperien, M., van der Bent, C., Yamashita, T., Papapoulos, S.E., Lowik, C.W., Expression of vascular endothelial growth factors and their receptors during osteoblast differentiation (2000) Endocrinology, 141, p. 1667; Petersen, W., Tsokos, M., Pufe, T., Expression of VEGF121 and VEGF165 in hypertrophic chondrocytes of the human growth plate and epiphyseal cartilage (2002) J Anat, 201, p. 153; Nakagawa, M., Kaneda, T., Arakawa, T., Morita, S., Sato, T., Yomada, T., Hanada, K., Hakeda, Y., Vascular endothelial growth factor (VEGF) directly enhances osteoclastic bone resorption and survival of mature osteoclasts (2000) FEBS Lett, 473, p. 161; Gerber, H.P., Vu, T.H., Ryan, A.M., Kowalski, J., Werb, Z., Ferrara, N., VEGF couples hypertrophic cartilage remodeling, ossification and angiogenesis during endochondral bone formation (1999) Nat Med, 5, p. 623; Oliveira, S.M., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., (2007) Engineering endochondral bone: In vitro studies; Hasegawa, S., Ishii, S., Tamura, J., Furukawa, T., Neo, M., Matsusue, Y., Shikinami, Y., Nakamura, T., A 5-7 year in vivo study of high-strength hydroxyapatite/ poly(L-lactide) composite rods for the internal fixation of bone fractures (2006) Biomaterials, 27, p. 1327; Gauthier, O., Muller, R., von Stechow, D., Lamy, B., Weiss, P., Bouler, J.M., Aguado, E., Daculsi, G., In vivo bone regeneration with injectable calcium phosphate biomaterial: A three-dimensional micro-computed tomographic, biomechanical and SEM study (2005) Biomaterials, 26, p. 5444; Chan, C., Thompson, I., Robinson, P., Wilson, J., Hench, L., Evaluation of Bioglass/dextran composite as a bone graft substitute (2002) Int J Oral Maxillofac Surg, 31, p. 73; Trojani, C., Boukhechba, F., Scimeca, J.C., Vandenbos, F., Michiels, J.F., Daculsi, G., Boileau, P., Rochet, N., Ectopic bone formation using an injectable biphasic calcium phosphate/Si-HPMC hydrogel composite loaded with undifferentiated bone marrow stromal cells (2006) Biomaterials, 27, p. 3256; van Gaalen, S.M., Dhert, W.J.A., van den Muysenberg, A., Oner, F.C., van Blitterswijk, C., Verbout, A.J., de Bruijn, J.D., Bone tissue engineering for spine fusion: An experimental study on ectopic and orthotopic implants in rats (2004) Tissue Eng, 10, p. 231; Kim, H., Suh, H., Jo, S.A., Kim, H.W., Lee, J.M., Kim, E.H., Reinwald, Y., Jo, I., In vivo bone formation by human marrow stromal cells in biodegradable scaffolds that release dexamethasone and ascorbate-2-phosphate (2005) Biochem Biophys Res Commun, 332, p. 1053; Krebsbach, P.H., Kuznetsov, S.A., Satomura, K., Emmons, R.V.B., Rowe, D.W., Robey, P.G., Bone formation in vivo: Comparison of osteogenesis by transplanted mouse and human marrow stromal fibroblasts (1997) Transplantation, 63, p. 1059; Musgrave, D.S., Bosch, P., Lee, J.Y., Pelinkovic, D., Ghivizzani, S.C., Whalen, J., Niyibizi, C., Huard, J., Ex vivogene therapy to produce bone using different cell types (2000) Clin Orthop Relat Res, 378, p. 290; Kojima, K., Bonassar, L.J., Ignotz, R.A., Syed, K., Cortiella, J., Vacanti, C.A., Comparison of tracheal and nasal chondrocytes for tissue engineering of the trachea (2003) Ann Thorac Surg, 76, p. 1884; van Susante, J.L., Buma, P., Homminga, G.N., van den Berg, W.B., Veth, R.P., Chondrocyte-seeded hydroxyapatite for repair of large articular cartilage defects: A pilot study in the goat (1998) Biomaterials, 19, p. 2367; Lu, J.X., Prudhommeaux, F., Meunier, A., Sedel, L., Guillemin, G., Effects of chitosan on rat knee cartilages (1999) Biomaterials, 20, p. 1937; Dorotka, R., Windberger, U., Macfelda, K., Bindreiter, U., Toma, C., Nehrer, S., Repair of articular cartilage defects treated by microfracture and a three-dimensional collagen matrix (2005) Biomaterials, 26, p. 3617; Marijnissen, W.J.C.M., van Osch, G.J.V.M., Aigner, J., Verwoerd-Verhoef, H.L., Verhaar, J.A.N., Tissueengineered cartilage using serially passaged articular chondrocytes. Chondrocytes in alginate, combined in vivo with a synthetic (E210) or biologic biodegradable carrier (DBM) (2000) Biomaterials, 21, p. 571; Case, N.D., Duty, A.O., Ratcliffe, A., Muller, R., Guldberg, R.E., Bone formation on tissue-engineered cartilage constructs in vivo: Effects of chondrocyte viability and mechanical loading (2003) Tissue Eng, 9, p. 587; Cancedda, R., Cancedda, F.D., Castagnola, P., Chondrocyte differentiation (1995) Int Rev Cytol, 159, p. 265; Hunziker, E.B., Mechanism of longitudinal bone-growth and its regulation by growth-plate chondrocytes (1994) Microsc Res Tech, 28, p. 505; Kirsch, T., Nah, H.D., Shapiro, I.M., Pacifici, M., Regulated production of mineralization-competent matrix vesicles in hypertrophic chondrocytes (1997) J Cell Biol, 137, p. 1149; Anderson, H.C., Molecular-biology of matrix vesicles (1995) Clin Orthop Relat Res, 314, p. 266; Yaylaoglu, M.B., Yildiz, C., Korkusuz, F., Hasirci, V., A novel osteochondral implant (1999) Biomaterials, 20, p. 1513; Garimella, R., Bi, X.H., Camacho, N., Sipe, J.B., Anderson, H.C., Primary culture of rat growth plate chondrocytes: An in vitro model of growth plate histotype, matrix vesicle biogenesis and mineralization (2004) Bone, 34, p. 961; Boskey, A., Camacho, N.P., FT-IR imaging of native and tissue-engineered bone and cartilage (2007) Biomaterials, 28, p. 2465; Jikko, A., Aoba, T., Murakami, H., Takano, Y., Iwamoto, M., Kato, Y., Characterization of the mineralization process in cultures of rabbit growth plate chondrocytes (1993) Dev Biol, 156, p. 372; Cadet, E.R., Gafni, R.I., McCarthy, E.F., McCray, D.R., Bacher, J.D., Barnes, K.M., Baron, J., Mechanisms responsible for longitudinal growth of the cortex: Coalescence of trabecular bone into cortical bone (2003) J Bone Joint Surg Am, 85 A, p. 1739; Lee, C., Grad, S., Wimmer, M., Alini, M., The influence of mechanical stimuli on articular cartilage tissue engineering (2006) Cartilage Tissue Eng, 2, p. 1; Trepczik, B., Lienau, J., Schell, H., Epari, D.R., Thompson, M.S., Hoffmann, J.E., Kadow-Romacker, A., Duda, G.N., Endochondral ossification in vitro is influenced by mechanical bending (2007) Bone, 40, p. 597; Tanck, E., Hannink, G., Ruimerman, R., Buma, P., Burger, E.H., Huiskes, R., Cortical bone development under the growth plate is regulated by mechanical load transfer (2006) J Anat, 208, p. 73; Dong, J., Uemura, T., Kojima, H., Kikuchi, M., Tanaka, J., Tateishi, T., Application of low-pressure system to sustain in vivo bone formation in osteoblast/porous hydroxyapatite composite (2001) DNLM, 17, p. 37; Stevens, M., Marini, R., Schaefer, D., Aronson, J., Langer, R., Shastri, V., In vivo engineering of organs: The bone bioreactor (2005) Proc Natl Acad Sci USA, 102, p. 11450; Rinaudo, M., Chitin and chitosan: Properties and applications (2006) Prog Polym Sci, 31, p. 603
Keywords: animal; animal experiment; animal tissue; Animals; article; Biological materials; Biomaterials; Bone; Bone and Bones; Bone formation; bone marrow; bone mineralization; Bone repair; bone transplantation; Calcification, Physiologic; Cartilage; cartilage cell; chick embryo; chitosan; Chondrocytes; Computerized tomography; controlled study; Cultured cell; cytology; drug effect; Ectopic bones; ectopic tissue; electron; enchondral ossification; Endochondral ossification; Fourier transform infrared spectroscopy; Growth (materials); Growth factor; Histological analysis; histology; implantation; in vivo study; In-control; In-vivo; infrared spectroscopy; Ligaments; male; metabolism; methodology; Mice; Mice, Nude; micro-computed tomography; Microcomputed tomography; Microscopy, Electron, Scanning; mineral; Minerals; mouse; Mus; Mus musculus; nonhuman; Nude mice; nude mouse; ossification; physiology; priority journal; Prosthesis Implantation; Scaffolds; Scanning electron microscopy; Spectroscopic analysis; Spectroscopy; Spectroscopy, Fourier Transform Infrared; Tissue changes; Tissue engineering; tissue scaffold; Tissue Scaffolds; Tomography; trabecular bone; vertebra

Fibronectin-mediated endothelialisation of chitosan porous matrices - Amaral, I.F.; Unger, R.E.; Fuchs, S.; Mendonça, A.M.; Sousa, S.R.; Barbosa, M.A.; Pêgo, A.P.; Kirkpatrick, C.J. (BiomaterialsBiomaterials, 2009)
Chitosan (Ch) porous matrices were investigated regarding their ability to be colonized by human microvascular endothelial cells (HPMEC-ST1.6R cell line) and macrovascular endothelial cells namely HUVECs. Specifically we assessed if previous incubation of Ch in a fibronectin (FN) solution was effective in promoting endothelial cell (EC) adhesion to Ch matrices with different degrees of acetylation (DAs). Upon FN physiadsorption, marked differences were found between the two DAs investigated, namely DA 4% and 15%. While cell adhesion was impaired on Ch with DA 15%, ECs were able to not only adhere to Ch with DA 4%, but also to spread and colonize the scaffolds, with retention of the EC phenotype and angiogenic potential. To explain the observed differences between the two DAs, protein adsorption studies using 125I-FN and immunofluorescent labelling of FN cell-binding domains were carried out. In agreement with the higher cell numbers found, scaffolds with DA 4% revealed a higher number of exposed FN cell-binding domains as well as greater ability to adsorb FN and to retain and exchange adsorbed FN in the presence of competitive proteins. These findings suggest that the DA is a key parameter modulating EC adhesion to FN-coated Ch by influencing the adsorbed protein layer. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.06.056PubMed ID: 19615736Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; fibronectin, 86088-83-7; Biocompatible Materials; Chitosan, 9012-76-4; FibronectinsReferences: Moon, J.J., West, J.L., Vascularization of engineered tissues: approaches to promote angiogenesis in biomaterials (2008) Current Topics in Medicinal Chemistry, 8 (4), pp. 300-310;Blitterswijk, C.A., Moroni, L., Rouwkema, J., Siddappa, R., Sohier, J., Tissue engineering - an introduction (2008) Tissue engineering, , Blitterswijk C.A. (Ed), Elsevier; Ehrbar, M., Zeisberger, S.M., Raeber, G.P., Hubbell, J.A., Schnell, C., Zisch, A.H., The role of actively released fibrin-conjugated VEGF for VEGF receptor 2 gene activation and the enhancement of angiogenesis (2008) Biomaterials, 29 (11), pp. 1720-1729; Elbjeirami, W.M., West, J.L., Angiogenesis-like activity of endothelial cells co-cultured with VEGF-producing smooth muscle cells (2006) Tissue Engineering, 12 (2), pp. 381-390; Unger, R.E., Peters, K., Wolf, M., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Endothelialization of a non-woven silk fibroin net for use in tissue engineering: growth and gene regulation of hunian endothelial cells (2004) Biomaterials, 25 (21), pp. 5137-5146; Fuchs, S., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Outgrowth endothelial cells isolated and expanded from human peripheral blood progenitor cells as a potential source of autologous cells for endothelialization of silk fibroin biomaterials (2006) Biomaterials, 27 (31), pp. 5399-5408; Kirkpatrick, C.J., Unger, R.E., Krump-Konvalinkova, V., Peters, K., Schmidt, H., Kamp, G., Experimental approaches to study vascularization in tissue engineering and biomaterial applications (2003) Journal of Materials Science, 14 (8), pp. 677-681; Calonder, C., Matthew, H.W.T., Van Tassel, P.R., Adsorbed layers of oriented fibronectin: a strategy to control cell-surface interactions (2005) Journal of Biomedical Materials Research Part A, 75 A (2), pp. 316-323; Kouvroukoglou, S., Dee, K.C., Bizios, R., McIntire, L.V., Zygourakis, K., Endothelial cell migration on surfaces modified with immobilized adhesive peptides (2000) Biomaterials, 21 (17), pp. 1725-1733; Burdick, J.A., Khademhosseini, A., Langer, R., Fabrication of gradient hydrogels using a microfluidics/photopolymerization process (2004) Langmuir, 20 (13), pp. 5153-5156; Garcia, A.J., Get a grip: integrins in cell-biomaterial interactions (2005) Biomaterials, 26, pp. 7525-7529; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18 (7), pp. 567-575; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cells osteogenic differentiation and fibronectin adsorption on chitosan membranes: the effect of the degree of acetylation (2005) Journal of Biomedical Materials Research Part A, 75 A (2), pp. 387-397; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Engineering, 8 (6), pp. 1009-1016; Oliveira, S.M., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: in vitro studies (2009) Tissue Engineering, 15 (3), pp. 625-634; Freier, T., Koh, H.S., Kazazian, K., Shoichet, M.S., Controlling cell adhesion and degradation of chitosan films by N-acetylation (2005) Biomaterials, 26 (29), pp. 5872-5878; Wang, X.H., Cui, F.Z., Feng, Q.L., Li, J.C., Zhang, Y.H., Preparation and characterization of collagen/chitosan matrices as potential biomaterials (2003) Journal of Bioactive and Compatible Polymers, 18 (6), pp. 453-467; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., Vascular cell responses to polysaccharide materials: in vitro and in vivo evaluations (2000) Biomaterials, 21 (22), pp. 2315-2322; Chung, T.W., Lu, Y.F., Wang, S.S., Lin, Y.S., Chu, S.H., Growth of human endothelial cells on photochemically grafted Gly-Arg-Gly-Asp (GRGD) chitosans (2002) Biomaterials, 23 (24), pp. 4803-4809; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., Adhesive protein interactions with chitosan: consequences for valve endothelial cell growth on tissue-engineering materials (2003) Journal of Biomedical Materials Research Part A, 67 A (2), pp. 538-547; Huang, Y., Onyeri, S., Siewe, M., Moshfeghian, A., Madihally, S.V., In vitro characterization of chitosan-gelatin scaffolds for tissue engineering (2005) Biomaterials, 26 (36), pp. 7616-7627; Huang, Y., Siewe, M., Madilhally, S.V., Effect of spatial architecture on cellular colonization (2006) Biotechnology and Bioengineering, 93 (1), pp. 64-75; Kirsebom, H., Aguilar, M.R., Roman, J.S., Fernandez, M., Prieto, M.A., Bondar, B., Macroporous scaffolds based on chitosan and bioactive molecules (2007) Journal of Bioactive and Compatible Polymers, 22 (6), pp. 621-636; Cao, W.L., Jing, D.H., Li, J.M., Gong, Y.D., Zhao, N.M., Zhang, X.F., Effects of the degree of deacetylation on the physicochemical properties and Schwann cell affinity of chitosan films (2005) Journal of Biomaterials Applications, 20 (2), pp. 157-177; Amaral, I.F., Sampaio, P., Barbosa, M.A., Three-dimensional culture of human osteoblastic cells in chitosan sponges: the effect of the degree of acetylation (2006) Journal of Biomedical Materials Research Part A, 76 A (2), pp. 335-346; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42 (8), pp. 3569-3580; Vachoud, L., Zydowicz, N., Domard, A., Formation and characterisation of a physical chitin gel (1997) Carbohydrate Research, 302 (3-4), pp. 169-177; Montembault, A., Viton, C., Domard, A., Physico-chemical studies of the gelation of chitosan in a hydroalcoholic medium (2005) Biomaterials, 26 (8), pp. 933-943; Amaral, I.F., Cordeiro, A.L., Sampaio, P., Barbosa, M.A., Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation (2007) Journal of Biomaterials Science Polymer Edition, 18 (4), pp. 469-485; Krump-Konvalinkova, V., Bittinger, F., Unger, R.E., Peters, K., Lehr, H.A., Kirkpatrick, C.J., Generation of human pulmonary microvascular endothelial cell lines (2001) Laboratory Investigation, 81 (12), pp. 1717-1727; Unger, R.E., Krump-Konvalinkova, V., Peters, K., Kirkpatrick, C.J., In vitro expression of the endothelial phenotype: comparative study of primary isolated cells and cell lines, including the novel cell line HPMEC-ST1.6R (2002) Microvascular Research, 64 (3), pp. 384-397; Jaffe, E.A., Nachman, R.L., Becker, C.G., Minick, C.R., Culture of human endothelial cells derived from umbilical veins. Identification by morphologic and immunologic criteria (1973) J Clin Invest, 52 (11), pp. 2745-2756; O'Brien, J., Wilson, I., Orton, T., Pognan, F., Investigation of the Alamar blue (resazurin) fluorescent dye for the assessment of mammalian cell cytotoxicity (2000) European Journal of Biochemistry, 267 (17), pp. 5421-5426; Teixeira, C.C., Hatori, M., Leboy, P.S., Pacifici, M., Shapiro, I.M., A rapid and ultrasensitive method for measurement of DNA, calcium and protein-content, and alkaline-phosphatase activity of chondrocyte cultures (1995) Calcified Tissue International, 56 (3), pp. 252-256; Barbosa, J.N., Amaral, I.F., Águas, A.P., Barbosa, M.A., Evaluation of the effect of the degree of acetylation on the inflammatory response to 3D porous chitosan scaffolds Journal of Biomedical Materials Research Part A, , in press, doi:10.1002/jbm.a.32499; Marshall, A.J., Barker, T., Sage, E.H., Hauch, K.D., Ratner, B.D., (2004) Pore size controls angiogenesis in subcutaneously implanted porous matrices. 7th World Biomaterials Congress; 2004, , Australian Society for Biomaterials Inc., Sydney, Australia p. 710; Unger, R.E., Sartoris, A., Peters, K., Motta, A., Migliaresi, C., Kunkel, M., Tissue-like self-assembly in cocultures of endothelial cells and osteoblasts and the formation of microcapillary-like structures on three-dimensional porous biomaterials (2007) Biomaterials, 28 (27), pp. 3965-3976; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13 (13), pp. 3404-3413; Wendt, D., Marsano, A., Jakob, M., Heberer, M., Martin, I., Oscillating perfusion of cell suspensions through three-dimensional scaffolds enhances cell seeding efficiency and uniformity (2003) Biotechnology and Bioengineering, 84 (2), pp. 205-214; Santos, M.I., Fuchs, S., Gomes, M.E., Unger, R.E., Reis, R.L., Kirkpatrick, C.J., Response of micro- and macrovascular endothelial cells to starch-based fiber meshes for bone tissue engineering (2007) Biomaterials, 28 (2), pp. 240-248; Vestweber, D., Molecular mechanisms that control endothelial cell contacts (2000) Journal of Pathology, 190 (3), pp. 281-291; Mori, T., Irie, Y., Nishimura, S., Tokura, S., Matsuura, M., Okumura, M., Endothelial cell responses to chitin and its derivatives (1998) Journal of Biomedical Materials Research, 43 (4), pp. 469-472; Panetti, T.S., Hannah, D.F., Avraamides, C., Gaughan, J.P., Marcinkiewicz, Z., Huttenlocher, A., Extracellular matrix molecules regulate endothelial cell migration stimulated by lysophosphatidic acid (2004) Journal of Thrombosis and Haemostasis, 2 (9), pp. 1645-1656; Garcia, A.J., Boettiger, D., Integrin-fibronectin interactions at the cell-material interface: initial integrin binding and signaling (1999) Biomaterials, 20 (23-24), pp. 2427-2433; Danen, E.H.J., Sonnenberg, A., Integrins in regulation of tissue development and function (2003) Journal of Pathology, 200 (4), pp. 471-480; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) Journal of Biomedical Materials Research Part A, 66 A (2), pp. 247-259; Renner, L., Jorgensen, B., Markowski, M., Salchert, K., Werner, C., Pompe, T., Control of fibronectin displacement on polymer substrates to influence endothelial cell behaviour (2004) Journal of Materials Science-Materials in Medicine, 15 (4), pp. 387-390; Garcia, A.J., Vega, M.D., Boettiger, D., Modulation of cell proliferation and differentiation through substrate-dependent changes in fibronectin conformation (1999) Molecular Biology of the Cell, 10 (3), pp. 785-798; Koenig, A.L., Gambillara, V., Grainger, D.W., Correlating fibronectin adsorption with endothelial cell adhesion and signaling on polymer substrates (2003) Journal of Biomedical Materials Research Part A, 64 A (1), pp. 20-37; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates focal adhesion composition and signaling through changes in integrin binding (2004) Biomaterials, 25, pp. 5947-5954; Pompe, T., Kobe, F., Salchert, K., Jorgensen, B., Oswald, J., Werner, C., Fibronectin anchorage to polymer substrates controls the initial phase of endothelial cell adhesion (2003) Journal of Biomedical Materials Research Part A, 67 A (2), pp. 647-657
Keywords: Acetylation; Adhesion; Adsorption; angiogenesis; article; Biocompatible Materials; Blood vessel prostheses; cell adhesion; Cell culture; cell invasion; Cell Line; Cell lines; Cell membranes; Cell number; cell proliferation; Cell size; cell spreading; cell survival; Cell-binding domain; Chitin; Chitin/chitosan; chitosan; colony formation; controlled study; Degrees of acetylation; Electric conductivity measurement; Electric currents; Endothelial cell; Endothelial Cells; Endothelialisation; endothelium; endothelium cell; epithelization; Fibronectin; Fibronectins; human; human cell; Human microvascular endothelial cells; Humans; immunofluorescence test; Key parameters; Labels; materials testing; Matrix algebra; Neovascularization, Physiologic; phenotype; porosity; Porous matrixs; priority journal; Protein adsorption; Protein layers; Scaffold; Scaffolds; Self assembly; Tissue engineering; tissue scaffold; umbilical vein

Improving chitosan-mediated gene transfer by the introduction of intracellular buffering moieties into the chitosan backbone - Moreira, C.; Oliveira, H.; Pires, L.R.; Simões, S.; Barbosa, M.A.; Pêgo, A.P. (Acta BiomaterialiaActa Biomater., 2009)
Chitosan was functionalized with imidazole moieties (CHimi) with the aim of improving its buffering capacity and promoting the endosomal escape ability of chitosan-DNA complexes, ultimately increasing their transfection efficiency. 5.6%, 12.9% and 22.1% of the glucosamine residues of chitosan were substituted. Complexes with different molar ratios of primary amines to DNA phosphate anion (N/P) were prepared by a coacervation method. For an N/P > 3, CHimi polymers are able to complex electrostatically with DNA and condense it into positively charged nanostructures (average size 260 nm and zeta potential +16 mV at pH 5.5). In the concentration range 2.5-100 μg ml
Cited By (since 1996): 17Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2009.04.021PubMed ID: 19427930Language of Original Document: EnglishCorrespondence Address: Pêgo, A.P.; INEB-Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: apego@ineb.up.ptChemicals/CAS: DNA, 9007-49-2; chitosan, 9012-76-4; imidazole, 1467-16-9, 288-32-4; Biocompatible Materials; Buffers; Chitosan, 9012-76-4; DNA, 9007-49-2; Drug CarriersReferences: Kirkpatrick, C.J., Fuchs, S., Peters, K., Brochhausen, C., Hermanns, M.I., Unger, R.E., Visions for regenerative medicine: interface between scientific fact and science fiction (2006) Artif Organs, 30, pp. 822-827;Simões, S., Filipe, A., Faneca, H., Mano, M., Penacho, N., Duzgunes, N., Cationic liposomes for gene delivery (2005) Expert Opin Drug Deliv, 2, pp. 237-254; Lungwitz, U., Breunig, M., Blunk, T., Gopferich, A., Polyethylenimine-based non-viral gene delivery systems (2005) Eur J Pharm Biopharm, 60, pp. 247-266; Filion, M.C., Phillips, N.C., Major limitations in the use of cationic liposomes for DNA delivery (1998) Int J Pharm, 162, pp. 159-170; Lv, H., Zhang, S., Wang, B., Cui, S., Yan, J., Toxicity of cationic lipids and cationic polymers in gene delivery (2006) J Control Release, 114, pp. 100-109; Itaka, K., Ohba, S., Miyata, K., Kawaguchi, H., Nakamura, K., Takato, T., Bone regeneration by regulated in vivo gene transfer using biocompatible polyplex nanomicelles (2007) Mol Ther, 15, pp. 1655-1662; Borchard, G., Chitosans for gene delivery (2001) Adv Drug Deliv Rev, 52, pp. 145-150; Khalil, I.A., Kogure, K., Akita, H., Harashima, H., Uptake pathways and subsequent intracellular trafficking in nonviral gene delivery (2006) Pharmacol Rev, 58, pp. 32-45; Behr, J.P., The proton sponge: a trick to enter cells the viruses did not exploit (1997) Chimia, 51, pp. 34-36; Kim, T.H., Kim, S.I., Akaike, T., Cho, C.S., Synergistic effect of poly(ethylenimine) on the transfection efficiency of galactosylated chitosan/DNA complexes (2005) J Control Release, 105, pp. 354-366; Midoux, P., Monsigny, M., Efficient gene transfer by histidylated polylysine/pDNA complexes (1999) Bioconjug Chem, 10, pp. 406-411; Benns, J.M., Choi, J.S., Mahato, R.I., Park, J.S., Kim, S.W., pH-sensitive cationic polymer gene delivery vehicle: N-Ac-poly(l-histidine)-graft-poly(l-lysine) comb shaped polymer (2000) Bioconjug Chem, 11, pp. 637-645; Putnam, D., Gentry, C.A., Pack, D.W., Langer, R., Polymer-based gene delivery with low cytotoxicity by a unique balance of side-chain termini (2001) Proc Natl Acad Sci USA, 98, pp. 1200-1205; Dubruel, P., Christiaens, B., Vanloo, B., Bracke, K., Rosseneu, M., Vandekerckhove, J., Physicochemical and biological evaluation of cationic polymethacrylates as vectors for gene delivery (2003) Eur J Pharm Sci, 18, pp. 211-220; Dubruel, P., Dekie, L., Schacht, E., Poly-l-glutamic acid derivatives as multifunctional vectors for gene delivery. Part A. Synthesis and physicochemical evaluation (2003) Biomacromolecules, 4, pp. 1168-1176; Kim, T.H., Ihm, J.E., Choi, Y.J., Nah, J.W., Cho, C.S., Efficient gene delivery by urocanic acid-modified chitosan (2003) J Control Release, 93, pp. 389-402; Dubruel, P., Christiaens, B., Rosseneu, M., Vandekerckhove, J., Grooten, J., Goossens, V., Buffering properties of cationic polymethacrylates are not the only key to successful gene delivery (2004) Biomacromolecules, 5, pp. 379-388; Juusola, P., Minkkinen, P., Leino, L., Laihia, J.K., Determination of the dissociation constants of urocanic acid isomers in aqueous solutions (2007) Monatsh Chem, 138, pp. 951-965; Roberts, J.D., Yu, C., Flanagan, C., Birdseye, T.R., A nitrogen-15 nuclear magnetic resonance study of the acid-base and tautomeric equilibria of 4-substituted imidazoles and its relevance to the catalytic mechanism of alfa-lytic protease (1982) J Am Chem Soc, 104, pp. 3945-3949; Roberts, G.A.F., (1992) Chitin chemistry, , Palgrave Macmillan, London; Nakagawa, Y., Murai, T., Hasegawa, C., Hirata, M., Tsuchiya, T., Yagami, T., Endotoxin contamination in wound dressings made of natural biomaterials (2003) J Biomed Mater Res B Appl Biomater, 66, pp. 347-355; (1987) Guideline on validation of the limulus amebocyte lysate test as an end-product endotoxin test for human and animal parenteral drugs, biological products, and medical devices, , U.S. Department of Health and Human Services, Public Health Service, Food and Drug Administration; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydr Polym, 29, pp. 63-68; Sehgal, D., Vijay, I.K., A method for the high-efficiency of water-soluble carbodiimide-mediated amidation (1994) Anal Biochem, 218, pp. 87-91; Leong, K.W., Mao, H.Q., Truong-Le, V.L., Roy, K., Walsh, S.M., August, J.T., DNA-polycation nanospheres as non-viral gene delivery vehicles (1998) J Control Release, 53, pp. 183-193; Lee, M., Nah, J.W., Kwon, Y., Koh, J.J., Ko, K.S., Kim, S.W., Water-soluble and low molecular weight chitosan-based plasmid DNA delivery (2001) Pharm Res, 18, pp. 427-431; van Kuppeveld, F.J., van der Logt, J.T., Angulo, A.F., van Zoest, M.J., Quint, W.G., Niesters, H.G., Genus- and species-specific identification of mycoplasmas by 16S rRNA amplification (1992) Appl Environ Microbiol, 58, pp. 2606-2615; van Kuppeveld, F.J., van der Logt, J.T., Angulo, A.F., van Zoest, M.J., Quint, W.G., Niesters, H.G., Genus- and species-specific identification of mycoplasmas by 16S rRNA amplification (1993) Appl Environ Microbiol, 59, p. 655; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Godbey, W.T., Ku, K.K., Hirasaki, G.J., Mikos, A.G., Improved packing of poly(ethylenimine)/DNA complexes increases transfection efficiency (1999) Gene Ther, 6, pp. 1380-1388; Pouton, C.W., Lucas, P., Thomas, B.J., Uduehi, A.N., Milroy, D.A., Moss, S.H., Polycation-DNA complexes for gene delivery: a comparison of the biopharmaceutical properties of cationic polypeptides and cationic lipids (1998) J Control Release, 53, pp. 289-299; Mao, H.Q., Roy, K., Troung-Le, V.L., Janes, K.A., Lin, K.Y., Wang, Y., Chitosan-DNA nanoparticles as gene carriers: synthesis, characterization and transfection efficiency (2001) J Control Release, 70, pp. 399-421; Poole, B., Ohkuma, S., Effect of weak bases on the intralysosomal pH in mouse peritoneal-macrophages (1981) J Cell Biol, 90, pp. 665-669; Bowman, E.J., Siebers, A., Altendorf, K., Bafilomycins: a class of inhibitors of membrane ATPases from microorganisms, animal cells, and plant cells (1988) Proc Natl Acad Sci USA, 85, pp. 7972-7976; van Deurs, B., Holm, P.K., Sandvig, K., Inhibition of the vacuolar H+ATPase with bafilomycin reduces delivery of internalized molecules from mature multivesicular endosomes to lysosomes in HEp-2 cells (1996) Eur J Cell Biol, 69, pp. 343-350; Merdan, T., Kopecek, J., Kissel, T., Prospects for cationic polymers in gene and oligonucleotide therapy against cancer (2002) Adv Drug Deliv Rev, 54, pp. 715-758; Mansouri, S., Lavigne, P., Corsi, K., Benderdour, M., Beaumont, E., Fernandes, J.C., Chitosan-DNA nanoparticles as non-viral vectors in gene therapy: strategies to improve transfection efficacy (2004) Eur J Pharm Biopharm, 57, pp. 1-8; Erbacher, P., Zou, S.M., Bettinger, T., Steffan, A.M., Remy, J.S., Chitosan-based vector/DNA complexes for gene delivery: biophysical characteristics and transfection ability (1998) Pharm Res, 15, pp. 1332-1339; Kiang, T., Wen, J., Lim, H.W., Leong, K.W., The effect of the degree of chitosan deacetylation on the efficiency of gene transfection (2004) Biomaterials, 25, pp. 5293-5301; Ishii, T., Okahata, Y., Sato, T., Mechanism of cell transfection with plasmid/chitosan complexes (2001) BBA-Biomembranes, 1514, pp. 51-64; Lavertu, M., Methot, S., Tran-Khanh, N., Buschmann, M.D., High efficiency gene transfer using chitosan/DNA nanoparticles with specific combinations of molecular weight and degree of deacetylation (2006) Biomaterials, 27, pp. 4815-4824; de Smedt, S.C., Demeester, J., Hennink, W.E., Cationic polymer based gene delivery systems (2000) Pharm Res, 17, pp. 113-126; Kichler, A., Leborgne, C., Coeytaux, E., Danos, O., Polyethylenimine-mediated gene delivery: a mechanistic study (2001) J Gene Med, 3, pp. 135-144; Wattiaux, R., Laurent, N., Wattiaux-De Coninck, S., Jadot, M., Endosomes, lysosomes: their implication in gene transfer (2000) Adv Drug Deliv Rev, 41, pp. 201-208; Pelkmans, L., Helenius, A., Endocytosis via caveolae (2002) Traffic, 3, pp. 311-320; Felgner, P.L., Gadek, T.R., Holm, M., Roman, R., Chan, H.W., Wenz, M., Lipofection-a highly efficient, lipid-mediated DNA-transfection procedure (1987) Proc Natl Acad Sci USA, 84, pp. 7413-7417; Conner, S.D., Schmid, S.L., Regulated portals of entry into the cell (2003) Nature, 422, pp. 37-44; Koping-Hoggard, M., Tubulekas, I., Guan, H., Edwards, K., Nilsson, M., Varum, K.M., Chitosan as a nonviral gene delivery system. Structure-property relationships and characteristics compared with polyethylenimine in vitro and after lung administration in vivo (2001) Gene Ther, 8, pp. 1108-1121; Boussif, O., Zanta, M.A., Behr, J.P., Optimized galenics improve in vitro gene transfer with cationic molecules up to 1000-fold (1996) Gene Ther, 3, pp. 1074-1080
Keywords: article; beta galactosidase; Biocompatible Materials; Buffers; Cell Line; cell transport; Chemical structure; chitosan; coacervation; complex formation; controlled study; Cytotoxicity; Diffusion; DNA; Drug Carriers; Drug Compounding; endosome; Gene delivery; Gene transfer; genetic transfection; human; human cell; Humans; imidazole; Kidney; materials testing; nanomaterial; nanoparticle; priority journal; protein expression; proton transport; Tissue engineering; Transfection

Induction of notch signaling by immobilization of jagged-1 on self-assembled monolayers - Gonçalves, R.M.; Martins, M.C.L.; Almeida-Porada, G.; Barbosa, M.A. (BiomaterialsBiomaterials, 2009)
Notch signaling is a key mechanism during mammal development and stem cell regulation. This study aims to target and control Notch signaling by ligands immobilization using self-assembled monolayers (SAMs) as model surfaces. Non-fouling substrates were prepared by immersion of gold substrates in (1-Mercapto-11-undecyl)tetra(ethylene glycol) thiol solutions. These surfaces were activated with N,N′-carbonyldiimidazole (CDI) at different concentrations (0, 0.03, 0.3, 3 and 30 mg/ml) and an anti-human IgG, Fc specific fragment antibody (Ab) was covalently bound to EG4-SAMs to guarantee the correct exposure of the Notch ligand Jagged-1/Fc chimera (Jag-1). The presence of Ab and Jag-1 was confirmed by radiolabeling, X-ray photoelectron spectroscopy (XPS), ellipsometry and ELISA. The biological activity of Jag-1-Ab-SAMs was assessed by real-time PCR for Hes-1 family gene expression, a Notch pathway target gene, in HL-60 cell line. Results have shown an increase of the amount of immobilized Ab with increasing surface activator concentrations. Jag-1 concentration also increases with Ab concentration. Interestingly, a higher Jagged-1 exposure and fold increase in Hes-1 expression were obtained for surfaces activated with the lowest concentration of CDI (0.03 mg/ml). These results illustrate the great importance of ligands orientation and exposure, when compared with density. This investigation brings new insights into Notch signaling mechanisms. In particular, Jag-1-Ab-SAMs have shown to be adequate model surfaces to study Notch pathway activation and may provide a basis to develop new interfaces in biomaterials to control Notch mechanism in different cell systems. © 2009 Elsevier Ltd.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.09.010PubMed ID: 19783294Language of Original Document: EnglishCorrespondence Address: Gonçalves, R.M.; INEB, Biomaterials Division, NEWTherapies Group, R. Campo Alegre, 823, 4150-180 Porto, Portugal; email: raquelg@ineb.up.ptChemicals/CAS: Calcium-Binding Proteins; Gold, 7440-57-5; Immunoglobulin G; Intercellular Signaling Peptides and Proteins; Membrane Proteins; Receptors, Fc; Receptors, Notch; Recombinant Fusion Proteins; Serrate proteins, 134324-36-0References: Artavanis-Tsakonas, S., Rand, M.D., Lake, R.J., Notch signaling: cell fate control and signal integration in development (1999) Science, 284, pp. 770-776;Leong, K., Karsan, A., Recent insights in the role of notch signaling in tumorigenesis (2006) Blood, 107 (6), pp. 2223-2233; Chiba, S., Concise review: notch signaling in stem cell systems (2006) Stem Cells, 24, pp. 2437-2447; Lowell, S., Benchoua, A., Heavey, B., Smith, A.G., Notch promotes neural lineage entry by pluripotent embryonic stem cells (2006) PLoS Biol, 4 (5); Hellström, M.P.L., Hofmann, J.J., Wallgard, E., Coultas, L., Lindblom, P., Alva, J., Dll4 signalling through notch1 regulates formation of tip cells during angiogenesis (2007) Nature, 15 (445), pp. 776-780; Hofmeister, C., Zhang, J., Knight, K.L., Le, P., Stiff, P.J., Ex vivo expansion of umbilical cord blood stem cells for transplantation: growing knowledge from the hematopoietic niche (2007) Bone Marrow Transplant, 39 (1), pp. 11-23; Hilton, M., Tu, X., Wu, X., Bai, S., Zhao, H., Kobayashi, T., F. Notch signaling maintains bone marrow mesenchymal progenitors by suppressing osteoblast differentiation (2008) Nat Med, 14 (3), pp. 306-314; Stylianou, S., Clarke, R.B., Brennan, K., Aberrant activation of notch signaling in human breast cancer (2006) Cancer Res, 66 (3), pp. 1517-1525; Demarest, R., Ratti, F., Capobianco, A.J., It's T-ALL about notch (2008) Oncogene, 27 (38), pp. 5082-5091; Fre, S., Huyghe, M., Mourikis, P., Robine, S., Louvard, D., Artavanis-Tsakonas, S., Notch signals control the fate of immature progenitor cells in the intestine (2005) Nature, 16 (435), pp. 964-968; Fischer, A., Gessler, M., Delta-notch-and then? Protein interactions and proposed modes of repression by Hes and Hey bHLH factors (2007) Nucleic Acids Res, 35 (14), pp. 4583-4596; Zweidler-McKay, P.A., He, Y., Xu, L., Rodriguez, C.G., Karnell, F.G., Carpenter, A.C., Notch signaling is a potent inducer of growth arrest and apoptosis in a wide range of B-cell malignancies (2005) Blood, 106 (12), pp. 3898-3906; Beckstead, B., Santosa, D.M., Giachelli, C.M., Mimicking cell-cell interactions at the biomaterial-cell interface for control of stem cell differentiation (2006) J Biomed Mater Res, 79 A, pp. 94-103; Varnum-Finney, B., Wu, L., Yu, M., Brashem-Stein, C., Staats, S., Flowers, D., Immobilization of Notch ligand, Delta-1, is required for induction of notch signaling (2000) J Cell Sci, 113 (23), pp. 4313-4318; Delaney, C., Varnum-Finney, B., Aoyama, K., Brashem-Stein, C., Bernstein, I.D., Dose-dependent effects of the notch ligand delta1 on ex vivo differentiation and in vivo marrow repopulating ability of cord blood cells (2005) Blood, 106, pp. 2693-2699; Lefort, N., Bennea, C., Lelièvrea, J.D., Dorivala, C., Balboa, M., Sakanoc, S., Short exposure to notch ligand delta-4 is sufficient to induce T-cell differentiation program and to increase the T cell potential of primary human CD34+ cells (2006) Exp Hematol, 34, pp. 1720-1729; Taqvi, S., Dixit, L., Krishnendu, R., Biomaterial-based notch signaling for the differentiation of hematopoietic stem cells into T cells (2006) J Biomed Mater Res, 79 A, pp. 689-697; Bernstein, I., Delaney, C., Dallas, M., Heimfeld, S., Varnum-Finney, B., Notch signaling in hematopoiesis: implication for improving stem cell transplantation (2008) Biol Blood Marrow Transplant, 14, pp. 94-99; De Smedt, M., Hoebeke, I., Reyvoet, K., Leclercq, G., Plum, J., Different thresholds of Notch signaling bias human precursor cells toward B-, NK-, monocytic/dendritic-, or T-cell lineage in thymus microenvironment (2005) Blood, 106, pp. 3498-3506; Mrksich, M., What can surface chemistry do for cell biology? (2002) Curr Opin Chem Biol, 6, pp. 794-797; France, R., Short, R.D., Dawsonb, R.A., MacNeilb, S., Attachment of human keratinocytes to plasma copolymers of acrylic acid/octa-1,7-diene and allyl amine/octa-1,7-diene (1998) J Mater Chem, 81 (1), pp. 37-42; Neves, H., Weerkamp, F., Gomes, A.C., Naber, B., Gameiro, P., Becker, J.L., Effects of delta1 and jagged1 on early human hematopoiesis: correlation with expression of notch signaling-related genes in CD34+ Cells (2006) Stem Cells, 24, pp. 1328-1337; Sokolova, V., Epple, M., Inorganic nanoparticles as carriers of nucleic acids into cells (2008) Angewandte Chemie, 47, pp. 1382-1395; Yao, J., Duan, L., Fan, M., Yuan, J., Wu, X., Notch1 induces cell cycle arrest and apoptosis in human cervical cancer cells: involvement of nuclear factor kappa B inhibition (2007) Int J Gynecol Cancer, 17, pp. 502-510; Chadwick, N., Nostro, M.C., Baron, M., Mottram, R., Brady, G., Buckle, A., Notch signaling induces apoptosis in primary human CD34+ hematopoietic progenitor cells (2007) Stem Cells, 25, pp. 203-210; Love, J., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chem Rev, 105, pp. 1103-1169; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Martins, M.C.L., Ratner, B., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl- terminated self-assembled monolyers (2003) J Biomed Mater Res, 67 (A), pp. 158-171; Martins, M.C.L., Curtins, S.A., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88 (1), pp. 162-173; Barrias, C.C., Martins, M.C.L., Bidarra, S., Sá Miranda, M.C., Barbosa, M.A., Adsorption of a therapeutic enzyme to self-assembled monolayers: effect of the surface chemistry and solution pH on the amount and activity of adsorbed enzyme (2005) Biomaterials, 26, pp. 2695-2704; Iodine-125. A guide to radioiodination techniques. In: techniques I-Agtr, ed.: Little Chalfort: Amersham Life Science 1993Horbett, T., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, pp. 183-214. , DF W. (Ed), CRC Press Inc, Harcover; Ohishi, K., Varnum-Finney, B., Bernstein, I.D., Delta-1 enhances marrow and thymus repopulating ability of human CD34+ CD38- cord blood cells (2002) J Clin Invest, 110, pp. 1165-1174; Li, L., Chen, S., Zheng, J., Ratner, B.D., Jiang, S., Protein adsorption on oligo(ethylene glycol)-terminated alkanethiolate self-assembled monolayers: the molecular basis for nonfouling behavior (2005) J Phys Chem B, 109 (7), pp. 2934-2941; Tohda, S., Murata-Ohsawa, M., Sakano, S., Nara, N., Notch ligands, Delta-1 and Delta-4 supress the self-renewal capacity and long-term growth of two myeloblastic leukemia cell lines (2003) Int J Oncol, 22 (5), pp. 1073-1079; Tohda, S.K.H., Murakami, N., Sakano, S., Nara, N., Diverse effects of the Notch ligands Jagged1 and Delta1 on the growth and differentiation of primary acute myeloblastic leukemia cells (2005) Exp Hematol, 33, pp. 558-563; Aoyama, K., Delaney, C., Varnun-Finney, B., Kohn, A.D., Moon, R.T., Bernstein, I.D., The interaction of the Wnt and notch pathways modulates natural killer versus T cell differentiation (2007) Stem Cells, 25, pp. 2488-2497; Beckstead B, Tung JC, Liang KJ, Tavakkol Z, Usui ML, Olerud JE, et al. Methods to promote notch signaling at the biomaterial interface and evaluation in a rafted organ culture model. J Biomed Mater Res A, in press. [Epub ahead of print]Semler, E., Dasgupta, A., Moghe, P.V., Cytomimetic engineering of hepatocyte morphogenesis and function by substrate-based presentation of acellular E-cadherin (2005) Tissue Eng, 11 (5-6), pp. 734-750; Zhao, Z., Matsui, H., Accurate immobilization of antibody-functionalized peptide nanotubes on protein-patterned arrays by optimizing their ligand-receptor interactions (2007) Small, 3 (8), pp. 1390-1393; Longo, G., Szleifer, Ligand-receptor interactions in tethered polymer layers (2005) Langmuir, 21, pp. 11342-11351; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption and clotting time of pHEMA hydrogels modified with C18 ligands to adsorb albumin selectively and reversibly (2009) Biomaterials, 30 (29), pp. 5541-5551
Keywords: Activator concentration; Adequate models; Adsorption; Animals; article; Bioactivity; Biological activities; Biological materials; biomaterial; Calcium-Binding Proteins; Carbonyldiimidazole; Cell culture; Cell Line; Cell membranes; cell strain HL 60; Cell system; Chemical activation; Concentration (process); Concentration of; controlled study; Covalently bound; Ethylene; Ethylene Glycol; gene expression; gold; Gold substrates; HL-60 cell line; human; human cell; Human IgG; Humans; Immunoassay; immunoglobulin Fc fragment; Immunoglobulin G; immunoglobulin G antibody; Intercellular Signaling Peptides and Proteins; Jagged1; Ligands; Mammalia; Membrane Proteins; Model surface; Molecular Structure; Nanostructured materials; Nanostructured surfaces; Nonfouling; Notch receptor; Notch signaling; Photoelectron spectroscopy; priority journal; Protein adsorption; protein immobilization; Radiolabeling; Real-time PCR; Receptors, Fc; Receptors, Notch; Recombinant Fusion Proteins; Sams; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; signal transduction; Signaling; stem cell; Surface Properties; Target genes; Tetra; transcription factor HES 1; X ray photoelectron spectroscopy

NPY revealed as a critical modulator of osteoblast function in vitro: New insights into the role of Y1 and Y2 receptors - Teixeira, L.; Sousa, D.M.; Nunes, A.F.; Sousa, M.M.; Herzog, H.; Lamghari, M. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2009)
Neuropeptide Y (NPY) has recently emerged as a potential regulator of bone homeostasis. However, the relevance of NPY's role in osteoblast activity and the biological functions involving NPY receptors in bone homeostasis remain to be clarified. Here we report that chronically elevated NPY levels leaded to a modulation of the level of Y2 receptor expression marked with a transient down and upregulation according to the stage of osteoblast differentiation. We also show that NPY is a negative regulator of Y1 receptor expression. The pharmalogical activation of Y2 receptor with its agonist resulted in similar effect. Functional analysis also revealed the osteogenic potential of NPY with osteoblast phenotype markers being significantly enhanced in osteoprogenitor cells stimulated by NPY, probably due to the down-regulation of Y1 receptor. In contrasts, these cells exhibit a reduction in calcium deposition in extracellular matrix most likely mediated via Y2 receptor signalling. Furthermore, we show that NPY modulates receptor activator of nuclear factor kB (NF-kB) (RANK) ligand and osteoprotegerin, two key factors regulating bone remodelling. Specifically, NPY inhibits the transcriptional activity of RANKL promoter in osteoprogenitor cells and enhances OPG expression in osteoblasts at early stages of differentiation. However, NPY effect on OPG seemed to be unrelated to Y2 receptor activation. Taken together the present data supported the contribution of NPY pathway in bone homeostasis via a direct action on osteoblasts cells. © 2009 Wiley-Liss, Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JCEBDdoi: 10.1002/jcb.22194PubMed ID: 19459152Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; Instituto de Engenharia Biomédica (INEB), Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: calcium, 14092-94-5, 7440-70-2; osteoclast differentiation factor, 200145-93-3; osteoprotegerin, 205944-50-9; Alkaline Phosphatase, 3.1.3.1; Neuropeptide Y; Osteoprotegerin; RANK Ligand; Receptors, Neuropeptide YReferences: Ahmed, M., Srinivasan, G.R., Theodorsson, E., Bjurholm, A., Kreicbergs, A., Extraction and quantitation of neuropeptides in bone by radioimmunoassay (1994) Regul Pept, 51, pp. 179-188;Allison, S.J., Herzog, H., NPY and bone (2006) EXS, 95, pp. 171-182; Allison, S.J., Baldock, P., Sainsbury, A., Enriquez, R., Lee, N.J., Lin, E.J., Klugman, M., Gardiner, E.M., Conditional deletion of hypothalamic Y2 receptors reverts gonadectomy-induced bone loss in adult mice (2006) J Biol Chem, 281, pp. 23436-23444; Amano, S., Arai, M., Goto, S., Togari, A., Inhibitory effect of NPY on isoprenaline-induced osteoclastogenesis in mouse bone marrow cells (2007) Biochim Biophys Acta, 1770, pp. 966-973; Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Ghomas, G.P., Gardiner, E.M., Herzog, H., Hypothalamic Y2 receptors regulate bone formation (2002) J Clin Investig, 109, pp. 915-921; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., Hypothalamic control of bone formation: Distinct actions of leptin and y2 receptor pathways (2005) J Bone Miner Res, 20, pp. 1851-1857; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., Herzog, H., Novel role of Y1 receptors in the coordinated regulation of bone and energy homeostasis (2007) J Biol Chem, 282, pp. 19092-19102; Chenu, C., Role of innervation in the control of bone remodelling (2004) J Musculoskel Neuron Interact, 4, pp. 132-134; Chenu, C., Marenzana, M., Sympathetic nervous system and bone remodeling (2005) Joint Bone Spine, 72, pp. 481-483; Clark, J.T., Kalra, P.S., Kalra, S.P., Neuropeptide Y stimulates feeding but inhibits sexual behavior in rats (1985) Endocrinology, 117, pp. 2435-2442; Dumont, Y., Jacques, D., Bouchard, P., Quirion, R., Species differences in the expression and distribution of the neuropeptide Y Y1, Y2, Y4, and Y5 receptors in rodents, guinea pig, and primates brains (1998) J Comp Neurol, 402, pp. 372-384; Elefteriou, F., Neuronal signalling and the regulation of bone remodelling (2005) Cell Mol Life Sci, 62, pp. 2339-2349; Ericsson, A., Schalling, M., McIntyre, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., Detection of neuropeptide Y and its mRNA in megakaryocytes: Enhanced levels in certain autoimmune mice (1987) Proc Natl Acad Sci USA, 84, pp. 5585-5589; Fu, Q., Manolagas, S.C., O'Brien, C.A., Parathyroid hormone controls receptor activator of NF-kappaB ligand gene expression via a distant transcriptional enhancer (2006) Mol Cell Biol, 26, pp. 6453-6468; Gori, F., Hofbauer, L.C., Dunstan, C.R., Spelsberg, T.C., Khosla, S., Riggs, B.L., The expression of osteoprotegerin and RANK ligand and the support of osteoclast formation by stromal-osteoblast lineage cells is developmentally regulated (2000) Endocrinology, 141, pp. 4768-4776; Herzog, H., Neuropeptide Y and energy homeostasis: Insights from Y receptor knockout models (2003) Eur J Pharmacol, 480 (1-3), pp. 21-29; Hill, E.L., Turner, R., Elde, R., Effects of neonatal sympathectomy and capsaicin treatment on bone remodeling in rats (1991) Neuroscience, 44 (3), pp. 747-755; Holliday, N.D., Michel, M.C., Cox, H.M., NPY receptor subtypes and their signal transduction (2004) Neuropeptide Y and related peptides, Handbook of experimental pharmacology, 162, pp. 45-74. , Michel MC, editor, Berlin: Springer-Verlag, Heidelberg, pp; Hosaka, H., Nagata, A., Yoshida, T., Shibata, T., Nagao, T., Tanaka, T., Saito, Y., Tatsuno, I., Pancreatic polypeptide is secreted from and controls differentiation through its specific receptors in osteoblastic MC3T3-E1 cells (2008) Peptides, 29 (8), pp. 1390-1395; Imai, S., Matsusue, Y., Neuronal regulation of bone metabolism and anabolism: Calcitonin gene-related peptide-, substance P-, and tyrosine hydroxylase-containing nerves and the bone (2002) Microsc Res Tech, 58, pp. 61-69; Kondo, H., Guo, J., Bringhurst, F.R., Cyclic adenosine monophosphate/protein kinase A mediates parathyroid hormone/parathyroid hormone-related protein receptor regulation of osteoclastogenesis and expression of RANKL and osteoprotegerin mRNAs by marrow stromal cells (2002) J Bone Miner Res, 17, pp. 1667-1679; Kuo, L.E., Kitlinska, J.B., Tilan, J.U., Li, L., Baker, S.B., Johnson, M.D., Lee, E.W., Zukowska, Z., Neuropeptide Y acts directly in the periphery on fat tissue and mediates stress-induced obesity and metabolic syndrome (2007) Nat Med, 13, pp. 803-811; Lee, S.K., Lornezo, J.A., Regulation of receptor activator of nuclear factor-kappaB ligand and osteoprotegerin mRNA expression by parathyroid hormone is predominantly mediated by the protein kinase a pathway in murine bone marrow cultures (2002) Bone, 31, pp. 252-259; Lerner, U.H., Lundberg, P., Kinins, neuro-osteogenic factors (2002) Principles of bone biology, pp. 773-799. , Bilezikian JP, Raisz LG, Rodan GA, editors, 2nd edition. San Diego: Academic Press. pp; Li, J., Ahmad, T., Spetea, M., Ahmed, M., Kreicbergs, A., Bone reinnervation after fracture: A study in the rat (2001) J Bone Miner Res, 16, pp. 1505-1510; Lundberg, P., Lerner, U.H., Expression and regulatory role of receptors for vasoactive intestinal peptide in bone cells (2002) Microsc Res Tech, 58, pp. 98-103; Lundberg, P., Boström, I., Mukohyama, H., Bjurholm, A., Smans, K., Lerner, U.H., Neuro-hormonal control of bone metabolism: Vasoactive intestinal peptide stimulates alkaline phosphatase activity and mRNA expression in mouse calvarial osteoblasts as well as calcium accumulation mineralized bone nodules (1999) Regul Pept, 85, pp. 47-58; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Herzog, H., Greater bone formation of Y2 knockout mice is associated with increased osteoprogenitor numbers and altered Y1 receptor expression (2007) J Biol Chem, 282, pp. 19082-19091; Michel, M.C., Beck-Sickinger, A., Cox, H., Doods, H.N., Herzog, H., Larhammar, D., Quirion, R., Westfall, T., XVI. International Union of Pharmacology recommendations for the nomenclature of neuropeptide Y, peptide YY, and pancreatic polypeptide receptors (1998) Pharmacol Rev, 50, pp. 143-150; Movafagh, S., Hobson, J.P., Spiegel, S., Kleinman, H.K., Zukowska, Z., Neuropeptide Y induces migration, proliferation, and tube formation of endothelial cells bimodallyvia Y1, Y2, and Y5 receptors (2006) FASEB J, 20, pp. 1327-1337; Sainsbury, A., Baldock, P.A., Schwarzer, C., Ueno, N., Enriquez, R.F., Couzens, M., Inui, A., Gardiner, E.M., Synergistic effects of Y2 and Y4 receptors on adiposity and bone mass revealed in double knockout mice (2003) Mol Cell Biol, 23, pp. 5225-5233; Serre, C.M., Farlay, D., Delmas, P.D., Chenu, C., Evidence for a dense and intimate innervation of the bone tissue, including glutamate-containing fibers (1999) Bone, 25, pp. 623-629; Simonet, W.S., Lacey, D.L., Dunstan, C.R., Kelley, M., Chang, M.S., Lüthy, R., Nguyen, H.Q., Boyle, W.J., Osteoprotegerin: A novel secreted protein involved in the regulation of bone density (1997) Cell, 89, pp. 309-319; Sudo, H., Kodama, H.A., Amagai, Y., Yamamoto, S., Kasai, S., In vitro differentiation and calcification in a new clonal osteogenic cell line derived from newborn mouse calvaria (1983) J Cell Biol, 96, pp. 191-198; Szczesny, G., Molecular aspects of bone healing, remodelling (2002) Pol J Pathol, 53, pp. 145-153; Tatemoto, K., Neuropeptide Y: Complete amino acid sequence of the brain peptide (1982) Proc Natl Acad Sci USA, 79, pp. 5485-5489; Thiriet, N., Deng, X., Solinas, M., Ladenheim, B., Curtis, W., Goldberg, S.R., Palmiter, R.D., Cadet, J.L., Neuropeptide Y protects against methamphetamine-induced neuronal apoptosis in the mouse striatum (2005) J Neurosci, 25, pp. 5273-5279; Wittmann, W., Loacker, S., Kapeller, I., Herzog, H., Schwarzer, C., Y1-receptors regulate the expression of Y2-receptors in distinct mouse forebrain areas (2005) Neuroscience, 136, pp. 241-250; Wortley, K.E., Garcia, K., Okamoto, H., Thabet, K., Anderson, K.D., Shen, V., Herman, J.P., Sleeman, M.W., Peptide YY regulates bone turnover in rodents (2007) Gastroenterology, 133, pp. 1534-1543
Keywords: alkaline phosphatase; animal cell; animal tissue; Animals; article; Bone; Bone Marrow Cells; bone remodeling; Calcium; cell activity; cell differentiation; cell function; Cell Line; cell stimulation; controlled study; down regulation; extracellular matrix; gene expression regulation; genetic transcription; Homeostasis; immunoglobulin enhancer binding protein; in vitro study; Mice; neuropeptide Y; neuropeptide Y1 receptor; neuropeptide Y2 receptor; nonhuman; NPY; nuclear factor Y; osteoblast; Osteoblasts; osteoclast differentiation factor; Osteoprotegerin; phenotype; priority journal; promoter region; protein expression; RANK Ligand; Receptors, Neuropeptide Y; Reverse Transcriptase Polymerase Chain Reaction; signal transduction; stem cell; Stromal Cells; upregulation; Y1 receptor; Y2 receptor

Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene delivery vectors - Santos, J.L.; Oramas, E.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Journal of Controlled ReleaseJ. Control. Release, 2009)
This paper reports the use of different generations of polyamidoamine (PAMAM) dendrimers for the in vitro transfection of mesenchymal stem cells (MSCs). A systematic study was carried out on the transfection efficiency achieved by the PAMAM dendrimers using a β-galactosidase reporter gene system. Transfection results were shown to be dependent upon the generation of dendrimers, the amine to phosphate group ratio and the cell passage number. In all cases, the transfection efficiency was very low. Nevertheless, it was hypothesized that a low transfection level could be sufficient to promote the in vitro differentiation of MSCs towards the osteoblastic lineage. To address this possibility, dendrimers carrying the human bone morphogenetic protein-2 (hBMP-2) gene-containing plasmid were used. All quantitative (alkaline phosphatase activity, osteocalcin secretion and calcium deposition) and qualitative (von Kossa staining) osteogenic markers were significantly stronger in transfected cells when compared to non-transfected ones. This study not only clearly demonstrates that a low transfection level can be sufficient for inducing in vitro differentiation of MSCs to the osteoblast phenotype but also highlights the importance of focusing research on the development of gene delivery vectors in the concrete application. © 2008 Elsevier B.V. All rights reserved.
Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: JCREEdoi: 10.1016/j.jconrel.2008.11.007PubMed ID: 19070635Language of Original Document: EnglishCorrespondence Address: Tomás, H.; Centro de Química da Madeira, Departamento de Química, Universidade da Madeira, Campus Universitario da Penteada, 9000-390 Funchal, Portugal; email: lenat@uma.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium, 14092-94-5, 7440-70-2; osteocalcin, 136461-80-8; phosphate, 14066-19-4, 14265-44-2; BMP2 protein, human; Bone Morphogenetic Protein 2; Dendrimers; PAMAM Starburst; Polyamines; beta-Galactosidase, 3.2.1.23References: Dai, J., Rabie, A.B.M., Hagg, U., Xu, R.A., Alternative gene therapy strategies for the repair of craniofacial bone defects (2004) Curr. Gene Ther., 4 (4), pp. 469-485;Gersbach, C.A., Phillips, J.E., Garcia, A.J., Genetic engineering for skeletal regenerative medicine (2007) Annu. Rev. Biomed. Eng., 9, pp. 87-119; Kofron, M.D., Laurencin, C.T., Orthopaedic applications of gene therapy (2005) Curr. Gene Ther., 5 (1), pp. 37-61; Kofron, M.D., Laurencin, C.T., Bone tissue engineering by gene delivery (2006) Adv. Drug Deliv. Rev., 58 (4), pp. 555-576; Luo, J., Sun, M.H., Kang, Q., Peng, Y., Jiang, W., Luu, H.H., Luo, Q., He, T.C., Gene therapy for bone regeneration (2005) Curr. Gene Ther., 5 (2), pp. 167-179; Partridge, K.A., Oreffo, R.O., Gene delivery in bone tissue engineering: progress and prospects using viral and nonviral strategies (2004) Tissue Eng., 10 (1-2), pp. 295-307; Turgeman, G., Aslan, H., Gazit, Z., Gazit, D., Cell-mediated gene therapy for bone formation and regeneration (2002) Curr. Opin. Mol. Ther., 4 (4), pp. 390-394; Chen, Y., Cheung, K.M.C., Kung, H.F., Leong, J.C.Y., Lu, W.W., Luk, K.D.K., In vivo new bone formation by direct transfer of adenoviral-mediated bone morphogenetic protein-4 gene (2002) Biochem. Biophys. Res. Commun., 298 (1), pp. 121-127; Lieberman, J.R., Daluiski, A., Stevenson, S., Wu, L., McAllister, P., Lee, Y.P., Kabo, J.M., Witte, O.N., The effect of regional gene therapy with bone morphogenetic protein-2-producing bone-marrow cells on the repair of segmental femoral defects in rats (1999) J. Bone Joint Surg. Am., 81 (7), pp. 905-917; Park, J., Ries, J., Gelse, K., Kloss, F., von der Mark, K., Wiltfang, J., Neukam, F.W., Schneider, H., Bone regeneration in critical size defects by cell-mediated BMP-2 gene transfer: a comparison of adenoviral vectors and liposomes (2003) Gene Ther., 10 (13), pp. 1089-1098; Riew, K.D., Wright, N.M., Cheng, S.L., Avioli, L.V., Lou, J., Induction of bone formation using a recombinant adenoviral vector carrying the human BMP-2 gene in a rabbit spinal fusion model (1998) Calcif. Tissue Int., 63 (4), pp. 357-360; Tsuda, H., Wada, T., Ito, Y., Uchida, H., Dehari, H., Nakamura, K., Sasaki, K., Hamada, H., Efficient BMP2 gene transfer and bone formation of mesenchymal stem cells by a fiber-mutant adenoviral vector (2003) Mol. Ther., 7 (3), pp. 354-365; De Laporte, L., Cruz Rea, J., Shea, L.D., Design of modular non-viral gene therapy vectors (2006) Biomaterials, 27 (7), pp. 947-954; Eliyahu, H., Barenholz, Y., Domb, A.J., Polymers for DNA delivery (2005) Molecules, 10 (1), pp. 34-64; Roth, C.M., Sundaram, S., Engineering synthetic vectors for improved DNA delivery: insights from intracellular pathways (2004) Annu. Rev. Biomed. Eng., 6, pp. 397-426; Corsi, K., Chellat, F., Yahia, L., Fernandes, J.C., Mesenchymal stem cells, MG63 and HEK293 transfection using chitosan-DNA nanoparticles (2003) Biomaterials, 24 (7), pp. 1255-1264; Hamm, A., Krott, N., Breibach, I., Blindt, R., Bosserhoff, A.K., Efficient transfection method for primary cells (2002) Tissue Eng., 8 (2), pp. 235-245; Lakshmipathy, U., Pelacho, B., Sudo, K., Linehan, J.L., Coucouvanis, E., Kaufman, D.S., Verfaillie, C.M., Efficient transfection of embryonic and adult stem cells (2004) Stem Cells, 22 (4), pp. 531-543; Kim, S.W., Ogawa, T., Tabata, Y., Nishimura, I., Efficacy and cytotoxicity of cationic-agent-mediated nonviral gene transfer into osteoblasts (2004) J. Biomed. Mater. Res. A, 71 (2), pp. 308-315; Dufes, C., Uchegbu, I.F., Schatzlein, A.G., Dendrimers in gene delivery (2005) Adv. Drug Deliv. Rev., 57 (15), pp. 2177-2202; Guillot-Nieckowski, M., Eisler, S., Diederich, F., Dendritic vectors for gene transfection (2007) New J. Chem., 31 (7), pp. 1111-1127; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications-reflections on the field (2005) Adv. Drug Deliv. Rev., 57 (15), pp. 2106-2129; Haensler, J., Szoka, F.C., Polyamidoamine cascade polymers mediate efficient transfection of cells in culture (1993) Bioconjug. Chem., 4 (5), pp. 372-379; Choi, J.S., Nam, K., Park, J., Kim, J.B., Lee, J.K., Park, J., Enhanced transfection efficiency of PAMAM dendrimer by surface modification with l-arginine (2004) J. Control. Release, 99 (3), pp. 445-456; Kono, K., Akiyama, H., Takahashi, T., Takagishi, T., Harada, A., Transfection activity of polyamidoamine dendrimers having hydrophobic amino acid residues in the periphery (2005) Bioconjug. Chem., 16 (1), pp. 208-214; KukowskaLatallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker, J.R., Efficient transfer of genetic material into mammalian cells using Starburst polyamidoamine dendrimers (1996) Proc. Natl. Acad. Sci. U. S. A., 93 (10), pp. 4897-4902; Gebhart, C.L., Kabanov, A.V., Evaluation of polyplexes as gene transfer agents (2001) J. Control. Release, 73 (2), pp. 401-416; Aubin, J.E., Osteoprogenitor cell frequency in rat bone marrow stromal populations: role for heterotypic cell-cell interactions in osteoblast differentiation (1999) J. Cell. Biochem., 72 (3), pp. 396-410; Lennon, D.P., Haynesworth, S.E., Young, R.G., Dennis, J.E., Caplan, A.I., A chemically-defined medium supports in-vitro proliferation and maintains the osteochondral potential of rat marrow-derived mesenchymal stem-cells (1995) Exp. Cell Res., 219 (1), pp. 211-222; Bielinska, A.U., Chen, C.L., Johnson, J., Baker, J.R., DNA complexing with polyamidoamine dendrimers: implications for transfection (1999) Bioconjug. Chem., 10 (5), pp. 843-850; Eichman, J.D., Bielinska, A.U., Kukowska-Latallo, J.F., Baker Jr., J.R., The use of PAMAM dendrimers in the efficient transfer of genetic material into cells (2000) Pharm. Sci. Technol. Today, 7, pp. 232-245; Haleem-Smith, H., Derfoul, A., Okafor, C., Tuli, R., Olsen, D., Hall, D.J., Tuan, R.S., Optimization of high-efficiency transfection of adult human mesenchymal stem cells in vitro (2005) Mol. Biotechnol., 30 (1), pp. 9-19; Fischer, D., Li, Y.X., Ahlemeyer, B., Krieglstein, J., Kissel, T., In vitro cytotoxicity testing of polycations: influence of polymer structure on cell viability and hemolysis (2003) Biomaterials, 24 (7), pp. 1121-1131; Jevprasesphant, R., Penny, J., Jalal, R., Attwood, D., McKeown, N.B., D'Emanuele, A., The influence of surface modification on the cytotoxicity of PAMAM dendrimers (2003) Int. J. Pharm., 252 (1-2), pp. 263-266; Wilke, M., Fortunati, E., vandenBroek, M., Hoogeveen, A.T., Scholte, B.J., Efficacy of a peptide-based gene delivery system depends on mitotic activity (1996) Gene Ther., 3 (12), pp. 1133-1142; Xie, Y.B., Yang, S.T., Kniss, D.A., Three-dimensional cell-scaffold constructs promote efficient gene transfection: implications for cell-based gene therapy (2001) Tissue Eng., 7 (5), pp. 585-598; Yamagiwa, H., Endo, N., Tokunaga, K., Hayami, T., Hatano, H., Takahashi, H.E., In vivo bone-forming capacity of human bone marrow-derived stromal cells is stimulated by recombinant human bone morphogenetic protein-2 (2001) J. Bone Miner. Metab., 19 (1), pp. 20-28; Chaudhari, A., Ron, E., Rethman, M.P., Recombinant human bone morphogenetic protein-2 stimulates differentiation in primary cultures of fetal rat calvarial osteoblasts (1997) Mol. Cell. Biochem., 167 (1-2), pp. 31-39; Hay, E., Hott, M., Graulet, A.M., Lomri, A., Marie, P.J., Effects of bone morphogenetic protein-2 on human neonatal calvaria cell differentiation (1999) J. Cell. Biochem., 72 (1), pp. 81-93; Yamaguchi, A., Regulation of differentiation pathway of skeletal mesenchymal cells in cell-lines by transforming growth-factor-beta superfamily (1995) Semin. Cell Biol., 6 (3), pp. 165-173; Yamaguchi, A., Ishizuya, T., Kintou, N., Wada, Y., Katagiri, T., Wozney, J.M., Rosen, V., Yoshiki, S., Effects of BMP-2, BMP-4, and BMP-6 on osteoblastic differentiation of bone marrow-derived stromal cell lines, ST2 and MC3T3-G2/PA6 (1996) Biochem. Biophys. Res. Commun., 220 (2), pp. 366-371; Baltzer, A.W.A., Lattermann, C., Whalen, J.D., Wooley, P., Weiss, K., Grimm, M., Ghivizzani, S.C., Evans, C.H., Genetic enhancement of fracture repair: healing of an experimental segmental defect by adenoviral transfer of the BMP-2 gene (2000) Gene Ther., 7 (9), pp. 734-739; Wang, E.A., Rosen, V., Dalessandro, J.S., Bauduy, M., Cordes, P., Harada, T., Israel, D.I., Wozney, J.M., Recombinant human bone morphogenetic protein induces bone-formation (1990) Proc. Natl. Acad. Sci. U. S. A., 87 (6), pp. 2220-2224; Chuang, C.K., Sung, L.Y., Hwang, S.M., Lo, W.H., Chen, H.C., Hu, Y.C., Baculovirus as a new gene delivery vector for stem cell engineering and bone tissue engineering (2007) Gene Ther., 14 (19), pp. 1417-1424; Aslan, H., Zilberman, Y., Arbeli, V., Sheyn, D., Matan, Y., Liebergall, M., Li, J.Z., Gazit, Z., Nucleofection-based ex vivo nonviral gene delivery to human stem cells as a platform for tissue regeneration (2006) Tissue Eng., 12 (4), pp. 877-889; Noel, D., Gazit, D., Bouquet, C., Apparailly, F., Bony, C., Plence, P., Millet, V., Jorgensen, C., Short-term BMP-2 expression is sufficient for in vivo osteochondral differentiation of mesenchymal stem cells (2003) Stem Cells, 22 (1), pp. 74-85
Keywords: alkaline phosphatase; amine; Amines; animal cell; Animals; article; beta galactosidase; beta-Galactosidase; Bone; Bone morphogenetic protein; bone morphogenetic protein 2; Bone Regeneration; Calcium; Cell culture; cell differentiation; Cell Line; cell lineage; cell survival; Cells; Cells, Cultured; controlled study; dendrimer; Dendrimers; embryo; enzyme activity; Flowcharting; gene expression; Gene transfer; Gene Transfer Techniques; gene vector; Genes, Reporter; genetic transfection; human; human cell; Humans; in vitro study; Kidney; male; Mesenchymal stem cell; Mesenchymal Stem Cells; nonhuman; Nonviral gene delivery; nonviral gene delivery system; Nucleic acids; osteoblast; osteocalcin; Osteogenesis; PAMAM dendrimers; phosphate; plasmid; Plasmids; polyamidoamine; Polyamines; priority journal; protein secretion; Proteins; qualitative analysis; quantitative analysis; rat; Rats; Rats, Wistar; reporter gene; staining

Physical, chemical and in vitro biological profile of chitosan hybrid membrane as a function of organosiloxane concentration - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Costa, M.A.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2009)
We attempted to prepare chitosan-silicate hybrid for use in a medical application and evaluated the physico-chemical properties and osteocompatibility of the hybrids as a function of γ-glycidoxypropyltrimethoxysilane (GPTMS) concentration. Chitosan-silicate hybrids were synthesized using GPTMS as the reagent for cross-linking of the chitosan chains. Fourier transform infrared spectroscopy, 29Si CP-MAS NMR spectroscopy and the ninhydrin assay were used to analyze the structures of the hybrids, and stress-strain curves were recorded to estimate their Young's modulus. The swelling ability, contact angle and cytocompatibility of the hybrids were investigated as a function of the GPTMS concentration. A certain fraction of GPTMS in each hybrid was linked at the epoxy group to the amino group of chitosan, which was associated with the change in the methoxysilane group of GPTMS due to hybridization. The cross-linking density was around 80% regardless of the volume of GPTMS. As the content of GPTMS increased, the water uptake decreased and the hydrophilicity of the hybrids increased except when the content exceeded amolar ratio of 1.5, when it caused a decrease. The values of the mechanical parameters assessed indicated that significant stiffening of the hybrids was obtained by the addition of GPTMS. The adhesion and proliferation of the MG63 osteoblast cells cultured on the chitosan-GPTMS hybrid surface were improved compared to those on the chitosan membrane, regardless of the GPTMS concentration. Moreover, human bone marrow osteoblast cells proliferated on the chitosan-GPTMS hybrid surface and formed a fibrillar extracellular matrix with numerous calcium phosphate globular structures, both in the presence and in the absence of dexamethasone. Therefore, the chitosan-GPTMS hybrids are promising candidates for basic materials that can promote bone regeneration because of their controllable composition (chitosan/GPTMS ratio). © 2008 Acta Materialia Inc.
Cited By (since 1996): 10Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2008.07.022PubMed ID: 18722166Language of Original Document: EnglishCorrespondence Address: Hayakawa, S.; Biomaterial Laboratory, Graduate School of Natural Science and Technology, Okayama University, Tsushima, Okayama-shi, 700-8530, Japan; email: satoshi@cc.okayama-u.ac.jpChemicals/CAS: (3 glycidyloxypropyl)trimethoxysilane, 2530-83-8; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; chitosan, 9012-76-4; silicate, 12627-13-3; Chitosan, 9012-76-4; Cross-Linking Reagents; gamma-glycidoxypropyltrimethoxysilane, 2530-83-8; Silanes; SiloxanesTradenames: AldrichReferences: Lai, J.Y., Lin, F.C., Wang, C.C., Wang, D.M., Effect of nonsolvent additives on the porosity and morphology of asymmetric TPX membranes [J] (1996) J Membrane Sci, 118, pp. 49-61;Wang, D.M., Lin, F.C., Chiang, J.C., Lai, J.Y., Control of porosity of asymmetric TPX membranes [J] (1998) J Membrane Sci, 141, pp. 1-12; Piattelli, A., Scarano, A., Russo, P., Matarasso, S., Evaluation of guided bone regeneration in rabbit tibia using bioresorbable and non-resorbable membranes (1996) Biomaterials, 17 (8), pp. 791-796; Gotfredsen, K., Nimb, L., Hjorting-Hansen, E., Immediate implant placement using a biodegradable barrier, polyhydroxybutyratehydroxyvalerate reinforced with polyglactin 910: an experimental study in dogs (1994) Clin Oral Implants Res, 5 (2), pp. 83-91; Kostopoulos, L., Karring, T., Augmentation of the rat mandible using guided tissue regeneration (1994) Clin Oral Implants Res, 5 (2), pp. 75-82; Kostopoulos, L., Karring, T., Guided bone regeneration in mandibular defects in rats using a bioresorbable polymer (1994) Clin Oral Implants Res, 5 (2), pp. 666-674; Nyman, S., Gottlow, J., Karring, T., The regeneration potential of the periodontal ligament: an experimental study in the monkey (1982) J Clin Periodontal, 9, pp. 257-265; Dupoirieux, L., Pourquier, D., Picot, M.C., Neves, M., Comparative study of three different membranes for guided bone regeneration of rat cranial defects (2001) Int J Oral Maxillofac Surg, 30 (1), pp. 58-62; Zhang, R., Ma, P.X., Porous poly(l-lactic acid)/apatite composites created by biomimetic process (1999) J Biomed Mater Res, 45, pp. 285-293; Murphy, W.L., Kohn, D.H., Mooney, D.J., Growth of continuous bonelike mineral within porous poly(lactide-co-glycolide) scaffolds in vitro (2000) J Biomed Mater Res, 50, pp. 50-58; Lin, F.C., Wang, D.M., Lai, J.Y., Asymmetric TPX membranes. J membranes with high gas flux. (1996) J Membrane Sci, 110, pp. 25-36; Vert, M., Mauduit, J., Li, S., Biodegradation of PLA/GA polymers: increasing complexity (1994) Biomaterials, 15, pp. 1209-1213; Lee, Y.K., Mooney, D.J., Hydrogels for tissue enigineering (2001) Chem Rev, 101, pp. 1869-1879; Domard, A., Rinaudo, M., Preparation and characterization fully deacetylated chitosan (1983) Int J Biol Macromol, 5, pp. 49-52; Chandy, T., Sharma, P.C., Chitosan - as a biomaterial (1990) Biomater Artif Cells Artif Organo, 18, pp. 1-24; Ueno, H., Yamada, H., Tanaka, I., Kaba, N., Matsuura, M., Okumura, M., Accelerating effects of chitosan for healing at early phase of experimental open wound in dogs (1999) Biomaterials, 20, pp. 1407-1414; Muzzareli, R.A.A., Mattioli-Belmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Stimulatory effect on bone formation exerted by a modified chitosan (1994) Biomaterials, 15, pp. 1075-1081; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., In vitro cytocompatibility of MG63 cells on chitosan-organosiloxane hybrid membranes (2005) Biomaterials, 26, pp. 485-493; Prochazkova, S., Varum, K.M., Æstgaard. Quantitative determination of chitosans by ninhydrin (1999) Carbohydr Polym, 38, pp. 115-122; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Coelho, M.J., Cabral, A.T., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in D-MEM (2000) Biomaterials, 21, pp. 1087-1094; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethhylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT): subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Argüelles-Monal, W., Desbriéres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Sol-gel preparation and in vitro deposition of apatite on porous gelatin-siloxane hybrids (2001) J Non Cryst Solid, 285, pp. 116-122; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Novel approach to fabricate porous gelatin-siloxane hybrids for bone tissue engineering (2002) Biomaterials, 23, pp. 4765-4773; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Incorporation of Ca 2+ ions in gelatin-siloxane hybrids through a sol-gel process (2001) J Ceram Soc Jpn, 109, pp. 403-408; Rashidova, S.S.h., Shakarova, D.S.h., Ruzimuradov, O.N., Satabaldieva, D.T., Zalyalieva, S.V., Shpigun, O.A., Bionanocompositional chitosan-silica sorbent for liquid chromatography (2004) J Chromatogr B, 800, pp. 49-53; Hench, L.L., Ethridge, E.C., (1982) Biomaterials an interfacial approach, , Academic Press, New York 10; Xynos, I.D., Hukkanen, M.V.J., Batten, J.J., Buttery, L.D., Hench, L.L., Polak, J.M., Bioglass ® 45S5 stimulates osteoblast turnover and enhances bone formation in vitro: implications and applications for bone tissue engineering (2000) Calcif Tissue Int, 67, pp. 321-329; Xynos, I.D., Edgar, A.J., Buttery, L.D.K., Hench, L.L., Ionic products of bioactive glass dissolution increase proliferation of human osteoblasts and induce insulin-like growth factor II mRNA expression and protein synthesis (2000) Biochem Biophys Res Commun, 276, pp. 461-465; Gough, J.E., Jones, J.R., Hench, L.L., Nodule formation and mineralisation of human primary osteoblasts cultured on a porous bioactive glass scaffold (2004) Biomaterials, 25, pp. 2039-2046; Maniatopoulos, C., Sodek, J., Melcher, A., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralization in serially passaged human alveolar bone cells (1997) J Mater Sci Mater Med, 8, pp. 61-65; Costa, M.A., Gutierres, M., Almeida, L., Lopes, M.A., Santos, J.D., Fernandes, M.H., In vitro mineralization of human bone marrow cells cultured on Bonelike ® (2004) Key Eng Mater, 254-256, pp. 821-824
Keywords: (3 glycidyloxypropyl)trimethoxysilane; article; assay; Biocompatibility; Bone Marrow Cells; calcium phosphate; cell adhesion; Cell Line, Tumor; cell proliferation; cell survival; cell viability; Chemical analysis; chitosan; concentration (parameters); controlled study; cross linking; Cross-Linking Reagents; extracellular matrix; human; human cell; Humans; hydrophobicity; in vitro study; infrared spectroscopy; Magnetic Resonance Spectroscopy; Microscopy, Electron, Scanning; molecular hybridization; Nuclear magnetic resonance spectroscopy; Organic-inorganic hybrid; osteoblast; Osteoblasts; Osteocompatibility; physical chemistry; priority journal; Silanes; silicate; siloxane; Siloxanes; Spectrophotometry, Ultraviolet; Spectroscopy, Fourier Transform Infrared; stress strain relationship; structure analysis; surface property; Tissue engineering; unclassified drug; water transport; γ-Glycidoxypropyltrimethoxysilane (GPTMS)

Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals - Costa, A.; Ayres-de-Campos, D.; Costa, F.; Santos, C.; Bernardes, J. (American Journal of Obstetrics and GynecologyAm. J. Obstet. Gynecol., 2009)
Objective: The objective of the study was to evaluate the accuracy of computer analysis of fetal heart rate (FHR) and ST event signals in prediction of neonatal acidemia. Study Design: One hundred forty-eight FHR tracings were evaluated to identify red alerts provided by the system, based on automated analysis of FHR and ST event signals, and compared with the occurrence of umbilical artery acidemia (pH ≤7.05). Results: The presence of red alerts obtained sensitivity of 1.00 (95% confidence interval [CI], 0.56-1.00), specificity of 0.94 (95% CI, 0.89-0.97), positive predictive value (PPV) of 0.47 (95% CI, 0.22-0.72), negative predictive value (NPV) of 1 (95% CI, 0.96-1.00), positive likelihood ratio (PLR) of 17.6 (95% CI, 9.0-34.5), and negative likelihood ratio (NLR) of 0. When limiting analysis to red alerts that did not include ST data, sensitivity was 0.57 (95% CI, 0.20-0.88), specificity was 0.97 (95% CI, 0.92-0.99), PPV was 0.50 (95% CI, 0.17-0.82), NPV was 0.98 (95% CI, 0.93-0.99), PLR was 20.14 (95% CI, 6.3-64.2), and NLR was 0.44 (95% CI, 0.19-1.04). Conclusion: Computer analysis of FHR and ST event signals provide higher accuracy in predicting neonatal academia. © 2009 Mosby, Inc. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: AJOGAdoi: 10.1016/j.ajog.2009.04.033PubMed ID: 19539895Language of Original Document: EnglishCorrespondence Address: Costa, A.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina, Hospital S. JoãoPortugal; email: cosantonia@gmail.comReferences: (2006) Perinatal Mortality Surveillance 2004: England, Wales, and Northern Ireland, , CEMACH (Confidential Enquiry into Maternal and Child Health), Confidential Enquiry into Maternal and Child Health, London, UK;(1997) 4th annual report, , CESDI (Confidential Enquiry into Stillbirths and Deaths in Infancy), Maternal and Child Health Research Consortium, London, UK; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-165; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Donker, D.K., van Geijn, H.P., Hasman, A., Interobserver variation in the assessment of fetal heart rate recordings (1993) Eur J Obstet Gynecol Reprod Biol, 52, pp. 21-28; Neilson, J.P., Fetal electrocardiogram (ECG) for fetal monitoring during labour (2006) Cochrane Database Syst Rev, 3; Doria, V., Papageorghiou, A., Gustafsson, A., Ugwumadu, A., Farrer, K., Arulkumaran, S., Review of the first 1502 cases of ECG-ST waveform analysis during labour in a teaching hospital (2007) BJOG, 114, pp. 1202-1207; Westerhuis, M., Kwee, A., van Ginkel, A., Drogtrop, A., Gyselaers, W., Visser, G., Limitations of ST analysis in clinical practice: three cases of intrapartum metabolic acidosis (2007) BJOG, 114, pp. 1194-1201; Amer-Wahlin, I., Arulkumaran, S., Hagberg, H., Marsal, K., Visser, G., Fetal electrocardiogram: ST waveform analysis in intrapartum surveillance (2007) BJOG, 114, pp. 1191-1193; Dawes, G.S., Redman, C.W., Smith, J.H., Improvements in the registration and analysis of fetal heart rate records at the bedside (1985) Br J Obstet Gynaecol, 92, pp. 317-325; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: the antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60. , SisPorto Multicentre Validation Study Group; Dawes, G.S., Moulden, M., Redman, C.W.G., System 8000: computerized antenatal FHR analysis (1991) J Perinat Med, 19, pp. 47-51; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, J.P., Pereira-Leite, L., SisPorto 2.0-a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto® 3.5-a central fetal monitoring station with online alerts based on computerized cardiotocogram+S.T.event analysis (2008) J Perinat Med, 36, pp. 260-264; Ayres-de-Campos, D., Bernardes, J., Kwee, A., Westehuis, M., Visser, G.H.A., Computer quantification of short-term variability as an adjunct to fetal electrocardiographic monitoring (2007) BJOG, 114, pp. 1446-1447; Downing, J.W., Houlton, P.C., Barclay, A., Extradural analgesia for cesarean section: a comparison with general anesthesia (1979) Br J Anaesth, 51, pp. 367-374; Crawford, J.S., James, F.M., Davies, P., Crawley, M., A further study of general anaesthesia for cesarean section (1976) Br J Anaesth, 48, pp. 661-667; Huch, A., Huch, C., Rooth, G., Guidelines for blood sampling and measurement of pH and blood gas values in obstetrics (1994) Eur J Obstet Gynecol Reprod Biol, 54, pp. 165-175; ACOG technical bulletin. Umbilical artery blood acid-base analysis (1996) Int J Gynecol Obstet, 52, pp. 305-310; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: a time for quality data (1994) Br J Obstet Gynaecol, 101, pp. 1054-1063; Low, J.A., Intrapartum fetal asphyxia: definition, diagnosis and classification (1997) Am J Obstet Gynecol, 176, pp. 957-959; Fleiss, J.L., (1981) Statistical methods for rates and proportions. 2nd ed., , John Wiley & Sons, New York, NY Section 5.6; Keith, R.D., Beckley, S., Garibaldi, J.M., Westgate, J.A., Ifeachor, E.C., Greene, K.R., A multicentre comparative study of 17 experts and an intelligent computer system for managing labour using cardiotocogram (1995) Br J Obstet Gynecol, 102, pp. 668-700; Chung, T.K., Mohajer, M.P., Yang, Z.j., Chang, A.M., Sahota, D.S., The prediction of fetal acidosis at birth by computerised analysis of intrapartum cardiotocography (1995) Br J Obstet Gynaecol, 102, pp. 454-460; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. II. The value of computer assessment compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464; Policy statement. The Apgar score-American Academy of Pediatrics and American College of Obstetricians and Gynecologists (2006) Pediatrics, 117, pp. 1444-1447; Casey, B.M., McIntire, D.D., Leveno, K.J., The continuing value of the Apgar score for the assessment of the newborn infants (2001) N Engl J Med, 334, pp. 467-471; Moster, D., Lie, R.T., Irgens, L.M., Bjerkedal, T., Markestad, The association of Apgar score with subsequent death and cerebral palsy: a population-based study in term infants (2001) J Pediatr, 138, pp. 798-803
Keywords: acidemia; Acidosis; article; autoanalysis; Cardiotocography; computer analysis; computer assisted; computer prediction; Diagnosis, Computer-Assisted; diagnostic value; Electrocardiography; Female; Fetal heart rate; Fetal hypoxia; Fetal monitoring; fetus electrocardiography; fetus heart rate; Heart Rate, Fetal; human; Humans; Infant, Newborn; major clinical study; male; newborn; newborn acidosis; observational study; pH; Predictive Value of Tests; priority journal; Prospective Studies; prospective study; Reproducibility of Results; sensitivity and specificity; signal transduction; ST segment; umbilical artery

Protein adsorption and clotting time of pHEMA hydrogels modified with C18 ligands to adsorb albumin selectively and reversibly - Gonçalves, I.C.; Martins, M.C.L.; Barbosa, M.A.; Ratner, B.D. (BiomaterialsBiomaterials, 2009)
This work intended to create a nanostructured biomaterial that would bind albumin in a selective and reversible way in order to inhibit the adsorption of other blood proteins and therefore minimize activation of coagulation. Different levels of C18 ligand have been immobilized on poly(2-hydroxyethyl methacrylate) (pHEMA). We hypothesize that samples with intermediate amounts of C18 ligand would allow albumin to recognize them and bind through its hydrophobic pockets specific for long chain fatty acids. Surface characterization has confirmed increasing amounts of C18 ligand on pHEMA as the percentage of C18 in solution increases, with maximum coverage achieved in 10% C18 samples. Adsorption from pure albumin solution revealed a small decrease in albumin adsorption from pHEMA to 1% C18 and 2.5% C18 samples, but on surfaces with 5% or higher C18 the amount of adsorbed albumin increased as the percentage of C18 increased. Competitive adsorption studies in the presence of both albumin and fibrinogen, and in the presence of all plasma proteins showed that 1% C18 and 2.5% C18 were the only surfaces selective for albumin, and that the presence of all plasma proteins may even potentiate albumin adsorption. Reversibility studies demonstrated that both 2.5% C18 and 5% C18 samples exchange 125I-albumin selectively in the presence of both unlabeled albumin and plasma, but 2.5% C18 samples presented higher exchangeability rates (58%). Clotting times using recalcified plasma revealed that samples with none or small amounts of C18 (pHEMA to 5% C18) did not shorten the clotting time compared to the negative control (polystyrene), indicating low activation of the intrinsic coagulation cascade. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.06.025PubMed ID: 19595453Language of Original Document: EnglishCorrespondence Address: Gonçalves, I.C.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: icastro@ineb.up.ptChemicals/CAS: fibrinogen, 9001-32-5; human serum albumin, 9048-49-1; polymacon, 25053-81-0, 25249-16-5, 98932-78-6; polystyrene, 9003-53-6; Biocompatible Materials; Coated Materials, Biocompatible; Hydrogels; Polyhydroxyethyl Methacrylate, 25249-16-5; Serum AlbuminReferences: Kottkemarchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., Effect of albumin coating on the in vitro blood compatibility of dacron arterial prostheses (1989) Biomaterials, 10 (3), pp. 147-155;Ji, J., Feng, L.X., Barbosa, M.A., Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin (2001) Biomaterials, 22 (22), pp. 3015-3023; Keogh, J.R., Eaton, J.W., Albumin-binding surfaces for biomaterials (1994) The Journal of Laboratory and Clinical Medicine, 124 (4), pp. 537-545; Keogh, J.R., Velander, F.F., Eaton, J.W., Albumin-binding surfaces for implantable devices (1992) Journal of Biomedical Materials Research, 26 (4), pp. 441-456; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., Albumin and fibrinogen adsorption on Cibacron blue F3G-A immobilised onto PU-PHEMA (polyurethane-poly(hydroxyethylmethacrylate)) surfaces (2003) Journal of Biomaterials Science Polymer Edition, 14 (5), pp. 439-455; McFarland, C.D., De Filippis, C., Jenkins, M., Tunstell, A., Rhodes, N.P., Williams, D.F., Albumin-binding surfaces: in vitro activity (1998) Journal of Biomaterials Science Polymer Edition, 9 (11), pp. 1227-1239; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., Alkyl substituted polymers with enhanced albumin affinity (1981) Transactions American Society for Artificial Internal Organs, 27, pp. 499-503; Tsai, C.C., Huo, H.H., Kulkarni, P., Eberhart, R.C., Biocompatible coatings with high albumin affinity (1990) ASAIO Transactions, 36 (3), pp. 307-310; Wang, D.A., Chen, B.L., Ji, J., Feng, L.X., Selective adsorption of serum albumin on biomedical polyurethanes modified by a poly(ethylene oxide) coupling-polymer with Cibacron blue (F3G-A) endgroups (2002) Bioconjugate Chemistry, 13 (4), pp. 792-803; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Naeemi, E., Ratner, B.D., Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands (2009) Journal of Biomedical Materials Research Part A, 89 A (3), pp. 642-653; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) Journal of the American Chemical Society, 111 (1), pp. 321-335; Kwok, S.C., Mourad, P.D., Crum, L.A., Ratner, B.D., Surface modification of polymers with self-assembled molecular structures: multitechnique surface characterization (2000) Biomacromolecules, 1, pp. 139-148; Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption on 18-alkyl chains immobilized on hydroxyl-terminated self-assembled monolayers (2005) Biomaterials, 26 (18), pp. 3891-3899; Ratner, B.D., Hoffman, A.F., Schoen, F.J., Lemons, J.L., (2004) Biomaterials science - an introduction to materials in medicine. 2nd ed., , Elsevier Academic Press, San Diego, CA, USA; Ratner, B.D., Miller, I.F., Interaction of urea with poly(2-hydroxyethyl methacrylate) hydrogels (1972) Journal of Polymer Science Part a-1-Polymer Chemistry, 10 (8), pp. 2425-2445; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of biocompatibility testing, pp. 183-214. , Williams D.F. (Ed), Harcover: CRC Press; Cao, L., Chang, M., Lee, C.Y., Castner, D.G., Sukavaneshvar, S., Ratner, B.D., Plasma-deposited tetraglyme surfaces greatly reduce total blood protein adsorption, contact activation, platelet adhesion, platelet procoagulant activity, and in vitro thrombus deposition (2007) Journal of Biomedical Materials Research Part A, 81 (4), pp. 827-837; Stovbun, E.V., Kuzaev, A.I., Baturin, S.M., (1996) Polymer Science Series A, 38, pp. 691-695; Tanaka, M., Motomura, T., Kawada, M., Anzai, T., Yuu, K., Shiroya, T., Blood compatible aspects of poly(2-methoxyethylacrylate) (PMEA) - relationship between protein adsorption and platelet adhesion on PMEA surface (2000) Biomaterials, 21 (14), pp. 1471-1481; Castner, D.G., Ratner, B.D., Hirao, A., Nakahama, S., Characterization of poly(2-hydroxyethyl methacrylate) (PHEMA) by XPS (1996) Surface Science Spectra, 4 (1-4), p. 14; López, G.P., Ratner, B.D., Rapoza, R.J., Horbett, T.A., Plasma deposition of ultrathin films of poly(2-hydroxyethyl methacrylate): surface analysis and protein adsorption measurements (1993) Macromolecules, 26 (13), pp. 3247-3253; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., Albumin and fibrinogen adsorption on PU-PHEMA surfaces (2003) Biomaterials, 24 (12), pp. 2067-2076; Tsukagoshi, T., Kondo, Y., Yoshino, N., Protein adsorption on polymer-modified silica particle surface (2007) Colloids and Surfaces B Biointerfaces, 54 (1), pp. 101-107; Ratner, B.D., Biomedical applications of hydrogels: review and critical appraisal (1981) Biocompatibility of clinical implant materials, , Williams D.F. (Ed), CRC Press; Höök, F., Vörös, J., Rodahl, M., Kurrat, R., Böni, P., Ramsden, J.J., A comparative study of protein adsorption on titanium oxide surfaces using in situ ellipsometry, optical waveguide lightmode spectroscopy, and quartz crystal microbalance/dissipation (2002) Colloids and Surfaces B Biointerfaces, 24 (2), pp. 155-170; Stryer, L., (1998) Biochemistry. 4th ed., , WH Freeman, New York; Garrett, Q., Chatelier, R.C., Griesser, H.J., Milthorpe, B.K., Effect of charged groups on the adsorption and penetration of proteins onto and into carboxymethylated poly(HEMA) hydrogels (1998) Biomaterials, 19 (23), pp. 2175-2186; Mequanint, K., Sheardown, H., 2-Methacryloyloxyethyl N-butylcarbamate: a new co-monomer for synthesis of polyurethane hydrogels with improved mechanical properties for biomedical applications (2005) Journal of Biomaterials Science Polymer Edition, 16 (10), pp. 1303-1318; Horbett, T.A., Adsorption of proteins from plasma to a series of hydrophilic-hydrophobic copolymers. II. Compositional analysis with the prelabeled protein technique (1981) Journal of Biomedical Materials Research, 15 (5), pp. 673-695; Feng, L., Andrade, J.D., Protein adsorption on low-temperature isotropic carbon. 3. isotherms, competitivity, desorption and exchange of human albumin and fibrinogen (1994) Biomaterials, 15 (5), pp. 323-333; Pitt, W.G., Cooper, S.L., Albumin adsorption on alkyl chain derivatized polyurethanes. 1. The effect of C-18 alkylation (1988) Journal of Biomedical Materials Research, 22 (5), pp. 359-382; Markiewski, M.M., Nilsson, B., Ekdahl, K.N., Mollnes, T.E., Lambris, J.D., Complement and coagulation: strangers or partners in crime? (2007) Trends in Immunology, 28 (4), pp. 184-192; Zhang, Z., Zhang, M., Chen, S., Horbett, T.A., Ratner, B.D., Jiang, S., Blood compatibility of surfaces with superlow protein adsorption (2008) Biomaterials, 29 (32), pp. 4285-4291; Grunkemeier, J.M., Tsai, W.B., Horbett, T.A., Hemocompatibility of treated polystyrene substrates: contact activation, platelet adhesion, and procoagulant activity of adherent platelets (1998) Journal of Biomedical Materials Research, 41 (4), pp. 657-670; Gorbet, M.B., Sefton, M.V., Biomaterial-associated thrombosis: roles of coagulation factors, complement, platelets and leukocytes (2004) Biomaterials, 25 (26), pp. 5681-5703
Keywords: Adsorption; article; Biocompatible Materials; Biomaterials; blood clotting time; Blood Coagulation Tests; Body fluids; Clotting time; Coagulation; Coated Materials, Biocompatible; concentration response; controlled study; Fatty acids; fibrinogen; human serum albumin; hydrogel; Hydrogels; hydrophilicity; Ligands; long chain fatty acid; materials testing; Plasmas; PolyHEMA; Polyhydroxyethyl Methacrylate; polymacon; Polymer blends; polystyrene; Polystyrenes; priority journal; Protein adsorption; protein binding; Proteins; Serum Albumin; Surface modification; surface property; Surface treatment

Role of vascular endothelial growth factor in the communication between human osteoprogenitors and endothelial cells - Grellier, M.; Ferreira-Tojais, N.; Bourget, C.; Bareillke, R.; Guillemot, F.; Amédée, J. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2009)
Proper bone remodeling requires an active process of angiogenesis which in turn supplies the necessary growth factors and stem cells. This tissue cooperation suggests a cross-talk between osteoblasts and endothelial cells. This work aims to identify the role of paracrine communication through vascular endothelial growth factor (VEGF) in co-culture between osteoblastic and endothelial cells. Through a well defined direct contact co-culture model between human osteoprogenitors (HOPs) and human umbilical vein endothelial cells (HUVECs), we observed that HUVECs were able to migrate along HOPs, inducing the formation of specific tubular-like structures. VEGF 165 gene expression was detected in the HOPs, was up-regulated in the co-cultured HOPs and both Fit-1 and KDR gene expression increased in co- cultured HUVECs. However, the cell rearrangement observed in co-culture was promoted by a combination of soluble chemoattractive factors and not by VEGF 165 alone. Despite having no observable effect on endothelial cell tubular-like formation, VEGF appeared to have a crucial role in osteoblastic differentiation since the inhibition of its receptors reduced the co-culture-stimulated osteoblastic phenotype. This co-culture system appears to enhance both primary angiogenesis events and osteoblastic differentiation, thus allowing for the development of new strategies in vascularized bone tissue engineering. © 2009 Wiley-Liss, Inc.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: JCEBDdoi: 10.1002/jcb.22018Language of Original Document: EnglishCorrespondence Address: Grellier, M.; 146 Rue Leo Saignat, Zone Nord, Bat 4A, Case 45, F-33076 Bordeaux Cedex, France; email: maritie.grellier@inserm.frMolecular Sequence Numbers: GENBANK: AB021221, AF063657, AF063658, BC015690, BC021289, NM_000089;Chemicals/CAS: vasculotropin A, 489395-96-2; vasculotropin receptor, 301253-48-5; Receptors, Vascular Endothelial Growth Factor, EC 2.7.1.112; RNA, Messenger; Vascular Endothelial Growth Factor AReferences: Bordenave, L., Baquey, C., Bareille, R., Lefebvre, F., Lauroua, C., Guerin, V., Rouais, F., Anderson, J.M., Endothelial cell compatibility testing of three different Pellethanes (1993) J Biomed Mater Res, 27, pp. 1367-1381;Bouletreau, P.J., Warren, S.M., Spector, J.A., Peled, Z.M., Gerrets, R.P., Greenwald, J.A., Longaker, M.T., Hypoxia and VEGF up-regulate BMP-2 mRNA and protein expression in microvascular endothelial cells: Implications for fracture healing (2002) Plast Reconstr Surg, 109, pp. 2384-2397; Carano, R.A., Filvaroff, E.H., Angiogenesis and bone repair (2003) Drug Discov Today, 8, pp. 980-989; Carmeliet, P., Collen, D., Molecular basis of angiogenesis. Role of VEGF and VE-cadherin (2000) Ann NY Acad Sci, 902, pp. 249-262. , discussion 262-264; Clarkin, C.E., Emery, R.J., Pitsillides, A.A., Wheeler-Jones, C.P., Evaluation of VEGF-mediated signaling in primary human cells reveals a paracrine action for VEGF in osteoblast-mediated crosstalk to endothelial cells (2007) J Cell Physiol, 214, pp. 437-444; Cross, M.J., Claesson-Welsh, L., FGF and VEGF function in angiogenesis: Signalling pathways, biological responses and therapeutic inhibition (2001) Trends Pharmacol Sci, 22, pp. 201-207; Cross, M.J., Dixelius, J., Matsumoto, T., Claesson-Welsh, L., VEGF-receptor signal transduction (2003) Trends Biochem Sci, 28, pp. 488-494; Dallas, S.L., Rosser, J.L., Mundy, G.R., Bonewald, L.F., Proteolysis of latent transforming growth factor-beta (TGF-beta)-binding protein-1 by osteoclasts. A cellular mechanism for release of TGF-beta from bone matrix (2002) J Biol Chem, 277, pp. 21352-21360; Ferrara, N., Gerber, H.P., LeCouter, J., The biology of VEGF and its receptors (2003) Nat Med, 9, pp. 669-676; Fiedler, J., Leucht, F., Waltenberger, J., Dehio, C., Brenner, R.E., VEGF-A and P1GF-1 stimulate chemotactic migration of human mesenchymal progenitor cells (2005) Biochem Biophys Res Commun, 334, pp. 561-568; Gerber, H.P., Ferrara, N., Angiogenesis and bone growth (2000) Trends Cardiovasc Med, 10, pp. 223-228; Gerhardt, H., Golding, M., Fruttiger, M., Ruhrberg, C., Lundkvist, A., Abramsson, A., Jeltsch, M., Betsholtz, C., VEGF guides angiogenic sprouting utilizing endothelial tip cell filopodia (2003) J Cell Biol, 161, pp. 1163-1177; Guillotin, B., Bourget, C., Remy-Zolgadri, M., Bareille, R., Fernandez, P., Conrad, V., Amedee-Vilamitjana, J., Human primary endothelial cells stimulate human osteoprogenitor cell differentiation (2004) Cell Physiol Biochem, 14, pp. 325-332; Guillotin, B., Bareille, R., Bourget, C., Bordenave, L., Amedee, J., Interaction between human umbilical vein endothelial cells and human osteoprogenitors triggers pleiotropic effect that may support osteoblastic function (2008) Bone, 42, pp. 1080-1091; Jaffe, E.A., Culture of human endothelial cells (1980) Transplant Proc, 12, pp. 49-53; Lamalice, L., Le Boeuf, F., Huot, J., Endothelial cell migration during angiogenesis (2007) Circ Res, 100, pp. 782-794; Lampugnani, M.G., Orsenigo, F., Gagliani, M.C., Tacchetti, C., Dejana, E., Vascular endothelial cadherin controls VEGFR-2 internalization and signaling from intracellular compartments (2006) J Cell Biol, 174, pp. 593-604; Lebrin, F., Deckers, M., Bertolino, P., Ten Dijke, P., TGF-beta receptor function in the endothelium (2005) Cardiovasc Res, 65, pp. 599-608; Mayr-Wohlfart, U., Waltenberger, J., Hausser, H., Kessler, S., Gunther, K.P., Dehio, C., Puhl, W., Brenner, R.E., Vascular endothelial growth factor stimulates chemotactic migration of primary human osteoblasts (2002) Bone, 30, pp. 472-477; Miralem, T., Steinberg, R., Price, D., Avraham, H., VEGF(165) requires extracellular matrix components to induce mitogenic effects and migratory response in breast cancer cells (2001) Oncogene, 20, pp. 5511-5524; Neufeld, G., Cohen, T., Gengrinovitch, S., Poltorak, Z., Vascular endothelial growth factor (VEGF) and its receptors (1999) FASEB J, 13, pp. 9-22; Ortega, N., Behonick, D., Stickens, D., Werb, Z., How proteases regulate bone morphogenesis (2003) Ann NY Acad Sci, 995, pp. 109-116; Rousseau, S., Houle, F., Huot, J., Integrating the VEGF signals leading to actin-based motility in vascular endothelial cells (2000) Trends Cardiovasc Med, 10, pp. 321-327; Sorrell, J.M., Baber, M.A., Caplan, A., Human dermal fibroblast subpo- pulations; differential interactions with vascular endothelial cells in coculture: Nonsoluble factors in the extracellular matrix influence interactions (2008) Wound Repair Regen, 16, pp. 300-309; Street, J., Bao, M., deGuzman, L., Bunting, S., Peale Jr., F.V., Ferrara, N., Steinmetz, H., Filvaroff, E.H., Vascular endothelial growth factor stimulates bone repair by promoting angiogenesis and bone turnover (2002) Proc Natl Acad Sci USA, 99, pp. 9656-9661; Suarez, S., Ballmer-Hofer, K., VEGF transiently disrupts gap junctional communication in endothelial cells (2001) J Cell Sci, 114, pp. 1229-1235; Sun, L., Vitolo, M., Passaniti, A., Runt-related gene 2 in endothelial cells: Inducible expression and specific regulation of cell migration and invasion (2001) Cancer Res, 61, pp. 4994-5001; Unger, R.E., Sartoris, A., Peters, K., Motta, A., Migliaresi, C., Kunkel, M., Bulnheim, U., Kirkpatrick, C.J., Tissue-like self-assembly in cocultures of endothelial cells and osteoblasts and the formation of microcapillary-like structures on three-dimensional porous biomaterials (2007) Biomaterials, 28, pp. 3965-3976; Villars, F., Bordenave, L., Bareille, R., Amedee, J., Effect of human endothelial cells on human bone marrow stromal cell phenotype: Role of VEGF? (2000) J Cell Biochem, 79, pp. 672-685; Villars, F., Guillotin, B., Amedee, T., Dutoya, S., Bordenave, L., Bareille, R., Amedee, J., Effect of HUVEC on human osteoprogenitor cell differentiation needs heterotypic gap junction communication (2002) Am J Physiol Cell Physiol, 282, pp. C775-C785; Walker, D.L., Vacha, S.J., Kirby, M.L., Lo, C.W., Connexin43 deficiency causes dysregulation of coronary vasculogenesis (2005) Dev Biol, 284, pp. 479-498; Wang, H., Keiser, J.A., Vascular endothelial growth factor upregulates the expression of matrix metalloproteinases in vascular smooth muscle cells: Role of flt-1 (1998) Circ Res, 83, pp. 832-840; Wang, D.S., Miura, M., Demura, H., Sato, K., Anabolic effects of 1,25- dihydroxyvitamin D3 on osteoblasts are enhanced by vascular endothelial growth factor produced by osteoblasts and by growth factors produced by endothelial cells (1997) Endocrinology, 138, pp. 2953-2962; Xin, X., Yang, S., Ingle, G., Zlot, C., Rangell, L., Kowalski, J., Schwall, R., Gerritsen, M.E., Hepatocyte growth factor enhances vascular endothelial growth factor-induced angiogenesis in vitro and in vivo (2001) Am J Pathol, 158, pp. 1111-1120
Keywords: angiogenesis; article; Cell Communication; cell contact; Cell culture; cell differentiation; cell migration; cell motion; Cell Movement; Cells, Cultured; Co-culture; coculture; Coculture Techniques; controlled study; cytology; Endothelial Cells; endothelium cell; Enzyme Activation; gene expression; gene expression regulation; genetics; human; human cell; Human stem cells; human tissue; Humans; Humulus; messenger RNA; metabolism; Microscopy, Electron, Scanning; Migration; nucleotide sequence; osteoblast; Osteoblasts; Osteogenesis; paracrine signaling; phenotype; priority journal; Receptors, Vascular Endothelial Growth Factor; RNA, Messenger; Scanning electron microscopy; secretion; stem cell; umbilical cord; umbilical vein; upregulation; Vascular Endothelial Growth Factor A; vasculotropin 165; vasculotropin A; vasculotropin receptor; vasculotropin receptor 1; vasculotropin receptor 2; Vegf

Sex differences in linear and complex fetal heart rate dynamics of normal and acidemic fetuses in the minutes preceding delivery - Bernardes, J.; Gonçalves, H.; Ayres-de-Campos, D.; Rocha, A.P. (Journal of Perinatal MedicineJ. Perinat. Med., 2009)
Aim: To assess linear and complex heart rate dynamics in relation to fetal gender in normal and acidemic fetuses during the minutes preceding delivery. Methods: Linear and non-linear fetal heart rate indices, namely mean FHR, long-term irregularity index, short-term variability, low and high frequency spectral indices, approximate and sample entropy, were assessed in 36 female and 30 male fetuses, adjusted for gestational age and weight, during the minutes preceding delivery. Analysis was performed in the initial and final minutes of each tracing in fetuses with umbilical artery blood pH at delivery ≥7.20, 7.11-7.19 and ≤7.10. Results: Progression of labor was associated with a significant decrease in non-linear indices and an increase in almost all linear indices, both in female and male fetuses, but changes were more marked in female fetuses. Non-acidemic females showed higher mean FHR in the final minutes of labor, compared with males. Acidemic females had higher linear indices when compared to similar male fetuses. Conclusions: During the minutes preceding delivery, female fetuses express higher linear indices than male fetuses, suggesting greater activation of the autonomic nervous system, while maintaining similar complexity indices, which suggests different reaction and adaptation capabilities to stress and distress. © 2009 by Walter de Gruyter.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JPEMAdoi: 10.1515/JPM.2009.024PubMed ID: 19021459Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Faculdade de Medicina, Universidade Do Porto, Ginecologia e Obstetrícia, Al. Hernani Monteiro, Porto, 4200, Portugal; email: jbernardes59@gmail.comReferences: Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310;Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sà, J.P., Pereira-Leite, L., SisPorto 2.0 - a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto 3.5 - a central fetal monitoring station with online alerts based on computerized cardio-tocogram+ST event analysis (2008) J Perinat Med, 36, pp. 260-264; Beckers, F., Verheyden, B., Aubert, A.E., Aging and non-linear heart rate control in a healthy population (2006) Am J Physiol Heart Circ Physiol, 290, pp. H2560-H2570; Bekedam, D.J., Engelsbel, S., Mol, B.W., Buitendijk, S.E., van der Pal-de Bruin, K.M., Male predominance in fetal distress during labor (2002) Am J Obstet Gynecol, 187, pp. 1605-1607; Bennet, L., Booth, L.C., Ahmed-Nasef, N., Dean, J.M., Davidson, J., Quaedackers, J.S., Male disadvantage? Fetal sex and cardiovascular responses to asphyxia in preterm fetal sheep (2007) Am J Physiol Regul Integr Comp Physiol, 293, pp. R1280-R1286; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Bernardes, J., Ayres-de-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int J Gynaecol Obstet, 62, pp. 141-147; Bernardes, J., Gonçalves, H., Ayres-de-Campos, D., Rocha, A.P., Linear and complex heart rate dynamics vary with sex in relation to fetal behavioural states (2008) Early Hum Dev, 84, pp. 433-439; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grosssesse et de l'accouchement. (2004) Encyclopédie Médico- Chirurgicale, 148, pp. 1-10; Browner, W.S., Newman, T.B., Cummings, S.R., Hulley, S.B., (2001) Estimating sample size and power: The nitty-gritty, pp. 65-84. , Hulley SB, Cummings SR, Browner WS, Grady D, Hearst N, Newman TB, editors. Philadelphia: Lippincot Williams & Wilkins; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J Matern Fetal Invest, 8, pp. 23-26; Dawes, G.S., Moulden, M., Redman, C.W., Improvements in computerized fetal heart rate analysis antepartum (1996) J Perinat Med, 24, pp. 25-36; Dawes, N.W., Dawes, G.S., Moulden, M., Redman, C.W., Fetal heart rate patterns in term labor vary with sex, gestational age, epidural analgesia, and fetal weight (1999) Am J Obstet Gynecol, 180, pp. 181-187; DiPietro, J.A., Costigan, K.A., Shupe, A.K., Pressman, E.K., Johnson, T.R., Fetal neurobehavioral development: Associations with socioeconomic class and fetal sex (1998) Dev Psychobiol, 33, pp. 79-91; Dudewicz, E., Mishra, S., (1998) Modern mathematical statistics, , John Wiley and Sons, Inc; Fleisher, L.A., Dipietro, J.A., Johnson, T.R., Pincus, S., Complementary and non-coincident increases in heart rate variability and irregularity during fetal development (1997) Clin Sci (Lond), 92, pp. 345-349; Fusheng, Y., Bo, H., Qingyu, T., (1998) Approximate entropy and its application in biosignal analysis, 2, pp. 72-91. , editor. Nonlinear biomedical signal processing, Dynamical analysis and modelling. IEEE Press;; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol Meas, 27, pp. 307-319; Goncalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med Biol Eng Comput, 44, pp. 847-855; Goncalves, H., Bernardes, J., Rocha, A.P., Ayres-de-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Hum Dev, 83, pp. 585-591; Groome, L.J., Mooney, D.M., Holland, S.B., Smith, L.A., Atterbury, J.L., Dykman, R.A., Behavioral state affects heart rate response to low-intensity sound in human fetuses (1999) Early Hum Dev, 54, pp. 39-54; Ingemarsson, I., Herbst, A., Thorngren-Jerneck, K., Long-term outcome after umbilical artery acidemia at term birth: Influence of gender and duration of fetal heart rate abnormalities (1997) Br J Obstet Gynaecol, 104, pp. 1123-1127; Jensen-Urstad, K., Storck, N., Bouvier, F., Ericson, M., Lindblad, L.E., Jensen-Urstad, M., Heart rate variability in healthy subjects is related to age and gender (1997) Acta Physiol Scand, 160, pp. 235-241; King, T., Parer, J., The physiology of fetal heart rate patterns and perinatal asphyxia (2000) J Perinat Neonat Nurs, 14, pp. 19-39; Kuo, T.B., Yang, C.C., Sexual dimorphism in the complexity of cardiac pacemaker activity (2002) Am J Physiol Heart Circ Physiol, 283, pp. H1695-H1702; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) J Obstet Gynecol Reprod Biol, 114, pp. 137-143; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000, Proceedings of the IEEE-INNS-ENNS International Joint Conference on Neural Networks, 3, pp. 637-641; Martinez, W.L., Martinez, A.R., (2002) Computational statistics handbook with MATLAB, , CRC Press;; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc Natl Acad Sci USA, 88, pp. 2297-2301; Pincus, S., Viscarello, R., Approximate Entropy: A regularity measure for fetal heart rate analysis (1992) Obstet Gynecol, 79, pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Ryan, S.M., Goldberger, A.L., Pincus, S.M., Mietus, J., Lipsitz, L.A., Gender- and age-related differences in heart rate dynamics: Are women more complex than men? (1994) J Am Coll Cardiol, 24, pp. 1700-1707; Sheiner, E., Hadar, A., Hallak, M., Katz, M., Mazor, M., Shoham-Vardi, I., Clinical significance of fetal heart rate tracings during the second stage of labor (2001) Obstet Gynecol, 97, pp. 747-752; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Transactions on Biomedical Engineering, 50, pp. 365-373; Siira, S.M., Ojala, T.H., Vahlberg, T.J., Jalonen, J.O., Välimäki, I.A., Rosén, K.G., Marked fetal acidosis and specific changes in power spectrum analysis of fetal heart rate variability recorded during the last hour of labor (2005) Br J Obstet Gynaecol, 112, pp. 418-423; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynecol, 182, pp. 1227-1232;
Keywords: acidemia; Acidemic fetuses; article; autonomic nervous system; Birth Weight; blood pH; Cross-Sectional Studies; delivery; Delivery, Obstetric; entropy; Entropy and spectral analysis; Female; Fetal Heart; fetus; fetus heart rate; Gestational Age; Heart Rate, Fetal; human; Humans; Hydrogen-Ion Concentration; Intrapartum; labor; Labor, Obstetric; male; Pregnancy; priority journal; Retrospective Studies; Sex Characteristics; sex difference; Umbilical Arteries; umbilical artery

Skin adhesive versus subcuticular suture for perineal skin repair after episiotomy - A randomized controlled trial - Mota, R.; Costa, F.; Amaral, A.; Oliveira, F.; Santos, C.C.; Ayres-de-Campos, D. (Acta Obstetricia et Gynecologica ScandinavicaActa Obstet. Gynecol. Scand., 2009)
Objective. Surgical repair of perineal lesions after delivery is frequently associated with pain and discomfort, interfering with the normal activities of the puerperium. The aim of this study was to compare perineal skin repair after episiotomy with adhesive glue versus a subcuticular suture, regarding the incidence of pain and wound complications. Study design. Randomized clinical trial. Setting. Tertiary care university hospital. Material and methods. One hundred women having mediolateral episiotomy at vaginal delivery were enrolled. They were randomized to receive skin adhesive (n = 53) or subcuticular suture (n = 47) for closure of perineal skin. The main outcome measure was self-evaluated pain in the 30 days following delivery. Secondary outcome measures were technical difficulties reported with the procedure, duration of surgical repair, wound complications observed at 42-68 hours post-partum and re-initiation of sexual activity by 30 days post-partum. Results. No significant differences were observed between the two groups in incidence of technical difficulties and failed procedures, pain during the procedure, wound complications at hospital discharge, self-evaluated measures of pain at 7 and 30 days or re-initiation of sexual activity by 30 days post-partum. The skin adhesive group had a significantly shorter mean duration of the procedure (four minutes less). Conclusion. Perineal skin closure using adhesive glue is faster than subcuticular suture, and associated with a similar incidence of complications and pain in the first 30 days.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: AOGSAdoi: 10.1080/00016340902883133Language of Original Document: EnglishCorrespondence Address: Mota, R.; Serviço de Ginecologia e Obstetrícia, Hospital de S. João, 4200-319 Porto, Portugal; email: sisporto@med.up.ptChemicals/CAS: Tissue Adhesives; cyanoacrylic acid octyl ester, 6701-17-3; polyglactin, 26780-50-7, 34346-01-5Tradenames: Dermabond, EthiconManufacturers: EthiconReferences: Kettle, C., Hills, R.K., Jones, P., Darby, L., Gray, R., Johanson, R., Continuous versus interrupted perineal repair with standard or rapidly absorbed sutures after spontaneous vaginal birth: A randomized controlled trial (2002) Lancet, 359, pp. 2217-2223;Gordon, B., Mackrodt, C., Fern, E., Truesdale, A., Ayers, S., Grant, A., The Ipswich Childbirth Study: 1. A randomized evaluation of two stage postpartum perineal repair leaving the skin unsutured (1998) Br J Obstet Gynaecol, 105, pp. 435-440; Mackrodt, C., Gordon, B., Fern, E., Ayers, S., Truesdale, A., Grant, A., The Ipswich Childbirth Study: 2. A randomized comparison of polyglactin 910 with chromic catgut for postpartum perineal repair (1998) Br J Obstet Gynaecol, 105, pp. 441-445; Kettle, C., Johanson, R.B., Continuous versus interrupted sutures for perineal repair (2000) Cochrane DataBase Syst Rev, (2). , CD000947; Kettle, C., Hills, R.K., Ismail, K.M.K., Continuous versus interrupted sutures for repair of episiotomy or second degree tears (2007) Cochrane DataBase Syst Rev, (4). , CD000947; Gemynthe, A., Langhoff-Roos, J., Sahl, S., Knudsen, J., New VICRYL formulation: An improved method of perineal repair? (1996) Br J Midwifery, 4, pp. 230-234; Oboro, V.O., Tabowei, T.O., Loto, O.M., Bosah, J.O., A multicentre evaluation of the two-layered repair of postpartum perineal trauma (2003) J Obstet Gynaecol, 23, pp. 5-8; Kindberg, S., Stehouwer, M., Hvidman, L., Henriksen, T.B., Postpartum perineal repair performed by midwives: A randomised trial comparing two suture techniques leaving the skin unsutured (2008) Br J Obstet Gynaecol, 115, pp. 472-479; Gennari, R., Rotmensz, N., Ballardini, B., Scevola, S., Perego, E., Zanini, V., A prospective, randomized, controlled clinical trial of tissue adhesive (2-octylcyanoacrylate) versus standard wound closure in breast surgery (2004) Surgery, 136, pp. 593-599; Bernard, L., Doyle, J., Friedlander, S.F., Eichenfield, L.F., Gibbs, N.F., Cunningham, B.B., A prospective comparison of octylcya-noacrylate tissue adhesive (dermabond) and suture for the closure of excisional wounds in children and adolescents (2001) Arch Dermatol, 137, pp. 1177-1180; Matin, S.F., Prospective randomized trial of skin adhesive versus sutures for closure of 217 laparoscopic port-site incisions (2003) J Am Coll Surg, 196, pp. 845-853; Bhende, S., Rothenburger, S., Spangler, D.J., Dito, M., In vitro assessment of microbial barrier properties of Dermabond( topical skin adhesive (2002) Surg Infect, 3, pp. 251-257; Rogerson, L., Mason, G.C., Roberts, A.C., Preliminary experience with twenty perineal repairs using Indermil tissue adhesive (2000) Eur J Obstet Gynecol Reprod Biol, 88, pp. 139-142; Bowen, M.L., Selinger, M., Episiotomy closure comparing enbucrilate tissue adhesive with conventional sutures (2002) Int J Gynecol Obstet, 78, pp. 201-205; Adoni, A., Anteby, E., The use of Histoacryl for the episiotomy repair (1991) Br J Obstet Gynaecol, 98, pp. 476-478; Man, J., Quinn, J., Cyanoacrylate tissue adhesives (1997) Am J Cosm Surg, 14, pp. 413-416; Maw, J.L., Quinn, J.V., Wells, G.A., Ducic, Y., Odell, P.F., Lamothe, A., A prospective comparison of octylcyanoacrylate tissue adhesive and suture for the closure of head and neck incisions (1997) J Otolaryngol, 26, pp. 26-30
Keywords: adult; article; clinical trial; comparative study; controlled clinical trial; controlled study; cyanoacrylic acid octyl ester; edema; episiotomy; Episiotomy closure; Female; granuloma; human; Humans; injury; major clinical study; obstetric care; pain; pain assessment; Perineal repair; perineum; perineum injury; polyglactin; priority journal; questionnaire; randomized controlled trial; sexual intercourse; Skin; Skin adhesive; suture; Suture Techniques; suturing method; Tissue adhesive; Tissue Adhesives; treatment outcome; vaginal delivery; wound closure; wound dehiscence; Wounds and Injuries

Biocompatibility of highly macroporous ceramic scaffolds: Cell adhesion and morphology studies - Teixeira, S.; Ferraz, M.P.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2008)
Hydroxyapatite porous scaffolds can be used for tissue engineering applications since they can serve as templates for cell adhesion, proliferation and ultimately for tissue repair. One way to address this issue is to evaluate the cell adhesion using several characterization techniques namely, cytotoxicity assays and cell visualization. On the other hand, when using highly macroporous scaffolds some techniques may not be adequate for evaluation, such as MTT. In this work, cytotoxicity assay (MTS), scanning electron microscopy (SEM) and Confocal laser scanning microscopy (CLSM) were used to evaluate cell adhesion in highly macroporous hydroxyapatite scaffolds. It was possible to observe that some techniques were not suitable to evaluate cell adhesion. In addition, it was shown that for this kind of scaffolds, confocal laser scanning microscopy is a powerful tool for cell adhesion and proliferation evaluation. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 23Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3005-xPubMed ID: 17665126Language of Original Document: EnglishCorrespondence Address: Teixeira, S.; Laboratório de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: smsilva@ineb.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; Biocompatible Materials; Ceramics; Durapatite, 1306-06-5References: Jones, A.C., (2004) Biomaterials, 25, p. 4947;Karaggeorgiou, V., (2005) Biomaterials, 27, p. 5474; Leon, C.A., Leon, Y., (1998) Adv. Colloid. Interface Sci., 76-77, p. 341; Kuboki, Y., Takita, H., Kobayashi, D., Tsuruga, E., Inoue, M., Murata, M., (1998) J. Biomed. Mater. Res., 39, p. 190. , 2; Heise, U., Osborn, J.F., Duwe, F., (1990) Int. Orthop., 14, p. 329; Bucholz, R.W., Carlton, A., Holmes, R.E., (1987) Orthop. Clin. North. Am., 18, p. 323; Hill, P.A., (1998) Br. J. Orthod., 25, p. 101; Martin, R.B., (1999) Mater. Sci. Forum, 293, p. 5; Nunes, C.R., Simske, S.J., Sachdeva, R., Wolford, L.M., (1997) J. Biomed. Mater. Res., 36, p. 560; Queiroz, A.C., Teixeira, S., Monteiro, F.J., Santos, J.D., (2004) Key Eng. Mater., 254-256, p. 997; Queiroz, A.C., Teixeira, S., Monteiro, F.J., Santos, J.D., (2004) Mater. Sci. Forum, 455-456, p. 358; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Porous, H.A., (2005) Key Eng. Mater., 284-286; Teixeira, S.M., Queiroz, A.C., Monteiro, F.J., Ferraz, M.P., In vitro analysis of macroporous ceramic matrices: Preliminary results (2005) 19th European Conference on Biomaterials, , PP-P173; Naples, Italy, Sept 11-15
Keywords: article; Bioassay; Biocompatibility; Biocompatible Materials; cell adhesion; Cell Line, Tumor; cell proliferation; cell structure; Ceramic materials; ceramics; confocal laser microscopy; controlled study; Cytotoxicity; Cytotoxicity assay; Durapatite; human; human cell; Humans; hydroxyapatite; Macroporous ceramic scaffolds; Microscopy, Confocal; Microscopy, Electron, Scanning; Osteoblasts; priority journal; Scanning electron microscopy; Tissue engineering; Tissue Scaffolds

Bone ingrowth in macroporous Bonelike ® for orthopaedic applications - Gutierres, M.; Lopes, M.A.; Sooraj Hussain, N.; Lemos, A.F.; Ferreira, J.M.F.; Afonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Acta BiomaterialiaActa Biomater., 2008)
The aim of this study was to evaluate the biological behaviour of porous scaffold structures of Bonelike ® which is suitable for either direct clinical use or tissue engineering applications. Porous cylindrical specimens 8 × 10 mm were implanted in the lateral aspect of the tibia of 13 patients (mean age 54 years), during osteotomy surgery for the treatment of medial compartment osteoarthritis of the knee. Implanted cylinders were retrieved at the same time as the removal of the blade plates at 3, 6, 9 and 12 months. Scanning electron microscopy and histological evaluations were performed to observe the biological responses of human bone tissue to porous Bonelike ®. The penetration depth was determined for all implantation periods, and after 6 months it was already possible to see new bone in the centre of the implanted cylinders, which gives 100% of penetration depth for all implantations periods except for 3 months when bone could only be seen in the peripherical region. Regarding the percentage of the area covered by new bone calculated from two-dimensional histological sections, values of 53 ± 15, 76 ± 12 and 88 ± 9% were achieved for 6, 9 and 12 months, respectively. Due to its structural features porous Bonelike ® permitted effective vascularization and bone ingrowth, and therefore was fully osteointegrated as shown in the histological surveys. A slow biomaterial degradation with implantation time is envisaged since the material has displayed surface degradation. Bonelike ® scaffolds show potential for complete ingrowth of osseous tissue and restoration of vascularization throughout the defected site. © 2007.
Cited By (since 1996): 13Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2007.06.009PubMed ID: 17716960Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; FEUP - Faculdade de Engenharia, Universidade do Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesTradenames: BonelikeReferences: Akamatsu, Y., Koshino, T., Saito, T., Wada, J., Changes in osteosclerosis of the osteoarthritic knee after high tibial osteotomy (1997) Clin Orthop, 334, pp. 207-214;Coventry, M.B., Ilstrup, D.M., Wallrichs, S.L., Proximal tibial osteotomy. A critical long-term study of eighty-seven cases (1993) J Bone Joint Surg, 75 -A, pp. 196-201; Hernigou, P., Medevielle, D., Debeyre, J., Goutallier, D., Proximal tibial osteotomy for osteoarthritis with varus deformity. A ten to thirteen-year follow-up study (1987) J Bone Joint Surg Am, 69, pp. 332-354; Hernigou, P., Ma, W., Open wedge tibial osteotomy with acrylic bone cement as bone substitute (2001) Knee, 8, pp. 103-110; Koshino, T., Murase, T., Saito, T., Medial opening-wedge high tibial osteotomy with use of porous hydroxyapatite to treat medial compartment osteoarthritis of the knee (2003) J Bone Joint Surg Am, 85, pp. 78-85; Simske SJ, Ayers RA, Bateman TA. Porous Materials for Bone Engineered. In: Materials Science Forum. Zurich: Trans Tech Publications; 1997. Vol. 250, pp. 151-182Hing, K.A., Bone repair in the twenty-first century: biology, chemistry or engineering? (2004) Philos Trans A Math Phys Eng Sci, 362 (1825), pp. 2821-2850; Hui, P.W., Leung, P.C., Sher, A., Fluid conductance of cancellous bone graft as a predictor for graft-host interface healing (1996) J Biomech, 29 (1), pp. 123-132; Ben-Nissan, B., Natural bioceramics: from coral to bone and beyond (2003) Curr Opin Solid State Mater Sci, 7 (4-5), p. 283; Shors, E.C., Holmes, R.E., Porous hydroxyapatite (1993) Introduction to Biomaterials, pp. 181-198. , Hench L.L., and Wilson J. (Eds), World Scientific, Singapore; Prado da Silva, M.H., Lemos, A.F., Gibson, I.R., Ferreira, J.M.F., Santos, J.D., Porous glass reinforced hydroxyapatite materials produced with different organic additives (2002) J Non-Cryst Solids, 304, pp. 286-292; Prado da Silva, M.H., Lemos, A.F., Ferreira, J.M.F., Lopes, M.A., Santos, J.D., Production of porous biomaterials based on glass reinforced hydroxyapatite composites (2002) Key Eng Mater, 230-232, pp. 483-486; Rocha, J., Lemos, A., Agathopoulos, S., Valério, P., Kannan, S., Oktar, F., Scaffolds for bone restoration from cuttlefish (2005) Bone, 37 (6), pp. 850-857; Sepulveda, P., Binner, J.G.P., Processing of cellular ceramics by foaming and in situ polymerization of organic monomers (1999) J Eur Ceram Soc, 19 (12), pp. 2059-2066; Ozgur Engin, N., Cuneyt Tas, A., Manufacture of macroporous calcium hydroxyapatite bioceramics (1999) J Eur Ceram Soc, 19 (13-14), pp. 2569-2572; Peng, H.X., Fan, Z., Evans, J.R.G., Busfield, J.J.C., Microstructure of ceramic foams (2000) J Eur Ceram Soc, 20 (7), pp. 807-813; Komlev Vladimir, S., Barinov Serguei, M., Koplik Elena, V., A method to fabricate porous spherical hydroxyapatite granules intended for time-controlled drug release (2002) Biomaterials, 23 (16), pp. 3449-3454; Milosevski, M., Bossert, J., Milosevski, D., Gruevska, N., Preparation and properties of dense and porous calcium phosphate (1999) Ceram Int, 25, pp. 693-696; Tadic, D., Beckmann, F., Schwarz, K., Epple, M., A novel method to produce hydroxyapatite objects with interconnecting porosity that avoids sintering (2004) Biomaterials, 25, pp. 3335-3340; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., Influence of characteristics of the starting hydroxyapatite powders and of deagglomeration procedure, on rheological behaviour of the suspensions (2004) Mater Sci Forum, 455-456, pp. 361-365; Lemos, A.F., Ferreira, J.M.F., Porous bioactive calcium carbonate implants processed by starch consolidation (2000) J Mat Sci Eng C, C11, pp. 35-40; Lemos, A.F., Ferreira, J.M.F., Combining foaming and starch consolidation methods to develop macroporous HA implants (2004) Key Eng Mater, 254-256, pp. 1041-1044; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., New method for the incorporation of soluble bioactive glasses to reinforce porous HA structures (2004) Key Eng Mater, 254-256, pp. 1033-1036; Gauthiera, O., Boulerb, J.M., Aguadoa, E., Piletb, P., Daculsi, G., Macroporous biphasic calcium phosphate ceramics: influence of macropore diameter and macroporosity percentage on bone ingrowth (1998) Biomaterials, 19, pp. 133-139; Hing, A.K., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Mediation of bone ingrowth in porous hydroxyapatite bone graft substitutes (2004) J Biomed Mater Res, 68 A, pp. 187-200; Rubin, P.A., Popham, J.K., Bilyk, J.R., Shore, J.W., Comparison of fibrovascular ingrowth into hydroxyapatite and porous polyethylene orbital implants (1994) Ophthal Plast Reconstr Surg, 10 (2), pp. 96-103; Hing, K.A., Annaz, B., Saeed, S., Revell, P.A., Buckland, T., Microporosity enhances bioactivity of synthetic bone graft substitutes (2005) J Mater Sci: Mater Med, 16, pp. 467-475; Klawitter, J.J., Bagwell, J.G., Weinstein, A.M., Sauer, B.W., An evaluation of bone growth into porous high density polyethylene (1976) J Biomed Mater Res, 10 (2), pp. 311-323; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Quantification of bone ingrowth within bone-derived porous hydroxyapatite implants of varying density (1999) J Mater Sci: Mater Med, 10, pp. 663-670; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Biomechanical assessment of bone ingrowth in porous hydroxyapatite (1997) J Mater Sci: Mater Med, 8, pp. 731-736; Ayers, R.A., Wolford, L.M., Bateman, T.A., Ferguson, V.L., Simske, S.J., Quantification of bone ingrowth into porous block hydroxyapatite in humans (1999) J Biomed Mater Res, 47, pp. 54-59; Lu, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Role of interconnections in porous bioceramics on bone recolonization in vitro and in vivo (1999) J Mater Sci: Mater Med, 10 (2), pp. 111-120; Eggli, P.S., Muller, W., Schenk, R.K., Porous hydroxyapatite and tricalcium phosphate cylinders with two different pore size ranges implanted in the cancellous bone of rabbits - A comparative histomorphometric and histologic study of bony ingrowth and implant substitution (1988) Clin Orthop Relat Res, 232, pp. 127-138; Kuhne, J.H., Bartl, R., Frisch, B., Hammer, C., Jansson, V., Zimmer, M., Bone formation in coralline hydroxyapatite. Effects of pore size studied in rabbits (1994) Acta Orthop Scand, 65 (3), pp. 246-252; Holmes, R., Mooney, V., Bucholz, R., Tencer, A., A coralline hydroxyapatite bone graft substitute. Preliminary report (1984) Clin Orthop Relat Res, 188, pp. 252-262; Lopes, M.A., Knowles, J.C., Santos, J.D., Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement (2000) Biomaterials, 21 (18), pp. 1905-1910; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39 (2), pp. 244-251; Santos JD, Hastings G, Knowles JC. Sintered hydroxyapatite compositions and method for the preparation thereof. Worldwide Application (PCT), Patent No. 1 189 851, 1999Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: fracture toughness and hardness dependence on microstructural characteristics (1999) Biomaterials, 20 (21), pp. 2085-2090; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength (1999) J Biomed Mater Res, 48 (5), pp. 734-740; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, Surface tension and Zeta potential measurements of glass reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Direct and Indirect effects of P 2O 5 - glass reinforced - hydroxyapatite composites and growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibiae of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and Double layer HA-P 2O 5/CaO Glass coatings: influence of chemical composition on human bone marrow cells osteoblastic behaviour (2001) J Mater Sci: Mater Med, 12, pp. 629-638; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Biological behaviour of Bonelike ® graft implanted in the tibia of humans (2005) Key Eng Mater, 17, pp. 1041-1044; Duarte, F., Santos, J.D., Afonso, A., Medical applications of Bonelike ® in maxillofacial surgery (2004) Adv Mater Forum, pp. 370-373; Lobato, J.V., Hussain, N.S., Botelho, C.M., Titanium dental implants coated with Bonelike ®: clinical case report (2006) Thin Solid Films, 515, p. 279; Coventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: a preliminary report (1965) J Bone Joint Surg Am, 47, pp. 984-990; Coventry, M.B., Upper tibia osteotomy for gonarthrosis. The evolution of the operation in the last 18 years and long term results (1979) Orthop Clin North Am, 10, pp. 191-210; Coventry, M.B., Current concepts review. Upper tibia osteotomy for osteoarthritis (1985) J Bone Joint Surg Am, 67 A, pp. 1136-1140
Keywords: adult; aged; article; biomaterial; bone defect; Bone graft; bone growth; Bone Regeneration; Bone Substitutes; bone tissue; Bonelike; clinical article; controlled study; Female; histology; human; human tissue; Humans; implant; knee osteoarthritis; male; materials testing; Microscopy, Electron, Scanning; Middle Aged; molecular scaffold; Orthopaedic; orthopedics; Osseointegration; Osteoarthritis; osteotomy; porosity; Porous materials; priority journal; Prostheses and Implants; Scanning electron microscopy; tibia; Time Factors; Tissue engineering; tissue section; vascularization; ®

Cell-induced response by tetracyclines on human bone marrow colonized hydroxyapatite and Bonelike ® - Gomes, P.S.; Santos, J.D.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2008)
Semi-synthetic tetracyclines are commonly used antibiotics that also seem to play an important role in the modulation of the immuno-inflammatory imbalance, verified in several bone diseases. The association of a therapeutic agent (that prevents bacterial infection and induces tissue formation) to a biomaterial aiming to repair/regenerate bone defects could contribute to a more predictable clinical outcome. The present study intends to evaluate the proliferation and functional activity of osteoblast-induced human bone marrow cells, cultured on the surface of hydroxyapatite (HA) and Bonelike ®, in the presence of therapeutic concentrations of doxycycline and minocycline. First passage bone marrow cells were cultured for 35 days on the surface of HA and Bonelike ® discs, in the absence or presence of 1 μg ml
Cited By (since 1996): 9Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2007.12.006PubMed ID: 18291737Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Laboratório de Farmacologia e Biocompatibilidade Celular, Faculdade de Medicina Dentária, Universidade do Porto (FMDUP), Rua Dr. Manuel Pereira da Silva, s/n, 4200-392 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; doxycycline, 10592-13-9, 17086-28-1, 564-25-0; hydroxyapatite, 1306-06-5, 51198-94-8; minocycline, 10118-90-8, 11006-27-2, 13614-98-7; Alkaline Phosphatase, EC 3.1.3.1; Bone Substitutes; Calcium, 7440-70-2; Culture Media; Durapatite, 1306-06-5; Minerals; Tetracycline, 60-54-8Tradenames: BonelikeReferences: Chambers, H., Protein synthesis inhibitors and miscellaneous antibacterial agents (2006) Goodman and Gilman's - The Pharmacological Basis of Therapeutics, pp. 1173-1202. , Brunton L. (Ed), McGraw-Hill, Germany;Alkan, A., Erdem, E., Gunhan, O., Karasu, C., Histomorphometric evaluation of the effect of doxycycline on the healing of bone defects in experimental diabetes mellitus: a pilot study (2002) J Oral Maxillofac Surg, 60, p. 898; Buchter, A., Kleinheinz, J., Meyer, U., Joos, U., Treatment of severe peri-implant bone loss using autogenous bone and a bioabsorbable polymer that delivered doxycycline (Atridox TM) (2004) Brit J Oral Maxillofacial Surg, 42, pp. 452-456; Ramamurthy, N., Rifkin, B., Greenwald, R., Xu, J.-W., Liu, Y., Turner, G., Inhibition of matrix metalloproteinase-mediated periodontal bone loss in rats: a comparison of 6 chemically modified tetracyclines (2005) J Periodontol, 73, pp. 726-734; Golub, L., Ramamurthy, N., Kaneko, H., Sasaki, T., Rifkin, B., McNamara, T., Tetracycline administration prevents diabetes-induced osteopenia in the rat: initial observations (1990) Res Commun Chem Pathol Pharmacol, 68, p. 27; Williams, S., Wakisaka, A., Zeng, Q., Barnes, J., Martin, G., Wechter, W., Minocycline prevents the decrease in bone mineral density and trabecular bone in ovariectomized aged rats (1996) Bone, 19, pp. 637-644; Williams, S., Wakisaka, A., Zeng, Q., Barnes, J., Seyedin, S., Martin, G., Effect of minocycline on osteoporosis (1998) Adv Dental Res, 12, pp. 71-75; Pytlik, M., Folwarczna, J., Janiec, W., Effects of doxycycline on mechanical properties of bones in rats with ovariectomy-induced osteopenia (2004) Calcified Tissue Int, 75, pp. 225-230; Holmes, S., Still, K., Buttle, D., Bishop, N., Grabowski, P., Chemically modified tetracyclines act through multiple mechanisms directly on osteoclast precursors (2004) Bone, 35, pp. 471-478; Polson, A., Bouwsma, O., McNamara, T., Golub, L., Enhancement of alveolar bone formation after tetracycline administration in squirrel monkeys (2005) J Appl Res Clin Dent, pp. 32-42; Yamaguchi, A., Udagawa, T., Sawai, T., Transport of divalent cations with tetracycline as mediated by the transposon Tn10-encoded tetracycline resistance protein (1990) J Biol Chem, 265, pp. 4809-4813; Li, S., de Wijn, J., Layrolle, P., de Groot, K., Synthesis of macroporous hydroxyapatite scaffolds for bone tissue engineering (2002) J Biomed Mater Res, 61, pp. 109-120; Giannoudis, P., Dinopoulos, H., Tsiridis, E., Bone substitutes: an update (2005) Int J Care Injured, 365, p. 220; LeGeros, R., Properties of osteoconductive biomaterials: calcium phosphates (2002) Clin Orthop, 395, pp. 81-98; Suchanek, W., Yoshimura, M., Processing and properties of hydroxyapatite-based biomaterials for use as hard tissue replacement implants (1998) J Mater Res, 13, pp. 94-117; Lopes, M., Santos, J., Monteiro, F., Knowles, J., Glass reinforced hydroxyapatite: a comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-250; Hench, L., Bioactive materials: the potential for tissue regeneration (1998) J Biomed Mater Res, 41, pp. 511-518; Kellomaki, M., Niiranen, H., Puumanen, K.A.N., Waris, T., Tormala, P., Bioabsorbable scaffolds for guided bone, regeneration, and generation (2000) Biomaterials, 21, pp. 2495-2505; Santos, J., Reis, R., Monteiro, F., Knowles, J., Hastings, G., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions structure and properties of the composites (1995) J Mater Sci Mat Med, 6, p. 348; Santos, J., Silva, P., Knowles, J., Talal, S., Monteiro, F., Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O and MgO (1996) J Mater Sci Mat Med., 7, p. 187; Duarte, F., Santos, J., Afonso, A., Medical applications of Bonelike in maxillofacial surgery (2004) Mater Sci Forum, 370, pp. 455-456; Gutierres, M., Hussain, N., Afonso, A., Almeida, L., Cabral, A., Lopes, M., Biological behaviour of bonelike ® graft implanted in the tibia of humans (2005) Key Eng Mater, 1041, pp. 284-286; Brause, B., Infections with prostheses in bones and joints (2000) Mandell, Douglas and Bennett's Principles and Practice of Infectious Diseases. 5th ed., pp. 1196-1200. , Mandell G., Bennet J., and Dolin R. (Eds), Churchill Livingstone, Philadelphia; Darley, E., MacGowan, A., Antibiotic treatment of Gram-positive bone and joint infections (2004) J Antimicrobial Chemotherapy, 53, pp. 928-935; Zucchelli, G., Sforza, N., Clauser, C., Cesari, C., De Sanctis, M., Topical and systemic antimicrobial therapy in guided tissue regeneration (1999) J Periodontol, 70, pp. 239-247; Yukna, R., Sepe, W., Clinical evaluation of localized periodontosis defects treated with freeze-dried bone allografts combined with local and systemic tetracyclines (1982) Int J Periodontics Restorative Dent, 2, pp. 8-21; Shirtliff, M., Mader, J., Acute septic arthritis (2002) Clin Microbiol Rev, 15, pp. 527-544; Sunder, M., Babu, N., Victor, S., Kumar, K., Kumar, T., Biphasic calcium phosphates for antibiotic release (2005) Trends Biomater Artif Organs, 18, pp. 213-218; Lieberman, J., Daluiski, A., Einhorn, T., The role of growth factors in the repair of bone: biology and clinical applications (2002) J Bone Joint Surg, 84, pp. 1032-1044; Carson, J., Bostrom, M., Synthetic bone scaffolds and fracture repair (2007) Injury, 38, pp. S33-S70; Regí-Vallet, M., Balas, F., Colilla, M., Manzano, M., Drug confinement and delivery in ceramic implants (2007) Drug Metabol Lett, 1, pp. 37-40; Lin, T.-L., Lu, F.-M., Conroy, S., Sheu, M.-S., Su, S.-H., Tang, L., Antimicrobial coatings: a remedy for medical device-related infections (2001) Med Device Technol., 12, pp. 26-30; Beardmore, A., Brooks, D., Wenke, J., Thomas, D., Effectiveness of local antibiotic delivery with an osteoinductive and osteoconductive bone-graft substitute (2005) J Bone Joint Surg, 87, pp. 107-112; Gomes, P., Fernandes, M., Effect of therapeutic levels of doxycycline and minocycline in the proliferation and differentiation of human bone marrow osteoblastic cells (2007) Arch Oral Biol, 52, pp. 251-259; Coelho, M., Fernandes, M., Human bone cell cultures in biocompatibility testing Part II. Effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Jørgensen, N., Henriksena, Z., Sørensena, O., Civitelli, R., Dexamethasone, BMP-2, and 1,25-dihydroxyvitamin D enhance a more differentiated osteoblast phenotype: validation of an in vitro model for human bone marrow-derived primary osteoblasts (2004) Steroids, 69, pp. 219-226; Sakellari, D., Goodson, J., Socransky, S., Kolokotronis, A., Konstantinidis, A., Concentration of 3 tetracyclines in plasma, gingival crevice fluid and saliva (2000) J Clin Periodontol, 27, pp. 53-60; Stein, G., Lian, J., Molecular mechanisms mediating proliferation/differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocr Rev, 14, pp. 424-442; Zhang, Y., Lopes, M., Santos, J., CaO-P 2O 5 Glass ceramics containing bioactive phases: crystallization and in vitro bioactivity studies (2001) Key Eng Mater, 192, pp. 643-646; Lopes, M., Knowles, J., Santos, J., Monteiro, F., Olsen, I., Direct and indirect effects of P 2O 5-glass reinforced hydroxyapatite on the growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Costa, M., Gutierres, M., Almeida, L., Lopes, M., Santos, J., Fernandes, M., In vitro mineralisation of human bone marrow cells cultured on Bonelike (2004) Key Eng Mater, pp. 254-256. , (821-4); Lopes, M., Santos, J., Monteiro, F., Ohtsuki, C., Osaka, A., Kaneko, S., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Gutierres, M., Hussain, N., Lopes, M., Afonso, A., Cabral, A., Almeida, L., Histological and scanning electron microscopy analyses of bone/implant interface using the novel Bonelike ® synthetic bone graft (2006) J Ortho Res, 24, p. 953; Kima, H.-W., Leea, E.-J., Kima, H.-E., Salihb, V., Knowles, J., Effect of fluoridation of hydroxyapatite in hydroxyapatite-polycaprolactone composites on osteoblast activity (2005) Biomaterials, 26, pp. 4395-4404; Williams, S., Barnes, J., Wakisaka, A., Ogasa, H., Liang, C., Treatment of osteoporosis with MMP inhibitors (1999) Ann NY Acad Sci, 878, pp. 191-200; Schwartz, Z., Lohmann, C., Wieland, M., Cochran, D., Dean, D., Textor, M., Osteoblast proliferation and differentiation on dentin slices are modulated by pretreatment of the surface with tetracycline or osteoclasts (2000) J Periodontol, 71, pp. 586-597; Bettany, J., Wolowacz, R., Tetracycline derivatives induce apoptosis selectively in cultured monocytes and macrophages but not in mesenchymal cells (1998) Adv Dent Res, 12, pp. 136-143; Duewelhenke, N., Krut, O., Eysel, P., Influence on mythochondria and cytotoxicity of different antibiotics administered in high concentrations on primary human osteoblasts and cell lines (2007) Antimicrobial Agents and Chemotherapy, 51, pp. 54-63; Golub, L., Wolff, M., Roberts, S., Lee, H.-M., Leung, M., Payonk, G., Treating periodontal diseases by blocking tissue-destructive enzymes (1994) JADA, 125, pp. 163-169; Woessner, J., Nagase, H., Inhibition of MMPs (2000) MMPs and Timps, pp. 109-125. , Woessner J., and Nagase H. (Eds), Oxford University Press, Oxford; Golub, L., Ramamurthy, N., McNamara, T., Gomes, B., Wolff, M., Casino, A., Tetracyclines inhibit tissue collagenase activity. A new mechanism in the treatment of periodontal disease (1984) J Periodontal Res, 19, pp. 651-655; Yu, Z., Ramamurthy, N., Leung, M., Chang, K., McNamara, T., Golub, L., Chemically-modified tetracycline normalizes collagen metabolism in diabetic rats: a dose-response study (1993) J Periodontal Res, 28, pp. 420-428; Karimbux, N., Ramamurthy, N., Golub, L., Nishimura, I., The expression of collagen I and XII on RNAs in porphyromonas gingivalis-induced periodontitis in rats: The effect of doxycycline and chemically-modified tetracycline (CMT-1) (1998) J Periodontol, 69, pp. 39-40; Ramamurthy, N., Pirila, E., Lee, H.-M., Delayed wound healing, altered collagen level and keratinocyte growth factor expression in skin of ovariectomized rat is normalized by estrogen or chemically modified doxycycline (2003) Menopause - The State of the Art in Research and Management. The Proceedings of the Tenth World Congress, pp. 236-243. , Schneider H. (Ed), Parthenon Publishing Group, New York; Gurkan, A., Çunarcuk, S., Huseyinov, A., Adjunctive subantimicrobial dose doxycycline: effect on clinical parameters and gingival crevicular fluid transforming growth factor-b 1 levels in severe, generalized chronic periodontitis (2005) J Clin Periodontol, 32, pp. 244-253; Caton, J., Evaluation of Periostat for patient management (1999) Compend Contin Edu Dent, 20, pp. 451-456; Salasznyk, R., Williams, W., Boskey, A., Batorsky, A., Plopper, G., Adhesion to vitronectin and collagen I promotes osteogenic differentiation of human mesenchymal stem cells (2004) J Biomed Biotechnol, 1, pp. 24-34; Gerstenfeld, L., Chipman, S., Kelly, C., Hodgens, K., Lee, D., Landis, W., Collagen expression, ultrastructural assembly, and mineralization in cultures of chicken embryo osteoblasts (1988) J Cell Biol, 106, pp. 979-989
Keywords: adult; alkaline phosphatase; alkaline phosphatase bone isoenzyme; antimicrobial activity; article; Bacteria (microorganisms); bone infection; bone marrow cell; Bone Marrow Cells; Bone Substitutes; Bonelike; Calcium; calcium phosphate; Cell culture; cell function; cell proliferation; cell survival; cell viability; Cells, Cultured; concentration response; controlled study; Culture Media; culture medium; doxycycline; Durapatite; enzyme activity; extracellular matrix; glass; human; human cell; Humans; hydroxyapatite; implant; Microscopy, Electron, Scanning; Middle Aged; Minerals; minocycline; osteoblast; Osteoblasts; priority journal; Scanning electron microscopy; stroma cell; Tetracycline; tetracycline derivative; Tetracyclines; X-Ray Diffraction

Data classification with multilayer perceptrons using a generalized error function - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Neural NetworksNeural Netw., 2008)
The learning process of a multilayer perceptron requires the optimization of an error function E (y, t) comparing the predicted output, y, and the observed target, t. We review some usual error functions, analyze their mathematical properties for data classification purposes, and introduce a new one, E Exp, inspired by the Z-EDM algorithm that we have recently proposed. An important property of E Exp is its ability to emulate the behavior of other error functions by the sole adjustment of a real-valued parameter. In other words, E Exp is a sort of generalized error function embodying complementary features of other functions. The experimental results show that the flexibility of the new, generalized, error function allows one to obtain the best results achievable with the other functions with a performance improvement in some cases. © 2008 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: NNETEdoi: 10.1016/j.neunet.2008.04.004PubMed ID: 18572384Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; INEB-Instituto de Engenharia Biomédica, Porto, Portugal; email: lmsilva@fe.up.ptReferences: Baum, E.B., Wilczek, F., Supervised learning of probability distributions by neural networks (1987) NIPS, pp. 52-61. , Anderson D.Z. (Ed), American Institute of Physics;Bishop, C., (1995) Neural networks for pattern recognition, , Oxford University Press; Blake, C., & Merz, C. (1998). UCI repository of machine learning databases. University of California, Irvine, Dept. of Information and Computer SciencesForina, M., Armanino, C., Eigenvector projection and simplified non-linear mapping of fatty acid content of italian olive oils (1981) Annali di Chimica (Rome), 50, pp. 127-155; Gish, H. (1990). A probabilistic approach to the understanding and training of neural network classifiers. In Proceedings of the 1990 IEEE international conference on acoustics, speech, and signal processingHampshire, J., Waibel, A., A novel objective function for improved phoneme recognition using time-delay neural networks (1990) IEEE Transactions on Neural Networks, 1 (2), pp. 216-228; Hinton, G.E., Connectionist learning procedures (1989) Artificial Intelligence, 40 (1-3), pp. 185-234; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Møller, M. (1993). Efficient training of feed-forward neural networks. Ph.D. thesis. Computer Science Department - Aarhus UniversityMarques de Sá, J., (2001) Pattern recognition: Concepts, methods and applications, , Springer Verlag; Matsuoka, K., & Yi, J. (1991). Backpropagation based on the logarithmic error function and elimination of local minima. In Proceedings of the 1990 IEEE international joint conference on neural networksRichard, M., Lippmann, R., Neural network classifiers estimate bayesian a posteriori probabilities (1991) Neural Computation, 3, pp. 461-483; Santos, J., Alexandre, L., & Marques de Sá, J. (2004). The error entropy minimization algorithm for neural network classification. In int. conf. on recent advances in soft computingSilva, L., Alexandre, L., Marques de Sá, J., Neural network classification: Maximizing zero-error density (2005) LNCS, 3686, pp. 127-135. , ICAPR 2005; Silva, L., Alexandre, L.A., & Marques de Sá, J. (2006). New developments of the Z-EDM algorithm. In Proceedings of the sixth international conference intelligent systems design and applications: Vol. 1 (pp. 1067-1072)Silva, L., Marques de Sá, J., & Alexandre, L. (2005). Neural network classification using Shannon's entropy. In European symposium on artificial neural networksSilverman, B., (1986) Density estimation for statistics and data analysis, , Chapman & Hall; Solla, S.A., Levin, E., Fleisher, M., Accelerated learning in layered neural networks (1988) Complex Systems, 2 (6), pp. 625-639
Keywords: algorithm; Algorithms; analytical error; article; calculation; Classification; Complementary features; Cybernetics; data analysis; Data classification; Data classifications; Data Interpretation, Statistical; Electric loads; entropy; Error functions; learning; Learning processes; mathematical analysis; Mathematical properties; Models, Statistical; Multilayer neural networks; Multilayer perceptron; Multilayer perceptrons; Multilayers; Neural networks; Neural Networks (Computer); Pattern recognition systems; perceptron; Performance improvements; priority journal; Probability density function

Hip fractures cluster in space: An epidemiological analysis in Portugal - De Pina, M.F.; Alves, S.M.; Barbosa, M.; Barros, H. (Osteoporosis InternationalOsteoporosis Int., 2008)
Summary: Using Portuguese hospital registers (2000-2002) we calculated age-standardized incidence rates of hip fractures. Spatial clusters of high incidence rates were found, with annual averages (per 100,000 inhabitants) varying from 154.4 to 572.2 and 77.3 to 231.5 for women and men, respectively. Geographic inequalities in the occurrence of hip fractures were also found. Introduction: The aim of this study was to identify spatial patterns in the incidence of hip fracture in Portugal during the period 2000 to 2002. Methods: From the National Hospital Discharge Register, admissions of patients (50 years of age or more) with low-energy hip fracture were selected. Age-standardized incidence rates in relation to the municipality of the patients' place of residence were calculated. Empirical Bayes estimators were used to smooth the local risk and spatial statistics methods were used to identify spatial clusters. Results: Of 25,634 hip fractures in individuals aged 50 years or more caused by low or moderate impact, 19,759 occurred in women (age, mean±SD, 80.6±8.6 years) and 5,875 in men (age 77.7±10.0 years). Incidence rates increased exponentially with age, being higher in women nation-wide (female to male ratio from 1.5 to 5.1). Significant geographic differences were found: the incidence rates (95% CI) varied from 154.4 (153.6-155.3) to 572.2 (569.5-575.0) in women and 77.3 (76.64-78.05) to 231.5 (229.9-233.0) in men per 100,000 inhabitants. Spatial autocorrelation values (Moran index) were 0.56 and 0.45 for women and men, respectively. Conclusion: Spatial clusters (p<0.0001) of high incidences were identified. Geographic differences in incidence rates were about threefold. Some regions had incidence rates as high as some north European countries. The geographic inequalities could be due to environmental or socioeconomic factors, but further investigation needs to be done to confirm this hypothesis. © 2008 International Osteoporosis Foundation and National Osteoporosis Foundation.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: OSINEdoi: 10.1007/s00198-008-0623-1PubMed ID: 18536955Language of Original Document: EnglishCorrespondence Address: De Pina, M. F.; Laboratório de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre, 823, Porto 4150-180, Portugal; email: fpina@ineb.up.ptReferences: Center, J., Eisman, J., The epidemiology and pathogenesis of osteoporosis (1997) Baillieres Clin Endocrinol Metab, 11, pp. 23-62. , 1;Cooper, C., Melton III, L.J., Marcus, R., Feldman, D., Kelsey, J., Magnitude and Impact of osteoporosis and fractures (1996) Osteoporosis, pp. 419-434. , Academic Press San Diego; Walker-Bone, K., Dennison, E., Cooper, C., Epidemiology of osteoporosis (2001) Rheum Dis Clin North Am, 27, pp. 1-18. , 1; Cummings, S.R., Melton III, L.J., Epidemiology and outcomes of osteoporotic fractures (2002) Lancet, 359, pp. 1761-1767; Cooper, C., Campion, G., Melton, L.J., Hip fractures in the elderly: A world-wide projection (1992) Osteoporos Int, 2, pp. 285-289; Karagas, M.R., Lu-Yao, G.L., Barrett, J.A., Heterogeneity of hip fracture: Age, race, sex, and geographic patterns of femoral neck and trochanteric fractures among the US elderly (1996) Am J Epidemiol, 143, pp. 677-682. , 7; Jordan, K.M., Cooper, C., Epidemiology of osteoporosis (2002) Best Pract Res Clin Rheumatol, 16, pp. 795-806. , 5; Orimo, H., Hashimoto, T., Sakata, K., Trends in the incidence of hip fracture in Japan, 1987-1997: The third nationwide survey (2000) J Bone Miner Metab, 18, pp. 126-131; Kennedy, S., Goodchild, M., Gopal, S., The small number problem and the accuracy of spatial databases (1994) Accuracy of Spatial Databases, pp. 187-196. , Taylor and Francis London; (1995) Interactive Spatial Data Analysis, , Bailey TC, Gatrell AC (eds) Longman, London; Anselin, L., Local indicators of spatial association - LISA (1995) Geogr Anal, 27, pp. 93-115. , 2; Chevalley, T., Herrmann, F.R., Delmi, M., Evaluation of the age-adjusted incidence of hip fractures between urban and rural areas: The difference is not related to the prevalence of institutions for the elderly (2002) Osteoporos Int, 13, pp. 113-118; Sanders, K., Nicholson, G.C., Ugoni, A.M., Fracture rates lower in rural than urban communities: The Geelong Osteoporosis Study (2002) J Epidemiol Community Health, 56, pp. 466-470; Vaz, A.L., Epidemiology and costs of osteoporotic hip fractures in Portugal (1993) Bone, 14, p. 9. , Suppl 1; Lofthus, C.M., Osnes, E.K., Falch, J.A., Epidemiology of hip fractures in Oslo, Norway (2001) Bone, 29, pp. 413-418. , 5; Nydegger, V., Rizzoli, R., Rapin, C.H., Epidemiology of fractures of the proximal femur in Geneva: Incidence, clinical and social aspects (1991) Osteoporos Int, 2, pp. 42-47. , 1; Hernandez, J., Olmos, J.M., Alonso, M.A., Trend in hip fracture epidemiology over a 14-year period in a Spanish population (2006) Osteoporos Int, 17, pp. 464-470; Giversen, I.M., Time trends of age-adjusted incidence rates of first hip fractures: A register-based study among older people in Viborg County, Denmark, 1987-1997 (2006) Osteoporos Int, 17, pp. 552-564; Coster, A., Haberkamp, M., Allolio, B., Incidence of femoral neck fractures in the German Federal Republic in comparison to other countries (1994) Soz Praventivmed, 39, pp. 287-292. , 5; Paspati, I., Galanos, A., Lyritis, G.P., Hip fracture epidemiology in Greece during 1977-1992 (1998) Calcif Tissue Int, 62, pp. 542-547. , 6; Kannus, P., Niemi, S., Parkkari, J., Hip fractures in Finland between 1970 and 1997 and predictions for the future (1999) Lancet, 353, pp. 802-805. , 9155
Keywords: adult; Age Distribution; aged; Aged, 80 and over; article; Bayes Theorem; Bone Density; Cluster Analysis; Databases, Factual; falling; Female; fracture; geographic information system; Geographic information systems; hip fracture; Hip fractures; human; Humans; incidence; international classification of diseases; major clinical study; male; Middle Aged; Osteoporosis; Portugal; priority journal; Risk Factors; sex difference; Sex Distribution; Space-Time Clustering; Spatial analysis; Spatial clusters; Spatial dependency

Jaw avascular osteonecrosis after treatment of multiple myeloma with zoledronate - Lobato, J.V.; Maurício, A.C.; Rodrigues, J.M.; Cavaleiro, M.V.; Cortez, P.P.; Xavier, L.; Botelho, C.; Hussain, N.S.; Santos, J.D. (Journal of Plastic, Reconstructive and Aesthetic SurgeryJ. Plast. Reconstr. Aesthetic Surg., 2008)
Purpose: Multiple myeloma, the second most common haematopoietic cancer, which represents the collection of plasma-cell neoplasms that invariably becomes fatal when self-renewing myeloma cells begin unrestrained proliferation. The major clinical manifestation of multiple myeloma is related to the loss of bone through osteolysis. This can lead to pathologic fractures, spinal cord compression, hypercalcaemia, and pain. It is also a major cause of morbidity and mortality in these patients, who frequently require radiation therapy, surgery and analgesic medications. Bisphosphonates are specific inhibitors of osteoclastic activity, and are currently used to prevent bone complications and to treat malignant hypercalcaemia in patients with multiple myeloma, or bone metastases from breast and prostate cancers. Hence, osteonecrosis of the mandible has been reported in three patients from Centro Hospitalar de Vila Nova de Gaia (CHVNG) with multiple myeloma treated for over 18-48 months with intravenous zoledronate, commonly prescribed for multiple myeloma therapy. Although, this report alerts clinicians about the potential complication of bone necrosis in patients receiving bisphosphonate therapy, many questions remain concerning the underlying pathogenesis of this process. Patients and methods: The medical and dental records of three patients with multiple myeloma, who were treated in CHVNG in the past 4 years, were reviewed. These three patients presented exposed bone and osteonecrosis of the mandible, and shared one common clinical feature: all of them were treated with bisphosphonate zoledronate, administered intravenously for long periods. Sequential orthopantomograms (OPGs) and histological evaluation have been analysed from the biopsies of the non healing dental extraction sites of these patients. Results: After a routine dental extraction, these patients developed avascular osteonecrosis of the mandible and secondary bone infection with Actinomyces israelii (actinomycotic osteomyelitis), with no evidence of metastatic disease evaluated by biopsy. In these three described clinical cases, surgical debridment without flap elevation, intensive antibiotherapy and the suspension of the zoledronate treatment allowed a partial recovery of the patients. The purpose of this clinical report is to point out that patients suffering from multiple myeloma can develop bone osteonecrosis induced by treatment with bisphosphonates. Research to determine the mechanism of this dental phenomenon is needed to fully validate and substantiate the possible link between bisphosphonate treatment of multiple myeloma or other cancer diseases and avascular osteonecrosis of the jaws. Until then, clinicians involved in the care of patients at risk should consider this possible complication. © 2006 British Association of Plastic, Reconstructive and Aesthetic Surgeons.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.bjps.2006.06.016PubMed ID: 18068658Language of Original Document: EnglishCorrespondence Address: Maurício, A.C.; Centro de Estudos de Ciência Animal (CECA), Instituto de Ciências, Tecnologias Agrárias e Agro-Alimentares (ICETA), Campus Agrario Vairao, Rua Padre Armando Quintas, 4485-661 Vairão, Portugal; email: ana.colette@mail.icav.up.ptChemicals/CAS: amoxicillin, 26787-78-0, 34642-77-8, 61336-70-7; cyclophosphamide, 50-18-0; cyclosporin, 79217-60-0; dexamethasone, 50-02-2; erythropoietin, 11096-26-7; thalidomide, 50-35-1; zoledronic acid, 118072-93-8, 131654-46-1, 165800-06-6, 165800-07-7; Bone Density Conservation Agents; Diphosphonates; Imidazoles; zoledronic acid, 118072-93-8References: Mundy, G.R., Bertoline, D.R., Bone destruction and hypercalcemia in plasma cell myeloma (1986) Semin Oncol, 13 (3), pp. 291-299;Belch, A.R., Bergsagel, D.E., Wilson, K., Effect of daily etidronate on the osteolysis of multiple myeloma (1991) J Clin Oncol, 9 (8), pp. 1397-1402; Kyle, R.A., Jowsey, J., Kelly, P.J., Multiple myeloma bone disease. The comparative effect of sodium fluoride and calcium carbonate or placebo (1975) N Engl J Med, 293 (26), pp. 1334-1338; Kyle, R.A., Multiple myeloma: review of 869 cases (1975) Mayo Clin Proc, 50 (1), pp. 29-40; Roodman, G.D., Pathogenesis of myeloma bone disease (2004) Blood Cells Mol Dis, 32 (2), pp. 290-292; Berenson, J.R., Myeloma bone disease (2005) Best Pract Res Clin Haematol, 18 (4), pp. 653-672; Ruggerio, S.L., Mekrotra, B., Rosenberg, T.J., Osteonecrosis of the jaws associated with the use of bisphosphonates: a review of 63 cases (2004) J Oral Maxillofac Surg, 62, pp. 527-534; Rodan, G.A., Fleisch, H.A., Bisphosphonates: mechanism of action (1996) J Clin Invest, 97 (12), pp. 2692-2696; Coleman, R.E., Metastatic bone disease: clinical features, pathophysiology and treatment strategies (2001) Cancer Treat Rev, 27 (3), pp. 165-176; Sietsema, W.K., Ebetino, F.H., Salvagno, A.M., Antiresorptive dose-response relationship across three generations of bisphosphonates (1989) Drugs Exp Clin Res, 15 (9), pp. 389-396; Schenk, R., Eggli, P., Fleisch, H., Quantitative morphometric evaluation of the inhibitory activity of new amino-bisphosphonates on bone resorption in the rat (1986) Calcif Tissue Int, 38, pp. 342-349; Jung, A., Bisaz, S., Fleisch, H., The binding of pyrophosphate and two diphosphonates by hydroxyapatite crystals (1973) Calcif Tissue Res, 11 (4), pp. 269-280; Coukell, A.J., Markham, A., Pamidronate. A review of its use in the management of osteolytic bone metastases, tumor-induced hypercalcaemia and Paget's disease of bone (1998) Drugs Aging, 12 (2), pp. 149-168; Hughes, D.E., MacDonald, B.R., Russel, R.G.G., Inhibition of osteoclast-like cell formation by bisphosphonates in long-term cultures of human bone marrow (1989) J Clin Invest, 83 (6), pp. 1930-1935; Hughes, D.E., Wright, K.R., Uy, H.L., Bisphosphonates promote apoptosis in murine osteoclasts in vitro and in vivo (1995) J Bone Miner Res, 10 (10), pp. 1478-1487; Murakami, H., Takahashi, N., Sasaki, T., A possible mechanism of the specific action of bisphosphonates on osteoclasts: tiludronate preferentially affects polarized osteoclasts having ruffled borders (1995) Bone, 17 (2), pp. 137-144; Sahni, M., Guenther, H.L., Fleisch, H., Bisphosphonates act on rat bone resorption through the mediation of osteoblasts (1993) J Clin Invest, 91 (5), pp. 2004-2011; Fleisch, H., Bisphosphonates: mechanisms of action (1998) Endocr Rev, 19 (1), pp. 80-100; Shinoda, H., Adamek, G., Félix, R., Structure-activity relationships of various bisphosphonates (1983) Calcif Tissue Int, 35 (1), pp. 87-99; Pereira, J., Mancini, I., Walker, P., The role of bisphosphonates in malignant bone pain: a review (1998) J Palliat Care, 14 (2), pp. 25-36; Purohit, O.P., Radstone, C.R., Anthony, C., A randomized double-blind comparison of intravenous pamidronate and clodronate in the hypercalcemia of malignancy (1995) Br J Cancer, 72 (5), pp. 1289-1293; Hillner, B.E., Ingle, J.N., Chlebowski, R.T., American Society of Clinical Oncology 2003 update on the role of bisphosphonates and bone health issues in women with breast cancer (2003) J Clin Oncol, 21 (21), pp. 4042-4057. , [Erratum in J Clin Oncol 2004;22(7):1351]; Hillner, B.E., Ingle, J.N., Berenson, J.R., American Society of Clinical Oncology guideline on the role of bisphosphonates in breast cancer. American Society of Clinical Oncology Bisphosphonates Expert Panel (2000) J Clin Oncol, 18 (6), pp. 1378-1391; Lacerna, L., Hohneker, J., Zoledronic acid for the treatment of bone metastases in patients with breast cancer and other solid tumours (2003) Semin Oncol, 30 (5 SUPPL. 16), pp. 150-160; Lipton, A., Costa, L., Ali, S., Use of markers of bone turnover for monitoring bone metastases and the response to therapy (2001) Semin Oncol, 28 (4 SUPPL. 11), pp. 54-59; Brincker, H., Westin, J., Abildgaard, N., Failure of oral pamidronate to reduce skeletal morbidity in multiple myeloma: a double-blind placebo-controlled trial. Danish-Swedish Co-operative Study Group (1998) Br J Haematol, 101 (2), pp. 3280-3286; Berenson, J.R., Lichtenstein, A., Porter, L., Long-term pamidronate treatment of advanced multiple myeloma patients reduces skeletal events. Myeloma Aredia Study Group (1998) J Clin Oncol, 16 (7), pp. 593-602; Berenson, J.R., Vescio, R.A., Lee, S.R., Phase I dose-ranging trial of monthly infusions of zoledronic acid for the treatment of osteolytic bone metastases (2001) Clin Cancer Res, 7 (3), pp. 478-485; Van Poznak, C.H., The use of bisphosphonates in patients with breast cancer (2002) Cancer Control, 9 (6), pp. 480-489; Marx, R.E., Pamidronate (Aredia) and zoledronate (Zometa) induced avascular necrosis of the jaws: a growing epidemic (2003) J Oral Maxillofac Surg, 61 (9), pp. 1115-1117; Vannucchi, A.M., Ficarra, G., Antonioli, E., Osteonecrosis of the jaw associated with zoledronate therapy in patient with multiple myeloma (2005) Br J Haematol, 128 (6), pp. 738-739; Wang, J., Goodger, N.M., Pogrel, M.A., Osteonecrosis of the jaws associated with cancer chemotherapy (2003) J Oral Maxillofac Surg, 61 (9), pp. 1104-1107; Purcell, P.M., Boyd, I.W., Bisphosphonates and osteonecrosis of the jaw (2005) Med J Aust, 182 (8), pp. 417-418; Carter, G., Goss, A.N., Doecke, C., Bisphosphonates and avascular necrosis of the jaw: a possible association (2005) Med J Aust, 182 (8), pp. 413-415; Durie, B., Katz, M., Crowley, J., Osteonecrosis of the jaw and bisphosphonates (2005) N Engl J Med, 353, pp. 99-102; Migliorati, C.A., Bisphosphonates and oral cavity avascular bone necrosis (2003) J Clin Oncol, 21 (22), pp. 4253-4254; Robinson, N.A., Yeo, J.F., Bisphosphonates - a word of caution (2004) Ann Acad Med Singapore, 33 (4), pp. 48-49; Starck, W.J., Epker, B.N., Failure of osseointegrated dental implants after diphosphonate therapy for osteoporosis: a case report (1995) Int J Oral Maxillofac Implants, 10 (1), pp. 74-78; Melo, M., Obeid, G., Osteonecrosis of the maxilla in a patient with a history of bisphosphonate therapy (2005) J Can Dent Assoc, 71 (2), pp. 111-113
Keywords: Actinomyces israelii; adult; aged; amoxicillin; antibiotic therapy; article; avascular necrosis; Avascular osteonecrosis; biopsy; Bisphosphonates; Bone Density Conservation Agents; case report; clinical feature; cyclophosphamide; cyclosporin; dexamethasone; Diphosphonates; drug induced disease; drug inhibition; drug withdrawal; erythropoietin; Female; histology; human; Humans; hypercalcemia; Imidazoles; Jaw; jaw avascular osteonecrosis; male; Mandibular Diseases; morbidity; mortality; Multiple myeloma; osteolysis; Osteonecrosis; pain; panoramic radiography; pathologic fracture; priority journal; Radiography, Panoramic; risk assessment; spinal cord compression; thalidomide; tooth extraction; zoledronic acid

Linear and nonlinear heart-rate analysis in a rat model of acute anoxia - Gonçalves, H.; Henriques-Coelho, T.; Bernardes, J.; Rocha, A.P.; Nogueira, A.; Leite-Moreira, A. (Physiological MeasurementPhysiol. Meas., 2008)
The objective of this study was the assessment of heart-rate (HR) dynamics with linear and nonlinear methods during episodes of mechanical ventilation and acute anoxia in rats. Namely, to assess whether linear and nonlinear HR analysis was able to discriminate acute anoxia from baseline in rats and if this was consistent with human foetal and adult studies. Five HR segments of 1 min duration, during baseline recording, mechanical ventilation and first, second and third minutes of induced acute anoxia, were analysed in ten adult Wistar rats. Linear time and frequency domain and nonlinear methods were used, namely mean HR (mHR), long-term irregularity (LTI), interval index (II), low frequency (LF) and high frequency (HF), approximate entropy (ApEn) and sample entropy (SampEn). New parameters for the entropy indices are proposed for the analysis of rats' HR. Bootstrap percentile confidence intervals and nonparametric statistical tests were used in the evaluation of the differences between segments. During mechanical ventilation a clear spectral band was detectable at the ventilation rate, but mHR, II and the 'new' entropy indices were the only significantly changed indices. In the transition from baseline-mechanical- ventilation to mechanical-ventilation-induced anoxia, a statistically significant decrease of mHR, II and entropy indices was observed, clearly discriminating these two instances, whereas most linear indices increased. With continued anoxia, most linear indices decreased significantly, whereas entropy remained stably low. These results are consistent with other foetal human and non-human studies and evidence that the rat model may be used for further research on linear and nonlinear analysis of heart-rate dynamics. The transition from baseline to acute anoxia was encompassed by signs of increased activation of the autonomic nervous system sympathetic branch, and decreased or blunted activity of the HR complexity regulatory centres. © 2008 Institute of Physics and Engineering in Medicine.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: PMEAEdoi: 10.1088/0967-3334/29/9/010PubMed ID: 18784391Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Matemática Aplicada, Faculdade de Ciências, Universidade Do Porto, Rua do Campo Alegre 687, 4169-007 Porto, Portugal; email: hernani.goncalves@fc.up.ptReferences: American College of Obstetricians and Gynecologists. ACOG Practice Bulletin. Clinical Management Guidelines for Obstetrician-Gynecologists, Number 70, December 2005 (2005) Obstet. Gynecol., 106, pp. 1453-1460;Ayres-De-Campos, D., Bernardes, J., Garrido, A., Marques-De-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J. Mat. Fet. Med., 9 (5), pp. 311-318; Ayres-De-Campos, D., Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto® validation study (2005) Eur. J. Obstet. Gynecol. Reprod. Biol., 118 (1), pp. 52-60; Beckers, F., Verheyden, B., Aubert, A.E., Aging and nonlinear heart rate control in a healthy population (2006) Am. J. Physiol. Heart Circ. Physiol., 290 (6), pp. 2560-H2570; Beckers, F., Verheyden, B., Ramaekers, D., Swinghedauw, B., Aubert, A.E., Effects of autonomic blockade on non-linear cardiovascular variability indices in rats (2006) Clin. Exp. Pharmacol. Physiol., 33 (5-6), pp. 431-439; Bernardes, J., Ayres-De-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int. J. Gynecol. Obstet., 62 (2), pp. 141-147; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J. Perinat. Med., 19, pp. 61-65; Cerutti, C., Gustin, M.P., Paultre, C.Z., Lo, M., Julien, C., Vincent, M., Sassard, J., Autonomic nervous-system and cardiovascular variability in rats-a spectral-analysis approach (1991) Am. J. Physiol., 261, pp. 1292-H1299; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J. Matern. Fetal Invest., 8, pp. 23-26; Dudewicz, E., Mishra, S., (1988) Modern Mathematical Statistics; Felgueiras, C., Marques-De-Sá, J.P., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomedical Eng., 36, pp. 197-201; Gonçalves, H., Bernardes, J., Rocha, A.P., Ayres-De-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Human Develop., 83 (9), pp. 585-591; Gonçalves, H., Rocha, A.P., Ayres-De-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol. Meas., 27 (3), pp. 307-319; Gonçalves, H., Rocha, A.P., Ayres-De-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med. Biol. Eng. Comput., 44 (10), pp. 847-855; Hayes, M., (1996) Statistical Digital Signal Processing and Modelling; Henriques-Coelho, T., Correia-Pinto, J., Roncon-Albuquerque, R., Baptista, M.J., Lourenco, A.P., Oliveira, S.M., Brandao-Nogueira, A., Leite-Moreira, A.F., Endogenous production of ghrelin and beneficial effects of its exogenous administration in monocrotaline-induced pulmonary hypertension (2004) Am. J. Physiol. Heart Circ. Physiol., 287 (6), pp. 2885-H2890; Kuwahara, M., Yayou, K., Ishii, K., Hashimoto, S., Tsubone, H., Sugano, S., Power spectral analysis of heart rate variability as a new method for assessing autonomic activity in the rat (1994) J. Electrocardiology, 27 (4), pp. 333-337; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Wu, G., Shen, L., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) Eur. J. Obstet. Gynecol. Reprod. Biol., 114 (2), pp. 137-143; Lourenço, A.P., Roncon-Albuquerque, R., Bras-Silva, C., Faria, B., Wieland, J., Henriques-Coelho, T., Correia-Pinto, J., Leite-Moreira, A.F., Myocardial dysfunction and neurohumoral activation without remodeling in left ventricle of monocrotaline-induced pulmonary hypertensive rats (2006) Am. J. Physiol. Heart Circ. Physiol., 291 (4), pp. 1587-H1594; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000: Proc. IEEE-INNS-ENNS Int. Joint Conf. on Neural Network, 3, pp. 637-641; Martinez, W.L., Martinez, A.R., (2002) Computational Statistics Handbook with MATLAB; Moraru, L., Cimponeriu, L., Tong, S., Thakor, N., Bezerianos, A., Characterization of heart rate variability changes following asphyxia in rats (2004) Methods Inf. Med., 43 (1), pp. 118-121; Moraru, L., Tong, S., Malhotra, A., Geocadin, R., Thakor, N., Bezerianos, A., Investigation of the effects of ischemic preconditioning on the HRV response to transient global ischemia using linear and nonlinear methods (2005) Med. Eng. Phys., 27 (6), pp. 465-473; Murasato, Y., Hirakawa, H., Harada, Y., Nakamura, T., Hayashida, Y., Effects of systemic hypoxia on R-r interval and blood pressure variabilities in conscious rats (1998) Am. J. Physiol., 275, pp. 797-H804; Niklasson, U., Wiklund, U., Bjerle, P., Olofsson, B.O., Heart-rate variation-what are we measuring? (1993) Clin. Physiol., 13 (1), pp. 71-79; Pincus, S., Aproximate entropy (ApEn) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Pincus, S.M., Gevers, E.F., Robinson, I.C.A.F., Vandenberg, G., Roelfsema, F., Hartman, M.L., Veldhuis, J.D., Females secrete growth hormone with more process irregularity than males in both humans and rats (1996) Am. J. Physiol., 270, pp. 107-E115; Pincus, S., Viscarello, R., Approximate Entropy: A regularity measure for fetal heart rate analysis (1992) Obstet. Gynecol., 79, pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am. J. Physiol. Heart Circ. Physiol., 278, pp. 2039-H2049; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans. Biomed. Eng., 50 (3), pp. 365-373; Siira, S.M., Ojala, T.H., Vahlberg, T.J., Jalonen, J.O., Valimaki, I.A., Rosen, K.G., Ekholm, E.M., Marked fetal acidosis and specific changes in power spectrum analysis of fetal heart rate variability recorded during the last hour of labour (2005) BJOG, 112 (4), pp. 418-423; Task force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology, Heart rate variability-standards of measurement, physiological interpretation and clinical use (1996) Circulation, 93, pp. 1043-1065; Vieira, P., Marques-De-Sá, J.P., Bernardes, J., Fractal analysis of foetal heart rate (2004) Proc. Biosignal 2004, pp. 53-55
Keywords: acute disease; animal experiment; animal model; Animals; Anoxia; article; artificial ventilation; bootstrapping; controlled study; entropy; Female; Fetal monitoring; frequency analysis; Heart rate; Heart rate variability; Humans; Linear analysis; linear system; lung ventilation; Models, Cardiovascular; nonhuman; nonlinear system; priority journal; rat; Rats; Rats, Wistar; Rattus; Rattus norvegicus; Respiration, Artificial; Statistical analysis; Variability; Wistar rat; Wistar rats

Omniview-SisPorto® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis - Ayres-de-Campos, D.; Sousa, P.; Costa, A.; Bernardes, J. (Journal of Perinatal MedicineJ. Perinat. Med., 2008)
Visual analysis of cardiotocograms is poorly reproducible and is currently recognized as the main weakness of the STAN® methodology. The Omniview-SisPorto® 3.5 program is the most recent version of a central monitoring system that provides visual and sound alerts, based on computer analysis of cardiotocographic and ST event features. This paper describes the program's main characteristics and provides an overview of the system's online alerts. Omniview-SisPorto® 3.5 is the first central monitoring system to incorporate computerized analysis of cardiotocographic and ST event features, providing health professionals with online alerts for minor and major changes in monitored signals. The system is currently undergoing extensive clinical evaluation. © 2008 by Walter de Gruyter.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JPEMAdoi: 10.1515/JPM.2008.030Language of Original Document: EnglishCorrespondence Address: Ayres-De-Campos, D.; Departmento Ginecologia e Obstetricia, Faculdade de Medicina, Universidade Do Porto, Alameda Hernani Monteiro, 4200-319 Porto, Portugal; email: sisporto@med.up.ptTradenames: Omniview-SisPorto 3.5 system, SpeculumManufacturers: SpeculumReferences: Amer-Wahlin, I., Arulkumaran, S., Hagberg, H., Marsal, K., Visser, G., Fetal electrocardiogram: ST waveform analysis in intrapartum surveillance (2007) Br J Obstet Gynaecol, 114, pp. 1191-1193;Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marquesde-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Bernardes, J., Comparison of fetal heart rate baseline estimation by SisPorto 2.01 and a consensus of clinicians (2004) Eur J Obstet Gynecol Reprod Biol, 117, pp. 174-178; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Bernardes, J., Kwee, A., Westehuis, M., Visser, G.H.A., Computer quantification of short-term variability as an adjunct to fetal electrocardiographic monitoring (2007) Br J Obstet Gynaecol, 114, pp. 1446-1447; Bernardes, J., Moura, C., Marques de, S.J., Pereira Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Electronic fetal heart rate monitoring: Research guidelines for interpretation (1997) Am J Obstet Gynecol, 177, pp. 1385-1390. , National Institute of Child Health and Human Development Research Planning Workshop; Neilson, J.P., Fetal electrocardiogram (ECG) for fetal monitoring during labor (2006) Cochrane Database of Systematic Reviews, (3); Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-165; (2001) Evidence-based clinical guideline: The use of electronic fetal monitoring, , RCOG, Royal College of Obstetricians and Gynaecologists, London, RCOG Press; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, pp. 159-167
Keywords: article; Cardiotocography; computer program; Computer-assisted; Electrocardiography; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus hypoxia; fetus monitoring; Heart rate; human; Humans; instrumentation; online system; Pregnancy; priority journal; Signal processing; ST segment

PLD bioactive ceramic films: The influence of CaO-P 2O 5 glass additions to hydroxyapatite on the proliferation and morphology of osteblastic like-cells - Oliveira, G.M.; Ferraz, M.P.; González, P.G.; Serra, J.; Leon, B.; Pèrez-Amor, M.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2008)
This work consists on the evaluation of the in vitro performance of Ti6Al4V samples PLD (pulsed laser deposition) coated with hydroxyapatite, both pure and mixed with a CaO-P 2O 5 glass. Previous studies on immersion of PLD coatings in SBF, showed that the immersion apatite films did not present the usual cauliflower morphology but replicated the original columnar structure and exhibited good bioactivity. However, the influence of glass associated to hydroxyapatite concerning adhesion, proliferation and morphology of MG63 cells on the films surface was unclear. In this study, the performance of these PLD coated samples was evaluated, not only following the physical-chemical transformations resulting from the SBF immersion, but also evaluating the cytocompatibility in contact with osteoblast-like MG63 cells. SEM and AFM confirmed that the bioactive ceramic PLD films reproduce the substrate's surface topography and that the films presented good adherence and uniform surface roughness. Physical-chemical phenomena occurring during immersion in SBF did not modify the original columnar structure. In contact with MG63 cells, coated samples exhibited very good acceptance and cytocompatibility when compared to control. The glass mixed with hydroxyapatite induced higher cellular proliferation. Cells grown on these samples presented many filipodia and granular structures, typical features of osteoblasts. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3331-zPubMed ID: 18058197Language of Original Document: EnglishCorrespondence Address: Oliveira, G. M.; Universidade Fernando Pessoa, Praça Nove de Abril 349, 4249-004 Porto, Portugal; email: gisela@ufp.ptChemicals/CAS: calcium oxide, 1305-78-8; hydroxyapatite, 1306-06-5, 51198-94-8; oxide, 16833-27-5; Biocompatible Materials; Calcium Compounds; Ceramics; Durapatite, 1306-06-5; Oxides; Phosphorus Compounds; Polystyrenes; lime, 1305-78-8; phosphorus pentoxide, 1314-56-3References: Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487;Hench, L.L., (1998) Biomaterials, 19, p. 1419; Park, S.H., Llinás, A., Goel, V.K., Keller, J.C., (2000) The Biomedical Engineering Handbook, , Edited by: J. D. BRONZINO (CRC Press, LLC, Boca Raton); Hench, L.L., (1994) 7th International Symposium on Ceramics in Medicine, p. 3. , Edited by: Ö. H. A. A. Y. URPO (Butterworth-Heinemann Ltd Oxford, England); Kokubo, T., (1991) Biomaterials, 12, p. 155; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, p. 6. , JAAS Takayan Press. Ishiyaku euroAmerica, Inc Tokyo; Orlovskii, V.P., Komlev, V.S., Barinov, S.M., (2002) Inorg. Mater., 38, p. 973; Kenny, S.M., Buggy, M., (2003) J. Mater. Sci. Mat. Med., 14, p. 923; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1995) J. Mat. Sci. Mat. Med., 6, p. 348; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (2001) J. Mater. Sci.: Mater. Med., 12, p. 629; Ferraz, M.P., Monteiro, F.J., Gião, D., Léon, B., Gonzalez, P., Liste, S., Serra, J., Perez-Amor, M., (2004) Key Eng. Mat., 254-256, p. 347; Porter, A.E., Hobbs, L.W., Benezra Rosen, V., Spector, M., (2002) Biomaterials, 23, p. 725; Kim, H.-K., Jang, J.-W., Lee, C.-H., (2004) J. Mater. Sci.: Mater. Med., 15, p. 825; Harada, Y., Wang, J.-T., Doppalapudi, V.A., Willis, A.A., Jasty, M., Harris, W.H., Nagase, M., Goldring, S.R., (1996) J. Biomed. Mater. Res., 31, p. 19; Arias, J.L., Mayor, M.B., Pou, J., Léon, B., Pérez-Amor, M., (2000) Appl. Surf. Sci., 154-155, p. 434; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1996) J. Mater. Sci.: Mater. Med., 7, p. 187; Arias, J.L., Mayor, M.B., Pou, J., Leng, Y., Léon, B., Pérez-Amor, M., (2003) Biomaterials, 24, p. 3403; Arias, J.L., Mayor, M.B., Pou, J., Léon, B., Pérez-Amor, M., (2002) Appl. Surf. Sci., 182, p. 448; Arias, J.L., Mayor, M.B., Pou, J., Léon, B., Pérez-Amor, M., (2002) Vaccum, 67, p. 653; Arias, J.L., Garcia-Sanz, F.J., Mayor, M.B., Chiussi, S., Pou, J., Léon, B., Pérez-Amor, M., (1998) Biomaterials, 19, p. 883; Mayor, M.B., Arias, J.L., Chiussi, S., Garcia, F., Pou, J., Léon, B., Pérez-Amor, M., (1998) Thin Solid Films, 317, p. 363; Kokubo, T., Kushitani, H., Sakka, S., Kitsuki, T., Yamamuro, T., (1990) J. Biomed. Mater. Res., 24, p. 721; Monteiro, F.J., Ferraz, M.P., Gião, D., Leon, B., Gonzalez, P., Liste, S., Serra, J., Perez-Amor, M., (2002) 17th European Conference on Biomaterials, pp. P65. , Edited by: E. S. F. Biomaterials (Barcelona, Spain); Lossdörfer, S., Schwartz, Z., Wang, L., Lohmann, C.H., Turner, J.D., Wieland, M., Cochran, D.L., Boyan, B.D., (2004) J. Biomed. Mater. Res, 70, p. 361; Bannister, S.R., Lohmann, C.H., Liu, Y., Sylvia, V.L., Cochran, D.L., Dean, D.D., Boyan, B.D., Schwartz, Z., (2002) J. Biomed. Mater. Res., 60, p. 164; Cleries, L., Fernandez-Pradas, J.M., Sardin, G., Morenza, J.L., (1998) Biomaterials, 19, p. 1483; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., (1996) J. Mater. Sci.: Mater. Med., 7, p. 21; Knabe, C., Klar, F., Fitzner, R., Radlanski, R.J., Gross, U., (2002) Biomaterials, 23, p. 3235; Garcia, F., Arias, J.L., Mayor, M.B., Pou, J., Rehman, I., Knowles, J., Best, S., Bonefield, W., (1998) J. Biomed. Mater. Res. (Appl. Biomater), 43, p. 69; Peng, P., Kumar, S., Voelcker, N.H., Szili, E., Smart, R.S.C., Griesser, H.J., (2006) J. Biomed. Mater. Res., 76, p. 347; Borsari, V., Giavaresi, G., Fini, M., Torriceli, P., Salito, A., Chiesa, R., Chiusoli, L., Giardino, R., (2005) J. Biomed. Mater. Res. Part B: Appl. Biomater., 75, p. 359; Massaro, C., Baker, M.A., Cosentino, F., Ramires, P.A., Klose, S., Milella, E., (2001) J. Biomed. Mater. Res., 58, p. 651; Bigi, A., Bracci, B., Cuisinier, F., Elkaim, R., Fini, M., Mayer, I., Mihailescu, I.N., Torricelli, P., (2005) Biomaterials, 26, p. 2381; Zeng, H., Lacefield, W.R., (2000) J. Biomed. Mater. Res., 50, p. 239; Clèries, L., Fernandez-Pradas, J.M., Morenza, J.L., (2000) Biomaterials, 21, p. 1861; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 45, p. 376; Li, P., Ducheyne, P., (1998) J. Biomed. Mater. Res., 41, p. 341; Weng, J., Liu, Q., Wolke, J.G., Zhang, X., De Groot, K., (1997) Biomaterials, 18, p. 1027; Tas, A.C., (2000) Biomaterials, 21, p. 1429; Kokubo, T., Kim, H.-M., Kawashita, M., (2003) Biomaterials, 24, p. 2161; Dewez, J.-L., Doren, A., Schneider, Y.-J., Rouxhet, P.G., (1999) Biomaterials, 20, p. 547; Anselme, K., Linez, P., Bigerelle, M., Le Maguer, D., Le Maguer, A., Hardouin, P., Hildebrand, H.F., Leroy, J.M., (2000) Biomaterials, 21, p. 1567; Okumura, A., Goto, M., Goto, T., Yoshinari, M., Masuko, S., Katsuki, T., Tanaka, T., (2001) Biomaterials, 22, p. 2263; Kim, H.J., Kim, S.H., Kim, M.S., Lee, E.J., Oh, H.G., Oh, W.M., Park, S.W., Dean, D.D., (2005) J. Biomed. Mater. Res., 74, p. 366
Keywords: Apatite; Apatite films; Bioactive ceramic films; Bioactive glass; Bioactivity; Bioceramics; Biocompatible Materials; Biofilms; Brassica oleracea var. botrytis; Calcium Compounds; calcium oxide; Cauliflower morphology; cell adhesion; cell proliferation; cell structure; cell survival; ceramics; Columnar structure; conference paper; controlled study; Durapatite; glass; human; human cell; Humans; hydroxyapatite; Lasers; materials testing; Microscopy, Atomic Force; Microscopy, Electron, Scanning; morphology; osteoblast; Osteoblasts; oxide; Oxides; phosphorous pentoxide; Phosphorus Compounds; Polystyrenes; priority journal; Pulsed laser deposition; unclassified drug

Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation - Amaral, I.F.; Cordeiro, A.L.; Sampaio, P.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2007)
Chitosan (Ch) is being actively investigated as a non-protein template for the growth of an increasing number of anchorage-dependent cells, including chondrocytes and bone cells. In the present work, Ch films with degrees of N-acetylation (DAs) in the range of 4 to 49% were evaluated with respect to the attachment, spreading and short-term proliferation of osteoblasts, using human osteoblastic MG-63 cells. The films were characterized in terms of surface morphology and surface charge by atomic force microscopy and streaming potential measurements, respectively. Cell attachment was assessed after 3 and 24 h of cell culture. After 24 h of incubation, cell attachment was found to be dependent on the DA, lower DAs favouring cell adhesion. With time, cell spreading and cytoskeleton organization were only attained for DAs ≤ 13%. Regarding cell proliferation, cells grown on films with the lowest DA (4%) revealed a higher specific growth rate as compared to those grown on films with higher DAs. Films with a DA of 49% failed to sustain cell proliferation. In addition, a longer lag-phase was observed on Ch, as compared to TCPS, in accordance to an observed delay of cell spreading. The present findings revealed that differences in the DA as small as 9% may be critical in terms of the osteoblast response to two-dimensional Ch-based matrices. © 2007 VSP.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBSEEdoi: 10.1163/156856207780425068Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; Biocompatible Materials; Chitosan, 9012-76-4References: Vacanti, C.A., Bonassar, L.J., Vacanti, J.P., (2000) Principles of Tissue Engineering, p. 671. , R. P. Lanza, R. Langer and J. Vacanti Eds, p, Academic Press, San Diego, CA;Bruder, S.P., Caplan, A.I., (2000) Principles of Tissue Engineering, p. 683. , R. P. Lanza, R. Langer and J. Vacanti Eds, p, Academic Press, San Diego, CA; Burg, K.J.L., Porter, S., Kellam, J.F., (2000) Biomaterials, 21, p. 2347; Khor, E., Lim, L.Y., (2003) Biomaterials, 24, p. 2339; Nettles, D.L., Elder, S.H., Gilbert, J.A., (2002) Tissue Eng, 8, p. 1009; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., (2002) J. Control. Rel, 78, p. 187; Muzzarelli, R.A.A., (1997) Cell. Mol. Life Sci, 53, p. 131; Madihally, S.V., Matthew, H.W.T., (1999) Biomaterials, 20, p. 1133; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., (2000) Biomaterials, 21, p. 2315; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., (2000) J. Biomed. Mater. Res, 51, p. 586; Ho, M.H., Wang, D.M., Hsieh, H.J., Liu, H.C., Hsien, T.Y., Lai, J.Y., Hou, L.T., (2005) Biomaterials, 26, p. 3197; A. Domard, in: Advances in Chitin Science, II, A. Domard, G. A. F. Roberts and K. M. Varum (Eds), p. 410. Jacques André, Lyon (1997)Tomihata, K., Ikada, Y., (1997) Biomaterials, 18, p. 567; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., (1992) Int. J. Biol. Macromol, 14, p. 166; Anselme, K., (2000) Biomaterials, 21, p. 667; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., (2000) J. Mater. Sci. Mater. Med, 11, p. 773; Chatelet, C., Damour, O., Domard, A., (2001) Biomaterials, 22, p. 261; Dhiman, H.K., Ray, A.R., Panda, A.K., (2004) Biomaterials, 25, p. 5147; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., (2001) Polymer, 42, p. 3569; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., (1983) J. Appl. Polym. Sci, 28, p. 1909; Aiba, S., (1986) Int. J. Biol. Macromol, 8, p. 173; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., (1996) Carbohydr. Polym, 29, p. 63; (1987) Guideline on Validation of the Limulus Amebocyte Lysate Test as an End-product Endotoxin Test for Human and Animal Parental Drugs, Biological Products, and Medical Devices, , US Department of Health and Human Services, Public Health Service, Food and Drug Administration, US Department of Health and Human Services, Washington, DC; Nakagawa, Y., Murai, T., Hasegawa, C., Hirata, M., Tsuchiya, T., Yagami, T., Haishima, Y., (2003) J. Biomed. Mater. Res, 66 B, p. 347; Walker, S.L., Bhattacharjee, S., Hoek, E.M.V., Elimelech, M., (2002) Langmuir, 18, p. 2193; Clover, J., Gowen, M., (1994) Bone, 15, p. 585; Mosmann, T., (1983) J. Immunol. Methods, 65, p. 55; Domke, J., Dannohl, S., Parak, W.J., Muller, O., Aicher, W.K., Radmacher, M., (2000) Colloid Surfaces B: Biointerfaces, 19, p. 367; Sorlier, P., Denuziere, A., Viton, C., Domard, A., (2001) Biomacromolecules, 2, p. 765; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J. Biomed. Mater. Res, 75 A, p. 387; Andrade, J.D., Smith, L.M., Gregonis, D.E., (1985) Surface and Interfacial Aspects of Biomedical Polymers, 1, p. 249. , J. D. Andrade Ed, p, Plenum Press, New York, NY; Dewez, J.L., Doren, A., Schneider, Y.J., Rouxhet, P.G., (1999) Biomaterials, 20, p. 547; Kikuchi, T., Yoshikai, Y., Miyoshi, J., Katsuki, M., Musikacharoen, T., Mitani, A., Tanaka, S., Matsuguchi, T., (2003) J. Dent. Res, 82, p. 546; Denuziere, A., Ferrier, D., Damour, O., Domard, A., (1998) Biomaterials, 19, p. 1275; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2005) Biomaterials, 26, p. 485; Wang, J.H., Wei, C.W., Liu, H.C., Young, T.H., (2003) J. Biomed. Mater. Res, 64 A, p. 606; Michael, K.E., Vernekar, V.N., Keselowsky, B.G., Meredith, J.C., Latour, R.A., Garcia, A.J., (2003) Langmuir, 19, p. 8033; Keselowsky, B.G., Collard, D.M., Garcia, A.J., (2003) J. Biomed. Mater. Res, 66 A, p. 247; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., (2003) J. Biomed. Mater. Res, 67 A, p. 538; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., (1999) J. Biomed. Mater. Res, 44, p. 1; Cowles, E.A., Brailey, L.L., Gronowicz, G.A., (2000) J. Biomed. Mater. Res, 52, p. 725; Marco, R.A.W., Diaz-Montero, C.M., Wygant, J.N., Kleinerman, E.S., McIntyre, B.W., (2003) J. Cell. Biochem, 88, p. 1038; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Dean, D.D., Boyan, B.D., (1995) J. Biomed. Mater. Res, 29, p. 389; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., (2000) J. Biomed. Mater. Res, 49, p. 155; Zinger, O., Anselme, K., Denzer, A., Habersetzer, P., Wieland, M., Jeanfils, J., Hardouin, P., Landolt, D., (2004) Biomaterials, 25, p. 2695
Keywords: Acetylation; AFM; article; Atomic force microscopy; Biocompatible Materials; biofilm; Biofilms; biomaterial; bone cell; cartilage cell; cell adhesion; cell anchorage; Cell culture; cell growth; Cell Line, Tumor; cell proliferation; Cell Shape; cell spreading; cell survival; Chemical structure; chemistry; Chitin; chitosan; comparative study; controlled study; cytoskeleton; Degree of acetylation; drug effect; Growth kinetics; human; human cell; Humans; incubation time; metabolism; Microscopy, Atomic Force; osteoblast; Osteoblast-like cells; Osteoblasts; Pathology; priority journal; Surface charge; Surface Properties; surface property; Surface treatment; tumor cell line; Zeta potential

Opening wedge high tibial osteotomy using 3D biomodelling Bonelike® macroporous structures: Case report - Gutierres, M.; Dias, A.G.; Lopes, M.A.; Hussain, N.S.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2007)
Two synthetic calcium phosphates in porous wedge shape, Bonelike® and a commercial HA/β-TCP biphasic material, were used as an alternative to bone autografts and allografts in the treatment of medial compartment osteoarthritis of varus knees. The structure of Bonelike® has a 3D architecture that is computer controlled, and a composition that mimics the mineral composition of natural bone. The HA/β-TCP biphasic material used as a control material in this study was prepared using conventional foaming based methods. No signs of inflammatory reactions were observed post-operatively for both materials. After 4 months signs of fusion at the osteotomy site and good integration of the implanted wedges were observed, showing good mechanical resistance. Concerning the final correction attained, the left knee revealed a satisfactory valgus of 10°, but the right one only had a final value of 6°. The clinical evaluation using International Knee Score (IKS) showed good outcome in all parameters with complete range of motion in both knees and climbing stairs without crutches with only slight pain. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3171-xPubMed ID: 17569003Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Instituto de Engenharia Biomédica (INEB), Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; Bone Substitutes; Calcium Phosphates; Ceratite, 124097-42-3; HydroxyapatitesTradenames: BonelikeReferences: Gaasbeek, R.D.A., Welsing, R.T.C., Verdonschot, N., Rijnberg, W.J., Van Loon, C.J.M., Van Kampen, A., (2005) Knee Surg. Sports Traumatol. Arthrosc., 13, p. 689. , 8;Scott, W.N., Clarke, H.D., (2004) Orthopedics, 27, p. 975. , 9; Virolainen, P., Aro, H.T., (2004) Arch. Orthop. Trauma Surg., 124, p. 258. , 4; Wright, J.M., Crockett, H.C., Slawski, D.P., Madsen, M.W., Windsor, R.E., (2005) J. Am. Acad. Orthop. Surg., 13, p. 279. , 4; Fujisawa, Y., Masura, K., Shiomi, S., (1979) Clin. Orthop. North Am., 10, p. 585; Odenbridge, S., Egund, N., Lindstrand, A., Lohmander, L.S., Willen, H., (1992) Clin Orthop., 277, p. 210; Koshino, T., Wada, S., Ara, Y., Saito, T., (2003) Knee, 10, p. 229; Hernigou, P., (2002) Knee, 9, p. 15. , 1; Hoell, S., Suttmoeller, J., Stoll, V., Fuchs, S., Gosheger, G., (2005) Arch. Orthop. Trauma Surg., 125, p. 638. , 9; Betz, R.R., (2002) Orthopedics, 25, p. 561. , 5; Legeros, R.Z., (2002) Clin. Orthop. Relat. Res., 395, p. 81; Steffen, T., Stoll, T., Arvinte, T., Schenk, R.K., (2001) Eur. Spine J., 10, p. 132; Chu, T.M.G., Orton, D.G., Hollister, S.J., Feinberg, S.E., Halloran, J.W., (2002) Biomaterials, 23, p. 1283. , 5; Hutmacher, D.W., Sittinger, M., Risbud, M.V., (2004) Trends Biotechnol., 22, p. 354. , 7; Jones, J.R., Ehrenfried, L.M., Hench, L.L., (2006) Biomaterials, 27, p. 964. , 7; Gauthier, O., Bouler, J.M., Aguado, E., Pilet, P., Daculsi, G., (1998) Biomaterials, 19, p. 133. , 1-3; LU, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Thierry, B., (1999) J. Mater. Sci. Mater. Med., 10, p. 111. , 2; Martina, M., Subramanyam, G., Weaver, J.C., Hutmacher, D.W., Morse, D.E., Valiyaveettil, S., (2005) Biomaterials, 26, p. 5609. , 28; Moroni, L., De Wijn, J.R., Van Blitterswijk, C.A., (2006) Biomaterials, 27, p. 974. , 7; Duarte, F., Santos, J.D., Afonso, A., (2004) Adv. Mater. Forum, 455-456, p. 370; Lobato, J.V., Hussain, N.S., Botelho, C.M., Mauricio, A.C., Lobato, J.M., Lopes, M.A., Afonso, A., Santos, J.D., (2006) Thin Solid Films, 515, p. 279. , 1; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Santos, J.D., (2005) Bioceramics, 17, p. 1041; Lobato, J.V., Hussain, N.S., Botelho, C.M., Rodrigues, J.M., Luís, A.L., Maurício, A.C., Lopes, M.A., Santos, J.D., (2005) Key Eng. Mater., 284-286, p. 877; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Leong, K.F., Cheah, C.M., Chua, C.K., (2003) Biomaterials, 24, p. 2363. , 13; Hutmacher, D.W., (2001) J. Biomater. Sci. Polym. Ed., 12, p. 107. , 1; Santos, J., Hastings, G., Knowles, J., Sintered hydroxyapatite compositions and method for the preparation thereof (1999), Worldwide Application (PCT), Patent No. 1 189 851Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244. , 2; Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905. , 18; Schwartz, C., Liss, P., Jacquemaire, B., Lecestre, P., Frayssinet, P., (1999) J. Mater. Sci. Mater. Med., 10, p. 821. , 12; Van Hemert, W.L.W., Willems, K., Anderson, P.G., Van Heerwaarden, R.J., Wymenga, A.B., (2004) Knee, 11, p. 451. , 6; Gaasbeek, R.D.A., Toonen, H.G., Van Heerwaarden, R.J., Buma, P., (2005) Biomaterials, 26, p. 6713. , 33; Hernigou, P., Ma, W., (2001) Knee, 8, p. 103. , 2; Koshino, T., Murase, T., Saito, T., (2003) J. Bone Joint Surg. Am., 85, p. 78. , 1; Koshino, T., Murase, T., Takagi, T., Saito, T., (2001) Biomaterials, 22, p. 1579. , 12; Zhim, F., Laflamme, G.Y., Viens, H., Saidane, K., Yahia, L., (2005) Clin. Biomech., 20, p. 871. , 8; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085. , 21; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 48, p. 734. , 5
Keywords: adult; article; Biological organs; Biomodeling; Bone; bone allograft; Bone graft; bone mineral; Bone Substitutes; calcium phosphate; Calcium phosphates; case report; climbing; clinical evaluation; Computer simulation; Grafts; human; Humans; hydroxyapatite; Hydroxyapatites; Imaging, Three-Dimensional; knee; knee pain; Macroporous structures; male; Mechanical properties; Middle Aged; Osteoarthritis; Osteoarthritis, Knee; Osteoblasts; osteotomy; pain assessment; porosity; Porous wedge shapes; priority journal; Prostheses and Implants; range of motion; structure analysis; tibia; tibia osteotomy; Tibial osteotomy; Valgus; valgus knee

Physicochemical degradation studies of calcium phosphate glass ceramic in the CaO-P 2O 5-MgO-TiO 2 system - Dias, A.G.; Gibson, I.R.; Santos, J.D.; Lopes, M.A. (Acta BiomaterialiaActa Biomater., 2007)
The aim of this work was to evaluate the in vitro degradation behaviour of a 45CaO-37P 2O 5-5MgO-13TiO 2 (mol.%) glass ceramic, under two different simulated physiological conditions: normal physiological pH 7.4, and pH 3.0, which was designed to simulate the acidic conditions produced by osteoclast cells. The in vitro testing was carried out at 37 °C for up to 42 days for the pH 7.4 solution and for up to 1 day for the pH 3.0 solution. The incorporation of TiO 2 into the glass structure leads to the precipitation of specific crystalline phases in the glass matrix, namely α- and β-Ca 2P 2O 7, TiP 2O 7 and CaTi 4(PO 4) 6. The degradation testing at pH 3.0 showed a higher weight loss compared with degradation testing at pH 7.4; the weight loss under the acidic condition after 1 day (24 h) was about 10 times higher than the weight loss after 42 days of immersion at pH 7.4. The ionic release profile of Ca 2+, PO 4 3 -, Mg 2+ and Ti 4+ showed a continuous increase in concentration over all immersion times for both testing solutions. After 1 day of immersion at pH 3.0, the concentration levels of Mg 2+, Ca 2+, PO 4 3 - were about six times higher than the levels achieved after 42 days of immersion at pH 7.4. The glass ceramic showed similar degradation to hydroxyapatite, and therefore has potential to be used in certain clinical applications where relatively slow resorption of the implant and replacement by bone is required, e.g. cranioplasty. © 2006 Acta Materialia Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2006.09.009PubMed ID: 17150421Language of Original Document: EnglishCorrespondence Address: Lopes, M.A.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: malopes@fe.up.ptChemicals/CAS: calcium ion, 14127-61-8; hydroxyapatite, 1306-06-5, 51198-94-8; phosphate, 14066-19-4, 14265-44-2; titanium, 7440-32-6; Biocompatible Materials; Calcium Compounds; calcium phosphate, 10103-46-5; Calcium Phosphates; Ceramics; Glass ceramics, 85422-94-2; lime, 1305-78-8; Magnesium Oxide, 1309-48-4; Oxides; Phosphorus Compounds; phosphorus pentoxide, 1314-56-3; titanium dioxide, 13463-67-7; Titanium, 7440-32-6References: (2003) Bone graft substitutes, , Laurencin C.T. (Ed), ASTM International;(1993) Introduction to bioceramics, , Hench L.L., and Wilson J. (Eds), World Scientific, Singapore; Ratner, B.D., Bryant, S.J., Biomaterials: where we have been and where we are going (2004) Ann Rev Biomed Eng, 6, p. 41; Fuchs, J.R., Nasseri, B.A., Vacanti, J.P., Tissue engineering: a 21st century solution to surgical reconstruction (2001) Ann Thorac Surg, 72, p. 577; Nasseri, B.A., Ogawa, K., Vacanti, J.P., Tissue engineering: an evolving 21st-century science to provide biologic replacement for reconstruction and transplantation (2001) Surgery, 130, p. 781; Stock, U.A., Vacanti, J.P., Tissue engineering: current state and prospects (2001) Ann Rev Med, 52, p. 443; Burnie, J., Gilchrist, T., Controlled release glass (CRG) - a new biomaterials (1983) Ceramics in Surgery, p. 169. , Vicenzi P. (Ed), Elsevier, Amsterdam; Burnie, J., Gilchrist, T., Duff, S.R.I., Drake, C.F., Harding, N.G.L., Malcolm, A.J., Controlled release glasses (CRG) for biomedical uses (1981) Biomaterials, 2, p. 244; (2004) Biomaterials Science: An Introduction to Materials in Medicine, , Ratner B.D., Hoffmam A.S., Schoen F.J., and Lemons F.J. (Eds), Elsevier, Amsterdam; Vogel, J., Wange, P., Hartmann, P., Phosphate glasses and glass-ceramics for medical applications (1997) Glastech Ber-Glass, 70, p. 220; Dorozhkin, S.V., Epple, M., Biological and medical significance of calcium phosphates (2002) Angew Chem Int Edit, 41, p. 3130; Grambow, B., Geochemical approach to glass dissolution (1992) Corrosion of Glass, Ceramics and Ceramic Superconductors, , Clark D.E., and Zoitos B.K. (Eds), Noyes, Park Ridge, NJ; Legeros, R.Z., Biodegradation and bioresorption of calcium phosphate ceramics (1993) Clin Mater, 14, p. 65; Lettuec, J.C., Clément, D., Lesprit, E., Faber, J., The use of calcium phosphates, their biological properties (2000) Eur J Orthopaedic Surg Traumatol, 10, p. 223; McCracken, W.J., Corrosion of glass-ceramics (1992) Corrosion of Glass, Ceramics and Ceramic Superconductors, , Clark D.E., and Zoitos B.K. (Eds), Noyes, Park Ridge, NJ; Dias, A.G., Costa, M.A., Lopes, M.A., Santos, J.D., Fernandes, M.H., Biological activity of two glass ceramics in the meta- and pyrophosphate region: a comparative study (2004) Key Eng Mater, 254-256, p. 825; Dias, A.G., Lopes, M.A., Afonso, A.A., Tsuru, K., Hayakawa, S., Takashima, S., In vivo performance of biodegradable calcium phosphate glass ceramics using the rabbit model: histological and SEM observation (2006) J Biomater Appl, 20, p. 253; Dias, A.G., Lopes, M.A., Cabral, A.T.T., Santos, J.D., Fernandes, M.H., In vitro studies of calcium phosphate glass ceramics with different solubility with the use of human bone marrow cells (2005) J Biomed Mater Res A, 74 A, p. 347; Dias, A.G., Skakle, J.M.S., Gibson, I.R., Lopes, M.A., Santos, J.D., In situ thermal and structural characterization of bioactive calcium phosphate glass ceramics containing TiO 2 and MgO oxides: high temperature XRD studies (2005) J Non-Cryst Solids, 351, p. 810; Baron, R., Neff, L., Louvard, D., Courtoy, P.J., Cell-mediated extracellular acidification and bone-resorption - evidence for a low ph in resorbing lacunae and localization of a 100-kD lysosomal membrane-protein at the osteoclast ruffled border (1985) J Cell Biol, 101, p. 2210; Teitelbaum, S.L., Bone resorption by osteoclasts (2000) Science, 289, p. 1504; Dias, A.G., Tsuru, K., Hayakawa, T., Lopes, M.A., Santos, J.D., Osaka, A., Crystallisation studies of biodegradable CaO-P 2O 5 glass with MgO and TiO 2 for bone regeneration applications (2004) Glass Tech, 45, p. 78; Nyquist, R.A., (1997) Handbook of infrared and raman spectra of inorganic compounds and organics salts, , Academic Press, New York; Tadic, D., Epple, M., A thorough physicochemical characterisation of 14 calcium phosphate-based bone substitution materials in comparison to natural bone (2004) Biomaterials, 25, p. 987; Ploska, U., Berger, G., Solubility of compositions in the system CaTixZr 4 - x(PO 4) 6 with x = 0-4 (1997) Biomaterials, 18, p. 1671; Lin, F.H., Liao, C.J., Chen, K.S., Sun, J.S., Liu, H.C., Degradation behaviour of a new bioceramic: Ca 2P 2O 7 with addition of Na 4P 2O 7 · 10H 2O (1997) Biomaterials, 18, p. 915; Koerten, H.K., van der Meulen, J., Degradation of calcium phosphate ceramics (1999) J Biomed Mater Res, 44, p. 78; Athanasou, N.A., Cellular biology of bone-resorbing cells (1996) J Bone Joint Surg Am, 78, p. 1096; Aoki, H., (1991) Science and medical applications of hydroxyapatite, , Takayama Press, Tokyo; Aoki, H., (1994) Medical applications of hydroxypatite, , Ishiyaku EuroAmerica, Inc., Tokyo; Hennequin, M., Douillard, Y., Effects of citric-acid treatment on the Ca, P and Mg contents of human dental roots (1995) J Clin Periodontol, 22, p. 550; Hennequin, M., Pajot, J., Avignant, D., Effects of different pH values of citric-acid solutions on the calcium and phosphorus contents of human root dentin (1994) J Endod, 20, p. 551; Misra, D.N., Interaction of citric-acid with hydroxyapatite - formation of calcium citrate (1995) J Dent Res, 74, p. 72; Misra, D.N., Interaction of citric acid with hydroxyapatite: surface exchange of ions and precipitation of calcium citrate (1996) J Dent Res, 75, p. 1418; Ribeiro, C.C., Barbosa, M.A., Machado, A., Tudor, A., Davies, M.C., Modifications in the molecular structure of hydroxyapatite induced by titanium ions (1995) J Mater Sci Mater Med, 6, p. 829; Tanizawa, Y., Sawamura, K., Suzuki, T., Reaction characteristics of dental and synthetic apatites with Al 3+ and La 3+ ions in acidic solutions (1990) J Chem Soc Faraday T, 86, p. 4025; Tanizawa, Y., Sawamura, K., Suzuki, T., Reaction characteristics of dental and synthetic apatites with Fe 2+ and Fe 3+ ions (1990) J Chem Soc Faraday T, 86, p. 1071; Gross, U., Muller-Mai, C., Voigt, C., Mesgarian, M., Berger, G., Ploska, U., Tissue response in the femur of rabbits after implantation of a new calcium titanium phosphate composition (2001) Key Eng Mater, 192-195, p. 383; Kitsugi, T.l.T., Yamamuro, T., Nakamura, T., Oka, M., Transmission electron microscopy observations at the interface of bone and four types of calcium phosphate ceramics with different calcium/phosphorous molar ratios (1995) Biomaterials, 16, p. 1101; Sun, J.-S., Chang, W.H.-S., Chen, L.-T., Huang, Y.-C., Juang, L.-W., Lin, F.-H., The influence on gene-expression profiling of osteoblasts behavior following treatment with the ionic products of sintered β-dicalcium pyrophosphate dissolution (2004) Biomaterials, 25, p. 607; Chun, S., Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., Biodegradation study of potassium calcium metaphosphate in the SBF and Tris-buffer solution (2002) Key Eng Mater, 218-220, p. 149
Keywords: acidity; article; Biocompatible Materials; Biomaterials; Bone; Bone and Bones; bone prosthesis; Calcium Compounds; calcium ion; calcium phosphate ceramic; Calcium phosphates; ceramics; Chemical structure; concentration response; controlled study; cranioplasty; Crystallization; Degradation; glass; Hydrogen-Ion Concentration; hydroxyapatite; In vitro biodegradation; in vitro study; Magnesium Oxide; materials testing; Microscopy, Electron, Scanning; Models, Statistical; osteoclast; Oxides; pH; phosphate; Phosphorus Compounds; physical chemistry; priority journal; prosthesis material; simulation; Spectrum Analysis, Raman; structure analysis; temperature; Time Factors; Titanium; weight reduction

Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix - Evangelista, M.B.; Hsiong, S.X.; Fernandes, R.; Sampaio, P.; Kong, H.-J.; Barrias, C.C.; Salema, R.; Barbosa, M.A.; Mooney, D.J.; Granja, P.L. (BiomaterialsBiomaterials, 2007)
There is a need for new therapeutic strategies to treat bone defects caused by trauma, disease or tissue loss. Injectable systems for cell transplantation have the advantage of allowing the use of minimally invasive surgical procedures, and thus for less discomfort to patients. In the present study, it is hypothesized that Arg-Gly-Asp (RGD)-coupled in a binary (low and high molecular weight) injectable alginate composition is able to influence bone cell differentiation in a three-dimensional (3D) structure. Viability, metabolic activity, cytoskeleton organization, ultrastructure and differentiation (alkaline phosphatase (ALP), von Kossa, alizarin red stainings and osteocalcin quantification) of immobilized cells were assessed. Cells within RGD-modified alginate microspheres were able to establish more interactions with the synthetic extracellular matrix as visualized by confocal laser scanning microscope and transmission electron microscopy imaging, and presented a much higher level of differentiation (more intense ALP and mineralization stainings and higher levels of osteocalcin secretion) when compared to cells immobilized within unmodified alginate microspheres. These findings demonstrate that peptides covalently coupled to alginate were efficient in influencing cell behavior within this 3D system, and may provide adequate preparation of osteoblasts for cell transplantation. © 2007 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 39Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2007.04.028PubMed ID: 17532040Language of Original Document: EnglishCorrespondence Address: Evangelista, M.B.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: mbe@ineb.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; alkaline phosphatase, 9001-78-9; arginylglycylaspartic acid, 99896-85-2; DNA, 9007-49-2; osteocalcin, 136461-80-8; Alginates; alginic acid, 9005-32-7; Alkaline Phosphatase, EC 3.1.3.1; arginyl-glycyl-aspartic acid, 99896-85-2; Glucuronic Acid, 576-37-4; Hexuronic Acids; Oligopeptides; Osteocalcin, 104982-03-8References: de Vos, P., de Haan, B., Wolters, G.H.J., VanSchilfgaarde, R., Factors influencing the adequacy of microencapsulation of rat pancreatic islets (1996) Transplantation, 62 (7), pp. 888-893;Brissova, M., Lacik, I., Powers, A.C., Anilkumar, A.V., Wang, T., Control and measurement of permeability for design of microcapsule cell delivery system (1998) J Biomed Mater Res, 39 (1), pp. 61-70; Strand, B.L., Gaserod, O., Kulseng, B., Espevik, T., Skjak-Braek, G., Alginate-polylysine-alginate microcapsules: effect of size reduction on capsule properties (2002) J Microencapsul, 19 (5), pp. 615-630; Chang, T.M.S., Artificial liver support based on artificial cells with emphasis on encapsulated hepatocytes (1992) Artif Organs, 16 (1), pp. 71-74; Uludag, H., Sefton, M.V., Microencapsulated human hepatoma (HepG2) cells-in-vitro growth and protein release (1993) J Biomed Mater Res, 27 (10), pp. 1213-1224; Canaple, L., Rehor, A., Hunkeler, D., Improving cell encapsulation through size control (2002) J Biomater Sci Polym Ed, 13 (7), pp. 783-796; Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomaterials, 21 (23), pp. 2405-2412; LeBaron, R.G., Athanasiou, K.A., Extracellular matrix cell adhesion peptides: functional applications in orthopedic materials (2000) Tissue Eng, 6 (2), pp. 85-103; Gumbiner, B.M., Cell adhesion: the molecular basis of tissue architecture and morphogenesis (1996) Cell, 84 (3), pp. 345-357; Majmudar, G., Bole, D., Goldstein, S.A., Bonadio, J., Bone cell-culture in a 3-dimensional polymer bead stabilizes the differentiated phenotype and provides evidence that osteoblastic cells synthesize type-III collagen and fibronectin (1991) J Bone Miner Res, 6 (8), pp. 869-881; Payne, R.G., Yaszemski, M.J., Yasko, A.W., Mikos, A.G., Development of an injectable, in situ crosslinkable, degradable polymeric carrier for osteogenic cell populations. Part 1. Encapsulation of marrow stromal osteoblasts in surface crosslinked gelatin microparticles (2002) Biomaterials, 23 (22), pp. 4359-4371; Lee, K.Y., Alsberg, E., Mooney, D.J., Degradable and injectable poly(aldehyde guluronate) hydrogels for bone tissue engineering (2001) J Biomed Mater Res, 56 (2), pp. 228-233; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dental Res, 80 (11), pp. 2025-2029; Burdick, J.A., Anseth, K.S., Photoencapsulation of osteoblasts in injectable RGD-modified PEG hydrogels for bone tissue engineering (2002) Biomaterials, 23 (22), pp. 4315-4323; Smidsrod, O., Skjak-Braek, G., Alginate as immobilization matrix for cells (1990) Trends Biotechnol, 8 (3), pp. 71-78; Boontheekul, T., Kong, H.J., Mooney, D.J., Controlling alginate gel degradation utilizing partial oxidation and bimodal molecular weight distribution (2005) Biomaterials, 26 (15), pp. 2455-2465; Kong, H.J., Alsberg, E., Kaigler, D., Lee, K.Y., Mooney, D.J., Controlling degradation of hydrogels via the size of cross-linked junctions (2004) Adv Mater, 16 (21), pp. 1917-1921; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20 (1), pp. 45-53; Bouhadir, K.H., Lee, K.Y., Alsberg, E., Damm, K.L., Anderson, K.W., Mooney, D.J., Degradation of partially oxidized alginate and its potential application for tissue engineering (2001) Biotechnol Prog, 17 (5), pp. 945-950; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24 (22), pp. 4023-4029; Bouhadir, K.H., Hausman, D.S., Mooney, D.J., Synthesis of cross-linked poly(aldehyde guluronate) hydrogels (1999) Polymer, 40 (12), pp. 3575-3584; Labarca, C., Paigen, K., Simple, rapid, and sensitive DNA assay procedure (1980) Anal Biochem, 102 (2), pp. 344-352; Caron, J.M., Kirschner, M.W., Autoregulation of tubulin synthesis (1986) Bioessays, 5 (5), pp. 211-216; Poole, C.A., Brookes, N.H., Clover, G.M., Keratocyte networks visualised in the living cornea using vital dyes (1993) J Cell Sci, 106, pp. 685-691; Li, R.H., Altreuter, D.H., Gentile, F.T., Transport characterization of hydrogel matrices for cell encapsulation (1996) Biotechnol Bioeng, 50 (4), pp. 365-373; Dulieu, C., Poncelet, D., Neufeld, R.J., Encapsulation and immobilization techniques (1999) Cell encapsulation technology and therapeutics, pp. 3-17. , Kühtreiber W.M., Lanza R.P., and Chick W.L. (Eds), Birkhäuser, Boston; Peirone, M., Ross, C.J.D., Hortelano, G., Brash, J.L., Chang, P.L., Encapsulation of various recombinant mammalian cell types in different alginate microcapsules (1998) J Biomed Mater Res, 42 (4), pp. 587-596; Kong, H.J., Kaigler, D., Kim, K., Mooney, D.J., Controlling rigidity and degradation of alginate hydrogels via molecular weight distribution (2004) Biomacromolecules, 5 (5), pp. 1720-1727; Boninsegna, S., Dal Toso, R., Dal Monte, R., Alginate microspheres loaded with animal cells and coated by a siliceous layer (2003) J Sol-Gel Sci Technol, 26 (1-3), pp. 1151-1157; Rokstad, A.M., Donati, I., Borgogna, M., Oberholzer, J., Strand, B.L., Espevik, T., Cell-compatible covalently reinforced beads obtained from a chemoenzymatically engineered alginate (2006) Biomaterials, 27 (27), pp. 4726-4737; Lu, M.Z., Lan, H.L., Wang, F.F., Chang, S.J., Wang, Y.J., Cell encapsulation with alginate and alpha-phenoxycinnamylidene-acetylated poly(allylamine) (2000) Biotechnol Bioeng, 70 (5), pp. 479-483; Stein, G.S., Lian, J.B., Molecular mechanisms mediating proliferation differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocrine Rev, 14 (4), pp. 424-442; Siebers, M.C., ter Brugge, P.J., Walboomers, X.F., Jansen, J.A., Integrins as linker proteins between osteoblasts and bone replacing materials. A critical review (2005) Biomaterials, 26 (2), pp. 137-146; Hynes, R.O., Integrins: bidirectional, allosteric signaling machines (2002) Cell, 110 (6), pp. 673-687; Giancotti, F.G., Ruoslahti, E., Transduction-integrin signaling (1999) Science, 285 (5430), pp. 1028-1032; Payne, R.G., McGonigle, J.S., Yaszemski, M.J., Yasko, A.W., Mikos, A.G., Development of an injectable, in situ crosslinkable, degradable polymeric carrier for osteogenic cell populations. Part 2. Viability of encapsulated marrow stromal osteoblasts cultured on crosslinking poly(propylene fumarate) (2002) Biomaterials, 23 (22), pp. 4373-4380; Franceschi, R.T., Iyer, B.S., Relationship between collagen-synthesis and expression of the osteoblast phenotype in MC3T3-E1 cells (1992) J Bone Miner Res, 7 (2), pp. 235-246; Franceschi, R.T., The developmental control of osteoblast-specific gene expression: role of specific transcription factors and the extracellular matrix environment (1999) Crit Rev Oral Biol Med, 10 (1), pp. 40-57; Gerstenfeld, L.C., Chipman, S.D., Kelly, C.M., Hodgens, K.J., Lee, D.D., Landis, W.J., Collagen expression, ultrastructural assembly, and mineralization in cultures of chicken-embryo osteoblasts (1988) J Cell Biol, 106 (3), pp. 979-989; Dudley, H.R., Spiro, D., Fine structure of bone cells (1961) J Biophys Biochem Cytol, 11 (3), pp. 627-649; Holtrop, M.E., The ultrastructure of bone (1975) Ann Clin Lab Sci, 5 (4), pp. 264-271; Rhodin, J.A.G., (1963) An atlas of ultrastructure, , W. B. Saunders Company, Philadelphia; Trojani, C., Weiss, P., Michiels, J.F., Vinatier, C., Guicheux, J., Daculsi, G., Three-dimensional culture and differentiation of human osteogenic cells in an injectable hydroxypropylmethylcellulose hydrogel (2005) Biomaterials, 26 (27), pp. 5509-5517; Kneser, U., Voogd, A., Ohnolz, J., Buettner, O., Stangenberg, L., Zhang, Y.H., Fibrin gel-immobilized primary osteoblasts in calcium phosphate bone cement: in vivo evaluation with regard to application as injectable biological bone substitute (2005) Cells Tissues Organs, 179 (4), pp. 158-169; Bancroft, J.D., Gamble, M., (2002) Theory and practice of histological techniques. 5th ed, , Elsevier Science, Edinburgh
Keywords: 3T3 Cells; Alginate; Alginates; alginic acid; alkaline phosphatase; animal cell; Animals; arginylglycylaspartic acid; article; Bone; bone cell; Bone Regeneration; calvaria; cell adhesion; cell differentiation; Cell encapsulation; Cell immobilization; cell metabolism; cell proliferation; cell survival; cell ultrastructure; cell viability; confocal laser microscopy; controlled study; cytology; cytoskeleton; DNA; DNA content; ECM (extracellular matrix); enzyme activity; extracellular matrix; Glucuronic Acid; Hexuronic Acids; hydrogel; immobilized cell; metabolism; Mice; Microscopy, Confocal; Microscopy, Electron, Transmission; microsphere; Microspheres; nonhuman; Oligopeptides; osteoblast; Osteoblasts; osteocalcin; Patient treatment; priority journal; rat; RGD peptide; structure analysis; three dimensional imaging; Tissue engineering; transmission electron microscopy; Transplantation (surgical)

Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers - Rodrigues, S.N.; Gonçalves, I.C.; Martins, M.C.L.; Barbosa, M.A.; Ratner, B.D. (BiomaterialsBiomaterials, 2006)
The effect of surface wettability on fibrinogen adsorption, platelet adhesion and platelet activation was investigated using self-assembled monolayers (SAMs) containing different ratios of longer chain methyl- and shorter chain hydroxyl-terminated alkanethiols (C15CH3 vs. C11OH) on gold. Protein adsorption studies were performed using radiolabeled human fibrinogen (HFG). Platelet adhesion and activation studies with and without pre-adsorbed fibrinogen, albumin and plasma were assessed using scanning electron microscopy (SEM) and a glutaraldehyde-induced fluorescence technique (GIFT). Results demonstrated a linear decrease of HFG adsorption with the increase of OH groups on the monolayer (increase of the hydrophilicity). Platelet adhesion and activation also decrease with increase of hydrophilicity of surface. Concerning SAMs pre-immersed in proteins, fibrinogen adsorption was related with high platelet adhesion and activation. The passivant effect of albumin on platelet adhesion and activation was only demonstrated on SAMs contained C11OH. When all the blood proteins are present (plasma) platelet adhesion was almost absent on SAMs with 65% and 100% C11OH. This could be explained by the higher albumin affinity of the SAMs with 65% C11OH and the lower total protein adsorption associated with SAMs with 100% C11OH. © 2006 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 70Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2006.06.010PubMed ID: 16842847Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: fibrinogen, 9001-32-5; glutaraldehyde, 111-30-8, 37245-61-7; gold, 7440-57-5; thiol derivative, 13940-21-1; Alkanes; Biocompatible Materials; Fibrinogen, 9001-32-5; hydroxide ion, 14280-30-9; Hydroxides; Sulfhydryl CompoundsReferences: Savage, B., Ruggeri, Z.M., Selective recognition of adhesive sites in surface-bound fibrinogen by glycoprotein-iib-iiia on nonactivated platelets (1991) J Biol Chem, 266 (17), pp. 11227-11233;Tsai, W.B., Grunkemeier, J.M., McFarland, C.D., Horbett, T.A., Platelet adhesion to polystyrene-based surfaces preadsorbed with plasmas selectively depleted in fibrinogen, fibronectin, vitronectin, or von Willebrand's factor (2002) J Biomed Mater Res, 60 (3), pp. 348-359; Kottkemarchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., Effect of albumin coating on the invitro blood compatibility of dacron arterial prostheses (1989) Biomaterials, 10 (3), pp. 147-155; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27 (12), pp. 1463-1476; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13 (13), pp. 3404-3413; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption on 18-alkyl chains immobilized on hydroxyl-terminated self-assembled monolayers (2005) Biomaterials, 26 (18), pp. 3891-3899; Peters, T., (1996) All about albumin: biochemistry, genetics and medical applications, , Academic Press Inc., San Diego, CA; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolavers (2003) J Biomed Mater Res A, 67 A (1), pp. 158-171; Frank, R.D., Dresbach, H., Thelen, H., Sieberth, H.G., Glutaraldehyde induced fluorescence technique (GIFT): a new method for the imaging of platelet adhesion on biomaterials (2000) J Biomed Mater Res, 52 (2), pp. 374-381; Feng, L., Andrade, J.D., Protein adsorption on low-temperature isotropic carbon. 3. Isotherms, competitivity, desorption and exchange of human albumin and fibrinogen (1994) Biomaterials, 15 (5), pp. 323-333; (1993) Iodine-125. A guide to radioiodination techniques, , Amersham Life Science, Little Chalfort; Porter, M.D., Bright, T.B., Allara, D.L., Chidsey, C.E.D., Spontaneously organized molecular assemblies. 4. Structural characterization of normal-alkyl thiol monolayers on gold by optical ellipsometry, infrared-spectroscopy, and electrochemistry (1987) J Am Chem Soc, 109 (12), pp. 3559-3568; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) J Am Chem Soc, 120 (14), pp. 3464-3473; Goodman, S.L., Sheep, pig, and human platelet-material interactions with model cardiovascular biomaterials (1999) J Biomed Mater Res, 45 (3), pp. 240-250; Slack, S.M., Horbett, T.A., Changes in fibrinogen adsorbed to segmented polyurethanes and hydroxyethylmethacrylate-ethylmethacrylate copolymers (1992) J Biomed Mater Res, 26 (12), pp. 1633-1649; Andrade, J.D., Hlady, V., Protein adsorption and materials biocompatibility-a tutorial review and suggested hypotheses (1986) Adv Polym Sci, 79, pp. 1-63; Roach, P., Farrar, D., Perry, C.C., Interpretation of protein adsorption: surface-induced conformational changes (2005) J Am Chem Soc, 127 (22), pp. 8168-8173; Silin, V., Weetall, H., Vanderah, D.J., SPR studies of the nonspecific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) J Colloid Interf Sci, 185 (1), pp. 94-103; Lin, Y., Wang, J., Wan, L.J., Fang, X.H., Study of fibrinogen adsorption on self-assembled monolayers on Au (1 1 1) by atomic force microscopy (2005) Ultramicroscopy, 105 (1-4), pp. 129-136; Norde, W., Favier, J.P., Structure of adsorbed and desorbed proteins (1992) Colloid Surf, 64 (1), pp. 87-93; Alfonsi-Hourdin, S., Longchamp, S., Gallet, O., Nigretto, J.M., Electrochemical processing of fibrinogen modified-graphite surfaces: effect on plasmin generation from adsorbed plasminogen (2006) Biomaterials, 27 (1), pp. 52-60; Tsai, W.B., Shi, Q., Grunkemeier, J.M., McFarland, C., Horbett, T.A., Platelet adhesion to radiofrequency glow-discharge-deposited fluorocarbon polymers preadsorbed with selectively depleted plasmas show the primary role of fibrinogen (2004) J Biomater Sci-Polym E, 15 (7), pp. 817-840; Stryer, L., (1998) Biochemistry. 4th ed., , WH Freeman, New York; Doolittle, R.F., Watt, K.W.K., Cottrell, B.A., Strong, D.D., Riley, M., Amino-acid sequence of the alpha-chain of human-fibrinogen (1979) Nature, 280 (5722), pp. 464-468; Kloczewiak, M., Timmons, S., Lukas, T.J., Hawiger, J., Platelet receptor recognition site on human-fibrinogen-synthesis and structure-function relationship of peptides corresponding to the carboxy-terminal segment of the gamma-chain (1984) Biochemistry, 23 (8), pp. 1767-1774; Tsai, W.B., Grunkemeier, J.M., Horbett, T.A., Variations in the ability of adsorbed fibrinogen to mediate platelet adhesion to polystyrene-based materials: a multivariate statistical analysis of antibody binding to the platelet binding sites of fibrinogen (2003) J Biomed Mater Res A, 67 A (4), pp. 1255-1268; Salsmann, A., Schaffner-Reckinger, E., Kabile, F., Plancon, S., Kieffer, N., A new functional role of the fibrinogen RGD motif as the molecular switch that selectively triggers integrin alpha IIb beta 3-dependent RhoA activation during cell spreading (2005) J Biol Chem, 280 (39), pp. 33610-33619; Lin, J.C., Chuang, W.H., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51 (3), pp. 413-423; Tanaka, M., Motomura, T., Kawada, M., Anzai, T., Kasori, Y., Shiroya, T., Blood compatible aspects of poly(2-methoxyethylacrylate) (PMEA)-relationship between protein adsorption and platelet adhesion on PMEA surface (2000) Biomaterials, 21 (14), pp. 1471-1481; Barbucci, R., Lamponi, S., Magnani, A., Fibrinogen conformation and platelet reactivity in relation to material-blood interaction: effect of stress hormones (2003) Biomacromolecules, 4 (6), pp. 1506-1513; Hylton, D.M., Shalaby, S.W., Latour, R.A., Direct correlation between adsorption-induced changes in protein structure and platelet adhesion (2005) J Biomed Mater Res A, 73 A (3), pp. 349-358; Brash, J.L., Tenhove, P., Protein adsorption studies on standard polymeric materials (1993) J Biomat Sci-Polym E, 4 (6), pp. 591-599
Keywords: Adsorption; Albumin; alkane derivative; Alkanes; article; binding affinity; Biocompatible Materials; Blood Platelets; Cells, Cultured; Chemical reactions; controlled study; Crystallization; fibrinogen; Fluorescence; fluorescence analysis; glutaraldehyde; gold; human; human cell; Humans; hydrophilicity; Hydroxides; hydroxyl group; materials testing; methyl group; Methylation; monolayer culture; Monolayers; normal human; Organic compounds; plasma; Plasma protein; Platelet activation; Platelet adhesion; Platelet Adhesiveness; priority journal; Protein adsorption; protein binding; Proteins; Radiolabeled human fibrinogen (HFG); Scanning electron microscopy; Self assembled; SEM; Sulfhydryl Compounds; surface property; thiol derivative; thrombocyte adhesion; wettability

Histological and scanning electron microscopy analyses of bone/implant interface using the novel Bonelike® synthetic bone graft - Gutierres, M.; Hussain, N.S.; Lopes, M.A.; Alfonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Orthopaedic ResearchJ. Orthop. Res., 2006)
Synthetic bone grafts provide an alternative to autografts and allografts. Bonelike® is a patented synthetic bone graft that mimics the mineral composition of bone. The aim of the present work was to assess the biological behavior of Bonelike® graft in humans, before using the material in orthopedic applications of bone regeneration, for example, in opening wedge high tibial osteotomies for medial knee osteoarthritis. Bonelike® granules were implanted in cortical bone of 11 patients undergoing osteotomies, and new bone formation, osteoconductive properties, and resorption characteristics of the granules were analyzed. The granules ranged from 500 to 1000 μm and were implanted in the lateral aspect of the tibia. The patients' mean age was 59 years (range 48 to 70 years); there were eight women and three men, all suffering from medial compartment osteoarthritis of the knee. At surgery, a 1 × 1 × 1-cm cortical defect was created 3 cm distal to the entry point of the screws, in line with the long axis of tibia. The implanted Bonelike® graft sample was extracted for analysis during removal of the metallic prosthesis after implantation times of 6, 9, and 12 months. Radiological follow-up, scanning electron microscopy, histological analysis, and histomorphometric measurements were conducted on the retrieved samples to assess bone regeneration in the defect area. Osteoconductive capacity was demonstrated by extensive mature bone formation around the implanted granules and high levels of percentage bone-to-graft contact (from 67-84%). Bonelike® acted as an excellent bioactive scaffold, allowing the migration, proliferation, and differentiation of bone cells on its surface, and therefore regeneration of the defects was achieved in a rapid, controlled manner. Our results suggest that Bonelike® graft is an excellent candidate for orthopedic applications where rapid new bone formation is a fundamental requirement. © 2006 Orthopaedic Research Society. Published by Wiley Periodicals, Inc.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JOREDdoi: 10.1002/jor.20117Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; DEMM, Faculty of Engg., University of Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesTradenames: Bonelike; JSM 630IF, JeolManufacturers: JeolReferences: Peter, P., Heinrich, R., Meinrad, P., (2003) Orthopaedic Issues in Osteoporosis, , YH An, editor. Boca Raton, FL: CRC Press;Hench, L.L., Wilson, J., (1999) An Introduction to Bioceramics, , Singapore: World Scientific Publishing Co. Pvt. Ltd; Corpe, R.S., Steflik, D.E., Whitehead, R.Y., Correlative experimental animal and human clinical retrieval evaluations (2000) Crit Rev Biomed Eng, 28, pp. 395-398; Kitsugi, T., Yamamuro, T., Nakamura, T., Four calcium phosphate ceramics as bone substitutes for non-weight bearing (1993) Biomaterials, 14, pp. 216-224; Koshino, T., Murase, T., Takagi, T., New bone formation around porous hydroxyapatite wedge implanted in opening wedge high tibial osteotomy in patients with osteoarthritis (2001) Biomaterials, 22, pp. 1579-1582; LeGeros, R.Z., (1991) Calcium Phosphates in Oral Biology and Medicine, pp. 4-45. , Meyers HM, editor. New York: Karger; Macdonald, D.E., Betts, F., Stranick, M., Physicochemical study of plasma-sprayed hydroxyapatite-coated implants in humans (2001) J Biomed Mater Res, 54, pp. 480-490; Oonishi, H., Yamamoto, M., Ishimaru, H., The effect of hydroxyapatite coating on bone growth into porous titanium alloy implants (1989) J Bone Surg Br, 71, pp. 213-216; Thomas, K.A., Hydroxyapatite coatings (1994) Orthopedics, 17, pp. 267-278; Doron, H., Amy, L.L., Bone graft substitutes (2003) Oper Tech Plastic Reconstruct Surg, 9, pp. 151-160; Write, S., The bone-graft market in Europe. Commentary extracted from a report entitled "Emerging technologies in orthopedics I.: Bone graft substitutes, bone growth stimulators and bone growth factors" (1999), pp. 591-595. , London: Datamonitor plcBotelho, C.M., Brooks, R.A., Best, S.M., Biological and physical-chemical characterization of phase pure HA and si-substituted hydroxyapatite by different microscopy techniques (2004) Key Eng Mater, 254, p. 845; Costa, M.A., Gutierres, M., Almeida, L., In vitro mineralisation of human bone marrow cells cultured on bonelike® (2004) Key Eng Mater, 254-256, pp. 821-824; Gutierres, M., Hussain, N.S., Afonso, A., Biological behaviour of bonelike® graft Implanted in the tibia of humans (2005) Key Eng Mater, 284-286, pp. 1041-1044; Lopes, M.A., Santos, J.D., Monteiro, F.J., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: Fracture toughness and hardness dependence on microstructural characteristics (1999) Biomaterials, 20, pp. 2085-2090; Lopes, M.A., Silva, R.F., Monteiro, F.J., Microstructural dependence of Young's and shear moduli of P 2O 5 glass reinforced hydroxyapatite for biomedical applications (2000) Biomaterials, 21, pp. 749-754; Lopes, M.A., Knowles, J.C., Santos, J.D., Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement (2000) Biomaterials, 21, pp. 1905-1910; Santos, J.D., Knowles, J.C., Reis, R.L., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Felson, D.T., Naimark, A., Anderson, J., The prevalence of knee osteoarthritis in the elderly: The Framingham Study (1987) Arthritis Rheum, 30, pp. 914-918; Guincamp, C., Pap, T., Schedel, J., Gene therapy in osteoarthritis (2000) Joint Bone Spine, 67, pp. 570-571; Marc, F., Serge, P., Mario, M.L.C., Assessment of the test-retest reliability and construct validity of a modified lequesne index in knee osteoarthritis (2003) Joint Bone Spine, 70, pp. 520-525; Pendleton, A., Arden, N., Dougados, M., EULAR recommendations for the management of knee osteoarthritis: Report of a task force of the Standing Committee for International Clinical Studies Including Therapeutic Trials (ESCISIT) (2000) Ann Rheum Dis, 59, pp. 936-944; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered hydroxyapatite compositions and method for the preparation thereof (1999) Eur. Pat. WO 0068164; Coventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: A preliminary report (1965) J Bone Joint Surg Am, 47, p. 984; Hing, K.A., Assessment of porous hydroxyapatite for bone replacement (1996), (Ph D Thesis). London: University of LondonLopes, M.A., Knowles, J.C., Santos, J.D., Direct and indirect effects of P 2O 5-glass reinforced-hydroxyapatite composites and growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Knowles, J.C., Santos, J.D., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Ross, M.H., Romrell, L.J., Kaye, G.I., (1995) Histology - A Text and Atlas, , 3rd ed. Baltimore, MD: Williams & Wilkins; Lobato, J.V., Hussain, N.S., Botelho, C.M., Assessment of the potential of Bonelike® graft for bone regeneration by using an animal model (2005) Key Eng Mater, 284-286, pp. 877-880; Duarte, F., Lopes, M.A., Santos, J.D., Bonelike® composites for the regeneration of bone lesions (2004) Mater Sci Forum, 455-456, pp. 370-373; Laurencin, C.T., (2003) Bone Graft Substitutes, , West Conshohocken, PA: ASTM International
Keywords: adult; aged; article; Bone; Bone and Bones; bone cell; bone conduction; bone development; Bone graft; bone prosthesis; bone radiography; Bone Regeneration; bone screw; Bone Substitutes; bone transplantation; Bonelike®; cell differentiation; cell migration; cell proliferation; Clinical applications; clinical article; controlled study; Female; follow up; Histological analysis; histology; human; Humans; knee osteoarthritis; male; Microscopy, Electron, Scanning; Middle Aged; morphometrics; orthopedics; ossification; Osteoconduction; Osteogenesis; osteolysis; Pathology; priority journal; Prostheses and Implants; prostheses and orthoses; prosthesis material; Scanning electron microscopy; surgical technique; Synthetic bone graft; tibia osteotomy; ultrastructure

Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters - Gonçalves, H.; Rocha, A.P.; Ayres-de-Campos, D.; Bernardes, J. (Physiological MeasurementPhysiol. Meas., 2006)
The effect of foetal heart rate (FHR) acquisition mode on linear and nonlinear parameters is still largely unknown. In 33 normal labouring women, FHR signals were acquired simultaneously by an external ultrasound sensor applied to the maternal abdomen and an internal scalp electrode, in the minutes preceding delivery. For each case, the initial and final 5, 10 and 20 min segments were analysed, considering FHR signals at a frequency of 4 Hz (the frequency at which they are transmitted by the majority of commercialized foetal monitors). Several time and frequency domain linear and nonlinear FHR indices were computed in these segments, namely mean FHR, very low frequency (VLF), low frequency (LF), high frequency (HF), approximate entropy (ApEn) and sample entropy (SampEn). Parametric confidence intervals, statistical tests and correlation coefficients were calculated in order to evaluate the effect of internal versus external FHR monitoring modes on the considered indices. The whole evaluation was repeated using FHR signals at a frequency of 2 Hz. Most time domain linear indices were similar with external and internal monitoring in the initial and final segments of the tracings. However, linear frequency domain indices were poorly correlated in the final segments and had significantly different mean values in the initial segments. Nonlinear indices were significantly different in both initial and final segments. The correlation between 4 and 2 Hz sampled parameters was high for both linear and nonlinear indices (most correlation coefficient values ranging between 0.95 and 1) but nonlinear index values were significantly higher at 2 Hz. In conclusion, the mode used to acquire FHR signals and the sampling rate employed can significantly affect most FHR indices. © 2006 IOP Publishing Ltd.
Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: PMEAEdoi: 10.1088/0967-3334/27/3/008PubMed ID: 16462016Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Matemática Aplicada, Faculdade de Ciências, Universidade Do Porto, Porto, Portugal; email: hernani.goncalves@fc.up.ptReferences: Ayres-De-Campos, D., Bernardes, J., Garrido, A., Marques-De-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J. Matern. Fetal Med., 9 (5), pp. 311-318;Ayres-De-Campos, D., Bernardes, J., Reynolds, A., Saraiva, J.P., Santos, C., Pereira-Leite, L., Computer evaluation of internal versus external FHR monitoring in the minutes preceding delivery (2000) Int. J. Gynecol. Obstet., 70, pp. 60-B61; Ayres-De-Campos, D., Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto ®multicentre validation study (2005) Eur. J. Obstet. Gynecol. Reprod. Biol., 118 (1), pp. 52-60; Bakker, P.C., Colenbrander, G.J., Verstraeten, A.A., Geijn, V., The quality of intrapartum fetal heart rate monitoring (2004) Eur. J. Obstet. Gynecol. Reprod. Biol., 116 (1), pp. 22-27; Bernardes, J., Ayres-De-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int. J. Gynecol. Obstet., 62 (2), pp. 141-147; Bernardes, J., Costa-Pereira, A., The effect of different sampling intervals on the measurement of intrapartum fetal heart rate variability (1997) Obstet. Gynecol., 90 (2), pp. 318-319; Bernardes, J., Garrido, A., Computerized fetal heart rate analysis in labour based on 2-s sampling. Can it proceed with confidence? (1995) Eur. J. Obstet. Gynecol. Reprod. Biol., 63 (1), pp. 105-107; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J. Perinat. Med., 19, pp. 61-65; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Van Geijn, H.P., Pereira-Leite, L., The Porto system (1994) A Critical Appraisal of Fetal Surveillance, pp. 315-324; Boog, G., Analyse informatisée du rythme cardiaque fetal au cours de la grosssesse et de l'accouchement (2004) Encyclopédie Médico-Chirurgicale, 148; Boos, A., Jagger, M.H., Paret, G.W., Hausmann, J.W., A new, lightweight fetal telemetry system (1995) Hewlett-Packard J., pp. 82-93; Carter, M.C., Signal processing and display-cardiotocographs (1993) Br. J. Obstet. Gynaecol., 100, pp. 21-23; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J. Matern. Fetal Invest., 8, pp. 23-26; Chang, A., Sahota, D.S., Reed, N.N., James, D.K., Mohajer, M.P., Computerised fetal heart rate analysis in labour-effect of sampling rate (1995) Eur. J. Obstet. Gynecol. Reprod. Biol., 59 (2), pp. 125-129; Court, D.J., Parer, J.T., Experimental studies of fetal asphyxia and fetal heart rate interpretation (1984) Research in Perinatal Medicine, pp. 113-169; Dawes, G., Computerized fetal heart rate analysis (1994) A Critical Appraisal of Fetal Surveillance, pp. 311-314; Dawes, G.S., Moulden, M., Sheil, O., Redman, C.W.G., Approximate entropy, a statistic of regularity, applied to fetal heart rate data before and during labour (1992) Obstet. Gynecol., 80, pp. 763-768; Dawes, G.S., Moulden, M., Redman, C.W., Criteria for the design of fetal heart rate analysis systems (1990) Int. J. Biomed. Comput., 25 (4), pp. 287-294; Di Renzo, G.C., Montani, M., Fioriti, V., Clerici, G., Branconi, F., Pardini, A., Indraccolo, R., Cosmi, E.V., Fractal analysis: A new method for evaluating fetal heart rate variability (1996) J. Perinat. Med., 24, pp. 261-269; Echeverria, J.C., Hayes-Gill, B.R., Crowe, J.A., Woolfson, M.S., Croaker, G.D., Detrended fluctuation analysis: A suitable method for studying fetal heart rate variability? (2004) Physiol. Meas., 25 (3), pp. 763-774; Felgueiras, C., Marques-De-Sá, J.P., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomed. Eng., 36, pp. 197-201; Felgueiras, C.S., Marques-De-Sá, J.P., Bernardes, J., Gama, S., On the reconstruction of fetal heart rate sequences (1996) Actas Do 4° Congresso Português de Engenharia Biomédica-BioEng'96, pp. 61-vii65; Fukushima, T., Flores, C.A., Hon, E.H., Davidson Jr., E.C., Limitations of autocorrelation in fetal heart rate monitoring (1985) Am. J. Obstet. Gynecol., 153, pp. 685-692; Fusheng, Y., Bo, H., Qingyu, T., Approximate entropy and its application in biosignal analysis (1998) Nonlinear Biomedical Signal Processing-Volume II: Dynamical Analysis and Modelling, pp. 72-91; Gough, N.A., Fractal analysis of fetal heart rate variability (1993) Physiol. Meas., 14 (3), pp. 309-315; Hayes, M., (1996) Statistical Digital Signal Processing and Modelling; Hewlett-Packard, (1993) Hewlett-Packard Series 50 Service Manual, M1351A and 1353A; Hirsch, M., Karin, J., Akselrod, S., Heart rate variability in the fetus (1995) Heart Rate Variability, pp. 517-531; Lawson, G.W., Belcher, R., Dawes, G.S., Redman, C.W., A comparison of ultrasound (with autocorrelation) and direct electrocardiogram fetal heart rate detector systems (1983) Am. J. Obstet. Gynecol., 147, pp. 721-722; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Wu, G., Shen, L., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) Eur. J. Obstet. Gynecol. Reprod. Biol., 114 (2), pp. 137-143; Lunghi, F., Magenes, G., Pedrinazzi, L., Signorini, M.G., Detection of fetal distress through a support vector machine based on fetal heart rate parameters (2005) Comput. Cardiol., 32, pp. 247-250; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000: Proc. IEEE-INNS-ENNS Int. Joint Conf. on Neural Networks, pp. 637-641; Electronic fetal heart rate monitoring: Research guidelines for interpretation (1997) Am. J. Obstet. Gynecol., 177 (6), pp. 1385-1390; Nijhuis, I., Ten Hof, J., Development of fetal heart rate and behavior: Indirect measures to assess the fetal nervous system (1999) Eur. J. Obstet. Gynecol. Reprod. Biol., 87 (1), pp. 1-2; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Baillieres Clin. Obstet. Gynaecol., 8, pp. 643-661; Peters, C.H., Ten Broeke, E.D., Andriessen, P., Vermeulen, B., Berendsen, R.C., Wijn, P.F., Oei, S.G., Beat-to-beat detection of fetal heart rate: Doppler ultrasound cardiotocography compared to direct ECG cardiotocography in time and frequency domain (2004) Physiol. Meas., 25 (2), pp. 585-593; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc. Natl. Acad. Sci. USA, 88, pp. 2297-2301; Pincus, S., Approximate entropy (ApEn) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Pincus, S., Viscarello, R., Approximate entropy: A regularity measure for fetal heart rate analysis (1992) Obstet. Gynecol., 79, pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am. J. Physiol. Heart Circ. Physiol., 278, pp. 2039-H2049; Salamalekis, E., Thomopoulos, P., Giannaris, D., Salloum, I., Vasios, G., Prentza, A., Koutsouris, D., Computerised intrapartum diagnosis of fetal hypoxia based on fetal heart rate monitoring and fetal pulse oximetry recordings utilising wavelet analysis and neural networks (2002) BJOG, 109 (10), pp. 1137-1142; Signorini, M., Cerutti, S., Nonlinear properties of Cardiovascular Time Series (1999) Methodology and Clinical Applications of Blood Pressure and Heart Rate Analysis, pp. 73-89; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans. Biomed. Eng., 50 (3), pp. 365-373; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Uehara, S., Yajima, A., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am. J. Obstet. Gynecol., 182 (5), pp. 1227-1232; Heart rate variability. Standards of measurement, physiological interpretation, and clinical use (1996) Eur. Heart J., 17, pp. 354-381; Wilcox, M.A., Wang, W., Sahota, D.S., Dawkins, R.R., Chung, T.K., Chang, A.M., The effect of different sampling intervals on the measurement of intrapartum fetal heart rate variability (1997) Obstet. Gynecol., 89 (4), pp. 577-580; Yum, M.K., Kim, K., Kim, J.H., Park, E.Y., A consistent abnormality in the average local smoothness of fetal heart rate in growth-restricted fetuses affected by severe pre-eclampsia (2004) Hypertens. Res., 27 (12), pp. 911-918
Keywords: abdomen; Algorithms; article; Cardiotocography; commercial phenomena; Confidence interval; controlled study; correlation coefficient; delivery; Diagnosis, Computer-Assisted; Electrocardiography; electrode; entropy; External and internal monitoring; Female; fetus electrocardiography; fetus monitoring; Foetal heart rate (FHR); Frequency domain analysis; Heart; Heart rate; human; intermethod comparison; intrapartum care; Linear and nonlinear analysis; Linear Models; mathematical computing; Nonlinear Dynamics; normal human; priority journal; Reproducibility of Results; sensitivity and specificity; sensor; Signal Processing, Computer-Assisted; Statistical significance; ultrasound; Variability

Leptin effect on RANKL and OPG expression in MC3T3-E1 osteoblasts - Lamghari, M.; Tavares, L.; Camboa, N.; Barbosa, M.A. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2006)
Recent studies have suggested that leptin hormone may play a pivotal role on bone remodeling through a direct effect by modulating positively the OPG/RANKL balance. Here, we investigate the effect of leptin hormone on RANKL and OPG expression in MC3T3-E1 osteoblasts using RT-PCR and ELISA measurements. We have at first identified the expression of Ob-Rb and Ob-Ra leptin receptor isoforms in MC3T3-E1 and observed that these cells respond to mrleptin treatments. We then investigated the effect of mrleptin on RANKL and OPG expression. We show that mrleptin dose-dependently regulated the expression of RANKL mRNA with complete inhibition observed at concentrations higher than 12 ng/ml. This effect was confirmed with sRANKL protein measurements. However, the exposure of MC3T3-E1 to mrleptin had no effect on OPG mRNA. Taken together, these results suggest that leptin modulates positively OPG/RANKL balance by inhibiting the expression of RANKL gene. © 2006 Wiley-Liss, Inc.
Cited By (since 1996): 17Export Date: 21 November 2012Source: ScopusCODEN: JCEBDdoi: 10.1002/jcb.20853PubMed ID: 16479591Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre 823, 4150-180, Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: osteoclast differentiation factor, 200145-93-3; osteoprotegerin, 205944-50-9; Alkaline Phosphatase, EC 3.1.3.1; Carrier Proteins; Glycoproteins; leptin receptor; Leptin; Membrane Glycoproteins; Osteoprotegerin; RANK Ligand; Receptor Activator of Nuclear Factor-kappa B; Receptors, Cell Surface; Receptors, Cytoplasmic and Nuclear; Receptors, Tumor Necrosis Factor; RNA, Messenger; Tnfrsf11a protein, mouse; Tnfrsf11b protein, mouse; Tnfsf11 protein, mouseReferences: Burguera, B., Hofbauer, L.C., Thomas, T., Gori, F., Evans, G.L., Khosla, S., Riggs, B.L., Turner, R.T., Leptin reduces ovariectomy-induced bone loss in rats (2001) Endocrinology, 142, pp. 3546-3553;Cornish, J., Callon, K.E., Bava, U., Lin, C., Naot, D., Hill, B.L., Grey, A.B., Reid, I.R., Leptin directly regulates bone cell function in vitro and reduces bone fragility in vivo (2002) J Endocrinol, 175, pp. 405-415; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., Leptin inhibits bone formation through a hypothalamic relay: A central control of bone mass (2000) Cell, 100, pp. 197-207; Elefteriou, F., Ahn, J.D., Takeda, S., Starbuck, M., Yang, X., Liu, X., Kondo, H., Karsenty, G., Leptin regulation of bone resorption by the sympathetic nervous system and CART (2005) Nature, 434, pp. 514-520; Elmquist, J.K., Hypothalamic pathways underlying the endocrine, autonomic, and behavioral effects of leptin (2001) Physiol Behav, 74, pp. 703-708; Gordeladze, J.O., Drevon, C.A., Syversen, U., Reseland, J.E., Leptin stimulates human osteoblastic cell proliferation, de novo collagen synthesis, and mineralization: Impact on differentiation markers, apoptosis, and osteoclastic signaling (2002) J Cell Biochem, 85, pp. 825-836; Holloway, W.R., Collier, F.M., Aitken, C.J., Myers, D.E., Hodge, J.M., Malakellis, M., Gough, T.J., Nicholson, G.C., Leptin inhibits osteoclast generation (2002) J Bone Miner Res, 17, pp. 200-209; Horwood, N.J., Elliott, J., Martin, T.J., Gillespie, M.T., Osteotropic agents regulate the expression of osteoclast differentiation factor and osteoprotegerin in osteoblastic stromal cells (1998) Endocrinology, 139, pp. 4743-4746; Kanematsu, M., Yoshimura, K., Takaoki, M., Sato, A., Vector-averaged gravity regulates gene expression of receptor activator of NF-κB (RANK) ligand and osteoprotegerin in bone marrow stromal cells via cyclic AMP/protein kinase A pathway (2002) Bone, 30, pp. 553-558; Lacely, D.L., Timms, E., Tan, H.L., Dunstan, C.R., Burgess, T., Elliott, R., Colombero, A., Boyle, W.J., Osteoproteferin ligand is a cytokine that regulates osteoclast differentiation and activation (1998) Cell, 93, pp. 165-167; Lee, S.K., Lorenzo, J.A., Parathyroid hormone stimulates TRANCE and inhibits osteoprotegerin messenger ribonucleic acid expression in murine bone marrow cultures: Correlation with osteoclast-like cell formation (1999) Endocrinology, 140, pp. 3552-3561; Lee, S.K., Lorenzo, J.A., Regulation of receptor activator of nuclear factor-κB ligand and osteoprotegerin mRNA expression by parathyroid hormone is predominantly mediated by the protein kinase a pathway in murine bone marrow cultures (2002) Bone, 31, pp. 252-259; Lee, Y.J., Park, J.H., Ju, S.K., You, K.H., Ko, J.S., Kim, H.M., Leptin receptor isoform expression in rat osteoblasts and their functional analysis (2002) FEBS Lett, 528, pp. 43-47; Liu, J., Yang, H., Liu, W., Cao, X., Feng, X., Sp1 and Sp3 regulate the basal transcription of receptor activator of nuclear factor kappa B ligand gene in osteoblasts and bone marrow stromal cells (2005) J Cell Biochem, 96 (4), pp. 716-727; Martin, A., De Vittoris, R., David, V., Moraes, R., Bégeot, M., Lafage-Proust, M.H., Alexandre, C., Thomas, T., Leptin modulates both résorption and formation while preventing disuse-induced bone loss in tail-suspended female rats (2005) Endocrinology, 146, pp. 3652-3659; Nagai, M., Sato, N., Reciprocal gene expression of osteoclastogenesis inhibitory factor and osteoclast differentiation factor regulates osteoclast formation (1999) Biochem Biophys Res Commun, 257, pp. 719-723; Nakajima, R., Inada, H., Koike, T., Yamano, T., Effects of leptin to cultured growth plate chondrocytes (2003) Horm Res, 60 (2), pp. 91-98; Parhami, F., Tintut, Y., Ballard, A., Fogelman, A.M., Demer, L.L., Leptin enhances the calcification of vascular cells: Artery wall as a target of leptin (2001) Circ Res, 88 (9), pp. 954-960; Reseland, J.E., Syversen, U., Bakke, I., Ovigstad, G., Eide, L.G., Hjertner, O., Gordeladze, J.O., Drevon, C.A., Leptin is expressed in and secreted from primary cultures of human osteoblasts and promotes bone mineralization (2001) J Bone Miner Res, 16, pp. 1426-11414; Rubin, J., Ackert-Bicknell, C., Zhu, L., Fan, X., Murphy, T., Nanes, M., Marcus, R., Rosen, C., Insulin like growth factor-I (IGF-I) regulates osteoprotegerin (OPG) and RANK ligand (RANKL) in vitro and osteoprotogerin in vivo (2002) J Clin Endocrinal Metab, 87, pp. 4273-4279; Rubin, J., Murphy, T., Fan, X., Goldschmidt, M., Taylor, W., Mechanical strain inhibits RANKL expression through activation of ERK1/2 in bone marrow stromal cells (2002) J Bone Miner Res, 17, pp. 1452-1460; Simonet, W.S., Lacey, D.L., Dunstan, C.R., Kelley, M., Chang, M.S., Luthy, R., Nguyen, H.Q., Boyle, W.J., Osteoprotegerin: A novel secreted protein involved in the regulation of bone density (1997) Cell, 89, pp. 309-319; Steppan, C.M., Crawford, T., Chidsey-Frink, K.L., Ke, H.Z., Swick, A.G., Leptin is a potent stimulator of bone growth in ob/ob mice (2000) Regul Pept, 92, pp. 73-78; Suda, T., Ueno, Y., Fujii, K., Shinki, T., Vitamin D and bone (2003) J Cell Biochem, 88, pp. 259-266; Thomas, T., Gori, F., Khosla, S., Jensen, M.D., Burguera, B., Riggs, B.L., Leptin acts on human marrow stromal cells to enhance differentiation to osteoblasts and to inhibit differentiation to adipocytes (1999) Endocrinology, 140, pp. 1630-1638; Udagawa, N., Takahashi, N., Yasuda, H., Mizuno, A., Itoh, K., Ueno, Y., Shinki, T., Suda, T., Osteoprotegerin produced by osteoblasts is an important regulator in osteoclast development and function (2000) Endocrinology, 141, pp. 3478-3484; Wamoto, I., Fujino, T., Douchi, T., The leptin receptor in human osteoblasts and the direct effect of leptin on bone metabolism (2004) Gynecol Endocrinol, 19, pp. 97-104; Yasuda, H., Shima, N., Nakagawa, N., Yamaguchi, K., Kinosaki, M., Mochizuki, S., Tomoyasu, A., Suda, T., Osteoclast differentiation factor is a ligand for osteoprotegerin/ osteoclastogenesis-inhibitory factor and is identical to TRANCE/RANKL (1998) Proc Natl Acad Sci USA, 95, pp. 3597-3602
Keywords: alkaline phosphatase; animal cell; Animals; article; bone remodeling; Carrier Proteins; Cell Line; enzyme linked immunosorbent assay; gene expression; gene expression regulation; Glycoproteins; hormone action; leptin; leptin receptor; leptin receptor a; leptin receptor b; MC3T3-E1; Membrane Glycoproteins; messenger RNA; Mice; mouse; nonhuman; Ob-Ra; Ob-Rb; OPG; osteoblast; Osteoblasts; osteoclast differentiation factor; Osteoprotegerin; priority journal; protein expression; RANK Ligand; RANKL; Receptor Activator of Nuclear Factor-kappa B; Receptors, Cell Surface; Receptors, Cytoplasmic and Nuclear; Receptors, Tumor Necrosis Factor; reverse transcription polymerase chain reaction; RNA extraction; RNA, Messenger; unclassified drug

The N-terminal half of the peroxisomal cycling receptor Pex5p is a natively unfolded domain - Carvalho, A.F.; Costa-Rodrigues, J.; Correia, I.; Costa Pessoa, J.; Faria, T.Q.; Martins, C.L.; Fransen, M.; Sá-Miranda, C.; Azevedo, J.E. (Journal of Molecular BiologyJ. Mol. Biol., 2006)
Targeting of most newly synthesised peroxisomal matrix proteins to the organelle requires Pex5p, the so-called PTS1 receptor. According to current models of peroxisomal biogenesis, Pex5p interacts with these proteins in the cytosol, transports them to the peroxisomal membrane and catalyses their translocation across the membrane. Presently, our knowledge on the structural details behind the interaction of Pex5p with the cargo proteins is reasonably complete. In contrast, information regarding the structure of the Pex5p N-terminal half (a region containing its peroxisomal targeting domain) is still limited. We have recently observed that the Stokes radius of this Pex5p domain is anomalously large, suggesting that this portion of the protein is either a structured elongated domain or that it adopts a low compactness conformation. Here, we address this issue using a combination of biophysical and biochemical approaches. Our results indicate that the N-terminal half of Pex5p is best described as a natively unfolded pre-molten globule-like domain. The implications of these findings on the mechanism of protein import into the peroxisome are discussed. © 2005 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: JMOBAdoi: 10.1016/j.jmb.2005.12.002PubMed ID: 16403517Language of Original Document: EnglishCorrespondence Address: Azevedo, J.E.; Instituto de Biologia Molecular e Celular, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jazevedo@ibmc.up.ptChemicals/CAS: Amino Acids; peroxisome-targeting signal 1 receptor; Receptors, Cytoplasmic and NuclearReferences: Brown, L.A., Baker, A., Peroxisome biogenesis and the role of protein import (2003) J. Cell. Mol. Med., 7, pp. 388-400;Heiland, I., Erdmann, R., Biogenesis of peroxisomes. Topogenesis of the peroxisomal membrane and matrix proteins (2005) FEBS J., 272, pp. 2362-2372; Lazarow, P.B., Peroxisome biogenesis: Advances and conundrums (2003) Curr. Opin. Cell Biol., 15, pp. 489-497; Moyersoen, J., Choe, J., Fan, E., Hol, W.G., Michels, P.A., Biogenesis of peroxisomes and glycosomes: Trypanosomatid glycosome assembly is a promising new drug target (2004) FEMS Microbiol. Rev., 28, pp. 603-643; Weller, S., Gould, S.J., Valle, D., Peroxisome biogenesis disorders (2003) Annu. Rev. Genomics Hum. Genet., 4, pp. 165-211; Gould, S.J., Keller, G.A., Hosken, N., Wilkinson, J., Subramani, S., A conserved tripeptide sorts proteins to peroxisomes (1989) J. Cell Biol., 108, pp. 1657-1664; Klein, A.T., Barnett, P., Bottger, G., Konings, D., Tabak, H.F., Distel, B., Recognition of peroxisomal targeting signal type 1 by the import receptor Pex5p (2001) J. Biol. Chem., 276, pp. 15034-15041; Lametschwandtner, G., Brocard, C., Fransen, M., Van Veldhoven, P., Berger, J., Hartig, A., The difference in recognition of terminal tripeptides as peroxisomal targeting signal 1 between yeast and human is due to different affinities of their receptor Pex5p to the cognate signal and to residues adjacent to it (1998) J. Biol. Chem., 273, pp. 33635-33643; Brocard, C., Kragler, F., Simon, M.M., Schuster, T., Hartig, A., The tetratricopeptide repeat-domain of the PAS10 protein of Saccharomyces cerevisiae is essential for binding the peroxisomal targeting signal-SKL (1994) Biochem. Biophys. Res. Commun., 204, pp. 1016-1022; Dodt, G., Braverman, N., Wong, C., Moser, A., Moser, H.W., Watkins, P., Mutations in the PTS1 receptor gene, PXR1, define complementation group 2 of the peroxisome biogenesis disorders (1995) Nature Genet., 9, pp. 115-125; Fransen, M., Brees, C., Baumgart, E., Vanhooren, J.C., Baes, M., Mannaerts, G.P., Van Veldhoven, P.P., Identification and characterization of the putative human peroxisomal C-terminal targeting signal import receptor (1995) J. Biol. Chem., 270, pp. 7731-7736; Gatto Jr., G.J., Geisbrecht, B.V., Gould, S.J., Berg, J.M., A proposed model for the PEX5-peroxisomal targeting signal-1 recognition complex (2000) Proteins: Struct. Funct. Genet., 38, pp. 241-246; Otera, H., Setoguchi, K., Hamasaki, M., Kumashiro, T., Shimizu, N., Fujiki, Y., Peroxisomal targeting signal receptor Pex5p interacts with cargoes and import machinery components in a spatiotemporally differentiated manner: Conserved Pex5p WXXXF/Y motifs are critical for matrix protein import (2002) Mol. Cell. Biol., 22, pp. 1639-1655; Terlecky, S.R., Nuttley, W.M., McCollum, D., Sock, E., Subramani, S., The Pichia pastoris peroxisomal protein PAS8p is the receptor for the C-terminal tripeptide peroxisomal targeting signal (1995) EMBO J., 14, pp. 3627-3634; Gatto Jr., G.J., Geisbrecht, B.V., Gould, S.J., Berg, J.M., Peroxisomal targeting signal-1 recognition by the TPR domains of human PEX5 (2000) Nature Struct. Biol., 7, pp. 1091-1095; Agne, B., Meindl, N.M., Niederhoff, K., Einwachter, H., Rehling, P., Sickmann, A., Pex8p: An intraperoxisomal organizer of the peroxisomal import machinery (2003) Mol. Cell., 11, pp. 635-646; Albertini, M., Girzalsky, W., Veenhuis, M., Kunau, W.H., Pex12p of Saccharomyces cerevisiae is a component of a multi-protein complex essential for peroxisomal matrix protein import (2001) Eur. J. Cell Biol., 80, pp. 257-270; Reguenga, C., Oliveira, M.E., Gouveia, A.M., Sa-Miranda, C., Azevedo, J.E., Characterization of the mammalian peroxisomal import machinery: Pex2p. Pex5p, Pex12p, and Pex14p are subunits of the same protein assembly (2001) J. Biol. Chem., 276, pp. 29935-29942; Huhse, B., Rehling, P., Albertini, M., Blank, L., Meller, K., Kunau, W.-H., Pex17p of Saccharomyces cerevisiae is a novel peroxin and component of the peroxisomal protein translocation machinery (1998) J. Cell Biol., 140, pp. 49-60; Liu, H., Tan, X., Russell, K.A., Veenhuis, M., Cregg, J.M., PER3, a gene required for peroxisome biogenesis in Pichia pastoris, encodes a peroxisomal membrane protein involved in protein import (1995) J. Biol. Chem., 270, pp. 10940-10951; Rehling, P., Skaletz-Rorowski, A., Girzalsky, W., Voorn-Brouwer, T., Fransen, M.M., Distel, B., Pex8p, an intraperoxisomal peroxin of Saccharomyces cerevisiae required for protein transport into peroxisomes binds the PTS1 receptor pex5p (2000) J. Biol. Chem., 275, pp. 3593-3602; Smith, J.J., Szilard, R.K., Marelli, M., Rachubinski, R.A., The peroxin Pex17p of the yeast Yarrowia lipolytica is associated peripherally with the peroxisomal membrane and is required for the import of a subset of matrix proteins (1997) Mol. Cell. Biol., 17, pp. 2511-2520; Waterham, H.R., Titorenko, V.I., Haima, P., Cregg, J.M., Harder, W., Veenhuis, M., The Hansenula polymorpha PER1 gene is essential for peroxisome biogenesis and encodes a peroxisomal matrix protein with both carboxy- and amino-terminal targeting signals (1994) J. Cell Biol., 127, pp. 737-749; Costa-Rodrigues, J., Carvalho, A.F., Gouveia, A.M., Fransen, M., Sa-Miranda, C., Azevedo, J.E., The N terminus of the peroxisomal cycling receptor, Pex5p, is required for redirecting the peroxisome-associated peroxin back to the cytosol (2004) J. Biol. Chem., 279, pp. 46573-46579; Dodt, G., Gould, S.J., Multiple, P.E.X., Genes are required for proper subcellular distribution and stability of Pex5p, the PTS1 receptor: Evidence that PTS1 protein import is mediated by a cycling receptor (1996) J. Cell Biol., 135, pp. 1763-1774; Gouveia, A.M., Guimaraes, C.P., Oliveira, M.E., Reguenga, C., Sa-Miranda, C., Azevedo, J.E., Characterization of the peroxisomal cycling receptor, Pex5p, using a cell-free in vitro import system (2003) J. Biol. Chem., 278, pp. 226-232; Oliveira, M.E., Gouveia, A.M., Pinto, R.A., Sa-Miranda, C., Azevedo, J.E., The energetics of Pex5p-mediated peroxisomal protein import (2003) J. Biol. Chem., 278, pp. 39483-39488; Glover, J.R., Andrews, D.W., Rachubinski, R.A., Saccharomyces cerevisiae peroxisomal thiolase is imported as a dimer (1994) Proc. Natl Acad. Sci. USA, 91, pp. 10541-10545; McNew, J.A., Goodman, J.M., An oligomeric protein is imported into peroxisomes in vivo (1994) J. Cell Biol., 127, pp. 1245-1257; Stewart, M.Q., Esposito, R.D., Gowani, J., Goodman, J.M., Alcohol oxidase and dihydroxyacetone synthase, the abundant peroxisomal proteins of methylotrophic yeasts, assemble in different cellular compartments (2001) J. Cell Sci., 114, pp. 2863-2868; Walton, P.A., Hill, P.E., Subramani, S., Import of stably folded proteins into peroxisomes (1995) Mol. Biol. Cell, 6, pp. 675-683; Saidowsky, J., Dodt, G., Kirchberg, K., Wegner, A., Nastainczyk, W., Kunau, W.H., Schliebs, W., The di-aromatic pentapeptide repeats of the human peroxisome import receptor PEX5 are separate high affinity binding sites for the peroxisomal membrane protein PEX14 (2001) J. Biol. Chem., 276, pp. 34524-34529; Schliebs, W., Saidowsky, J., Agianian, B., Dodt, G., Herberg, F.W., Kunau, W.H., Recombinant human peroxisomal targeting signal receptor PEX5. Structural basis for interaction of PEX5 with PEX14 (1999) J. Biol. Chem., 274, pp. 5666-5673; Costa-Rodrigues, J., Carvalho, A.F., Fransen, M., Hambruch, E., Schliebs, W., Sa-Miranda, C., Azevedo, J.E., Pex5p, the peroxisomal cycling receptor, is a monomeric non-globular protein (2005) J. Biol. Chem., 280, pp. 24404-24411; Elgersma, Y., Elgersma-Hooisma, M., Wenzel, T., McCaffery, J.M., Farquhar, M.G., Subramani, S., A mobile PTS2 receptor for peroxisomal protein import in Pichia pastoris (1998) J. Cell Biol., 140, pp. 807-820; Rehling, P., Marzioch, M., Niesen, F., Wittke, E., Veenhuis, M., Kunau, W.H., The import receptor for the peroxisomal targeting signal 2 (PTS2) in Saccharomyces cerevisiae is encoded by the PAS7 gene (1996) EMBO J., 15, pp. 2901-2913; Zhang, J.W., Lazarow, P.B., Peb1p (Pas7p) is an intraperoxisomal receptor for the NH2-terminal, type 2, peroxisomal targeting sequence of thiolase: Peb1p itself is targeted to peroxisomes by an NH2-terminal peptide (1996) J. Cell Biol., 132, pp. 325-334; Dodt, G., Warren, D., Becker, E., Rehling, P., Gould, S.J., Domain mapping of human PEX5 reveals functional and structural similarities to Saccharomyces cerevisiae Pex18p and Pex21p (2001) J. Biol. Chem., 276, pp. 41769-41781; Einwachter, H., Sowinski, S., Kunau, W.H., Schliebs, W., Yarrowia lipolytica Pex20p Saccharomyces cerevisiae Pex18p/Pex21p and mammalian Pex5pL fulfil a common function in the early steps of the peroxisomal PTS2 import pathway (2001) EMBO Rep., 2, pp. 1035-1039; Matsumura, T., Otera, H., Fujiki, Y., Disruption of the interaction of the longer isoform of Pex5p, Pex5pL, with Pex7p abolishes peroxisome targeting signal type 2 protein import in mammals. Study with a novel Pex5-impaired Chinese hamster ovary cell mutant (2000) J. Biol. Chem., 275, pp. 21715-21721; Gouveia, A.M., Guimaraes, C.P., Oliveira, M.E., Sa-Miranda, C., Azevedo, J.E., Insertion of Pex5p into the peroxisomal membrane is cargo protein-dependent (2003) J. Biol. Chem., 278, pp. 4389-4392; De La Torre, J.G., Hydrodynamics of segmentally flexible macromolecules (1994) Eur. Biophys. J., 23, pp. 307-322; Denning, D.P., Uversky, V., Patel, S.S., Fink, A.L., Rexach, M., The Saccharomyces cerevisiae nucleoporin Nup2p is a natively unfolded protein (2002) J. Biol. Chem., 277, pp. 33447-33455; Permyakov, S.E., Millett, I.S., Doniach, S., Permyakov, E.A., Uversky, V.N., Natively unfolded C-terminal domain of caldesmon remains substantially unstructured after the effective binding to calmodulin (2003) Proteins: Struct. Funct. Genet., 53, pp. 855-862; Uversky, V.N., Natively unfolded proteins: A point where biology waits for physics (2002) Protein Sci., 11, pp. 739-756; Lydakis-Simantiris, N., Hutchison, R.S., Betts, S.D., Barry, B.A., Yocum, C.F., Manganese stabilizing protein of photosystem II is a thermostable, natively unfolded polypeptide (1999) Biochemistry, 38, pp. 404-414; Sreerama, N., Woody, R.W., Estimation of protein secondary structure from circular dichroism spectra: Comparison of CONTIN, SELCON, and CDSSTR methods with an expanded reference set (2000) Anal. Biochem., 287, pp. 252-260; Stanley, W.A., Sokolova, A., Brown, A., Clarke, D.T., Wilmanns, M., Svergun, D.I., Synergistic use of synchrotron radiation techniques for biological samples in solution: A case study on protein-ligand recognition by the peroxisomal import receptor Pex5p (2004) J. Synchrotron Radiat., 11, pp. 490-496; Oberg, K.A., Fink, A.L., A new attenuated total reflectance Fourier transform infrared spectroscopy method for the study of proteins in solution (1998) Anal. Biochem., 256, pp. 92-106; Navea, S., Tauler, R., De Juan, A., Application of the local regression method interval partial least-squares to the elucidation of protein secondary structure (2005) Anal. Biochem., 336, pp. 231-242; Obradovic, Z., Peng, K., Vucetic, S., Radijovac, P., Dunker, A.K., Exploiting heterogeneous sequence properties improves prediction of protein disorder (2006) Proteins, , In the press; Gould, S.J., Collins, C.S., Opinion: Peroxisomal-protein import: Is it really that complex? (2002) Nature Rev. Mol. Cell. Biol., 3, pp. 382-389; Shoemaker, B.A., Portman, J.J., Wolynes, P.G., Speeding molecular recognition by using the folding funnel: The fly-casting mechanism (2000) Proc. Natl Acad. Sci. USA, 97, pp. 8868-8873; Pontius, B.W., Close encounters: Why unstructured, polymeric domains can increase rates of specific macromolecular association (1993) Trends Biochem. Sci., 18, pp. 181-186; Tompa, P., Intrinsically unstructured proteins (2002) Trends Biochem. Sci., 27, pp. 527-533; Gouveia, A.M., Reguenga, C., Oliveira, M.E., Sa-Miranda, C., Azevedo, J.E., Characterization of peroxisomal Pex5p from rat liver. Pex5p in the Pex5p-Pex14p membrane complex is a transmembrane protein (2000) J. Biol. Chem., 275, pp. 32444-32451; Dammai, V., Subramani, S., The human peroxisomal targeting signal receptor, Pex5p, is translocated into the peroxisomal matrix and recycled to the cytosol (2001) Cell, 105, pp. 187-196; Imanaka, T., Small, G.M., Lazarow, P.B., Translocation of acyl-CoA oxidase into peroxisomes requires ATP hydrolysis but not a membrane potential (1987) J. Cell Biol., 105, pp. 2915-2922; Wendland, M., Subramani, S., Cytosol-dependent peroxisomal protein import in a permeabilized cell system (1993) J. Cell Biol., 120, pp. 675-685; Azevedo, J.E., Costa-Rodrigues, J., Guimaraes, C.P., Oliveira, M.E., Sa-Miranda, C., Protein translocation across the peroxisomal membrane (2004) Cell Biochem. Biophys., 41, pp. 451-468; Wang, D., Visser, N.V., Veenhuis, M., Van Der Klei, I.J., Physical interactions of the peroxisomal targeting signal 1 receptor pex5p, studied by fluorescence correlation spectroscopy (2003) J. Biol. Chem., 278, pp. 43340-43345; Oliveira, M.E., Reguenga, C., Gouveia, A.M., Guimaraes, C.P., Schliebs, W., Kunau, W.H., Mammalian Pex14p: Membrane topology and characterisation of the Pex14p-Pex14p interaction (2002) Biochim. Biophys. Acta, 1567, pp. 13-22; Fransen, M., Wylin, T., Brees, C., Mannaerts, G.P., Van Veldhoven, P.P., Human pex19p binds peroxisomal integral membrane proteins at regions distinct from their sorting sequences (2001) Mol. Cell. Biol., 21, pp. 4413-4424; Sreerama, N., Venyaminov, S.Y., Woody, R.W., Estimation of protein secondary structure from circular dichroism spectra: Inclusion of denatured proteins with native proteins in the analysis (2000) Anal. Biochem., 287, pp. 243-251; Vigano, C., Margolles, A., Van Veen, H.W., Konings, W.N., Ruysschaert, J.M., Secondary and tertiary structure changes of reconstituted LmrA induced by nucleotide binding or hydrolysis. a Fourier transform attenuated total reflection infrared spectroscopy and tryptophan fluorescence quenching analysis (2000) J. Biol. Chem., 275, pp. 10962-10967; Laurent, T.C., Killander, J., Theory of gel filtration + its experimental verification (1964) J. Chromatog., 14, pp. 217-230;
Keywords: Amino acids; amino terminal sequence; article; biogenesis; Calorimetry, Differential Scanning; cell membrane; cell receptor; Chromatography, Gel; circular dichroism; cytosol; differential scanning calorimetry; human; Humans; infrared spectroscopy; matrix protein; Natively unfolded; Peroxisomal protein import; peroxisome; Pex5p; priority journal; Protein conformation; protein degradation; protein domain; protein folding; protein interaction; protein Pex5p; protein structure; Protein Structure, Secondary; Protein Structure, Tertiary; protein transport; pts1 receptor; PTS1-receptor; Receptors, Cytoplasmic and Nuclear; Spectroscopy, Fourier Transform Infrared; unclassified drug

The uptake of titanium ions by hydroxyapatite particles - Structural changes and possible mechanisms - Ribeiro, C.C.; Gibson, I.; Barbosa, M.A. (BiomaterialsBiomaterials, 2006)
In order to understand the effect of titanium ions on the molecular structure of hydroxyapatite (HAp), HAp powders were incubated in solutions with different titanium concentrations. After incubation, the powders obtained were analysed using different techniques, namely X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), differential thermal analysis (DTA), X-ray photoelectron spectroscopy (XPS), and energy dispersive spectroscopy (EDS). The results suggest that, depending on the concentration of titanium in solution, two different mechanisms of interaction with HAp occur. For concentrations equal to or smaller than 200 ppm, the titanium uptake by the solid seems to be primarily due to incorporation in the lattice. For higher concentrations, a dissolution-precipitation process seems to occur, leading to formation of a titanium phosphate compound. © 2005 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 44Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2005.09.043PubMed ID: 16256192Language of Original Document: EnglishCorrespondence Address: Ribeiro, C.C.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: cribeiro@ineb.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; titanium, 7440-32-6; Biocompatible Materials; Durapatite, 1306-06-5; Ions; Solutions; titanium phosphate, 17017-57-1; Titanium, 7440-32-6References: Fowler, B.O., Infrared studies of apatites. II Preparation of normal and isotopically substituted calcium, strontium, and barium hydroxyapatites and spectra-structure-composition correlations (1974) Inorg Chem, 13, pp. 207-214;Legeros, R.Z., Daculsi, G., Orly, I., Abergas, T., Torres, W., Solution mediated transformation of octacalcium phosphate (OCP) to apatite (1989) Scann Microsc, 3, pp. 129-138; Takahashi, H., Yashima, M., Kakihana, M., Yoshimura, M., Synthesis of stoichiometric hydroxyapatite by a "gel" route from the aqueous solution of citric and phosphonoacetic acids (1995) Eur J Solid State Inorg Chem, 32, pp. 829-835; Posner, A.S., Blumenthal, N., Betts, F., Chemistry and structure of precipitated hydroxyapatites (1984) Phosphate Minerals, pp. 330-347. , J.O. Nriagu P.B. Moore Springer New York; Yamashita, K., Kanazawa, T., Hydroxyapatite (1989) Inorganic Phosphate Materials, pp. 15-54. , T. Kanazawa Kodansha Tokyo; Legros, R., Balmain, N., Bonel, G., Age related changes in mineral of rat and bovine cortical bone (1987) Calcif Tissue Int, 41, pp. 137-144; Legeros, R.Z., Quirolgico, G., Legeros, J.P., Trace elements: Incorporation of monovalent cations, Na +, K +, Li + (1981) J Dent Res, 60, pp. 452-458; Christoffersen, J., Christoffersen, M.R., Kolthoff, N., Barenholdt, O., Effects of strontium ions on growth and dissolution of hydroxyapatite and on bone mineral detection (1997) Bone, 20, pp. 47-54; Suzuki, T., Hatsushika, T., Hayakawa, Y., Synthetic hydroxyapatites employed as inorganic cation-exchangers (1981) J Chem Soc Faraday Trans, 77, pp. 1059-1062; Miyake, M., Ishigaki, K., Suzuki, T., Structure refinements of Pb2+ ion exchanged apatites by X-ray powder pattern-fitting (1986) J Solid State Chem, 61, pp. 230-235; Ergun, C., Webster, T.J., Bizios, R., Doremus, R.H., Hydroxylapatite with substituted magnesium, zinc, cadmium, and yttrium I. Structure and microstructure (2002) J Biomed Mater Res, 59, pp. 305-311; Bonel, G., Montel, G., Sur une nouvelle apatite carbonatée synthétique (1964) Compt Rend, 258, pp. 923-926; Legeros, R.Z., Singer, L., Ophaug, R.H., Quirolgico, G., Thein, A., Legeros, J.P., The effect of fluoride on the stability of synthetic and biological (bone) mineral apatites (1982) Osteoporosis, pp. 327-341. , J. Menczel G.C. Robin M. Makin R. Steinbeg Wiley New York; Kreidler, E.R., Hummel, F.A., The crystal chemistry of apatite: Structure fields of fluor and chloroapatite (1970) Am Mineral, 55, pp. 171-184; LeGeros, R.Z., Trautz, O.R., LeGeros, J.P., Klein, E., Carbonate substitution in the apatite structure (1) (1968) Extrait du Bulletin de la Societé Chimique de France, (SPEC. NO.), pp. 1712-1718; Azimov, S.Y., Ismatov, A.A., Fedorov, N.F., Synthetic silicophosphates, silicovanadates, and silicoarsenates with the apatite structure (1981) Inorg Mater, 17, pp. 1384-1387; Termine, J.D., Lundy, D.R., Hydroxide and carbonate in rat bone mineral and its synthetic analogues (1973) Calcif Tissue Res, 13, pp. 73-78; Lacout, J.L., Nounah, A., Ferhat, M., Strontium-cadmium substitution in hydroxy-and fluor-apatites (1998) Ann Chim Sci Mater, 23, pp. 57-60; El Feki, H., Savariault, J.M., Ben Salah, A., Structure refinements by Rietveld method of partially substituted hydroxyapatite: Ca 9Na 0.5(PO 4) 4.5(CO 3) 1.5(OH) 2 (1999) J Alloys Compounds, 287, pp. 114-120; Legeros, R.Z., Apatites in biological systems (1981) Prog Cryst Growth Charact, 4, pp. 1-45; Rey, C., Calcium phosphates for medical applications (1998) Calcium Phosphates in Biological and Industrial Systems, pp. 217-251. , A. Zahid Kluwer Academic Publishers Boston; Watanabe, T., Makitsuru, K., Nakazawa, H., Hara, S., Suehiro, T., Yamamoto, A., Separation of double strand DNA fragments by high-performance liquid chromatography using a ceramic hydroxyapatite column (1999) Anal Chim Acta, 386, pp. 69-75; Bett, J.A.S., Christner, L.G., Hall, W.K., Studies of the hydrogen held by solids. XII (1967) J Am Chem Soc, 89, pp. 5535-5541; Takeuchi, Y., Arai, H., Removal of coexisting Pb 2+, Cu 2+ and Cd 2+ ions from water by addition of hydroxyapatite powder (1990) J Chem Eng Japan, 23, pp. 75-80; Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterisation of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Legeros, R.Z., Ultrastructural properties of human enamel apatite (1983) Handbook of Experimental Aspects of Oral Biochemistry, pp. 159-179. , E.P. Lazzari CRC Press FL; Young, R.A., Elliott, J.C., Atomic-scale bases for several properties of apatites (1966) Archs Oral Biol, 11, pp. 699-707; Elliott, J.C., The problems of the composition and structure of the mineral components of hard tissues (1973) Clin Orthoped, 93, pp. 313-317; Christofferson, M.R., Thyregod, H.C., Cristofferson, J., Effects of aluminum (III), chromium (III) and iron (III) on the rate of dissolution of calcium hydroxyapatite crystals in the absence and presence of chelating agent desferrioxamine (1987) Calcif Tissue Int, 41, pp. 27-30; Posner, A.S., Blumenthal, N.C., In vitro model of aluminum-induced osteomalacia: Inhibition of hydroxyapatite formation and growth (1984) Calcif Tissue Int, 36, pp. 439-441; Levin, S.M., Goldberg, M., Clinical evaluation and management of lead-exposed construction workers (2000) Am J Ind Med, 37, pp. 23-43; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, pp. 52-54. , H. Aoki Takayama Press System Center Tokyo; Kay, M.I., Young, R.A., Posner, A.S., Crystal structure of hydroxyapatite (1964) Nature, 204, pp. 1050-1052; Stavitzky, A., Golay, M.J.E., Smoothing and differentiation of data by simplified least squares procedures (1964) Anal Chem, 36, pp. 1627-1639; Elliot, J.C., (1994) Structure and Chemistry of the Apatites and Other Calcium Orthophosphates, , J.C. Elliot Elsevier Amsterdam; Morgan, H., Wilson, R.M., Elliot, J.C., Dowker, S.E.P., Anderson, P., Preparation and characterisation of monoclinic hydroxyapatite and its precipitated carbonate apatite intermediate (2000) Biomaterials, 21, pp. 617-627; Nakamoto, K., (1978) Infrared and Raman Spectra of Inorganic and Coordination Compounds, , K. Nakamoto Wiley New York; Legeros, R.Z., Bonel, G., Legros, R., Types of "h 2O" in human enamel and in precipitated apatites (1978) Calcif Tissue Res, 26, pp. 111-118; Joris, S.J., Amberg, C.H., The nature of deficiency in non-stoichiometric hydroxyapatites II. Spectroscopic studies of calcium and strontium hydroxyapatites (1971) J Phys Chem, 75, pp. 3172-3178; Leung, Y., Walters, M.A., Legeros, R.Z., Second derivative infrared spectra of hydroxyapatite (1990) Spectroc Acta, 46 (10), pp. 1453-1459; Miller, L.M., Vaiaravamurthy, V., Chance, M.R., Mendelshon, R., Paschalis, E.P., Betts, F., In situ analysis of mineral content and crystallinity in bone using infrared micro-spectroscopy of the ν 4 PO 4 3- vibration (2001) Biochim Biophys Acta, 1527, pp. 11-19; Fowler, B.O., Infrared studies of apatites I. Vibrational assignments for calcium, strontium and barium hydroxyapatites utilizing isotopic substitutions (1974) Inorg Chem, 13, pp. 194-207; Fowler, B.O., Moreno, E.C., Brown, W.E., Infra-red spectra of hydroxyapatite, octacalcium phosphate and pyrolised calcium phosphate (1966) Arch Oral Biol, 11, pp. 477-492; Rey, C., Shimizu, M., Collins, B., Glimcher, M.J., Resolution enhanced Fourier transform infrared spectroscopy study of the environment of phosphate ion in the early deposits of a solid phase calcium phosphate in bone and enamel and their evolution with age: Investigations in the ν 3 PO 4 3- domain (1991) Calcif Tissue Int, 49, pp. 383-388; Rey, C., Shimizu, M., Collins, B., Glimcher, M.J., Resolution enhanced Fourier transform infrared spectroscopy study of the environment of phosphate ion in the early deposits of a solid phase calcium phosphate in bone and enamel and their evolution with age: Investigations in the ν 4 PO 4 3- domain (1990) Calcif Tissue Int, 46, pp. 384-394; Gadaleta, S.J., Paschalis, E.P., Betts, F., Mendelsohn, R., Boskey, A.L., Fourier transform infrared spectroscopy of the solution-mediated conversion of amorphous calcium phosphate to hydroxyapatite: New correlations between X-ray diffraction and infrared data (1996) Calcif Tissue Int, 58, pp. 9-16; Bailey, R.T., Holt, C., Fourier transform infrared spectroscopy and characterisation of biological calcium phosphates (1989) Calcified Tissues, pp. 93-120. , D.W.L. Hukins Macmillan Press Basingstoke; Baddiel, C.B., Berry, E.E., Spectra structure correlations in hydroxy and fluorapatite (1966) Spectroc Acta, 22, pp. 1407-1416; Paschalis, E.P., Di Carlo, E., Betts, F., Sherman, P., Mendelsohn, R., Boskey, A.L., FTIR Microspectroscopic analysis of human osteonal bone (1996) Calcif Tissue Int, 59, pp. 480-487; Gibson, I.R., Rehman, I., Best, S.M., Bonfield, W., Characterization of the transformation from calcium-deficient apatite to β-tricalcium phosphate (2000) J Mater Sci: Mater Med, 12, pp. 799-804; Szirtes, L., Riess, L., Megyeri, J., Thermoanalytical investigation of layered titanium salts (2003) J Thermal Anal Calorim, 73, pp. 209-218; Schroeder, L.W., Dickens, B., Brown, W.E., Crystallographic studies of the role of Mg as a stabilizing impurity in β-Ca 3(PO 4) 2 - II. Refinement of Mg-containing β-Ca 3(PO 4) 2 (1977) J Sol State Chem, 22, pp. 253-262; Leadley, S.R., Davis, M.C., Ribeiro, C.C., Barbosa, M.A., Paul, A.J., Watts, J.F., Investigation of the dissolution of the bioceramic hydroxyapatite in the presence of titanium ions using ToF-SIMS and XPS (1997) Biomaterials, 18, pp. 311-316; Chusuei, C.C., Goodman, D.W., Van Stipdonk, M.J., Justes, D.R., Schweikert, E.A., Calcium phosphate phase identification using XPS and time-of-flight cluster SIMS (1999) Anal Chem, 71, pp. 149-153; Lu, H.B., Campbell, C.T., Graham, D.J., Ratner, B.D., Surface characterization of hydroxyapatite and related calcium phosphates by XPS and TOF-SIMS (2000) Anal Chem, 72, pp. 2886-2894; Tanahashi, M., Matsuda, T., Surface functional group dependence on apatite formation on self-assembled monolayers in a simulated body fluid (1997) J Biomed Mater Res, 34, pp. 305-315; Ma, Q.Y., Traina, S.J., Logan, T.J., Ryan, J.A., In situ lead immobilization by apatite (1993) Environ Sci Technol, 27, pp. 1803-1810; Xu, Y., Schwartz, F.W., Lead immobilization by hydroxyapatite in aqueous solutions (1994) J Contam Hydro, 15, pp. 187-206; Lower, S.K., Maurice, P.A., Traina, S.J., Carlson, E.H., Aqueous Pb sorption by hydroxylapatite: Applications of atomic force microscopy to dissolution, nucleation, and growth studies (1998) Am Miner, 83, pp. 147-158; Ribeiro, C.C., Barbosa, M.A., MacHado, A., Tudor, A., Davies, M.C., Modifications in the molecular structure of hydroxyapatite induced by Ti ions (1995) J Mater Sci: Mater Med, 6, pp. 829-834; Tanizawa, Y., Sawamura, K., Suzuki, T., Reaction characteristics of dental and synthetic apatites with Fe 2+ and Fe 3+ ions (1990) J Chem Soc Faraday Trans, 86, pp. 1071-1075; Tanizawa, Y., Sawamura, K., Suzuki, T., Reaction characteristics of dental and synthetic apatites with Al 2+ and La 3+ ions in acidic solutions (1990) J Chem Soc Faraday Trans, 86, pp. 4025-4029; Layani, J.D., Mayer, I., Cuisinier, F.J.G., Carbonated hydroxyapatites precipitated in the presence of Ti (2000) J Inorg Biochem, 81, pp. 57-63; Gonzalez-Diaz, P.F., Santos, M., On the hydroxyl ions in apatites (1977) J Sol State Chem, 22, pp. 193-199; Vilchez, G.F., Griffith, W.P., Transition-metal tetra-oxo-complexes and their vibrational spectra (1972) J Chem Soc Dalton, 2, pp. 1416-1421; Bamberger, C.E., Begun, G.M., Cavin, O.B., Synthesis and characterization of sodium-titanium phosphates, Na 4(TiO)(PO 4) 2, Na(TiO)PO 4 and NaTi 2(PO 4) 3 (1988) J Solid State Chem, 73, pp. 317-324; El Jazouli, A., Krimi, S., Manoun, B., Chaminade, J.P., Gravereau, P., De Waal, D., Preparation and structural characterization of two new titanium phosphates NaCa 0.5Ti(PO 4) 3 and Ni 0.5TiOPO 4 (1998) Ann Chim Sci Mater, 23, pp. 7-10; Chernorukov, N.G., Korshunov, I.A., Zhuk, M.I., Hydro-ortho-derivatives of titanium of composition Ti(OH)PO 4 and Ti(OH)AsO 4 (1982) Russ J Inorg Chem, 27, pp. 1728-1731; Bamberger, C.E., Begun, G.M., Synthesis and characterisation of titanium phosphates, TiP 2O 7 and (TiO) 2P 2O 7 (1987) J Less Common Metals, 134, pp. 201-206
Keywords: article; Biocompatible Materials; concentration response; differential scanning calorimetry; drug mechanism; drug structure; Durapatite; Energy dispersive spectroscopy; Fourier transform infrared spectroscopy; hydroxyapatite; Incubation; infrared spectroscopy; Ions; Lattice constants; particulate matter; powder; Precipitation (chemical); priority journal; Solutions; Spectroscopy; Spectroscopy, Fourier Transform Infrared; temperature; Titanium; Titanium ions; Titanium phosphate; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; X-Ray Diffraction

Biocatalytic synthesis of highly ordered degradable dextran-based hydrogels - Ferreira, L.; Gil, M.H.; Cabrita, A.M.S.; Dordick, J.S. (BiomaterialsBiomaterials, 2005)
We have prepared unique macroporous and ordered dextran-based hydrogels using a single-step biocatalytic transesterification reaction between dextran and divinyladipate in neat dimethylsulfoxide. These hydrogels show a unimodal distribution of interconnected pores with average diameters from 0.4 to 2.0 μm depending on the degree of substitution. In addition, the hydrogels show a higher elastic modulus for a given swelling ratio than chemically synthesized dextran-based hydrogels. In vivo studies in rats show that the hydrogel networks are degradable over a range of time scales from 5 to over 40 days, and possess good biocompatibility, as reflected in only a mild inflammatory reaction and minor fibrous capsule formation during the time-frame of subcutaneous implantation. These combined properties may offer competitive advantages in biomedical applications ranging from tissue engineering to controlled drug delivery. © 2004 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2004.11.051PubMed ID: 15763250Language of Original Document: EnglishCorrespondence Address: Dordick, J.S.; Dept. of Chem. and Biol. Engineering, Rensselaer Polytechnic Institute, 102 Ricketts Bldg., Troy, NY 12180, United States; email: dordick@rpi.eduChemicals/CAS: dextran, 87915-38-6, 9014-78-2; dimethyl sulfoxide, 67-68-5; Biocompatible Materials; Dextrans, 9004-54-0; Hydrogels; Peptide Hydrolases, EC 3.4.-Manufacturers: Fluka, SwitzerlandReferences: Lee, K.Y., Peters, M.C., Anderson, K.W., Mooney, D.J., Controlled growth factor release from synthetic extracellular matrices (2000) Nature, 408, pp. 998-1000;Zhu, G., Mallery, S.R., Schwendeman, S.P., Stabilization of proteins encapsulated in injectable poly(lactide-co- glycolide) (2000) Nature Biotechnol, 18, pp. 52-57; Shea, L.D., Smiley, E., Bonadio, J., Mooney, D.J., DNA delivery from polymer matrices for tissue engineering (1999) Nature Biotechnol, 17, pp. 551-554; Griffith, L.G., Naughton, G., Tissue engineering-current challenges and expanding opportunities (2002) Science, 295, pp. 1009-1014; Lee, K.Y., Mooney, D.J., Hydrogels for tissue engineering (2001) Chem Rev, 101, pp. 1869-1879; Wong, W.H., Mooney, D.J., Synthesis and properties of biodegradable polymers used as synthetic matrices for tissue engineering (1997) Synthetic Biodegradable Polymer Scaffolds, pp. 49-82. , A. Atala D.J. Mooney Birkhäuser Boston; Holmes, T.C., Novel peptide-based biomaterial scaffolds for tissue engineering (2002) TIBTECH, 20, pp. 16-21; Mehvar, R., Dextrans for targeted and sustained delivery of therapeutic and imaging agents (2000) J Control Rel, 69, pp. 1-25; Kim, S.-H., Chu, C.-C., Synthesis and characterization of dextran-methacrylate hydrogels and structural study by SEM (2000) J Biomed Mater Res, 49, pp. 517-527; Kim, S.-H., Chu, C.-C., Pore structure analysis of swollen dextran-methacrylate hydrogels by SEM and mercury intrusion porosimetry (2000) J Biomed Mater Res (Appl Biomater), 53, pp. 258-266; Meyvis, T., De Smedt, S., Stubbe, B., Hennink, W., Demeester, J., On the release of proteins from degrading dextran methacrylate hydrogels and the correlation with the rheologic properties of the hydrogels (2001) Pharm Res, 18, pp. 1593-1599; Patil, N.S., Dordick, J.S., Rethwisch, D.G., Macroporous poly(sucrose acrylate) hydrogel for controlled release of macromolecules (1996) Biomaterials, 17, pp. 2343-2350; Park, H., Park, K., Biocompatibility issues of implantable drug delivery systems (1996) Pharm Res, 13, pp. 1770-1776; Loebsack, A., Greene, K., Wyatt, S., Culberson, C., Austin, C., Beiter, R., Roland, W., Halberstadt, C., In vivo characterization of a porous hydrogel material for use as a tissue bulking agent (2001) J Biomed Mater Res, 57, pp. 575-581; Cadée, J.A., Luyn, M.J.A., Brouwer, L.A., Plantinga, J.A., Van Wachem, P.B., Groot, C.J., Otter, W., Hennink, W.E., In vivo biocompatibility of dextran-based hydrogels (2000) J Biomed Mater Res, 50, pp. 397-404; Ferreira, L., Gil, M.H., Dordick, J.S., Enzymatic synthesis of dextran-containing hydrogels (2002) Biomaterials, 23, pp. 3957-3967; Washburn, E.W., Note on a method of determining the distribution of pore sizes in a porous material (1921) Proc Natl Acad Sci, 7, pp. 115-116; Brancroft, J.D., Stevens, A., (1996) Theory and Practice of Histological Techniques, , Churchill Livingstone Edinburgh; Martin, B.D., Linhardt, R.J., Dordick, J.S., Highly swelling hydrogels from ordered galactose-based polyacrylates (1998) Biomaterials, 19, pp. 69-76; Ferreira, L., Ramos, M.A., Gil, M.H., Dordick, J.S., Exquisite regioselectivity and transesterification activity enhancement of an immobilized Bacillus subtilis protease (2002) Biotechnol Prog, 18, pp. 986-993; Ferreira, L., Gil, M.H., Carvalho, R., Geraldes, C.F.G.C., Kim -., D.Y., Dordick, J.S., Biocatalytic polytransesterification of inulin with divinyladipate (2002) Chem Mater, 14, pp. 4009-4011; Zaks, A., Klibanov, A.M., Enzymatic catalysis in nonaqueous solvents (1988) J Biol Chem, 263, pp. 3194-3201; Almarsson, Ö., Klibanov, A.M., Remarkable activation of enzymes in nonaqueous media by denaturing organic cosolvents (1996) Biotechnol Bioeng, 49, pp. 87-92; Brøndsted, H., Hovgaard, L., Simonsen, L., Dextran hydrogels for colon-specific drug delivery II. Synthesis and characterization (1996) Eur J Pharm Biopharm, 42, pp. 85-89; De Smedt, S.C., Lauwers, A., Demeester, J., Van Steenbergen, M.J., Hennink, W.E., Roefs, S.P.F.M., Characterization of the network structure of dextran glycidyl methacrylate hydrogels by studying the rheological and swelling behavior (1995) Macromolecules, 28, pp. 5082-5088; Dziubla, I.D., Torjman, M.C., Joseph, J.I., Murphy-Tatum, M., Lowman, A.M., Evaluation of porous networks of poly(2-hydroxyethylmethacrylate) as interfacial drug delivery devices (2001) Biomaterials, 22, pp. 2893-2899; Kuijpers, A.J., Wachem, P.B., Luyn, M.J.A., Plantinga, J.A., Engbers, G.H.M., Krijgsveld, J., Zaat, S.A.J., Feijen, J., In vivo compatibility and degradation of crosslinked gelatin gels incorporated in knitted Dacron (2000) J Biomed Mater Res, 51, pp. 136-145; Suggs, L.J., Krishnan, R.S., Garcia, C.A., Peter, S.J., Anderson, J.M., Mikos, A.G., In vitro and in vivo degradation of poly(propylene fumarate-co-ethylene glycol) hydrogels (1998) J Biomed Mater Res, 42, pp. 312-320; Ferreira, L., Rafael, A., Lamghari, M., Barbosa, M.A., Gil, M.H., Cabrita, A.M.S., Dordick, J.S., Biocompatibility of chemoenzymatically derived dextran-acrylate hydrogels (2004) J Biomed Mater Res, 68, pp. 584-596; Van Dijk-Wolthuis, W.N.E., Hoogeboom, J.A.M., Van Steenbergen, M.J., Tsang, S.K.Y., Hennink, W.E., Degradation and release behavior of dextran-based hydrogels (1997) Macromolecules, 30, pp. 4639-4645
Keywords: Absorbable Implants; adipic acid derivative; animal experiment; animal tissue; Animals; article; Bacillus subtilis; Biocatalysts; Biocompatibility; Biocompatible Materials; Biodegradation; Biomedical engineering; biosynthesis; catalysis; Controlled drug delivery; controlled study; Cross-linking; dextran; Dextran-based hydrogels; Dextrans; dimethyl sulfoxide; Dimethylsulfoxide; Elastic moduli; Elasticity; Enzyme; Foreign-Body Reaction; hydrogel; Hydrogels; implantation; in vivo study; Inflammation; male; materials testing; nonhuman; Peptide Hydrolases; porosity; priority journal; rat; Rats; Rats, Wistar; substitution reaction; Sulfur compounds; Surface Properties; Swelling; Swelling ratio; synthesis; Tissue; transesterification; Transesterification reactions

Bonelike®/PLGA hybrid materials for bone regeneration: Preparation route and physicochemical characterisation - Oliveira, J.M.; Miyazaki, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Bonelike®/PLGA hybrid materials have been developed using γ-MPS as silane-coupling agent between the inorganic and organic phases for controlled drug delivery applications. Silanization showed to be more effective when cyclohexane was used as a non-polar solvent (nP method) due to a chemical interaction between Bonelike®, and the silane film, while by using a 95/5 (V/V) methanol/water as a polar solvent (P method), a much thinner film was achieved. Functional groups of PLGA, such as the carbonyl group (C=O), were identified using Raman and FTIR-ATR analysis and therefore these groups may be used to link therapeutic molecules. These novel hybrid materials prepared by combining silanization and post-hybridisation processes are expected to find use in medical applications of bone regeneration and as drug delivery carrier for therapeutic molecules. © 2005 Springer Science + Business Media, Inc.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-005-6687-yLanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB - Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; lactic acid, 113-21-3, 50-21-5; polyglycolic acid, 26124-68-5; cyclohexane, 110-82-7; methanol, 67-56-1; polyglactin, 26780-50-7, 34346-01-5; silane, 7803-62-5; water, 7732-18-5; Durapatite, 1306-06-5; Lactic Acid, 50-21-5; Polyglycolic Acid, 26009-03-0; polylactic acid-polyglycolic acid copolymer; Polymers; SilanesTradenames: Bonelike, AldrichManufacturers: AldrichReferences: Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , JAAS;Glimcher, M.J., (1976) Handbook of Physiology, Endocrinology, , edited by R. O. Greep and E. B. Astwood (American Physiological Society, Washington D.C.); Shors, E.C., Holmes, R.E., (1993) An Introduction to Bioceramics, p. 181. , edited by L. L. Hench and J. Wilson (World Scientific, Hong-Kong); Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 48, p. 734; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085; Lopes, M.A., Silva, R.F., Monteiro, F.J., Santos, J.D., (2000) Biomaterials, 21, p. 749; Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905; Jha, L.J., Santos, J.D., Knowles, J.C., (1996) J. Biomed. Mater. Res., 31, p. 481; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (2001) J. Mater. Sci.: Mater. Med., 12, p. 629; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Wang, M., Deb, S., Bonfield, W., (2000) Mater. Lett., 44, p. 119; George, I., Viel, P., Bureau, C., Suski, J., Lécayon, G., (1996) Surf. Interf. Anal., 24, p. 774; Liu, Q., De Wijn, J.R., De Groot, K., Van Blitterwijk, C.A., (1998) Biomaterials, 19, p. 1067; Ara, M., Watanabe, M., Imai, Y., (2002) Biomaterials, 23, p. 2479; Agrawal, C.M., Ray, R.B., (2001) J. Biomed. Mater. Res., 55, p. 141; Arnold, U., Lindenhayn, K., Perka, C., (2002) Biomaterials, 23, p. 2303; Rizzi, S.C., Heath, D.J., Coombes, A.G.A., Bock, N., Textor, M., Downes, S., (2001) J. Biomed. Mater. Res., 55, p. 475; Simon Jr., C.G., Khatri, C.A., Wight, S.A., Wang, F.W., (2002) J. Orthop. Res., 20, p. 473; Mikos, A.G., Temenoff, J.S., (2000) EJB Electr. J. Biotechn., 3 (2); Laurencin, C.T., Attawia, M.A., Lu, L.Q., Borden, M.D., Lu, H.H., Gorum, W.J., Lieberman, J.R., (2001) Biomaterials, 22, p. 1271; Takenaga, M., Yamaguchi, Y., Kitagawa, A., Ogawa, Y., Mizushima, Y., Igarashi, R., (2002) J. Contr. Rel., 79, p. 81; Dupraz, A.M.P., De Wijn, J.R., Van De Meer, S.A.T., De Groot, K., (1996) J. Biomed. Mater. Res., 30, p. 231; Sheldon, R.P., (1982) Appl. Sci. Publ., 1, p. 1; Zhu, P.X., Ishikawa, M., Seo, W.S., Hozumi, A., Yokogawa, Y., Koumoto, K., (2002) J. Biomed. Mater. Res., 59, p. 294; Hooshmand, T., Van Noort, R., Keshvad, A., (2002) Dent. Mater., 18, p. 179; Venhoven, B.A.M., De Gee, A.J., Werner, A., Davidson, C.L., (1994) Biomaterials, 15, p. 1152; Yerby, S.A., Paal, A.F., Young, P.M., Beaupré, G.S., Ohashi, K.L., Goodman, S.B., (2000) J. Biomed. Mater. Res., 49, p. 127; Wang, M., Bonfield, W., (2001) Biomaterials, 22, p. 1311; Santos, C., Luklinska, Z.B., Clarke, R.L., Davy, K.W.M., (2001) J. Mater. Sci.: Mat. Med., 12, p. 565; Santos, J.D., Knowles, J.C., Hastings, G.W., in "Sintered Hydroxyapatite Compositions and Method for the Preparation Thereof," European Patent No. WO0068164 (2000)Afonso, A., Santos, J.D., Vasconcelos, M., Branco, R., Cavalheiro, J., (1996) J. Mater. Sci.: Mater. Med., 7, p. 507; Hoffman, R., Westheim, J.G.F., Pouwel, I., Fransen, T., Gellings, P.J., (1996) Surf. Interf. Anal., 24, p. 1; Rider, A.N., Arnott, D.R., (1996) Surf. Interf. Anal., 24, p. 583; Eufinger, S., Van Ooij, W.J., Conners, K.D., (1996) Surf. Interf. Anal., 24, p. 841
Keywords: analytic method; article; Biological materials; Bone; Bone Regeneration; carbonyl derivative; chemical bond; chemical interaction; chemical reaction; Chemical reactions; chemistry; Chemistry, Physical; cyclohexane; Drug delivery; drug delivery system; Drug therapy; Durapatite; film; Fourier transform infrared spectroscopy; Hybrid materials; hybridization; hydroxyapatite; infrared spectroscopy; Lactic Acid; methanol; methodology; Microscopy, Electron, Scanning; Molecules; physical chemistry; polyglactin; polyglycolic acid; polylactic acid polyglycolic acid copolymer; polylactic acid-polyglycolic acid copolymer; polymer; Polymers; priority journal; Raman spectrometry; Raman spectroscopy; reaction analysis; Scanning electron microscopy; silane; silane derivative; Silanes; Silanization; solvent effect; Solvents; Spectroscopy, Fourier Transform Infrared; Spectrum Analysis, Raman; synthesis; Water; X ray; X-Rays

Chemical modification of chitosan by phosphorylation: An XPS, FT-IR and SEM study - Amaral, I.F.; Granja, P.L.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2005)
In the present work, the surface of chitosan membranes was modified using a phosphorylation method carried out at room temperature. Phosphorylation may be of particular interest in materials for orthopaedic applications, due to the cation-exchange properties of phosphate functionalities. Phosphate groups chelate calcium ions, thus inducing the deposition of an apatite-like layer known to improve the osteoconduction of polymer-based implants. Additionally, the negatively charged phosphate functionalities, together with the positively charged amine groups from chitosan, are expected to provide chitosan with an amphoteric character, which may be useful as a combinatorial therapeutic strategy, by simultaneously allowing the immobilization of signalling molecules like growth factors. Phosphorylation was carried out at room temperature using the H 3 PO 4/Et 3 PO 4/P 2O 5/butanol method. Surface characterization was performed by XPS, ATR-FT-IR, and SEM. Cross-sections were analyzed by SEM fitted with EDS. The phosphate content increased with the reaction time, as shown by XPS and ATR-FT-IR, a P/N atomic ratio of 0.73 being obtained after 48 h of treatment. High-resolution XPS spectra regarding C 1s, O 1s, N 1s and P 2p are discussed. The introduction of a neutralization step led to a reduction of P content, which pointed out to the presence of phosphates ionically bound to protonated amines, in addition to phosphate esters. EDS analysis of cross-sections revealed a gradual P reduction up to 50% towards the inner part of the membrane. © VSP 2005.
Cited By (since 1996): 50Export Date: 21 November 2012Source: ScopusCODEN: JBSEEdoi: 10.1163/156856205774576736Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; Laboratório de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; phosphate, 14066-19-4, 14265-44-2; apatite, 64476-38-6; butanol, 35296-72-1, 71-36-3; calcium ion, 14127-61-8; Chitosan, 9012-76-4; PhosphatesReferences: Khor, E., (2001) Chitin: Fulfilling a Biomaterials Promise, , Elsevier Science, Oxford;Vande Vord, P.J., Matthew, H.W.T., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., (2002) J. Biomed. Mater. Res., 59, p. 585; Muzzarelli, R.A.A., Mattioli-Belmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., (1994) Biomaterials, 15, p. 1075; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., (2002) J. Control. Rel., 78, p. 187; (2002) Chitosan in Pharmacy and Chemistry, p. 233. , R.A. A. Muzzarelli and C. Muzzarelli (Eds), in: Atec, Grottammare; Zhao, F., Yin, Y.J., Lu, W.W., Leong, J.C., Zhang, W.J., Zhang, J.Y., Zhang, M.F., Yao, K.D., (2002) Biomaterials, 23, p. 3227; Tanahashi, M., Matsuda, T., (1997) J. Biomed Mater. Res., 34, p. 305; Yokogawa, Y., Reyes, J.P., Mucalo, M.R., Toriyama, M., Kawamoto, Y., Suzuki, T., Nishizawa, K., Kamayama, T., (1997) J. Mater. Sci. Mater. Med., 8, p. 407; Varma, H.K., Yokogawa, Y., Espinosa, F.F., Kawamoto, Y., Nishizawa, K., Nagata, F., Kameyama, T., (1999) Biomaterials, 20, p. 879; Orban, J.M., Marra, K.G., Hollinger, J.O., (2002) Tissue Eng., 8, p. 529; Ilyina, A.V., Varlamov, V.P., Tikhonov, V.E., Yamskov, I.A., Davankov, V.A., (1994) Biotechnol. Appl. Biochem., 19, p. 199; Sugihara, J., Imamura, T., Yanase, T., Yamada, H., Imoto, T., (1982) J. Chromatogr., 229, p. 193; Kennedy, J.F., Cabral, J.M.S., (1983) Solid Phase Biochemistry: Analytical Synthetic Aspects, p. 253. , in: W. H. Schouten (Ed.) Wiley, New York, NY; Chatelet, C., Damour, O., Domard, A., (2001) Biomaterials, 22, p. 261; Granja, P.L., Pouysegu, L., Petraud, M., De Jeso, B., Baquey, C., Barbosa, M.A., (2001) J. Appl. Polym. Sci., 82, p. 3341; Fricain, J.C., Granja, P.L., Barbosa, A.M., de Jeso, B., Barthe, N., Baquey, C., (2002) Biomaterials, 23, p. 971; Sakairi, N., Shirai, A., Miyazaki, S., Tashiro, H., Tsuji, Y., Kawahara, H., Yoshida, T., Tokura, S., (1998) Kobunshi Ronbunshu, 55, p. 212; Sakaguchi, T., Horkoshi, T., Nakajima, A., (1981) Agricult. Biol. Chem., 45, p. 2191; Nishi, N., Ebina, A., Nishimura, S., Tsutsumi, A., Hasegawa, O., Tokura, S., (1986) Int. J. Biol. Macromol., 8, p. 311; Baxter, B., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., (1992) Int. J. Biol. Macromol., 14, p. 166; Wang, W., Bo, S.Q., Li, S.Q., Qin, W., (1991) Int. J. Biol. Macromol., 13, p. 281; Aiba, S., (1986) Int. J. Biol. Macromol., 8, p. 173; Hirano, S., Ohe, Y., Ono, H., (1976) Carbohydr. Res., 47, p. 315; Shigemasa, Y., Matsuura, H., Sashiwa, H., Saimoto, H., (1996) Int. J. Biol. Macromol., 18, p. 237; Seah, M.P., (1990) Practical Surface Analysis, 1, p. 541. , D.in: Briggs and M. P. Seah (Eds) Wiley, Chichester; Sherwood, P.M.A., (1990) Practical Surface Analysis, 1, p. 555. , in: D. Briggs and M. P. Seah (Eds) Wiley, Chichester; Hudson, S.M., Smith, C., (1998) Bio-polymers from Renewable Resources, p. 96. , in: D. L. Kaplan (Ed.) Springer, Berlin; Shepherd, R., Reader, S., Falshaw, A., (1997) Glycoconj. J., 14, p. 535; Wang, X.H., Ma, J.B., Wang, Y.N., He, B.L., (2001) Biomaterials, 22, p. 2247; Lee, Y.M., Shin, E.M., (1991) J. Membr. Sci., 64, p. 145; Kim, S.S., Jeong, W.Y., Shin, B.C., Oh, S.Y., Kim, H.W., Rhee, J.M., (1998) J. Biomed. Mater. Res., 40, p. 401; Whistler, R.L., Towle, G.A., (1969) Arch. Biochem. Biophys., 135, p. 396; Gardner, S.D., Singamsetty, C.S.K., Booth, G.L., He, G., (1995) Carbon, 33, p. 587; Briggs, D., (1990) Practical Surface Analysis, 1, p. 437. , in: D. Briggs and M. P. Seah (Eds) Wiley, Chichester; Beamson, G.D.B., (1992) High Resolution XPS of Organic Polymers, , Wiley, Chichester; Ratner, B.D., Caster, D.G., (1997) Surface Analysis - The Principal Techniques, p. 43. , in: J. C. Vickerman (Ed.) Wiley, Chichester; Bourbigot, S., Lebras, M., Gengembre, L., Delobel, R., (1994) Appl. Surf. Sci., 81, p. 299; Kilpadi, D.V., Raikar, G.N., Liu, J., Lemons, J.E., Vohra, Y., Gregory, J.C., (1998) J. Biomed. Mater. Res., 40, p. 646; Landis, W.J., (1984) Vac. Technol., A2, p. 1108; Wagner, C.D., Naumkin, A.V., Kraut-Vass, A., Alisson, J.W., Powell, C.J., Rumble Jr., J.R., (2003) NIST-X-ray Photoelectron Spectroscopy Database 20 Version 3.4, , http://srdata.nist.gov/xps/, National Institute of Standards and Technology, Gaithersburg, MD Available online at; Quan, D.T., Le Bloa, A., Habib, H., Bonnaud, O., Meinnel, J., Quemerais, A., Marchand, R., (1989) Rev. Phys. Appl., 24, p. 545; Lindberg, B., Maripuu, R., Siegbahn, K., Larsson, R., Golander, C.G., Eriksson, J.C., (1983) J. Colloid Interf. Sci., 95, p. 308; Domard, A., (1997) Advances in Chitin Science, 2, p. 410. , in: A. Domard, G. Roberts and K. Vårum (Eds) Jacques André, Lyon; Granja, P.L., Pouysegu, L., Deffieux, D., Daude, G., De Jeso, B., Labrugere, C., Baquey, C., Barbosa, M.A., (2001) J. Appl. Polym. Sci., 82, p. 3354; Roeges, N.P.G., (1994) A Guide to the Complete Interpretation of Infrared Spectra of Organic Structures, , Wiley, Chichester; Pearson, F.G., Marchessault, R.H., Liang, C.Y., (1960) J. Polym. Sci., 43, p. 101; Roberts, G.A.F., (1992) Chitin Chemistry, , Macmillan, London; Kuptsov, A.H., Zhizhin, G.N., (1998) Handbook of Fourrier Transform Raman and Infrared Spectra of Polymers, , Elsevier, Amsterdam; Daasch, L.W., Smith, D.C., (1951) Anal. Chem., 23, p. 854; Bueno, W.A., (1990) Manual De Espectroscopia Vibracional, , McGraw-Hill, São Paulo; Nyquist, R.A., Craver, C.D., (1997) The Coblentz Society Desk Book of Infrared Spectra, , The Coblentz Society, French Village, MO; Hirano, S., Tobetto, K., Noishiki, Y., (1981) J. Biomed. Mater. Res., 15, p. 903
Keywords: Acetylation; amine; animal; Animals; Apatite; article; bone conduction; butanol; calcium ion; cation exchange; cephalopod; chelate; Chemical modification; chemistry; Chitin; chitosan; comparative study; controlled study; Decapodiformes; Fourier transform infrared spectroscopy; Fourier transform infrared spectroscopy (FT-IR); Growth factor; immobilization; Implants (surgical); infrared spectroscopy; isolation and purification; Microscopy, Electron, Scanning; molecular weight; organophosphate; phosphate; Phosphate groups; Phosphates; Phosphorylation; Phosphorylation method; Plastics applications; priority journal; reflectometry; room temperature; Scanning electron microscopy; SEM-EDS; signal transduction; spectrometry; Spectrometry, X-Ray Emission; Spectroscopy, Fourier Transform Infrared; Surface chemical reaction; Surface Properties; surface property; temperature; time; Time Factors; viscosity; X ray photoelectron spectroscopy; X-rayphotoelectron spectroscopy (XPS)

Development of a system to adsorb drugs onto calcium phosphate materials - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Several studies were carried out in order to reduce the systemic use of antibiotics due to the high concentration required to provide the minimum inhibitory concentration (MIC) at infected sites. The aim of this study was to develop a system of drug adsorption onto commercial hydroxyapatite (HA, Ca 10(PO 4) 6(OH) 2) and glass reinforced hydroxyapatite (GR-HA) granules. The drug will then be released for the local treatment of periodontitis. The antibiotics used in this study were metronidazole, a specific antibiotic indicated for the systemic treatment of periodontitis, and ampicillin, a wide spectrum antibiotic. UV spectroscopy was used to measure the amount of drug adsorbed onto HA and GR-HA granules. Results showed that metronidazole was unable to adsorb on the material's surface, as opposed to ampicillin which adsorbed both onto HA and GR-HA. Preliminary release kinetics studies were carried out using a flow through dissolution system. Results are discussed in terms of the influence of the different surface characteristics of the materials on the adsorption processes. © 2005 Springer Science + Business Media, Inc.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-005-2535-3PubMed ID: 15965596Language of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180, Porto, Portugal; email: aqueiroz@ineb.up.ptChemicals/CAS: ampicillin, 69-52-3, 69-53-4, 7177-48-2, 74083-13-9, 94586-58-0; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; metronidazole, 39322-38-8, 443-48-1; Ampicillin, 69-53-4; Anti-Infective Agents; calcium phosphate, 10103-46-5; Calcium Phosphates; Coated Materials, Biocompatible; Delayed-Action Preparations; Drug Carriers; Metronidazole, 443-48-1References: Seymour, R.A., Heasman, P.A., Macgregor, I.D.M., (1992) Drugs, Diseases, and the Periodontium, 1. , edited by R. A. Seymour and P. A. Heasman Oxford University Press, Oxford;Carnevale, R.A., Greco, G.W., Bullard, C.M., Hanker, J.S., (1987) Biomedical Materials and Devices, p. 247. , edited by J. S. Hanker and B. L. Giammara Materials Research Society, Pittsburgh; Friedman, M., Steinberg, D., (1990) Pharm. Res., 7, p. 313; Hagiwara, S., Takamatsu, N., Tominaga, Y., Umeda, M., (1998) J. Period., 69, p. 62; Wright, T.L., Ellen, R.P., Lacroix, J.M., Sinnadurai, S., Mittelman, M.W., (1997) J. Period. Res., 32, p. 473; Golomb, G., Friedman, M., Soskolne, A., Stabholz, A., Sela, M.N., (1984) J. Dent. Res., 63, p. 1149; Goodson, J.M., Hogan, P.E., Dunham, S.L., (1984) J. Period., 55, p. 81; Somayaji, B.V., Jariwala, U., Jayachandran, P., Vidyalakshim, K., Dudhani, R.V., (1998) J. Period., 69, p. 409; Stoltze, K., (1992) J. Clin. Period., 19, p. 698; Goodson, J.M., Holborow, D., Dunn, R.L., Hogan, P., Dunham, S., (1983) J. Period., 54, p. 575; Yu, D., Wong, J., Matsuda, Y., Fox, J.L., Higuchi, W.I., Otsuka, M., (1992) J. Pharm. Sci., 81, p. 529; Nishihara, K., (1993) Clin. Mater., 12, p. 159; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mat. Res., 45, p. 376; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mat. Res., 47, p. 603; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mat. Res., 54, p. 463; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., (2001) Biomaterials, 22, p. 1393; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Knowles, J.C., Santos, J.D., Hastings, G.W., World Patent, WO0068164 (1994)Myers, H.M., Tochon-Danguy, H.J., Baud, C.A., (1983) Calcif. Tissue Int., 35, p. 745; Ratier, A., Gibson, I.R., Best, S.M., Freche, M., Lacout, J.L., Rodrigues, F., (2001) Biomaterials, 22, p. 897; Ando, D.J., (1996) Ultraviolet and Visible Spectroscopy, p. 16. , John Wiley & Sons, West Sussex
Keywords: Adsorption; ampicillin; Anti-Infective Agents; Antibiotics; article; Calcium Compounds; calcium phosphate; Calcium phosphates; Coated Materials, Biocompatible; concentration response; Delayed-Action Preparations; Diffusion; Dissolution; drug absorption; drug adsorption; Drug Carriers; Drug release; drug stability; glass; Glass reinforced hydroxyapatie (GR-HA); human; Humans; hydroxyapatite; Kinetics; Material's surface; Materials science; materials testing; metronidazole; minimum inhibitory concentration; Minimum inhibitory concentration (MIC); periodontitis; priority journal; Reaction kinetics; reduction; surface property; Ultraviolet spectroscopy

In vitro cytocompatibility of MG63 cells on chitosan-organosiloxane hybrid membranes - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (BiomaterialsBiomaterials, 2005)
Chitosan-silicate hybrids were synthesized using γ- glycidoxypropyltrimethoxysilane (GPSM) as the agent for cross-linking the chitosan chains. CaCl 2 was introduced in the hybrids in expectation that it would improve cell adhesion and differentiation of the hybrid surfaces. Fourier-transform infrared (FT-IR) spectroscopy and 29Si CP-MAS NMR spectroscopy were used to analyze the structures of the hybrids. Cytocompatibility of the hybrids was investigated in terms of proliferation of an osteoblastic cell line, MG63. The adhesion and proliferation of the osteoblastic cells cultured on the surface of a chitosan-GPSM hybrid without calcium were similar to those on a control culture plate, and were better than those on a chitosan membrane. The ALP activity of the cells cultured on this hybrid was higher than that on the chitosan membrane. Contrary to expectations, the incorporation of calcium ions into the hybrids did not improve cell attachment and proliferation on their surfaces. © 2004 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 55Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2004.02.056PubMed ID: 15276356Language of Original Document: EnglishCorrespondence Address: Hayakawa, S.; Biomaterial Laboratory, Faculty of Engineering, Okayama Univ., 3-1-1 T., Okayama-shi, Japan; email: satoshi@cc.okayama-u.ac.jpChemicals/CAS: calcium chloride, 10043-52-4; Alkaline Phosphatase, EC 3.1.3.1; Biocompatible Materials; Calcium, 7440-70-2; Chitosan, 9012-76-4; Cross-Linking Reagents; gamma-glycidoxypropyltrimethoxysilane, 2530-83-8; Membranes, Artificial; Neoplasm Proteins; SilanesManufacturers: Chisso, Japan; Kasei, JapanReferences: Park, J.B., Lakes, R.S., (1992) Biomaterials An Introduction, pp. 223-234. , New York: Plenum Press;Wise, D.L., (2000) Biomaterials and Bioengineering Handbook, pp. 556-559. , New York: Marcel Dekker; Lee, Y.K., Mooney, J.D., Hydrogels for tissue engineering (2001) Chem Rev, 101, pp. 1869-1879; Park, S.N., Park, J.C., Kim, H.O., Song, M.J., Suh, H., Characterization of porous collagen/hyaluronic acid scaffold modified by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide cross-linking (2002) Biomaterials, 23, pp. 1205-1212; Kuo, C.K., Ma, P.X., Ionically crosslinked alginate hydrogels as scaffolds for tissue engineering: Part 1 Structure, gelation rate and mechanical properties (2001) Biomaterials, 22, pp. 511-521; Widmer, M.S., Gupta, P.K., Lu, L., Meszlenyi, R.K., Evans, G.R.D., Brandt, K., Savel, T., Mikos, A.G., Manufacture of porous biodegradable polymer conduits by an extrusion process for guided tissue regeneration (1998) Biomaterials, 19, pp. 1945-1955; Wang, Y.C., Lin, M.C., Wang, D.M., Hsieh, H.J., Fabrication of a novel porous PGA-chitosan hybrid matrix for tissue engineering (2003) Biomaterials, 24, pp. 1047-1057; Domard, A., Rinaudo, M., Preparation and characterization of fully deacetylated chitosan (1983) Int J Biol Macromol, 5, pp. 49-52; Chandy, T., Sharma, P.C., Chitosan - As a biomaterial (1990) Biomater Artif Cells Artif Organo, 18, pp. 1-24; Ueno, H., Yamada, H., Tanaka, I., Kaba, N., Matsuura, M., Okumura, M., Kadosawa, T., Fujinaga, T., Accelerating effects of chitosan for healing at early phase of experimental open wound in dogs (1999) Biomaterials, 20, pp. 1407-1414; Varma, H.K., Yokogawa, Y., Espinosa, F.F., Kawamoto, Y., Nishizawa, K., Nagata, F., Kameyama, T., Porous calcium phosphate coating over phosphorylated chitosan film by a biomimetic method (1999) Biomaterials, 20, pp. 879-884; Xiao, C., Gao, S., Wang, H., Zhang, L., Blend films from chitosan and konjac glucomannan solutions (2000) J Appl Polym Sci, 76, pp. 509-515; Chung, T.W., Lu, Y.F., Wang, S.S., Lin, Y.S., Chu, S.H., Growth of human endothelial cells on photochemically grafted Gly-Arg-Gly-Asp (GRGD) chitosans (2002) Biomaterials, 23, pp. 4803-4809; Muzzareli, R.A.A., Mattioli-Belmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., Stimulatory effect on bone formation exerted by a modified chitosan (1994) Biomaterials, 15, pp. 1075-1081; Park, Y.J., Lee, M.Y., Lee, J.Y., Seol, Y.J., Chung, C.P., Lee, S.J., Controlled release of platelet-derived growth factor-BB from chondroitin sulfate-chitosan sponge for guided bone regeneration (2000) J Controlled Rel, 67, pp. 385-394; Suzuki, T., Mizushima, Y., Umeda, T., Ohashi, R., Further biocompatibility testing of silica-chitosan complex membrane in the production of tissue plasminogen activator by epithelial and fibroblast cells (1999) J Biosci Bioeng, 88, pp. 194-199; Yamaguchi, I., Itoh, S., Suzuki, M., Sakane, M., Osaka, A., Tanaka, J., The chitosan prepared from crab tendon I: The characterization and the mechanical properties (2003) Biomaterials, 24, pp. 2031-2036; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J Controlled Rel, 78, pp. 187-197; Kawamura, Y., Mitsuhashi, M., Tanibe, H., Yoshida, H., Adsorption of metal ions on polyaminated highly porous chelating resin (1993) Ing Eng Chem Res, 32, pp. 386-391; Jameela, S.R., Jayakrishnan, A., Glutaraldehyde crosslinked chitosan as a long acting biodegradable drug delivery vehicle: Studies on the in vitro release of mitoxantrone and in vivo degradation of microspheres in rat muscle (1995) Biomaterials, 16, pp. 769-775; Speer, D.P., Chvapil, M., Eskelson, C.D., Ulreich, J., Biological effects of residual glutaraldehyde in glutaraldehyde-tanned collagen biomaterials (1980) J Biomed Mater Res, 14, pp. 753-764; Nishi, C., Nakajima, N., Ikada, Y., In vitro evaluation of cytotoxicity of diepoxy compounds used for biomaterial modification (1995) J Biomed Mater Res, 29, pp. 829-834; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Sol-gel preparation and in vitro deposition of apatite on porous gelatin-siloxane hybrids (2001) J Non-Cryst Solid, 285, pp. 116-122; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Novel approach to fabricate porous gelatin-siloxane hybrids for bone tissue engineering (2002) Biomaterials, 23, pp. 4765-4773; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethylthiazol-2- yl)-2,5-diphenyltetrazolium bromide (MTT) subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Incorporation of Ca 2+ ions in gelatin-siloxane hybrids through a sol-gel process (2001) J Ceramic Soc Japan, 109, pp. 403-408; Yamaguchi, I., Tokuchi, K., Fukuzaki, H., Koyama, Y., Takakuda, K., Monma, H., Tanaka, J., Preparation and microstructure analysis of chitosan/hydroxyapatite nanocomposites (2001) J Biomed Mater Res, 55, pp. 20-27; Hench, L.L., Ethridge, E.C., (1982) Biomaterias An Interfacial Approach, p. 10. , New York: Academic Press; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Martin, T.J., Findlay, D.M., Heath, J.K., Ng, K.W., Osteoblasts: Differentiation and function (1993) Handbook of Experimental Pharmacology, pp. 149-183. , J.R. Mundy, & T.J. Martin. Berlin: Springer; Aubin, J.E., Turksen, K., Heersch, J.N.M., Osteoblastic cell lineage (1993) Cellular and Molecular Biology of Bone, pp. 1-45. , M. Noda. Tokyo: Academic Press Inc; Anderson, S.I., Downes, S., Perry, C.C., Caballero, A.M., Evaluation of the osteoblast response to a silica gel in vitro (1998) J Mater Sci: Mater Med, 9, pp. 731-735; Rhee, S.H., Hwang, M., Si, H.J., Choi, J.Y., Biological activities of osteoblasts on poly(methyl methacrylate)/silica hybrid containing calcium salt (2003) Biomaterials, 24, pp. 901-906; Kalonji, E.E., Denis, I., Lieberherr, M., Pointillart, A., Effects of extracellular calcium on the proliferation and differentiation of porcine osteoblasts in vitro (1998) Cell Tissue Res, 292, pp. 163-171; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma-sprayed coatings (2000) Biomaterials, 21, pp. 813-820; Bilezikian, J.P., Raisz, L.G., Rodan, G.A., (2002) Principles of Bone Biology, p. 1325. , New York: Academic Press
Keywords: alkaline phosphatase; article; artificial membrane; Biocompatibility; Biocompatible Materials; Bone Neoplasms; Calcium; calcium chloride; cell adhesion; Cell attachments; Cell culture; cell differentiation; Cell Division; Cell Line, Tumor; chitosan; chitosan derivative; controlled study; cross linking; Cross-Linking Reagents; Crosslinking; Cytocompatibility; Fourier transform infrared spectroscopy; human; human cell; Humans; hybrid; infrared spectroscopy; Magnetic Resonance Spectroscopy; materials testing; Membranes, Artificial; MG63 osteoblastic cells; Microscopy, Electron, Scanning; Neoplasm Proteins; Nuclear magnetic resonance spectroscopy; Organic-inorganic hybrid; osteoblast; Osteoblasts; Osteosarcoma; priority journal; Silanes; Silicates; siloxane; Spectroscopy, Fourier Transform Infrared; structure analysis; surface property; Synthesis (chemical); wettability; γ-Glycidoxypropyltrimethoxysilane (GPSM)

In vitro degradation behavior of a novel bioresorbable composite material based on PLA and a soluble CaP glass - Navarro, M.; Ginebra, M.P.; Planell, J.A.; Barrias, C.C.; Barbosa, M.A. (Acta BiomaterialiaActa Biomater., 2005)
Poly(α-hydroxy acids), and in particular polylactic acid (PLA), are nowadays amongst the most used bioabsorbable materials. However, this polymer may not meet some application requirements due to inadequate mechanical properties and or its degradation characteristics. A possible strategy to tackle this problem is the incorporation of an inorganic phase into the polymeric matrix. In this work a new fully biodegradable composite material made with PLA and calcium phosphate soluble glass particles has been developed. The behaviour of the PLA/ glass composite has been analysed during its degradation in simulated physiological conditions by means of weight loss, molecular weight and thermal properties analysis and electron microscopy observation. The results showed that the incorporation of phosphate glass particles into the polymer significantly accelerated the degradation of the PLA and induced the formation of calcium phosphate precipitates at the composite surface. © 2005 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 24Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2005.03.004PubMed ID: 16701822Language of Original Document: EnglishCorrespondence Address: Ginebra, M.P.; Reference Centre for Bioengineering of Catalonia (CREBEC), Department of Materials Science, Universitat Politècnica de Catalunya, Av. Diagonal 647, 08028 Barcelona, Spain; email: maria.pau.ginebra@upc.esChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; polylactic acid, 26100-51-6; Bone Substitutes; calcium phosphate, 10103-46-5; Calcium Phosphates; Lactic Acid, 50-21-5; poly(lactic acid), 26100-51-6; PolymersManufacturers: Purac, NetherlandsReferences: Rokkanen, P., Bioabsorbable fixation in orthopaedic surgery and traumatology (2000) Biomaterials, 21, pp. 2607-2613;Middleton, J.C., Tipton, A.J., Synthetic biodegradable polymers as orthopedic devices (2000) Biomaterials, 21 (23), pp. 2335-2346; Adriano, K.P., Daniels, A.U., Smutz, W.P., Wyatt, R.W.B., Heller, J., Preliminary biocompatibility screening of several biodegradable phosphate fiber reinforced polymers (1993) J Appl Biomater, 4, pp. 1-12; Nazhat, S.N., Kellomaki, M., Tormala, P., Tanner, K.E., Bonfield, W., Dynamic mechanical characterization of biodegradable composites of hydroxyapatite and polylactides (2001) J Biomed Mater Res, 58 (4), pp. 335-343; Dupraz, A.M.P., de Wijn, J.R., v.d. Meer, S.A.T., de Groot, K., Characterization of silane-treated hydroxyapatite powders for use as filler in biodegradable composites (1996) J Biomed Mater Res, 30, pp. 231-238; Kasuga, T., Maeda, H., Kato, K., Nogami, M., Hata, K.-I., Ueda, M., Preparation of poly (lactic acid) composites containing calcium carbonate (vaterite) (2003) Biomaterials, 24, pp. 3247-3253; Ylinen, P., Suuronen, R., Taurio, R., Tormala, P., Rokkanen, P., Use of hydroxylapatite/polymer-composite in facial bone augmentation. An experimental study (2002) Int J Oral Maxillofac Surg, 31 (4), pp. 405-409; Lu, H.H., El-Amin, S., Scott, K., Laurencin, C., Three-dimensional, bioactive, biodegradable, polymer-bioactive glass composite scaffolds with improved mechanical properties support collagen synthesis and mineralization of human osteoblast-like cells in vitro (2003) J Biomed Mater Res, 64 A, pp. 465-474; Navarro, M., Ginebra, M.P., Planell, J.A., Zeppetelli, S., Ambrosio, L., Development and cell response of a new biodegradable composite scaffold for guided bone regeneration (2004) J Mater Sci-Mater Med, 15 (4), pp. 419-422; Klein, C.P.A.T., Driessen, A.A., Degroot, K., Vandenhooff, A., Biodegradation behavior of various calcium-phosphate materials in bone tissue (1983) J Biomed Mater Res, 17 (5), pp. 769-784; Denissen, H.W., Degroot, K., Makkes, P.C., Vandenhooff, A., Klopper, P.J., Tissue-response to dense apatite implants in rats (1980) J Biomed Mater Res, 14 (6), pp. 713-721; Navarro, M., Ginebra, M.P., Clement, J., Martinez, S., Avila, G., Planell, J.A., Physicochemical degradation of titania-stabilized soluble phosphate glasses for medical applications (2003) J Am Ceram Soc, 86 (8), pp. 1345-1352; Navarro, M., Ginebra, M.P., Planell, J.A., Cellular response to calcium phosphate glasses with controlled solubility (2003) J Biomed Mater Res Part A, 67 A (3), pp. 1009-1015; Li, S.M., Hydrolytic degradation characteristics of aliphatic polyesters derived from lactic and glycolic acids (1999) J Biomed Mater Res, 48 (3), pp. 342-353; Burg, K.J.L., Shalaby, S.W., Physicochemical changes in degrading polylactide films (1997) J Biomat Sci Polym, 9 (1), pp. 15-29; Li, S.M., Vert, M., Hydrolytic degradation of coral/poly(DL-lactic acid) bioresorbable material (1996) J Biomat Sci-Polym, 7 (9), pp. 817-827; Agrawal, C.M., Athanasiou, K.A., Technique to control pH in vicinity of biodegrading PLA-PGA implants (1997) J Biomed Mater Res, 38 (2), pp. 105-114; Kokubo, T., Kushitani, H., Sakka, S., Kitsugi, T., Yamamuro, T., Solutions able to reproduce invivo surface-structure changes in bioactive glass-ceramic A-W3 (1990) J Biomed Mater Res, 24 (6), pp. 721-734; Fischer, E.W., Sterzel, H.J., Wegner, G., Investigation of the structure of solution grown crystals of lactide copolymers by means of chemical reactions (1973) Kolloid-Zeitschrift and Z Polymere, 251, pp. 978-990; Driessens, F.C.M., Fernandez, E., Ginebra, M.P., Boltong, M.G., Planell, J.A., Calcium phosphates and ceramic bone cements vs. acrylic cements (1997) Anales Quimica, 93 (1), pp. S38-S43; Berry, E.E., Baddiel, C.B., Some assignments in infra-red spectrum of octacalcium phosphate (1967) Spectrochim Acta Part A - Mol Spectrosc A, 23 (6), p. 1781; Fowler, B.O., Moreno, E.C., Brown, W.E., Infra-red spectra of hydroxyapatite octacalcium phosphate and pyrolysed octacalcium phosphate (1966) Arch Oral Biol, 11 (5), p. 477; Elliot, J.C., General chemistry of the calcium orthophosphates. Structure and chemistry of the apatites and other calcium orthophosphates (1994), pp. 1-61. , Elsevier AmsterdamStutman, J.M., Termine, J.D., Posner, A.S., Vibrational spectra and structure of phosphate ion in some calcium phosphates (1965) Trans New York Acad Sci, 27 (6), p. 669; Cornilsen, B.C., Condrate, R.A., The vibrational spectra of β-Ca 2P 2 O 7 and γ-Ca 2P 2O 7 (1979) J Inorg Nucl Chem, 41, pp. 602-605; Cornilsen, B.C., Condrate, R.A., Vibrational spectra of α-alkaline earth pyrophosphates (1978) J Solid State Chem, 23, pp. 375-382; de Fátima Gimenez, I., Mazali, I.O., Alves, O.L., Application of Raman spectroscopy to the study of the phase composition of phosphate based glass-ceramics (2001) J Phys Chem Solids, 62, pp. 1251-1255; Kasuga, T., Abe, Y., Calcium phosphate invert glasses with soda and titania (1999) J Non-Cryst Solids, 243, pp. 70-74; Imai, Y., Fukuzawa, A., Watanabe, M., Effect of blending tricalcium phosphate on hydrolytic degradation of a block polyester containing poly(L-lactic acid) segment (1999) J Biomat Sci - Polym, 10 (7), pp. 773-786; Huffman, K.R., Casey, D.J., Effect of carboxyl end groups on hydrolysis of polyglycolic acid (1985) J Polym Sci Part A - Polym Chem, 23 (7), pp. 1939-1954; Termine, J.D., Eanes, E.D., Comparative chemistry of amorphous and apatitic calcium phosphate preparations (1972) Calcif Tissue Res, 10 (3), p. 171; Zahidi, E., Lebugle, A., Bonel, G., On a new class of biomaterials for osseous or dental prosthesis (1985) Bull Soc Chim France, (4), pp. 523-527; Eanes, E.D., Gillesse, I.H., Gosner, A.S., Intermediate states in precipitation of hydroxyapatite (1965) Nature, 208 (5008), p. 365; Tung, M.S., Brown, W.E., An intermediate state in hydrolysis of amorphous calcium-phosphate (1983) Calcif Tissue Int, 35 (6), pp. 783-790; Wuthier, R.E., Rice, G.S., Wallace, J.E.B., Weaver, R.L., Legeros, R.Z., Eanes, E.D., Invitro precipitation of calcium-phosphate under intracellular conditions - Formation of brushite from an amorphous precursor in the absence of Atp (1985) Calcif Tissue Int, 37 (4), pp. 401-410; Root, M.J., Inhibition of the amorphous calcium-phosphate phase-transformation reaction by polyphosphates and metal-ions (1990) Calcif Tissue Int, 47 (2), pp. 112-116;
Keywords: Absorbable Implants; Absorption; article; biodegradability; Biodegradable composite; Biomimetic materials; Body fluids; Bone Regeneration; Bone Substitutes; calcium phosphate; Calcium phosphates; composite material; Degradation; electron microscopy; glass; In vitro degradation; in vitro study; Lactic Acid; materials testing; molecular weight; observation; Phosphate glass; polylactic acid; Polymers; precipitation; priority journal; reaction analysis; simulation; Solubility; Surface Properties; surface property; temperature; weight reduction

Inflammatory cell recruitment and adhesion to methyl-terminated self-assembled monolayers: Effect of implantation time - Barbosa, J.N.; Barbosa, M.A.; Águas, A.P. (Microscopy Research and TechniqueMicrosc. Res. Tech., 2005)
The contribution of methyl groups in implant-triggered inflammation was investigated in vivo using self-assembled monolayers (SAMs) of alkanethiols on gold. The CH 3-coated implants were inserted in an air-pouch cavity induced in BALB/c mice. The in situ inflammatory response was monitored 24, 48, and 72 hours later. Inflammatory cells recovered from the air pouches were counted and observed by light microscopy. The cellularity of the implant surfaces was defined by scanning electron microscopy (SEM). In comparison with gold implants, the CH 3-coated SAMs recruited a significantly higher number of inflammatory cells. Polymorphonuclear leukocytes (PMN) were more numerous than mononuclear cells (Mo) in the exudates recovered from the air pouches with CH 3-coated SAMs. The opposite PMN/Mo proportion was observed in air pouches of the two control groups (mice receiving gold implants or sham-operated animals). A low density of adherent cells was seen on CH 3-coated implants, with no significant quantitative differences during the time course of the study. In contrast, the gold-coated surfaces were covered with numerous cells during all of the 3 days of the inflammation. In conclusion, implants with CH 3 surfaces are likely to induce PMN-dominated local acute inflammation but these surfaces are not associated with a significant adherence of leukocytes to the implant. © 2005 Wiley-Liss, Inc.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: MRTEEdoi: 10.1002/jemt.20141PubMed ID: 15816035Language of Original Document: EnglishCorrespondence Address: Barbosa, J.N.; INEB, Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ibmc.up.ptChemicals/CAS: gold, 7440-57-5; thiol derivative, 13940-21-1; Coated Materials, Biocompatible; Gold, 7440-57-5References: Anderson, J.M., Biological responses to materials (2001) Annu Rev Mater Res, 31, pp. 81-110;Babensee, J.E., Anderson, J.M., Mclntire, L.V., Mikos, A.G., Host response to tissue engineered devices (1998) Adv Drug Deliv Rev, 33, pp. 111-139; Barbosa, J.N., Barbosa, M.A., Águas, A.P., Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethiolates on gold (2004) Biomaterials, 25, pp. 2557-2563; Castro, A.G., Esaguy, N., Macedo, P.M., Águas, A.P., Silva, M.T., Live but not heat-killed mycobacteria cause rapid chemotaxis of large numbers of eosinophils in vivo and are ingested by the attracted granulocytes (1991) Infect Immun, 59, pp. 3009-3014; Gelb, H., Schumacher, H.R., Cuckler, J., Ducheyne, P., Baker, D.G., In vivo inflammatory response to polymethylmethacrylate particulate debris: Effect of size, morphology, and surface area (1994) J Orthop Res, 12, pp. 83-92; Hooper, K.A., Nickolas, T.L., Yurkow, E.J., Kohn, J., Laskin, D., Characterization of the inflammatory response to biomaterials using a rodent air pouch model (2000) J Biomed Mater Res, 50, pp. 365-374; Hu, W., Eaton, J.W., Tang, L., Molecular basis of biomaterial-mediated foreign body reactions (2001) Blood, 98, pp. 1231-1238; Isaji, M., Momose, Y., Naito, J., Enhancement of inflammatory reactions in a non-immunological air pouch model in rats (1989) Br J Exp Pathol, 70, pp. 705-716; Källtorp, M., Oblogina, S., Jacobsson, S., Karlsson, A., Tengvall, P., Thomsen, P., In vivo cell recruitment, cytokine release and chemiluminescence response at gold, and thiol functionalized surfaces (1999) Biomaterials, 20, pp. 2123-2137; Kao, W.J., Evaluation of leukocyte adhesion on polyurethanes: The effects of shear stress and blood proteins (2000) Biomaterials, 21, pp. 2295-2303; Kao, W.J., Liu, Y., Gundloori, R., Li, J., Lee, D., Einerson, N., Burmania, J., Stevens, K., Engineering endogenous inflammatory cells as delivery vehicles (2002) J Control Release, 78, pp. 219-233; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51, pp. 413-423; Lindblad, M., Lestelius, M., Johansson, A., Tengvall, P., Thomsen, P., Cell and soft tissue interactions with methyl- and hydroxyl-terminated alkane thiols on gols surfaces (1997) Biomaterials, 18, pp. 1059-1068; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27, pp. 1463-1476; Martins, M.C.L., Naeemi, E., Ratner, B.D., Barbosa, M.A., Albumin adsorption on cibacron blue F3G-A immobilized onto oligo(ethylene glycol)-terminated self-assembled monolayers (2003) J Mater Sci Mater Med, 14, pp. 945-954; Mrksich, M., Using self-assembled monolayers to understand the biomaterials interface (1997) Curr Opin Colloid Int Sci, 2, pp. 83-88; Mrkisich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Mrksich, M., Whitesides, G.M., Interactions of SAMs with proteins (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-57; Pan, S., Castner, D.G., Ratner, B.D., Multitechnique surface characterization of derivatization efficiences for hydroxyl-terminated self-assembled monolayers (1998) Langmuir, 14, pp. 3545-3550; Prime, K.L., Whitesides, G.M., Self assembled organic monolayers: Model systems for studying the adsorption of proteins at surfaces (1991) Science, 252, pp. 1164-1167; Sedwick, A.D., Sin, Y.M., Edwards, J.C., Willoughby, D.A., Increased inflammatory reactivity in newly formed lining tissue (1983) J Pathol, 141, pp. 483-495; Tang, L., Eaton, J.W., Mechanisms of acute inflammatory response to biomaterials (1994) Cells and Materials, 4, pp. 429-436; Tang, L., Eaton, J.W., Inflammatory responses to biomaterials (1995) Am J Clin Pathol, 103, pp. 466-471; Tang, L., Ugarova, T.P., Plow, E.F., Eaton, J.W., Molecular determinants of acute inflammatory responses to biomaterials (1997) J Clin Invest, 97, pp. 1329-1334; Tang, L., Jennings, T.A., Eaton, J.W., Mast cells mediate acute inflammatory responses to implanted biomaterials (1998) Proc Natl Acad Sci, 95, pp. 8841-8846; Tang, L., Liu, L., Elwing, H.B., Complement activation and inflammation triggered by model biomaterial surfaces (1998) J Biomed Mater Res, 41, pp. 333-340; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Tomczok, J., Sliwa-Tomczok, W., Klein, C.L., Van Kooten, T.G., Kirkpatrick, C.J., Biomaterial-induced alterations of human neutrophils under fluid shear stress: Scanning electron microscopical study in vitro (1996) Biomaterials, 17, pp. 1359-1367; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Wooley, P.H., Mayton, L., Sud, S., Nasser, S., Synergistic inflammatory responses to metallic and polymeric particles in the murine air pouch model of aseptic loosening (1996) Arthritis Rheum, 39, pp. 175-183; Wooley, P.H., Morren, R., Andary, J., Sud, S., Yang, S., Mayton, L., Markel, D., Nasser, S., Inflammatory responses to orthopaedic biomaterials in the murine air pouch (2002) Biomaterials, 23, pp. 517-526; Yun, J.K., DeFife, K., Colton, E., Stack, S., Azeez, A., Cahalan, L., Verhoeven, M., Anderson, J.M., Human monocyte/macrophage adhesion and cytokine production on surface-modified poly (tetrafluoroethylene/hexafluoropropylene) polymers with and without protein preadsorption (1995) J Biomed Mater Res, 29, pp. 257-268
Keywords: Air-pouch model; animal experiment; animal model; Animalia; Animals; article; biomaterial; cell adhesion; Cell Count; cell density; cell surface; Cell-surface interactions; Coated Materials, Biocompatible; Contact angle; controlled study; gold; implantation; Implants, Experimental; Inflammation; inflammatory cell; Inflammatory responses; leukocyte adherence; Leukocytes; male; materials testing; methyl group; Mice; Microscopy, Electron, Scanning; mononuclear cell; mouse; neutrophil; nonhuman; priority journal; Scanning electron microscopy; Self-assembled monolayers; Surface Properties; thiol derivative; Time Factors

Recombinant glucocerebrosidase uptake by Gaucher disease human osteoblast culture model - Lamghari, M.; Barrias, C.C.; Sá Miranda, C.; Barbosa, M.A. (Blood Cells, Molecules, and DiseasesBlood Cells Mol. Dis., 2005)
Bone lesions are a major cause of morbidity in Gaucher disease (GD) type I. Enzyme replacement therapy (ERT) has been successful in treating many symptoms of type I GD but skeletal response lags behind. Local exogenous glucocerebrosidase supplementation in bone lesions via a drug delivery system may overcome this limitation. Although local enzyme supplementation aims to target lipid-engorged macrophages (Gaucher Cells) in bone compartment, enzyme uptake by osteoblasts is not excluded. To investigate the ability of human osteoblasts to internalize recombinant glucocerebrosidase (rGCR), we have used an artificial GD human osteoblasts cell culture system. MG63 human osteoblasts were treated with conduritol B epoxide (CBE) to induce complete and prolonged inhibition of endogenous glucocerebrosidase activity of cells. rGCR uptake by glucocerebrosidase-inactivated osteoblasts was examined using 125I-radiolabelling, Western blot analysis and measurement of glucocerebrosidase activity. Analysis of radiolabeled enzyme uptake by CBE treated osteoblasts showed 67.9% of internalized protein in cell extract. Enzyme internalization was also observed by Western blot analysis where the amount of mature form of glucocerebrosidase protein recognized by the glucocerebrosidase antibody was increased following the administrations of rGCR. Moreover, enzymatic activity measurement showed 23.9% of glucocerebrosidase activity of control cells. The rGCR internalization by MG63 osteoblast seems to be partially mediated by mannose receptors. These data provide evidence that MG63 human osteoblasts are able to internalize rGCR. © 2005 Elsevier Inc. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BCMDFdoi: 10.1016/j.bcmd.2005.07.009PubMed ID: 16125984Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, R. Campo Alegre 823, 4150-180 Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: conduritol b epoxide, 6090-95-5; imiglucerase, 154248-97-2; iodine 125, 14158-31-7, 22822-81-7; conduritol epoxide, 6090-95-5; Glucosylceramidase, EC 3.2.1.45; Inositol, 6917-35-7; Recombinant ProteinsTradenames: cerezyme, GenzymeManufacturers: GenzymeReferences: Beutler, E., Grabowski, G., Gaucher disease (1995) The Metabolic and Molecular Bases of Inherited Disease, 2, pp. 2641-2661. , C.R. Scriber A.L. Beaudet W.S. Sly 7th ed. McGraw-Hill New York, NY;Beutler, E., Enzyme replacement in Gaucher disease (2004) PLoS Med., 1 (2), p. 21; Elstein, D., Itzchaki, M., Mankin, H., Skeletal involvement in Gaucher's disease (1997) Ballière's Clin. Haematol., 10 (4), pp. 793-815; Wenstrup, R.J., Roca-Espiau, M., Weinreb, N.J., Bembi, B., Skeletal aspects of Gaucher disease: A review (2002) Br. J. Radiol., 75 (1 SUPPL.), pp. 2-A12; Barranger, J.A., O'Rourke, E., Lessons learned from the development of enzyme therapy for Gaucher disease (2001) J. Inherited Metab. Dis., 24 (2 SUPPL.), pp. 89-96; Zimran, A., Elstein, D., Levy-Lahad, E., Zevin, S., Hadas-Halpern, I., Bar-Ziv, Y., Foldes, J., Abrahamov, A., Replacement therapy with imiglucerase for type 1 Gaucher's disease (1995) Lancet, 345 (8963), pp. 1479-1480; Barton, N.W., Brady, R.O., Dambrosia, J.M., Di Bisceglie, A.M., Doppelt, S.H., Hill, S.C., Mankin, H.J., Argoff, C.E., Replacement therapy for inherited enzyme deficiency-macrophage-targeted glucocerebrosidase for Gaucher's disease (1991) N. Engl. J. Med., 324 (21), pp. 1464-1470; Barton, N.W., Furbish, F.S., Murray, G.J., Garfield, M., Brady, R.O., Therapeutic response to intravenous infusions of glucocerebrosidase in a patient with Gaucher disease (1990) Proc. Natl. Acad. Sci. U. S. A., 87 (5), pp. 1913-1916; Friedman, B., Vaddi, K., Preston, C., Mahon, E., Cataldo, J.R., McPherson, J.M., A comparison of the pharmacological properties of carbohydrate remodeled recombinant and placental-derived beta-glucocerebrosidase: Implications for clinical efficacy in treatment of Gaucher disease (1999) Blood, 93, pp. 2807-2816; Grabowski, G.A., Leslie, N., Wenstrup, R., Enzyme therapy for Gaucher disease: The first 5 years (1998) Blood Rev., 12 (2), pp. 115-133; Samuel, R., Katz, K., Papapoulos, S.E., Yosipovitch, Z., Zaizov, R., Liberman, U.A., Aminohydroxy propylidene bisphosphonate (APD) treatment improves the clinical skeletal manifestations of Gaucher's disease (1994) Pediatrics, 94 (3), pp. 385-389; Shiffmann, R., Mankin, H., Dambrosia, J.M., Xavier, R.J., Kreps, C., Hills, S.C., Barton, N.W., Rosenthal, D.I., Decreased bone density in splenectomized Gaucher patients receiving enzyme replacement therapy (2002) Blood Cells Mol. Dis., 28, pp. 288-296; (1993) Iodine-125, a Guide to Radioiodination, p. 64. , Amersham Life Science; Barrias, C.C., Martins, M.C.L., Sá Miranda, M.C., Barbosa, M.A., Adsorption of a therapeutic enzyme to self-assembled monolayers: Effect of surface chemistry and solution pH on the amount and activity of adsorbed enzyme (2005) Biomaterials, 26, pp. 2695-2704; Laemmli, U.K., (1970) Nature, 227, pp. 680-685; Sá Miranda, M.C., Aerts, J.M., Pinto, R., Fontes, A., Lacerda, L.W., Van Weely, S., Barranger, J., Tager, J.M., Activity of glucocerebrosidase in extracts of different cell types from type 1 Gaucher disease patients (1990) Clin. Genet., 38, pp. 218-227; Barrias, C.C., Lamghari, M., Granja, P.L., Sá Miranda, C., Barbosa, M.A., Biological evaluation of calcium alginate microspheres as a vehicle for the localised delivery of a therapeutic enzyme (2005) J. Biomed. Mater. Res.; Barrias, C.C., Ribeiro, C.C., Lamghari, M., Sá Miranda, C., Barbosa, M.A., Proliferation, activity, and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres (2005) J. Biomed. Mater. Res., 72 A (1), pp. 57-66; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25 (18), pp. 4363-4373; Das, P.K., Murray, G.J., Gal, A.E., Barranger, J.A., Glucocerebrosidase deficiency and lysosomal storage of glucocerebroside induced in cultured macrophages (1987) Exp. Cell Res., 168 (2), pp. 463-474; Pelled, D., Shogomori, H., Futerman, A.H., The increased sensitivity of neurons with elevated glucocerebroside to neurotoxic agents can be reversed by imiglucerase (2000) J. Inherited Metab. Dis., 23 (2), pp. 175-184; Hanley, K., Jiang, Y., Holleran, W.M., Elias, P.M., Williams, M.L., Feingold, K.R., Glucosylceramide metabolism is regulated during normal and hormonally stimulated epidermal barrier development in the rat (1997) J. Lipid Res., 38 (3), pp. 576-584; Marshall, J., McEachern, K.A., Kyros, J.A., Nietupski, J.B., Budzinski, T., Ziegler, R.J., Yew, N.S., Cheng, S.H., Demonstration of feasibility of in vivo gene therapy for Gaucher disease using a chemically induced mouse model (2002) Mol. Ther., 6 (2), pp. 179-189; Mistry, P.K., Wraight, E.P., Cox, T.M., Therapeutic delivery of proteins to macrophages: Implications for treatment of Gaucher's disease (1996) Lancet, 348 (9041), pp. 1555-1559; Xu, Y.H., Ponce, E., Sun, Y., Leonova, T., Bove, K., Witte, D., Grabowski, G.A., Turnover and distribution of intravenously administered mannose-terminated human acid beta-glucosidase in murine and human tissues (1996) Pediatr. Res., 39 (2), pp. 313-322; Beutler, E., Kuhl, W., Vaughan, L.M., Failure of alglucerase infused into Gaucher disease patients to localize in marrow macrophages (1995) Mol. Med., 1, pp. 320-324; Sato, Y., Beutler, E., Binding, internalization, and degradation of mannose-terminated glucocerebrosidase by macrophages (1993) J. Clin. Invest., 91, pp. 1909-1917; Schueler, U., Kaneski, C., Murray, G., Sandhoff, K., Brady, R.O., Uptake of mannose-terminal glucocerebrosidase in cultured human cholinergic and dopaminergic neuron cell lines (2002) Neurochem. Res., 27 (4), pp. 325-330; Furbish, F.S., Steer, C.J., Barranger, J.A., Jones, E.A., Brady, R.O., The uptake of native and desialylated glucocerebrosidase by rat hepatocytes and Kupffer cells (1978) Biochem. Biophys. Res. Commun., 81, pp. 1047-1053; Furbish, F.S., Steer, C.J., Krett, N.L., Barranger, J.A., Uptake and distribution of placental glucocerebrosidase in rat hepatic cells and effects of sequential deglycosylation (1981) Biochim. Biophys. Acta, 673, pp. 425-434; East, L., Isacke, C.M., The mannose receptor family (2002) Biochim. Biophys. Acta., 1572, pp. 364-386; East, L., Rushton, S., Taylor, M.E., Isack, C.M., Characterization of sugar binding by the mannose receptor family member, Endo180 (2002) J. Biol. Chem., 277 (52), pp. 50469-50475; Engelholm, L.H., Nielsen, B.S., Netzel-Arnett, S., Solberg, H., Chen, X.D., Lopez Garcia, J.M., Lopez-Otin, C., Bugge, T.H., The urokinase plasminogen activator receptor-associated protein/endo180 is coexpressed with its interaction partners urokinase plasminogen activator receptor and matrix metalloprotease-13 during osteogenesis (2001) Lab. Invest., 81, pp. 1403-1414; Bailey, L., Wienke, D., Howard, M., Knauper, V., Isacke, C.M., Murphy, G., Investigation of the role of Endo180/urokinase-type plasminogen activator receptor-associated protein as a collagenase 3 (matrix metalloproteinase 13) receptor (2002) Biochem. J., 1 (363 PART 1), pp. 67-72
Keywords: article; Cell culture; cell extract; Cells, Cultured; conduritol b epoxide; controlled study; drug activity; drug uptake; enzyme activity; enzyme antibody; Enzyme inhibition; Enzyme uptake; epoxide; Gaucher disease; Glucocerebrosidase; Glucosylceramidase; human; human cell; Humans; imiglucerase; Inositol; internalization; iodine 125; isotope labeling; mannose receptor; osteoblast; Osteoblasts; priority journal; Recombinant Proteins; unclassified drug; Western blotting

TiO 2 type influences fibronectin adsorption - Sousa, S.R.; Moradas-Ferreira, P.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Human fibronectin (FN) plays a key role in the biointegration of implants as the success depends on adsorption of proteins like FN [1]. Indeed FN can be an intermediary between the biomaterial surface and cells. The adsorption of human fibronectin (FN) on commercially pure titanium with a titanium oxide layer formed in a H 2O 2 solution (TiO 2 cp) and TiO 2 sputtered on Si (TiO 2 sp) was studied. Adsorption isotherms and the work of adhesion were assessed by wettability studies, X-ray photoelectron spectroscopy (XPS), and by radiolabelling of FN with 125I, 125I-FN. Exchangeability of bound FN by free FN, was also evaluated by the radiolabelling technique. Contact angle determinations have shown that FN displays higher affinity for the TiO 2 cp surface than for the TiO 2 sp. As expected from the surface free energy values, the work of adhesion of FN is higher for the TiO 2 cp substrate, the more hydrophilic one, and lower for the TiO 2 sp substrate, the more hydrophobic one. The adsorption isotherms were evaluated by two different techniques: radiolabelling of FN ( 125I-FN) and XPS. TiO 2 cp adsorbs more FN than the TiO 2 sp surfaces as shown by the radiolabelling data. FN molecules are also more strongly attached to the former surface as indicated by the work of adhesion and by the exchangeability studies. Results using 125I-FN also suggests that FN adsorbs as a multilayer for FN concentrations in solution higher than 100 μg/mL. © 2005 Springer Science + Business Media, Inc.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-005-4725-4Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; INEB, Instituto de Engenharia Biomédica, Lab. Biomateriais, R. do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ssousa@ibmc.up.ptChemicals/CAS: fibronectin, 86088-83-7; titanium dioxide, 1317-70-0, 1317-80-2, 13463-67-7, 51745-87-0; titanium, 7440-32-6; hydrogen peroxide, 7722-84-1; iodine 125, 14158-31-7, 22822-81-7; Fibronectins; Solutions; titanium dioxide, 13463-67-7; Titanium, 7440-32-6References: Horbett, T.A., (1994) Colloids and Surfaces B: Biointerfaces, 2, p. 225;Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J Biomed Mater Res., 75 A, p. 387; Johnson, K.J., Sage, H., Briscoe, G., Erickson, H.P., (1999) J. Biol. Chem., 274, p. 15473; Bergkvist, M., Carlsson, J., Oscarsson, S., (2003) J. Biomed. Mater. Res. Part A., 64 A, p. 349; Ugarova, T.P., Zamarron, C., Veklich, Y., Bowditch, R.D., Ginsberg, M.H., Weisel, J.W., Plow, E.F., (1995) Biochemistry, 34, p. 4457; Sukenik, C.N., Balachander, N., Culp, L.A., Lewandowska, K., Merritt, K., (1990) J. Biomed. Mater. Res., 24, p. 1307; Sousa, S.R., Moradas- Ferreira, P., Melo, L.V., Saramago, B., Barbosa, M.A., (2004) Langmuir, 20, p. 9745; Gehanno, V., Freitas, P.P., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Soares, J.C., Silva, M.F., (1999) IEEE Trans. Magn., 35, p. 4361; (2003) Iodine-125, A Guide to Radioiodination Techniques - Amersham Life Science, p. 64. , Amersham International plc, Amersham Place, Little Chalfont, Bucks, HP7 9NA, England, 199; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., (2001) J. Biomed. Mater. Res., 55, p. 45; Yu, X.J., Brash, J.L., (1993) Test Procedures for the Blood Compatibility of Biomaterials, Dordrecht, p. 287. , edited by S. Dawids (Kluwer Academic Publishers, Dordrecht); Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., (1985) Analytical Biochemistry, 150, p. 76; Lindberg, B., Maripuu, R., Siegbahn, K., Larsson, R., Golander, C.G., Eriksson, J.C., (1983) J. Colloid Interface Sci., 95, p. 308; Auditore, A., Satriano, C., Coscia, U., Ambrosone, G., Parisi, V., Marletta, G., (2002) Biomolecular Engineering, 19, p. 85; Miller, R., Treppo, S., Voigt, A., Zingg, W., Neumann, A.W., (1993) Colloids and Surfaces, 69, p. 203; Serro, A.P.V., Fernandes, A.C., Saramago, B.D.V., (1997) Colloids and Surfaces A-Physicochemical and Engineering Aspects, 125, p. 209; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., (1997) Langmuir, 13, p. 3404; Matsuura, T., Hosokawa, R., Okamoto, K., Kimoto, T., Akagawa, Y., (2000) Biomaterials, 21, p. 1121; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., (2001) Biomaterials, 22, p. 3105; Do Serro, A., Fernandes, A.C., Saramago, B.D.V., Norde, W., (1999) J. Biomed. Mater. Res., 46, p. 376; Norde, W., Anusiem, A.C.I., (1992) Colloids and Surfaces, 66, p. 73; Rouxhet, L., Duhoux, F., Borecky, O., Legras, R., Schneider, Y.J., (1998) Journal of Biomaterials Science-Polymer Edition, 9, p. 1279; Norde, W., (1986) Advances in Colloid and Interface Science, 25, p. 267; Tamada, Y., Ikada, Y., (1993) J. Colloid Interface Sci., 155, p. 334
Keywords: Adsorption; adsorption kinetics; article; binding affinity; Biointegration; Biomaterials; Cells; chemistry; conference paper; Contact angles; Fibronectin; Fibronectins; human; Human fibronectin (FN); Humans; hydrogen peroxide; hydrophilicity; hydrophobicity; Implants (surgical); iodine 125; isotherm; Isotherms; isotope labeling; physical chemistry; priority journal; protein binding; Proteins; Radiolabelling; solution and solubility; Solutions; surface property; Titanium; Titanium dioxide; wettability; X ray photoelectron spectroscopy

Calcium phosphate-alginate microspheres as enzyme delivery matrices - Ribeiro, C.C.; Barrias, C.C.; Barbosa, M.A. (BiomaterialsBiomaterials, 2004)
The present study concerns the preparation and initial characterisation of novel calcium titanium phosphate-alginate (CTP-alginate) and hydroxyapatite-alginate (HAp-alginate) microspheres, which are intended to be used as enzyme delivery matrices and bone regeneration templates. Microspheres were prepared using different concentrations of polymer solution (1% and 3%w/v) and different ceramic-to-polymer solution ratios (0.1, 0.2 and 0.4w/w). Ceramic powders were characterised using X-ray diffraction, laser granulometry, Brunauer, Emmel and Teller (BET) method for the determination of surface area, zeta potential and Fourier transform infrared spectroscopy (FT-IR). Alginate was characterised using high performance size exclusion chromatography. The methodology followed in this investigation enabled the preparation of homogeneous microspheres with a uniform size. Studies on the immobilisation and release of the therapeutic enzyme glucocerebrosidase, employed in the treatment of Gaucher disease, were also performed. The enzyme was incorporated into the ceramic-alginate matrix before gel formation in two different ways: pre-adsorbed onto the ceramic particles or dispersed in the polymeric matrix. The two strategies resulted in distinct release profiles. Slow release was obtained after adsorption of the enzyme to the ceramic powders, prior to preparation of the microspheres. An initial fast release was achieved when the enzyme and the ceramic particles were dispersed in the alginate solution before producing the microspheres. The latter profile is very similar to that of alginate microspheres. The different patterns of enzyme release increase the range of possible applications of the system investigated in this work. © 2003 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 92Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2003.11.028PubMed ID: 15046927Language of Original Document: EnglishCorrespondence Address: Ribeiro, C.C.; Laboratório de Biomateriais, INEB, Inst. de Engenharia Biomédica, Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: cribeiro@ineb.up.ptChemicals/CAS: Alginates; alginic acid, 9005-32-7; calcium phosphate, 10103-46-5; Calcium Phosphates; Drug Carriers; Enzymes, Immobilized; Glucosylceramidase, EC 3.2.1.45; Glucuronic Acid, 576-37-4; Hexuronic Acids; PowdersReferences: Griffith, L.G., Naughton, G., Tissue engineering: Current challenges and expanding opportunities (2002) Science, 295, pp. 1009-1014;Hench, L.L., Polak, J.M., Third-generation biomedical materials (2002) Science, 295, pp. 1014-1017; Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomaterials, 21, pp. 2405-2412; Laurencin, C.T., Lu, H.H., Polymer-ceramic composites for bone tissue engineering (2000) Bone Engineering, pp. 463-472. , J.E. Davies. Toronto, Canada: EM Squared Inc; Gauthier, O., Bouler -., J.M., Weiss, P., Bosco, J., Daculsi, G., Aguado, E., Kinetic study of bone ingrowth and ceramic resorption associated with the implantation of different injectable calcium-phosphate bone substitutes (1999) J Biomed Mater Res, 47, pp. 28-35; Dupraz, A., Delecrin, J., Moreau, A., Pilet, P., Passut, N., Long term bone response to particulate injectable ceramic (1998) J Biomed Mater Res, 42, pp. 368-375; Grimandi, G., Weiss, P., Millot, F., Daculsi, G., In vitro evaluation of a new injectable calcium phosphate material (1998) J Biomed Mater Res, 39, pp. 660-666; Gauthier, O., Boix, D., Grimandi, G., Aguado, E., Bouler, J.M., Weiss, P., Daculsi, G., A new injectable phosphate biomaterial for immediate bone filling of extraction sockets: A preliminary study in dogs (1999) J Periodontol, 70, pp. 375-383; Peter, S.J., Nolley, J.A., Widmer, M.S., Mervin, J.E., Yaszemski, M.J., Yasko, A.W., Engel, P.S., Mikos, A.G., In vitro degradation of a poly (propylene fumarate)/β-tricalcium phosphate composite orthopedic scaffold (1997) Tissue Eng, 3, pp. 207-215; Sims, C.D., Butler, P.E.M., Casanova, R., Lee, B.T., Randolph, M.A., Lee, W.P.A., Vacant, C.A., Yamremchuk, M.J., Injectable cartilage using polyethylene oxide polymer substrates (1996) Plast Reconstr Surg, 98, pp. 843-850; Suggs, L.J., Shive, M.S., Garcia, C.A., Anderson, J.M., Mikos, A.G., In vitro cytotoxicity and in vivo biocompalibility of poly (propylene fumarate-co-ethylene glycol) hydrogels (1999) J Biomed Mater Res, 46, pp. 22-32; Suggs, L.J., Krishnan, R.S., Garcia, C.A., Peter, S.J., Anderson, J.M., Mikos, A.G., In vitro and in vivo degradation of poly(propylene fumarate-co-ethylene glycol) hydrogels (1998) J Biomed Mater Res, 42, pp. 312-320; Frazier, D.D., Lathi, V.K., Gerhart, T.N., Hayes, W.C., Ex vivo degradation of a poly (propylene glycol-fumarate) biodegradable particulate bone cement (1997) J Biomed Mater Res, 35, pp. 383-389; Kharas, G.B., Kamanetsky, M., Simantirakis, J., Beinlich, K.C., Rizzo, A.-.M.T., Caywood, G.A., Watson, K., Synthesis and characterization of fumarate-based polyesters for use in bioresorbable bone cement composites (1997) J Appl Polym Sci, 66, pp. 1123-1137; Paige, K.T., Cima, L.G., Yaremchuck, M.J., Vacant, J.P., Vacant, C.A., Injectable cartilage (1995) Plast Reconstr Surg, 96, pp. 1390-1400; Paige, K.T., Cima, L.G., Yaremchuck, M.J., Vacant, J.P., Vacant, C.A., De novo cartilage generation using calcium-alginate-chondrocyte constructs (1996) Plast Reconstr Surg, 97, pp. 168-180; Kulseng, B., Skjak-Braek, G., Ryan, L., Andersson, A., King, A., Faxvaag, A., Espevik, T., Transplantation of alginate microcapsules (1999) Transplantation, 67, pp. 978-984; Martinetti, R., Dolcini, L., Ravaglioli, A., Krajewski, A., Mangano, C., Experimental study on hydroxyapatite/N-carboxymethyl chitosan fillers (1997) Bioceramics, 10, pp. 503-506. , L. Sedel, & C. Rey. Oxford, UK: Elsevier; Maruyama, M., Ito, M., In vitro properties of a chitosan-bonded self hardening paste with hydroxyapatite granules (1996) J Biomed Mater Res, 32, pp. 527-532; Dupraz, A., Nguyen, T.P., Richard, M., Daculsi, G., Passuti, N., Influence of a cellulosic ether carrier on the structure of biphasic calcium phosphate ceramic particles in an injectable composite material (1999) Biomaterials, 20, pp. 663-673; Ribeiro, C.C., Ma, B., Calcium-Titanium-Phosphate: A Potential Material to Be Used in the Biomedical Field, , submitted for publication; Alamo, J., Chemistry and properties of solids with NZP skeleton (1993) Solid State Ionics, 63, pp. 547-561; Takahiro, S., Motohiro, T., Hosono, H., Application of a microporous glass-ceramic with a skeleton of CaTi 4(PO 4) 6 to carriers for immobilization of enzymes (1991) J Ferment Bioeng, 72, pp. 384-391; Gross, U., Muller-Mai, C., Voigt, C., Mesgarian, M., Berger, G., Ploska, U., Tissue response in femur of rabbits after implantation of a new calcium titanium phosphate composition (2001) Key Eng Mater, 192-195, pp. 383-386; Otsuka, M., Matsuda, Y., Fox, J.L., Higuchi, W.I., Yu, D., Wong, J., A novel skeletal drug delivery system for anti bacterial drugs using self-setting hydroxyapatite cement (1990) Chem Pharm Bull (Tokyo), 38, pp. 3500-3502; Guicheux, J., Grimandi, G., Trecant, M., Faivre, A., Takahashi, S., Apatite as a carrier for growth hormone: In vitro characterization of loading and release (1997) J Biomed Mater Res, 34, pp. 165-170; Gombotz, W.R., Wee, S.F., Protein release from alginate matrices (1998) Adv Drug Deliv Rev, 31, pp. 267-285; Eiselt, P., Yeh, J., Latvala, R.K., Shea, L.D., Mooney, D.J., Porous carriers for biomedical applications based on alginate hydrogels (2000) Biomaterials, 21, pp. 1921-1927; Alsberg, V., Anderson, K., Albeiruti, A., Franceshi, R.T., Mooney, D.J., Cell interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80, pp. 2025-2029; Smidsrod, O., Draget, K.I., Chemistry and physical properties of alginates (1996) Carbohyd Europe, 14, pp. 6-13; Sivakumar, M., Manjubala, I., Panduranga Rao, K., Preparation, characterization and in-vitro release of gentamicin from coralline hydroxyapatite-chitosan composite microspheres (2002) Carbohyd Pol, 49, pp. 281-288; Qiu, Q.Q., Ducheyne, P., Ayyaswamy, P.S., New bioactive, degradable composite microspheres as tissue engineering substrates (2000) J Biomed Mater Res, 52, pp. 66-76; Hsu, F.Y., Chueh -., S.C., Wang, Y.J., Microspheres of hydroxyapatite/reconstituted collagen as supports for osteoblast cell growth (1999) Biomaterials, 20, pp. 1931-1936; Grabowski, G.A., Leslie, N., Wenstrup, R., Enzyme therapy for Gaucher disease: The first 5 years (1998) Blood Rev, 12, pp. 115-133; Xu, Y.H., Ponce, E., Sun, Y., Leonova, T., Bove, K., Witte, D., Grabowski, G.A., Turnover and distribution of intravenously administered mannose-terminated human acid beta glucosidase in murine and human tissues (1996) Pediatr Res, 39, pp. 313-322; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., Effect of chemical composition on hydrophobicity and zeta-potential of plasma spayed HA/CaO-P 2O 5 glass coatings (2001) Biomaterials, 22, pp. 3105-3112; Lopes, M.A., Monteiro, F.L., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential measurements of glass reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Dupuy, B., Arien, A., Minnot, A.P., FT-IR membranes made with alginate/polylysine complexes. Variations with mannuronic or guluronic content of the polysaccharides. Art Cells, Blood Subs (1994) Immob Biotech, 20, pp. 71-82; Peters, T., (1996) All about Albumin: Biochemistry, Genetics and Medical Applications, , San Diego, CA: Academic Press Inc; Nakanishi, K., Sakiyama, T., Imamura, K., On the adsorption of proteins on solid surfaces, a common but very complicated phenomenon (2001) J Biosci Bioeng, 91, pp. 233-244
Keywords: Absorption; Adsorption; Alginate; Alginates; article; Biomaterials; Bone; Calcium Compounds; Calcium phosphates; Calcium titanium phosphate; calcium titanium phosphate alginate; ceramics; Drug Carriers; Drug Delivery Systems; Enzyme delivery; Enzyme-delivery; Enzymes; Enzymes, Immobilized; Fourier transform infrared spectroscopy; Glucosylceramidase; Glucuronic Acid; Hexuronic Acids; High performance liquid chromatography; hydroxyapatite; hydroxyapatite alginate; laser; methodology; microsphere; Microspheres; Molecular Conformation; Particle Size; Powders; priority journal; surface property; unclassified drug; X ray diffraction

Fabrication of alternating polycation and albumin multilayer coating onto stainless steel by electrostatic layer-by-layer adsorption - Ji, J.; Tan, Q.; Fan, D.-Z.; Sun, F.-Y.; Barbosa, M.A.; Shen, J. (Colloids and Surfaces B: BiointerfacesColloids Surf. B Biointerfaces, 2004)
Multilayer films consisting of polyethylenimine (PEI) and albumin were successfully prepared on biomedical 316L stainless steel surface via electrostatic self-assembly of the PEI and albumin. The process of electrostatic self-assembly of PEI/albumin was monitored by 125I radiolabeling, electrochemical impedance spectroscopy (EIS) and atomic force microscopy (AFM). The EIS data revealed that the multilayer coating was stable in Tris-HCl (pH 7.35) buffer solution for 21 days. 125I radiolabeling experiments indicated that less than 10% albumin was eluted by PBS in 45 days. Static platelet adhesion experiments indicated that the PEI/albumin deposited on stainless steel could resist platelet adhesion effectively. Such an easy processing and shape-independent method may have good potential for surface modification of cardiovascular devices. © 2004 Elsevier B.V. All rights reserved.
Cited By (since 1996): 17Export Date: 21 November 2012Source: ScopusCODEN: CSBBEdoi: 10.1016/j.colsurfb.2003.12.015PubMed ID: 15261073Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: iodine 125, 14158-31-7, 22822-81-7; polyethyleneimine, 74913-72-7; stainless steel, 12597-68-1; Albumins; Lipid Bilayers; Polyamines; polycations; Polyethyleneimine, 9002-98-6; Stainless Steel, 12597-68-1References: Thomann, U.I., Uggowitzer, P.J., (2000) Wear, 239, p. 48;Cheatham, J., (2001) Prog. Pediat. Cardiol., 14, p. 95; Donachie, M., (1998) Adv. Mater. Process, 154, p. 63; Bertrand, P., (2000) Macromol. Rapid Commun., 21, p. 319; Ulman, A., (1996) Chem. Rev., 96, p. 1533; Sano, M., Lvov, Y., Kunitake, T., (1996) Annu. Rev. Mater. Sci., 26, p. 153; Laschewsky, A., (1997) Eur. Chem. Chronicle (ECC), 2, p. 13; Decher, G., (1997) Science, 277, p. 1232; Yoo, D., Seimei, S., Michael, F.R., (1998) Macromolecules, 31, p. 4309; Picart, C., Lavalle, Ph., Hubert, P., Cuisinier, F.J.G., Decher, G., Schaaf, P., Voegel, J.-C., (2001) Langmuir, 17, p. 7414; Houska, M., Brynda, E., (1997) J. Colloid Interf. Sci., 188, p. 243; Brynda, E., Houska, M., (1996) J. Colloid Interf. Sci., 183, p. 18; Lu, C.H., Luo, C.Q., Cao, W.X., (2002) Colloids Surf. B: Biointerf., 25, p. 19; Keogh, R.J., Eaton, J.W., (1994) J. Lab. Clin. Med., 124, p. 537; Munro, M.S., (1981) Trans. Am. Soc. Artif. Intern. Organs, 27, p. 499; Brynda, E., Houska, M., (2000) Protein Architecture: Interfacing Molecular Assemblies and Immobilization, pp. 251-285. , Y. Lvov, H. Moehwald (Eds.), Marcel Dekker, New York; Keogh, J.R., Velander, F.F., Eaton, W., (1992) J. Biomed. Mater. Res., 26, p. 441; Ji, J., Feng, L., Barbosa, M.A., (2001) Biomaterials, 22, p. 3015; Lopez, G.P., Ratner, B.D., Tidwell, C.D., Haycox, C.L., Rapoza, R.J., Horbett, T.A., (1992) J. Biomed. Mater. Res., 26, p. 415; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of Biocompatibility Tests, 2, pp. 183-214. , D.F. Williams (Ed.), CRC Press, Harcover; Cheng, Z., Cheng, L., Dong, S., Yang, X., (2001) J. Electrochem. Soc., 148, p. 227; Lima, J., (2001) J. Biomed. Mater. Res., 55, p. 45; Iodine-125, a Guide to Radioiodination Techniques (1993) Amersham Life Sci., p. 64; Takahara, A., Jo, N.J., Kajiyama, T., (1989) J. Biomater. Sci. Polym. Ed., 1, p. 17; Haynes, C.A., Norde, W., (1994) Colloids Surf. B: Biointerf., 2, p. 517; Ladam, G., Gergely, C., Senger, B., Decher, G., Voegel, J.C., Schaaf, P., Cuisinier, F.J.G., (2000) Biomacromolecules, 1, p. 674; Ladam, G., Schaaf, P., Cuisinier, F.J.G., Decher, G., Voegel, J.C., (2001) Langmuir, 17, p. 878; Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., (2000) Macromol. Rapid Commun., 21, p. 319
Keywords: Adhesion; Adsorption; Albumin; Albumins; article; Atomic force microscopy; Cardiovascular devices; Chemical modification; Coatings; Electric Impedance; Electric Potential; Electrochemical impedance spectroscopy; electrochemistry; Electrons; Electrostatics; film coating; iodine 125; isotope labeling; Layer-by-layer; Lipid Bilayers; Microscopy, Atomic Force; Multilayers; Nonthrombogenic; pH effects; Platelet Adhesiveness; Polyamines; polycation; Polycations; Polyethyleneimine; priority journal; Proteins; Self assembly; Spectroscopy; Spectrum Analysis; Stainless steel; Surface modification; Surface Properties; surface property; Surface treatment; thrombocyte adhesion

Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethiolates on gold - Barbosa, J.N.; Barbosa, M.A.A.; Águas, A.P. (BiomaterialsBiomaterials, 2004)
The acute inflammatory response and the adhesion of cells to self-assembled monolayers (SAMs) of well-defined surface chemistry was studied in vivo using a rodent air-pouch model of inflammation. SAMs with three different terminal functional groups (OH, COOH and CH 3) were implanted in subcutaneous air pouches induced in BALB/c mice. After 24h, inflammatory cells were recovered from the air pouches and the implants were removed and prepared for observation by scanning electron microscopy (SEM). The implants coated with OH and CH 3, were found to cause the highest recruitment of inflammatory cells into the subcutaneous pouches. Polymorphonuclear neutrophils (PMNs) leukocytes predominated over mononuclear cells in inflammatory exudates of SAMs-coated implants, the opposite being found in uncoated implants (controls). CH 3-coated implants induced the highest number of inflammatory cells and also the largest percentage of PMNs seen in the subcutaneous pouches. Control and OH-covered implants presented the higher densities of attached inflammatory cells detected by SEM. In contrast, the CH 3-coated implants showed a very low density of cells adherent to the implant surface. We conclude that the chemical nature and the degree of hydrophobicity of the surface of implants modulate both the local acute inflammatory reaction and the adhesion of leukocytes. © 2003 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2003.09.047PubMed ID: 14751741Language of Original Document: EnglishCorrespondence Address: Barbosa, J.N.; INEB - Inst. de Engenharia Biomedica, Laboratório de Biomaterials, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ibmc.up.ptChemicals/CAS: Gold, 7440-57-5; Sulfhydryl CompoundsReferences: Tang, L., Jiang, W., Welty, S.E., The participation of P- and E-selectins on biomaterial-mediated tissue responses (2002) J Biomed Mater Res, 62, pp. 471-477;Thomsen, P., Gretzer, C., Macrophage interactions with modified material surfaces (2001) Curr Opin Solid State Mater Sci, 5, pp. 163-176; Kao, W.J., Liu, Y., Gundloori, R., Li, J., Lee, D., Einerson, N., Burmania, J., Stevens, K., Engineering endogenous inflammatory cells as delivery vehicles (2002) J Control Release, 78, pp. 219-233; Anderson, J.M., Mechanisms of inflammation and infection with implanted devices (1993) Cardiovasc Pathol, 2, pp. 33S-41S; Anderson, J.M., Inflammatory response to implants (1988) ASAIO J, 11, pp. 101-107; Babensee, J.E., Anderson, J.M., McLntire, L.V., Mikos, A.G., Host response to tissue engineered devices (1998) Adv Drug Deliver Rev, 33, pp. 111-139; Mrksich, M., Whitesides, G.M., Interactions of SAMs with proteins (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-57; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Mrksich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Nuzzo, R.G., Allara, D.L., Adsorption of biofunctional organic dissulfides on gold surfaces (1983) J Am Chem Soc, 105, pp. 4481-4483; Pan, S., Castner, D.G., Ratner, B.D., Multitechnique surface characterization of derivatization efficiencies for hydroxyl-terminated self-assembled monolayers (1998) Langmuir, 14, pp. 3545-3550; Sedwick, A.D., Sin, Y.M., Edwards, J.C., Willoughby, D.A., Increased inflammatory reactivity in newly formed lining tissue (1983) J Pathol, 141, pp. 483-495; Castro, A.G., Esaguy, N., MacEdo, P.M., Águas, A.P., Silva, M.T., Live but not heat-killed mycobacteria cause rapid chemotaxis of large numbers of eosinophils in vivo and are ingested by the attracted granulocytes (1991) Infect Immun, 59, pp. 3009-3014; Isaji, M., Momose, Y., Naito, J., Enhancement of inflammatory reactions in a non-immunological air pouch model in rats (1989) Br J Exp Pathol, 70, pp. 705-716; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51, pp. 413-423; Hooper, K.A., Nickolas, T.L., Yurkow, E.J., Kohn, J., Laskin, D., Characterization of the inflammatory response to biomaterials using a rodent air pouch model (2000) J Biomed Mater Res, 50, pp. 365-374; Wooley, P.H., Morren, R., Andary, J., Sud, S., Yang, S., Mayton, L., Markel, D., Nasser, S., Inflammatory responses to orthopaedic biomaterials in the murine air pouch (2002) Biomaterials, 23, pp. 517-526; Gelb, H., Schumacher, H.R., Cuckler, J., Ducheyne, P., Baker, D.G., In vivo inflammatory response to polymethylmethacrylate particulate debris: Effect of size, morphology, and surface area (1994) J Orthop Res, 12, pp. 83-92; Wooley, P.H., Mayton, L., Sud, S., Nasser, S., Synergistic inflammatory responses to metallic and polymeric particles in the murine air pouch model of aseptic loosening (1996) Arthritis Rheum, 39, pp. 175-183; Moore, R., Beredjiklian, P., Rhoad, R., Theiss, S., Cuckler, J., Ducheyne, P., Baker, D.G., A comparison of the inflammatory potential of particulates derived from two composite materials (1997) J Biomed Mater Res, 34, pp. 137-147; Krause, T.J., Robertson, F.M., Greco, R.S., Measurement of intracellular hydrogen peroxide induced by biomaterials implanted in a rodent air pouch (1993) J Biomed Mater Res, 27, pp. 65-69; Yang, S., Ren, W., Park, Y., Sieving, A., Hsu, S., Nasser, S., Wooley, P.H., Diverse cellular and apoptotic responses to variant shapes of UHMWPE particles in a murine model of inflammation (2002) Biomaterials, 23, pp. 3535-3543; Lindblad, M., Lestelius, M., Johansson, A., Tengvall, P., Thomsen, P., Cell and soft tissue interactions with methyl- and hydroxyl-terminated alkanethiols on gold surfaces (1997) Biomaterials, 18, pp. 1059-1068; Tengvall, P., Askendal, A., Lundsröm, I., Complement activation by 3-mercapto-1,2-propanediol immobilized on gold surfaces (1996) Biomaterials, 17, pp. 1001-1007; Liu, L., Elwing, H., Complement activation on thiol-modified gold surfaces (1996) J Biomed Mater Res, 30, pp. 535-541; Tang, L., Liu, L., Elwing, H.B., Complement activation and inflammation triggered by model biomaterial surfaces (1998) J Biomed Mater Res, 41, pp. 333-340; Källtorp, M., Oblogina, S., Jacobsson, S., Karlsson, A., Tengvall, P., Thomsen, P., In vivo cell recruitment, cytokine release and chemiluminescence response at gold, and thiol functionalized surfaces (1999) Biomaterials, 20, pp. 2123-2137; Tang, L., Ugarova, T.P., Plow, E.F., Eaton, J.W., Molecular determinants of acute inflammatory responses to biomaterials (1997) J Clin Invest, 97, pp. 1329-1334; Hu, W., Eaton, J.W., Tang, L., Molecular basis of biomaterial-mediated foreign body reactions (2001) Blood, 98, pp. 1231-1238; Silver, J.H., Hergenrother, R.W., Lin, J., Lim, F., Lin, H., Okada, T., Chaudhury, M.K., Cooper, S.L., Surface and blood-contacting properties of alkylsiloxane monolayers supported on silicone rubber (1995) J Biomed Mater Res, 29, pp. 535-548; Werthén, M., Sellborn, A., Källtorp, M., Elwing, H., Thomsen, P., In vitro study of monocyte viability during the initial adhesion to albumin- and fibrinogen-coated surfaces (2001) Biomaterials, 22, pp. 827-832; Tang, L., Eaton, J.W., Fibrin(ogen) mediates acute inflammatory responses to biomaterials (1993) J Exp Med, 178, pp. 2147-2156; Liu, L., Elwing, H., Complement activation on solid surfaces as determined by C3 deposition and hemolytic consumption (1994) J Biomed Mater Res, 28, pp. 767-773; Tengvall, P., Askendal, A., Lundstrom, I., Complement activation by IgG immobilized on methylated silicon (1996) J Biomed Mater Res, 31, pp. 305-312; Källtorp, M., Askendal, A., Thomsen, P., Tengvall, P., Ellipsometric studies in vitro on kinetics of rat complement activation (1999) J Biomed Mater Res, 44, pp. 222-225; Barbosa, J.N., Barbosa, M.A., Águas, A.P., Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces (2003) J Biomed Mater Res, 65, pp. 429-434
Keywords: Air-pouch model; alkane derivative; animal cell; animal experiment; animal model; Animals; article; Biomaterials; cell adhesion; Cell culture; cell density; cell surface; Cell-surface interactions; controlled study; exudate; gold; gold complex; hydrophobicity; implantation; Inflammation; Inflammatory responses; leukocyte; Leukocytes; male; material coating; Mice; Mice, Inbred BALB C; Microscopy, Electron, Scanning; mouse; neutrophil; nonhuman; polymorphonuclear cell; priority journal; Rodentia; Scanning electron microscopy; Self assembly; Self-assembled monolayers; Sulfhydryl Compounds; Surface chemistry; surface property

Laser surface modification of hydroxyapatite and glass-reinforced hydroxyapatite - Queiroz, A.C.; Santos, J.D.; Vilar, R.; Eugénio, S.; Monteiro, F.J. (BiomaterialsBiomaterials, 2004)
Surface treatment of materials with excimer laser radiation often results in the formation of a rough columnar or cone-shaped surface topography, which leads to a considerable increase in the surface area. As a result, the search for a non-porous bioactive material with adequate mechanical properties and a high surface to volume ratio, similar to porous materials, which could be used for drug delivery in the treatment of periodontitis, justified assessing excimer laser surface treatment to promote controlled roughning of hydroxyapatite (HA) and glass-reinforced hydroxyapatite (GR-HA). A KrF excimer laser with 248nm radiation wavelength and 30ns pulse duration was used for surface modification. The laser treatment was carried out in air, using wide ranges of radiation fluence and number of laser pulses. In order to identify the physico-chemical changes induced by the laser treatment and the column formation mechanisms in these materials, the treated surfaces were characterised by laser profilometry, scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Fourier transform infra-red spectroscopy (FTIR). Laser processing induced the formation of a surface topography consisting of cone-shaped features. The constitution of the surface layer was also modified, as revealed by FTIR, XPS and XRD. This work has shown that laser surface modification increases the surface area of HA and GR-HA and is a promising technique to increase the reactivity and drug delivery capability of both materials. © 2003 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2003.11.054PubMed ID: 15120506Language of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; INEB-Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180, Porto, Portugal; email: aqueiroz@ineb.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; Biocompatible Materials; Durapatite, 1306-06-5; Macromolecular SubstancesReferences: Krejci, C.B., Bissada, N.F., Farah, C., Greenwell, H., Clinical evaluation of porous and nonporous hydroxyapatite in the treatment of human periodontal bony defects (1987) J Periodontol, 58, pp. 521-528;Seymour, R.A., Heasman, P.A., MacGregor, I.D.M., The pathogenesis of periodontal disease (1992) Drugs, Diseases, and the Periodontium, pp. 1-10. , I.D.M. MacGregor. Oxford: Oxford University Press; Systemic antibiotics in periodontics (1996) J Periodontol, 67, pp. 831-838; Steinberg, D., Friedman, M., Soskolne, A., Sela, M.N., A new degradable controlled release device for treatment of periodontal disease: In vitro release study (1990) J Periodontol, 61, pp. 393-398; Soskolne, W.A., Heasman, H.A., Stabholz, A., Smart, G.J., Palmer, M., Flashner, M., Newman, H.N., Sustained local delivery of chlorhexidine in the treatment of periodontitis: A multi-center study (1997) J Periodontol, 68, pp. 32-38; Prado Da Silva, M.H., Lemos, A.F., Gibson, I.R., Ferreira, J.M.F., Santos, J.D., Porous glass reinforced hydroxyapatite materials produced with different organic additives (2002) J Non-Cryst Solids, 304, pp. 286-292; Barinov, S.M., Baschenko, Y.V., Application of ceramic composits as implants: Result and problem (1992) Bioceramics and the Human Body, pp. 206-210. , A. Krajewski. UK: Elsevier Science Publishers; Koshino, T., Murase, T., Takagi, T., Saito, T., New bone formation around porous hydroxyapatite wedge implanted in opening wedge high tibial osteotomy in patients with osteoarthritis (2001) Biomaterials, 22, pp. 1579-1582; Nishihara, K., Studies on peri-root tissue formation around new type artificial root made of dense hydroxyapatite (1993) Clin Mater, 12, pp. 159-167; Chang, B., Lee, C., Hong, K., Youn, H., Ryu, H., Chung, S., Park, K., Osteoconduction at porous hydroxyapatite with various pore configurations (2000) Biomaterials, 21, pp. 1291-1298; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tensions, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Santos, J.D., Silva, P.L., Knowles, J.C., Talal, S., Monteiro, F.J., Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O and MgO (1996) J Mater Sci: Mater Med, 7, pp. 187-189; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of effects of glass on response of osteosarcoma cells to plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings (1999) J Biomed Mater Res, 47, pp. 603-611; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P2O5 Glass hydroxyapatite double-layer plasma-sprayed coating: In vitro bioactivity evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., Adsorption and release of sodium ampicillin from hydroxyapatite and glass-reinforced hydroxyapatite composites (2001) Biomaterials, 22, pp. 1393-1400; Clèries, L., Fernández-Pradas, J.M., Morenza, J.L., Behaviour in simulated body fluid of calcium phosphate coating obtained by laser ablation (2000) Biomaterials, 21, pp. 1861-1865; D'Alession, L., Teghil, R., Zaccardo, I., Ferro, D., Marotta, V., Pulsed laser ablation and deposition of bioactive glass as coating material for biomedical applications (1999) Appl Surf Sci, 138-139, pp. 527-532; Fernández-Pradas, J.M., Clèries, L., Serra, P., Sardin, G., Morenza, J.L., Evolution of the depositon rate during pulsed laser deposition of hydroxyapatite coatings and its relation with target morphology (2001) Appl Phys a, 72, pp. 613-618; Zeng, H., Lacefield, W.R., XPS, EDX and FTIR analysis of pulsed laser deposited calcium phosphate bioceramic coatings: The effects of various process parameters (2000) Biomaterials, 21, pp. 23-30; Serra, P., Fernández-Pradas, J.M., Sardin, G., Morenza, J.L., Interaction effects of an excimer laser beam with hydroxyapatite targets (1997) Appl Surf Sci, 109-110, pp. 384-388; Serra, P., Morenza, J.L., Fluence dependence of hydroxyapatite laser ablantion plumes (1998) Thin Solid Films, 335, pp. 43-48; Foltyn, S.R., Dye, R.C., Ott, K.C., Peterson, E., Hubbard, K.M., Hutchinson, W., Muenchausen, R.E., Wu, X.D., Target modification in the excimer laser deposition of YBa 2Cu 3O 7-x thin films (1991) Appl Phys Lett, 59, pp. 594-596; Oliveira, V., Conde, O., Vilar, R., UV laser micromachining of ceramic materials: Formation of columnar topographies (2001) Adv Eng Mater, 3, pp. 75-81; Ricci, J.L., Alexander, H., Laser microtexturing of implant surfaces for enhanced tissue integration (2001) Key Eng Mater, 198-199, pp. 179-202; Khor, K.A., Vreeling, A., Dong, Z.L., Cheang, P., Laser treatment of plasma sprayed HA coatings (1999) Mater Sci Eng a, 266, pp. 1-7; Sobol, E.M., (1995) Phase transformations and ablation in laser-treated solids, , New York: Wiley; Underwood, E.E., (1970) Quantitative Stereology, , Reading: Addison-Wesley;; Underwood, E.E., Banerji, K., Quantitative fractography (1987) ASM-Metals Handbook, 12; Rey, C., Shimizu, M., Collins, B., Glimcher, M.J., Resolution enhanced Fourier transform infrared spectroscopy study of the environment of phosphate ion in the early deposits of a solid phase calcium phosphate in bone and enamel and their evolution with age: Investigations in the ν 4 PO 4 3- domain (1990) Calcif Tissue Int, 46, pp. 384-394; Rey, C., Shimizu, M., Collins, B., Glimcher, M.J., Resolution enhanced Fourier transform infrared spectroscopy study of the environment of phosphate ion in the early deposits of a solid phase calcium phosphate in bone and enamel and their evolution with age: Investigations in the ν 3 PO 4 3- domain (1991) Calcif Tissue Int, 49, pp. 383-388; Elliott, J.C., Structure and chemistry of apatites and other calcium orthophosphates (1994) Inorganic Chemistry, 18, p. 50. , Elliott J.C. Amsterdam: Elsevier Science; Dupraz, A., Nguyen, T.P., Richard, M., Dalcusi, G., Passuti, N., Influence of a cellulosic ether carrier on the structure of biphasic calcium phosphate ceramic particles in an injectable composite material (1999) Biomaterials, 20, pp. 663-673; Franke, R., Chassé, Th., Streubel, P., Meisel, A., Auger parameters and relaxation energies of phosphorus in solid compounds (1991) J Electron Spectrosc Relat Phemon, 56, pp. 381-388; Heitz, J., Pedarning, J.D., Bauerle, D., Petzow, G., Excimer laser ablation and micro-patterning of ceramic Si 3N 4 (1997) Appl Phys a, 65, pp. 259-261; Foltyn, S.R., Surface modification of materials by cumulative laser irradiation (1994) Pulsed Laser Deposition of Thin Films, pp. 89-113. , D.B. Chrisey, & G.K. Hubler. New York: Wiley; Lappalainen, J., Frantti, J., Lanto, V., Surface structure and particulate generation in Pb 0.97Nd 0.02(Zr 0.55Ti 0.45)O 3 ablation targets during pulsed laser deposition (1999) J Am Cer Soc, 82, pp. 889-896; Óbrien, T.P., Lawler, J.F., Lunney, J.G., Blau, W.J., The effect of laser fluence on the ablation and deposition of YBa 2Cu 3O 7 (1992) Mater Sci Eng, 13, pp. 9-13; Man, H.C., Zhang, X.M., Yue, T.M., Lau, W.S., Excimer-laser surface modification of engineering ceramics for adhesive bonding (1997) J Mater Proc Techn, 66, pp. 123-129; Sánchez, F., Morenza, J.L., Trtik, V., Characterization of the progressive growth of columns by excimer laser irradiation of silicon (1999) Appl Phys Lett, 75, pp. 3303-3305; Pedraza, A., Fowlkes, J.D., Lowndes, D.H., Self organized silicon microcolumns arrays generated by pulsed laser irradiation (1999) Appl Phys a, 69, pp. 731-S734; Usoskin, A., Freyhardt, H.C., Krebs, H.U., Influence of light scattering on the development of laser induced ridge-cone structure on target surfaces (1999) Appl Phys a, 69, pp. 823-S826
Keywords: article; Biocompatible Materials; Biomaterials; drug delivery system; Durapatite; Excimer laser; Excimer lasers; Fourier transform infrared spectroscopy; FTIR; glass; hydroxyapatite; infrared spectroscopy; laser; Lasers; Macromolecular Substances; materials testing; Molecular Conformation; Non-porous bioactive materials; periodontitis; physical chemistry; porosity; priority journal; Profilometry; Radiation Dosage; Reinforcement; Scanning electron microscopy; Surface area; Surface modification; Surface Properties; Surface treatment; topography; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; XPS; XRD

A model for educational simulation of infant cardiovascular physiology - Goodwin, J.A.; van Meurs, W.L.; Sá Couto, C.D.; Beneken, J.E.W.; Graves, S.A. (Anesthesia and AnalgesiaAnesth. Analg., 2004)
Full-body patient simulators provide the technology and the environment necessary for excellent clinical education while eliminating risk to the patient. The extension of simulator-based training into management of basic and critical situations in complex patient populations is natural. We describe the derivation of an infant cardiovascular model through the redefinition of a complete set of parameters for an existing adult model. Specifically, we document a stepwise parameter estimation process, explicit simplifying assumptions, and sources for these parameters. The simulated vital signs are within the target hemodynamic variables, and the simulated systemic arterial pressure wave form and left ventricular pressure volume loop are realistic. The system reacts appropriately to blood loss, and incorporation of aortic stenosis is straightforward. This infant cardiovascular model can form the basis for screen-based educational simulations. The model is also an essential step in attaining a full-body, model-driven infant simulator.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: AACRAdoi: 10.1213/01.ANE.0000134797.52793.AFPubMed ID: 15562049Language of Original Document: EnglishCorrespondence Address: Goodwin, J.A.; Nemours Children's C., 807 Children's Way, Jacksonville, FL 32207, United States; email: jgoodwin@nemours.orgReferences: Good, M.L., Gravenstein, J.S., Training for safety in an anesthesia simulator (1993) Semin Anesth, 12, pp. 235-250;Gaba, D.M., DeAnda, A., The response of anesthesia trainees to simulated critical incidents (1989) Anesth Analg, 68, pp. 444-451; Howard, S.K., Gaba, D.M., Fish, K.J., Anesthesia crisis resource management training: Teaching anesthesiologists to handle critical incidents (1992) Aviat Space Environ Med, 63, pp. 763-770; Euliano, T.Y., Caton, D., Van Meurs, W., Good, M.L., Modeling obstetric cardiovascular physiology on a full-scale patient simulator (1997) J Clin Monit, 13, pp. 293-297; Halamek, L.P., Kaegi, D.M., Gaba, D.M., Time for a new paradigm in pediatric medical education: Teaching neonatal resuscitation in a simulated delivery room environment (2000) Pediatrics, 106, pp. E45; Beneken, J.E.W., (1965) A Mathematical Approach to Cardiovascular Function: The Uncontrolled Human System, , [PhD thesis]. Medisch Fysisch Institut TNO, Utrecht, The Netherlands; Beneken, J.E.W., DeWit, B., A physical approach to hemodynamic aspects of the human cardiovascular system (1967) Physical Bases of Circulatory Transport: Regulation and Exchange, pp. 1-45. , Reeve EB, Guyton AC, eds. Philadelphia: Saunders; Wesseling, K.H., Settels, J.J., Baromodulation explains short-term blood pressure variability (1985) Psychophysiology of Cardiovascular Control, pp. 69-97. , Orlebeke JF, Mulder G, van Doornen LJP, eds. New York: Plenum Press; Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324; Pruitt, A.W., Gersony, W.M., The cardiovascular system (1992) Nelson Textbook of Pediatrics. 14th Ed., pp. 1125-1227. , Behrman RE, ed. Philadelphia: Saunders; Gregory, G.A., Monitoring during surgery (1994) Pediatric Anesthesia, pp. 261-279. , Gregory GA, ed. New York: Churchill Livingstone; Graham Jr., T.P., Jarmakani, M.M., Evaluation of ventricular function in infants and children (1971) Pediatr Clin North Am, 18, pp. 1109-1132; Wodey, E., Plady, P., Copin, C., Comparative hemodynamic depression of sevoflurane versus halothane in infants (1997) Anesthesiology, 87, pp. 795-800; Suga, H., Sagawa, K., Shoukas, A.A., Load independence of the instantaneous pressure-volume ratio of the canine left ventricle and effects of epinephrine and heart rate on the ratio (1973) Circ Res, 2, pp. 314-322; Ten Voorde, B., (1992) Modeling the Baroreflex: A System Analysis Approach, , [PhD thesis]. Vakgroep Medische Fysica, Amsterdam, The Netherlands; Cunningham, M.D., Bedside pulmonary function testing of infants (1990) Essentials of Pediatric Intensive Care, pp. 878-883. , Levin DL, Morriss FC, eds. St. Louis: Quality Medical; Strafford, M.A., Cardiovascular physiology (1996) Smith's Anesthesia for Infants and Children, pp. 69-104. , Motoyama EK, Davis PJ, eds. St. Louis: Mosby; Lake, C.L., Cardiovascular anatomy and physiology (1992) Clinical Anesthesia, pp. 989-1020. , Barash PG, Cullen BF, Stoelting RK, eds. Philadelphia: Lippincott; Hsieh, K., Chen, P., Fu, S., A simple, noninvasive method to investigate vascular characteristics in children (1996) Angiology, 47, pp. 361-367; Stoelting, R.K., Miller, R.D., (2000) Basics of Anesthesia, pp. 364-375. , Philadelphia: Churchill Livingstone; Thilenius, O.G., Argilla, R.A., Angiographic right and left ventricular volume determination in normal infants and children (1974) Pediatr Res, 8, pp. 67-74; Drouin, E., Gournay, V., Calamel, J., Assessment of spontaneous baroreflex sensitivity in neonates (1997) Arch Dis Child Fetal Neonatal Ed, 76, pp. F108-12
Keywords: aging; Algorithms; Anesthesiology; aorta stenosis; Aortic Valve Stenosis; arterial pressure; article; Baroreflex; biological model; bleeding; Blood Loss, Surgical; cardiovascular function; Cardiovascular physiology; Computer simulation; education; heart ventricle pressure; hemodynamic parameters; Hemodynamic Processes; Humans; Infant; Models, Biological; priority journal; Pulmonary Circulation; simulation; Ventricular Function, Left; Ventricular Function, Right

Albumin adsorption on alkanethiols self-assembled monolayers on gold electrodes studied by chronopotentiometry - Martins, M.C.L.; Fonseca, C.; Barbosa, M.A.; Ratner, B.D. (BiomaterialsBiomaterials, 2003)
Chronopotentiometry was used to study the adsorption of human serum albumin (HSA) to self-assembled monolayers with the following terminal functional groups: CH 3, COOH and OH. Surfaces were characterized by X-ray photoelectron spectroscopy, water contact angle measurements and cyclic voltammetry. HSA coverage of the different SAMs was investigated by chronopotentiometry and the total amount of adsorbed protein was determined using radiolabelled albumin. Both techniques have demonstrated that HSA adsorption to the different SAM-modified electrodes increases in the following order: OH<COOH<CH 3-terminated SAMs. A good correlation between coverage and total amount of HSA adsorbed was observed for long adsorption times (900s). © 2003 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(03)00244-8PubMed ID: 12818541Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; INEB - Inst. de Engenharia Biomed., Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: gold, 7440-57-5; thiol derivative, 13940-21-1; water, 7732-18-5; Albumins; Alkanes; Biocompatible Materials; Gold, 7440-57-5; Serum Albumin; Sulfhydryl CompoundsReferences: Ratner, B.D., Hoffman, A.S., Schoen, F.J., Lemons, J.L., (1996) Biomaterials science - an introduction to materials in medicine, , San Diego, CA, USA: Academic Press;Nakanishi, K., Sakiyama, T., Imamura, K., On the adsorption of proteins on solid surfaces, a common but very complicated phenomenon (2001) J Biosci Bioeng, 91, pp. 233-244; Mrksich, M., Whitesides, G.M., Using self-assembled monolayers to understand the interactions of man-made surfaces with proteins and cells (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-78; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) J Am Chem Soc, 120, pp. 3464-3473; Taborelli, M., Eng, L., Descouts, P., Ranieri, J.P., Bellamkonda, R., Aebisher, P., Bovine serum albumin conformation on methyl and amine functionalized surfaces compared by scanning force microscopy (1995) J Biomed Mater Res, 29, pp. 707-714; Silin, V., Weetall, H., Vanderah, D., SPR studies of the nonspecific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) J Colloid Interface Sci, 185, pp. 94-103; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27, pp. 1463-1476; Wadu-Mesthrige, K., Amro, N.A., Liu, G., Immobilization of proteins on self-assembled monolayers (2000) Scanning, 22, pp. 380-388; Takahara, A., Hara, Y., Kojio, K., Kajiyama, T., Plasma protein adsorption behaviour onto the surface of phase-separated organosilane monolayers on the basis of scanning force microscopy (2002) Colloids Surf B: Biointerfaces, 23, pp. 141-152; Kalltorp, M., Carlén, A., Thomsen, P., Olsson, J., Tengvall, P., Analysis of rat plasma proteins desorbed from gold and methyl- and hydroxyl-terminated alkane thiols on gold surfaces (2000) J Mater Sci: Mater Med, 11, pp. 191-199; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Endothelial cell growth and protein adsorption on terminal functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13, pp. 3404-3413; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111, pp. 321-335; Ulman, A., (1991) An introduction to ultrathin organic films: From Langmuir-Blodgett to self-assembled, , San Diego, CA, USA: Academic Press; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionlity (2000) J Biomed Mater Res, 51, pp. 413-423; Mirsky, V.M., Riepl, M., Wolfbeis, O.S., Capacitive monitoring of protein immobilization and antigen/antibody reactions on monomolecular alkylthiol films on gold electrodes (1997) Biosensors Bioelectron, 12, pp. 977-989; Viana, A.S., Jones, A.H., Abrantes, L.M., Kalaji, M., Redox induced orientational changes in a series of short chain ferrocenyl alkyl thiols self-assembled on gold(1 1 1) electrodes (2001) J Electroanal Chem, 500, pp. 290-298; Kondo, T., Okamura, M., Uosaki, K., Anion effect on the electrochemical characteristics of a gold electrode modified with a self-assembled monolayer of ferrocenylhexanethiol in aqueous and dichlomethane solutions (2001) J Organometal Chem, 637-639, pp. 841-844; Dong, S., Li, J., Self-assembled monolayers of thiols on gold electrodes for bioelectrochemistry and biosensors (1997) Bioelectrochem Bioenergetics, 42, pp. 7-14; Gooding, J.J., Hibbert, D.B., The application of alkanethiol self-assembled monolayers to enzyme electrodes (1999) Trends Anal Chem, 18, pp. 525-533; Spangler, B.D., Tyler, B.J., Capture agents for quartz crystal microbalance-continuous flow biosensor: Functionalized self-assembled monolayers on gold (1999) Anal Chem Acta, 399, pp. 51-62; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Tengvall, P., Lundstrom, I., Liedberg, B., Protein adsorption studies on model organic surfaces: An ellipsometric and infrared spectroscopic approach (1998) Biomaterials, 19, pp. 407-422; Shen, D., Huang, M., Chow, L., Yang, M., Kinetic profile of the adsorption and conformational change of lysozyme on self-assembled monolayers as revealed by quartz crystal resonator (2001) Sensor Actuators B, 77, pp. 664-670; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Silva, M.F., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, 2, pp. 183-214. , Williams D.F. Harcover: CRC Press; Du, Y.J., Cornelius, R.M., Brash, J.L., Measurement of protein adsorption to gold surface by radioiodination methods: Suppression of free iodide sorption (2000) Colloid Surf B, 17, pp. 59-67; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., Measurement of protein using bicinchoninic acid (1985) Anal Biochem, 150, pp. 756-785; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., Interactions between calcium, phosphate, and albumin on the surface of titanium (2001) J Biomed Mater Res, 55, pp. 45-53; (1993) Iodine-125. A Guide to Radioiodination Techniques, p. 64. , Amersham Life Science. Little Chalfort, UK: Amersham International plc; Bain, C.D., Evall, J., Whitesides, G.M., Formation of monolayer coadsorption of thiols on gold: Variation in the head group, tail group and solvent (1989) J Am Chem Soc, 111, pp. 7155-7164; Castner, D.G., Hinds, K., Grainger, D.W., X-ray photoelectron spectroscopy sulfur 2p study of organic thiol and disulfide binding interactions with gold surfaces (1996) Langmuir, 12, pp. 5083-5086; Keller, H., Schrepp, W., Fuchs, H., Self-assembled organic films on gold and silver (1992) Thin Solid Films, 210-211, pp. 799-802; Chidsey, C.E.D., Loiacono, D.N., Chemical functionality in self-assembled monolayers: Structural and electrochemical properties (1990) Langmuir, 6, pp. 682-691; Porter, M.D., Bright, T.B., Allara, D.L., Chidsey, C.E.D., Spontaneously organized molecular assemblies. 4. Structural characterization of n-alkyl thiol monolayers on gold by optical ellipsometry, infrared spectroscopy and electrochemistry (1987) J Am Chem Soc, 109, pp. 3559-3568; Miller, C., Cuendet, P., Gratzel, M., Adsorbed ω-hydroxy thiol monolayers on gold electrodes: Evidence for electron tunneling to redox species in solution (1991) J Phys Chem, 95, pp. 877-886; Krysinski, P., Brzostowska-Smolska, M., Capacitance characteristics of self-assembled monolayers on gold electrode (1998) Bioelectrochem Bioenergetics, 44, pp. 163-168; Guo, B., Anzai, J., OSA, T., Adsorption behaviour of serum albumin on electrodes surfaces and the effects of electrode potential (1996) Chem Pharm Bull, 44, pp. 800-803; Dent, A.H., Aslam, M., Other categories of protein coupling (1998) Bioconjugation, protein coupling techniques for the biomedical sciences, pp. 504-569. , M. Aslam, & A.H. Dent. London: Macmillan; Seigal, R.R., Harder, P., Dahint, R., Grunze, M., On-line detection of nonspecific protein adsorption at artificial surfaces (1997) Anal Chem, 69, pp. 3321-3328; Norde, W., Giacomelli, C.E., BSA structural changes during homomolecular exchange between the adsorbed and the dissolved states (2000) J Biotechnol, 79, pp. 259-268; Peters T., Jr., (1996) All about albumin: Biochemistry, genetics, and medical applications, , San Diego, CA, USA: Academic Press; Feng, L., Andrade, J.D., Protein adsorption on low temperature isotropic carbon. III. Isoterms, competitivity, desorption and exchange of albumin and fibrinogen (1994) Biomaterials, 15, pp. 323-333
Keywords: Adsorption; Albumin; Albumin adsorption; Albumins; alkane; Alkanes; article; Biocompatible Materials; biomaterial; Biomaterials; carboxyl group; Chemical modification; Chronopotentiometry; Contact angle; correlation analysis; cyclic potentiometry; Cyclic voltammetry; electrochemistry; electrode; Electron Probe Microanalysis; Functional groups; gold; Humans; hydroxyl group; isotope labeling; methyl group; Monolayers; potentiometry; priority journal; protein analysis; Self assembly; Self-assembled monolayers; Serum Albumin; Sulfhydryl Compounds; Surface modification; Surface Properties; surface property; temperature; thiol derivative; Time Factors; Water; X ray photoelectron spectroscopy

Albumin adsorption on Cibacron Blue F3G-A immobilized onto oligo(ethylene glycol)-terminated self-assembled monolayers - Martins, Ma.C.L.; Naeemi, E.; Ratner, B.D.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2003)
Self-assembled monolayers can be tailored with specific ligands to a certain protein and at the same time prevent the non-specific adsorption of other proteins. Cibacron Blue F3G-A (CB-thiol) was successfully immobilized onto tetra(ethylene glycol)-terminated alkanethiol (CB-thiol). The affinity of human serum albumin (HSA) to immobilized Cibacron Blue F3G-A was studied using mixed thiolate self-assembled monolayers on gold with different n-alkyl chain lengths and functional terminal groups (CH 3-; OH- and tetra(ethylene glycol)). Surfaces were characterized using X-ray photoelectron spectroscopy and water contact angle measurements. Albumin adsorption and exchangeability of the adsorbed albumin molecules with other albumin molecules in solution were evaluated using 125I-radiolabeled HSA. Competitive adsorption between albumin and fibrinogen to the different self-assembled monolayers (SAMs) was also investigated. Results showed that the incorporation of CB-thiol on the monolayers does not increase the HSA adsorption and reversibility on the SAMs. However, although specific adsorption of HSA to the immobilized Cibacron Blue F3G-A was not demonstrated, the presence of CB-thiol decreases the affinity of fibrinogen to the OH-terminated SAMs. © 2003 Kluwer Academic Publishers.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1026394431100Language of Original Document: EnglishCorrespondence Address: Martins, Ma.C.L.; INEB - Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: cibacron blue f3ga, 12236-82-7, 53127-08-5; ethylene glycol, 107-21-1; fibrinogen, 9001-32-5; gold, 7440-57-5; human serum albumin, 9048-49-1; iodine 125, 14158-31-7, 22822-81-7; macrogol, 25322-68-3; thiol derivative, 13940-21-1; water, 7732-18-5References: Ratner, B.D., (1996) J. Mol. Recognit., 9, p. 617;Kottke-Marchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., (1998) Biomaterials, 10, p. 147; Dequeiroz, A.A.A., Barrak, E.R., Gil, H.A.C., Higa, O.Z., (1997) J. Biomater. Sci. Polym. Ed., 8, p. 667; Kamath, K.R., Park, K., (1994) J. Appl. Biomater., 5, p. 163; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., (1981) Trans. Am. Soc. Artif. Intern. Organs, 27, p. 499; Ji, J., Feng, L., Barbosa, M.A., (2001) Biomaterials, 22, p. 3015; Keogh, J.R., Eaton, J.W., (1994) J. Lab. Clin. Med., 121, p. 537; Wang, D., Chen, B., Ji, J., Feng, L., (2002) Bioconjugate Chem., 13, p. 792; Ji, J., Barbosa, M.A., Feng, L., Shen, J., (2002) J. Mat. Sci. Mat. Med., 13, p. 677; Mcfarland, C.D., Jenkins, M., Griesser, H.J., Chatelier, R.C., Steele, J.G., Underwood, P.A., (1998) J. Biomater. Sci. Polym. Ed., 9, p. 1207; Mcfarland, C.D., Filippis, C.D., Jenkins, M., Tunstell, A., Rhodes, N.P., Williams, D.F., Steele, J.G., (1998) J. Biomater. Sci. Polym. Ed., 9, p. 1277; Kopperschlager, G., Bohme, H.J., Hofmann, E., (1982) Adv. Biochem. Eng., 25, p. 101; Travis, J., Bowen, J., Tewksbury, D., Johnson, D., Pannell, R., (1976) Biochem. J., 157, p. 301; Leatherbarrow, R.L., Dean, P.D.G., (1980) Biochem. J., 189, p. 27; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., (2003) J. Biomater. Sci. Polym. Ed., 14, p. 439; Dockal, M., Carter, D.C., Ruker, F., (1999) J. Biol. Chem., 274, p. 29303; Ostuni, E., Yan, L., Whitesides, G.M., (1999) Colloid Surf. B-Biointerfaces, 15, p. 3; Ulman, A., (1991) An Introduction to Ultrathin Organic Films: From Langmuir-Blodgett to Self-Assembled, , Academic Press Inc: San Diego, CA, USA; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., (1989) J. Am. Chem. Soc., 111, p. 321; Porter, M.D., Bright, T.B., Allara, D.L., Chidsey, C.E.D., (1987) J. Am. Chem. Soc., 109, p. 3559; Sigal, G.B., Mrksich, M., Whitesides, G.M., (1998) J. Am. Chem. Soc., 120, p. 3464; Seigal, R.R., Harder, P., Dahint, R., Grunze, M., (1997) Anal. Chem., 69, p. 3321; López, G.P., Biebuyck, H.A., Harter, R., Kumar, A., Whitesides, G.M., (1993) J. Am. Chem. Soc., 115, p. 10774; Prime, K., Whitesides, G.M., (1991) Science, 252, p. 1164; Chinn, J.A., Horbett, T.A., Ratner, B.D., (1991) Thromb. Haemost., 65, p. 608; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Silva, M.F., (1999) IEEE Trans. Magn., 35, p. 4361; Pale-Grosdemange, C., Simon, E.S., Prime, K.L., Whitesides, G.M., (1991) J. Am. Chem. Soc., 113, p. 12; Castner, D.G., Hinds, K., Grainger, D.W., (1996) Langmuir, 12, p. 5083; Lin, J.C., Chuang, W.H., (2000) J. Biomed. Mater. Res., 51, p. 413; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., (2001) J. Biomed. Mater. Res., 55, p. 45; (1993) Iodine-125, a Guide to Radioiodination Techniques - Amersham Life Science, p. 64. , Amersham International plc, Amersham Place, Little Chalfont, Bucks. HP7 9NA, England; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of Biocompatibility Tests, p. 183. , edited by D. F. Williams (Harcover, CRC Pr); Du, Y.J., Cornelius, R.M., Brash, J.L., (2000) Colloid Surf. B-Biointerfaces, 17, p. 59; Beamson, G., Briggs, D., (1992) High Resolution XPS of Organic Polymers - The Scienta ESCA300 Database, , John Wiley & Sons Ltd, Chichester, England; htpp://www.lasurface.com/Tarlov, M.J., Burgess Jr., D.R.F., Gillen, G., (1993) J. Am. Chem. Soc., 115, p. 5305; Tegoulia, V.A., Cooper, S.L., (2000) J. Biom. Mater. Res., 50, p. 291; Ishida, T., Tsuneda, S., Nishida, N., Hara, M., Sasabe, H., Knoll, W., (1997) Langmuir, 13, p. 4638; Silver, J.H., Hergenrother, R.W., Lin, J.C., Lim, F., Lin, H.B., Okada, T., Chaudhury, M.K., Cooper, S.L., (1995) J. Biom. Mater. Res., 29, p. 535; Smith, T., (1980) J. Colloid. Interf. Sci., 75, p. 51; Tidwell, C.D., Ertel, S.I., Ratner, B.D., (1997) Langmuir, 13, p. 3404; Silin, V., Weetall, H., Vanderah, D., (1997) J. Colloid. Interf. Sci., 185, p. 94; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., (2003) J. Biom. Mater. Res., 67 A, p. 158; Schlereth, D.D., (1997) Sens. Actuator B-Chem., 43, p. 78; Mrksich, M., Grunwell, J.R., Whitesides, G.M., (1995) J. Am. Chem. Soc., 117, p. 12009; Hodneland, C.D., Lee, Y.S., Min, D.H., Mrksich, M., (2002) PNAS, 99, p. 5048; Malmsten, M., Lassen, B., (1994) J. Colloid. Interf. Sci., 166, p. 490; Feng, L., Andrade, J.D., (1994) Biomaterials, 15, p. 323; Bertilsson, L., Butt, H.J., Nelles, G., Schlereth, D.D., (1997) Biosens. Bioelectron., 12, p. 839
Keywords: Adsorption; Albumin; aqueous solution; article; Cell immobilization; cibacron blue f3ga; Contact angle; controlled study; Drug products; Ethylene Glycol; fibrinogen; functional group; Glycols; gold; human; human serum albumin; iodine 125; isotope labeling; ligand; macrogol; molecule; priority journal; protein assembly; protein binding; protein immobilization; protein structure; Proteins; radioassay; Self assembly; surface property; synthesis; tetra(ethylene glycol) undecanethiol; thiol; thiol derivative; unclassified drug; Water; X ray photoelectron spectroscopy

Albumin and fibrinogen adsorption on Cibacron blue F3G-A immobilised onto PU-PHEMA (polyurethane-poly (hydroxyethylmethacrylate)) surfaces - Martins, M.C.L.; Wang, D.; Ji, J.; Feng, L.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2003)
In the present work, it is intended to study the effect of Cibacron blue F3G-A (CB) immobilised onto PU-PHEMA (polyurethane-poly(hydroxyethylmethacrylate)) surfaces on protein adsorption and bacterial adhesion. CB immobilisation was carried out by covalent binding between its triazine ring and the hydroxyl groups of the polymer. Characterisation of the films was carried out by attenuated total reflection Fourier transform infrared spectroscopy (ATR-FT-IR), contact angle measurements, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). CB efficiency was evaluated using radiolabelled albumin and fibrinogen from pure solutions, mixtures of both and plasma. Bacterial adhesion tests before and after albumin pre-coating were also performed. The presence of CB increases albumin and fibrinogen adsorption to PU-PHEMA surfaces. The incorporation of CB onto the PU-PHEMA surface also increases bacterial adhesion. Although albumin pre-coating decreases bacterial adhesion onto PU (67% decrease) and PU-PHEMA-CB (80%), bacterial adhesion is always lower on PU and PU-PHEMA surfaces than on PU-PHEMA-CB. These results demonstrate that, in contrast to what has been described for CB bound to dextran, CB immobilisation on PU-PHEMA surfaces presents low selectivity to albumin and increased bacterial adhesion relatively to PU and PU-PHEMA surfaces.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: JBSEEdoi: 10.1163/156856203766652057PubMed ID: 12807146Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: cibacron blue f3ga, 12236-82-7, 53127-08-5; dextran, 87915-38-6, 9014-78-2; fibrinogen, 9001-32-5; polymacon, 25053-81-0, 25249-16-5, 98932-78-6; polyurethan, 61789-63-7; Albumins; Biocompatible Materials; Cibacron Blue F 3GA, 12236-82-7; Fibrinogen, 9001-32-5; Membranes, Artificial; Polyhydroxyethyl Methacrylate, 25249-16-5; TriazinesReferences: Ratner, B.D., Hoffman, A.S., Schoen, F.J., Lemons, J.L., (1996) Biomaterials Science - an Introduction to Materials in Medicine, , (Eds), Academic Press, San Diego, CA;Greco, R.S., (1994) Implantation Biology, the Host Response and Biomedical Devices, , (Ed.), CRC Press, Ann Arbour, MI; Sapatnekar, S., Anderson, J.M., (1999) Handbook of Biomaterials Evaluation. Scientific, Technical and Clinical Testing of Implant Materials, p. 353. , A. F. von Recum (Ed.), Taylor & Francis, Philadelphia, PA; Kottke-Marchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., (1998) Biomaterials, 10, p. 147; Keogh, J.R., Eaton, J.W., (1994) J. Lab. Clin. Med., 121, p. 537; Sapatnekar, S., Kieswetter, K.M., Merritt, K., Anderson, J.M., Cahalan, L., Verhoeven, M., Hendriks, M., Cahalan, P., (1995) J. Biomed. Mater Res., 29, p. 247; Paulsson, M., Kober, M., Freij-Larsson Stollenwerk, C., Wesslén, B., Ljungh, Å., (1993) Biomaterials, 14, p. 845; Kopperschlager, G., Bohme, H.J., Hofmann, E., (1982) Adv. Biochem. Eng., 25, p. 101; Travis, J., Bowen, J., Tewksbury, D., Johnson, D., Pannell, R., (1976) Biochem. J., 157, p. 301; Arica, M.Y., Testereci, H.N., Denizli, A., (1998) J. Chromatogr A., 799, p. 83; Denizli, A., Salih, B., Senel, S., Arica, M.Y., (1998) J. Appl. Polym. Sci., 68, p. 657; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., (2003) Biomaterials, 24. , (in press); Leatherbarrow, R.L., Dean, P.D.G., (1980) Biochem. J., 189, p. 27; Horbett, T.A., (1986) Techniques of Biocompatibility Tests, 2, p. 183. , D. F. Williams (Ed.), CRC Press, Boca Raton, FL; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., (2001) J. Biomed. Mater. Res., 55, p. 45; (1993) Iodine-125, A Guide to Radioiodination Techniques, 64. , Amersham Life Science; Schrader, B., (1995) Infrared and Raman Spectroscopy, , (Ed.), VCH, Weinheim; Lamba, N.M.K., Woodhouse, K.A., Cooper, S.L., (1998) Polyurethanes in Biomedical Applications, , (Eds), CRC Press, Boca Raton, FL; http://www.lasurface.com/Beamson, G., Briggs, D., (1992) High Resolution XPS of Organic Polymers - The Scienta ESCA300 Database, , (Eds), Wiley, Chichester; Morra, M., Cassinelli, C., (1995) J. Biomed. Mater. Res., 29, p. 39; Compagnini, A., Fisichella, S., Foti, S., Maccarrone, G., Saletti, R., (1996) J. Chromatogr. A, 736, p. 115; Tanaka, M., Motomura, T., Kawada, M., Anzai, T., Kasori, Y., Shiroya, T., Shimura, K., Mochizuki, A., (2000) Biomaterials, 21, p. 1471; Feng, L., Andrade, J.D., (1994) Biomaterials, 15, p. 323; Peters T., Jr., (1996) All About Albumin. Biochemistry, Genetics and Medical Applications, , (Ed.), Academic Press, San Diego, CA; Dockal, M., Carter, D.C., Rüker, F., (1999) J. Biol. Chem., 274, p. 29303; Denizli, A., Kocakulak, M., Piskin, E., (1998) J. Chromatogr. B., 707, p. 25; Salih, B., Zenobi, R., (1998) Anal. Chem., 70, p. 1536; Österberg, E., Bergström, K., Holmberg, K., Schuman, T.P., Riggs, J.A., Burns, N.L., (1995) J. Biomed. Mater. Res., 29, p. 741; Beeskow, T., Kroner, K.H., Anspach, F.B., (1997) J. Colloid. Interf. Sci., 196, p. 278; Frazier, R.A., Matthijs, G., Davies, M.C., Roberts, C.J., Schacht, E., Tendler, S.J.B., (2000) Biomaterials, 21, p. 957; Bertilsson, L., Butt, H.J., Nelles, G., Schlereth, D.D., (1997) Biosens. Bioelectron., 12, p. 839; Kao, J.M., Rose, R., Yousef, M., Hunter, S.K., Rodgers, V.G.J., (1999) J. Biomed. Mater. Res., 47, p. 537; Tegoulia, V.A., Cooper, S.L., (2002) Colloid. Surf. B: Biointerf., 24, p. 217
Keywords: Adsorption; Albumin; Albumins; article; Bacterial adhesion; bacterium adherence; Biocompatible Materials; Chemical structure; Cibacron blue; cibacron blue f3ga; Contact angle; controlled study; covalent bond; dextran; fibrinogen; hydroxyl group; immobilization; infrared spectroscopy; isotope labeling; Membranes, Artificial; Microscopy, Electron, Scanning; nonhuman; PHEMA; Polyhydroxyethyl Methacrylate; polymacon; polyurethan; priority journal; Protein adsorption; Scanning electron microscopy; Spectroscopy, Fourier Transform Infrared; Staphylococcus epidermidis; Surface Properties; triazine derivative; Triazines; X ray photoelectron spectroscopy; XPS

Albumin and fibrinogen adsorption on PU-PHEMA surfaces - Martins, M.C.L.; Wang, D.; Ji, J.; Feng, L.; Barbosa, M.A. (BiomaterialsBiomaterials, 2003)
Materials that adsorb specific proteins may find a variety of applications in the biomedical field. The aim of this study was the preparation of a hydrophilic surface, with low protein adsorption, to be used in the future as a support for the immobilisation of several species, e.g. Cibacron Blue F3G-A, which has been described to induce specific albumin adsorption. Poly(hydroxyethylmethacrylate) (PHEMA) and poly(hydroxyethylacrylate) (PHEA) were chosen as the hydrophilic surface because they can be easily polymerised and possess hydroxyl groups that can be used for the immobilisation of different compounds. Thin films of PHEMA and PHEA were successfully graft polymerised onto the surface of a commercial poly(etherurethane) (PU) using ceric ion as initiator. Grafting polymerisations were followed by mass gain and attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR). Since stability tests demonstrated that only PU-PHEMA was stable in alkaline solutions, a necessary condition to future immobilisations, the investigation was focused on the coating of PU with PHEMA. PU-PHEMA films were characterised in detail using several techniques as mass gain, ATR-FTIR, contact angle measurements, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). Protein adsorption was evaluated using radiolabelled albumin and fibrinogen from pure solutions and from mixtures of both proteins. PU surfaces modified with PHEMA have demonstrated low protein adsorption, showing their potential use as substrates. This opens the possibly of exploring the advantages of selective adsorption by appropriate immobilisation of specific molecules. © 2003 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 41Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(03)00002-4PubMed ID: 12628827Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; Laboratório de Biomateriais, Inst. de Engenharia Biomédica, Rua do Campo Algre 823, Porto 4150-180, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: acrylic acid ethyl ester, 140-88-5; fibrinogen, 9001-32-5; poly(2 hydroxyethyl acrylate), 26022-14-0; polyetherurethan, 76600-67-4; polymacon, 25053-81-0, 25249-16-5, 98932-78-6; protein, 67254-75-5; Albumins; Biocompatible Materials; Fibrinogen, 9001-32-5; poly(2-hydroxyethyl acrylate), 26022-14-0; Polyhydroxyethyl Methacrylate, 25249-16-5; Water, 7732-18-5References: Ratner, B.D., Hoffman, A.S., Schoen, F.J., Lemons, J.L., (1996) Biomaterials science - An introduction to materials in medicine, , CA, USA, San Diego: Academic Press;Greco, R.S., (1994) Implantation biology, the host response and biomedical devices, , Ann Arbour, USA: CRC Press; Sapatnekar, S., Anderson, J.M., Hemocompatibility: Effects on humoral elements (1999) Handbook of biomaterials evaluation, Scientific technical and clinical testing of implant materials, pp. 353-365. , A.F. von Recum. Philadelphia, PA, USA: Taylor & Francis; Lopez, G.P., Ratner, B.D., Tidwell, C.D., Haycox, C.L., Rapoza, R.J., Horbett, T.A., Glow discharge plasma deposition of tetraethylene glycol dimethyl ether for fouling-resistant biomaterials surfaces (1992) J Biomed Mater Res, 26, pp. 415-439; Johnston, E.E., Bryers, J.D., Ratner, B.D., Interactions between Pseudomonas Aeruginosa and plasma-deposited PEO-like thin films during initial attachment and growth (1997) ACS Polym Prep, 38, pp. 1016-1017; Kottke-Marchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., Effect of albumin coating on the in vitro blood compatibility of Dacron arterial prostheses (1998) Biomaterials, 10, pp. 147-155; Sapatnekar, S., Kieswetter, K.M., Merritt, K., Anderson, J.M., Cahalan, L., Verhoeven, M., Hendriks, M., Cahalan, P., Blood-biomaterial interactions in a flow system in the presence of bacterial, effect of protein adsorption (1995) J Biomed Mater Res, 29, pp. 247-256; Paulsson, M., Kober, M., Freij-Larsson, C., Stollenwerk Wesslén, B., Ljungh, Å., Adhesion of staphylococci to chemically modified and native polymers, and the influence of preadsorbed fibronectin, vitronectin and fibrinogen (1993) Biomaterials, 14, pp. 845-853; Keogh, J.R., Eaton, J.W., Albumin binding surfaces for biomaterials (1994) J Lab Clin Med, 121, pp. 537-545; Keogh, J.R., Velander, F.F., Eaton, J.W., Albumin-binding surfaces for implantable devices (1992) J Biomed Mater Res, 26, pp. 441-456; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., Alkyl substituted polymers with enhanced albumin affinity (1981) Trans Am Soc Artif Intern Organs, 27, pp. 499-503; Kamath, K.R., Park, K., Surface modification of polymeric biomaterials by albumin grafting using y-radiation (1994) J Appl Biomater, 5, pp. 163-173; McFarland, C.D., Filippis, C.D., Jenkins, M., Tunstell, A., Rhodes, N.P., Williams, D.F., Steele, J.G., Albumin binding surfaces: In vitro activity (1998) J Biomat Sci Polymer Ed, 9, pp. 1239-1277; Ji, J., Feng, L., Barbosa, M.A., Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin (2001) Biomaterials, 22, pp. 3015-3023; Tsai, C.C., Huo, H.H., Kulkarni, P., Eberhart, R.C., Biocompatible coatings with high albumin affinity (1990) ASAIO Trans, 36, pp. 307-M310; Bekos, E.J., Ranieri, J.P., Aebisher, P., Gardella J.A., Jr., Bright, F.V., Structural changes of bovine serum albumin upon adsorption to modified fluoropolymer substrates used for neural cell attachment studies (1995) Langmuir, 11, pp. 984-989; Bailly, A., Laurent, A., Lu, H., Elalami, I., Jacob, P., Mundler, O., Merland, J., Soria, C., Fibrinogen binding and platelet retention: Relationship with the thrombogenicity of catheters (1996) J Biomed Mater Res, 30, pp. 101-108; Montheard, J.P., Chatzopoulos, M., Chappard, D., 2-Hydroxyethyl methacrylate (HEMA): Chemical properties and applications in biomedical fields (1992) J M S-Rev Macromol Chem Phys, C32, pp. 1-34; Feng, X.D., Sun, Y.H., Qiu, K.Y., Reactive site and Mechanism of graft copolymerisation onto poly(ether urethane) with Ceric ion as initiator (1985) Macromolecules, 18, pp. 2105-2109; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, 2, pp. 183-214. , Williams DF, editor. Harcover: CRC Press; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., Interactions between calcium, phosphate, and albumin on the surface of titanium (2001) J Biomed Mater Res, 55, pp. 45-53; (1993) Iodine-125. A Guide to Radioiodination Techniques, p. 64. , Amersham Life Science, Little Chalfont, England: Amersham International plc; Schrader, B., (1995) Infrared and Raman spectroscopy: methods and applications, , Weinheim: VCH Publishers, Inc., (Federal Republic of German); Lamba, N.M.K., Woodhouse, K.A., Cooper, S.L., (1998) Polyurethanes in biomedical applications, , Boca Raton, FL, USA: CRC Press; Bandekar, J., Sawyer, A., FT-IR spectroscopic studies of polyurethanes: IV studies of the effect of the presence of processing aids on the hemocompatibility of polyurethanes (1995) J Biomater Sci Polym Ed, 7, pp. 485-501; Tingey, K.G., Andrade, J.D., McGary C.W., Jr., Zdrahala, R.J., Surface analysis of commercial biomedical polyurethanes (1988) Polymer surface dynamics, , Andrade JD, editor. New York: Plenum Press; Beamson, G., Briggs, D., (1992) High resolution XPS of organic polymers - the scienta ESCA300 database, , Chichester, England: Wiley; Hsiue, G., Lee, S., Wang, C., Shiue, M.H., Chang, P.C., Plasma-induced graft copolymerisation of HEMA onto silicone rubber and TPX film improving rabbit corneal epithelial cell attachment and growth (1994) Biomaterials, 15, pp. 163-171; Lee, J.H., Ju, Y.M., Lee, W.K., Park, K.D., Kim, Y.H., Platelet adhesion onto segmented polyurethane surfaces modified by PEO - And sulfonated PEO-containing block copolymer additives (1998) J Biomed Mater Res, 40, pp. 314-323; Morra, M., Occhiello, E., Garbassi, F., On the wettability of poly(2-hydroxyethylmetacrylate) (1992) J Colloid Interface Sci, 149, pp. 84-91; Morra, M., Cassinelli, C., Surface field of forces and protein adsorption behavior of poly(hydroxyethylmethacrylate) films deposited from plasma (1995) J Biomed Mater Res, 29, pp. 39-45; Elam, J., Nygren, Adsorption of coagulation proteins from whole blood on to polymer materials: Relation to platelet activation (1992) Biomaterials, 13, pp. 3-8; Chin, J.A., Horbett, T.A., Ratner, B.D., Baboon fibrinogen adsorption and platelet adhesion to polymeric materials (1991) Thromb Haemostas, 65, pp. 608-617; Horbett, T.A., Adsorption of proteins from plasma to a series of hydrophilic-hydrophobic copolymers. II Compositional analysis with the prelabeled protein technique (1981) J Biom Mater Res, 15, pp. 673-695; Garrett, Q., Chatelier, R.C., Griesser, H.J., Milthorpe, B.K., Effect of charged groups on the adsorption and penetration of proteins onto and into carboxymethylated poly(HEMA) hydrogels (1998) Biomaterials, 19, pp. 2175-2186; Feng, L., Andrade, J.D., Protein adsorption on low temperature isotropic carbon. III. Isoterms, competitivity, desorption and exchange of albumin and fibrinogen (1994) Biomaterials, 15, pp. 323-333; Bohnert, J.L., Horbett, T.A., Changes in adsorbed fibrinogen and albumin interactions with polymers indicated by decreases in detergent elutability (1986) J Colloid Interface Sci, 111, pp. 363-377; Slack, S.M., Horbett, T.A., Changes in fibrinogen adsorbed to segmented polyurethanes and hydroxyethylmethacrylate-ethylmethacrylate copolymers (1992) J Biom Mater Res, 26, pp. 1633-1649; Tanaka, M., Motomura, T., Kawada, M., Anzai, T., Kasori, Y., Shiroya, T., Shimura, K., Mochizuki, A., Blood compatible aspects of poly(hydroxyethylacrylate) (PMEA) - Relationship between protein adsorption and platelet adhesion on PHEA surface (2000) Biomaterials, 21, pp. 1471-1481; Vroman, L., Adams, A.L., Fisher, G.C., Munoz, P.C., Interaction of high molecular weight kininogen, Factor XII and fibrinogen in plasma at interfaces (1980) Blood, 55, pp. 156-159; Vroman, L., Adams, A.L., Adsorption of proteins out of plasma and solutions in narrow spaces (1986) J Colloid Interface Sci, 111, pp. 391-402; Andrade, J.D., Hlady, V., Protein adsorption and materials biocompatibility: A tutorial review and suggested hypotheses (1986) Adv Polym Sci, 79, pp. 1-63; Andrade, J.D., Hlady, V., Vroman effects, techniques and philosophies (1991) J Biomater Sci Polym Ed, 2, pp. 161-172; Brash, J.L., Studies of protein adsorption relevant to blood compatible materials (1991) Modern aspects of protein adsorption on biomaterials, p. 23. , Y.F. Missirlis, & W. Lemm. Kluwer Netherland: Academic Publishers; Brash, J.L., Hove, P.T., Protein adsorption studies on standard polymeric materials (1993) J Biomater Sci Polymer Ed, 4, pp. 591-599
Keywords: acrylic acid ethyl ester; Adsorption; Albumin; Albumins; article; ATR-FTIR; Biocompatible Materials; Chemical modification; Dose-Response Relationship, Drug; fibrinogen; film; Fourier transform infrared spectroscopy; Graft polymerisation; Humans; Hydrogen-Ion Concentration; Hydrophilic surfaces; hydrophilicity; hydroxyl group; infrared spectroscopy; isotope labeling; Microscopy, Electron, Scanning; molecular stability; Pellethane; PHEMA; poly(2 hydroxyethyl acrylate); polyetherurethan; Polyhydroxyethyl Methacrylate; polymacon; Polymerization; priority journal; protein; Protein adsorption; Proteins; Scanning electron microscopy; Spectrometry, X-Ray Emission; Spectroscopy, Fourier Transform Infrared; surface property; Thin films; unclassified drug; Water; X ray photoelectron spectroscopy

Constructing thromboresistant surface on biomedical stainless steel via layer-by-layer deposition anticoagulant - Tan, Q.; Ji, J.; Barbosa, M.A.; Fonseca, C.; Shen, J. (BiomaterialsBiomaterials, 2003)
Multilayer films consisting of polyethylenimine (PEI) and heparin were successfully prepared on biomedical 316L stainless steel surface via electrostatic self-assembly (ESA) of the PEI and heparin. The process of ESA of PEI/heparin was monitored by static contact angle, electrochemical impedance spectroscopy (EIS), reflection adsorption spectroscopy and X-ray photoelectron spectroscopy data. The contact angle and EIS data revealed that the multilayer coating was stable in Tris-HCl (pH 7.35) buffer solution for 21 days. The static platelet adhesion and static clotting time experiments indicated that the PEI/heparin-deposited stainless steel could resist the platelet adhesion and prolong the static clotting time effectively. Such an easy processing and shape-independent method may have good potential for surface modification of cardiovascular devices. © 2003 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 67Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(03)00363-6PubMed ID: 12951013Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; polyethyleneimine, 74913-72-7; stainless steel, 12597-68-1; trometamol, 1185-53-1, 77-86-1; Anticoagulants; Coated Materials, Biocompatible; Heparin, 9005-49-6; Polyethyleneimine, 9002-98-6; Stainless Steel, 12597-68-1Manufacturers: AldrichReferences: Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., Ultrathin polymer coating by complexation of polyelectrolytes at interfaces: Suitable materials, structure and properties (2000) Macromol Rapid Commun, 21, pp. 319-348;Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Sano, M., Lvov, Y., Kunitake, T., (1996) Annu Rev Mater Sci, 26, pp. 153-187; Laschewsky, A., (1997) Eur Chem Chron ECC, 2, pp. 13-24; Picart, C., Lavalle, Ph., Hubert, P., Cuisnier, Fj., Decher, G., Schaaf, P., Voegel, J.C., Buildup mechanism for poly (L-lysine)/hyaluronic acid films onto a solid surface (2001) Langmuir, 17, pp. 7414-7424; Houska, M., Brynda, E., Interactions of proteins with polyelectrolytes at solid/liquid interfaces: Sequential adsorption of albumin and heparin (1997) J Colloid Interface Sci, 188, pp. 243-250; Brynda, E., Houska, M., Multiple alternating molecular layers of albumin and heparin on solid surfaces (1996) J Colloid Interface Sci, 183, pp. 18-25; Thomann, U.I., Uggowitzer, P.J., Wear-corrosion behavior of biocompatible austenitic stainless steels (2000) Wear, 239, pp. 48-58; Cheatham, J., Improved stents for pediatric applications (2001) Prog Pediatr Cardiol, 14, pp. 95-115; Donachie, M., Biomedical alloys (1998) Adv Mater Process, 154, pp. 63-65; Decher, G., Fuzzy nanoassemblies: Toward layered polymeric multicomposites (1997) Science, 277, pp. 1232-1237; Raposo, M., Pontes, R.S., Mattoso, L.H.C., Oliveira, O.N., Kinetics of adsorption of poly (o-methoxyaniline) self-assembled films (1997) Macromolecules, 30, pp. 6095-6101; Vov, Y.L., Rusling, J., Thomsen, D.L., Papadimitrakopoulos, F., Kawakami, T., Kunitake, T., High-speed multilayer film assembly by alternate adsorption of silica nanoparticles and linear polycation (1998) Chem Commun, 11, pp. 1229-1230; Lowack, K., Helm, C.A., Controlling the self-assembly process of polyelectrolyte multilayers (1998) Macromolecules, 31, pp. 823-833; Cheng, Z., Cheng, L., Dong, S., Yang, X., Formation and characterization of heteropolyacid/polycation multilayer films on gold electrode (2001) J Electrochem Soc, 148, p. 227
Keywords: 316L stainless steel; Adhesion; Adsorption; anticoagulant agent; Anticoagulants; aqueous solution; article; Biocompatibility; biomaterial; Biomaterials; blood clotting time; Blood Platelets; Blood-compatibility; buffer; Coated Materials, Biocompatible; coating; Coatings; Contact angle; controlled study; Deposition; device; electricity; Electrochemical impedance spectroscopy; electrochemistry; Electrostatics; heparin; human; human cell; Humans; implant; Layer-by-layer; material coating; materials testing; Multilayers; Organic polymers; pH; Platelet Adhesiveness; Polyethyleneimine; priority journal; reflection adsorption spectroscopy; Self assembly; Spectroscopy; Stainless steel; Surface Properties; surface property; Surfaces; thrombocyte adhesion; Thromboresistant surfaces; trometamol; X ray photoelectron spectroscopy

Corrosion behaviour of commercially pure titanium shot blasted with different materials and sizes of shot particles for dental implant applications - Aparicio, C.; Javier Gil, F.; Fonseca, C.; Barbosa, M.; Planell, J.A. (BiomaterialsBiomaterials, 2003)
It is well known that the osseointegration of the commercially pure titanium (c.p. Ti) dental implant is improved when the metal is shot blasted in order to increase its surface roughness. This roughness is colonised by bone, which improves implant fixation. However, shot blasting also changes the chemical composition of the implant surface because some shot particles remain adhered on the metal. The c.p. Ti surfaces shot blasted with different materials and sizes of shot particles were tested in order to determine their topographical features (surface roughness, real surface area and the percentage of surface covered by the adhered shot particles) and electrochemical behaviour (open circuit potential, electrochemical impedance spectroscopy and cyclic polarisation). The results demonstrate that the increased surface area of the material because of the increasing surface roughness is not the only cause for differences found in the electrochemical behaviour and corrosion resistance of the blasted c.p. Ti. Among other possible causes, those differences may be attributed to the compressive residual surface stresses induced by shot blasting. All the materials tested have an adequate corrosion and electrochemical behaviour in terms of its possible use as dental implant material. © 2002 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 77Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00314-9Language of Original Document: EnglishCorrespondence Address: Aparicio, C.; Res. Center in Biomed. Eng. (CREB), Department of Materials Science, Universitat Politecnica de Catalunya, Av. Diagonal 647, 08028 Barcelona, Spain; email: conrado.aparicio@upc.esChemicals/CAS: Dental Implants; Titanium, 7440-32-6References: Brånemark, P.I., Hansson, B.O., Adell, R., Breine, U., Lindström, J., Hallen, O., Öhman, A., Osseointegrated implants in the treatment of edentulous jaw experience from a 10-year period (1977) Scand J Reconstr Surg, 16 (SUPPL.), pp. 1-132;Lemons, J.E., Application of materials in medicine and dentistry. Dental implants (1996) Biomaterials Science: An Introduction to Materials in Medicine, pp. 308-318. , B.D. Ratner, A.S. Hoffman, F.J. Schoen, & J.E. Lemons. San Diego: Academic Press; Pourbaix, M., Electrochemical corrosion of metallic biomaterials (1984) Biomaterials, 5, pp. 122-134; Bardos, D.I., Titanium and titanium alloys (1990) Encyclopaedia of Medical and Dental Materials, pp. 360-365. , D. William. Oxford: Pergamon Press; Boyer, R., Welsh, G., Colling, E.W., (1994) Materials Properties Handbook: Titanium Alloys, pp. 181-219. , Ohio: ASM International; Kasemo, B., Lausmaa, J., Surface science aspects on inorganic biomaterials (1986) CRC Crit Rev Biocompatibilty, 4, pp. 335-380; Tengvall, P., Lundtröm, I., Physico-chemical considerations of titanium as a biomaterial (1992) Biomaterials, 9, pp. 115-134; Albrektsson, T., Brånemark, P.I., Hansson, B.O., Lindström, J., Osseointegrated titanium implants (1981) Acta Orthop Scand, 52, pp. 155-170; Thomas, K.A., Cook, S., An evaluation of variables influencing implant fixation by direct bone apposition (1985) J Biomed Mater Res, 19, pp. 875-901; Wennerberg, A., (1996) On Surface Roughness and Implant Incorporation, , Ph.D. thesis, Göteborg: University of Göteborg; Bowers, K.T., Keller, J.C., Randolph, B.A., Wick, D.G., Michaels, C.M., Optimization of surface micromorphology from enhanced osteoblast response in vitro (1992) Int J Oral Maxillofac Implants, 7, pp. 302-310; Groessner-Schereider, B., Tuan, R.S., Enhanced extracellular matrix production and mineralization by osteoblasts cultured on titanium surfaces in vitro (1992) J Cell Sci, 101, pp. 209-217; Schwartz, Z., Boyan, B.D., Underlaying mechanisms at the bone biomaterial interface (1994) J Cell Biochem, 56, pp. 340-347; Boyan, B.D., Hummert, T.W., Kieswetter, K., Schraub, D., Dean, D.D., Schwartz, Z., Effect of titanium surface characteristics on chondrocytes and osteoblasts in vitro (1995) Scanning Electron Microsc (Cells and Materials), 5, pp. 323-335; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Dean, D.D., Boyan, B.D., Effect of titanium surface roughness on proliferation, differentiation and protein synthesis of human osteoblast-like cells (MG63) (1995) J Biomed Mater Res, 29, pp. 389-401; Ong, J.L., Prince, C.W., Raikar, G.N., Lucas, L.C., Effect of surface topography of titanium on surface chemistry and cellular response (1996) Implant Dent, 5, pp. 83-88; Deligianni, D.D., Katsal, N., Ladas, S., Sotiropoulou, D., Amedee, J., Missirlis, Y.F., Effect of surface roughness of the titanium alloy Ti-6Al-4V on human bone marrow cell response and on protein adsorption (2001) Biomaterials, 22, pp. 1241-1251; Schwartz, Z., Lohmann, C.H., Sisk, M., Cochran, D.L., Sylvia, V.L., Simpson, J., Dean, D.D., Boyan, B.D., Local factor production by MG63 ostoblast-like cells in response to surface roughness and 1,25-(OH) 2D 3 is mediated via protein kinase C- and protein kinase A-dependent pathways (2001) Biomaterials, 22, pp. 731-741; Predecki, P., Stephan, J.E., Auslander, B.A., Mooney, V.L., Kirkland, K., Kinetics of bone growth into cylindrical channels in aluminium oxide and titanium (1972) J Biomed Mater Res, 6, pp. 375-400; Buser, D., Schenk, R.K., Steinemann, S., Fiorelini, J.P., Fox, C.H., Stich, H., Influence of surface characteristics on bone integration of titanium implants. A histomorphometric study in miniature pigs (1991) J Biomed Mater Res, 25, pp. 889-902; Ericsson, I., Johansson, C., Bystedt, H., Norton, M.R., A histomorphometric evaluation of bone-to-implant contact on machined-prepared roughened titanium dental implants (1994) Clin Oral Implant Res, 5, pp. 202-206; Feighan, J.E., Goldberg, V.M., Davy, D., Parr, J.A., Stevenson, S., The influence of surface-blasting on the incorporation of titanium alloy implants in a rabit intramedullary model (1995) J Bone Jt Surg Am, 77, pp. 1380-1395; Wennerberg, A., Albrektsson, T., Andersson, B., An animal study of c.p. titanium screws with different surface topographies (1995) J Mater Sci: Mater Med, 6, pp. 302-309; Wong, M., Eulenberger, J., Schenk, R., Hunziker, E., Effect of surface topology on the osseointegration of implant materials in trabecular bone (1995) J Biomed Mater Res, 29, pp. 1567-1575; Wennerberg, A., Albrektsson, T., Johansson, C., Andersson, B., Experimental study of turned and grit-blasted screw-shaped implants with special emphasis on effects of blasting material and surface topography (1996) Biomaterials, 17, pp. 15-22; Cochran, D.L., Schenk, R.K., Lussi, A., Higginbottom, F.L., Buser, D., Bone response to unloaded and loaded titanium implants with a sandblasted and acid etched surface: A histometric study in the canine mandible (1998) J Biomed Mater Res, 40, pp. 1-11; Piatelli, A., Manzon, L., Scarano, A., Paolantonio, M., Piatelli, M., Histologic and histomorphometric analysis of the bone response to machined and sandblasted titanium implants: An experimental study in rabbits (1998) Int J Oral Maxillofac Implants, 13, pp. 805-810; Svehla, M., Morberg, P., Zicat, B., Bruce, W., Sonnabend, D., Walsh, W.R., Morphometric and mechanical evaluation of titanium implant integration: Comparison of five surface structures (2000) J Biomed Mater Res, 51, pp. 15-22; Gotfredsen, K., Nimb, L., Hjorting-Hansen, E., Jensen, J.S., Holmen, A., Histomorphometric and removal torque analysis for TiO 2-blasted titanium implants (1994) Clin Oral Implant Res, 5, pp. 202-206; Jones, F., Teeth and bones: Applications of surface science to dental materials and related biomaterials (2001) Surf Sci Rep, 42, pp. 75-205; Naji, A., Harnad, M.F., Cytocompatibility of two coating materials, amorphous alumina and silicon carbide, using human differentiated cell cultures (1991) Biomaterials, 12, pp. 690-694; Darvell, B.W., Samman, N., Luk, W.K., Clark, K.F., Tideman, H., Contamination of titanium casting by aluminium oxide blasting (1995) J Dent, 23, pp. 319-322; Placko, H.E., Mishra, S., Weimer, J.J., Lucas, L.C., Surface Characterization of titanium-based implant materials (2000) Int J Oral Maxillofac Implants, 15, pp. 355-363; Orsini, G., Assenza, B., Scarano, A., Piatelli, M., Piatelli, A., Surface analysis of machined versus sandblasted and acid-etched titanium implants (2000) Int J Oral Maxillofac Implants, 15, pp. 779-784; Gross, U., Strunz, V., The interface of various glasses and glass ceramics with a bony implantation bed (1985) J Biomed Mater Res, 19, pp. 251-271; Aparicio, C., Gil, F.J., Peraire, C., Padrós, A., Planell, J.A., Effect of size and material of the shot peening particles on adhesion and differentiation of osteoblast-like cell cultures on commercially pure titanium (1998) North Sea Biomaterials 1998 Proceedings, p. 137. , The Hague; Fontana, M.G., Green, N.D., (1978) Corrosion Engineering: Mc Graw Hill Series in Materials Science and Engineering, , USA: McGraw-Hill; Standard practice for laboratory immersion corrosion testing metals (1992) 1992 Annual Book of ASTM Standards, pp. 102-109. , vol. 03.02. Philadelphia: ASTM; Boukamp, B.A., (1989) Equivalent Circuit (EQUIVCRTPAS). User's Manual, , Enschede: University of Twente; Standard test method for conducting cyclic potentiodynamic polarization measurements for localized corrosion susceptibility of iron-nickel, or cobalt-based alloys (1992) 1992 Annual Book of ASTM Standards, pp. 231-235. , vol. 03.02. Philadelphia: ASTM; (1984) Norme FEPA des Grains de Corindon Electrofondu et de Carbure de Silicium Pour Abrasifs Agglomeres, , Paris: Fedération Européenne des Fabricants de Produits Abrasifs; Bohn, P., Qualitaty control of shot media by sieve analysis (1999) Shot Peener, 13, pp. 6-9; Mehelich, C.S., Van Kuiken, L., Woelfel, M.M., Shot peening (1995) ASM Metals Handbook. Vol. 5: Surface Engineering, 5, pp. 138-149. , USA: ASM International; Udupa, G., Singaperumal, M., Sirohi, R.S., Kothiyal, M.P., Characterization of surface topography by confocal microscopy: II. The micro and macro surface irregularities (2000) Meas Sci Technol, 11, pp. 315-329; Arnell, R.D., Davie, P.B., Halling, J., Whomes, T.L., (1991) Tribology: Principles and Design Applications, , London: Mac Millan; Udupa, G., Singaperumal, M., Sirohi, R.S., Kothiyal, M.P., Characterization of surface topography by confocal microscopy: I. Principles and the measurement system (2000) Meas Sci Technol, 11, pp. 305-314; Solar, R.J., Pollack, S.R., Korostoff, E., In vitro corrosion testing of titanium surgical implant alloys: An approach to understanding titanium release from implants (1979) J Biomed Mater Res, 13, pp. 217-250; Hoar, T.P., Mears, D.C., Corrosion resistant alloys in chloride solutions, materials for surgical implants (1966) Proc Royal Soc London Ser A, 294, pp. 486-510; Gonzalez, J.E.G., Mirza-Rosca, J.C., Study of the corrosion behaviour of titanium and some of its alloys for biomedical and dental implant applications (1999) J Electroanal Chem, 471, pp. 109-115; McDonald, J.R., (1987) Impedance Spectroscopy, , New York: Wiley; Aziz-Kerrzo, M., Conroy, K.G., Fenelson, A.M., Farrell, S.T., Breslin, C.B., Electrochemical studies on the stability and corrosion resistance of titanium-based implant materials (2001) Biomaterials, 22, pp. 1531-1539; Cai, Z., Nakajima, H., Woldu, M., Berglund, A., Bergman, M., Okabe, T., In vitro corrosion resistance of titanium made using different fabrication methods (1999) Biomaterials, 20, pp. 183-190; Kobayashi, M., Matsui, T., Murakami, Y., Mechanism of creation of compressive residual stresses by shot peening (1998) Int J Fatigue, 20, pp. 351-357; Prevey, P.S., X-ray diffraction characterization of residual stresses produced by shot peening (2001) Shot Peener, 15, pp. 4-8; Mueller, H.J., Greener, E.H., Polarization studies of surgical materials in Ringer's solution (1970) J Biomed Mater Res, 4, pp. 29-41; Speck, K.M., Fraker, A.C., Anodic polarization behavior of Ti-Ni and Ti-6Al-4V in simulated physiological solution (1980) J Dent Res, 59, pp. 1590-1595; Sousa, S.R., Barbosa, M.A., Corrosion resistance of titanium cp in saline physiological solutions with calcium phosphate and proteins (1993) Biomaterials, 14, pp. 287-294; Khan, M.A., Williams, R.L., Williams, D.F., In-vitro corrosion and wear of titanium alloys in the biological environment (1996) Biomaterials, 17, pp. 2117-2126; Ewers, G.J., Greener, E.H., The electrochemical activity of the oral cavity - A new approach (1985) J Oral Rehab, 12, pp. 469-476
Keywords: article; Blast finishing; chemical composition; chemistry; Corrosion; Dental implant; Dental Implants; Dental prostheses; Electric Potential; Electrochemical impedance spectroscopy; electrochemistry; impedance; materials testing; Particle Size; Polarization; priority journal; Shot blasting; Spectroscopy; stress; Surface roughness; Surface topography; Titanium; tooth implantation

Surface engineering of poly(DL-lactide) via electrostatic self-assembly of extracellular matrix-like molecules - Zhu, H.; Ji, J.; Tan, Q.; Barbosa, M.A.; Shen, J. (BiomacromoleculesBiomacromolecules, 2003)
We report the development of new biomacromolecule coatings on biodegradable biomaterials based on electrostatic assembly of extracellular matrix-like molecules. Poly(ethylene imine) (PEI) was employed to engineer poly(DL-lactide) (PDL-LA) substrate to obtain a stable positively charged surface. An extracellular matrix- (ECM-) like biomacromolecule, gelatin, was selected as the polyelectrolyte to deposit on the activated PDL-LA substrate via the electrostatic assemble technique. The extracellular matrix-like multilayer on the PDL-LA substrate was investigated by attenuated total reflection (ATR-FTIR), X-ray photoelectron spectrscopy (XPS), contact angle, and atomic force microscopy (AFM). The gradual buildup of the protein layer was investigated by UV-vis spectra, and it was further given a quantitative analysis of the protein layer on the PDL-LA substrate via the radioiodination technique. The stability of the protein layer under aqueous condition was also tested by the radiolabeling method. Chondrocyte was selected as the model system for testing the cell behavior and morphology on modified PDL-LA substrates. The chondrocyte test about cell attachment, proliferation, cell activity and cell morphology by SEM, and confocal laser scanning microscopy (CLSM) investigation on extracellular matrix-like multilayer modified PDL-LA substrate was shown to promote chondrocyte attachment and growth. Comparing conventional coating methods, polyelectrolyte multiplayers are easy and stable to prepare. It may be a good choice for the modification of 3-D scaffolds used in tissue engineering. These very flexible systems allow broad medical applications for drug delivery and tissue engineering.
Cited By (since 1996): 48Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm025773pPubMed ID: 12625735Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science/Eng., Zhejing University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: gelatin, 9000-70-8; polyethyleneimine, 74913-72-7; polylactide, 26680-10-4; poly(lactide), 26969-66-4; PolyestersTradenames: AXIOVERT 200, Zeiss; ESCA LAB 200A, VG; Radiance 2100, Biorad; Shimadzu UV-1201, Shimadzu; SPA 400, Seiko; Vectro 22, BrukerManufacturers: Biorad; Bruker; Seiko; Shimadzu; VG; ZeissReferences: Sittinger, M., Perka, C., Schutz, O., Haupl, T., Burmester, G.R.Z., (1999) Rheumatol., 58, pp. 130-135;Kim, B.S., Mooney, D.J., (1998) Trends Biotechnol., 16, p. 224; Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., (2000) Macromol. Rapid Commun., 21, p. 319; Ulman, A., (1996) Chem. Rev., 96, p. 1533; Sano, M., Lvov, Y., Kunitake, T., (1996) Annu. Rev. Mater. Sci., 26, pp. 153-187; Laschewsky, A., (1997) Eur. Chem. Chronicle ECC, 2, pp. 13-24; Chluba, J., Voegel, J.C., Decher, G., Erbacher, P., Schaaf, P., Ogier, J., (2001) Biomacromolecules., 2, pp. 800-805; Iler, R., (1966) J. Colloid Interface Sci., 21, p. 569; Fromhertz, P., (1980) Electron Microscopy at Molecular Dimension, p. 338. , Baumeister, W., Ed.; Springer-Verlag: Berlin; Lee, H., Kepley, L., Hong, H.-G., Mallouk, T., (1988) J. Am. Chem. Soc., 110, p. 618; Decher, G., Hong, J.-D., (1991) Ber. Bunsen-Ges., 95, p. 1430; Decher, G., (1997) Science, 227, p. 1232; Lvov, Y., Decher, G., Mohwald, H., (1993) Langmuir, 9, p. 481; Lvov, Y., Haas, H., Decher, G., Mohwald, H., Mikhailov, A., Mtchedlishvily, B., Morgunova, E., Vainshtein, B., (1994) Langmuir, 10, p. 4232; Kleinfeld, E., Ferguson, G., (1994) Science, 265, p. 370; Hong, J.-D., Lowack, K., Schmitt, J., Decher, G., (1993) Prog. Colloid Polym. Sci., 93, p. 98; Schmitt, J., Grunewald, T., Krajer, K., Pershan, P., Decher, G., Loshe, M., (1993) Macromolecules, 26, p. 7058; Korneev, D., Lvov, Y., Decher, G., Schmitt, J., Yarodaikin, S., (1995) Physica B, 214, p. 954; Iodine-125, a Guide to Radioiodination Techniques (1993), p. 64. , Amersham Life ScienceHwan, M.K., Sang, B.H., Moon, S.K., Jong, S.K., Goo, T.O., Dong, H.H., (1996) J. Pharmacol. Toxicol. Methods, 36, pp. 163-169; Adamson, A.W., Gast, A.P., (1997) Physical Chemsitry of Surfaces, pp. 27-28. , John Wiley & Sons: New York; Klagsbrum, M., (1979) Methods Enzymol., 58, p. 560; Blum, R.N., Wright, R.A., (1992) J. Gen. Intern. Med., 7, pp. 140-144; Okuda, M., Miura, I., Juji, F., Takashima, H., (1994) Int. Arch. Allergy Immunol., 104 (1 SUPPL. 1), pp. 6-8; Mosmann, T., (1983) J. Immunol. Methods, 65, pp. 55-63; Zund, G., Ye, Q., Hoerstrup, S.P., Schoeberlein, A., Schmid, A.C., Grunenfelder, J., Vogt, P., Turina, M., (1999) Eur. J. Cardio-thoracic Surg., 15, pp. 519-524; Risbud, M.V., Bhonde, M.R., Bhonde, R.R., (2001) J. Biomed. Mater. Res., 57, pp. 300-305; Strand, B.L., Ryan, T.L., In't Veld, P., Kulseng, B., Rokstad, A.M., Skjak-Brek, G., Espevik, T., (2001) Cell Transplant., 10, pp. 263-275; De Ceuninck, F., Gaufillier, S., Bonnaud, A., Sabatini, M., Lesur, C., Pastoureau, P., (2001) Biochem. Biophys. Res. Commun., 285, pp. 926-931; Bancel, S., Hu, W.S., (1996) Biotechnol. Prog., 12, pp. 398-402; Davids, S., (1993) Test Procedures for the Blood Compatibility of Biomaterials, pp. 287-330. , Kluwer Academic Publishers: Dordrecht
Keywords: animal cell; Animalia; Animals; article; Atomic force microscopy; biodegradability; biomaterial; cartilage cell; cell activity; cell adhesion; cell function; cell growth; cell proliferation; cell structure; Cells, Cultured; Chondrocytes; confocal laser microscopy; controlled study; Electron Probe Microanalysis; Electrostatics; extracellular matrix; Fourier transform infrared spectroscopy; gelatin; macromolecule; Macromolecules; Microscopy, Atomic Force; nonhuman; polyelectrolyte; Polyesters; Polyethyleneimine; Polyethylenes; polylactide; priority journal; protein analysis; protein stability; quantitative analysis; Rabbits; radioiodination; Scanning electron microscopy; Self assembly; Spectrophotometry, Ultraviolet; Spectroscopy, Fourier Transform Infrared; Surface charge; Surface engineering; Surface Properties; Tissue engineering; Ultraviolet spectroscopy; X ray photoelectron spectroscopy

Cellulose phosphates as biomaterials. In vivo biocompatibility studies - Fricain, J.C.; Granja, P.L.; Barbosa, M.A.; De Jéso, B.; Barthe, N.; Baquey, C. (BiomaterialsBiomaterials, 2002)
Femoral implantation of regenerated cellulose hydrogels revealed their biocompatibility, but a complete osseointegration could not be observed. Phosphorylation was therefore envisaged as the means to enhance cellulose bioactivity. In vitro studies showed that regenerated cellulose hydrogels promote bone cells attachment and proliferation but do not mineralize in acellular simulated physiological conditions. On the contrary, phosphorylated cellulose has shown an opposite behavior, by inducing the formation of a calcium phosphate layer in simulated physiological conditions, but behaving as a poor substrate for bone cells attachment and proliferation. In order to investigate the in vivo behavior of these materials, and assess the influence of mineralization induction ability vs. bone cells compatibility, unmodified and phosphorylated cellulose hydrogels were implanted in rabbits for a maximum period of 6 months and bone regeneration was investigated. Despite the difficulties arising from the retraction of cellulose hydrogels upon dehydration during the preparation of retrieved implants, histological observations showed no inflammatory response after implantation, with bone intra-spongious regeneration of cells and the integration of the unmodified as well as the phosphorylated cellulose implants. After a maximum implantation period of 6 months, histological observations, histomorphometry and the measurement of the amount of 45Ca incorporated in the surrounding tissue indicated a slightly better osseointegration of phosphorylated cellulose, although no significant differences between the two materials were found. © 2001 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 45Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(01)00152-1PubMed ID: 11791931Language of Original Document: EnglishCorrespondence Address: Granja, P.L.; Laboratório de Biomateriais, INEB-Inst. de Engenliaria Biomedica, Rua do Campo Alegre, 823-4150-180 Porto, Portugal; email: pgranja@ibmc.up.ptChemicals/CAS: Biocompatible Materials; Calcium Radioisotopes; Calcium, 7440-70-2; Cellulose, 9004-34-6; phosphocellulose, 9015-14-9References: Jochanan, H., Boss, M.D., Osseointegration (1999) J Long-Term Eff Med Impl, 9, pp. 1-10;Albrektsson, T., Hard tissue response (1998) Handbook of biomaterial properties, pp. 500-512. , Black J, Hastings G, editors. London, UK: Chapman & Hall; Hench, L.L., Bioactive materials: The potential for tissue regeneration (1998) J Biomed Mater Res, 41, pp. 511-517; Yaszemski, M.J., Payne, R.G., Hayes, W.C., Langer, R., Mikos, A.G., Evolution of bone transplantation: Molecular, cellular and tissue strategies to engineer human bone (1996) Biomaterials, 17, pp. 175-185; Hollinger, J., McAllister, B., Bone and its repair (1995) Bioceramics, 8, pp. 3-9. , Wilson J, Hench LL, Greenspon D, editors. FL, USA: Pergamon Press; Friedman, R.J., Black, J., Galante, J.O., Jacobs, J.J., Skinner, H.B., Current concepts in orthopaedic biomaterials and implant fixation (1993) J Bone Jt Surg, 75 A, pp. 1086-1109; Bakker, D., Grote, J.J., Vrouenraets, C.M.F., Hesseling, S.C., De Wijn, J.R., Van Blitterswijk, C.A., Bone-bonding polymer (polyactive™) (1990) Clinical implant materials, Advances in Biomaterials Series, 9, pp. 99-104. , Heimke G, Soltész U, Lee AJC, editors. Amsterdam, The Netherlands: Elsevier; LeGeros, R.Z., Calcium phosphate materials in restorative dentistry: A review (1988) Adv Dent Res, 2, pp. 164-183; Hastings, G.W., Mahmud, F.A., Intelligent orthopaedic materials (1993) J Intell Mat Syst Str, 4, pp. 452-456; Black, J., (1988) Orthopaedic biomaterials in research and practice, , New York, USA: Churchill Livingstone; Li, P., Ye, X., Kangasniemi, I., De Blieck-Hogervorst, J.M.A., Klein, C.P.A.T., De Groot, K., In vivo calcium phosphate formation induced by sol-gel-prepared silica (1995) J Biomed Mater Res, 29, pp. 325-328; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., Apatite coated on organic polymers by biomimetic process: Improvement in its adhesion to substrate by glow-discharge treatment (1995) J Biomed Mater Res, 29, pp. 349-357; Li, P., Ohtsuki, T., Kokubo, T., Nakanishi, K., Soga, N., Nakamura, T., Yamamuro, T., Process of formation of bone-like apatite layer on silica gel (1993) J Mater Sci: Mater Med, 4, pp. 127-131; Radin, S.R., Ducheyne, P., The effect of calcium phosphate ceramic composition and structure on in vitro behavior. II. Precipitation (1993) J Biomed Mater Res, 27, pp. 35-45; Puleo, D.A., Nanci, A., Understanding and controlling the bone-implant interface (1999) Biomaterials, 20, pp. 2311-2321; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., Attachment of cultured human bone cells to novel polymers (1999) J Biomed Mater Res, 44, pp. 1-11; Dalton, B.A., McFarland, C.D., Gengenbach, T.R., Griesser, H.J., Steele, J.G., Polymer surface chemistry and bone cell migration (1998) J Biomater Sci Polym Ed, 9, pp. 781-799; Scotchford, C.A., Cooper, E., Leggett, G.J., Downes, S., Growth of human osteoblast-like cells on alkenethiol on gold self-assembled monolayers: The effect of surface chemistry (1998) J Biomed Mater Res, 41, pp. 431-442; Adams, A.M., Soames, J.V., Searle, R.F., Ultrastructural changes in cultured human periodontal ligaments cells exposed to dental materials (1995) J Biomed Mater Res, 29, pp. 999-1004; Lamba, N.M.K., Baumgartner, J.A., Cooper, S.L., Cell-synthetic surface interactions (1998) Frontiers in tissue engineering, pp. 121-137. , Patrick CW, Mikos AG, McIntire LV, editors. Amsterdam, The Netherlands: Elsevier; Dalton, B.A., McFarland, C.D., Gengenbach, T.R., Griesser, H.J., Steele, J.G., Polymer surface chemistry and bone cell migration (1998) J Biomater Sci Polym Ed, 9, pp. 781-799; Healy, K.E., Thomas, C.H., Rezania, A., Kim, J.E., McKeown, P.J., Lom, B., Hockberger, P.E., Kinetics of bone cell organization and mineralization on materials with patterned surface chemistry (1996) Biomaterials, 17, pp. 195-208; Kasemo, B., Lausmaa, J., Material-tissue interfaces: The role of surface properties and processes (1995) Environ Health Perspect, 102, pp. 41-45; Von Recum, A.F., Van Kooten, T.G., The influence of micro-topography on cellular response and the implications for silicone implants (1995) J Biomater Sci Polym Ed, 7, pp. 181-198; Vogler, E.A., (1993) Interfacial chemistry in biomaterials science, Surfactant Science Series, vol. 49 (Wettability), 49, pp. 183-250. , Berg JC, editor. New York, USA: Marcel Dekker; Horbett, T.A., Weathersby, P.K., Adsorption of proteins from plasma to a series of hydrophilic-hydrophobic copolymers. I. Analysis with the in situ radionation technique (1981) J Biomed Mater Res, 15, pp. 403-423; Martson, M., Viljanto, J., Hurme, T., Saukko, P., Biocompatibility of cellulose sponge with bone (1998) Eur Surg Res, 30, pp. 426-432; Gross, U., Muller-Mai, C., Voigt, C., The tissue response on cellulose cylinders after implantation in the distal femur of rabbits (1992) Fourth World Biomaterials Congress, p. 192. , Berlin, Germany, April; Chauveaux, D., Barbie, C., Barthe, X., Baquey, C., Poustis, J., Biological behaviour of cellulosic materials after bone implantation: Preliminary results (1990) Clin Mater, 5, pp. 251-258; Ikada, Y., Biomedical applications of cellulose membranes (1989) Cellulose: structural and functional aspects, pp. 447-455. , Kennedy JF, Phillips GO, Williams PA, editors. Chichester, UK: Ellis Horwood; Miyamoto, T., Takahashi, S., Ito, H., Inagaki, H., Noishiki, Y., Tissue biocompatibility of cellulose and its derivatives (1989) J Biomed Mater Res, 23, pp. 125-133; Franz, G., Polysaccharides in pharmacy (1986) Adv Polym Sci, 76, pp. 1-30; Philipp, B., Bock, W., Schierbaum, F., Application of polysaccharides and their derivatives as supporting materials and auxiliary substances in medicine and nutrition (1979) J Polym Sci Polym Symp, 66, pp. 83-100; Galgut, P.N., Oxidized cellulose mesh. I. Biodegradable membrane in periodontal surgery (1990) Biomaterials, 11, pp. 561-564; Skoog, T., The use of periosteum and surgicel® for bone restoration in congenital clefts of the maxilla (1967) Scand J Plast Reconstr Surg, 1, pp. 113-130; Degenshein, G.A., Hurwitz, A., Ribacoff, S., Experience with regenerated oxidized cellulose (1963) NY State J Med, 63, pp. 2639-2643; Poustis, J., Baquey, C., Chauveaux, D., Mechanical properties of cellulose in orthopaedic devices and related environments (1994) Clin Mater, 16, pp. 119-124; Baquey, C., Barbié, C., More, N., Rouais, F., Poustis, J., Chauveaux, D., In vivo study of the biostability of a cellulose material (1992) Fourth World Biomaterials Congress, p. 365. , Berlin, Germany, April; Brie, J., Lafage, M.H., Chauveaux, D., Gueroult, J.M., Poustis, J., Baquey, C., La cellulose macroporeuse: Un matériau potentiellement utilisable pour le comblement osseux. Biomatériaux et organes artificiels (1992) Proceedings of the BIOMAT 92 Congress, , Bordeaux, France, November; Pommier, J.C., Poustis, J., Baquey, C., Chauveaux, D., Biocompatible, hydrophilic material. Method of manufacture and uses of same, , Fr Pat No. 8610331, 1986; Eur Pat No. 0256906 A1, 1987; US Pat No. 4904258, 1990; Barbié, C., Chauveaux, D., Baquey, C., Poustis, J., Pommier, J.C., Morlier, R., Ducassou, D., Évaluation des proprietés mecaniques de matériaux cellulosiques et perspectives d'application originales de ces matériaux en chirurgie orthopédique (1987) Calcif Tiss Biomaterials, Proceedings of the BIOMAT 87 Congress, pp. 319-325. , Bordeaux, France, December; Li, S., Liu, Q., De Wijn, J., Wolke, J., Zhou, B., De Groot, K., In-vitro apatite formation on phosphorylated bamboo (1997) J Mater Sci: Mater Med, 8, pp. 543-549; Mucalo, M.R., Yokogawa, Y., Toryiama, M., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, K., Growth of calcium phosphate on surface-modified cotton (1995) J Mater Sci: Mater Med, 6, pp. 597-605; Mucalo, M.R., Yokogawa, Y., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, K., Further studies of calcium phosphate growth on phosphorylated cotton fibres (1995) J Mater Sci: Mater Med, 6, pp. 658-669; Granja, P.L., Baquey, C., Pouységu, L., Bareille, R., De Jéso, B., Barbosa, M.A., (1996) Cellulose-based biomaterials for bone regeneration: Hemi-synthesis and characterisation. Polymers in Medicine and Surgery - PIMS'96, pp. 73-80. , Glasgow, UK; Granja, P.L., Barbosa, M.A., Pouységu, L., De Jéso, B., Baquey, C., Cellulose phosphates as biomaterials (1999) Frontiers in biomedical polymers applications 2, pp. 195-225. , Lancaster, PA, USA: Technomic Press; Granja, P.L., Pouységu, L., De Jéso, B., Rouais, F., Baquey, C., Barbosa, M.A., Cellulose phosphates as biomaterials. Mineralization of chemically modified regenerated cellulose hydrogels (2001) J Mater Sci: Mater Med, , submitted for publication; Granja, P.L., De Jéso, B., Bareille, R., Rouais, F., Baquey, C., Barbosa, M.A., (2001) Cellulose phosphates as biomaterials. In vitro biocompatibility studies, , submitted for publication; (1994) Évaluation biologique des dispositifs médicaux. Partie 6: Essais concernant les effets locaux après implantation; Wolf, E., Roser, K., Hahn, M., Wezkerling, H., Delling, G.G., Enzyme and immunohistochemistry on undecalcified bone and bone marrow biopsy after embedding in plastic: A new embedding method for routine application (1992) Virchow Archiv Pathol Anat Histopathol, 420, pp. 17-24; Van der Lubbe, H.B.M., Patchin, C., De Groot, K., A simple method for preparing thin (10 μm) histological sections of undecalcified plastic embedded bone with implant (1988) Saint Technol, 63, pp. 171-176; Daculsi, G., LeGeros, R.Z., Nery, E., Lynch, K., Transformation of biphasic calcium phosphate ceramics in vivo (1989) J Biomed Mater Res, 23, pp. 883-894; Charpak, G., Dominik, W., Zaganidis, N., Optical imaging of the spatial distribution of b-particles emerging from surfaces (1989) Proc Natl Acad Sci USA, 86, pp. 1741-1745; Charpak, G., Dominik, W., Fabre, J.P., Gaudaen, J., Sauli, F., Suzuki, M., Studies of light emission by continuously sensitive avalanche chambers (1988) Nucl Instrum Methods A, 269, pp. 142-148; Charpak, G., Dominik, W., Fabre, J.P., Santiard, J.C., Sauli, F., Solomey, N., Gaseous detectors with parallel electrodes and anode mesh planes (1979) Nucl Instrum Meth, 161, pp. 19-34; Daculsi, G., Passutti, N., Effect of the macroporosity for the osseous substitution of calcium phosphate ceramics (1990) Biomaterials, 11, pp. 86-87; Le Huec, J.C., Clément, D., Brouillaud, B., Barthe, N., Dupuy, B., Foliguet, B., Basse-Cathalinat, B., Evolution of the local calcium content around irradiated β-tricalcium phosphate ceramic implants: In vivo study in the rabbit (1998) Biomaterials, 19, pp. 733-738; Bloebaum, D., Bachus, K., Momberger, N., Hofmann, A., Mineral apposition rates of human cancellous bone at the interface of porous coated implants (1994) J Biomed Mater Res, 28, pp. 537-544; Gross, U.M., Hard tissue histology (1999) Handbook of biomaterials evaluation: scientific, technical and clinical testing of implant materials. 2nd Ed., pp. 689-719. , von Recum AF, editor. MI, USA: Edwards Brothers, Ann Arbor Science; Sakkers, R.J.B., Dalmeyer, R.A.J., De Wijn, J.R., Van Blitterswijk, C.A., Use of bone-bonding hydrogel copolymers in bone: An in vitro and in vivo study of expanding PEO-PBT copolymers in goat femora (2000) J Biomed Mater Res, 49, pp. 312-318; Elliot, J.C., (1994) Structure and chemistry of the apatites and other calcium orthophosphates, Studies in Inorganic Chemistry Series, 18. , Amsterdam, The Netherlands: Elsevier; Aoki, H., (1994) Medical applications of hydroxyapatite, , Tokyo, Japan: Ishiyaku EuroAmerica; Goodman, S., Aspenberg, P., Effects of mechanical stimulation on the differentiation of hard tissues (1993) Biomaterials, 14, pp. 563-569; Klemm, D., Philipp, B., Heinze, T., Heinze, U., Wagenknecht, W., (1998) Comprehensive cellulose chemistry, vol. 2, functionalization of cellulose, 2, pp. 133-140. , Weinheim, Germany: Wiley-VCH Verlag. Chapter 4; Touey, G.P., Kingsport, T., Preparation of cellulose phosphates, , US Pat No. 2759924, 1956; Hayashi, T., Biodegradable polymers for biomedical uses (1994) Prog Polym Sci, 19, pp. 663-702; Fricain, J.C., Baquey, C., Dupuy, B., Resorption of corals implanted in diffusion chambers (1995) J Mater Sci: Mater Med, 6, pp. 680-684
Keywords: animal experiment; Animal implantation; animal tissue; Animalia; Animals; article; Biocompatibility; Biocompatible Materials; biomaterial; Biomaterials; Bone; bone cell; bone mineralization; Bone Regeneration; Calcium; calcium 45; Calcium Compounds; calcium phosphate; Calcium Radioisotopes; cell adhesion; cell proliferation; Cells; Cellulose; Cellulose phosphate; Chemical modification; controlled study; Dehydration; histology; hydrogel; Hydrogels; implant; in vivo study; Inflammation; materials testing; Microscopy, Electron, Scanning; morphometrics; nonhuman; Oryctolagus cuniculus; Osseointegration; Phosphates; Phosphorylation; priority journal; Prostheses and Implants; rabbit; Rabbits; Regenerated cellulose hydrogels

Densification route and mechanical properties of Si 3N 4-bioglass biocomposites - Amaral, M.; Lopes, M.A.; Silva, R.F.; Santos, J.D. (BiomaterialsBiomaterials, 2002)
The processing route and the final microstructural and mechanical characteristics of a novel biomaterial composite are described. This new material is composed of 70 wt% Si 3N 4 ceramic phase and 30 wt% bioglass, the later performing as a liquid sintering aid system and simultaneously providing bioactivity characteristics to the composite. The conditions for fabrication of an almost fully dense material (∼98% of relative density) were pursued. Optimised parameters were 1350°C-40min-30 MPa by hot-pressing technique. The very fast densification rate of the process avoided the crystallisation of the bioglass intergranular phase and therefore its intrinsic properties were maintained. Also, the large amount of glassy phase assured the densification by liquid phase assisted grain rearrangement without Si 3N 4 phase transformation. The final mechanical properties of the Si 3N 4-bioglass were as follows: fracture toughness, K IC = 4.4 MPa m 1/2; Vickers hardness, H V = 10.3 GPa; Young's modulus, E = 197 GPa; bending strength, σ R = 383 MPa; Weibull modulus, m = 8.3. These values provide an attractive set of properties among other bioactive materials, namely by upgrading the main drawback of bioceramics and bioglasses for high-load medical applications, which is the lack of satisfactory fracture toughness. © 2001 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(01)00194-6PubMed ID: 11771704Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Secção de Materiais, Fac. Eng. da Univ. do Porto (FEUP), Universidade do Porto, Rua Roberto Frias, 4200-465 Porto Cedex, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Biocompatible Materials; Bioglass; Ceramics; Composite Resins; Silicon Compounds; silicon nitride, 12033-89-5Tradenames: BioglassReferences: Kue, R., Sohrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteacalcin production by human osteablast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201;Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon Nitride-Bioglass®45S5 composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Gazzara, C.P., Messier, D.R., Determination of phase content of Si 3N 4 by X-ray diffraction analysis (1997) Am Ceram Soc Bull, 56 (9), pp. 777-780; Niihara, K., Morena, R., Hasselman, D.P., Evaluation of K IC of brittle solids by the indentation method with low crack-to-indent ratios (1982) J Mater Sci Lett, 1, pp. 13-16; Standard test method for dynamic Young's modulus, shear modulus, and Poisson's ratio for advanced ceramics by impulse excitation of vibration; Kingery, W.D., Densification during sintering in the presence of a liquid phase. I. Theory (1959) J Appl Phys, 30 (3), pp. 301-306; Ziegler, G., Heinrich, J., Wötting, G., Review: Relationships between processing, microstructure and properties of dense and reaction-bonded silicon nitride (1987) J Mater Sci, 22, pp. 3041-3086; Filho, O.P., LaTorre, G.P., Hench, L.L., Effect of crystallization on apatite-layer formation of bioactive glass 45S5 (1996) J Biomed Mater Res, 30, pp. 509-514; Evans, A.G., Wilshaw, T.R., Quasi-static solid particle damage in brittle solids I. Observations, analysis and implications (1976) Acta Metall, 24, pp. 939-956; Yamamuro, T., Reconstruction of the iliac crest with bioactive glass-ceramic prostheses (1990) Handbook of Bioactive Ceramics, 1, pp. 335-342. , Yamamuro T, Hench LL, Wilson J, editors. Boca Raton: CRC Press; Hench, L.L., Bioceramics (1998) J Am Ceram Soc, 81, pp. 1705-1728; Ravaglioli, A., Krajewski, A., (1992) Bioceramics - materials, properties and applications, , London: Chapman & Hall; Kong, Y.M., Kim, S., Kim, H.E., Reinforcement of hydroxyapatite bioceramic by addition of ZrO 2 coated with Al 2O 3 (1999) J Am Ceram Soc, 82 (11), pp. 963-968; Ducheyne, P., Marcolongo, M., Schepers, E., Bioceramic composites (1993) An Introduction to Bioceramics. Advanced series in ceramics, 1, pp. 281-297. , Hench L, Wilson J, editors. Singapore: World Scientific. Chapter 15
Keywords: 3N; 4-bioglass composites; article; Bending strength; Biocompatible Materials; biomaterial; Biomaterial composites; Biomaterials; Ceramic materials; ceramics; Composite Resins; Crystallization; Densification; Densification behaviour; density; Elastic moduli; Fracture toughness; glass; hardness; heat; Hot pressing; Hot-pressing; Kinetics; Mechanical properties; phase transition; Phase transitions; priority journal; Si; Silicon compounds; silicon derivative; Sintering; strength; Stress, Mechanical; technique; Thermodynamics; Vickers hardness testing; X-Ray Diffraction; young modulus

Electrochemical and microstructural studies of tantalum and its oxide films for biomedical applications in endovascular surgery - Silva, R.A.; Walls, M.; Rondot, B.; Da Cunha Belo, M.; Guidoin, R. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2002)
The most popular coronary stents are made of 316L stainless steel and self-expandable Nitinol. Nevertheless, Ta has already been used to make stents for endovascular surgery and may constitute a good alternative to the other materials because of its higher corrosion resistance and radio-opacity property, which may facilitate the follow-up of stent catheterization. The characterization of Ta and its natural passive oxide films has been performed in a 0.15M NaCl solution (simulated body fluid - SBF) using anodic polarizations, electrochemical impedance spectroscopy and photoelectrochemical techniques. Changes in microstructure have been observed by atomic force microscopy (AFM). Polarization curves show the existence of a current density increase between 1.40 and 1.80V. Bode complex plots show that some perturbation of the film occurred in this potential interval which may be associated with a decrease in polarization resistance, Rp, indicating that the film may be less resistant to corrosive attack. Mott-Schottky capacity measurements show that the density of donors, Nd, varies with polarization. The optical band gap, E g, which is equal to 4.1 eV did not show variations in our experiments. The localized formation on the electrode surface, in the above potential interval of a Ta compound (possibly an oxide-hydroxide) was observed by AFM, and this may explain the appearance of the current density peak and capacity behavior at those potentials. © 2002 Kluwer Academic Publishers.
Cited By (since 1996): 17Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1014779008598Language of Original Document: EnglishCorrespondence Address: Silva, R.A.; CIEA/ISEP, Rua S. Tomé, 4200 Porto, PortugalReferences: Sigwart, U., Puel, J., Mirkovitch, V., Joffre, F., Kappenberger, L., (1987) New Engl. J. Med., 316 (12), pp. 701-706;Serruys, P.W., De Jaegere, P., Kiemeneij, F., Macaya, C., Heindrickx, W., (1994) New Engl. J. Med., 331 (8), pp. 489-495; Fischman, D.L., Leon, M.B., Baim, D.S., Schatz, R.A., Savage, M.P., Penn, I., (1994) New Engl. J. Med., 331 (8), pp. 496-501; Serruys, P.W., Emanuelsson, H., Van Der Giessen, W., Lunn, A.C., Kiemeney, F., Macaya, C., (1996) Circulation, 93 (3), pp. 412-422; Cohen, D.J., Breall, J.A., Ho, K.K., Kuntz, R.E., Goldman, L., Baim, D.S., (1995) New Engl. J. Med., 92, pp. 1859-1874; Cohen, D.J., Breall, J.A., Ho, K.K., Weintraub, R.M., Kuntz, R.E., Weistein, M.C., (1993) J. Amer. Coll. Cardiology, 22 (4), pp. 1052-1059; Cohen, D.J., Krumholz, H.M., Sukin, C.A., Ho, K.K., Siegrist, R.B., Cleman, M., (1995) Circulation, 92, pp. 2480-2487; Colombo, A., Hall, P., Nakamura, S., Almagor, Y., Maiello, L., Martini, O., (1995) Circulation, 91 (6), pp. 1676-1688; Goy, J.J., Eeckhout, E., Stauffer, J.C., Vogt, P., Kappenberger, L., (1995) Catheter. Cardiov. Diag., 34, pp. 128-132; Hamasaki, N., Nosaka, H., Nobuyoshi, M., (1995) J. Amer. Coll. Cardiol., 239 A (SPEC. ISSUE); Hamm, C.W., Beythien, C., Sievert, H., Langer, A., (1995) Amer. Heart J., 129 (3), pp. 423-429; Kiemeneij, F., Hofland, J., Laarman, G.J., Hupkens Van der Elst, D., Van der Lubbe, H., (1995) Catheter. Cardiov. Diag., 35, pp. 301-308; Mehan, V.K., Kaufmann, U., Urban, P., Chatelain, P., Meier, B., (1995) Catheter. Cardiov. Diag., 34, pp. 122-127; Robinson, N.M., Thomas, M.R., Jewitt, D.E., Wainwright, R.J., (1995) Cardiology, 7 (6), pp. 156-164; Stauffer, J.C., Eeckhout, E., Goy, J.J., Nacht, C.A., Vogt, P., Kappenberger, C., (1995) J. Invas. Cardiol., 7 (8), pp. 221-227; Webb, J., Stertzer, S., Ahmad, T., Carere, R., Mercier, B., Dodek, A., (1996) Catheter. Cardiov. Diag., 37, pp. 120-124; Schöneberger, A.A., Schmidt, K., (1996) New Engl. J. Med., 335 (15), p. 1160; Priestley, K.A., Clague, J.R., Buller, N.P., Sigwart, U., (1996) Europ. Heart J., 17 (3), pp. 438-444; Silva, R.A., Marques, M.A., Silveira, A., Walls, M., Rondot, B., Guidoin, R., (1998) Proceedings of the 14th European Conference on Biomaterials, p. 37. , The Hague, September, edited by the Dutch Society for Biomaterials; Pypen, C.M.J.M., Plenk H., Jr., Ebel, M.F., Svagera, R., Verenisch, J., (1997) J. Mater. Sci. Mater. Med., 8, pp. 781-784; Park, J.B., (1984) Biomaterials Science and Engineering, p. 217. , New York, Plenum Press; Jonhson, P.F., Bernstein, J.J., Hunter, G., Dawson, W.W., Hench, L.L., (1977) J. Biomed. Mater. Res., 11, pp. 637-656; Black, J., (1994) Clin. Mater., 16, pp. 167-173; Stackpool, G.J., Kay, A.B., Morton, P., Harvey, E.J., Tanzer, M., Bone, J.D., (1995) Proceedings of Combined Orthopaedic Research Societies Meeting, p. 45. , edited by Orthopaedic Research Society (Rider Dickerson Inc., Chicago); Macagno, V.A., Schultze, J.W., (1984) J. Electroanal. Chem., 180, pp. 157-170; Schultze, J.W., Macagno, V.A., (1986) Electrochim. Acta, 31, pp. 355-363; Kerrec, O., Devilliers, D., Groult, H., Chemla, M., (1995) Electrochim. Acta, 40, pp. 719-724; Degryse, R., Gomes, W.P., Cardon, F., Vennik, J., (1975) J. Electrochem. Soc., 122, p. 711; Gartner, W.W., (1959) Phys. Rev., 116, p. 84; Butler, M.A., (1977) J. Appl. Phys., 48, p. 1914; Ginley, D.S., Butler, M.A., (1977) J. Appl. Phys., 48, p. 2019; Clechet, P., Martin, J.-R., Olier, R., Vallouy, C., (1976) C. R. Acad. Sci. Paris, 282, pp. 887-890; Lohrengel, M.M., (1994) Electrochim. Acta, 39, pp. 1265-1271
Keywords: article; Atomic force microscopy; body fluid; coronary stent; Corrosion; Corrosion resistance; Current density; Electric Potential; electrochemical analysis; Electrochemical impedance spectroscopy; electrochemistry; electrode; endovascular surgery; Energy gap; film; heart catheterization; hydroxide; Materials science; metal oxide; Metallic films; Microstructure; nitinol; optical density; Oxide films; Polarization; priority journal; simulation; sodium chloride; Stainless steel; structure analysis; Surgery; Tantalum; Tantalum compounds; tantalum oxide; unclassified drug

A novel urethane containing copolymer as a surface modification additive for blood contact materials - Ji, J.; Barbosa, M.A.; Feng, L.; Shen, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2002)
Surface modification to develop a biomolecules-presenting surface is of interest, both from a scientific and an industrial point of view. In this research, a penta-block-coupling polymer of warfarin-PEO-MDI-PEO-warfarin was specially designed as the surface modifying additive (SMA). The warfarin-modified polyurethane surfaces were then prepared by dip-coating method. Attenuated total reflection fourier transform infra-red (ATR-FTIR) spectra revealed that the urethane segments in the SMA could penetrate into the hard block of segmented polyurethane (SPU) via intermolecular hydrogen bonds. The X-ray photoelectron spectroscopy (XPS) results indicated that the intermolecular hydrogen bonds were strong enough to form stable warfarin-PEO composite surfaces in an aqueous environment. Fibrinogen and albumin adsorption onto unmodified and SMA-modified SPU was investigated by the 125l-labeled method. The surface for attracting and reversibly binding albumin, which was proved to suppress the platelet adhesion and prolong the clotting time, has been developed by the simple coating of the novel SMA in SPU. © 2002 Kluwer Academic Publishers.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1015789726455Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, HangZhou 310027, China; email: jianji@mail.hz.zj.cnReferences: Elbert, D., Hubbell, J., (1996) Annu. Rev. Mater., p. 365;Munro, M., Quattrone, A., Ellsworth, S., Kulkarni, P., Eberhart, R., (1981) Trans. Am. Soc. Artif. Intern. Organs., p. 499; Park, K., Okano, T., Nojiri, C., Kim, S., (1988) J. Biomed. Mater. Res., p. 977; Han, D., Jeong, S., Kim, Y., Min, B., Cho, H., (1991) J. Biomed. Mater. Res., p. 561; Ji, J., Feng, L.X., Barbosa, M.A., (2001) Biomaterials, 22, p. 3015; Ji, J., Feng, L.X., Qiu, Y.X., Yu, X.J., Barbosa, M.A., (2000) J. Colloid Interfac. Sci., 15, p. 224; (2000) J. Colloid Interfac. Sci., 15, pp. 255-260; Ji, J., Feng, L.X., Qiu, Y., Yu, X., (2000) Polymer, p. 3713; Ishihara, K., Hanyuda, H., Nakabayashi, N., (1995) Biomaterials, p. 873; Amiji, M., Park, K., (1993) J. Biomater. Sci. Polym. Ed., p. 217; Lamba, N., Woodhouse, K., Cooper, S.L., (1998) Polyurethanes in Biomedical Applications, p. 43. , CRC Press, New York; Nelson, K.D., Eisenbaumer, R., Pomerantz, M., Eberhart, R.C., (1996) ASAIO Journal, p. 884; Wang, D.A., Ji, J., Feng, L.X., (2000) Macromol. Chem. Phys., p. 1574; Wang, D.A., Ji, J., Feng, L.X., (2000) Macromolecules, p. 8472; Brash, J.L., Davidson, V.J., (1976) Thromb. Res., p. 249; Qiu, Y.X., Yu, X.J., Feng, L.X., (1992) Markromol. Chem., p. 1377; Okkema, A.Z., Grasel, T.G., Zdrahala, R.J., Solomon, D.D., Cooper, S.L., (1989) J. Biomater. Sci. Polym. Ed., p. 43; Takahara, A., Jujo, A.N., Kajiyama, N.T., (1989) J. Biomater. Sci. Polym. Ed., p. 17
Keywords: Adhesion; Adsorption; Albumin; article; Attenuation; biomaterial; Block copolymers; Blood; blood clotting time; Chemical modification; Coatings; copolymer; fibrinogen; Fourier transform infrared spectroscopy; human; human cell; hydrogen bond; Hydrogen bonds; infrared spectroscopy; iodine 125; material coating; Polyurethanes; priority journal; Surface modifying additives (SMA); surface property; Surface treatment; synthesis; thrombocyte adhesion; urethan; warfarin; X ray photoelectron spectroscopy

Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells - Amaral, M.; Costa, M.A.; Lopes, M.A.; Silva, R.F.; Santos, J.D.; Fernandes, M.H. (BiomaterialsBiomaterials, 2002)
The in vitro osteocompatibility of a novel Si 3N 4-bioglass composite (70-30% weight proportion) with improved mechanical properties (fracture toughness=4.4MPam 1/2; bending strength=383±47MPa) is reported. Immersion of the composite samples in culture medium (30min to 7 days) resulted in rapid protein adsorption to the surface and, also, dissolution of the intergranular phase of bioglass (time-dependent process) with the formation of different size cavities. "As-received" and pre-treated material samples presented a similar behaviour concerning the proliferation of MG63 osteoblast-like cells, evaluated during a 5-day culture period. Seeded materials showed a higher cell growth rate as compared to cultures performed on the standard plastic culture plates. To assess the osteogenic potential of the composite, "as-received" material samples were seeded with human bone marrow cells and cultured for 35 days in experimental conditions that favour the development of the osteoblastic phenotype. The cell adhesion process was similar to that observed in control cultures. Cells successfully adapted to the irregularities of the surface and were able to grow towards inside the cavities; in addition, osteogenic differentiation occurred with the formation of abundant cell-mediated mineralised deposits. Results suggest that this Si 3N 4-bioglass composite seems to be a promising candidate for high-stress medical applications. © 2002 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00249-1PubMed ID: 12361631Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Dr Manuel Pereira da Silva, 4200-393 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium, 7440-70-2; Phosphorus, 7723-14-0; Silicon Compounds; silicon nitride, 12033-89-5References: Amaral, M., Lopes, M.A., Silva, R.F., Santos, J.D., Densification route and mechanical properties of Si 3N 4-bioglass biocomposites (2002) Biomaterials, 23, pp. 857-862;Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon Nitride - Bioglass ® 45S5 composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Maniatopoulos, C., Sodek, J., Melcher, A., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblastic phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 43, pp. 213-221; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Stein, G.S., Lian, J.B., Stein, J.L., Van Wijnem, A.J., Frenkel, B., Montecino, M., Mechanisms regulating osteoblast proliferation and differentiation (1996) Principles of bone biology, pp. 69-86. , J.P. Bilizikian, L.G. Raisz, & G.A. Rodan. New York: Academic Press; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralization in serially passaged human alveolar bone cells (1997) J Mater Sci: Mater Med, 8, pp. 61-65; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: Effect of ascorbic acid β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Costa, M.A., Fernandes, M.H., Long-term effects of parathyroid hormone, 1,25-dihydroxyvitamin D3 and dexamethasone on the cell growth and functional activity of human osteogenic alveolar bone cell cultures (2000) Pharmacol Res, 42, pp. 345-353; Coelho, M.J., Trigo Cabral, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in DMEM (2000) Biomaterials, 21, pp. 1087-1094; Aubin, J.E., Liu, F., The osteoblastic lineage (1996) Principles of bone biology, pp. 51-67. , J.P. Bilizikian, L.G. Raisz, & G.A. Rodan. New York: Academic Press; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro bioactivity evatuation (1999) J Biomed Mater Res, 45, pp. 376-383; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Ca, P-rich layer formed on high-strenght bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 331-343; Daculsi, G., Legeros, R.Z., Heughebaert, M., Barbieux, I., Formation of carbonato-apatite crystals after implantation of calcium phosphate ceramics (1990) Calcif Tissue Int, 46 (1), pp. 20-27; Neo, M., Nakamura, T., Ohtsuki, C., Kokubo, T., Yamamuro, T., Apatite formation on three kinds of bioactive material at an early stage in vivo: A comparative study by transmission electron microscopy (1993) J Biomed Mater Res, 27, pp. 999-1006; Bagambisa, F.B., Joos, U., Schilli, W., Mechanisms and structure of the bond between bone and hydroxyapatite ceramics (1993) J Biomed Mater Res, 27, pp. 1047-1055; Bagambisa, F.B., Kappert, H.F., Schilli, W., Interfacial reactions of osteoblast to dental and implant materials (1994) J Oral Maxillofac Surg, 52, pp. 52-56; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., Initial bone matrix formation at the hydroxyapatite interface (1995) J Biomed Mater Res, 29 (1), pp. 89-99; Hulshott, J.E.G., Van Kijk, K., De Ruijter, J.E., Rietveld, F.J.R., Ginsel, L.A., Jansen, J.A., Interfacial phenomena: An in vitro study of the effect of calcium phosphate (Ca-P) ceramic on bone formation (1998) J Biomed Mater Res, 40, pp. 464-474; De Santis, D., Guerriero, C., Nocini, P.F., Vangersbock, A., Richard, G., Gotte, P., Armato, U., Adult human bone cells from jaw bones cultured on plasma-sprayed or polished surfaces of titanium or hydroxyapatite discs (1996) J Mater Sci Mater Med, 7, pp. 21-28; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., In vitro growth of human adult bone-derived cells on hydroxyapatite plasma-sprayed coatings (1997) J Biomed Mater Res, 34, pp. 247-259; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblastic-like human bone marrow cells on a glass reinforced hydroxyapatite plasma-speayed coating (1999) J Mater Sci: Mater Med, 10, pp. 567-576; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma sprayed coatings (2000) Biomaterials, 21, pp. 813-820; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and double-layer HA/CaO-P 2O 5 glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behaviour (2001) J Mater Sci: Mater Med, 7, pp. 628-638; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Direct and indirect effects of P 2O 5-glass reinforced hydroxyapatite composites on the growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Gwynn, I.A.P., Cell biology at interfaces (1994) J Mater Sci Mater Med, 5, pp. 357-360; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; KirkPatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., The cell and molecular biological approach to biomaterial research: A perspective (1997) J Mater Sci Mater Med, 8, pp. 131-141; Verrier, S., Bareille, R., Rovira, A., Dard, M., Amedee, J., Human osteoprogenitor responses to orthopaedic implant: Mechanism of cell attachment and cell adhesion (1996) J Mater Sci Mater Med, 7, pp. 46-51; Dee, K.C., Rueger, D.C., Andersen, T.T., Bizios, R., Conditions which promote mineralization at the bone-implant interface: A model for in vitro study (1996) Biomaterials, 17, pp. 209-215; Anseme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., Qualitative and quantitative study of human osteoblast adhesion on materials with various surface roughnesses (2000) J Biomed Mater Res, 49, pp. 155-166; Diniz, M.G., Soares, G.A., Coelho, M.J., Fernandes, M.H., Surface topography modulates the osteogenesis in human bone marrow cell cultures grown on titanium samples prepared by a combination of mechanical and acid treatments (2002) J Mater Sci: Mater Med, 13, pp. 421-432; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Min, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Min, 17, pp. 15-29
Keywords: 3N; 4-bioglass composite; Adhesion; Adsorption; alkaline phosphatase; article; Biocompatibility; Bioglass; Biomaterials; bone marrow cell; Bone Marrow Cells; Calcium; cell adhesion; Cell Culture Techniques; cell differentiation; Cell Division; cell growth; cell proliferation; composite material; controlled study; culture medium; Dissolution; glass; Growth kinetics; human; Human bone marrow cells; human cell; Humans; immersion; in vitro study; Mechanical properties; MG63 osteoblast-like cells; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; Osteocompatibility; Osteogenic differentiation; phenotype; phosphorus; priority journal; Proteins; rigidity; Si; Silicon compounds; silicon derivative; surface property; tensile strength; Time Factors

Silicon and iron levels in tissues of animals treated with a "ferrimagnetic ceramic" with oncotherapeutic potential (anti-tumor) value - Almeida, T.; Soares, M.E.; Cavalheiro, J.; Bastos, M.D.L. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 2002)
The stability in a biological environment of an injectable cement with oncotherapeutic potential - consisting of a glass powder of SiO 2 (35.6%), CaO (42.4%), P 2O 5 (17%), Na 2O (5%) and 30% of its weight of Fe 3O 4 dissolved in (NH 4) 2HPO 4 plus NH 4H 2PO 4 - was evaluated referring to the release of silicon and iron. The experimental model was the rat, and organs (liver, kidney, spleen, lung, heart, and brain) of the implanted and control animals were collected for quantification of these elements by electrothermal atomization atomic absorption spectrometry methods. In most of the analysed organs no significant difference in the contents of silicon and iron between the implanted and the control animals was found.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JTEBFdoi: 10.1016/S0946-672X(02)80054-2PubMed ID: 12530589Language of Original Document: EnglishCorrespondence Address: Bastos, M.D.L.; Toxicology Department, Faculty of Pharmacy, University of Porto, Rua Aníbal Cunha 164, 4050 Porto, PortugalChemicals/CAS: calcium oxide, 1305-78-8; iron, 14093-02-8, 53858-86-9, 7439-89-6; phosphorus pentoxide, 1314-56-3; silicon dioxide, 10279-57-9, 14464-46-1, 14808-60-7, 15468-32-3, 60676-86-0, 7631-86-9; silicon, 7440-21-3; Biocompatible Materials; Ceramics; Iron, 7439-89-6; Silicon, 7440-21-3; Tissue ExtractsReferences: Rofstad, E.K., Brustad, T., Primary and secondary cell death in human melanoma xenografts following hyperthermic treatment (1986) Cancer Res., 46, pp. 355-361;Nishimura, Y., Shibamoto, Y., Jo, S., Akuta, K., Hiraoka, M., Takahashi, M., Abe, M., Relationship between heat-induced vascular damage and thermosensitivity in four mouse tumors (1988) Cancer Res., 48, pp. 7226-7230; Brown, S.L., Hunt, J.W., Hill, R.P., Differential thermal sensitivity of tumour and normal tissue microvascular response during hyperthermia (1992) Int. J. Hyperthermia, 8, pp. 501-514; Dudar, T.E., Jain, R.K., Differential response of normal and tumor microcirculation to hyperthermia (1984) Cancer Res., 44, pp. 605-612; Hill, S.A., Smith, K.A., Denekamp, J., Reduced thermal sensitivity of the vasculature in a slowly growing tumour (1989) Int. J. Hyperthermia, 5, pp. 359-370; Bicher, H.I., Hetzel, F.W., Sandhu, T.S., Frinak, S., Vaupel, P., O'Hara, M.D., O'Brien, T., Effects of Hyperthermia on normal and tumor microenvironment (1980) Radiology, 137, pp. 523-530; Song, C.W., Kang, M.S., Rhee, J.G., Levitt, S.H., The effect of hyperthermia on vascular function, pH, and cell survival (1980) Radiology, 137, pp. 795-803; Emami, B., Song, C.W., Physiological mechanisms in hyperthermia: A review (1984) Int. J. Radiation Oncology Biol. Phys., 10, pp. 289-295; Cavalheiro, J., Vasconcelos, M., Afonso, A., Branco, R., Ferrimagnetic and biocompatible cement for tumours thermotherapy (1996) Bioceramics, 9, pp. 243-246; Coury, A.J., Levy, R.J., McMillin, C.R., Pathak, Y., Ratner, B.D., Schoen, F.J., Williams, D.F., Williams, R.L., Degradation of materials in the biological environment (1996) Biomaterials Science, pp. 243-260. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (Eds). Academic Press, San Diego; Williams, D.F., Williams, R.L., Degradative effects of the biological environment on metals and ceramics (1996) Biomaterials Science, pp. 260-267. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (Eds). Academic Press, San Diego; Van Dyck, K., Robberecht, H., Van Cauwenbergh, R., Deelstra, H., Arnaud, J., Willemyns, L., Benijts, F., Uytterhoeven, M., Spectrometric determination of silicon in food and biological samples: An interlaboratory trial (2000) J. Anal. At. Spectrom., 15, pp. 735-741; Adler, A.J., Etzion, Z., Berlyne, G.M., Uptake, distribution, and excretion of 31silicon in normal rats (1986) Am. J. Physiol., 251, pp. E670-E673; Beattie, J.H., Avenell, A., Trace element nutrition and bone metabolism (1992) Nutrition Res. Rev., 5, pp. 167-188; Robinson, C.H., Lawler, M.R., Mineral elements (1982) Normal and Therapeutic Nutrition, 16 th Edition, pp. 131-160. , Robinson CH, Lawler MR (Eds). Macmillan Publishing Co., Inc., New York, Collier Macmillan Publishers, London; Sorond, F.A., Ratan, R.R., Ironing-out mechanisms of neuronal injury under hypoxic-ischemic conditions and potential role of iron chelators as neuroprotective agents (2000) Antioxid. Redox Signal, 2, pp. 421-436; Bonkovsky, H.L., Lambrecht, R.W., Iron-induced liver injury (2000) Clin. Liver Dis., 4, pp. 409-429; Bartfay, W.J., Bartfay, E., Iron-overload cardiomyopathy: Evidence for a free radical-mediated mechanism of injury and dysfunction in a murine model (2000) Biol. Res. Nurs., 2, pp. 49-59; Kang, J.L., Pack, I.S., Lee, H.S., Castranova, V., Enhancement of nuclear factor-KB activation and protein tyrosine phosphorylation by a tyrosine phosphatase inhibitor, pervanadate, involves reactive oxygen species in silica-stimulated macrophages (2000) Toxicology, 151, pp. 81-89
Keywords: animal model; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Biocompatible Materials; calcium oxide; cancer therapy; cement; ceramics; controlled study; experimental model; Ferrimagnetic ceramic; heat; Humans; implant; Iron; Magnetics; materials testing; Neoplasms; nonhuman; Oncotherapy; phosphorus pentoxide; powder; priority journal; Prostheses and Implants; rat; Rats; Reproducibility of Results; Silicon; silicon dioxide; tissue distribution; Tissue Extracts

Soluble silk-like organic matrix in the nacreous layer of the bivalve Pinctada maxima: A new insight in the biomineralization field - Pereira-Mouriès, L.; Almeida, M.-J.; Ribeiro, C.; Peduzzi, J.; Barthélemy, M.; Milet, C.; Lopez, E. (European Journal of BiochemistryEur. J. Biochem., 2002)
Nacre organic matrix has been conventionally classified as both 'water-soluble' and 'water-insoluble', based on its solubility in aqueous solutions after decalcification with acid or EDTA. Some characteristics (aspartic acid-rich, silk-fibroin-like content) were specifically attributed to either one or the other. The comparative study on the technique of extraction (extraction with water alone vs. demineralization with EDTA) presented here, seems to reveal that this generally accepted classification may need to be reconsidered. Actually, the nondecalcified soluble organic matrix, extracted in ultra-pure water, displays many of the characteristics of what until now has been called 'insoluble matrix'. We present the results obtained on this extract and on a conventional EDTA-soluble matrix, with various characterization methods: fractionation by size-exclusion and anion-exchange HPLC, amino acid analysis, glycosaminoglycan and calcium quantification, SDS/PAGE and FTIR spectroscopy. We propose that the model for the interlamellar matrix sheets of nacre given by Nakahara [In: Biomineralization and Biological Metal Accumulation, Westbroek, P. & deJong, E.W., eds, (1983) pp. 225-230. Reidel, Dordrecht, Holland] and Weiner and Traub [Phil. Trans. R. Soc. Lond. B (1984) 304, 425-434] may no longer be valid. The most recent model, proposed by Levi-Kalisman et al. [J. Struct. Biol. (2001) 135, 8-17], seemed to be more in accordance with our findings.
Cited By (since 1996): 58Export Date: 21 November 2012Source: ScopusCODEN: EJBCAdoi: 10.1046/j.1432-1033.2002.03203.xPubMed ID: 12383258Language of Original Document: EnglishCorrespondence Address: Lopez, E.; Lab. de Physiologie Gen. et Comparee, UMR CNRS 8572, Museum National d'Histoire Naturelle, 7 rue Cuvier, 75231 Paris Cedex 05, France; email: lopez@mnhn.frChemicals/CAS: Amino Acids; Calcium, 7440-70-2; Edetic Acid, 60-00-4; Extracellular Matrix Proteins; Glycosaminoglycans; Insect Proteins; SilkReferences: Crenshaw, M.A., The soluble matrix from Mercenaria mercenaria shell (1972) Biomineralization, 6, pp. 6-11;Krampitz, G., Engels, J., Cazaux, C., Biochemical studies on water-soluble proteins and related components of gastropod shells (1976) The Mechanisms of Mineralization in the Invertebrates and Plants, pp. 175-190. , Watabe, N. & Wilbur, K.M., eds. The Barush B.W. Library in Marine Science no. 5, The University of South Carolina Press, Columbia; Weiner, S., Traub, W., Lowenstam, H.A., Organic matrix in calcified exoskeletons (1983) Biomineralization and Biological Metal Accumulation, pp. 205-224. , Westbroek, P. & deJong, E.W., eds. Reidel, Dordrecht, Holland; Keith, J., Stockwell, D., Ball, D., Remillard, K., Kaplan, D., Thannhauser, T., Sherwood, R., Comparative analysis of macromolecules in mollusc shells (1993) Comp. Biochem. Physiol., 105 B, pp. 487-496; Levi-Kalisman, Y., Falini, G., Addadi, L., Weiner, S., Structure of the nacreous organic matrix of a bivalve mollusk shell examined in the hydrated state using cryo-TEM (2001) J. Struct. Biol., 135, pp. 8-17; Weiner, S., Hood, L., Soluble protein of the organic matrix of mollusk shells: A potential template for shell formation (1975) Science, 190, pp. 987-989; Weiner, S., Traub, W., Macromolecules in mollusc shells and their functions in biomineralization (1984) Phil. Trans. R. Soc. Lond. B, 304, pp. 425-434; Belcher, A.M., Wu, X.H., Christensen, R.J., Hansma, P.K., Stucky, G.D., Morse, D.E., Control of crystal phase switching and orientation by soluble mollusc-shell proteins (1996) Nature, 381, pp. 56-58; Kamat, S., Su, X., Ballarini, R., Heuer, A.H., Structural basis for the fracture toughness of the shell of the conch Strombus gigas (2000) Nature, 405, pp. 1036-1040; Hare, P.E., Amino acids in the proteins from aragonite and calcite in the shells of Mytilus californianus (1963) Science, 139, pp. 216-217; Hare, P.E., Abelson, P.H., Amino acid composition of some calcified proteins (1965) Carnegie Inst. Washington Year Book, 64, p. 223; Watabe, N., Shell (1984) Biology of the Integument, 1, pp. 448-485. , Invertebrates (Bereiterhahn, J., Matolsty, A.G. & Richards, K.S., eds). Springer-Verlag, Berlin; Mann, S., Molecular recognition in biomineralization (1988) Nature, 332, pp. 119-124; Kono, M., Hayashi, N., Samata, T., Molecular mechanism of the nacreous layer formation in Pinctada maxima (2000) Biochem. Biophys. Res. Commun., 269, pp. 213-218; Lopez, E., Berland, S., Le Faou, A., Nacre, osteogenic and osteoinductive properties (1994) Bull. Inst. Océan Monaco, 14, pp. 49-57; Lopez, E., Vidal, B., Berland, S., Camprasse, C., Camprasse, G., Silve, C., Demonstration of the capacity of nacre to induce bone formation by human osteoblasts maintained in vitro (1992) Tissue Cell, 24, pp. 667-679; Atlan, G., Balmain, N., Berland, S., Vidal, B., Lopez, E., Reconstruction of human maxillary defects with nacre powder: Histological evidence for bone regeneration (1997) C. R. Acad. Sci. Paris, Life Sci., 320, pp. 253-258; Atlan, G., Delattre, O., Berland, S., Le Faou, A., Nabias, G., Cot, D., Lopez, E., Interface between bone and nacre implants in sheep (1999) Biomaterials, 20, pp. 1017-1022; Lamghari, M., Almeida, M.J., Berland, S., Huet, H., Laurent, A., Milet, C., Lopez, E., Stimulation of bone marrow cells and bone formation by nacre: In vivo and in vitro studies (1999) Bone, 25 S, pp. 91S-94S; Almeida, M.J., Milet, C., Peduzzi, J., Pereira, L., Haigle, J., Barthélemy, M., Lopez, E., The effect of water-soluble matrix fraction extracted from the nacre of Pinctada maxima on the alkaline phosphatase activity of cultured fibroblasts (2000) J. Exp. Zool. (Mol. Dev. Evol.), 288, pp. 327-334; Almeida, M.J., Pereira, L., Milet, C., Haigle, J., Barbosa, M., Lopez, E., Comparative effects of nacre water-soluble matrix and dexamethasone on the alkaline phosphatase activity of MRC-5 fibroblasts (2001) J. Biomed. Mater. Res., 57, pp. 306-312; Lamghari, M., Berland, S., Laurent, A., Huet, H., Lopez, E., Bone reactions to nacre injected percutaneously into the vertebrae of sheep (2001) Biomaterials, 22, pp. 555-562; Lopez, E., Giraud, M., Le Faou, A., Berland, S., Gutierrez, J., (1995), Procédé de préparation de substances actives à partir de la nacre, produits obtenus, utiles comme médicaments. Patent CNRS no. FR. 9515650, 28/12/1995, WO 97/24133-10/07/97Wheeler, A.P., Rusenko, K.W., George, J.W., Sikes, S., Evaluation of calcium binding by molluscan shell organic matrix and its relevance to biomineralization (1987) Comp. Biochem. Physiol., 87 B, pp. 953-960; Cohen-Solal, L., Lian, J.B., Kossiva, D., Glimcher, M.J., The identification of O-phosphothreonine with soluble non-collagenous phosphoproteins of bone matrix (1978) FEBS Lett., 89, pp. 107-110; Cohen, S.A., Strydom, D.J., Amino acid analyses utilizing phenylisothiocyanate derivatives (1988) Anal. Biochem., 174, pp. 1-16; Hewitt, B.R., Spectrophotometric determination of protein in alkaline solution (1958) Nature, 187, p. 246; Whiteman, P., The quantitative determination of glycosaminoglycans in urine with Alcian blue 8GX (1973) Biochem. J., 131, pp. 351-357; Whiteman, P., The quantitative measurement of Alcian blue-glycosaminoglycan complexes (1973) Biochem. J., 131, pp. 343-350; Gold, E.W., A simple spectrophotometric method for estimating glycosaminoglycan concentrations (1979) Anal. Biochem., 99, pp. 183-188; Laemmli, U.K., Cleavage of structural proteins during the assembly of the head of bacteriophage T4 (1970) Nature, 227, pp. 680-685; Morrissey, J.H., Silver stain for proteins in polyacrylamide gels: A modified procedure with enhanced uniform sensitivity (1981) Anal. Biochem., 117, pp. 307-310; Wheeler, A.P., Rusenko, K.W., Sikes, S., Organic matrix from carbonate biomineral as a regulator of mineralization (1988) Chemical Aspects of Regulation of Mineralization, , (Sikes, C.S. & Wheeler, A.P., eds). University of South Alabama Publication Services, Mobile, Alabama; Weiner, S., Aspartic acid-rich proteins: Major components of the soluble organic matrix of mollusk shells (1979) Calcif. Tissue Int., 29, pp. 163-167; Wheeler, A.P., Rusenko, K.W., Swift, D.M., Sikes, S., Regulation of in vitro and in vivo CaCO 3 crystallization by fractions of oyster shell organic matrix (1988) Mar. Biol., 98, pp. 71-80; Halloran, B.A., Donachy, J.E., Characterization of organic matrix macromolecules from the shells of the antarctic scallop Adamussium colbecki (1995) Comp. Biochem. Physiol., 111 B, pp. 221-231; Scott, J.E., Quintarelli, G., Dellovo, M.C., The chemical and histochemical properties of Alcian blue staining (1964) Histochemie, 4, pp. 73-85; Nakamoto, K., (1986) IR and Raman Spectra of Inorganic and Coordination Compounds, , J. Wiley & Sons, New York; Samata, T., Krampitz, G.P., Calcium binding polypeptides in oyster shells (1982) Malacologia, 22, pp. 225-233; Roeges, N.P.G., (1998) A Guide to the Complete Interpretation of Infrared Spectra of Organic Structures, , J. Wiley & Sons, New York; Cariolou, M., Morse, D., Purification and characterization of calcium binding conchiolin shell peptides from the mollusc, Haliotis rufescens, as a function of development (1988) J. Comp. Physiol., 157 B, pp. 717-729; Krampitz, G.P., Structure of the organic matrix in mollusc shells and avian eggshells (1982) Biological Mineralization and Demineralization, pp. 219-232. , Nancollas, G.H., ed. Springer-Verlag, Berlin, Heidelberg, New York; Weiner, S., Addadi, L., Acidic macromolecules of mineralized tissues: The controllers of crystal formation (1991) Trends Biochem. Sci., 16, pp. 252-256; Marin, F., Pereira, L., Westbroek, P., Large-scale fractionation of molluscan shell matrix (2001) Protein Expr. Purif., 23, pp. 175-179; Balmain, J., Hannoyer, B., Lopez, E., Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction analyses of mineral and organic matrix during heating of mother of pearl (nacre) from the shell of the mollusc Pinctada maxima (1999) J. Biomed. Mater. Res. Appl. Mat., 48, p. 754; Marxen, J.C., Hammer, M., Gehrke, T., Becker, W., Carbohydrates of the organic shell matrix and the shell forming tissue of the snail Biomphalaria glabrata (Say) (1998) Biol. Bull., 194, pp. 231-240; Miyazawa, T., Blout, E.R., The infrared spectra of polypeptides in various conformations - Amide I and II bands (1961) J. Am. Chem. Soc., 83, pp. 712-719; Worms, D., Weiner, S., Mollusk shell organic matrix: Fourier transform infrared study of the acidic macromolecules (1986) J. Exp. Zool., 237, pp. 11-20; Weiner, S., Traub, W., X-ray diffraction study of the insoluble organic matrix of mollusk shells (1980) FEBS Lett., 111, pp. 311-316; Pereira-Mouriès, L., Almeida, M.J., Marin, F., Gay, M., Milet, C., Lopez, E., Soluble proteins of the nacre from the giant oyster Pinctada maxima with highly hydrophobic amino acids (2002) Biomineralization: Formation, Diversity, Evol. Appl., , in press; Nakahara, H., Kakei, M., Bevelander, G., Fine structure and amino acid composition of the organic 'envelope' in the prismatic layer of some bivalve shells (1980) Venus Jpn. J. Malacol., 39, pp. 167-177; Falini, G., Albeck, S., Weiner, S., Addadi, L., Control of aragonite or calcite polymorphism by mollusk shell macromolecules (1996) Science, 271, pp. 67-69; Simkiss, K., The organic matrix of the oyster shell (1965) Comp. Biochem. Physiol., 16, pp. 427-435; Golberg, M., Takagi, M., Dentine proteoglycans: Composition, ultrastructure, and functions (1993) Histochem. J., 25, pp. 781-806; Wilbur, K.M., Recent studies of invertebrate mineralization (1976) The Mechanisms of Mineralization in Invertebrates and Plants, pp. 79-108. , Watabe, N. & Wilbur, K.M., eds. The University of South Carolina Press, The Belle W. Baruch Library in Marine Science no. 5, Columbia; Addadi, L., Moradian, J., Shay, E., Maroudas, N.G., Weiner, S., A chemical model for the cooperation of sulfates and carboxylates in calcite crystal nucleation: Revelance to biomineralization (1987) Proc. Natl. Acad. Sci. USA, 84, pp. 2732-2736; Marxen, J.C., Becker, W., Calcium binding constituents of the organic shell matrix from the freshwater snail Biomphalaria glabrata (2000) Comp. Biochem. Physiol., 127 B, pp. 235-242; Tanaka, Y., Adams, D.H., Shaw, S., Proteoglycans on endothelial cells present adhesion-inducing cytokines to leukocytes (1993) Immunol. Today, 14, pp. 111-115; Jackson, R.L., Bush, S.J., Cardin, A.D., Glycosaminoglycans: Molecular properties, protein interactions, and role in physiological processes (1991) Physiol. Rev., 71, pp. 481-539; Nakahara, H., Calcification of gastropod nacre (1983) Biomineralization and Biological Metal Accumulation, pp. 225-230. , Westbroek, P. & deJong, E.W., eds. Reidel, Dordrecht, Holland; Zentz, F., Bédouet, L., Almeida, M.J., Milet, C., Lopez, E., Giraud, M., Characterization and quantification of chitosan extracted from nacre of the abalone Haliotis tuberculata and the oyster Pinctada maxima (2001) Mar. Biotechnol., 3, pp. 36-44; Alzieu, C., Thibaud, Y., Heral, M., Boutier, B., Evaluation des risques dus a l'emploi des peintures anti-sallissures dans les zones conchyoliques (1980) Rev. Trav. Inst. Pêches Marit., 44, pp. 301-348; Alzieu, C., Heral, M., Thibaud, Y., Dardignac, M.J., Feuillet, M., Influence des peintures anti-sallissures à base d'organostanniques sur la calcification de la coquille de l'huître Crassostrea gigas (1982) Rev. Trav. Inst. Pêches Marit., 45, pp. 101-116; Krampitz, G., Drolshagen, H., Deltreil, J.P., Soluble matrix components in malformed oyster shells (1983) Experientia, 39, pp. 1105-1106; Alzieu, C., Heral, M., Ecotoxicological effects of organotin coumpounds on oyster culture (1984) Ecotoxicological Testing for the Marine Environment, 2, pp. 187-196. , Persoone, G., Jaspers, E. & Claus, C., eds. State University Ghent and Inst. Mar. Sci. Res., Bredene, Belgium; Almeida, M.J., (1996) Crescimento em Ostras: Factores que Afectam a Formação e Estrutura da Concha, , PhD Thesis, Instituto de Ciências Biomédicas Abel Salazar, University of Porto, Portugal; Sudo, S., Fujikawa, T., Nagakura, T., Ohkubo, T., Sakaguchi, K., Tanaka, M., Nakashina, K., Takahashi, T., Structures of mollusc shell framework proteins (1997) Nature, 387, pp. 563-564; Shen, X., Belcher, A.M., Hansma, P.K., Stucky, G.D., Morse, D.E., Molecular cloning and characterization of Lustrin A, a matrix protein from shell and pearl nacre of Haliotis rufescens (1997) J. Biol. Chem., 272, pp. 32472-32481; Samata, T., Hayashi, N., Kono, M., Hasegawa, K., Horita, C., Akera, S., A new matrix protein family related to the nacreous layer formation of Pinctada fucata (1999) FEBS Lett., 462, pp. 225-229; Mann, S., Webb, J., Williams, R.J.P., (1989) Biomineralization: Chemical and Biochemical Perspectives, pp. 35-62. , VCH, Weinheim; Simkiss, K., Wilbur, K.M., (1989) Biomineralization - Cell Biology and Mineral Deposition, , Academic Press, San Diego; Sarashina, I., Endo, K., Primary structure of a soluble matrix protein of scallop shell: Implications for calcium carbonate biomineralization (1998) Am. Mineral., 83, pp. 1510-1515; Weiss, I., Kaufmann, S., Mann, K., Fritz, M., Purification and characterization of perlucin and perlustrin, two new proteins from the shell of the mollusc Haliotis laevigata (2000) Biochem. Biophys. Res. Commun., 267, pp. 17-21; Pereira-Mouriès, L., Milet, C., Almeida, M.J., Rousseau, M., Borzeix, S., Lopez, E., Biological effect of the water-soluble matrix extract of the nacre shell layer of Pinctada maxima on vertebrate cell proliferation and differentiation (2001) Proceedings of the 3rd International Satellite Symposium on the Comparative Endocrinology of Calcium Regulation, , http://www.sci.port.ac.uk/-cecr, Gay, C.V., Dacke, C.G., Dancks, J.A. & Cox, P.A., eds; Pereira-Mouriès, L., Almeida, M.J., Milet, C., Berland, S., Lopez, E., Bioactivity of nacre water-soluble organic matrix from the bivalve mollusk Pinctada maxima in three mammalian cell types: Fibroblasts, bone marrow stromal cells and osteoblasts (2002) Comp. Biochem. Physiol., 132, pp. 215-217
Keywords: amino acid analysis; Amino acids; Animals; anion exchange chromatography; article; Biochemistry; biomineralization; bivalve; Bivalvia; Calcium; Chemical Fractionation; Chromatography, High Pressure Liquid; controlled study; demineralization; edetic acid; EDTA-soluble matrix; Electrophoresis, Polyacrylamide Gel; Extracellular Matrix Proteins; extraction; fractionation; gel permeation chromatography; glycosaminoglycan; Glycosaminoglycans; High performance liquid chromatography; hydrophobicity; infrared spectroscopy; Insect Proteins; model; Nacre; nonhuman; Ostreidae; Pinctada; Pinctada maxima; polyacrylamide gel electrophoresis; priority journal; Silk; Silk-fibroin-like-proteins; Solubility; Spectroscopy, Fourier Transform Infrared; Undecalcified soluble matrix; Water

Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy - Botelho, C.M.; Lopes, M.A.; Gibson, I.R.; Best, S.M.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2002)
The aim of this study was to determine the effect of the incorporation of silicon on the surface charge of hydroxyapatite (HA) and to assess surface structural changes of HA and Si-HA induced by dissolution in both static and dynamic systems. X-ray photoelectron spectroscopy (XPS) analysis showed that SiO 4 4- groups were substituted for PO 4 3- groups in the silicon-hydroxyapatite (Si-HA) lattice according to a previously proposed substitution mechanism without the formation of other crystalline phases, such as tricalcium phosphate or calcium oxide. The substituted silicon induced a decrease in the net surface charge and the isoelectric point of HA as determined by zeta potential (ZP) measurements. At physiological pH = 7.4 the surface charge of Si-HA was significantly lowered compared to unmodified HA, i.e. -50 ±5 to - 71 ± 5 eV, caused by the presence of silicate groups in the HA lattice, which may account for a faster in vitro apatite formation using SBF testing. XPS results indicated that silicon seems to be preferentially leached out from Si-HA surface compared to other ionic species after dissolution studies in tris-buffer using a dynamic system. © 2002 Kluwer Academic Publishers.
Cited By (since 1996): 59Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1021177601899Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB - Inst. de Engenharia Biomedica, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: calcium oxide, 1305-78-8; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; phosphate, 14066-19-4, 14265-44-2; silicon, 7440-21-3Tradenames: Philips PW1606 spectrometer, Philips; Siemens D5000 X ray diffractometer, Siemens; Sotax CE6Manufacturers: Philips; SiemensReferences: Carlisle, E.M., (1984) Fed. Proc., 43, p. 680;Carlisle, E.M., (1986) Silicon Biochemistry, , edited by D. Evered and M. O'Connor (Wiley, New York); Schwarz, K., (1978) Biochemistry of Silicon and Related Problems, pp. 207-230. , edited by G. Bendz and I. Lindqvist (Plenum Press, New York); Schwarz, K., Milne, D.B., (1972) Nature, 239, p. 333; Voronkov, M.G., Skorobogatova, V.I., Vugmeister, E.K., Makarskii, V., (1975) Doklady Biochemistry, 222, p. 29; Hench, L.L., (1999) Biological Implications, pp. 116-163; Keeting, P.E., Oursler, M.J., Weigand, K.E., Bonds, S.K., Spelsberg, T.S., Riggs, B.L., (1992) J. Bone Mineral Res., 7, p. 1281; Hench, L.L., (1982) J. Phys., 43, p. 625; Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487; Hench, L.L., Wilson, J., (1999) An Introduction to Bioceramics, , World Scientific Publishing Co., Singapore; Jha, L.J., Best, S., Santos, J.D., Gibson, I.R., Bonfield, W., Silicon-Substituted Apatites and Process for the Preparation Thereof, , Worldwide Patent, PCT/GB97/02325 and US Patent Serial No 09/147773 (1999); Gibson, I.R., Best, S.M., Bonfield, W., (1999) J. Biomed. Mat. Res., 44, p. 422; Gibson, I.R., Huang, J., Best, S.M., Bonfield, W., (1999) Bioceramics, Vol. 12, Proceedings of the 12th International Symposium on Ceramics in Medicine (Nara, Japan November 1999), 12, pp. 191-194. , edited by H. Ohgushi, G. W. Hastings and T. Yoshikawa (World Scientific Publishing Co., London); Gibson, I.R., Hing, K.A., Revell, P.A., Santos, J.D., Best, S.M., Bonfield, W., (2002) Key Engin. Mat., 218-222, p. 203; Maroudas, N.G., (1975) J. Theoret. Biol., 49, p. 417; Van Wachem, P.B., Hogt, A.H., Beueling, T., (1987) Biomaterials, 8, p. 323; Davies, J.E., (1998) Surface Characterization of Biomaterials, pp. 219-234. , edited by B. D. Ratner (Elsevier, Amsterdam); Shelton, R.M., Rasmussen, A.C., Davies, J.E., (1988) Biomaterials, 9, p. 24; Ducheyne, P., Beight, J., Cuckler, J., Evans, B., Radin, S., (1990) Biomaterials, 11, p. 531; Ohgushi, H., Goldberg, V.M., Caplan, A.I., (1989) J. Orthop. Res., 7, p. 568; Daculsi, G., Le Geros, R.Z., Nery, E., Lynch, K., Kerebel, B., (1989) J. Biomed. Mater. Res., 23, p. 883; Hyakuna, K., Yamamuro, T., Kotoura, Y., Kakutani, Y., Kitsugi, T., Takagi, H., Oka, M., Kokubo, T., (1989) J. Biomed. Mater. Res., 23, p. 1049; Kotoura, Y., Yamamuro, T., Shikata, J., Kakutani, Y., Kitsugi, T., Hyakuna, K., Tanaka, H., (1986) Orthop. Res. Sci., 13, p. 633; Fujiu, T., Ogino, M., (1984) J. Biomed. Mater. Res., 18, p. 845; Rehman, I., Bonfield, W., (1997) J. Mat. Sci.: Mater. in Med., 8, p. 1; Nyquist, R.A., Putzig, C.L., Leugers, M.A., (1995) Infrared and Raman Spectral Atlas of Inorganic Compounds and Organic Salts, 3; NIST - National Institute of Standards and Technology Database; Van Raemdonck, W., Ducheyne, P., De Meester, P., (1984) Metal and Ceramic Biomaterials, pp. 143-146. , CRC Press; Gibson, I.R., Jha, L.J., Santos, J.D., Best, S.M., Bonfield, W., (1998) Bioceramics, Vol. 11, Proceedings of the 11th International Symposium on Ceramics in Medicine (New York, NY, USA, November 1998), , edited by R. Z. LeGeros and J. P. LeGeros (World Scientific Publishing Co., USA)
Keywords: calcium oxide; calcium phosphate; Chemical modification; conference paper; crystal structure; Dissolution; Electric Potential; electricity; hydroxyapatite; in vitro study; isoelectric point; Lime; molecular dynamics; pH; pH measurement; phase transition; phosphate; Phosphorus Compounds; priority journal; reaction analysis; Silicon; Silicon compounds; silicon derivative; structure analysis; surface property; X ray photoelectron spectroscopy; Zeta potential

Wettability and surface charge of Si 3N 4-bioglass composites in contact with simulated physiological liquids - Amaral, M.; Lopes, M.A.; Santos, J.D.; Silva, R.F. (BiomaterialsBiomaterials, 2002)
Wettability and surface charge studies were performed on a novel Si 3N 4-30wt% bioglass biocomposite. Contact angle and surface tension variation with time were determined at 25°C, respectively, by the sessile and pendant drop techniques, for distinct testing liquids: water, diiodomethane, simulated body fluid (SBF) and bovine serum albumin (BSA) dissolved in SBF solution. This biocomposite revealed a hydrophilic character (θ=26.6±2.0°) and a surface tension value (66.6mJm
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00155-2Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Inst. de Engenharia Biomedica (INEB), Rua do Campo Alegre, 823, 4150 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Serum Albumin, Bovine; Silicon Compounds; silicon nitride, 12033-89-5References: Von Recum, A.F., (1999) Handbook of biomaterials evaluation: scientific, technical, and clinical testing of implant materials, 2nd. ed., , Hemisphere Pub;Davies, J.E., The importance and measurement of surface charge species in cell behaviour at the biomaterial interface (1998) Surface characterisation of biomaterials, 6, pp. 219-234. , Ratner, editor. Progress in Biomedical Engineering. Amsterdam: Elsevier; Lampin, M., Warocquier-Clérout, R., Legris, C., Degrange, M., Sigot-Luizard, M.F., Correlation between substratum roughness and wettability, cell adhesion, and cell migration (1997) J Biomed Mater Res, 36, pp. 99-108; Dewez, J.L., Schneider, Y.J., Rouxhet, P.G., Coupled influence of substratum hydrophilicity and surfactant on epithelial cell adhesion (1996) J Biomed Mater Res, 30, pp. 373-383; Hallab, N.J., Bundy, K., O'Connor, R., Clark, R., Moses, R.L., Cell adhesion to biomaterials: Correlations between surface charge, surface roughness, adsorbed protein, and cell morphology (1995) J Long-Term Effects Med Implants, 3, pp. 209-231; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 7, pp. 667-681; Garbassi, Morra, Occhiello, Polymer surfaces, from physics to technology, , Wiley & Sons, New York [Chapter 4]; Adamson, A.W., (1990) Physical chemistry of surfaces, , 5th ed, New York: Wiley; Correia, N.T., Ramos, J.M., Saramago, B., Calado, J., Estimation of the surface tension of a solid: Application to a liquid crystalline (1997) J Colloid Interface Sci, 189, pp. 361-369; Schrader, M.E., Young-Dupre Revisited (1995) Langmuir, 11, pp. 3585-3589; Nishizawa, K., Toriyama, M., Effects of the surface wettability and zeta potential of bioceramics on the adhesiveness of anchorage-dependent animal-cells (1993) J Ferment Bioeng, 6, pp. 435-437; Suzuki, T., Nishizawa, K., Yokogawa, Y., Kameyama, T., Time-dependent variation of the surface structure of bioceramics in tissue culture medium and the effect on adhesiveness of cells (1996) J Ferment Bioeng, 3, pp. 226-232; Parfitt, G.D., (1967) Principles of the colloidal state, , London: Royal Institute of Chemistry; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Amaral, M., Lopes, M.A., Silva, R.F., Santos, J.D., Densification route and mechanical properties of Si3N4-bioglass biocomposites (2002) Biomaterials, 23, pp. 857-862; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon nitride-bioglass ® composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Krajewski, A., Piancastelli, A., Malavolti, R., Albumin adhesion on ceramics and correlation with their Z-potential (1998) Biomaterials, 19, pp. 637-641; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Chemical reaction of bioactive glass and glass-ceramics with a simulated body fluid (1992) J Mater Sci: Mater Med, 3, pp. 79-83; Vogler, E.A., Interfacial chemistry in biomaterials science (1993) Wettability, surfactant science series, 49, pp. 183-250. , Berg J.C., editor, Chapter 4; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., Effect of chemical composition on hydrophobicity and zeta potential of plasma sprayed HA/CaO-P 2O 5 glass coatings (2001) Biomaterials, 22, pp. 3105-3112; Agathopoulos, S., Nikolopoulos, P., Wettability and interfacial interactions in bioceramic-body-liquid systems (1995) J Biomed Mater Res, 29, pp. 421-429; Agathopoulos, S., Nikolopoulos, P., Determination of the energy of the interactions between oxides and biological liquids (1995) Fourth Euro ceramics, 8, pp. 319-324. , A. Ravaglioli; Wang, L., Sigmund, W., Aldinger, F., Systematic approach for dispersion of silicon nitride powder in organic media: I, surface chemistry of the powder (2000) J Am Ceram Soc, 4, pp. 691-696; Galassi, C., Bertoni, F., Water-based Si 3N 4 suspensions: Part I effect of processing routes on the surface chemistry and particle interactions (2000) J Mater Res, 1, pp. 155-163; Haynes, C.A., Norde, W., Globular proteins at solid/liquid interfaces (1994) Colloids Surf B: Biointerfaces, 2, pp. 517-566
Keywords: 3N; 4-bioglass composites; Adsorption; aqueous solution; article; Biocomposites; Biomaterials; body fluid; Body fluids; Bovinae; bovine serum albumin; cation; Cattle; ceramics; chemistry; conformation; Conformations; Contact angle; electrochemistry; enthalpy; entropy; glass; Glass ceramics; Hydrogen-Ion Concentration; hydrophilicity; liquid; methyl iodide; methylene iodide; pH; Physiological models; priority journal; Serum Albumin; Serum Albumin, Bovine; Si; Silicon compounds; silicon derivative; Silicon nitride; simulation; Support, Non-U.S. Gov't; Surface charge; Surface chemistry; Surface Properties; surface property; Surface tension; temperature; time; unclassified drug; Water; wettability; Wetting; Zeta potential

Adsorption and release studies of sodium ampicillin from hydroxyapatite and glass-reinforced hydroxyapatite composites - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J.; Gibson, I.R.; Knowles, J.C. (BiomaterialsBiomaterials, 2001)
As a potential therapy for periodontitis, sodium ampicillin, a broad spectrum antibiotic, was adsorbed onto hydroxyapatite (HA) and glass-reinforced hydroxyaptite (GR-HA) composites, and was subsequently released in vitro. The sodium ampicillin, was adsorbed more on HA compared to the GR-HA composites. X-ray diffraction (XRD) and Rietveld analysis were used to identify and quantify the levels of HA and β-tricalcium phosphate (β-TCP) in the microstructure of the GR-HA composites. Lattice parameters changes were observed for the β-TCP phase dependant on the amount of glass added. The release kinetics were shown to be divided into three stages, the first of which where a large amount of sodium ampicillin is released, followed by a slower release rate and then a final stage where the release amount approaches zero, until no more sodium ampicillin was present. X-ray photoeletron spectroscopy (XPS) studies were carried out in order to ensure that the entire antibiotic adsorbed onto the materials had been released. These kinetics studies have indicated the possibility of using these materials as possible carriers for drug delivery. Copyright © 2001 Elsevier Science Ltd.
Cited By (since 1996): 55Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(00)00296-9PubMed ID: 11336313Language of Original Document: EnglishCorrespondence Address: Knowles, J.C.; Department of Biomaterials, Eastman Dental Institute, University College London, 256 Gray's Inn Road, London WC1X 8LD, United Kingdom; email: j.knowles@eastman.ucl.ac.ukChemicals/CAS: Ampicillin, 69-53-4; Durapatite, 1306-06-5; PenicillinsManufacturers: Plasma Biotal, United KingdomReferences: Farag, S.A., Simultaneous liquid chromatographic analysis of the β-lactam antibiotics cefazolin, cefadroxil, cepalexin, ampicillin, and cephradine in solution (1998) J AOAC Int, 81, pp. 381-385;Somayaji, B.V., Jariwala, U., Jayachandran, P., Vidyalakshmi, K., Dudhani, R.V., Evaluation of antimicrobial efficacy and release pattern of tetracycline and metronidazole using a local delivery system (1998) J Periodontol, 69, pp. 409-413; Soskolne, W.A., Heasman, P.A., Stabholz, A., Smart, G.J., Palmer, M., Flashner, M., Newman, H.N., Sustained local delivery of chlorhexidine in the treatment of periodontitis; a multi-center study (1997) J Periodontol, 68, pp. 32-38; Steinberg, D., Friedman, M., Soskolne, A., Sela, M.N., A new degradable controlled release device for treatment of periodontal disease; in vitro release study (1990) J Periodontol, 61, pp. 393-398; Stoltze, K., Concentration of metronidazole in periodontal pockets after application of a metronidazole 25% dental gel (1992) J Clin Periodontol, 19, pp. 698-701; Ramaglia, L., Sbordone, L., Lenci, F., Gulletta, E., Amato, G., Kennedy, E.B., Microbiology of porous hydroxylapatite implants in human periodontal osseous defects (1986) Biomaterials and clinical applications, 7 vol., pp. 675-680. , Pizzoferrate A., Marachetti P.G., Ravaglioli A., Lee A.J.C. (Eds.), Netherlands: Elsevier; Wilson, J., Low, S., Fetner, A., Hench, L.L., Bioactive materials for periodontal treatment; a comparative study (1986) Biomaterials and clinical applications, 7 vol., pp. 223-228. , Pizzoferrate A., Marachetti P.G., Ravaglioli A., Lee A.J.C. (Eds.), Netherlands: Elsevier; Kenney, E.B., Lekovic, V., Sa Ferreira, J.C., Han, T., Dimitrijavic, B., Carranza F.A. Jr, Bone formation within porous hydroxyapatite implants in human periodontal defects (1986) J Periodontol, 57, pp. 76-83; Krejei, C.B., Bissada, N.F., Farah, C., Greenwell, H., Clinical evaluation of porous and nonporous hydroxyapatite in treatment of human periodontal bony defects (1987) J Periodontol, 58, pp. 521-528; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tensions, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Santos, J.D., Silva, P.L., Knowles, J.C., Talal, S., Monteiro, F.J., Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O, MgO (1996) J Mater Sci Mater Med, 7, pp. 187-189; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Osteocompatibility and in vivo evaluation of glass reinforced hydroxyapatite composites (1999) Bioceramics, 12 vol., pp. 421-424. , Ohgushi H., Hastings G.W., Yoshikawa T. (Eds.), Japan: World Scientific; Santos, J.D., Vasconcelos, M., Reis, R.L., Afonso, A., Monteiro, F.J., Hastings, G.W., Glass reinforced hydroxyapatite composites; physical properties and preliminary histological studies in rabbits (1994) Bioceramics, 7 vol., pp. 243-248. , Andersson O.H., Yli-Urpo A. (Eds.), Finland: Pergamon Press; Klein, C.P.A.T., Wolke, J.G.C., de Blieck-Hogervorst, J.M.A., de Groot, K., Features of calcium phosphate plasma-sprayed coatings; an in vitro study (1994) J Biomed Mater Res, 28, pp. 961-967; Klein, C.P.A.T., Wolke, J.G.C., de Blieck-Hogervorst, J.M.A., de Groot, K., Calcium phosphate plasma-sprayed coatings and their stability; an in vivo study (1994) J Biomed Mater Res, 28, pp. 909-917; Langnbucher, F., Benz, D., Kürth, W., Möller, H., Otz, M., Standardized Flow-cell method as an alternative to existing pharmacopoeial dissolution testing (1989) Pharm Ind, 51, pp. 1276-1281; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite; a comprehensive study of the effect of glass composition on crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Thomas M. Ultraviolet and visible spectroscopy, second edition. In: Ando DJ, editor. England: Wiley, 1996. p. 16-30Itokazu, M., Itoh, Y., Fukuta, M., Miyamato, K., Ohara, A., Oshima, K., Nishimoto, Y., Shimizu, K., Treatment of osteomyelitis by using antibiotic loaded porous ceramic (1999) Bioceramics, 12 vol., pp. 3-6. , Ohgushi H., Hastings G.W., Yoshikawa T. (Eds.), Japan: World Scientific; Shinto, Y., Uchida, A., Korkusuz, F., Araki, N., Ono, K., Calcium hydroxyapatite ceramic used as a delivery system for antibiotics (1992) J Bone Jt Surg, 74 B, pp. 600-604; Downes, S., Clifford, C.J., Scotchford, C., Klein, C.P.A.T., Comparison of the release of growth hormone from hydroxyapatite, heat-treated hydroxyapatite, and fluoroapatite coatings on titanium (1995) J Biomed Mater Res, 29, pp. 1053-1060; Curtis, M.A., Griffiths, G.S., Johnson, N.W., The total protein concentration of gingival crevicular fluid. Variation with sampling time and gingival inflammation (1988) J Clin Periondontol, 15, pp. 628-632; Stoltze K. Concentration of metronidazole in periodontal pockets after application of a metronidazole 25% dental gel. J Clin Periondontol 1992, 689-701Jones, A.A., Koenman, K.S., Newbold, D.A., Manwell, M.A., Clinical and microbiological effects of controlled release locally delivered minocycline in periodontitis (1994) J Periodontol, 65, pp. 1058-1066
Keywords: Adsorption; ampicillin; Antibiotics; article; calcium phosphate; composite material; controlled study; drug adsorption; Drug delivery; drug delivery system; Drug release; Durapatite; glass; Glass-reinforced hydroxyapatite; hydroxyapatite; Kinetics; Microstructure; Penicillins; periodontitis; priority journal; Reinforcement; Rietveld analysis; roentgen spectroscopy; Sodium ampicillin; Sodium compounds; structure analysis; unclassified drug; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; X-Ray Diffraction

Effect of chemical composition on hydrophobicity and zeta potential of plasma sprayed HA/CaO-P 2O 5 glass coatings - Ferraz, M.P.; Monteiro, F.J.; Serro, A.P.; Saramago, B.; Gibson, I.R.; Santos, J.D. (BiomaterialsBiomaterials, 2001)
Multilayered plasma sprayed coatings on the surface of Ti-6Al-4V alloys have been prepared, which were composed of an underlayer of HA and a surface layer of a CaO-P 2O 5 glass-HA composite, with 2 or 4 wt% of glass. Contact angle and surface tension variation with time, for both water and a protein solution, were determined by the sessile and pendent drop methods respectively using the ADSA-P software. Wettability studies showed that hydrophobicity of the coatings increase with the glass addition. The work of adhesion of albumin was also altered in a controlled manner by the addition of the CaO-P 2O 5 glass, being lower on the composite coatings than on HA. Zeta potential (ZP) results showed that composite coatings presented a higher net negative charge than HA coatings and that ZP values were also influenced by the content of the glass. This study demonstrated that the surface properties of those coatings may be modified by the addition of CaO-P 2O 5 glass. © 2001 Published by Elsevier Science Ltd.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(01)00059-XPubMed ID: 11603581Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Inst. de Engenharia Biomedica (INEB), Rua do Campo Alegre 823, 4150 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Calcium Compounds; Durapatite, 1306-06-5; lime, 1305-78-8; Oxides; Phosphorus Compounds; phosphorus pentoxide, 1314-56-3; Serum Albumin, BovineReferences: Klein, C.P.A.T., Patka, P., Van der Lubbe, H.B.M., Plasma-sprayed coatings of tetracalciumphosphate, hydroxyl-apatite, and α-TCP on titanium alloy: An interface study (1991) J Biomed Mater Res, 25, pp. 53-65;Jansen, J.A., Van der Waerden, J.P., Wolke, J.G., Histologic investigation of the biologic behavior of different hydroxyapatite plasma-sprayed coatings in rabbits (1993) J Biomed Mater Res, 14, pp. 603-610; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., Comparative biological properties of HA plasma-sprayed coatings having different crystallinities (1994) J Mater Sci: Mater Med, 5, pp. 11-17; Courteney-Harris, R.G., Kayser, M.V., Downes, S., Comparison of the early production of extracellular matrix on dense hydroxyapatite and hydroxyapatite-coated titanium in cell and organ culture (1995) Biomaterials, 16, pp. 489-495; Labat, B., Chanson, A., Frey, J., Effects of γ-alumina and hydroxyapatite coatings on the growth and metabolism of human osteoblasts (1995) J Biomed Mater Res, 29, pp. 1397-1401; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., Adult human bone cells derived from jaw bones cultured on plasma-sprayed or polished surfaces to titanium or hydroxyapatite discs (1996) J Mater Sci: Mater Med, 7, pp. 21-28; Silva, P.L., Santos, J.D., Monteiro, F.J., Knowles, J.C., Adhesion and microstructural characterisation of plasma-sprayed hydroxyapatite/glass ceramic coatings onto Ti-6Al-4V substrates (1998) Surf Coating Technol, 102, pp. 191-196; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double-layer plasma-sprayed coating: In vitro bioactivity evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblast-like human bone marrow cells on glass reinforced HA plasma-sprayed coatings (1999) J Mater Sci: Mater Med, 10 (9), pp. 567-576; Lapin, M., Warocquier-Clérout, R., Legris, C., Degrange, M., Luizard, M.F.S., Correlation between roughness and wettability, cell adhesion and cell migration (1997) J Biomed Mater Res, 36, pp. 99-108; Williams, D.F., (1982) Fundamental aspects of biocompatibility, , Boca Raton: CRC Press; Adamson, W., (1990) Physical chemistry of surfaces, 5th ed., , New York: Wiley; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions: Structure and properties of the composites (1995) J Mater Sci: Mater Med, 6, pp. 348-352; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Chen, P., Li, D., Boruvka, L., Rotenberg, Y., Neumann, A.W., Automation of axisymmetric drop shape analysis for measurements of interfacial tensions and contact angles (1990) Coll and Surf, 43, pp. 151-197; Cheng, P., Neumann, A.W., Computational evaluation of axisymmetric drop shape analysis-profile (ASA-P) (1992) Coll and Surf, 62, pp. 297-306; Young, T., (1835) Miscellaneous works, 1, p. 418. , Peacock G, editor. London: Murray; Schrader, M.E., Young Dupré revisited (1995) Langmuir, 11, p. 3585; Owens, D.K., Wendt, R.D., Estimation of the surface free energy of polymers (1969) J Appl Polym Sci, 13, pp. 1741-1769; Williams, R.L., Williams, D.F., Albumin adsorption on metal surfaces (1988) Biomaterials, 9, pp. 206-212; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Tripp, B.C., Magda, J.J., Andrade, J.D., Adsorption of globular proteins at the air/water interface as measured via dynamic surface tension: Concentration dependence, mass-transfer and adsorption kinetics (1995) J Coll Interface Sci, 173, pp. 16-27; Voigt, A., Thiel, O., Williams, D., Policova, Z., Zing, W., Neumann, A.W., Axisymmetric drop shape analysis (ADSA) applied to protein solutions (1991) Coll and Surf, 58, pp. 315-326; Suzuki, T., Nishizawa, K., Yokogawa, Y., Kameyama, T., Time-dependent variation of the surface structure of bioceramics in tissue culture medium and the effect of adhesiveness of cells (1996) J Ferment Bioeng, 81, pp. 226-232; Susuki, T., Yamamoto, T., Yoriyama, M., Kameyama, T., Surface instability of calcium phosphate ceramics in tissue culture medium and the effect on adhesion and growth of anchorage-dependent animal cells (1997) J Biomed Mater Res, 34, pp. 504-517; Haynes, C.A., Norde, W., Globular proteins at solid/liquid interfaces (1994) Coll and Surf B: Biointerfaces, 2, pp. 517-566; Kondori, K., Soito, M., Takebe, T., Yasukawa, A., Adsorption of bovine serum albumin on synthetic carbonate calcium hydroxyapatite (1995) J Coll Interface Sci, 184, pp. 124-129
Keywords: Adhesion; alloy; analytic method; article; bovine serum albumin; Calcium Compounds; calcium oxide; chemical composition; Chemical modification; Coatings; Composition; computer program; Contact angle; Durapatite; glass; hydrophobicity; hydroxyapatite; Hydroxyapatite glass composites; oxide; Oxides; pentoxide; Phosphorus Compounds; priority journal; protein; Serum Albumin, Bovine; Sprayed coatings; Surface charge; Surface Properties; Surface tension; Surface tension zeta potential; time; unclassified drug; Water; wettability; Wetting; X-Ray Diffraction; Zeta potential

HA and double-layer HA-P 2O 5/CaO glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behavior - Ferraz, M.P.; Fernandes, M.H.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2001)
Human osteoblastic bone marrow derived cells were cultured for 28 days onto the surface of a glass reinforced hydroxyapatite (HA) composite and a commercial type HA plasma sprayed coatings, both in the "as-received" condition and after an immersion treatment with culture medium during 21 days. Cell proliferation and differentiation were analyzed as a function of the chemical composition of the coatings and the immersion treatment. Cell attachment, growth and differentiation of osteoblastic bone marrow cells seeded onto "as-received" plasma sprayed coatings were strongly affected by the time-dependent variation of the surface structure occurring during the first hours of culture. Initial interactions leading to higher amounts of adsorbed protein and zeta potential shifts towards negative charges appeared to result in surface structures with better biological performance. Cultures grown onto the pretreated coatings showed higher rate of cell proliferation and increased functional activity, as compared to those grown onto the corresponding "as-received" materials. However, the cell behavior was similar in the glass composite and HA coatings. The results showed that the glass composites present better characteristics for bone cell growth and function than HA. In addition, this work also provide evidence that the biological performance of the glass composites can be modulated and improved by manipulations in the chemical composition, namely in the content of glass added to HA. © 2001 Kluwer Academic Publishers.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1011245828046Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Rua Dr. Manuel Pereira da Silva, 4200 Porto, PortugalReferences: Klein, C.P.A.T., Patka, P., Van der Lubbe, H.B.M., (1991) J. Biomed. Mater. Res., 25, p. 53;Jansen, J.A., Van Der Waerden, J.P.C.M., Wolke, J.G.C., (1993) J. Mater. Sci Mater. Med., 4, p. 466; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., (1994) J. Mater. Sci. Mater. Med., 5, p. 11; Courteney-Harris, R.G., Kayser, M.V., Downes, S., (1995) Biomaterials, 16, p. 489; Labat, B., Chanson, A., Frey, J., (1995) J. Biomed. Mater. Res., 29, p. 1397; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., (1996) J. Mater. Sci. Mater. Med., 7, p. 21; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., (1999) J. Mater. Sci: Mater. Med., 10, p. 567; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mat. Res., 45, p. 376; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 47, p. 603; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., (1997) J. Biomed. Mat. Res., 34, p. 247; Ong, J.L., Prince, C.W., Lucas, L.C., (1995) J. Biomed. Mat. Res., 29, p. 165; Gregoire, M., Orly, I., Kerebel, L.-M., Kerebel, B., (1987) Biol. Cell., 255, p. 59; Morgan, J., Holtman, K., Stanford, C., (1995) J. Dent. Res., 74, p. 190; Chou, L., Firth, J.D., Uitto, V.-J., Brunette, D.M., (1995) J. Cell. Sci., 108, p. 1563; Chou, L., Marek, B., Wagner, W.R., (1999) Biomaterials, 20, p. 977; Susuki, T., Nishizawa, K., Yokogawa, Y., Nagata, F., Kawamoto, Y., Kameyama, T., (1996) J. Ferment. Bioeng., 81, p. 226; Lampin, M., Warocquier-Clerout, R., Legris, C., Degrange, M., Sigot-Luizard, M.F., (1997) J. Biomed. Mater. Res., 36, p. 99; Best, S., Sim, B., Kayser, M., Downes, S., (1997) J. Mater. Sci. Mater. Med., 8; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., (1999) J. Mater. Sci. Mater. Med., 10, p. 663; Maniatopoulos, C., Sodek, J., Melcher, A., (1988) Cell Tissue Res., 254, p. 317; Gundle, R., Joyner, C.Y., Triffit, J.T., (1995) Bone, 16, p. 597; Fernandes, M.H., Costa, M.A., Carvalho, G.S., (1997) J. Mater. Sci. Mater. Med., 8, p. 61; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., (1997) J. Mater. Sci. Mater. Med., 8, p. 233; Fernandes, M.H., (1999) J. Biomat. App., 14, p. 113; Martin, T.J., Findlay, D.M., Heath, J.K., Ng, K.W., (1993) Handbook of Experimental Pharmacology, p. 149. , edited by J. R. Mundy and T. J. Martin (Springer-Verlag, Berlin); Stein, G.S., Lian, J.B., (1993) Cellular and Molecular Biology of Bone, p. 47. , edited by M. Noda (Academic Press Inc., Tokyo); Coelho, M.J., Trigo Cabral, A., Fernandes, M.H., Biomaterials, , in press; Coelho, M.J., Fernandes, M.H., Biomaterials, , in press; Anderson, H.C., Morris, D.C., (1993) Handbook of Experimental Pharmacology, p. 267. , edited by J. R. Mundy and T. J. Martin (Springer-Verlag, Berlin); Krajewski, A., Piancastelli, A., Malavolti, R., (1998) Biomaterials, 19, p. 637; Krajewski, A., Malavolti, R., Piancastelli, A., (1996) Biomaterials, 17, p. 53; Ducheyne, P., Kim, C.S., Pollack, S.R., (1992) J. Biomed. Mater. Res., 26, p. 147; Susuki, T., Yamamoto, T., Toriyama, M., Nishizawa, K., Yokogawa, Y., Mucalo, M.R., Kawamoto, Y., Kameyama, T., (1997) J. Biomed. Mater. Res., 34, p. 507; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Biomaterials, , in press; Kokubo, T., (1993) Bone-Bonding Biomaterals, p. 31. , edited by P. Ducheyne, T. Kokubo and C. A. Blitterswijk (Reed Health-Care Communications, Leiden, The Netherlands); Daculsi, G., Legeros, R.Z., Henghebaert, M., Barbieux, I., (1990) Calcif. Tissue Int., 46, pp. 20-27; Bagambisa, F.B., Joos, U., Schilli, W., (1993) J. Biomed. Mat. Res., 27, pp. 1047-1055; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., (1995) J. Biomed. Mat. Res., 29, pp. 89-99; Gwynn, I.A.P., (1994) J. Mater. Sci. Mater Med., 5, pp. 357-360; Ghannam, E.L., Ducheyne, P., Spapiro, I., (1995) J. Biomed Mat. Res., 29, pp. 359-370; Kirkpatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., (1997) J. Mater. Sci. Mater Med., 8, pp. 131-141; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., J. Biomed. Mater. Res., , in press
Keywords: Adsorption; alkaline phosphatase; article; Biomedical engineering; Bone; bone marrow; bone marrow cell; Calcium; calcium oxide; cell adhesion; Cell culture; cell differentiation; cell growth; cell proliferation; chemical composition; Coatings; controlled study; culture medium; enzyme activity; glass; Growth kinetics; human; human cell; hydroxyapatite; immersion; osteoblast; oxygen; performance; phosphorus; priority journal; protein binding; protein content; Proteins; Scanning electron microscopy; Surface charge; surface property; time; X ray diffraction

Mineralization of regenerated cellulose hydrogels - Granja, P.L.; Ribeiro, C.C.; De Jéso, B.; Baquey, C.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2001)
Due to their high water swelling, regenerated cellulose hydrogels and sponges were pre-incubated in a Ca-containing solution, and their mineralization was investigated. Results obtained demonstrate that a simple pre-incubation treatment in a Ca containing solution can induce mineralization in materials with limited or no tendency to mineralize. The minerals formed had an apatitic carbonated and poorly crystalline structure, resembling carbonated hydroxyapatite found in bone mineral. The apatitic layer formed showed a relatively accelerated growth using this technique, exhibiting nodules in their macroscopic structure, which seem to indicate lateral growth. The porous structure of regenerated cellulose sponges was also homogeneously mineralized using this technique. © 2001 Kluwer Academic Publishers.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1013960601330Language of Original Document: EnglishCorrespondence Address: Granja, P.L.; INEB - Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Portugal and Universidade do Porto, Rua do Campo Alegre, 823-4150-180 Porto, Portugal; email: pgranja@ibmc.up.ptTradenames: Cellspon, Hexabio, France; Regenerated cellulose hydrogel (CRV), Hexabio, FranceManufacturers: Cellomeda, Finland; Hexabio, FranceReferences: Abdel-Fattah, W.I., El-Sayed, A.M., Ali, F.M., Beheri, H.H., (1994) Biomaterials, 15, p. 643;Schwartz, Z., Braun, G., Kohavi, D., Brooks, B., Amir, D., Sela, J., Boyan, B., (1993) J. Biomed. Mater. Res., 27, p. 1029; Royer, P., Amrah-Bouali, S., Freche, M., Rey, C., Rouquet, N., Bonel, G., (1992) Bioceramics, 5, p. 95. , edited by T. Yamamuro, T. Kokubo and T. Nakamura (Kobunshi-Kankokai, Kyoto, Japan); Krajewski, A., Ravaglioli, A., Mongiorgi, R., Moroni, A., (1988) J. Biomed. Mater. Res., 22, p. 445; Hench, L.L., (1998) J. Biomed. Mater. Res., 41, p. 511; Hayakawa, S., Tsuru, K., Iida, H., Ohtsuki, C., Osaka, A., (1996) J. Ceram. Soc. Jpn., 104, p. 1000; Kitsugi, T., Yamamuro, T., Nakamura, T., Kokubo, T., (1989) J. Biomed. Mater. Res., 23, p. 631; Li, P., Ye, X., Kangasniemi, I., De Blieck-Hogervorst, J.M.A., Klein, C.P.A.T., De Groot, K., (1995) J. Biomed. Mater. Res., 29, p. 325; Li, P., Ohtsuki, T., Kokubo, T., Nakanishi, K., Soga, N., Nakamura, T., Yamamuro, T., (1993) J. Mater. Sci.: Mater. Med., 4, p. 127; Damen, J.J.M., Ten Cate, J.M., (1989) J. Dent. Res., 68, p. 1355; Leitão, E., Barbosa, M.A., De Grout, K., (1995) J. Mater. Sci.: Mater. Med., 6, p. 849; Li, P., Kangasniemi, I., De Grout, K., (1994) J. Am. Ceram. Soc., 77, p. 1307; Lowenberg, B., Chernecky, R., Shiga, A., Davies, J.E., (1991) Cells & Materials, 1, p. 177; Hanawa, T., Ota, M., (1991) Biomaterials, 12, p. 767; Damen, J.J.M., Ten Cate, J.M., Ellingsen, J.E., (1991) J. Dent. Res., 7, p. 1346; Radder, A.M., Van Loon, J.A., Puppels, G.J., Van Blitterswijk, C.A., (1995) J. Mater. Sci.: Mater. Med., 6, p. 510; Gaillard, M.L., Van Blitterswijk, C.A., (1994) J. Mater. Sci.: Mater. Med., 5, p. 695; Golomb, G., (1992) J. Mater. Sci.: Mater. Med., 3, p. 272; Golomb, G., Wagner, D., (1991) Biomaterials, 12, p. 397; Verheyen, C.C.P.M., De Wijn, J.R., Van Blitterswijk, C.A., De Grout, K., Rozing, P.M., (1993) J. Biomed. Mater. Res., 27, p. 433; Stupp, S.I., Ciegler, G.W., (1992) J. Biomed. Mater. Res., 26, p. 169; Bonfield, W., (1988) Bioceramics: Materials Characteristics vs In Vivo Behavior, p. 173. , edited by P. Ducheyne and J. E. Lemons (Ann. New York Academy of Sciences., NY, USA); Suzuki, K., Kobayashi, R., Yokoyama, Y., Harada, Y., Kokubo, T., (1993) Bioceramics, 6, p. 245. , edited by P. Ducheyne and D. Christiansen (Butterworth-Heinemann, Guilford, UK); Tanahashi, M., Hata, K., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., (1992) Bioceramics, 5, p. 57. , edited by T. Yamamuro, T. Kokubo and T. Nakamura (Kobunshi-Kankokai, Kyoto, Japan); Kokubo, T., Hata, K., Nakamura, T., Yamamuro, T., (1991) Bioceramics, 4, p. 113. , edited by W. Bonfield, G. W. Hastings and K. E. Turner (Butterworth-Heinemann, Guildford, UK); Oyane, A., Minoda, M., Miyamoto, T., Takahashi, R., Nakanishi, K., Kim, H.M., Kokubo, T., Nakamura, T., (1999) J. Biomed. Mater. Res., 47, p. 367; Osaka, A., Ohtsuki, C., Tsuru, K., (1995) Bioceramics, 8, p. 441. , edited by J. Wilson, L. L. Hench and D. Greenspon (Pergamon Press, New York, USA); Li, S., Liu, Q., De Wijn, J., De Grout, K., Zhou, B., (1996) J. Mater. Sci. Lett., 15, p. 1882; Hossainy, S.F.A., Hubbell, J.A., (1994) Biomaterials, 15, p. 921; Granja, P.L., Barbosa, M.A., Pouységu, L., De Jésu, B., Baquey, C., (1999) Frontiers in Biomedical Polymers Applications 2, p. 195. , edited by R. Ottenbrite (Technomic Press, Lancaster, PA, USA); Granja, P.L., Pouységu, L., De Jésu, B., Rouais, F., Baquey, C., Barbosa, M.A., (2001) J. Mater. Sci.: Mater. Med., , In press; Tanahashi, M., Matsuda, T., (1997) J. Biomed. Mater. Res., 34, p. 305; Li, S., Liu, Q., De Wijn, J., Wolke, J., Zhou, B., De Grout, K., (1997) J. Mater. Sci.: Mater. Med., 8, p. 543; Kato, E., Eika, Y., Ikada, Y., (1996) J. Biomed. Mater. Res., 32, p. 687; Mucalo, M.R., Yokogawa, Y., Toryiama, M., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, N., (1995) J. Mater. Sci.: Mater. Med., 6, p. 597; Mucalo, M.R., Yokogawa, Y., Suzuki, T., Kawamoto, Y., Nagata, K., Nishizawa, F., (1995) J. Mater. Sci.: Mater. Med., 6, p. 658; Poustis, J., Baquey, C., Chauveaux, D., (1994) Clin. Mater., 16, p. 119; Chauveaux, D., Barbié, C., Barthe, X., Baquey, C., Poustis, J., (1990) Clin. Mater., 5, p. 251; Pommier, J.C., Poustis, J., Baquey, C., Chauveaux, D., (1986), Fr. Patent No. 8610331Eur. Patent No. 0256906 A1 (1987)US Patent No. 4904258 (1990)Martson, M., Viljanto, J., Hurme, T., Laippala, P., Saukko, P., (1999) Biomaterials, 20, p. 1899; Pajulo, O., Lonnberg, B., Lonnqvist, K., Viljanto, J., (1993) Abstracts Books of the XXXVIII Congress of The European Society for Surgical Research ESSR, p. 156. , edited by H. Aro and J. Niinikovski (Turku, Finland); Kokubo, T., (1990) Handbook of Bioactive Ceramics: Bioactive Glasses and Glass-Ceramics, 1, p. 41. , edited by T. Yamamuro, L. L. Hench and J. Wilson (CRC Press, Boca Raton, FL, USA); Ribeiro, C.C., (1994), MSc Thesis. Porto, Portugal, Faculdade de Engenharia da Universidade do PortoRhee, S.-H., Tanaka, J., (1999) Biomaterials, 20, p. 2155; Miyaji, F., Kim, H.-M., Handa, S., Kokubo, T., Nakamura, T., (1999) Biomaterials, 20, p. 913; Radin, S.R., Ducheyne, P., (1993) J. Biomed. Mater. Res., 27, p. 35; Sauer, G.R., Wuthier, R.E., (1988) J. Biol. Chem., 263, p. 13718; Elliot, J.C., (1994) "Structure and Chemistry of the Apatites and Other Calcium Orthophosphates", Studies in Inorganic Chemistry Series 18, , Elsevier, Amsterdam, The Netherlands; Hanawa, T., Ota, M., (1991) Biomaterials, 12, p. 767; Rey, C., Shimizu, M., Collins, B., Glimcher, M.J., (1990) Calcif. Tissue Int., 46, p. 384; Legeros, R.Z., (1993) Clin. Mater., 14, p. 65; Heughebaert, M., Legeros, R.Z., Gineste, M., Guilhem, A., Bonel, G., (1988) J. Biomed. Mater. Res.: Appl. Biomaterials, 22, p. 257; Kieswetter, K., Bauer, T.W., Brown, S.A., Van Lente, F., Merritt, K., (1994) Biomaterials, 15, p. 183; Rey, C., (1995) Actual. Chimique, p. 41; Nancollas, G.H., (1989) Biomineralization. Chemical and Biochemical Perspectives, p. 157. , edited by S. Mann, J. Webb and R. J. P. Williams (VCH, Weinheim, Germany); Bohic, S., Heymann, D., Pouezat, J.A., Gauthier, O., Daculsi, G., (1998) Sciences de la vie, 321, p. 865; Rey, C., Strawich, E., Glimcher, M.J., (1994) Bulletin de l'Institut Océanographique, Monaco, 14, p. 55; Dasarathy, H., Riley, C., Coble, H.D., (1993) J. Biomed. Mater. Res., 27, p. 477; Yamashita, K., Horisaka, Y., Satomura, K., Takagi, T., (1991) Jpn. J. Oral Biol., 33, p. 166; Bonel, G., Heughebaert, J.-C., Heughebaert, M., Lacout, J.L., Lebugle, A., (1988) Ann. N. Y. Acad. Sci., 523, p. 115
Keywords: Apatite; article; Bone; bone mineral; Calcification (biochemistry); Calcium; Carbon; Cellulose; crystal; hydrogel; Hydrogels; hydroxyapatite; Incubation; infrared spectroscopy; mineralization; porosity; priority journal; Scanning electron microscopy; surface property; Swelling; Water

Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin - Ji, J.; Feng, L.; Barbosa, M.A. (BiomaterialsBiomaterials, 2001)
An ideal surface for many biomedical applications would resist non-specific protein adsorption while at the same time triggering a specific biological pathway. Based on the approach of selectively binding albumin to free fatty acids, stearyl groups were immobilized onto poly(styrene) backbone via poly(ethylene oxide) side chains. X-ray photoelectron spectroscopy (XPS) analysis indicates substantial surface enrichment of the stearyl poly(ethylene oxide) (SPEO). In an aqueous environment, the surface rearrangement is limited, as proved by dynamic contact angle tests. The comb-like copolymer presents a special hydrophobic surface with high SPEO surface density, which may be due to the 'tail like' SPEO architecture at the copolymer/water interface. Protein adsorption tests confirm that the comb-like surfaces adsorb high levels of albumin and resist fibrinogen adsorption very significantly. The surfaces prepared in this research attract and reversibly bind albumin due to the synergistic action of the PEO chains and the stearyl end groups. Copyright © 2001 Elsevier Science Ltd.
Cited By (since 1996): 26Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(01)00048-5PubMed ID: 11575476Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, Hangzhou 310027, China; email: @@@Chemicals/CAS: Biocompatible Materials; Fibrinogen, 9001-32-5; Ligands; polyethylene glycol-polystyrene; Polyethylene Glycols; Polystyrenes; Serum Albumin; Stearates; stearyl poly(ethylene oxide)References: Andrade, J.D., Nagaoka, S., Cooper, S., Okano, T., Kim, S.W., Surface and blood compatibility; current hypothesis (1987) ASAIO Trans, 33 (2), pp. 75-76;Ranter, B.D., The engineering of biomaterials exhibiting recognition and specificity (1996) J Mol Recognition, 9, pp. 617-625; Jeon, S.I., Lee, J.H., Andrade, J.D., De Gennes, P.G., Protein-surface interactions in the presence of polyethylene oxide (1991) J Colloid Interface Sci, 142 (1), pp. 149-158; Merrill, E.W., Salzman, E.W., Polyethylene oxide as a biomaterial (1983) ASAIO J, 6, pp. 60-64; Amiji, M., Park, K., Prevention of protein adsorption and platelet adhesion on surfaces by PEO/PPO/PEO triblock copolymers (1992) Biomaterials, 13, pp. 682-692; Mayes, A.M., Irine, D.J., Tailoring polymer surface for control cell behavior (1998), pp. 73-84. , Thomson G., Mooney R.C., Healy D.J., Ikada K.E., Mikos Y. (Eds.), Biomaterials regulating cell function and tissue development, Warrendale, PA: MRSKeogh, R.J., Eaton, J.W., Albumin binding surfaces for biomaterials (1994) J Lab Clin Med, 124 (4), pp. 537-545; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., Alkyl substituted polymers with enhanced albumin affinity (1981) Trans Am Soc Artif Intern Organs, 27, pp. 499-503; Pitt, W.G., Cooper, S.L., Albumin adsorption on alkyl chain derivatized polyurethane; I. The effect of C-18 alkylation (1988) J Biomed Mater Res, 22, pp. 359-382; Frautschi, J.R., Munro, M.S., Lloyd, D.R., Eberhart, R.C., Alkyl derivatized cellulose acetate membranes with enhanced albumin affinity (1983) Trans Am Soc Artif Intern Organs, 29, pp. 242-244; Keogh, J.R., Velander, F.F., Eaton, J.W., Albumin-binding surface for implantable devices (1992) J Biomed Mater Res, 26, pp. 441-456; Qiu, Y.X., Yu, X.J., Feng, L.X., Yang, S.L., Synthesis and characterization of amphiphilic and microphase-separated graft copolymer (1992) Makromol Chem, 173, p. 1377; Gallo BM, Russo S. In: Platzer NAJ, editor. Copolymer, polymers and composites. Washington, DC, 1975. p. 85Neumann AW, Good RJ. In: Good RJ, Stromberg RR, editors. Surface and colloid science, vol. 11, Experimental methods. New York: Plenum Press, 1979. p. 31Brash, J.L., Davidson, V.J., Adsorption of glass and polyethylene from solutions of fibrinogen and albumin (1976) Thromb Res, 9 (3), pp. 249-259; Lide DR. In: Lider DR, editor. Surface tension of common liquids, Handbook of chemistry and physics. Boca Raton, FL: CRC Press, 1996. p. 6-147Carel, J.V.O., (1994), pp. 170-177. , Carel J.V.O. (Ed.), Interfacial forces in aqueous media, New York: Marcel DekkerMori, Y., Nagaoka, S., Takiuchi, H., Kikuci, T., Noguchi, N., Tanzawa, H., Noishili, Y., A new antithrombogenic material with long polyethyleneoxide chains (1982) Trans Am Soc Artif Intern Organs, 28, pp. 459-463; Wu, D., Jian, K., (1995) Sci China (B), 25 (11), p. 1121; Wu, D., Jian, K., (1995) Sci China (B), 26 (5), p. 409; Walton, D.G., Soo, P.P., Mayes, A.M., Sofia Allgor, S.J., Fujii, J.T., Griffith, L.G., Ankner, J.F., Satija, S.K., Creation of stable poly(ethylene oxide) surfaces on poly(methyl methacrylate) using blends of branched and linear polymer (1997) Macromolecules, 30 (22), pp. 6947-6956; Walton, D.G., Mayes, A.M., Entropically driven segregation in blend of branched and liner polymers (1996) Phys Rev E, 54 (3), pp. 2811-2815
Keywords: Adsorption; Albumin; Amphiphilic copolymer; article; Biocompatible Materials; Biomedical engineering; Catalyst selectivity; Cell immobilization; Contact angle; copolymer; Copolymers; density; Electron Probe Microanalysis; fibrinogen; Grafting (chemical); Humans; hydrophobicity; Ligands; macrogol; macrogol derivative; materials testing; Polyethylene Glycols; Polystyrenes; priority journal; Protein adsorption; protein binding; Proteins; roentgen spectroscopy; Serum Albumin; Stearates; Stearyl end groups; Surface Properties; surface property; Ultraviolet spectroscopy; X ray photoelectron spectroscopy

Concept, design and fabrication of smart orthopedic implants - Burny, F.; Donkerwolcke, M.; Moulart, F.; Bourgois, R.; Puers, R.; Van Schuylenbergh, K.; Barbosa, M.; Paiva, O.; Rodes, F.; Bégueret, J.B.; Lawes, P. (Medical Engineering and PhysicsMed. Eng. Phys., 2000)
Extensive clinical experience has been built up using orthopaedic implants instrumented with strain gauges connected to a Wheatstone bridge by means of percutaneous leads. This research showed the medical relevance of the monitoring of the deformation of implants as a powerful tool to evaluate nursing and rehabilitation exercises, for tracing dangerous overloads and anticipating implant failure and also to observe the healing process. The IMPACT 3500 project focuses on the instrumentation of femoral implants with on board sensors: regular Benoist-Girard implants have been modified, to contain a 'sensing cell', and thoroughly tested in vitro and in vivo. The implant deformations are measured with resistive strain gauges, and the signal is transferred to a personal computer for processing and display, via a hard wired connection, or via a telemetry system. Two fully implantable wireless designs, called Linkstrain and Sealstrain, are powered from the outside by magnetic induction. As Sealstrain contains the whole telemetric system in its cavity, the highest miniaturization was required; this seriously deteriorates the efficiency of the inductive power link. © 2001 IPEM.
Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: MEPHEdoi: 10.1016/S1350-4533(00)00062-XPubMed ID: 11165144Language of Original Document: EnglishCorrespondence Address: Burny, F.; Service d'Orthopedie-Traumatologie, Cliniques Universitaires Bruxelles, Hôpital Erasme, Brussels, Belgium; email: fburny@ulb.ac.beChemicals/CAS: Biocompatible Materials; Ceramics; Metals; Stainless Steel, 12597-68-1References: Burny, F., Donkerwolcke, M., Moulart, F., Clinical application of the monitoring of orthopedic implants (1993), pp. 138-146. , Burny R, Puers F, editors. Monitoring of orthopedic implants. A biomaterials microelectronics - challenge. Amsterdam: ElsevierBurny, F., Zucman, J., Bourgois, R., Aubriot, J.H., Sedel, J., Utilisation des jauges extensométriques pour la mesure de la consolidation des fractures du tibia traitées par enclouage centromédullaire. Etude théorique et premiers résultats (1971) Acta Orthop Belg, 37, pp. 266-277;Moulart, F., (1975) Rééducation des fractures hautes du fémur. Mesure des déformations du matériel d'ostéosynthese, , Mémoire de Licence en Kinésithérapie, Université Libre de Bruxelles; Burny, F., Moulart, F., Hinsenkamp, M., Traitement des fractures métastatiques de la region sous-trochantérienne. Etude biomécanique; cas cliniques (1976) Acta Orthop Belg, 42, pp. 31-41; Burny, F., Donkerwolcke, M., Telemetry in the musculoskeletal system (1991), pp. 391-394. , Payne PA, editor. Concise encyclopedia of biological and biomedical measurement systems. Oxford: Pergamon PressPuers, R., Burny, F., Biotelemetry in orthopaedics (1992), 3, pp. 285-306. , Muster D. et al., editors. European Materials Research Society Monographs. Biomaterials. Hard Tissue Repair and Replacement, Amsterdam: ElsevierKadefors, R., Kaiser, E., Petersen, I., Energizing implantable transmitters by means of coupled inductance coils (1969) IEEE Trans Biomed Eng, 16 BME, pp. 177-183; Ko, W.H., Liang, S.P., Fung, C.D.F., Design of radio-frequency powered coils for implant intruments (1977) Med Biol Eng Comput, 15, pp. 634-640; Donaldson, N., De, N., Perkins, T.A., Analysis of resonant coupled coils in the design of radio frequency trancutaneous links (1983) Med Biol Eng Comput, 21, pp. 612-627; Grossman, D.G., Machining a machinable glass-ceramic (1978) Vacuum, 28, pp. 55-61; Van Schuylenbergh, K., Puers, R., The influence of moisture leakage on implant strain measurements with resistive strain gauges (1993), pp. 125-137. , Burny R, Puers F, editors. Monitoring of orthopedic implants. A biomaterials microelectronics - challenge. Amsterdam: ElsevierWranglén, G., (1985) An introduction to corrosion and protection of metals, , London: Chapman & Hall; Barbosa, M.A., Surface layers and the reactivity of metallic implants (1992), pp. 257-284. , Muster D, editor. Biomaterials - hard tissue repair and replacement, E-MRS Monographs. North-Holland: Elsevier ScienceNicholas, M.G., Active metal brazing (1986) British Ceramic Transactions Journal, 85, pp. 144-146; Pattee, H.E., Joining ceramics to metals and other materials (1972) Welding Research Council Bulletin, 178, pp. 2435-2442. , New York; Nicholas, M.G., Crispin, R.M., Brazing ceramics with alloys containing titanium (1989) Ceramic Engineering and Science Proceedings, 10, pp. 1602-1612; Rodes, F., Zardini, C., Devall, Y., Puers, R., Van Schuylenbergh, K., Burny, F., Donkerwolcke, M., Moulart, F., Direct digitization of low level transducer outputs for low power intracorporal telemetry systems (1993), pp. 401-409. , Mancini P, Fioretti S, editors. 12th Int. Symposium on Biotelemetry, Ancona. Pisa, Italy: Universitaria Litografia FeliciFlack, F.C., James, E.D., Schlapp, D.M., Mutual inductance of air-cored coils: Effect on design of radio-frequency coupled implants (1971) Med Biol Eng Comput, 9, pp. 79-85;
Keywords: article; atomic absorption spectrometry; Biocompatible Materials; biomechanics; body movement; Bone Plates; ceramics; compression; Corrosion; Failure of implants; Femoral Fractures; femur; Fracture healing; healing; Humans; materials testing; metal; metal implantation; Metals; microcomputer; Microscopy, Electron, Scanning; Monitoring, Physiologic; Orthopedic implants; orthopedic surgery; priority journal; Prostheses and Implants; Prosthesis Design; prosthesis failure; Rehabilitation; Scanning electron microscopy; sensor; Sensors; Smart implants; Spectrum Analysis; Stainless steel; strain gauge transducer; Strain measurements; Stress, Mechanical; Telemetry; Weight-Bearing

Direct and indirect effects of P 2O 5 glass reinforced-hydroxyapatite composites on the growth and function of osteoblast-like cells - Lopes, M.A.; Knowles, J.C.; Santos, J.D.; Monteiro, F.J.; Olsen, I. (BiomaterialsBiomaterials, 2000)
Human osteoblast-like cells were plated on hydroxyapatite and P 2O 5-glass reinforced hydroxyapatite composite discs. They were also cultured in the presence of media obtained by incubating the discs in the absence of cells. The effects of these direct and indirect interactions were examined by measuring cell proliferation and the expression of certain key extracellular matrix antigens. One composite was found to initially delay cell growth, while the extract of a different composite appeared to down-regulate DNA synthesis. Flow cytometry analysis showed that growth directly on the discs had little effect on collagen type I, but reduced fibronectin and osteocalcin levels. The extracts of the materials generally had less effect, although one extract obtained from the glass-reinforced hydroxyapatite significantly down-regulated fibronectin. These in vitro studies thus suggest that there were only few differences overall in the growth of the cells directly on the glass-reinforced compared with the hydroxyapatite discs and also only relatively small effects of the extracts on the cells. However, the flow cytometry results suggest that both the materials and the extracts may have a potentially important influence on connective tissue production, and that these effects are both material- and antigen-specific. Copyright (C) 2000 Elsevier Science Ltd. Human osteoblast-like cells were plated on hydroxyapatite and P 2O 5-glass reinforced hydroxyapatite composite discs. They were also cultured in the presence of media obtained by incubating the discs in the absence of cells. The effects of these direct and indirect interactions were examined by measuring cell proliferation and the expression of certain key extracellular matrix antigens. One composite was found to initially delay cell growth, while the extract of a different composite appeared to down-regulate DNA synthesis. Flow cytometry analysis showed that growth directly on the discs had little effect on collagen type I, but reduced fibronectin and osteocalcin levels. The extracts of the materials generally had less effect, although one extract obtained from the glass-reinforced hydroxyapatite significantly down-regulated fibronectin. These in vitro studies thus suggest that there were only few differences overall in the growth of the cells directly on the glass-reinforced compared with the hydroxyapatite discs and also only relatively small effects of the extracts on the cells. However, the flow cytometry results suggest that both the materials and the extracts may have a potentially important influence on connective tissue production, and that these effects are both material- and antigen-specific.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(00)00007-7PubMed ID: 10817269Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University College London, 256 Gray's Inn Road, London WC1X 8LD, United Kingdom; email: iolsen@eastman.ucl.ac.ukChemicals/CAS: Antigens; Biocompatible Materials; DNA, 9007-49-2; Hydroxyapatites; PhosphatesReferences: Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytoxicity in vitro (1992) Regulatory Affairs, 4, pp. 13-32;Hanson, S., Lalor, P.A., Niemi, S.M., Ratner, B.D., (1996) Biomaterials Science. An Introduction to Materials in Medicine, pp. 215-242. , B.D. Ratner, & A.S. Hoffman. Basel: Karger; Bou-Gharios, G., Osman, J., Atherton, A., Monoghan, P., Vancheeswaran, R., Black, C., Olsen, I., Expression of ectopeptidaes in scleroderma (1995) Ann Rheum Dis, 54, pp. 111-116; Goseki, T., Shimizu, N., Iwasawa, T., Takiguchi, H., Abiko, Y., Effects of in vitro cellular aging on alkaline phosphatase, cathepsin activities and collagen secretion of human periodontal ligament-derived cells (1996) Mech Age Dev, 91, pp. 1761-1783; Parkar, M.H., Kuru, L., O'Hare, M., Newman, H.N., Hughes, F., Olsen, I., Retroviral transduction of periodontal cells with a temperature-sensitive SV40 large T antigen (1999) Archs Oral Biol, 44, pp. 823-834; Simon, L.V., Beauchamp, J.R., O'Hare, M., Olsen, I., Establishment of long-term myogenic cultures from patients with Duchenne muscular dystrophy by retroviral transduction of a temperature-sensitive SV40 large T-antigen construct (1996) Exp Cell Res, 224, pp. 264-271; Clover, J., Gowen, M., Are MG-63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype (1994) Bone, 15, pp. 585-591; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Di Silvio, L., A novel application of two biomaterial for the delivery of growth hormone and its effect on osteoblasts (1995) PhD Thesis, , Univ Lon: Univ Coll Lon Med Sch; Kapuscinski, J., Skoczylas, B., Simple and rapid fluorimetric method for DNA microassay (1977) Anal Biochem, 83, pp. 252-257; Nishizawa, K., Toriyama, M., Suzuki, T., Kawamoto, Y., Yokogawa, Y., Nagae, H., Effects of the surface wettability and zeta potential of bioceramics on the adhesiveness of anchorage-dependent animal cells (1993) J Ferm Bioengng, 75, pp. 435-437; Chesmel, K.D., Clark, C.C., Brighton, C.T., Black, J., Cellular response to chemical and morphologic aspects of biomaterial surfaces. II. The biosynthetic and migratory response of bone cell populations (1995) J Biomed Mater Res, 29, pp. 1101-1110; Harmand, M.F., Human cell culture and characterization of cell-biomaterial interface (1992) Clinical Materials, 11, pp. 145-150; Lincks, J., Boyan, B.D., Blanchard, C.R., Lohmann, C.H., Liu, Y., Cochran, D.L., Dean, D.D., Schawrtz, Z., Response of MG63 osteoblast-like cells to titanium and titanium alloy is dependent on surface roughness and composition (1998) Biomaterials, 19, pp. 2219-2232; Lopes, M.A., Santos, J.D., Monteiro, F.J., Glass reinforced hydroxyapatite composites: Secondary phases proportions and densification effects on biaxial bending strength (1999) J Biomed Mater Res, 48, pp. 734-740; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Lopes, M.A., Saramago, B., Santos, J.D., Monteiro, F.J., Hydrophobicity and zeta potencial of glass reinforced hydroxyapatite composites (1999) J Biomed Mater Res: Appl Biomater, 45, pp. 370-375; Hall, B.K., (1992) Fracture Repair and Regeneration, pp. 33-66. , Boca Raton, FL, USA: CRC Press; Legeros, R.Z., (1991) Calcium Phosphates in Oral Biology and Medicine, , Basel: Karger; Altankov, G., Groth, T., Fibronectin matrix formation and the biocompatibility of materials (1996) J Mater Sci: Mater Med, 7, pp. 425-429; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Lopes, M.A., Knowles, J.C., Hing, K., Santos, J.D., Monteiro, F.J., Olsen, I., Sedel, L., Rey, C., Biological evaluation of glass reinforced hydroxyapatite by flow cytometry (1997) Bioceramics, 10, pp. 575-578. , Paris, Oxford, UK: Elsevier; Kirkpatrick, C.J., Mittermayer, C., Theoretical and practical aspects of testing potential biomaterials in vitro (1990) J Mater Sci: Mater Med, 1, pp. 9-13; Marie, P.J., De Vernejoul, M.C., Lomri, A., Stimulation of bone formation in osteoporosis patients treated with fluoride associated with increased DNA synthesis by osteoblastic cells in vitro (1992) J Bone Miner Res, 7, pp. 103-113; Davies, J.E., In vitro modelling of the bone-implant interface (1996) Anat Rec, 245, pp. 426-445; Verrier, S., Bareille, R., Rovira, A., Dard, M., Amdee, J., Human osteoprogenitor responses to orthopaedic implant: Mechanism of cell attachment and cell adhesion (1996) J Mater Sci: Mater Med, 17, pp. 46-51; Sumner, H., Abraham, D., Bou-Gharios, G., Plater-Zyberk, C., Olsen, I., Simultaneous measurement of cell surface and intracellular antigens by multiple flow cytometry (1991) J Immun Meth, 136, pp. 259-267; Bou-Gharios, G., Osman, J., Black, C., Olsen, I., Excess matrix accumulation in Scleroderma is caused partly by differential regulation of stromelysin and TIMP-1 synthesis (1994) Clin Chim Acta, 231, pp. 69-78; Kuru, L., Parkar, M.H., Griffiths, G.S., Newman, H.N., Olsen, I., Flow cytometry analysis of functionally distinct gingival and periodontal ligament cells (1998) J Dent Res, 77, pp. 555-564; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of glass on the biocompatibility of plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings (1999) J Biomed Mater Res, 47, pp. 603-611
Keywords: Animal cell culture; antigen expression; Antigens; article; Biocompatibility; Biocompatible Materials; Biomaterials; Bone; Bone cells; cell antigen; Cell culture; Cell Division; cell function; cell growth; Cell Line; cell proliferation; cell structure; collagen type 1; controlled study; DNA; DNA Replication; DNA synthesis; extracellular matrix; Fibronectin; flow cytometry; glass; Glass fibers; Glass-reinforced hydroxyapatite; Growth kinetics; human; human cell; Humans; hydroxyapatite; Hydroxyapatites; immunofluorescence; In vitro; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; osteocalcin; Phosphate minerals; Phosphates; phosphorus pentoxide; priority journal; Proteins; Reinforcement; Scanning electron microscopy

Fetal heart rate baselines in twins: Interobserver agreement in antepartum estimation - Bernardes, J.; Costa-Pereira, A.; Calejo, L.; Ayres-de-Campos, D.; Patrício, B.; Pereira-Leite, L. (Journal of Reproductive Medicine for the Obstetrician and GynecologistJ. Reprod. Med. Obstet. Gynecol., 2000)
OBJECTIVE: To assess interobserver agreement in antepartum estimation of fetal heart rate (FHR) baselines in twins. STUDY DESIGN: Two residents and one specialist in obstetrics and gynecology, all with special interest in FHR monitoring, independently estimated baselines in 162 consecutive antepartum FHR tracings recorded in 24 twins. Tracings were obtained with a dual-channel fetal monitor for the simultaneous recording of both twins' heart rates. Baselines were estimated, as single values corresponding to the mean of the lowest stable FHR segment, in the absence of fetal movements and uterine contractions, within physiologic limits (110-150 beats per minute [bpm]). If these criteria were not met, the possibility of persistent bradycardia or tachycardia was considered, and if this was confirmed in a tracing with at least 40 minutes, a baseline < 110 or > 150 bpm was chosen. Interobserver agreement was assessed by the proportions of agreement (PA), kappa statistic (K) and intraclass correlation coefficient (ICCC), with 95% confidence intervals (CIs). RESULTS: Interobserver agreement was excellent, with a PA of 0.90 (95% CI: 0.89-0.91), K of 0.88 (95% CI: 0.84-0.92) and ICCC of 0.91 (95% CI: 0.88-0.94). CONCLUSION: Interobserver agreement in antepartum estimation of fetal heart rate baselines in twins was excellent with the baseline concept used in this study.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JRPMAPubMed ID: 10710739Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Depto. de Ginecologia e Obstetricia, Faculdade de Medicina do Porto, Al. Prof. Hernani Monteiro, 4200 Porto, Portugal; email: Jbernardes@mail.telepac.ptReferences: Sherman, S.J., Kovacs, B.W., Medearis, A.L., Nonstress test assessment of twins (1992) J Reprod Med, 37, pp. 804-808;Grant, J.M., The fetal heart rate is normal, isn't it?: Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Cibils, L.A., On intrapartum fetal monitoring (1996) Am J Obstet Gynecol, 174, pp. 1382-1389; Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Bernardes, J., Costa-Pereira, A., Van Geijn, H.P., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Bernardes, J., Ayres-De-Campos, D., Costa-Pereira, A., Objective computerized fetal heart rate analysis (1998) Int J Gynecol Obstet, 62, pp. 141-147; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 11, pp. 307-310; Armitage, P., Berry, G., (1994) Statistical Methods in Medical Research, pp. 273-276. , Oxford, Blackwell Science Ltd; Khan, K.S., Chien, P.F.W., Honest, M.R., Evaluating measurement variability of clinical investigations: The case of ultrasonic estimation of urinary bladder volume (1997) Br J Obstet Gynaecol, 104, pp. 1036-1043; Devoe, L.D., Carlton, E., Prescott, P., Neural network prediction of nonstress test results: How often should we perform nonstress tests? (1995) Am J Obstet Gynecol, 173, pp. 1128-1131; Bernardes, J., Ayres De Campos, D., Costa-Pereira, A., Baseline estimation in typical fetal heart rate patterns using different computerized methods (1997) Acta Obstet Gynecol Scand (Suppl), 76, p. 56;
Keywords: adult; article; clinical article; Electrocardiography; Female; Fetal heart rate; Fetal monitoring; fetus; fetus heart rate; fetus monitoring; Heart rate variability; Heart Rate, Fetal; human; Humans; Internship and Residency; observer variation; Obstetrics; Pregnancy; Prenatal Care; priority journal; Professional Competence; Twins

Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma-sprayed coatings - Ferraz, M.P.; Knowles, J.C.; Olsen, I.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
Multilayered coatings composed of mixtures of HA and P 2O 5-based bioactive glasses are of potential clinical benefit in orthopaedic and dental surgery. Pre-immersion of these materials has been reported to further enhance their efficacy in vivo, although the precise biological effects of this treatment are not yet known. In this study we have therefore prepared double-layer plasma-sprayed coatings and evaluated the effects of pre-immersion on the growth and function of human osteosarcoma cells in vitro, using the MTT assay and flow cytometry analysis, respectively. The results showed that the increase in numbers of viable cells was the same or elevated following incubation on the pre-immersed HA and glass-reinforced HA coatings compared with the non-immersed materials. In addition, the expression of bone sialoprotein and fibronectin, two key connective tissue antigens, was up-regulated in cultures grown on the pre-immersed surfaces compared with the non-treated materials. Moreover, cell numbers and antigen expression both improved as the proportion of glass increased, particularly in the pre-immersed samples. Our findings thus suggest that the immersion treatment of these materials appeared to improve the response of these bone-like cells. Copyright (C) 2000 Elsevier Science Ltd. Multilayered coatings composed of mixtures of HA and P 2O 5-based bioactive glasses are of potential clinical benefit in orthopaedic and dental surgery. Pre-immersion of these materials has been reported to further enhance their efficacy in vivo, although the precise biological effects of this treatment are not yet known. In this study we have therefore prepared double-layer plasma-sprayed coatings and evaluated the effects of pre-immersion on the growth and function of human osteosarcoma cells in vitro, using the MTT assay and flow cytometry analysis, respectively. The results showed that the increase in numbers of viable cells was the same or elevated following incubation on the pre-immersed HA and glass-reinforced HA coatings compared with the non-immersed materials. In addition, the expression of bone sialoprotein and fibronectin, two key connective tissue antigens, was up-regulated in cultures grown on the pre-immersed surfaces compared with the non-treated materials. Moreover, cell numbers and antigen expression both improved as the proportion of glass increased, particularly in the pre-immersed samples. Our findings thus suggest that the immersion treatment of these materials appeared to improve the response of these bone-like cells.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00249-5PubMed ID: 10721750Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University College London, 256 Gray's Inn Road, London WC1X 8LD, United Kingdom; email: iolsen@eastman.ucl.ac.ukChemicals/CAS: Biocompatible Materials; bone sialoprotein; Coated Materials, Biocompatible; Durapatite, 1306-06-5; Fibronectins; SialoglycoproteinsManufacturers: Plasma Biotal, United KingdomReferences: Passuti, N., Daculsi, G., Martin, S., Macroporous calcium phosphate ceramics for long bone surgery in human and dogs - Clinical and histological studies (1990) Clinical Implant Materials, pp. 255-258. , V. Soltesz, & A. Lee. Amsterdam: Elsevier Science Publishers;Legeros, R., Calcium phosphate materials in restorative dentistry (1988) A Review. Adv Dent Res, 2, pp. 164-180; Hench, L.L., Bioactive ceramics: From concept to clinic (1992) J Am Ceram Soc, 74, pp. 1487-1510; Conish, H., Aoki, H., Sawai, K., (1981) Science and Medical Applications of Hydroxyaptite, , editors Tokyo: Takyama Press System Centre Co; Raemdonck, W., Ducheyne, P., Meester, P., Calcium phosphate ceramics (1984) Metal and Ceramic Materials, pp. 143-166. , P. Ducheyne, & G.W. Hastings. Boca Raton, FL, USA: CRC Press; Rey, C., Freche, M., Heughebaert, M., Vignoles, M., Apatite chemistry in biomaterial preparation, shaping and biological behaviour (1991) Fourth Symposium on Ceramics in Medicine - Bioceramics 4, pp. 57-64. , G.W. Hastings, & K.E. Tanner. London: Butterworth-Heinemann; Nagase, M., Abe, Y., Udagwa, E., Toxicity of silica-containing calcium phosphate glasses demonstrated in mice (1992) Biomaterials, 13, pp. 172-175; Burnie, J., Gilchrist, T., Controlled released glass - A new biomaterial (1983) Ceramics in Surgery, pp. 169-176. , P. Vicenzini. Amsterdam: Elsevier Science Publishers; Burnie, F., Gilchrist, T., (1983) Ceramics in Surgery, pp. 177-180. , P. Vicenzini. Amsterdam: Elsevier Science; Rawlings, R.D., Rogers, P.S., Stokes, P.M., Glass-ceramics containing apatite (1987) High Tech Ceramics, pp. 73-82. , P. Vicenzini. Amsterdam: Elsevier Science Publishers; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Santos, J.D., Lakhan, J.J., Monteiro, F.J., Surface modifications of glass-reinforced hydroxyapatite composites (1995) Biomaterials, 16, pp. 521-526; Ferraz, M.P., Monteiro, F.J., Santos, J.D., In vitro bioactivity and osteocompatibility evaluation of plasma sprayed hydroxyapatite/glass composite coatings onto Ti-6Al-4V substrates (1997) Ninth International Conference on Biomedical Engineering, pp. 557-559. , In: Goh JCH, editor Singapore; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., Plasma-sprayed coatings of tetracalciumphosphate, hydroxyl-apatite, and α-TCP on titanium alloy: An interface study (1991) J Biomed Mater Res, 25, pp. 53-65; Jansen, J.A., Van Der Waerden, J.P., Wolke, J.G., Histologic investigation of the biologic behavior of different hydroxyapatite plasma-sprayed coatings in rabbits (1993) J Biomed Mater Res, 4, pp. 603-610; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the bone-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., Comparative biological properties of HA plasma-sprayed coatings having different crystallinities (1994) J Mater Sci: Mater Med, 5, pp. 11-17; Lugscheider, E., Knepper, M., Heimberg, B., Dekker, A., Kirkpatrick, C.J., Cytotoxicity investigations of plasma-sprayed calcium-phosphate coatings (1994) J Mater Sci: Mater Med, 5, pp. 371-375; Courteney-Harris, R.G., Kayser, M.V., Downes, S., Comparison of the early production of extracellular matrix on dense hydroxyapatite and hydroxyapatite-coated titanium in cell and organ culture (1995) Biomaterials, 16, pp. 489-495; Labat, B., Chanson, A., Frey, J., Effects of γ-alumina and hydroxyapatite coatings on the growth and metabolism of human osteoblasts (1995) J Biomed Mater Res, 29, pp. 1397-1401; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., Adult human bone cells derived from jaw bones cultured on plasma-sprayed or polished surfaces to titanium or hydroxyapatite discs (1996) J Mater Sci: Mater Med, 7, pp. 21-28; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Ariola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Mater, 15, pp. 173-190; Puleo, D.A., Preston, K.E., Shaffer, J.B., Bizios, R., Examination of osteoblast-orthopaedic biomaterial interactions using molecular techniques (1993) Biomaterials, 14, pp. 111-114; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J Mater Sci: Mater Med, 7, pp. 637-643; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblast-like human bone marrow cells on glass reinforced HA plasma sprayed coatings (1999) J Mater Sci: Mater Med, 10, pp. 567-576; Macey, M.G., (1994) Flow Cytometry - Clinical Applications, , editor Oxford: Blackwell Scientific; Shapiro, H.M., (1995) Practical Flow Cytometry, , New York: Wiley-Liss; Melamed, M.R., Lindmo, T., Mandelsohn, M.L., (1990) Flow Cytometry and Sorting, , editors New York: Wiley-Liss; Muirhead, K.A., Horan, P.K., Applications of flow cytometry to tissue culture systems (1983) Adv Cell Culture, 3, pp. 57-91; Corver, W.E., Cornelisse, C.J., Fleuren, G.J., Simultaneous measurement of two cellular antigens and DNA using fluorescein-isothiocyanate, R-phycoerythrin and propidium iodide on a standard FACScan (1994) Cytometry, 15, pp. 117-128; Pande, G., Kumar, N.A., Manogaran, P.S., Flow cytometric study of changes in intracellular free calcium during the cell cycle (1996) Cytometry, 24, pp. 55-63; Kamiya, I., Okuda, K., Hara, K., Flow cytometric identification and detection of Porphyromonas gingivalis by a LPS specific monoclonal antibody (1994) J Periodont, 65, pp. 309-315; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of glass on the biocompatibility of plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings J Biomed Mater Res, , in press; Cowles, E.A., DeRome, M.E., Pastizzo, G., Brailey, L.L., Gronowicz, G.A., Mineralization and the expression of matrix proteins during in vivo bone development (1998) Calcif Tissue Int, 62, pp. 74-82; Globus, R.K., Dotty, S.B., Lull, J.C., Holmuhamedov, E., Humphries, M.J., Damsky, C.H., Fibronectin is a survival factor for differentiated osteoblasts (1998) J Cell Sci, 111, pp. 1385-1393; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Wojciech, G., Melamed, M.R., Darzynkiewicz, Z., Analysis of apoptosis by flow cytometry (1998) Flow Cytometry Protocols, pp. 217-238. , M.J. Jaroszeski, & R. Heller. Totowa, NJ, USA: Humana Press
Keywords: antigen expression; article; Bioactive glasses; Biocompatibility; Biocompatible Materials; Biomaterials; Cell culture; Cell Division; cell growth; cell proliferation; Cell size; Coated Materials, Biocompatible; controlled study; cytology; Cytoplasmic Granules; Dental Materials; drug manufacture; Durapatite; Fibronectin; Fibronectins; flow cytometry; Flow cytometry analysis; glass; Glass fibers; Glass-reinforced hydroxyapatite; Growth kinetics; human; human cell; Humans; hydroxyapatite; in vitro study; materials testing; orthopedics; Osteosarcoma; osteosarcoma cell; Phosphates; Plasma spraying; Pre-immersion; priority journal; protein expression; Proteins; Sialoglycoproteins; sialoprotein; Sprayed coatings; Surface Properties; technique; Tumor Cells, Cultured

Microstructural dependence of Young's and shear moduli of P 2O 5 glass reinforced hydroxyapatite for biomedical applications - Lopes, M.A.; Silva, R.F.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
P 2O 5 glass reinforced hydroxyapatite composite materials were prepared through a liquid-phase sintering process. Secondary phases, β- and α- tricalcium phosphate (β-TCP and α-TCP), were formed in the microstructure of the composites, due to the reaction between the liquid glassy phase and the hydroxyapatite matrix. The dynamic Young's modulus (E) and shear modulus (G) of these composites were determined using an impulse excitation method. By applying the Duckworth-Knudsen equation, the elastic property results were correlated with the relative proportion of β-TCP and α-TCP phases and with the porosity percentage present in the microstructure. Glass reinforced hydroxyapatite composites showed lower Young's and shear moduli than unmodified hydroxyapatite, mainly due to presence of β-TCP phase. The Duckworth-Knudsen model demonstrated an exponential dependence of E and G modulus with porosity and mathematical equations were derived for composite materials with porosity correction factors (b) of 4.04 and 4.11, respectively, indicating that porosity largely decreased both E and G moduli. (C) 2000 Elsevier Science Ltd. 2O 5 glass reinforced hydroxyapatite composite materials were prepared through a liquid-phase sintering process. Secondary phases, β- and α-tricalcium phosphates (β-TCP and α-TCP), were formed in the microstructure of the composites, due to the reaction between the liquid glassy phase and the hydroxyapatite matrix. The dynamic Young's modulus (E) and shear modulus (G) of these composites were determined using an impulse excitation method. By applying the Duckworth-Knudsen equation, the elastic property results were correlated with the relative proportion of β-TCP and α-TCP phases and with the porosity percentage present in the microstructure. Glass reinforced hydroxyapatite composites showed lower Young's and shear moduli than unmodified hydroxyapatite, mainly due to the presence of β-TCP phase. The Duckworth-Knudsen model demonstrated an exponential dependence of E and G modulus with porosity and mathematical equations were derived for composite materials with porosity correction factors (b) of 4.04 and 4.11, respectively, indicating that porosity largely decreased both E and G moduli.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00248-3PubMed ID: 10711972Language of Original Document: EnglishCorrespondence Address: Lopes, M.A.; INEB Inst. de Engenharia Biomedica, Laboratorio de Biomaterials, Rua do Campo Alegre 823, 4150 Porto, PortugalChemicals/CAS: Biocompatible Materials; Hydroxyapatites; PhosphatesReferences: Burstein, A., Wright, T.M., (1994) Fundamentals of Orthopaedic Biomechanics, , Lippincott: Williams & Wilkins;Carter, D.R., Giori, N.J., Effect of mechanical stresses on tissue differentiation in the bony implant bed (1991) In the Bone-material Interface, pp. 367-379. , J.E. Davies. Toronto: University of Toronto Press; (1995) E - Advanced Technical Ceramics, (PART 2). , European prestandard, ref. no. ENV 843-2:; Schreiber, E., Anderson, O.L., Soga, N., (1989) Elastic Constant and Their Measurements, , New York: McGraw-Hill; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Knowles, J.C., Talal, S., Santos, J.D., Sintering effects in a glass reinforced hydroxyapatite (1996) Biomaterials, 17, pp. 1437-1442; Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Biological evaluation of glass reinforced hydroxyapatite by flow cytometry (1998) Bioceramics, 10, pp. 575-578; Rice, R.W., Microstructure dependence of mechanical behaviour (1977) Treatise on Materials Science and Technology, 11, pp. 200-382. , MacCrone R.K. New York: Academic Press; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Murtage, B., (1981) Advanced Linear Programming, , New York: McGraw-Hill; Chátal, V., (1990) Linear Programming, , New York: W. H. Freeman; Tampieri, A., Celotti, G., Szontagh, F., Landi, E., Sintering and characterisation of hydroxyapatite and tricalcium phosphates with control of their strength and phase porosity (1997) J Mater Sci, 8, pp. 29-37; Knowles, J.K., Development of hydroxyapatite with enhanced mechanical properties: Effect of high glass additions on mechanical properties and phase stability of sintered hydroxyapatite (1994) Br Ceram Trans, 93, pp. 100-103; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Japanese Association of Apatite Science. Tokyo: Takayama Press System Center Co. Inc; Sax, M., Zografou, C., Telle, R., Kalawrytimos, G., Properties of sintered apatite ceramics (1995) Ceramic Processing Science and Technology, Ceramic Transactions, 51, pp. 701-705. , In: Hausner H, editor; Katz, J.L., Akers, A.S., Germiller, J.A., Obremski, S.M., Singh, S., The elastic properties of apatites and tricalcium phosphates-calcite mixtures (1989) Bioceramics, 1, pp. 86-91; Dewith, G., Vandijk, J.A., Hattu, N., Prijs, K., Preparation, microstructure and mechanical properties of dense polycrystalline hydroxyapatite (1981) J Mater Sci, 16, pp. 1592-1598; Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812
Keywords: article; Biocompatible Materials; Ceramic matrix composites; Chemical analysis; chemical composition; composite graft; Duckworth-Knudsen model; Elastic moduli; Elasticity; glass; hydroxyapatite; Hydroxyapatite glass composites; Hydroxyapatites; Implants (surgical); Mathematical models; Microstructure; Molecular Structure; Phosphate minerals; Phosphates; porosity; priority journal; Shear modulus; shear stress; young modulus; Young's modulus

Object recognition in image sequences with cellular neural networks - Milanova, M.; Büker, U. (NeurocomputingNeurocomputing, 2000)
In this paper, the application of CNN associative memories for 3D object recognition is presented. The main idea is to analyse the optical flow in an image sequence of an object. Several features of the optical flow between two succeeding images are calculated and merged to a time series of features for the whole image sequence. These features show several object specific characteristics and are used for a classification step in an object recognition system. Therefore, the feature vectors of an object set are learnt and recalled by an associative memory based on the paradigm of cellular neural networks (CNN). (C) 2000 Elsevier Science B.V.In this paper, the application of CNN associative memories for 3D object recognition is presented. The main idea is to analyze the optical flow in an image sequence of an object. Several features of the optical flow between two succeeding images are calculated and merged to a time series of features for the whole image sequence. These features show several object specific characteristics and are used for a classification step in an object recognition system. Therefore, the feature vectors of an object set are learnt and recalled by an associative memory based on the paradigm of cellular neural networks (CNN).
Cited By (since 1996): 14Export Date: 21 November 2012Source: ScopusCODEN: NRCGEdoi: 10.1016/S0925-2312(99)00177-0Language of Original Document: EnglishCorrespondence Address: Buker, U.; Heinz Nixdorf Institute, University of Paderborn, Department of Electrical Engineering, 33095 Paderborn, Germany; email: bueker@get.uni-paderborn.deReferences: Bradski, G., Grossberg, S., Fast-learning VIEWNET architectures for recognizing three-dimensional objects from multiple two-dimensional views (1995) Neural Networks, 8 (7-8), pp. 1053-1080;Büker, U., Hartmann, G., Knowledge based view control of a neural 3D object recognition system (1996) In: Proceedings of the 13th International Conference on Pattern Recognition, ICPR'96, Wien, 4, pp. 24-29. , IEEE Computer Soc. Press, Los Alamitos; Büker, U., Hybrid object models: combining symbolic and subsymbolic object recognition strategies (1998) In: Proceedings of the 4th International Conference on Information Systems, Analysis, and Synthesis, 1, pp. 444-451. , IIIS, Orlando; Bülthoff, H., Little, J., Poggio, T., A parallel algorithm for real-time computation of optical flow (1989) Nature, 337, pp. 549-553; Bülthoff, H., Edelman, S., Tarr, M., How are three-dimensional objects represented in the brain? (1994) Technical Report, A.I.Memo N1479, , Massachusetts Institute of Technology, A.I. Lab; Chua, L.O., Yang, L., Cellular neural networks: Theory (1988) IEEE Trans. Circuits Systems, 35, pp. 1257-1272; Chua, L.O., Roska, T., The CNN Paradigm (1993) IEEE Trans. Circuits Systems (Part I) CAS-40, 3, pp. 559-577; Fu, L.M., Analysis of the dimensionality of neural networks for pattern recognition (1990) Pattern Recognition, 23, pp. 1131-1140; Grassi, G., A new approach to design cellular neural networks for associative memories (1997) IEEE Trans. Circuits Systems - I Fundam. Theory Appl., 44 (9), pp. 362-366; Hartmann, G., Drüe, S., Dunker, J., Kräuter, K.O., Mertsching, B., Seidenberg, E., The SENROB Vision-System and its Philosophy (1994) In: Proceedings of the 12th International Conference on Pattern Recognition ICPR'94, 2, pp. 573-576. , Jerusalem, IEEE Computer Soci. Press, Los Alamitos; Hartmann, G., Büker, U., Drüe, S., A hybrid neuro-artificial intelligence architecture (1999) Handbook on Computer Vision and Applications, 3, pp. 153-196. , in: B. Jähne et al. (Eds.), Academic Press, San Diego; Hebert, M., (1995) Object Recognition in Computer Vision, , (Eds.), Springer, New York; Kikuchi, M., Fukushima, K., Neural network model of the visual system: Binding: Form and motion (1996) Neural Networks, 9 (8), pp. 1417-1427; Kosslyn, S.M., (1995) Image and Brain, , Cambridge: MIT Press; Lin, W.G., Wang, S.S., A new neural model for invariant pattern recognition (1996) Neural Networks, 9 (5), pp. 899-913; Little, J., Boyd, J., Describing motion for recognition (1995) IEEE Symp. Comput. Vision, pp. 235-240; Little, J., Boyd, J., (1997) Recognizing People by their Gait: The Shape of Motion, , http://www-vision.ucsd.edu/, On-line document; Liu, D., Michel, A., Sparsely interconnected neural networks for associative memories with applications to cellular neural networks (1994) IEEE Trans. Circuits Systems - II Analog Digital Signal Process, 41 (4), pp. 295-307; Liu, D., Cloning template design of cellular neural networks for associative memories (1997) IEEE Trans. Circuits Systems - I Fundam. Theory Appl., 44 (7), pp. 646-650; Liu, D., Lu, Z., A new synthesis approach for feedback neural networks based on the perceptron training algorithm (1997) IEEE Trans. Neural Networks, 8 (6), pp. 1468-1482; Michel, A., Jie Si, Yen, G., Analysis and Synthesis of a Class of Discrete-Time Neural Networks Described on Hypercubes (1991) IEEE Trans. Neural Networks, 2 (1), pp. 32-46; Pandya, A., MacY, R., (1996) Pattern Recognition with Neural Networks in C++, , CRC Press, Florida; Rekecsky, C., Roska, T., Ushida, A., CNN-based difference-controlled adaptive non-linear image filters (1998) Internat. J. of Circuit Theory Appl., 26 (4), pp. 374-423; Roska, T., Vandewalle, J., (1993) Cellular Neural Networks, , John Wiley & Sons, New York; Szolgay, P., Szatmari, I., Laszlo, K., A Fast Fixed Point Learning Method to Implement Associative Memory on CNN's (1997) IEEE Trans. Circuits Systems-I: Fundamental Theory and Applications, 44 (4), pp. 362-366; Treisman, A., A feature-integration theory of attention (1980) Cognitive Psychology, 12, pp. 97-136; Tn, S., Hao, J., Vanderwalle, J., Cellular neural networks as a model of associative memories (1990) Proceedings of the CNNA-90, pp. 26-35. , Budapest, IEEE, New York
Keywords: algorithm; artificial neural network; Associative memory; Associative storage; Cellular neural networks; Computational methods; computer system; Image analysis; Image sequences; mathematical computing; Object recognition; Optical flow; Optical flows; Pattern recognition; Pattern recognition systems; priority journal; review; Three dimensional computer graphics; Time series analysis; Vectors

Self-assembly and surface structure of an amphiphilic graft copolymer, polystyrene-graft-ω-stearyl-poly(ethylene oxide) - Ji, J.; Feng, L.; Qiu, Y.; Yu, X.; Barbosa, M.A. (Journal of Colloid and Interface ScienceJ. Colloid Interface Sci., 2000)
Surface properties of the polystyrene-graft-ω-stearyl-poly(ethylene oxide) (PS-g-SPEO) have been characterized by X-ray photoelectron spectroscopy (XPS), differential scanning calorimetry (DSC), contact angle, and spin probe techniques. The XPS results indicate that the surface and bulk composition of the PS-g-SPEO copolymers differ remarkably from each other. The stearyl and EO components enrich at the copolymer/air interfaces due to the self-assembly of the stearyl groups. At the PS-g-SPEO-72.6 surface (the x in PS-g-SPEO-x indicates the bulk density of the SPEO in wt%), the self- assembly of the hydrophobic stearyl groups is strong enough to form a stable liquid crystalline phase as indicated by DSC. At polymer/water interfaces, PS-g-SPEO-72.6 presents a hydrophilic surface with low PEO mobility, whereas PS-g-SPEO-50.6 and PS-g-SPEO-31.0 present the hydrophobic surface with high PEO mobility. The two different types of the surfaces, with different characters in surface energy, surface mobility of PEO, and surface architecture of SPEO, will be quite valuable as models for detecting the synergistic action of the PEO chains and the stearyl groups (specific ligand for albumin binding) in protein solutions. (C) 2000 Academic Press.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JCISAdoi: 10.1006/jcis.2000.6729Language of Original Document: EnglishCorrespondence Address: Ji, J.; Instituto de Engenharia Biomedica, Laboratorio de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jian@ibmc.up.ptChemicals/CAS: macrogol, 25322-68-3; polystyrene, 9003-53-6; stearic acid, 57-11-4, 646-29-7References: Brash, J.L., (1983) Biocompatible Polymer, Metals and Composites, p. 35. , M. Szycher. Lancaster: Technomic;Gombotz, W.R., Guanghui, W., Horbett, T.A., Hoffman, A.S., (1991) J. Biomed. Mater. Res., 25, p. 1547; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., (1981) Trans. ASAIO, 17, p. 499; Grasel, T.G., Pierce, J.A., Cooper, S.L., (1987) J. Biomed. Mater. Sci., 21, p. 815; Duncan, A.C., Sefton, M.V., Brash, J.L., (1997) Biomaterials, 18, p. 1585; Keogh, J.R., Velander, F.F., Eaton, W., (1992) J. Biomed. Mater. Sci., 26, p. 441; Lee, J.H., Jeong, B.J., Lee, H.B., (1997) J. Biomed. Mater. Sci., 34, p. 105; Bots, J.G.F., Van Der Does, L., Bentjes, A., (1986) Biomaterials, 7, p. 393; Osterberg, E., Holmberg, K., Schuman, T.P., Riggs, J.A., Burns, N.L., Van Alstine, J.M., Harris, J.M., (1995) J. Biomed. Mater. Res., 29, p. 741; Hubbell, J.A., (1997) Polym. Prepr., 38, p. 528; Harris, J.M., (1997) Polym. Prepr., 38, p. 520; Qiu, Y.X., Yu, X.J., Feng, L.X., (1992) Markromol. Chem., 173, p. 1377; Neumann, A.W., Good, R.J., (1979) Surface and Colloid Science, Vol. 11, Experimental Methods, p. 31. , R. J. Good, & R. R. Stromberg. New York: Plenum Press; Ji, J., Feng, L., Qiu, Y., Yu, X., (1998) Macromol. Rapid Commun., 19, p. 473; Cameron, G.G., (1989) Comprehensive Polymer Science, Polymer Characterization, p. 517. , S. G. Allen. Oxford: Pergamon Press; Andrade, J.D., Ma., S.M., (1979) J. Colloid Interface Sci., 12, p. 488; Ranter, B.D., (1985) Surface and Interfacial Aspects of Biomedical Polymers Vol.1, p. 374. , J. D. Andrade. New York: Plenum Press; Takahara, A., Jo, N.J., Kajiyama, T., (1989) J. Biomater. Sci. Polym. Ed., 1, p. 17; Lide, D.R., (1996) Handbook of Chemistry and Physics, , D. R. Lider. Boca Raton: CRC Press; Van Oss, C.J., (1994) Interfacial Forces in Aqueous Media, pp. 170-177. , C. J. Van Oss. New York: Marcel Dekker Inc; Gombotz, W.R., Guanhui, W., Horebett, T.A., Hoffman, A.S., (1992) Poly(ethylene Glycol) Chemistry: Biotechnical and Biomedical Application, pp. 247-261. , J. M. Harris. New York: Plenum Press; Wu, D., Jian, K., (1995) Sci. China (B), 25, p. 1121; Wu, D., Jian, K., (1995) Sci. China (B), 26, p. 409; Ji, J., Feng, L., Qiu, Y., Yu, X., Polymer, , in press; Hester, J.F., Banerjee, P., Mayes, A.M., (1999) Macromolecules, 32, p. 1643
Keywords: Amphiphilic copolymer; article; biomaterial; copolymer; crystal; differential scanning calorimetry; electron microscopy; electron spin resonance; hydrophobicity; macrogol; polystyrene; priority journal; protein assembly; protein binding; protein structure; Self-assembly; stearic acid; Surface structure; X ray analysis

Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement - Lopes, M.A.; Knowles, J.C.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
Phase transformations and interstitial and/or substitution of trace elements during the liquid-phase sintering process of P 2O 5-CaO-MgO glass-reinforced hydroxyapatite (GR-HA) composites were examined by X-ray diffraction and Rietveld analyses. Using the Rietveld method for structure refinement, changes in the lattice parameters of the two main phases of the composites, hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP), as well as changes in several bond lengths and in the occupancy of the hydroxyl oxygen site in the HA phase structure were assessed. The glasses gave rise to formation of between approximately 45 and 50% of β-TCP, with evidence for the Mg 2+ enhancing the formation of β-TCP. Between 1300 and 1350°C, the β-TCP inverts to α-TCP, without further decomposition of the residual HA. The glasses showed evidence for stabilisation of the hydroxyl group located in the hydroxyl channels. This is supported by measurements of the hydroxyl channel radius (R(c)), the Ca 2-OH bond length and the hydroxyl oxygen occupancy (O(occ)). Results showed that the Mg 2+ containing glasses induced the β-TCP phase formation in the structure of GR-HA composites and retarded the β-TCP into α-TCP transformation at higher temperatures. The chemical composition of the P 2O 5 glasses also induces modifications in the lattice parameters of the crystallographic phases present in the microstructure of the composites. This suggests some substitution of Mg 2+-for-Ca 2+ in the β-TCP structure during the liquid-phase sintering process. Copyright (C) 2000 Elsevier Science Ltd. Phase transformations and interstitial and/or substitution of trace elements during the liquid-phase sintering process of P 2O 5-CaO-MgO glass-reinforced hydroxyapatite (GR-HA) composites were examined by X-ray diffraction and Rietveld analyses. Using the Rietveld method for structure refinement, changes in the lattice parameters of the two main phases of the composites, hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP), as well as changes in several bond lengths and in the occupancy of the hydroxyl oxygen site in the HA phase structure were assessed. The glasses gave rise to formation of between approximately 45 and 50% of β-TCP, with evidence for the Mg 2+ enhancing the formation of β-TCP. Between 1300 and 1350 °C, the β-TCP inverts to α-TCP, without further decomposition of the residual HA. The glasses showed evidence for stabilization of the hydroxyl group located in the hydroxyl channels. This is supported by measurements of the hydroxyl channel radius (R c), the Ca 2-OH bond length and the hydroxyl oxygen occupancy (O occ). Results showed that the Mg 2+ containing glasses induced the β-TCP phase formation in the structure of GR-HA composites and retarded the β-TCP into α-TCP transformation at higher temperatures. The chemical composition of the P 2O 5 glasses also induces modifications in the lattice parameters of the crystallographic phases present in the microstructure of the composites. This suggests some substitution of Mg 2+-for-Ca 2+ in the β-TCP structure during the liquid-phase sintering process.
Cited By (since 1996): 14Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(00)00068-5PubMed ID: 10919694Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto Engenharia Biomedica, Laboratorio de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: jdsantos@alf.fe.up.ptChemicals/CAS: beta-tricalcium phosphate; Biocompatible Materials; Calcium Phosphates; Hydroxyapatites; Magnesium, 7439-95-4; Trace Elements; tricalcium phosphate, 7758-87-4References: Elliot, J.C., Structure and chemistry of the apatites and other calcium orthophosphates (1994) Studies in Inorganic Chemistry, 18. , Amsterdam: Elsevier Science;Okazaki, M., Sato, M., Computer graphics of hydroxyapatite and β -tricalcium phosphate (1990) Biomaterials, 11, pp. 573-578; Hench, L.L., Wilson, J., An introduction to bioceramics (1993) Advanced Series in Ceramics, 1, pp. 139-180. , editors. Singapore: World Scientific; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15 (1), pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39 (2), pp. 244-251; Lopes, M.A., Santos, J.D., Monteiro, F.J., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Li, P., (1993) In Vitro and in Vivo Calcium Phosphate Induction on Gel Oxides, , PhD thesis, Leiden, Offsetdrukkerij Haveka B.V. ed; Hagen, A.R., Structural features of biologically involved phosphates (1970) Acta Odontol Scand, 58, pp. 149-173; Narasaraju, T.S.B., Phebe, D.E., Review: Some physicochemical aspects of hydroxylapatite (1996) J Mater Sci, 31, pp. 1-21; Kay, M.I., Young, R.A., Posner, A.S., The crystal structure of hydroxyapatite (1964) Nature, 204, pp. 1050-1052; Montel, G., Bonel, G., Heughebaert, J.C., Trombe, J.C., Rey, C., New concepts in the composition, crystallisation and growth of the mineral component of calcified tissues (1981) J Crystal Growth, 53, pp. 74-99; Fanovich, M.A., Castro, M.S., Porto López, J.M., Analysis of the microstructural evolution in hydroxyapatite ceramics by electrical characterisation (1999) Ceramics Int, 25, pp. 517-522; Bigi, A., Falini, G., Foresti, E., Gazzano, M., Ripamonti, A., Roveri, N., Rietveld structure refinements of calcium hydroxyapatite containing magnesium (1996) Acta Crystallogr, 52, pp. 87-92; Okazaki, M., Sato, M., Takahashi, J., Space-cutting model of hydroxyapatite (1995) Biomaterials, 16, pp. 45-49; Ravalgloli, A., Krajewski, A., (1992) Bioceramics, pp. 16-59. , London: Chapman & Hall; Okazaki, M., Takahashi, J., Kimura, H., Unstable behavior of magnesium-containing hydroxyapatites (1986) Caries Res, 20, pp. 324-331; Kotani, S., Fijita, Y., Kitsugi, T., Nakamura, T., Yamamuro, T., Ohtsuki, C., Kokubo, T., Bone bonding mechanism of β -tricalcium phosphate (1991) J Biomed Mater Res, 25, pp. 1303-1315; Eanes, E.D., Thermochemical studies on amorphous calcium phosphate (1970) Calcif Tiss Res, 5, pp. 133-145; De Groot, K., Klien, P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., Chemistry of calcium phosphate bioceramics (1990) Handbook of Bioactive Ceramics, 2, pp. 3-16. , T. Yamamuro, L.L. Hench, Wilson J. Boca Raton, FL: CRC Press; Legeros, R.Z., Calcium phosphates in oral biology and medicine (1991) Monographs in Oral Science, 15, pp. 87-107. , New York: Karger
Keywords: article; Biocompatible Materials; Biomedical engineering; Calcium Compounds; calcium phosphate; Calcium phosphates; Chemical bonds; chemical composition; Composition effects; Crystal lattices; Crystal microstructure; crystal structure; Crystallization; decomposition; Fiber reinforced materials; glass; Glass fibers; Glass-reinforced hydroxyapatite; Glass-reinforced hydroxyapatite composites; hydroxyapatite; Hydroxyapatites; Implants (surgical); Liquid-phase sintering; Magnesium; Mg-apatites; Models, Molecular; phase transition; Phase transitions; Phosphate minerals; priority journal; Rietveld refinement; Rietveld refinement analysis; Sintering; spectacles; structure analysis; temperature; Thermodynamics; Trace Elements; Tricalcium phosphate; X ray analysis; X ray crystallography; β-TCP

Glass-reinforced hydroxyapatite composites: Fracture toughness and hardness dependence on microstructural characteristics - Lopes, M.A.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 1999)
Fracture toughness and hardness properties of CaO-P 2O 5 glass-reinforced hydroxyapatite composites have been assessed using indentation techniques and results calculated according to Laugier and Evans' equations. Both properties showed to be dependent upon several microstructural characteristics, namely residual porosity and the percentage of secondary β and α tricalcium phosphate phases in the structure of the composites. Composites presented a Palmqvist-type indentation crack system, which is the specific crack system addressed by Laugier's approach. Fracture toughness determinations according to Evan's equation, which is a universal one and adapted to both median and Palmqvist crack systems, did not correlate well with Laugier determinations. Copyright (C) 1999 Elsevier Science Ltd. Fracture toughness and hardness properties of CaO-P 2O 5 glass-reinforced hydroxyapatite composites have been assessed using indentation techniques and results calculated according to Laugier and Evans' equations. Both properties showed to be dependent upon several microstructural characteristics, namely residual porosity and the percentage of secondary β and α tricalcium phosphate phases in the structure of the composites. Composites presented a Palmqvist-type indentation crack system, which is the specific crack system addressed by Laugier's approach. Fracture toughness determinations according to Evan's equation, which is a universal one and adapted to both median and Palmqvist crack systems, did not correlate well with Laugier determinations.
Cited By (since 1996): 65Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00112-XPubMed ID: 10535820Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratorio de Biomateriais, Instituto de Engenharia Biomedica, INEB, Rua do Campo Alegre 823, 4150 Porto, PortugalChemicals/CAS: alpha-tricalcium phosphate; Biocompatible Materials; calcium phosphate, 10103-46-5; Calcium Phosphates; Composite Resins; dicalcium phosphate anhydrous, 7757-93-9; Durapatite, 1306-06-5; monocalcium phosphate; tetracalcium phosphateReferences: Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812;Martin, R.I., Brown, P.W., Mechanical properties of hydroxyapatite formed at physiological temperature (1995) J Mater Sci Mater Med, 6, pp. 138-143; Aoki, H., (1994) Medical Applications of Hydroxyapatite, pp. 90-173. , Tokyo, Missouri, USA: Ishiyaku EuroAmerica Inc; Yamamuro, T., Hench, L., Wilson, J., Calcium phosphate and hydroxyapatite ceramics (1990) In: Handbook of Bioactive Ceramics, 2, pp. 273-335. , editors. Florida: CRC Press Inc; Cao, W., Hench, L.L., Bioactive materials (1996) Ceramics Int, 22, pp. 493-507; Davidge, R.W., (1979) Mechanical Behaviour of Ceramics, , Cambridge: Cambridge University Press; Orange, G., Liang, K.M., Crack resistance and fracture toughness of alumina and zirconia ceramics: comparisons of notched-beam and indent techniques (1988) Science of Ceramics, 14, pp. 709-714. , Amsterdam: Elsevier; Niihara, K., Morena, R., Hasselman, D.P.H., Evaluation of K IC of brittle solids by the indentation method with low crack-to-indent ratios (1982) J Mater Sci Lett, 1, pp. 13-16; Evans, G., Fracture toughness: The role of indentation techniques (1979) Fracture Mechanics Applied to Brittle Materials ASTM STP 678, pp. 112-135. , S.W. Freiman. Blasksbaurg: American Society for Testing and Materials; Anstis, G.R., Chantikul, P., Lawn, B.R., Marshall, D.B., A critical evaluation of indentation techniques for measuring fracture toughness: I. Direct crack measurements (1981) J Am Ceram Soc, 64 (9), pp. 533-538; Chantikul, P., Anstis, G.R., Lawn, B.R., Marshall, D.B., A critical evaluation of indentation techniques for measuring fracture toughness: II. Strength method (1981) J Am Ceram Soc, 64 (9), pp. 539-543; Evans, G., Charles, E.A., Fracture toughness determinations by indentation (1976) J Am Ceram Soc, 59 (78), pp. 371-372; Marion, R.H., Use of indentation fracture to determine fracture toughness (1979) Fracture Mechanics Applied to Brittle Materials, ASTM STP 678, pp. 103-111. , S.W. Freiman. Blasksbaurg: American Society for Testing and Materials; Knowles, J.C., Talal, S., Santos, J.D., Sintering effects in a glass reinforced hydroxyapatite (1996) Biomaterials, 17, pp. 1437-1442; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength (1999) J Appl Biomater, , in press; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 4, pp. 649-656; Santos, D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15 (1), pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39 (2), pp. 244-251; Laugier, M.T., New formula for indentation toughness in ceramics (1987) J Mater Sci Lett, 6, pp. 355-356; Ampiro, R., (1958) Acta Anat, 3, p. 161; De With, G., Van Dijk, H.J.A., Hattu, N., Prijs, K., Preparation, microstructure and mechanical properties of dense polycrystalline hydroxyapatite (1981) J Mater Sci, 16, pp. 1592-1598; German, R.M., (1985) Liquid Phase Sintering, , Oxford: Plenum Press; Rice, R.W., Microstructure dependence of mechanical behaviour (1977) Treatise on Materials Science and Technology, 11. , MacCrone R.K. New York: Academic Press; Rice, R.W., Grain size and porosity dependence of ceramic fracture energy and toughness at 22°C (1996) J Mater Sci, 31, pp. 1969-1983; Lankford, J., Indentation microfracture in the Palmqvist crack regime: Implications for fracture toughness evaluation by the indentation method (1982) J Mater Sci Lett, 1, pp. 493-495; Li, Z., Ghosh, A.A., Kobayashi, A.S., Bradt, R.C., Indentation fracture toughness of sintered silicon carbide in the Palmqvist crack regime (1989) J Am Ceram Soc, 72 (6), pp. 904-911; Lawn, R., Marshall, D.B., Hardness, toughness and brittleness: An indentation analysis (1980) J Am Ceram Soc, 62 (78), pp. 347-350; Niihara, K., A fracture mechanics analysis of indentation-induced Palmqvist crack in ceramics (1983) J Mater Sci Lett, 2, pp. 221-223; Plannel, J.A., Vallet-Regi, M., Fernandez, E., Driessens, F.C.M., Fracture toughness evaluation of sintered hydroxyapatite (1994) Bioceramics 7, Proceedings of the Seventh International Symposium on Ceramics in Medicine, pp. 18-22. , In: Andersson OH, Yli-Urpo A, editors; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Japanese Association of Apatite Science. Tokyo: Takayama Press System Center Co. Inc; Hauber, R.A., Anderson, R.M., Engineering properties of glass-matrix composites In: Ceramics and Glasses, Engineered Materials Handbook, pp. 858-869. , USA: ASM Publication; Barsoum, M., Mechanical properties: Fast fracture (1997) Fundamentals of Ceramics. Series in Materials Science and Engineering, pp. 391-439. , New York: McGraw-Hill; Slosarczyk, A., Bia Oskorski, J., Hardness and fracture toughness of dense calcium-phosphate based materials (1998) J Mater Sci Mater Med, 9, pp. 103-108
Keywords: article; Biocompatible Materials; Biomaterials; calcium phosphate; Calcium phosphates; ceramics; Composite materials; Composite Resins; Cracks; Durapatite; Evan's equation; Fracture toughness; glass; hardness; hydroxyapatite; Hydroxyapatite-glass composites; Indentation techniques; Kinetics; Laugier equations; material state; mechanical stress; Microscopy, Electron, Scanning; Microstructure; Palmqvist crack systems; Phosphate minerals; porosity; priority journal; Stress, Mechanical; tensile strength; Tricalcium phosphate

Histological effects of iron accumulation on mice liver and spleen after administration of a metallic solution - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (BiomaterialsBiomaterials, 1999)
Special attention has been focused on the toxicity of some metallic species released from implanted materials, which accumulate in vital organs over long periods of time. A set of experiments with mice was designed to investigate the individual effects caused by iron in the liver and spleen. Histological features of these organs were evaluated and slight morphological changes were observed during the treatment time suggesting a negative correlation with the duration of the iron treatment. In addition, to associate the histological changes in the organs with iron accumulation an electrochemical method, adsorptive stripping voltammetry, was chosen to quantify the iron levels in these mentioned organs. The accuracy of the proposed method was checked by atomic absorption spectrometry. Both organs showed elevated concentrations of iron, nearly twofold, 7 days after iron administration compared to control organs.Special attention has been focused on the toxicity of some metallic species released from implanted materials, which accumulate in vital organs over long periods of time. A set of experiments with mice was designed to investigate the individual effects caused by iron in the liver and spleen. Histological features of these organs were evaluated and slight morphological changes were observed during the treatment time suggesting a negative correlation with the duration of the iron treatment. In addition, to associate the histological changes in the organs with iron accumulation an electrochemical method, adsorptive stripping voltammetry, was chosen to quantify the iron levels in these mentioned organs. The accuracy of the proposed method was checked by atomic absorption spectrometry. Both organs showed elevated concentrations of iron, nearly twofold, 7 days after iron administration compared to control organs.
Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00124-6PubMed ID: 10555088Language of Original Document: EnglishCorrespondence Address: Pereira, M.C.; Departamento de Engenharia Quimica, Faculdade de Engenharia, Universidade do Porto, Rua dos Bragas, 4050-123 Porto, Portugal; email: mcsp@fe.up.ptChemicals/CAS: Iron, 7439-89-6; SolutionsReferences: Rheinold, J.B., Trace elements - A selective survey (1975) Clin Chem, 21, p. 476;Crichton, R.R., Ward, R.J., Structure and molecular biology of iron binding-proteins and the regulation of free iron pools (1992) Iron and Human Diseases, pp. 23-75. , R.B. Lauffer. Boca Raton: CRC Press Inc; Lynch, S.R., Lipschitz, D.A., Bothwell, T.H., Charlton, R.W., Iron and the reticulo-endothelial system (1974) Iron in Biochemistry and Medicine, p. 563. , A. Jacobs, & M. Worwood. London: Academic Press; Black, J., Mineral metabolism (1981) Biological Performance of Materials: Fundamentals of Biocompatibility. Biomedical Engineering and Instrumentation, 8, pp. 158-168. , R. Plonsey, Katz J.L. New York: Marcel Dekker; Sutow, E.J., Pollack, S.R., The biocompatibility of certain stainless steels (1981) Biocompatibility of Clinical Implant Materials, pp. 77-98. , D.F. Williams. Boca Raton, FL: CRC Press; Winter, G.D., Tissue reactions to metallic wear and corrosion products in human patients (1974) J Biomed Mater Res Symp, 5, pp. 11-26; Winter, G.D., Wear and corrosion products in tissues and the reactions they provoke (1976) Biocompatibility of Implant Materials, pp. 28-54. , In: Williams, DF, editor London; Ferguson A.B., Jr., Laing, P.G., Hodge, E.S., The ionization of metal implants in living tissues (1960) J Bone Jt Surg a, 42, pp. 77-90; Pohler, O.E.M., Degradation of metallic orthopedic implants (1983) Biomaterials in Reconstructive Surgery, pp. 196-197. , In: Rubin LR, editor London: The C.V. Mosby Company; Lux, F., Zeisler, R., Investigations of the corrosive deposition of components of metal implants and the behaviour of biological trace elements in metallosis tissue by means of instrumental multi-element activation analysis (1974) J Radioanal Chem, 19, pp. 289-297; Traisnel, M., Le Maguer, D., Hildebrand, H.F., Iost, A., Corrosion of surgical implants (1990) Clin Mater, 5, pp. 309-318; Gosztonyi, E., (1983) Iron Metabolism, p. 339. , New York: Plenum Press; Weinberg, E.D., Cellular acquisition of iron and the iron-withholding defense against microbial and neoplastic invasion (1992) Iron and Human Diseases, pp. 179-207. , R.B. Lauffer. Boca Raton, FL: CRC Press Inc; Pereira, M.L., Pereira, M.C., Sousa, J.P., Evaluation of nickel effects on mouse liver: Tissue response and metal ion accumulation (1995) Biomed Lett, 52, pp. 235-244; Pereira, M.C., Pereira, M.L., Sousa, J.P., Evaluation of nickel toxicity on liver, spleen and kidney of mice after administration of high-dose metal ion (1998) J Biomed Mater Res, 40, pp. 40-47; Pereira, M.C., Sousa, J.P., Nickel quantification in mice organs by adsorptive cathodic stripping voltammetry using microelectrodes (1997) Electroanalysis, 9, pp. 150-154; Pereira, M.C., Pereira, M.L., Sousa, J.P., Adsorptive stripping measurements of iron accumulation in mice kidney using microelectrodes and histological features (1998) J Trace Elements Med Biol, 12, pp. 50-55; Van Den Berg, C.M.G., Huang, Z.Q., Determination of iron in seawater using cathodic stripping voltammetry proceeded by adsorptive collection with the hanging mercury drop electrode (1984) J Electroanal Chem, 177, pp. 269-280; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 223-247. , A.C. Fraker, & C.D. Griffin. Philadelphia: American Society for Testing and Materials; Barbosa, M.A., (1991) Biomaterials Degradation, p. 227. , Barbosa M.A. The Netherlands: Elsevier Science Publisher; Steinemann, S.G., Corrosion of surgical implants in vivo and in vitro tests (1980) Evaluation of Biomaterials, pp. 1-34. , In: Winter GD et al., editors UK: John Wiley & Sons Inc; Smith, G.K., Systemic aspects of metallic implant degradation (1983) Biomaterials in Reconstructive Surgery, pp. 229-242. , In: Rubin LR, London: The C.V. Mosby Company; Britton, S.R., Ramm, G.A., Olynyk, J., Singh, R., O'Neill, R., Bacon, B.R., Pathophysiology of iron toxicity (1994) Progress in Iron Research, pp. 239-253. , C. et al. Hershko. New York: Plenum Press
Keywords: Absorption spectroscopy; accuracy; Adsorption; Adsorptive stripping voltametry; Adsorptive stripping voltammetry; animal experiment; animal model; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Atomic spectroscopy; bioaccumulation; biomaterial; controlled study; Corrosion; electrochemistry; histology; histopathology; Implants (surgical); Injections, Subcutaneous; Iron; iron metabolism; Kinetics; Liver; liver toxicity; male; metal implantation; Mice; morphology; mouse; nonhuman; Organ Size; potentiometry; priority journal; quantitative assay; Solutions; Spleen; Stainless steel; tissue distribution; toxicity

In vitro growth and differentiation of osteoblast-like human bone marrow cells on glass reinforced hydroxyapatite plasma-sprayed coatings - Ferraz, M.P.; Fernandes, M.H.; Cabral, A.T.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1999)
Human osteoblastic bone marrow cells were cultured far periods of up to 28 days in control conditions and on the surface of a glass reinforced hydroxyapatite composite (HA/G1) and commercial hydroxyapatite (HA) plasma-sprayed coatings, in the 'as-received' condition and after immersion treatment in culture medium for 21 days. Cultures were characterized for total protein content and alkaline phosphatase activity. Scanning electron microscope analyses were performed on control cultures, seeded materials and materials incubated in the absence of cells. Culture media were analyzed for total and ionized calcium and phosphorus concentrations throughout the incubation period. Immersion of HA/G1 and HA coatings in culture medium resulted in significant alterations to the levels of calcium and phosphorus in the medium, leading to surface modifications. However, seeded material samples showed significant differences in the pattern of variation of the levels of these species. Cell proliferation was observed in the 'as-received' HA/G1 composite, but cell mediated formation of mineral deposits was not proved. In contrast, 'as-received' HA hardly supported cell growth. Previously immersed material samples showed cell proliferation and evidence of biological formation of mineral deposits. However, the HA/G1 composite presented better surface characteristics for cell growth as the behavior of bone marrow eel Is was closer to that observed in control cultures.Human osteoblastic bone marrow cells were cultured for periods of up to 28 days in control conditions and on the surface of a glass reinforced hydroxyapatite composite (HA/G1) and commercial hydroxyapatite (HA) plasma-sprayed coatings, in the 'as-received' condition and after immersion treatment in culture medium for 21 days. Cultures were characterized for total protein content and alkaline phosphatase activity. Scanning electron microscope analyses were performed on control cultures, seeded materials and materials incubated in the absence of cells. Culture media were analyzed for total and ionized calcium and phosphorus concentrations throughout the incubation period. Immersion of HA/G1 and HA coatings in culture medium resulted in significant alterations to the levels of calcium and phosphorous in the medium, leading to surface modifications. However, seeded material samples showed significant differences in the pattern of variation of the levels of these species. Cell proliferation was observed in the 'as-received' HA/G1 composite, but cell mediated formation of mineral deposits was not proved. In contrast, 'as-received' HA hardly supported cell growth. Previously immersed material samples cell proliferation and evidence of biological formation of mineral deposits. However, the HA/G1 composite presented better surface characteristics for cell growth as the behavior of bone marrow cells was closer to that observed in control cultures.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1008924516146Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Institute of Biomedical Engineering, Faculties of Dental Medicine, Universidade do Porto, 4200 Porto, PortugalChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium ion, 14127-61-8; hydroxyapatite, 1306-06-5, 51198-94-8; phosphorus, 7723-14-0; protein, 67254-75-5References: Passuti, N., Daculsi, G., Martin, S., (1990) Clinical Implant Materials, p. 255. , edited by V. Soltesz and A. Lee (Elsevier, Amsterdam);Legeros, R., (1988) Adv. Dental Res., 2, p. 164; Hench, L.L., (1992) J. Amer. Ceram. Soc., 74, p. 1487; Kokubo, T., (1993) Bone-Bonding Biomaterals, p. 31. , edited by P. Ducheyne, T. Kokubo and C. A. Blitterswijk (Reed Health-Care Comunications, Leiden, The Netherlands); Daculsi, G., Legeros, R.Z., Henghebaert, M., Barbieux, I., (1990) Calcif. Tissue Int., 46, p. 20; Bagambisa, F.B., Joos, U., Schilli, W., (1993) J. Biomed. Mater. Res., 27, p. 1047; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., (1995) J. Biomed. Mater. Res., 29, p. 89; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , JAAS; Raemdonck, W., Ducheyne, P., Meester, P., (1984) Metal and Ceramic Materials, p. 143. , edited by P. Ducheyne and G. W. Hastings (CRC Press, Boca Raton, FL); Rey, C., Freche, M., Heughebaert, M., Vignoles, M., (1991) Bioceramics 4, p. 57. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner (Butterworth-Heinemann, London); Nagase, M., Abe, Y., Udagawa, E., (1992) Biomaterials, 13, p. 172; Burnie, J., Gilchrist, T., (1993) Ceramics in Surgery, p. 169. , edited by P. Vincenzini (Elsevier, Amsterdam); Burnie, F., Gilchrist, T., Ceramics in Surgery, p. 177; Rawlings, R.D., Rogers, P.S., Stokes, P.M., (1987) High Tech Ceramics, p. 73. , edited by P. Vincenzini (Elsevier, Amsterdam); Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Santos, J.D., Lakhan, J.J., Monteiro, F.J., (1995) Biomaterials, 16, p. 521; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1995) J. Mater. Sci. Mater. Med., 6, p. 348; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., (1991) J. Biomed. Mater. Res., 25, p. 53; Jansen, J.A., Van Der Waerden, J.P.C.M., Wolke, J.G.C., (1993) J. Mater. Sci. Mater. Med., 4, p. 466; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., (1992) J. Biomed. Mater. Res., 26, p. 1365; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., (1994) J. Mater. Sci. Mater. Med., 5, p. 11; Lugscheider, E., Knepper, M., Heimberg, B., Dekker, A., Kirkpatrick, C.J., (1994) J. Mater. Sci. Mater. Med., 5, p. 371; Courteney-Harris, R.G., Kayser, M.V., Downes, S., (1995) Biomaterials, 16, p. 489; Labat, B., Chanson, A., Frey, J., (1995) J. Biomed. Mater. Res., 29, p. 1397; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., (1996) J. Mater. Sci. Mater. Med., 7, p. 21; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., (1997) J. Biomed. Mater. Res., 34, p. 247; Ong, J.L., Prince, C.W., Lucas, L.C., (1995) J. Biomed. Mater. Res., 29, p. 165; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., (1995) J. Mater. Sci. Mater. Med., 6, p. 144; Amédée, J., Bareille, R., Jeandot, R., Bordenave, L., Rémy, M., Rouais, F., Baquey, C., (1994) Biomaterials, 15, p. 1029; Maniatopoulos, C., Sodek, J., Melcher, A., (1988) Cell Tissue Res., 254, p. 317; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., (1990) J. Cell Phys., 143, p. 213; Gundle, R., Joyner, C.J., Triffit, J.T., (1995) Bone, 16, p. 597; Fernandes, M.H., Costa, M.A., Carvalho, G.S., (1997) J. Mater. Sci. Mater. Med., 8, p. 61; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., (1997) J. Mater. Sci. Mater. Med., 8, p. 233; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., (1996) J. Mater. Sci. Mater. Med., 7, p. 291; Morais, S., Dias, N., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., (1999) J. Biomed. Mater. Res., 44, p. 176; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Min., 14, p. 27; Ferraz, M.P., Monteiro, F.J., Santos, J.D., J. Biomed. Mater. Res., , submitted; Owen, T.A., Aronow, M., Shalhoub, V., (1990) J. Cell Phys., 143, p. 420; Martin, T.J., Findlay, D.M., Heath, J.K., Ng, K.W., (1993) Handbook of Experimental Pharmacology, p. 149. , edited by J. R. Mundy and T. J. Martin Berlin (Springer-Verlag); Stein, G.S., Lian, J.B., (1993) Cellular and Molecular Biology of Bone, p. 47. , edited by M. Noda (Academic Press, Tokyo); Anderson, H.C., Morris, D.C., (1993) Handbook of Experimental Pharmacology, p. 267. , edited by J. R. Mundy and T. J. Martin Berlin (Springer-Verlag); Gwynn, I.A.P., (1994) J. Mater. Sci. Mater. Med., 5, p. 357; Kirkpatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., (1997) J. Mater. Sci. Mater. Med., 8, p. 131; Legeros, R.Z., Orly, I., Gregoire, M., Daculsi, G., (1991) The Bone-Biomaterial Interface, p. 76. , edited by J. E. Davies (University of Toronto Press, Toronto); Chern Lin, J.H., Liu, M.L., Ju, C.P., (1994) J. Biomed. Mater. Res., 28, p. 723; Ghannam, E.L., Ducheyne, P., Spapiro, I., (1995) J. Biomed. Mater. Res., 29, p. 359; Radin, S.R., Ducheyne, P., (1993) J. Biomed. Mater. Res., 27, p. 35; Radin, S.R., Ducheyne, P., (1993) J. Biomed. Mater. Res., 27, p. 1047; Best, S., Sim, B., Kayser, M., Downes, S., (1997) J. Mater. Sci. Mater. Med., 8, p. 97
Keywords: adult; alkaline phosphatase; article; Bone; bone marrow cell; Bone replacement materials; Calcium; calcium ion; case report; Cell culture; cell differentiation; cell growth; Cells; controlled study; culture medium; enzyme activity; Enzyme kinetics; glass; Growth kinetics; human; Human bone marrow cell; human cell; hydroxyapatite; male; osteoblast; Phosphates; phosphorus; priority journal; protein; protein determination; Proteins; scanning electron microscope; Scanning electron microscopy; Sprayed coatings

Adsorptive stripping measurements of iron accumulation in mice kidney using microelectrodes and histological features - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 1998)
The toxic effects caused by iron in kidney was performed on experimental studies with mice following administration of a metallic solution of this specie to simulate the iron corrosion products of a metallic implant. To quantify the total levels of iron present in this organ, an electrochemical method was chosen based on the application of square wave voltammetry using adsorptive collection of iron-catechol on a mercury film microelectrode (MFM). The optimal working conditions to produce a very stable and reproducible iron peak in the digested kidney samples were found to be pH=7.2 provided by 8.0 mmol/L PIPES buffer, catechol concentration of 3.0x10
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JTEBFPubMed ID: 9638613Language of Original Document: EnglishCorrespondence Address: Sousa, J.P.; INEB-Inst. de Engenharia Biomedica, Departamento de Engenharia Quimica, Faculdade Engenharia Univ. do Porto, Praca do Coronel Pacheco, 1, 4050 Porto, PortugalChemicals/CAS: Iron, 7439-89-6; Mercury, 7439-97-6References: Traisnel, M., Le Maguer, D., Hildebrand, H.F., Iost, A., Corrosion of surgical implants (1990) Clin. Mater., 5, pp. 309-318;Sutow, E.J., Pollack, S.R., The biocompatibility of certain stainless steels (1981) Biocompatibility of Clinical Implant Materials, 1, pp. 77-98. , Williams, D.F. eds CRC Press, Boca Raton, Florida; Ferguson Jr., A.B., Laing, P.G., Hodge, E.S., The ionization of metal implants in living tissues (1960) J. Bone Joint Surg., 42 A, pp. 77-90; Winter, G.D., Wear and corrosion products in tissues and the reactions they provoke (1976) Biocompatibility of Implant Materials, pp. 28-54. , Williams, D.F. eds London; Lux, F., Zeisler, R., Investigations of the corrosive deposition of components of metal implants and the behaviour of biological trace elements in metallosis tissue by means of instrumental multi-element activation analysis (1974) J. Radioanal. Chem., 19, pp. 289-297; Merritt, K., Brown, S.A., Sharkey, N.A., Blood distribution of nickel, cobalt, and chromium following intramuscular injection into hamsters (1984) J. Biomed. Mater. Res., 18, pp. 991-1004; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 195-207. , Fraker, A.C., Griffin, C.D. eds American Society for Testing and Materials, Philadelphia; K. Merritt, K.A., Brown, S.A., Metal sensitivity reactions to bone screws in rabbits (1982) Clinical Applications of Biomaterials, pp. 85-93. , John Wiley & Sons Ltd; Woodman, J.L., Black, J., Jimenez, S., Organometallic corrosion products of 316L SS HS-21 in serum: In vitro and in vivo comparison in an acute rat model (1982) Biomaterials 1980, pp. 245-250. , Winter, G.D., Gibbons, D.F., Plenk, Jr., H. John Wiley & Sons Ltd; Merritt, K., Crowe, T.D., Brown, S.A., Elimination of nickel, cobalt, and chromium following repeated injections of high dose metal salts (1989) J. Biomed. Mater. Res., 23, pp. 845-862; Pereira, M.L., Pereira, M.C., Sousa, J.P., Evaluation of nickel effects on mouse liver: Tissue response and metal ion accumulation (1995) Biomedical Letters, 52, pp. 235-244; Pereira, M.C., Pereira, M.L., Sousa, J.P., Evaluation of nickel toxicity on liver, spleen and kidney of mice after administration of high-dose metal ion (1997) J. Biomed. Mater Res., pp. XXXXXX. , in press; Schafer, B.A.I., Cheron, R.G., Dluhy, R., Cooper, B., Gleason, R.E., Soeldner, J.S., Bunn, H.F., Clinical consequences of acquired transfusional iron overload in adults (1981) N Engl. J. Med., 304, p. 319; Black, J., Mineral metabolism (1981) Biological Performance of Materials: Fundamentals of Biocompatibility. Biomedical Engineerins and Instrumentation Series, pp. 158-168. , Plonsey R., Katz, J.L. Marcel Dekker; Bernat, I., Iron deficiency (1983) Iron Metabolism, pp. 215-274. , Plenum Press, New York; Nakamura, K., Watanabe, H., Orii, H., Direct measurement of iron in serum by electrothermal atomic absorption spectrometry (1980) Anal. Chim. Acta., 108, pp. 67-71; Van Beek, H., Greefkes, H.C.A., Baars, A.J., Determination of copper, iron, manganese, lead and cadmium in automatically wet-digested animal tissue by graphite-furnace atomic absorption spectrometry with Zeeman background correction (1993) Talanta., 34, pp. 580-582; Van Wyck, D.B., Schifman, R.B., Stivelman, J.C., Ruiz, J., Martin, D., Rapide sample preparation for determination of iron in tissue by closed-vessel digestion and microwave energy (1988) Clin. Chem., 34 (6), pp. 1128-1130; Chakraborti, D., Burguera, M., Burguera, J.L., Analysis of standard reference materials after microwave-oven digestion in open vessels using graphite furnace atomic absorption spectrophotometry and Zeeman-effect background correction (1993) Fresenius J. Anal. Chem., 347, pp. 233-237; Lugowski, S., Smith, D.C., Van Loon, J.C., The determination of At, Cr, Co, Fe, and Ni in whole blood by electrothermal atomic absorption spectrophotometry (1987) J. Biomed. Mater. Res., 21, pp. 657-674; Wightman, R.M., Microvoltammetric electrodes (1981) Anal. Chem., 53, pp. 1125A-1134A; Pletcher, D., Why microelectrodes? (1991) Microelectrodes: Theory and Applications, pp. 3-16. , Montenegro, M.I., Queirós, M.A., Daschbach, J.L eds NATO-ASI, Kluwer Academic Publishers, the Netherlands; Wojciechowski, M., Go, W., Osteryoung, J., Square-wave anodic stripping analysis in the presence of dissolved oxygen (1984) Anal. Chem., 57, pp. 155-158; Kalvoda, R., Kopanica, M., (1989) Pure & Appl. Chem., 61, pp. 97-112; Wang, J., Principles (1985) Stripping Analysis, pp. 9-64. , VCH publishers, Inc; Perejra, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., Nickel quantification in mice organs by adsorptive cathodic stripping voltammetry using mercury microelectrodes (1996) Electroanalysis, 9, pp. 150-154; Van Den Berg, C.M.G., Huang, Z.Q., Determination of iron in seawater using cathodic stripping voltammetry preceded by adsorptive collection with the hanging mercury drop electrode (1984) J. Electroanal. Chem., 177, pp. 269-280; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell cultures medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9; Wang, J., Mannino, S., Application of adsorptive stripping voltammetry to the speciation and determination of iron (III) and total iron in wines (1989) Analyst, 114, pp. 643-645; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 223-247. , Fraker, A.C. and Griffin. Eds. American Society for Testing Materials; Pereira, M.C., Sousa, J.P., Determination of total iron in biological sample solutions with mercury microelectrodes (1996) Portugaliae Electrochimica Acta, 14, pp. 273-278; Pereira, M.C., Pereira, M.L., Sousa, J.P., Adsorptive stripping voltammetric measurements of chromium accumulation in mice organs using mercury microelectrodes (1997) Electroanalysis, 9, pp. 941-944
Keywords: , biomaterials; Adsorptive stripping; animal experiment; animal model; animal tissue; Animals; article; atomic absorption spectrometry; biomaterial; controlled study; electrochemical analysis; electrochemistry; histology; Iron; iron absorption; Kidney; male; Mercury; metal implantation; Mice; microelectrode; Microelectrodes; mouse; nonhuman; potentiometry; priority journal; Toxicology

Chromium determination in osteoblast-like cell culture medium by catalytic cathodic stripping voltammetry with a mercury microelectrode - Morais, S.; De Carvalho, G.S.; Sousa, J.P. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 1998)
A catalytic cathodic stripping voltammetric procedure for the determination of total chromium in osteoblast-like cell culture medium using a mercury film microelectrode (MFM) was optimised. The method is based on the pre-concentration of the Cr(III)-diethylenetriaminepentaacetic acid (DTPA) complex by adsorption at the potential of -1.00 V (vs. Ag/AgCl) in the presence of 10 x 10
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JTEBFPubMed ID: 9760419Language of Original Document: EnglishCorrespondence Address: Morais, S.; Inst. Engenharia Biomedica (INEB), Praca Coronel Pacheo 1, 4050 Porto, PortugalChemicals/CAS: Acetates; Chromium, 7440-47-3; Culture Media; Mercury, 7439-97-6; NitratesReferences: Ferguson Jr., A.B., Laing, P.G., Hodge, E.S., The ionization of metal implants in living tissues (1960) J. Bone Joint Surg., 42 A, pp. 77-90;Ferguson Jr., A.B., Akahoshi, Y., Laing, P.G., Hodge, E.S., Trace metal ion concentration in the liver, kidney, spleen and lung of normal rabbits (1962) J Bone Joint Surg., 44 A, pp. 317-322; Ferguson Jr., A.B., Akahoshi, Y., Laing, P.G., Hodge, E.S., Characteristics of trace ions released from embedded metal implants in the rabbit (1962) J. Bone Joint Surg. 1962, 44 A, pp. 323-336; Lux, F., Ziesler, R., Investigations of the corrosive deposition of components of metal implants and of the behaviour of biological trace elements in metallosis tissue by means of instrumental multi-elemental activation analysis (1974) J. Radioanal. Chem., 19, pp. 289-297; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 223-247. , ASTM STP 859 (Fraker, A. C. and Griffin, C. D. ,Eds.). American Society for Testing and Materials, Philadelphia; Minski, M.J., Dobbs, H.S., (1980) Trace Element Analytical Chemistry in Medicine and Biology, pp. 339-350. , Bratter, P., Schramel, P., Eds., Walter de Gruyter, Berlin; Smith, G.K., (1982) Systemic Transport and Distribution of Iron and Chromium from 316L Stainless Steel Implants, , Ph.D. Thesis, University of Pennsylvania, Philadelphia; Brown, S.A., Farnsworth, L.J., Merritt, K., Crowe, T.D., In vitro and in vivo metal ion release (1988) J. Biomed. Materials Research, 22, pp. 321-338; Lucas, L.C., Bearden, L.J., Lemons, J.E., Ultrastructural examination of in vitro and in vivo cells exposed to elements from type 316L stainless steel (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 208-222. , ASTM STP 859 (Fraker, A. C. and Griffin, C. D., Eds.), American Society for Testing and Materials, Philadelphia; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 195-207. , ASTM STP859 (Fraker, A. C. and Griffin, C. D., Eds.), American Society for Testing and Materials, Philadelphia; Smith, G.K., Black, J., Models for systemic effects of metallic implants (1977) NBS Special Publication 472, pp. 23-28. , Weinstein, A., Eds., U. S. Government Printing Office, Washington D. C; Deutman, R., Mulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J. Bone Jt. Surg., 59 A, pp. 862-865; Crosmun, S.T., Mueller, T.R., The determination of chromium (VI) in natural waters by differential pulse polarography (1975) Anal. Chim. Acta, 75, pp. 199-205; Golimowski, J., Valenta, P., Nurnberg, H.W., Trace determination of chromium in various water types by adsorption differential pulse polarography (1985) Fresenius Z. Anal. Chem., 322, pp. 315-322; Boussemart, M., Van Den Berg, C.M.G., Ghaddaf, M., The determination of the chromium speciation in sea water using catalytic cathodic stripping voltammetry (1992) Anal. Chim. Acta, 262, pp. 103-115; Paneli, M., Voulgaropoulos, A.V., Kalcher, K., The catalytic adsorptive stripping voltammetry determination of chromium with TTHA and nitrate (1993) Mikrochim. Acta, 110, pp. 205-215; Wang, J., Lu, J.A., Olsen, K., Measurement of ultratrace levels of chromium by adsorptive-catalytic stripping voltammetry in the presence of cupferron (1992) Analyst, 117, pp. 1913-1917; Nurnberg, H.W., Studies on toxic trace metals in the environment by advanced polarographic methods (1978) Proc. Analyt. Div. Chem. Soc., 15, pp. 275-283; Ottaway, J.M., Fell, G.S., Determination of chromium in biological materials (1986) Pure and Applied Chemistry, 58, pp. 1707-1720; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of nickel in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionised calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8, pp. 1174-1178; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast-like cells: Part I- Retardation of tissue mineralisation by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., Bruijn, J.D., Van Blitterswijk, C.A., Decreased consumption of Ca and P during in vitro biomineralisation and biologically-induced deposition of Ni and Cr in the presence of stainless steel corrosion products (1998) J. Biomed. Mater. Res., , in press; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro osteoblastic differentiation of human bone marrow cells in the presence of metal ions (1998) J. Biomed. Mater. Res., , in press; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res., 254, pp. 317-330; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, M., Tolg, G., Wet mineralisation of organic matrices in glassy carbon vessels in a pressure-bomb system for trace element analysis (1979) Talanta, 26, pp. 681-691; Peng, J., Jin, W., Anodic stripping voltammetric determination of trace lead in micro-samples with a mercury-ultramicroelectrode (1992) Anal. Chim. Acta, 264, pp. 213-219; Wehmeyer, K.R., Wightman, R.M., Cyclic voltammetry and anodic stripping voltammetry with mercury ultramicroelectrodes (1985) Anal. Chem., 57, pp. 1989-1993; Wightman, R.M., Wiptd, O., Voltammetry at ultramicroelectrodes (1989) Electroanalytical Chemistry, 15, pp. 335-336. , Bard, A. J., Ed., Marcel, Dekker, New York; Wurfels, M., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid Part 3 a (1989) Anal. Chim. Acta, 226, pp. 31-41; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast-like cells: Part II- Characterisation of cellular culture supernatants (1998) Biomaterials, 19, pp. 23-29; Wurfels, M., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid Part 2 a (1989) Anal. Chim. Acta, 226, pp. 17-30; Gilbert, T.R., Clay, A.M., Determination of chromium in sea water by atomic absorption spectrometry (1973) Anal. Chim. Acta, 67, pp. 289-295; Ping, L., Matsumoto, K., Fuwa, K., Determination of urinary chromium levels for healthy men and diabetic patients by electric thermal atomic absorption spectrometry (1983) Anal. Chim. Acta, 147, pp. 205-212; Torrance, K., Gatford, C., Determination of soluble chromium in simulated PWR coolant by differential-pulse adsorptive stripping voltammetry (1987) Talanta, 34, pp. 939-944; Lanza, P., Taddia, M., The differential pulse polarographic determination of chromium in gallium arsenide (1984) Anal. Chim. Acta, 157, pp. 37-44; Miller, J.N., Basic statistical methods for analytical chemistry. Part 2: Calibration and regression (1991) Analyst, 116, pp. 3-14; Ringbom, A., (1963) Complexation in Analytical Chemistry, pp. 332-333. , Elving, P. J. and Kolthoff, I. M., Eds, Interscience Publishers, New York/London; Black, J., Maitin, E.C., Gelman, H., Morris, D.M., Serum concentrations of Cr, Co, and Ni after total hip replacement: A six months study (1983) Biomaterials, 4, pp. 160-164; Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8; Dobbs, H.S., Minski, J., Metal ion release after total hip replacement (1980) Biomaterials, 1, pp. 193-198; Katz, S., Salem, H., The toxicology of chromium with respect to its speciation: A review (1993) J. Applied Toxicology, 13, pp. 217-224; Bianchi, V., Toso, R.D., Debetto, P., Mechanisms of chromium toxicity in mammalian cell cultures (1980) Toxicology, 17, pp. 219-224; Hopkins, L.L., Schwartz, K., Chromium (III) binding to serum proteins, specifically siderophilin (1964) Biochem. Biophys. Acta, 90, pp. 484-491; Nurnberg, H.W., The voltammetric approach in trace metal chemistry of natural waters and atmospheric precipitation (1984) Anal. Chim. Acta, 164, pp. 1-21
Keywords: Acetates; animal cell; Animalia; Animals; article; atomic absorption spectrometry; Bone Marrow Cells; catalysis; Cell culture; Cells, Cultured; Chromium; complex formation; controlled study; Culture Media; culture medium; drug determination; electrochemistry; Electrodes; Hydrogen-Ion Concentration; in vitro study; Kinetics; Mercury; microelectrode; Microelectrodes; Nitrates; nonhuman; osteoblast; Osteoblasts; potentiometry; priority journal; Rabbits; Reproducibility of Results; sensitivity and specificity; Stromal Cells; technique

Effects of AISI 316L corrosion products in in vitro bone formation - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S.; De Bruijn, J.D.; Van Blitterswijk, C.A. (BiomaterialsBiomaterials, 1998)
Rat bone marrow cells were cultured in experimental conditions that favour the proliferation and differentiation of osteoblastic cells (i.e., 2.52 x 10
Cited By (since 1996): 38Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00234-2PubMed ID: 9692798Language of Original Document: EnglishCorrespondence Address: Morais, S.; Universidade do Porto, Porto, PortugalChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium Phosphates; Calcium, 7440-70-2; Phosphorus, 7723-14-0; Stainless Steel, 12597-68-1References: Spector, M., Cease, C., Tong-Li, X., The local tissue response to biomaterials (1989) Crit Rev Biocompat, 5, pp. 269-295;Van Blitterswijk, C.A., Bakker, D., Hesseling, S.C., Koerten, H.K., Reactions of cells at implant surfaces (1991) Biomaterials, 12, pp. 187-193; Bagambisa, F.B., Kappert, H.F., Schilli, W., Interfacial reactions of osteoblasts to dental and implant materials (1994) J Oral Maxillofac Surg, 52, pp. 52-56; Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., Initial bone matrix formation at the hydroxyapatite interface in vivo (1995) J Biomed Mat Res, 29, pp. 89-99; Pilliar, R.M., Porous-surface metallic implants for orthopedic applications (1987) J Biomed Mat Res, 21 (A1), pp. 1-33; Bobyn, J.D., Tanzer, M., Drygier, J.J., Du Joune, A.R., Brooks, C.E., Concerns with modularity in total hip arthroplasty (1994) Clin Orthop, 298, pp. 27-36; Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8; Dorr, L.D., Blocbaum, R., Emmanual, J., Meldrum, R., Histologic, biochemical and ion analysis of tissue and fluids retrieved during total hip arthroplasty (1990) Clin Orthop, 261, pp. 82-95; Hennig, F.F., Raithel, H.J., Schaller, K.H., Dohler, J.R., Nickel-chromand cobalt-concentrations in human tissue and body fluids of hip prosthesis patients (1992) J Trace Elem Electrolytes Health Dis, 6, pp. 239-243; Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J Bone Jt Surg, 56 B, pp. 626-642; Deutman, R., Rulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J Bone Jt Surg, 59 A, pp. 862-865; Huo, M.H., Salvati, E.A., Lieberman, Jr., Betts, F., Bansal, M., Metallic debris in femoral endoseolysis in failed cemented total hip arthroplasties (1992) Clin Orthop, 276, pp. 157-168; Kirkpatrick, C.J., Mittermayer, C., Theoretical and practical aspects of testing potential biomaterials in vitro (1990) J Mat Mat Med, 1, pp. 9-13; Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytotoxicity in vitro (1992) Regulatory Affairs, 4, pp. 13-22; Pizzoferrato, A., Ciapetti, G., Stea, S., Cell culture methods for testing biocompatibility (1994) Clin Mat, 15, pp. 173-190; Bizios, R., Mini review: Osteoblasts: An in vitro model of bone-implant interactions (1994) Biotechnol and Bioeng, 43, pp. 582-585; Pules, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 109-116; Thompson, G.J., Pules, D.A., Effects of sublethal metal ion concentrations on osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 249-258; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures (1996) J Mater Sc Mater Med, 7, pp. 291-296; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., The use of rat, rabbit or human bone marrow derived cells for cytocompatibility evaluation of metallic elements (1997) J Mater Sc Mater Med, 8, pp. 233-238; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast-like cells: Part 1 - Retardation of tissue mineralisation by metal salts Biomaterials 1998; Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., Toxic effects caused by stainless steel corrosion products on mouse seminiferous cells (1994) Cytobios, 77, pp. 73-80; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Chromium accumulation and ultrastructural changes in the mouse liver caused by stainless steel corrosion products (1995) J Mater Sci Mater Med, 6, pp. 523-527; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel corrosion products cause alterations on mouse spleen cellular populations (1995) J Mater Sci Mater Med, 6, pp. 56-61; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., Metals electrochemically dissolved in human serum inhibit T-lymphocyte function (1992) Advances in Biomaterials, pp. 7-11. , Doherty PJ et al., editors. Amsterdam: Elsevier; Carvalho, G.S., Castanheira, M., Diogo, I., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1995) J Mater Sci Mater Med, 7, pp. 77-83; Pohler, O.E.M., Degradation of metallic orthopedic implants Biomaterials in Reconstructive Surgery, pp. 158-228. , Rubin LR, editor. St. Louis: C. V. Mosby, 1983; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tiss Res, 254, pp. 317-330; McGee-Russell, S.M., Histochemical methods for calcium (1958) J Histochem Cytochem, 6, pp. 22-42; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionized calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8, pp. 1174-1178; Fiske, C.H., Subbarow, Y., The colorimetric determination of phosphorus (1925) J Biol Chem, 66, pp. 373-400; Miller, J.C., Miller, J.N., (1993) Statistics for Analytical Chemistry (3rd Ed.), pp. 32-35. , Massen M, Tyson J, Stockwell P, Miller J, Chalmers R, Harwood E, editors. New York, London: Ellis Horwood, PTR Prentice Hall; De Bruijn, J.D., Cpat, K., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the one-hydroxyapatite interface in vitro (1992) J Biomed Mat Res, 26, pp. 1365-1382; Davies, J.E., Chernecky, R., Lowenberg, B., Shiga, A., Deposition and resorption of calcified matrix in vitro by rat marrow cells (1991) Cells and Mat, 1, pp. 3-15; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulte formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralization of osteoblastic cells derived from human bone (1990) Bone Min, 8, pp. 239-250; Cheng, S.L., Yang, J.W., Riffins, L., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Min, 17, pp. 15-29; Boskey, A.L., Stiner, D., Doty, S.B., Binderman, I., Levoy, P., Studies of mineralization in tissue culture: Optimal conditions for cartilage calcification (1992) Bone Min, 16, pp. 11-36; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Min, 14, pp. 27-40; Chung, C.H., Golub, E.E., Forbes, E., Mechanisms of action of β-glycerophosphate on bone cell mineralization (1992) Calcif Tissue Int, 51, pp. 305-311
Keywords: Absorption spectroscopy; alkaline phosphatase; animal cell; Animal cell culture; Animals; article; ascorbic acid; atomic absorption spectrometry; Bioassay; Biomaterials; bone development; bone marrow cell; Bone Marrow Cells; Calcium; Calcium phosphates; Cell culture; Cell Death; Cells, Cultured; Corrosion; Corrosion products; culture medium; dexamethasone; electrochemical analysis; electrochemistry; Enzymes; glycerophosphate; histochemistry; Histocytochemistry; in vitro study; male; metal ion; Mineralisation; mineralization; nonhuman; ossification; osteoblast; Osteoblast-like cells; Osteoblasts; phosphate; Phosphate minerals; phosphorus; priority journal; rat; Rats; Rats, Wistar; Scanning electron microscopy; Slurries; Stainless steel; Stainless steel 316L; Stainless-steel corrosion products; Steel corrosion

In vitro biomineralization by osteoblast-like cells I. Retardation of tissue mineralization by metal salts - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S. (BiomaterialsBiomaterials, 1998)
The cytocompatibility of stainless steel 316L (SS 316L) corrosion products was investigated with particular focus on the dose- and time-effect of electrochemically dissolved SS and the corresponding separate metal ions on osteogenic bone marrow derived cells. Type AISI 316L stainless steel (Fe 63.9%, Cr 18.0%, Ni 12.5%, Mo 2.8%, Si 1.2%, Mn 1.6% and C 0.025%, weight for weight) was anodically dissolved in Hank's Balanced Salt Solution (HBSS) and diluted to the following concentrations: 500 μgml
Cited By (since 1996): 39Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00149-XPubMed ID: 9678845Language of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; IEC, Universidade do Minho, Largo do Paco, 4719 Braga Codex, PortugalChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium, 7440-70-2; Cations; Chromium, 7440-47-3; Iron, 7439-89-6; Metals; Nickel, 7440-02-0; Phosphates; Stainless Steel, 12597-68-1; Tetrazolium Salts; Thiazoles; thiazolyl blue, 298-93-1References: Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J Bone Jt Surg, 56 B, pp. 626-642;Deutman, R., Rulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J Bone Jt Surg, 59 A, pp. 862-865; Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8; Dorr, L.D., Blocbaum, R., Emmanual, J., Meldrum, R., Histologic, biochemical and ion analysis of tissue and fluids retrieved during total hip arthroplasty (1990) Clin Orthop, 261, pp. 82-95; Henning, F.F., Raithel, H.J., Schaller, K.H., Dohler, J.R., Nickel-, chromium- and cobalt-concentrations in human tissue and body fluids of hip prosthesis patients (1992) J Trace Elem Electrolytes Health Dis, 6, pp. 239-243; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures (1996) J Mater Sci Mater Med, 7, pp. 291-296; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., The use of rat, rabbit or human bone marrow derived cells for cytocompatibility evaluation of metallic elements (1997) J Mater Sci Mater Med, 8, pp. 233-238; Pules, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 109-116; Thompson, G.J., Pules, D.A., Effects of sublethal metal ion concentrations on osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 249-258; McGee-Russell, S.M., Histochemical methods for calcium (1958) J Histochem Cytochem, 6, pp. 22-42; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Wong, M., Rao, L.G., Li, H., Long-term effects of physiologic concentrations of dexamethasone on human bone derived cells (1990) J Bone Miner Res, 5, pp. 803-813; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralisation of osteoblastic cells derived from human bone (1990) Bone Miner, 8, pp. 239-250; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralisation of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Miner, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralisation of osteoid nodules in vitro (1992) Bone Miner, 17, pp. 15-29; Chung, C.H., Golub, E.E., Forbes, E., Mechanisms of action of β-glycerophosphate on bone cell mineralisation (1992) Calcif Tissue Int, 51, pp. 305-311; Schimdt, R., Kulbe, K.D., Long term cultivation of human osteoblasts (1993) Bone Miner, 20, pp. 211-221; Cheng, S.L., Yang, J.W., Riffins, L., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralisation in serially passaged human alveolar bone cells (1997) J Mater Sci Mater Med, 8, pp. 73-76; Martin, A., Clynes, M., Comparison of 5 microplate colorimetric assays for in vitro cytotoxicity testing and cell proliferation assays (1993) Cytotechnology, 11, pp. 49-58; Sgouras, D., Duncan, R., Methods for the evaluation of biocompatibility of soluble synthetic polymers which have potential for biomedical use. 1. Use of the tetrazolium-based colorimetric assay (MTT) as a preliminary screen for evaluation of in vitro cytotoxicity (1990) J Mater Sci Mater Med, 1, pp. 61-68; Ciapetti, G., Cenni, E., Stea, S., Pizzoferrato, A., In vitro evaluation of cell/biomatrial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Yoshimura, T., Kurita, C., Hayata, M., Nagai, H., Diagnosis of drug allergy by the lymphocyte stimulation test with the MTT (3-(4,5-dimethyl thiazol-2-yl)-2,2-diphenyl tetrazolium bromide) assay (1993) Biol Pharm Bull, 16, pp. 686-689; Sasanaluckit, P., Albustany, K.R., Doherty, P.J., Williams, D.F., Biocompatibility of glass ionomer cements (1993) Biomaterials, 14, pp. 906-916; Carvalho, G.S., Castanheira, M., Diogo, I., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1996) J Mater Sci Mater Med, 7, pp. 77-83; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., Histological and biochemical evaluation of osteoblasts cultured on bioactive glass, hydroxylapatite, titanium alloy and stainless steel (1993) J Biomed Mater Res, 27, pp. 465-475; Owen, M., Marrow stromal stem cells (1988) J Cell Sci, 10, pp. 63-76; Beresford, J.N., Osteogenic stem cells and the stromal system of bone and marrow (1989) Clin Orthop Rel Res, 240, pp. 270-280; Owen, T.A., Arohow, M., Shalhonb, V., Progressive development of the rat osteoblast phenotype in vitro: Reciprocal relationships in expression of genes associated with osteoblast proliferation during formation of bone extracellular matrix (1990) J Cell Phys, 143, pp. 420-430; Malaval, L., Modrowski, D., Gupta, K., Aubin, J.E., Cellular expression of bone related proteins during in vitro osteogenesis in rat bone marrow stromal cell cultures (1994) J Cell Phys, 158, pp. 555-572; Stein, G.S., Lion, J.B., Molecular mechanisms mediated proliferation-differentiation interrelationships during progressive development of the osteoblast phenotype: Update 1995 (1995) End Rev, 4, pp. 290-297
Keywords: Absorption spectroscopy; alkaline phosphatase; animal cell; Animalia; Animals; article; ascorbic acid; atomic absorption spectrometry; balanced salt solution; Bioassay; Biocompatibility; biomaterial; Biomaterials; biomineralization; bone marrow cell; bone mineralization; Bovinae; Calcification, Physiologic; Calcium; calcium phosphate; Carbon; Cations; Cattle; Cell Division; cell proliferation; cell survival; cell viability; Cells, Cultured; Chromium; controlled study; Corrosion; dexamethasone; electrochemistry; enzyme activity; Enzyme kinetics; glycerol 2 phosphate; histochemistry; Iron; Kinetics; manganese; metal ion; Metal ions; Metals; molybdenum; Nickel; nonhuman; Oryctolagus cuniculus; osteoblast; Osteoblast cells; Osteoblast-like cells; Osteoblasts; Phosphates; priority journal; rabbit; Rabbits; serum; Silicon; Stainless steel; Steel corrosion; Tetrazolium Salts; Thiazoles; Tissue culture

In vitro biomineralization by osteoblast-like cells II. Characterization of cellular culture supernatants - Morais, S.; Carvalho, G.S.; Faria, J.L.; Gomes, H.T.; Sousa, J.P. (BiomaterialsBiomaterials, 1998)
The quantification of total calcium, phosphorus, iron, chromium and nickel in cell culture medium by electrochemical or spectroscopic means may require digestion of samples. Nevertheless, when pH adjustment is performed for values higher than about 6.5, the formation of two phases occurs: a white precipitate and a clear solution. Analysing both phases using microelectrodes, atomic absorption spectrometry (AAS), diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy. X-ray dispersive (XRD) analysis, scanning electron microscopy (SEM) and energy dispersive spectroscopic (EDS) analysis, it was oberved that iron, chromium and nickel are not co-precipitating with the white solid phase. If quantification of calcium, phosphorus and magnesium is intended, a ten-fold dilution at least, must be performed to avoid most of these elements going into the precipitate. This knowledge is crucial if a mineralization study is going to be made.The quantification of total calcium, phosphorus, iron, chromium and nickel in cell culture medium by electrochemical or spectroscopic means may require digestion of samples. Nevertheless, when pH adjustment is performed for values higher than about 6.5, the formation of two phases occurs: a white precipitate and a clear solution. Analyzing both phases using microelectrodes, atomic absorption spectrometry (AAS), diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy, X-ray dispersive (XRD) analysis, scanning electron microscopy (SEM) and energy dispersive spectroscopic (EDS) analysis, it was observed that iron, chromium and nickel are not co-precipitating with the white solid phase. If quantification of calcium, phosphorus and magnesium is intended, a ten-fold dilution at least, must be performed to avoid most of these elements going into the precipitate. This knowledge is crucial if a mineralization study is going to be made.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00150-6PubMed ID: 9678846Language of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; IEC, Universidade do Minho, Largo do Paco, 4719 Braga Codex, PortugalChemicals/CAS: Calcium, 7440-70-2; Chromium, 7440-47-3; Culture Media; Iron, 7439-89-6; Metals; Nickel, 7440-02-0; Phosphorus, 7723-14-0; Stainless Steel, 12597-68-1References: Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., Toxic effects caused by stainless steel corrosion products on mouse seminiferous cells (1994) Cytobios, 77, pp. 73-80;Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Chromium accumulation and ultrastructural changes in the mouse liver caused by stainless steel corrosion products (1995) J Mater Sci Mater Med, 6, pp. 523-527; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel corrosion products cause alterations on mouse spleen cellular populations (1995) J Mater Sci Mater Med, 6, pp. 56-61; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., Metals electrochemically dissolved in human serum inhibit T-lymphocyte function (1992) Advances in Biomaterials, pp. 7-11. , Doherty PJ, et al., editors. Amsterdam: Elsevier; Carvalho, G.S., Castanheira, M., Diogo, I., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1995) J Mater Sci Mater Med, 7, pp. 77-83; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro bone formation in the presence of stainless steel corrosion products (1994) Poster Section, 11th European Conference on Biomaterials, , Pisa, Italy; Sousa, J.P., Requirements in materials for biosensors J Mater Sci Mater Med, , in press; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast like cells. I. Retardation of tissue mineralisation by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of nickel in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9 (5), pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Optimization study for nickel quantification in cell culture medium using mercury film microelectrodes (1996) Portugaliae Electrochimica Acta, 14, pp. 267-272; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Chromium determination in osteoblast-like cell culture medium by catalytic stripping voltammetry with a mercury microelectrode Electroanalysis, , submitted for publication; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionised calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8 (12), pp. 1174-1178; Morais, S., Carvalho, G.S., Sousa, J.P., Inorganic phosphorus determination in osteoblast-like cell culture for in vitro mineralisation study (1996) Poster Section, 15th Meeting of the Portuguese Chemical Society, , Porto; Pend, J., Jin, W., Anodic stripping voltammetric determination of trace lead in micro-samples with a mercury ultramicroelectrode (1992) Anal Chim Acta, 264, pp. 213-219; Pereira, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., Nickel quantification in mice organs by adsorptive cathodic stripping voltammetry using mercury microelectrodes (1997) Electroanalysis, 9, p. 1501; Wurfels, W., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid. Part 3a (1989) Anal Chim Acta, 226, pp. 31-41; Wurfels, W., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid. Part 2a (1989) Anal Chim Acta, 226, pp. 17-30; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, R., Tolg, G., Wet mineralisation of organic matrices in glassy carbon vessels in a pressure-bomb system for trace element analysis (1979) Talanta, 26, pp. 681-691; Nakamoto, K., (1970) Infrared Spectra of Inorganic and Coordination Compounds, 2nd Edn., , NY: Wiley Interscience; Lin-Vien, D., Colthup, N.B., Fateley, W.G., Grasselli, J.G., (1991) The Handbook of Infrared and Raman Characteristic Frequencies of Organic Molecules, , Boston: Academic Press; Walsh, W.R., Christiansen, D.L., Demineralized bone matrix as a template for mineral-organic composites (1995) Biomaterials, 16 (18), pp. 1363-1371; Koeneman, J., Lemons, J., Ducheyne, P., Lacefield, W., Magee, F., Calahan, K.J., Workshop on characterisation of calcium phosphate materials (1990) J Appl Biomater, 1, pp. 79-90; Mann, S., Webb, J., Williams, R.J.P., (1989) Biomineralization: Chemical and Biochemical Perspectives, , Germany: VCH, Weinheim; Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J Bone Jt Surg, 566, pp. 626-642; De Vernejoul, M.C., Pointillart, A., Golenzer, C.C., Metals in bone (1985) Lancaster, pp. 321-331. , Priest ND, editor. MTT; Kusec, R., Nikolic, V., Hancevic, J., Davila, S., Alkovic, V., Trace elements in periosteal callus and cortical bone after plating for fracture (1990) Periodicum Biologorum, 92 (3), pp. 325-327; Betts, F., Wright, T., Salvati, E.A., Boskey, A., Mansal, M., Cobalt alloy metal debris in periarticular tissues from total hip revision arthoplasties (1992) Clin Orthop, 278, pp. 75-82; Brien, W.W., Salvati, E.A., Betts, F., Metal levels in cemented total hip arthroplasty: A comparison of well-fixed and loose implants (1992) Clin Orthop, 276, pp. 66-74
Keywords: Absorption spectroscopy; Animals; article; atomic absorption spectrometry; Biomaterials; bone mineralization; Calcification, Physiologic; Calcium; Cell culture medium; Cells, Cultured; Chromium; Culture Media; culture medium; Diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy; electrochemistry; Energy dispersive spectroscopic analysis; Fourier transform infrared spectroscopy; Hydrogen-Ion Concentration; infrared spectroscopy; Iron; Magnesium; Metals; microelectrode; Microelectrodes; Nickel; nonhuman; osteoblast; Osteoblast cells; Osteoblasts; pH effects; phosphorus; precipitation; Precipitation (chemical); priority journal; Rabbits; Scanning electron microscopy; Spectrophotometry, Atomic; Spectroscopic techniques; Spectroscopy; Stainless steel; supernatant; Supernatants; Tissue culture; X ray analysis; X ray dispersive analysis

In vitro testing of surface-modified biomaterials - Leitão, E.; Barbosa, M.A.; De Groot, K. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1998)
The influence of surface modification treatments such as ion implantation and sputter coating on an in vitro rat bone-marrow cell culture was studied by scanning electron microscopy and X-ray microanalysis. 316 L stainless steel, Ti-6Al-4V and Ti-5Al-2.5Fe were nitrogen ion-implanted with three fluences: 10 15, 10 16 and 10 17 ion cm
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1008896106994Language of Original Document: EnglishCorrespondence Address: Leitao, E.; INEB-Instituto Engenharia Biomedica, FEUP-Faculdade de Engenharia, Universidade do Porto, Praca Coronel Pacheco 1, 4050 Porto, Portugal; email: eleitao@fsl.ho.man.ac.ukChemicals/CAS: calcium, 7440-70-2; carbon, 7440-44-0; nitrogen, 7727-37-9; stainless steel, 12597-68-1Tradenames: 316 L, aubert and duval; Thermanox; Ti-5Al-2.5Fe, deutsch titan; Ti-6Al-4V, deutsch titanManufacturers: aubert and duval; deutsch titanReferences: Kirkpatrick, C.J., Mittermayer, C., (1990) J. Mater. Sci. Mater. Med., 1, p. 9;Van Loon, J., (1995), PhD thesis, University of Leiden, The NetherlandsLi, P., De Groot, K., (1991) J. Mater. Sci. Mater. Med., 2, p. 125; Davies, J.E., (1990) Handbook of Bioactive Ceramics, 1, pp. 1-65. , edited by T. Yamamuro et al., CRC Press, Boca Raton, FL; Davies, J.E., Ottensmeyer, P., Shen, X., Hashimoto, M., Peel, S.A.F., (1991) Proceedings of the Bone Biomaterial Interface Workshop, pp. 214-228. , edited by J. E. Davies University of Toronto Press, Toronto; Gristina, A.G., Naylor, P., Myrvik, Q., (1988) Med. Progr. Through Technol., 14, p. 205; Kirkpatrick, C.J., Otterbach, T., Ander-Heiden, D., Schifer, J., Richter, H., Höcker, H., Mittermayer, C., Dekker, A., (1992) Cells Mater., 2, p. 169; Howlett, C.R., Evans, M.D.M., Wildish, K.L., Kelly, J.C., Fisher, L.R., Francis, G.W., Best, D.J., (1993) Clin. Mater., 14, p. 57; Howlett, C.R., Zreiqat, H., O'Dell, R., Noorman, J., Evans, P., Dalton, B.A., McFarland, C., Steele, J.G., (1994) J. Mater. Sci. Mater. Med., 5, p. 715; Lee, J.-S., Kaibara, M., Iwaki, M., Sasabe, H., Suzuki, Y., Kusakabe, M., (1993) Biomaterials, 14, p. 958; Röstlund, T., Thomsen, P., Bjursten, L.M., Ericson, L.E., (1990) J. Biomed. Mater. Res., 24, p. 847; Johansson, C.B., Lausmaa, J., Röstlund, T., Thomsen, P., (1993) J. Mater. Sci. Mater. Med., 4, p. 132; Harmand, M.-F., Naji, A., Gonfrier, P., (1994) Clin. Mater., 15, p. 281; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Vrouwenvelder, W.C.A., De Groot, C.G., De Groot, K., (1993) J. Biomed. Mater. Res., 27, p. 465; Puleo, D.A., Holleran, L.A., Doremus, R.H., Bizios, R., (1991) J. Biomed. Mater. Res., 25, p. 711; Davies, J.E., Lowenberger, B., Shiga, A., (1990) J. Biomed. Mater. Res., 24, p. 1289; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., (1993) Cells Mater., 3, p. 407; Gaillard, M.L., (1995), PhD thesis, University of Leiden, The NetherlandsRadder, A.M., Davies, J.E., Leenders, H., Van Blitterswijk, C.A., (1994) J. Biomed. Mater. Res., 28, p. 269; Shen, X., Roberts, E., Peel, S.A.F., Davies, J.F., (1993) Cells Mater., 3, p. 257; Gomi, K., Davies, J.E., (1993) J. Biomed. Mater. Res., 27, p. 429; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., (1992) J. Biomed. Mater. Res., 26, p. 1365; Orr, R.D., De Bruijn, J.D., Davies, J.E., (1992) Cells Mater., 2, p. 241
Keywords: animal cell; animal tissue; article; biomaterial; Biomaterials; bone marrow culture; Calcium; Carbon; Cell culture; cell suspension; collagen fiber; extracellular matrix; implantation; in vitro study; In vitro testing; Ion implantation; male; materials testing; mineralization; morphology; nitrogen; nonhuman; priority journal; rat; Scanning electron microscopy; Sputtering; Stainless steel; Titanium alloys; Titanium aluminum iron alloy; Titanium aluminum vanadium alloy; X ray analysis; X ray microanalysis

New starch-based thermoplastic hydrogels for use as bone cements or drug-delivery carriers - Pereira, C.S.; Cunha, A.M.; Reis, R.L.; Vázquez, B.; San Román, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1998)
The development of new biodegradable hydrogels, based on corn starch/cellulose acetate blends, produced by free-radical polymerization with methyl methacrylate monomer (MMA) and/or an acrylic acid monomer (AA), is reported. The polymerization was initiated by a redox system consisting of a benzoyl peroxide and 4-dimethlyaminobenzyl alcohol at low temperature. These hydrogels may constitute an alternative to the materials currently used as bone cements or drug-delivery carriers. Swelling studies were carried out, as a function of pH and temperature, in buffered solutions. The xerogels were further characterized by Fourier transform-infrared spectroscopy. Tensile and compression tests, and dynamic mechanical thermal analysis were used to assess the mechanical performance of the developed materials. The fracture surfaces were observed by scanning electron microscopy. The developed materials are sensitive to the pH, showing a clear reversible transition in a relatively narrow interval of pH, which is just in the range of physiological conditions. These properties make the materials developed in this study very promising for biomedical applications. Fickian-type diffusion is the mechanism predominant in these systems, except for the composition with a higher concentration of AA, that corresponds to the most desirable kinetical behavior for controlled release (case II-transport mechanism). Furthermore, the results obtained in the mechanical tests are in the range of those reported for typical PMMA bone cements, showing that it is possible to develop partially degradable cements with an adequate mechanical behavior.
Cited By (since 1996): 67Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1008944127971Language of Original Document: EnglishCorrespondence Address: Reis, R.L.; INEB-Inst for Biomedical Engineering, Biomaterials Laboratory, Rua do Campo Alegre 823, 4150 Porto, Portugal; email: rgreis@fe.up.ptChemicals/CAS: acrylic acid, 10344-93-1, 79-10-7; alcohol, 64-17-5; benzoyl peroxide, 94-36-0; cellulose acetate, 9004-35-7; poly(methyl methacrylate), 39320-98-4, 9008-29-1; starch, 9005-25-8, 9005-84-9Tradenames: AA, Merck, Germany; BPO, Merck, Germany; Master-Bi Y101U, novamont, Italy; MMA, Merck, GermanyManufacturers: Merck, Germany; novamont, ItalyReferences: Peppas, N.A., Mikos, A.G., (1988) Hydrogels in Medicine and Pharmacy-Fundamentals, 1, p. 1. , edited by N. A. Peppas CRC Press, Boca Raton, FL;Netti, P.A., Shelton, J.C., Revell, P.A., Pirie, C., Smith, S., Ambrosio, L., Nicolais, L., Bonfield, W., (1993) Biomaterials, 14, p. 1098; Woerly, S., (1993) Biomaterials, 14, p. 1056; Peppas, N.A., (1996) Biomaterials Science an Introduction to Materials in Medicine-Part I, p. 60. , edited by B. D. Ratner, A. S. Hoffman, F. J. Schoen and J. E. Lemons Academic Press, London; Pascual, B., Castellano, I., Vázquez, B., Gurruchaga, M., Goñi, I., (1996) Polymer, 37, p. 1005; Mack, E.J., Okano, T., Kim, S.W., (1988) Hydrogels in Medicine and Pharmacy-Polymers, 2, p. 65. , edited by N. A. Peppas CRC Press, Boca Raton, FL; Karadag, E., Saraydin, D., Çetinkaya, S., Guven, O., (1996) Biomaterials, 17, p. 67; Kim, S.W., Bae, Y.H., Okano, T., (1992) Pharmaceut. Res., 9, p. 283; Blanco, M.D., García, O., Trigo, R.M., Teijon, J.M., Katime, I., (1996) Biomaterials, 17, p. 1061; Abusafieh, A., Siegler, S., Kalidingi, S.R., (1997) J. Biomed. Res., 38, p. 314; Norman, T.L., Kish, V., Blaha, J.D., Gruen, T.A., Hustosky, K., (1995) J. Biomed. Mater. Res., 29, p. 495; Yang, J., (1997) Biomaterials, 18, p. 1293; Lewis, G., Nyman, J.S., Trieu, H.H., (1997) J. Biomed. Mater. Res., 38, p. 221; Lewis, G., (1997) J. Biomed. Mater. Res., 38, p. 155; Domb, A.J., Manor, N., Elmalak, O., (1996) Biomaterials, 17, p. 411; Kost, J., Langer, R., (1988) Hydrogels in Medicine and Pharmacy-Properties and Applications, 3, p. 95. , edited by N. A. Peppas CRC Press, Boca Raton, FL; Lohmann, D., (1995) Macromol. Symp., 100, p. 25; Ogawa, Y., (1997) J. Biomater. Sci. Polymer Edn, 8, p. 391; Di Silvio, L., Gurav, N., Kayser, M.V., Braden, M., Downes, S., (1994) Biomaterials, 15, p. 931; Andreopoulos, A.G., (1994) Clin. Mater., 15, p. 691; Langer, R., (1995) MRS Bull., p. 18; Heller, J., (1996) Applications of Materials in Medicine and Dentistry-Part II, p. 346. , edited by B. D. Ratner, A. S. Hoffman, F. J. Schoen and J. E. Lemons Academic Press, London; Bastioli, C., (1994) Recycle'94 - Davos Global Forum and Exposition, , Switzerland, March; Bastioli, C., (1995) Degradadble Polymers-Principles and Applications, p. 112. , Chapman and Hall, London; Reis, R.L., Cunha, A.M., (1995) J. Mater. Sci. Mater. Med., 6, p. 786; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) Polym. Adv. Technol., 7, p. 784; Reis, R.L., Mendes, S.C., Cunha, A.M., Bevis, M.J., (1997) Polym. Int., 43, p. 347; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1997) Adv. Poly. Technol., 16, p. 263; Reis, R.L., Cunha, A.M., Bevis, M.J., (1997) Med. Plast. Biomateri., p. 46; Pereira, C.S., Gomes, M.E., Reis, R.L., Cunha, A.M., (1998) Foams, Emulsion and Cellular Materials, , edited by J. F. Sadoc and N. River NATO/ASI series, Kluwer Press, Dordrecht, in press; Reis, R.L., Cunha, A.M., (1998) Antec'98-Plastics on My Mind, , Society of Plastics Engieers, Atlanta, April/May in press; Reis, R.L., Cunha, A.M., (1998) Antec'98-Plastics on My Mind; Elvira, C., Levenfeld, B., Vázquez, B., San Román, J., (1996) J. Polym. Sci. A Polym. Chem., 34, p. 2783; Liso, P.A., Vázquez, B., Rebuelta, M., Hernáhz, M.L., Rotger, R., San, J., (1997) Biomaterials, 18, p. 15; Vázquez, B., Elvira, C., Levenfeld, B., Pascual, B., Goñi, I., Gurruchaga, M., Ginerba, M.P., San Róman, J., (1997) J. Biomed. Mater. Res., 34, p. 129; Vázquez, B., Elvira, C., San Román, J., Levenfeld, B., (1997) Polymer, 38, p. 4365; Castellano, I., Pascual, B., Vázquez, B., Goñi, I., Gurrruchaga, M., (1994) J. Appl. Polym. Sci., 54, p. 577; Jane, J., (1995) J.M.S. Pure Appl. Chem., A32, p. 751; Peppas, N.A., Korsmeyer, R.W., (1988) Medicine and Pharmacy-Properties and Applications, 3, p. 109. , edited by N. A. Peppas CRC Press, Boca Raton, FL; Saha, S., Pal, S., (1984) J. Biomed. Mater. Res., 18, p. 435; Lautenschlager, E.P., Moore, B.K., Schoenfeld, C.M., (1974) J. Biomed. Mater. Res. Symp., p. 185; Migiaresi, C., Fambri, L., Kolanik, J., (1994) Biomaterials, 15, p. 875; Topoleski, L.D.T., Ducheyne, P., Cuckler, J.M., (1993) Biomaterials, 14, p. 1165; Clarke, R.L., (1989) Biomaterials, 10, p. 494
Keywords: acrylic acid; alcohol; article; benzoyl peroxide; Biodegradation; bone cement; buffer; cellulose acetate; compression; Diffusion; drug delivery system; dynamics; fracture; free radical; hydrogel; infrared spectroscopy; Kinetics; low temperature; mechanical stress; oxidation reduction reaction; pH; poly(methyl methacrylate); Polymerization; priority journal; Scanning electron microscopy; Starch; tensile strength; Thermal analysis

Objective computerized fetal heart rate analysis - Bernardes, J.; Ayres-de-Campos, D.; Costa-Pereira, A.; Pereira-Leite, L.; Garrido, A. (International Journal of Gynecology and ObstetricsInt. J. Gynecol. Obstet., 1998)
Objective: To assess the validity of a computerized methodology for cardiotocogram analysis based on a recently described reproducible visual estimation of the baseline. Methods: Forty-two antepartum and 43 intrapartum cardiotocograms (CTGs) acquired by a personal computer were selected. Antepartum tracings were performed in the 48 h that preceded an elective cesarean section, and intrapartum tracings were performed until delivery. FHR baselines were estimated by an expert, according to an objective and reproducible methodology. Using these baselines, automated detection of accelerations and decelerations and estimation of variability was performed by the personal computer. A quantitative adaptation of the FIGO guidelines for fetal monitoring was used to classify tracings. Perinatal outcome was classified according to the Apgar score and umbilical arterial pH. Validity was then assessed by the proportions of agreement (PA), kappa statistic (κ), sensitivity and specificity, with 95% confidence intervals (95% CI). Cases showing a disagreement between CTG and perinatal classification were reviewed and an adjustment in baseline definition was tested. Results: The initial overall PA and κ between CTG and perinatal classification were, respectively, 0.79 (95% CI: 0.69-0.87) and 0.62 (95% CI: 0.41-0.83). The overall PA and κ, after baseline adjustment were, respectively, 0.89 (95% CI: 0.81-0.95) and 0.78 (95% CI: 0.58-0.98). Sensitivities and specificities ranged between 79% (95% CI: 60-92%) and 100% (95% CI: 95-100%). Conclusions: Good clinical prediction may be possible with an objective methodology for cardiotocogram analysis based on a recently described reproducible baseline estimation.
Cited By (since 1996): 23Export Date: 21 November 2012Source: ScopusCODEN: IJGOAdoi: 10.1016/S0020-7292(98)00079-4PubMed ID: 9749885Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Departmento Ginecologia Obstetricia, Faculdade Medicina-Hospital S. Joao, Porto, Portugal; email: sisporto@mail.telepac.ptReferences: Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57 (1), pp. 33-37;Bernardes, J., Costa-Pereira, A., Van Geijn, H.P., Pereira-Leite, L., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Grant, A., Principles for clinical evaluation of methods of perinatal monitoring (1984) J Perinat Med, 12, pp. 227-231; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., Van Geijn, H.P., The Porto System (1994) A Critical Appraisal of Fetal Surveillance, pp. 315-324. , In: van Geijn HP, Copray FJA, editors. Amsterdam: Elsevier Science; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring. FIGO news (1987) Int J Gynaecol Obstet, 25, pp. 159-167; Mohide, P., Grant, A., Evaluating diagnosis and screening during pregnancy and childbirth (1989) Effective Care in Pregnancy and Childbirth, pp. 66-80. , In: Chalmers I, Enkin M, Keirse M JNC, editors. Oxford University Press; Garcia-Romero, H., Garcia-Barrios, C., Ramos-Gutierrez, F.R., Effects of uncertain results on sensitivity and specificity of diagnostic tests (1996) Lancet, 348, pp. 1745-1746; Grant, J.M., The fetal heart rate is normal, isn't it?. Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Guzman, E., Vintzileos, A., Martins, M., Benito, C., Houlihan, C., The efficacy of individual computer heart rate indices in detecting acidemia at birth in growth-restricted fetuses (1996) Obstet Gynecol, 87, pp. 969-974; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. II. The value of compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464; Chung, T.K.H., Mohajer, M.P., Yang, Z.J., Chang, A.M.Z., Sahota, D.S., The prediction of fetal acidosis at birth by computerized analysis of intrapartum cardiotocography (1995) Br J Obstet Gynaecol, 102, pp. 454-460; Stigsby, B., Nielson, P.V., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. I. Methods of data reduction and diagnostic procedure (1988) Acta Obstet Gynecol Scand, 67, pp. 455-460
Keywords: Apgar score; arterial pH; article; Cardiotocography; cesarean section; computer analysis; Computerized analysis; Female; Fetal heart rate; fetus; fetus heart rate; fetus monitoring; Heart Rate, Fetal; human; Humans; Image Processing, Computer-Assisted; practice guideline; Predictive Value of Tests; Pregnancy; priority journal; umbilical artery; validity

Semiautomated ultrasonographic measurement of fetal nuchal translucency using a computer software tool - Bernardino, F.; Cardoso, R.; Montenegro, N.; Bernardes, J.; Marques de Sá, J. (Ultrasound in Medicine and BiologyUltrasound Med. Biol., 1998)
Nuchal translucency (NT) thickness measurement has been recently proposed as a part of routine ultrasound scanning during the late first trimester of pregnancy, for the early screening of chromosomal abnormalities. Manual determination of NT is currently performed using electronic callipers placed by the operator in the middle of two echogenic fines displayed on the screen. Therefore, intraobserver and interobserver repeatability can be questioned. This paper presents a software tool that has been developed for achieving this goal in a semiautomatic way, improving the reproducibility of the method.Nuchal translucency (NT) thickness measurement has been recently proposed as a part of routine ultrasound scanning during the late first trimester of pregnancy, for the early screening of chromosomal abnormalities. Manual determination of NT is currently performed using electronic callipers placed by the operator in the middle of two echogenic lines displayed on the screen. Therefore, intraobserver and interobserver repeatability can be questioned. This paper presents a software tool that has been developed for achieving this goal in a semiautomatic way, improving the reproducibility of the method.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: USMBAdoi: 10.1016/S0301-5629(97)00235-4PubMed ID: 9483771Language of Original Document: EnglishCorrespondence Address: Marques De Sa, J.; Instituto de Engenharia Biomedica, Pt. Coronel Pacheco 1, P-4050 Porto, Portugal; email: jmsa@garfield.fe.up.ptTradenames: Microsoft Visual C++, microsoft, United StatesManufacturers: microsoft, United StatesReferences: Jain, A.K., (1982) Fundamentals of Digital Image Processing, , New York: Prentice Hall International Editions;Neilson, J., Grant, A., Ultrasound in pregnancy (1989) A Guide to Effective Care in Pregnancy and Childbirth., pp. 48-56. , Enkin M, Keirse MJN, Chalmers I. eds. New York, London: Oxford University Press; Nicolaides, K.H., Azar, G., Byrne, D., Mansur, C., Marks, K., Fetal nuchal translucency: Ultrasound screening for chromosomal detects in first trimester of pregnancy (1992) BMJ, 304, pp. 867-869; Pandya, P.P., Brizot, M.L., Kuhn, P., Snijders, R.J.M., Nicolaides, K.H., First trimester fetal nuchal translucency thickness and risk for trisomies (1994) Obstet Gynecol, 84, pp. 420-423; Pandya, P.P., Kondylios, A., Hilbert, L., Snijders, R.J.M., Nicolaides, K.H., Chromosomal defects and outcome in 1015 fetuses with increased nuchal translucency (1995) Ultrasound Obstet Gynecol, 5, pp. 15-19; Pandya, P.P., Altman, D.G., Brizot, M.L., Pettersen, H., Nicolaides, K.H., Repeatability of measurement of fetal nuchal translucency thickness (1995) Ultrasound Obstet Gynecol, 5, pp. 334-337; Roberts, L.J., Bewley, S., Mackinson, A.M., Rodeck, C.H., First trimester fetal nuchal translucency: Problems of screening the general population (1995) Br J Obstet Gynaecol, 102, pp. 381-385; Zador, I.E., Salari, V., Sokol, R.J., Computer applications in fetal medicine (1994) The Fetus As A Patient, pp. 117-124. , Kurjak A, Chervenak FA, eds. London/ New York: Parthenon Publ
Keywords: article; cervical spine; chromosome aberration; Chromosome Aberrations; Chromosome Disorders; Computer aided diagnosis; computer program; Computer software; computer system; Female; Fetal monitoring; Fetal nuchal translucency; fetus echography; first trimester pregnancy; Humans; Image analysis; Image Processing, Computer-Assisted; Image thresholding; Medical imaging; Neck; observer variation; Pregnancy; Pregnancy Trimester, First; priority journal; reproducibility; Reproducibility of Results; Software; Software package NUCA; Thickness measurement; Ultrasonic imaging; Ultrasonography, Prenatal; ultrasound

Apatite deposition on titanium surfaces - The role of albumin adsorption - Serro, A.P.; Fernandes, A.C.; Saramago, B.; Lima, J.; Barbosa, M.A. (BiomaterialsBIOMATERIALS, 1997)
Titanium implant surfaces are known to spontaneously nucleate apatite layers when in contact with simulated body fluids. However, adsorption of proteins may influence the process of apatite layer formation. In this study the role of bovine serum albumin (BSA) adsorption in the process of apatite deposition on titanium substrates is investigated. Deposition of calcium phosphate was induced by immersing titanium substrates in a Hank's balanced salt solution (HBSS) for times ranging from 1 to 23 days. The resulting substrates were studied by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), wettability measurements and electrochemical impedance determinations. All these methods indicate the presence of a calcium phosphate layer. The same procedure was repeated substituting HBSS with a solution of BSA in HBSS. Although SEM, EDS and electrochemical impedance spectra do not reveal the presence of an apatite layer, XPS analysis strongly indicates that the inhibition of apatite formation by BSA is only partial. The competition between BSA adsorption and apatite deposition seems to lead to a mixed film where the protein co-exists with calcium phosphate. Wettability studies suggest that this surface film is heterogeneous and porous, similar to the thicker films formed in albumin-free HBSS.Titanium implant surfaces are known to spontaneously nucleate apatite layers when in contact with simulated body fluids. However, adsorption of proteins may influence the process of apatite layer formation. In this study the role of bovine serum albumin (BSA) adsorption in the process of apatite deposition on titanium substrates is investigated. Deposition of calcium phosphate was induced by immersing titanium substrates in a Hank's balanced salt solution (HBSS) for times ranging from 1 to 23 days. The resulting substrates were studied by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), wettability measurements and electrochemical impedance determinations. All these methods indicate the presence of a calcium phosphate layer. The same procedure was repeated substituting HBSS with a solution of BSA in HBSS. Although SEM, EDS and electrochemical impedance spectra do not reveal the presence of an apatite layer, XPS analysis strongly indicates that the inhibition of apatite formation by BSA is only partial. The competition between BSA adsorption and apatite deposition seems to lead to a mixed film where the protein co-exists with calcium phosphate. Wettability studies suggest that this surface film is heterogeneous and porous, similar to the thicker films formed in albumin-free HBSS.
Cited By (since 1996): 72Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00031-8PubMed ID: 9212191Language of Original Document: EnglishCorrespondence Address: Serro, A.P.; Centro de Quimica Estrutural, Complexo I, Instituto Superior Tecnico, Av. Rovisco Pais, 1096 Lisboa Codex, PortugalChemicals/CAS: alpha-tricalcium phosphate; Apatites; calcium phosphate, 10103-46-5; Calcium Phosphates; dicalcium phosphate anhydrous, 7757-93-9; Hanks Balanced Salt Solution; Isotonic Solutions; monocalcium phosphate; Serum Albumin, Bovine; tetracalcium phosphate; Titanium, 7440-32-6References: Sundgren, J.-E., Bodo, P., Lundstrom, I., Auger electron spectroscopic studies of the interface between human tissue and implants of titanium and stainless steel (1986) J. Colloid Interface Sci., 10, pp. 9-20;Hanawa, T., Ota, M., Characterization of surface film formed on titanium in electrolyte using XPS (1992) Appl. Surface Sci., 55, pp. 269-276; Sousa, S.R., Barbosa, M.A., Corrosion resistance of titanium cp in saline physiological solutions with calcium phosphate and proteins (1993) Clin. Mater., 14, pp. 287-294; Li, P., Ohtsuki, C., Kokubo, T., Nakanishi, K., Soga, N., De Groot, K., The role of hydrated silica, titania and alumina in inducing apatite on implants (1994) J. Biomed. Mater. Res., 28, pp. 7-15; Tanahashi, M., Yao, T., Kokubo, T., Apatite coating on organic polymers by a biomimetic process (1994) J. Am. Ceram. Soc., 77, pp. 2805-2808; Martin, R.I., Brown, P.W., Formation of hydroxy-apatite in serum (1994) J. Mater. Sci.: Mater. Med., 5, pp. 96-102; Malmsten, M., Ellipsometric studies of protein layers adsorbed at hydrophobia surfaces (1994) J. Colloid Interface Sci., 166, pp. 333-342; Oscarsson, S., Protein adsorption onto protein-covered silica-gels (1994) J. Colloid Interface Sci., 165, pp. 402-410; Baier, R.E., Meyer, J.R., Natella, R.R., Carter, J.M., Surface properties determine bioadhesive outcomes: Methods and results (1984) J. Biomed. Mater. Res., 18, pp. 337-355; Andrade, J.D., (1985) Surface and Interfacial Aspects of Biomedical Polymers, 2, pp. 1-80. , ed. J. D. Andrade. Plenum Press, New York; Van Der Vegt, W., Van Der Mei, H.C., Busscher, H.J., Interfacial free energies in protein solution droplets on FEP-Teflon by axisymmetric drop shape analysis by profile - IgG versus BSA (1993) J. Colloid Interface Sci., 156, pp. 129-136; Kipaldi, V.D., Lemons, J.E., Surface energy characterization of unalloyed titanium (1994) J. Biomed. Mater. Res., 28, pp. 1419-1425; Van Der Vegt, W., Van Der Mei, H.C., Busscher, H.J., A comparison of different approaches to calculate surface free energy of protein-coated substrata from measured contact angles of liquids (1994) Langmuir, 10, pp. 1314-1318; Cheng, P., Li, D., Boruvka, L., Rotenberg, Y., Neumann, A.W., Automation of axisymmetric drop shape analysis for measurements of interfacial tensions and contact angles (1990) Colloids Surfaces, 43, pp. 151-167; Cheng, P., Neumann, A.W., Computational evaluation of axisymmetric drop shape analysis - Profile (ADSA-P) (1992) Colloids Surfaces, 62, pp. 297-306; Barbosa, M.A., Electrochemical impedance studies on calcium phosphate-metal interfaces (1991) Bioceramics, 4, pp. 325-333. , ed. W. Bonfield, G. W. Hastings and K. E. Tanner. Butterworth-Heinemann, London; Ström, G., Carlsson, G., Wettability of kraft pulps -Effect of surface composition and oxygen plasma treatment (1993) Contact Angle, Wettability and Adhesion, pp. 475-491. , ed. K. L. Mittal. VSP, Utrecht; Good, G.R., Contact angle, wetting, and adhesion: A critical review (1992) J. Adhesion Sci. Technol., 6, pp. 1269-1302; Gomes, C.M., Fernandes, A.C., Almeida, B.S., The surface tension of cork from contact angle measurements (1993) J. Colloid Interface Sci., 156, pp. 195-201; Van Oss, C.J., Good, R.J., Chaudhury, M.K., The role of van der Waals and hydrogen bonds in hydrophobic interactions between biopolymers and low energy surfaces (1986) J. Colloid Interface Sci., 111, pp. 378-390; Absolom, D.R., Van Oss, C.J.A., Neumann, A.W., Determination of surface tensions of proteins. II. Surface tension of serum albumin, altered at the protein-air interface (1981) Biochim. Biophys. Acta, 670, pp. 74-78; Paynter, R.W., Ratner, B., The study of interfacial proteins and biomolecules by X-ray photoelectron spectroscopy (1985) Surface and Interfacial Aspects of Biomedical Polymers, 2, pp. 189-216. , ed. J. D. Andrade. Plenum Press, New York; Raider, S.I., Flitsch, R., Palmer, M.J., Oxide growth on etched silicon in air at room temperature (1975) J. Electrochem. Soc.: Solid State Sci. Technol., 122, pp. 413-418
Keywords: Adsorption; Albumin; Albumin adsorption; Animals; Apatite; Apatite deposition; Apatites; article; Binding Sites; Bovinae; bovine serum albumin; Calcium Compounds; calcium phosphate; Calcium phosphates; Cattle; Deposition; Electric Impedance; Electrochemical impedance; Energy dispersive spectroscopy; impedance; implant; Isotonic Solutions; Microscopy, Electron, Scanning; priority journal; Prostheses and Implants; Proteins; Scanning electron microscopy; Serum Albumin, Bovine; Spectrometry, X-Ray Emission; Substrates; Surface Properties; surface property; Surfaces; Tissue Preservation; Titanium; wettability; X ray photoelectron spectroscopy

Electrochemical and surface modifications on N +-ion-implanted 316L stainless steel - Leitão, E.; Silva, R.A.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1997)
The effect of nitrogen-ion implantation on the electrochemical behaviour of 316L stainless steel in a simulated physiological solution (HBSS-Hank's Balanced Salt Solution) was studied by open-circuit potential versus time and cyclic polarization techniques, with the aim of characterizing the surfaces and choosing the best nitrogen-ion fluence. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. The 10 16 ions/cm 2 N + fluence improves the corrosion resistance of the 316L stainless steel. The effect of nitrogen-ion implantation on the electrochemical behaviour of 316L stainless steel in a simulated physiological solution (HBSS-Hank's Balanced Salt Solution) was studied by open-circuit potential versus time and cyclic polarization techniques, with the aim of characterizing the surfaces and choosing the best nitrogen-ion fluence. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. The 10 16 ions/cm 2 N + fluence improves the corrosion resistance of the 316L stainless steel.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018532900458Language of Original Document: EnglishCorrespondence Address: Leitao, E.; Instituto de Engenharia Biomedica, Praca do Coronel Pacheco 1, 4050 Porto, PortugalReferences: Seah, K.H.W., Chen, X., (1993) Corros. Sci., 34, pp. 1841-1851;Fraker, A.C., Ruff, A.W., Sung, P., Van Orden, A.C., Speck, K.M., (1983) Titanium Alloys in Surgical Implants, pp. 206-219. , ASTM STP 796, edited by H. A. Luckey and F. Kublei Jr; Nakayama, Y., Yamamuro, T., Kumar, P., Shimisu, K., Kotoura, Y., Oka, M., Kwafuku, J., Takashima, T., (1990) J. Appl. Biomater., 1, pp. 307-313; Puleo, D.A., Huh, W.W., (1995) J. Appl. Biomater., 6, pp. 109-116; Sundgreen, J.-E., Bodö, P., Lundström, I., (1986) J. Colloid Interface Sci., 110, pp. 9-20; Merrit, K., Brown, S.A., (1995) J. Biomedical Mater. Res., 29, pp. 627-633; Merrit, K., Brown, S.A., (1994) Tech Orthop., 8, pp. 228-236; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, pp. 523-527; Johansson, C.B., Lausmaa, J., Röstlund, T., Thomsen, P., (1993) J. Mater. Sci. Mater. Med., 4, pp. 132-141; Bernard, F., Dupuy-Philon, J., Bert, J., Remy, D., Moyen, B., Besse, J.L., Advances in materials science and implant orthopaedic surgery (1995) NATO-ASI Series E: Applied Science, 24, pp. 195-206. , edited by R. Kossowsky and N. Kossowsky; Rauschenbach, B., (1991) Nucl. Instrum. Methods Phys. Res., B53, pp. 35-45; Rauschenbach, B., Kolitsch, A., Hohmuth, K., (1983) Phys. Status Solidi (A), 80, pp. 471-482; Howlett, C.R., Evans, M.D.M., Wildish, K.L., Kelly, J.C., Fisher, L.R., Francis, G.W., Best, D.J., (1993) Clin. Mater., 14, pp. 57-64; Howlett, C.R., Zreiqat, H., O'Dell, R., Noorman, J., Evans, P., Dalton, B.A., Mcfarland, C., Steele, J.G., (1994) J. Mater. Sci. Mater. Med., 5, pp. 715-722; Röstlund, T., Thomson, P., Bjursten, L.M., Ericson, L.E., (1990) J. Biomed. Mater. Res., 24, pp. 847-860; Leitão, E., Sá, C., Silva, R.A., Barbosa, M.A., Ali, H., (1995) Corros. Sci., 37, pp. 1861-1866; Barbosa, M.A., (1989) Portugaliae Electrochimica Acta, 7, pp. 567-590; Rauschenbach, B., Kolitsch, A., (1983) Phys. Status Solidi (A), 80, pp. 211-222; Rauschenbach, B., (1991) Nucl. Tracks Radiat. Meus., 19, pp. 943-946; Carbucicchio, M., Bardani, L., Tosto, S., (1981) J. Appl. Phys., 52, p. 4589; Hu, W.W., Herman, H., Clayton, C.R., Kozubowski, J., Kant, R.A., Hirvonen, J.K., Maccrone, R.K., Surface related mechanical properties of nitrogen implanted 1018 steel (1979) Proc. Ion Implantation Metallurgy, p. 92. , edited by C. M. Preece and J. K. Hirvonen AIME. Warrendale, Cambridge, MA; Dos Santos, C.A., Behar, M., De Souza, J.P., Baumvol, I.J.R., (1983) Nucl. Inustrum. Methods, 209-210, pp. 907-912; Sousa, S., Barbosa, M.A., (1991) J. Mater. Sci. Mater. Med., 2, pp. 19-26; Klein, C.A.P.T., Patka, P., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., (1994) Biomaterials, 15, pp. 146-150
Keywords: article; balanced salt solution; Composition effects; Corrosion; Corrosion resistance; Cyclic polarization technique; Electrochemical corrosion; electrochemistry; implantation; Ion implantation; limb prosthesis; nitrogen; Polarization; priority journal; prosthesis failure; Simulated physiological solutions; Solutions; Stainless steel; Stainless steel 316L; Surface Properties; Surface treatment; time

Guided bone regeneration using osteopatite® granules and polytetrafluoroethylene membranes - Vasconcelos, M.; Afonso, A.; Branco, R.; Cavalheiro, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1997)
Granules of a modified hydroxyapatite, Osteopatite®, were implanted in the right posterior tibiae of adult rabbits. We studied the extent of bone regeneration in bone holes. In the right tibiae, that were filled with granules of this biomaterial covered with a polytetrafluoroethylene (PTFE) membrane using, as a control, uncovered granules. In the left tibia, an empty hole was covered with PTFE membrane and a second hole was left empty to be used as a control. A histomorphometric study was carried out using light microscopy, four and eight weeks after the surgery. The covered granules presented a higher percentage of bone contact than the uncovered ones, and it was also possible to observe a better bone tissue organization, mainly produced by the immobilization action of the PTFE membrane. Empty bone defects covered with PTFE membranes, two months after implantation, presented large areas of Haversian bone and direct bone contact to the PTFE membrane.Granules of a modified hydroxyapatite, Osteopatite, were implanted in the right posterior tibiae of adult rabbits. We studied the extent of bone regeneration in bone holes. In the right tibiae, that were filled with granules of this biomaterial covered with a polytetrafluoroethylene (PTFE) membrane using, as a control, uncovered granules. In the left tibia, an empty hole was covered with PTFE membrane and a second hole was left empty to be used as a control. A histomorphometric study was carried out using light microscopy, four and eight weeks after the surgery. The covered granules presented a higher percentage of bone contact than the uncovered ones, and it was also possible to observe a better bone tissue organization, mainly produced by the immobilization action of the PTFE membrane. Empty bone defects covered with PTFE membranes, two months after implantation, presented large areas of Haversian bone and direct bone contact to the PTFE membrane.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018533217238Language of Original Document: EnglishCorrespondence Address: Vasconcelos, M.; Faculty of Dental Medicine, University of Porto, Rua Dr. Roberto Frias, 4200 Porto, PortugalTradenames: OsteopatiteReferences: Cavalheiro, J., Branco, R., Vasconcelos, M., (1991) Proceedings of the 4th International Conference on Bioceramics, p. 205. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner, London, UK Butterworth-Heinemann, Oxford;Cavalheiro, J., Vasconcelos, M., Afonso, A., Peres, F., Branco, R., (1994) Stoma, 30, p. 15; Dahlin, C., Lekholm, U., Becker, W., Becker, B., Higuchi, K., Callens, A., Steenberghe, D., (1995) Int. J. Oral Maxillofac. Implants, 3, p. 312; Aughtun, M., Doz, P., Yildirim, M., Spiekermann, H., Biesterfeld, S., (1995) Int. J. Oral Maxillofac. Implants, 4, p. 421; Simion, M., Scarano, A., Gionso, L., Piattelli, A., (1995) Int. J. Oral Maxillofac. Implants, 3, p. 312; Afonso, A., Santos, J.D., Vasconcelos, M., Branco, R., Cavalheiro, J., (1996) J. Mater. Sci: Mater. Med., 7, p. 507; Jovanovic, S.A., Schenk, R.K., Orsini, M., Kenney, E.B., (1995) Int. J. Oral Maxillofac. Implants, 1, p. 27; Sander, L., Karring, T., (1995) J. Clin. Periodontol., 22, p. 295; Grevstad, H.J., Leknes, K.N., (1993) J. Clin. Periodontol., 20, p. 193; Piattelli, A., Scarano, A., Russo, P., Matarasso, S., (1996) Biomaterials, 17, p. 791
Keywords: animal experiment; Animalia; biomaterial; Bone; bone defect; Bone Regeneration; conference paper; controlled study; haversian canal; hydroxyapatite; Implants (surgical); microscopy; nonhuman; Optical microscopy; Oryctolagus cuniculus; Phosphate minerals; politef; Polymeric membranes; Polytetrafluoroethylenes; priority journal; rabbit; tibia

Investigation of the dissolution of the bioceramic hydroxyapatite in the presence of titanium ions using ToF-SIMS and XPS - Leadley, S.R.; Davies, M.C.; Ribeiro, C.C.; Barbosa, M.A.; Paul, A.J.; Watts, J.F. (BiomaterialsBIOMATERIALS, 1997)
Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS) analyses have been used to investigate the dissolution of hydroxyapatite in the presence of titanium chloride suggesting the substitution of titanium ions for calcium in the hydroxyapatite structure. The surface analytical data suggest that titanium was incorporated within the solid phase as titanium phosphate. Comparison of relative ion intensities in the ToF-SIMS spectra reveals changes in the composition of the surface chemistry of hydroxyapatite. These relative ion intensities show that the maximum surface uptake of titanium occurred at a solution concentration of 500 ppm titanium chloride for a time of incubation of 30 min. These data correlate with that obtained using XPS highlighting the semi-quantitative information which ToF-SIMS can provide.Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS) analyses have been used to investigate the dissolution of hydroxyapatite in the presence of titanium chloride suggesting the substitution of titanium ions for calcium in the hydroxyapatite structure. The surface analytical data suggest that titanium was incorporated within the solid phase as titanium phosphate. Comparison of relative ion intensities in the ToF-SIMS spectra reveals changes in the composition of the surface chemistry of hydroxyapatite. These relative ion intensities show that the maximum surface uptake of titanium occurred at a solution concentration of 500 ppm titanium chloride for a time of incubation of 30 min. These data correlate with that obtained using XPS highlighting the semi-quantitative information which ToF-SIMS can provide.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(96)00134-2PubMed ID: 9068892Language of Original Document: EnglishCorrespondence Address: Davies, M.C.; Lab. Biophysics and Surface Analysis, Department Pharmaceutical Sciences, University of Nottingham, Nottingham NG7 2RD, United KingdomChemicals/CAS: Biocompatible Materials; Cations; Ceramics; Durapatite, 1306-06-5; Titanium, 7440-32-6References: Hench, L.L., Wilson, J., Bioceramics (1991) MRS Bull, p. 62. , September;Katz, J.L., Harper, R.A., (1990) Concise Encyclopedia of Medical and Dental Materials, p. 87. , ed. D. F. Williams, Pergamon Press, Oxford; Posner, A.S., Betts, F., Synthetic amorphous calcium phosphate and its relation to bone mineral structure (1975) Acct Chem Res, 8, p. 2373; De Groot, K., (1981) Biocompatibility of Clinical Implant Materials. Vol. I, 1, p. 199. , ed. D. F. Williams, CRC Press, Boca Raton; Van Blitterswijk, C.A., Grote, J.J., Kuijpers, W., Daems, W.T., De Groot, K., Macropore tissue ingrowth: A quantitative and qualitative study on hydroxyapatite ceramic (1986) Biomaterials, 7, p. 137; Jarcho, M., Calcium phosphate ceramics as hard tissue prosthetics (1981) Clin Orthop Rel Res, 157, p. 259; De Groot, K., Geesink, R., Klein, C.P.A.T., Serekian, P., Plasma sprayed coatings of hydroxylapatite (1987) J Biomed Mater Res, 21, p. 1375; Kay, J.F., Golec, T.S., Riley, R.L., Hydroxyapatite coated sub-periosteal dental implants: Design rationale and clinical experience (1987) J Prosthet Dent, 58, p. 339; Geesink, R.G.T., De Groot, K.A., Klein, C.P.A.T., Chemical implant fixation using hydroxylapatite coatings: The development of a human total hip prosthesis for chemical fixation to bone using hydroxylapatite coatings on titanium substrates (1987) Clin Orthop Rel Res, 225, p. 147; Cook, S.D., Thomas, K.A., Kay, J.F., Jarcho, M., Hydroxyapatite coated titanium for orthopaedic implant applications (1988) Clin Orthop Rel Res, 232, p. 225; Van Blitterswijk, C.A., Grote, J.J., Kuijpers, Blok-Van Hoek, C.J.G., Daems, W.T., Bioreactions at the tissue/hydroxyapatite interface (1985) Biomaterials, 6, p. 243; De Lange, G.L.A., Donath, K., Interface between bone tissue and implants of solid hydroxyapatite-coated titanium implants (1989) Biomaterials, 10, p. 121; Craig, G.T., Brook, I.M., Lamb, D.J., Tissue response to subperiosteal implantation of dense hydroxyapatite: Case report (1989) Biomaterials, 10, p. 133; Lemons, J.E., Hydroxyapatite coatings (1988) Clin Orthop Rel Res, 235, p. 220; Van Blitterswijk, C.A., Grote, J.J., (1989) Critical Reviews in Biocompatibility, 5 (ISSUE 1), p. 13. , CRC Press; Driessens, F.C.M., (1983) Bioceramics of Calcium Phosphate, p. 1. , ed. K. de Groot, CRC Press, Boca Raton; Van Raemdonck, W., Ducheyne, P., DeMeester, P., (1984) Metal and Ceramic Biomaterials Vol. II, Strength and Surface, 2, p. 143. , eds P. Ducheyne and G. W. Hastings, CRC Press, Boca Raton; Lee, D.R., (1988) Dissolution Characterisation of Commercially Available Hydroxylapatite Particulate, , MSc thesis, University of Alabama at Birmingham; Whithead, R.Y., Lucas, L.C., Lacefield, W.R., The effect of dissolution on plasma sprayed hydroxylapatite coating on titanium (1993) Clin Materials, 12, p. 31; Driessens, F.C.M., Van Dijk, J.W.E., Borggreven, J.M.P.M., Biological calcium phosphates and their role in the physiology of bone and dental tissues I. Composition and solubility of calcium phosphates (1978) Calcif Tiss Res, 26, p. 127; LeGeros, R.Z., Tung, M.S., Chemical stability of carbonate and fluoride containing apatites (1983) Caries Research, 17, p. 419; Christoffersen, M.R., Thyregood, H.C., Christoffersen, J., Effects of aluminium (III), chromium (II), and iron (III) on the rate of dissolution of calcium hydroxyapatite crystals in the absence and presence of the chelating agent desferrioxamine (1987) J Calcif Tiss Int, 41, p. 27; Blumenthal, N.C., Cosma, V., Inhibition of apatic formation by titanium and vanadium ions (1989) J Biomed Mater Res, 23, p. 13; Ducheyne, P., Van Raemdonck, W., Heughebaert, J.C., Heughebaert, M., Structural analysis of hydroxyapatite coatings on titanium (1986) Biomaterials, 7, p. 97; Ellies, L.G., Nelson, D.G.A., Featherstone, J.D.B., Crystallographic structure and surface morphology of sintered carbonated apatites (1988) J Biomed Mater Res, 22, p. 541; Posner, A.S., The structure of bone apatite surfaces (1985) J Biomed Mater Res, 19, p. 241; Tudor, A.M., Davies, M.C., Melia, C.D., Anderson, D., Hastings, C., Santos, J.D., Barbosa, M., Morrey, S., The analysis of biomedical hydroxyapatite powders and hydroxyapatite coatings on metallic implant by near-IR Fourier transform Raman spectroscopy (1993) Spectrochimica Acta, 5-6, p. 675; Van Raemdonck, W., Ducheyne, P., De Meester, P., Auger electron spectroscopic analysis of hydroxyapatite coatings on titanium (1984) J Am Ceramic Soc, 67, p. 381; Smith, D.C., Murray, D.G., Zuccolin, J.D., Ruse, N.D., Surface characteristics of hydroxyapatite and adhesive bonding. 1. Surface characterisation (1987) J Adhesion, 22, p. 291; Meachim, G., Williams, D.F., (1973) J Biomed Mater Res, 13, p. 555; Pohler, O.E.M., (1983) Biomaterials in Reconstructive Surgery, p. 158. , ed. C. V. Mosby, London; Ribeiro, C.C., (1994), MSc. Thesis, University of PortoEccles, A.J., Vickerman, J.C., (1989) J Vac Sci Technol, A7, p. 234; Briggs, D., Hearn, M.J., Interaction of ion beams with polymer, with particular respect to SIMS (1986) Vacuum, 36, p. 1005; Ribeiro, C.C., Barbosa, M.A., Influence of metal ions on the dissolution behaviour of hydroxyapatite (1991) Bioceramics, 4, p. 145. , eds W. Bonfield, G. H. Hastings and K. E. Tanner, Butterworth-Heinemann; Reed, N.M., Vickerman, J.C., (1993) Surface Characterisation of Advanced Polymers, p. 83. , eds L. Sabbatini and P. G. Zambonin, Weinheim, VCH; Davies, M.C., Lynn, R.A.P., Paul, A.J., Vickerman, J.C., Heller, J., ToF-SIMS and XPS analysis of the surface chemical structure of some linear poly(ortho esters) (1991) Macromolecules, 24, p. 5508; Davies, M.C., Leadley, S.R., Paul, A.J., Vickerman, J.C., Heller, J., Franson, N.M., Probing the surface chemical structure of some novel poly(ortho-esters) prepared with N-methyl and N-phenyl ethanolamine by time-of-flight secondary ion mass spectrometry (ToF-SIMS) (1992) Polymers for Advanced Technologies, 3, pp. 293-301; Briggs, D., Ratner, B.D., A semi-quantitative SIMS analysis of the surfaces of random ethyl methacrylate:-Hydroxyethylmethacrylate copolymer films (1988) Polym Comm, 29, p. 6; Hearn, M.J., Ratner, B.D., Briggs, D., SIMS and XPS studies of poly(urethane) surfaces. I. Preliminary studies (1988) Macromolecules, 21, p. 2950; Briggs, D., Analysis of polymer surfaces by SIMS. VII. Homopolymer and copolymer nylons (1987) Org Mass Spectrom, 22, p. 91
Keywords: article; Bioceramic hydroxyapatite; Biocompatible Materials; biomaterial; Biomaterials; Cations; ceramic prosthesis; ceramics; Composition; Dissolution; Durapatite; hydroxyapatite; information processing; mass spectrometry; Phosphates; priority journal; Radiography; Secondary ion mass spectrometry; Spectrometry, Mass, Secondary Ion; Spectrometry, X-Ray Emission; Spectrophotometry; Substitution reactions; Surface chemistry; surface property; Surface structure; Time of flight secondary ion mass spectrometry; Time-of-flight secondary ion mass spectrometry; Titanium; Titanium chloride; X ray photoelectron spectroscopy; X-ray photoelectron spectroscopy

Mineralization in serially passaged human alveolar bone cells - Fernandes, M.H.; Costa, M.A.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1997)
Well-characterized human bone cell cultures have been regarded as a useful tool to study bone control mechanisms and also to analyse bone/biomaterials interactions. In the present study, human alveolar bone cells were cultured in a-minimal essential medium (α-MEM) containing 10% foetal bovine serum (FBS), 50 μg/ml ascorbic acid, 10 mM sodium β-glycerophosphate and either in the presence or in the absence of 10 nM dexamethasone (Dexa). Cultures were characterized concerning cell viability/proliferation, alkaline phosphatase (ALP), acid phosphatase (ACP) and tartraric acid resistant phosphatase (TRAP) activities, and formation of mineralized areas. Cell proliferation increased gradually for approximately 20 days. In the presence of Dexa, cells formed isolated or interconnected multilayered clusters that increased with culture time. Histochemical assays revealed strong positive reactions for ALP and calcium and phosphates deposits, mainly in relation to cells associated with the clusters. High levels of ALP activity (biochemical determination) were observed. Cells cultured in the absence of Dexa showed significantly lower ALP activity and no calcium and phosphates deposits were present. Serially passaged cells kept the proliferation rate constant but a decrease in ALP activity was observed either in the presence or in the absence of Dexa. The ability to form mineralized areas (cultures fed with Dexa) also decreased on serial subculture.Well-characterized human bone cell cultures have been regarded as a useful tool to study bone control mechanisms and also to analyse bone/biomaterials interactions. In the present study, human alveolar bone cells were cultured in α-minimal essential medium (α-MEM) containing 10% foetal bovine serum (FBS), 50 μg/ml ascorbic acid, 10 mM sodium β-glycerophosphate and either in the presence or in the absence of 10 nM dexamethasone (Dexa). Cultures were characterized concerning cell viability/proliferation, alkaline phosphatase (ALP), acid phosphatase (ACP) and tartaric acid resistant phosphatase (TRAP) activities, and formation of mineralized areas. Cell proliferation increased gradually for approximately 20 days. In the presence of Dexa, cells formed isolated or interconnected multilayered clusters that increased with culture time. Histochemical assays revealed strong positive reactions for ALP and calcium and phosphates deposits, mainly in relation to cells associated with the clusters. High levels of ALP activity (biochemical determination) were observed. Cells cultured in the absence of Dexa showed significantly lower ALP activity and no calcium and phosphates deposits were present. Serially passaged cells kept the proliferation rate constant but a decrease in ALP activity was observed either in the presence or in the absence of Dexa. The ability to form mineralized areas (cultures fed with Dexa) also decreased on serial subculture.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018598430983Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Rua do Doutor Roberto Frias, 4200 Porto, PortugalReferences: Spector, M., Cease, C., Tong, X., (1989) Crit. Rev. Biocompat., 5, p. 269;Van Blitterswijk, C.A., Bakker, D., Hesseling, S.C., Koerten, H.K., (1991) Biomaterials, 12, p. 187; Galante, J.O., Lemons, J., Spector, M., Wilson Jr., P.D., Wright, T.M., (1991) J. Orthop. Res., 9, p. 760; Bagambisa, F.B., Kappert, H.F., Schilli, W., (1994) J. Oral Maxillofac. Surg., 5, p. 52; Bruijn, J.D., Bovell, Y.D., Blitterwijk, C.A., (1994) Biomaterials, 15, p. 543; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Mineral, 14, p. 27; Davies, J.E., Chernecky, R., Loweenberg, B., Shiga, A., (1991) Cells and Materials, 1, p. 3; Bruijn, J.D., Davies, J.E., Flach, J.S., De Groot, K., Blitterwijk, C.A., (1992) Mater. Res. Soc. Symp. Proc., 252, p. 63; Puleo, D.A., Bizios, R., (1992) J. Biomed. Mater. Res., 26, p. 291; Bruijn, J.D., Klein, C.P., De Groot, K., Van Blitterswijk, C.A., (1992) J. Biomed. Mater. Res., 26, p. 1365; Bruijn, J.D., Klein, C.P., De Groot, K., Van Blitterswijk, C.A., (1993) Cells and Materials, 3, p. 407; Shen, X., Roberts, E., Peel, S.A., Davies, J.E., (1993) Cells and Materials, 3, p. 257; Meyer, U., Szulczewski, D.H., Moller, K., Heide, H., Jones, D.B., (1993) Cells and Materials, 3, p. 129; Meyer, U., Szulczewski, D.H., Brackhaus, R.H., Atkinson, M., Jones, D.B., (1993) Biomaterials, 14, p. 917; Bizios, R., (1994) Biotechnol. Bioeng., 43, p. 582; Gotoh, Y., Hiraiwa, K., Nagayama, M., (1990) Bone and Mineral, 8, p. 23; Berstein, A., Bernauer, I., Marx, R., Geurtsen, W., (1992) Biomaterials, 13, p. 98; Schmiddt, R., Kulbe, K.D., (1993) Bone and Mineral, 20, p. 211; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Benayahu, D., Kletter, Y., Zipori, D., Wientroub, S., (1989) J. Cell Physiol., 140, p. 1; Wong, M.-M., Rao, L.G., Ly, H., Hamilton, L., Tong, J., Sturtridge, W., Mcbroom, R., Murray, T.M., (1990) J. Bone Miner. Res., 5, p. 803; Leboy, P.S., Beresford, J.N., Devlin, C., Owen, M.E., (1991) J. Cell Physiol., 146, p. 370; Shalhoub, V., Conlon, D., Tassinari, M., Quinn, C., Partridge, N., Stein, G.S., Lian, J.B., (1992) J. Cell Biochem., 50, p. 425; Cheng, S.-L., Yang, J.W., Rifas, L., Zhang, S.-F., Avioli, L.V., (1994) Endocrinology, 134, p. 277; Bellows, C.G., Aubin, J.E., Heersche, J.M.N., (1991) Bone and Mineral, 14, p. 27; Satomura, K., Nagayama, M., (1991) Acta Anat., 142, p. 97; Van Straalen, J.P., Sanders, E., Prummel, M.F., Sanders, G.T.B., (1991) Clin. Chem. Acta, 201, p. 27; Aufmkolk, B., Hauschka, P.V., Schwartz, E.R., (1987) Calcif. Tissue Int., 37, p. 228
Keywords: Acid phosphatase; Acid resistance; alkaline phosphatase; alveolar bone; article; ascorbic acid; Bioassay; Biocompatibility; Biomaterials; Bone; bone cell; Bovinae; Cell culture; cell proliferation; Characterization; Chemical reactions; controlled study; culture medium; dexamethasone; Foetal bovine serum; glycerophosphate; Histochemical assays; histochemistry; human; Human alveolar bone cells; human cell; mineralization; Minimal essential medium; Phosphates; priority journal; Proteins; tartaric acid; Tartraric acid resistant phosphatase; Tissue culture

Treatments to induce the nucleation and growth of apatite-like layers on polymeric surfaces and foams - Reis, R.L.; Cunha, A.M.; Fernandes, M.H.; Correia, R.N. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1997)
In this work, a bioactive glass is used as a percusor of calcium-phosphate (Ca-P) film deposition onto several polymer-based materials. Both bioinert (high molecular weight polyethylene, HMWPE), and biodegradable (corn starch-based blends, SEVA-C) polymers, unreinforced or reinforced with hydroxylapatite (HA), were coated by the very simple proposed route. Also polyurethane (PU) foams, with an open-cell structure, were mineralized by the proposed method. In fact, it was possible to induce the growth of the Ca-P films not only at the surface, but also in the bulk of the PU foam. These cellular materials are intended for cancellous bone replacement applications. The morphology of the formed films was strongly dependent on the used substrate, its polar character, and on the presence of HA in its composition, as observed by SEM. Nevertheless, a well defined needle like structure was observed in all samples at high magnifications. The Ca:P ratios of the films were between 1.5 and 1.7, i.e. in the range of tricalcium phosphate-hydroxylapatite. Raman spectroscopy and thin-film x-ray diffraction (XRD) evidenced the formation of mostly amorphous calcium-phosphate films. After scraping the coating from the polymer surface and heat-treating the resulting powder at 1000°C for 1 h, HA and β-tricalcium phosphate (TCP) typical peaks were found on XRD patterns.In this work, a bioactive glass is used as a percussor of calcium-phosphate (Ca-P) film deposition onto several polymer-based materials. Both bioinert (high molecular weight polyethylene, HMWPE), and biodegradable (corn starch-based blends, SEVA-C) polymers, unreinforced or reinforced with hydroxylapatite (HA), were coated by the very simple proposed route. Also polyurethane (PU) foams, with an open-cell structure, were mineralized by the proposed method. In fact, it was possible to induce the growth of the Ca-P films not only at the surface, but also in the bulk of the PU foam. These cellular materials are intended for cancellous bone replacement applications. The morphology of the formed films was strongly dependent on the used substrate, its polar character, and on the presence of HA in its composition, as observed by SEM. Nevertheless, a well defined needle like structure was observed in all samples at high magnifications. The Ca:P ratios of the films were between 1.5 and 1.7, i.e. in the range of tricalcium phosphate-hydroxylapatite. Raman spectroscopy and thin-film x-ray diffraction (XRD) evidenced the formation of mostly amorphous calcium-phosphate films. After scraping the coating from the polymer surface and heat-treating the resulting powder at 1000 °C for 1 h, HA and β-tricalcium phosphate (TCP) typical peaks were found on XRD patterns.
Cited By (since 1996): 51Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018514107669Language of Original Document: EnglishCorrespondence Address: Reis, R.L.; INEB-Inst. Biomedical Engineering, Praca do Coronel Pacheco 1, 4050 Porto, PortugalTradenames: Hostalen GM9255F, hoechst, Germany; SEVA-CManufacturers: hoechst, GermanyReferences: Lowenstam, H.A., Weiner, S., (1989) On Biomineralization, , Oxford University Press, Oxford;Mann, S., (1988) Nature, 332, p. 119; Mann, S., (1991) Endeavour, 15, p. 120; Mann, S., (1993) Nature, 365, p. 499; Heur, A.H., Fink, D.J., Laraia, V.J., Calvert, P.D., Kendall, K., Messing, G.L., Blackwell, J., Caplan, A.I., (1992) Science, 255, p. 1098; Hench, L.L., (1991) J. Amer. Ceram. Soc., 74, p. 1487; Legeros, R.Z., Orly, I., Gregoire, M., Daculsi, G., (1991) The Bone-Biomaterial Interface, p. 76. , edited by J. E. Davies University of Toronto Press, Torento; Hench, L.L., (1995) Chem. & Indust., 17, p. 547; Hayakawa, S., Isuru, S., Iida, H., Ohtsuki, C., Osaka, A., (1996) Phys. Chem. Glasses, 37, p. 188; Li, P., Ye, X., Kangasniemi, I., De Blieckhogervorst, J.M.A., Klein, C.P.A.T., De Groot, K., (1995) J. Biomed. Matter. Res., 29, p. 325; Li, P., Othsuki, C., Kokubo, T., Nakanish, K., Soga, N., Nakamura, T., Yamamuro, T., (1992) J. Amer. Ceram. Soc., 75, p. 2094; Cho, S.B., Nakanishi, K., Kokubo, T., Saga, N., Ohtsuki, C., Nakamura, T., (1996) J. Biomed. Mater. Res., 33, p. 145; Radder, A.M., Leenders, H., Van Blitterswijk, C.A., (1994) J. Biomed. Mater. Res., 28, p. 141; Ries, R.L., Cunha, A.M., (1995) J. Mater. Sci. Mater. Med., 6, p. 786; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) J. Polym. Adv. Technol., 7, p. 784; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1997) Adv. Polym. Technol., , in press; Reis, R.L., Mendes, S.C., Cunha, A.M., Bevis, M.J., (1997) Polym. Int., 43, p. 347; Bonfield, W., Grynpas, M.D., Tully, A.E., Bowman, J., Abram, J., (1981) Biomaterials, 2, p. 185; Wang, M., Porter, D., Bonfield, W., (1994) Br. Ceram. Trans., 93, p. 104; Campbell, A.A., Fryxell, G.E., Linehan, J.C., Graff, G.L., (1996) J. Biomed. Mater. Res., 32, p. 111; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., (1994) J. Amer. Ceram. Soc., 77, p. 2805; Hata, K., Kokubo, T., Nakamura, T., Yamamuro, T., (1995) J. Amer. Ceram. Soc., 78, p. 1049; Kokubo, T., Hata, K., Nakamura, T., Yamamuro, T., (1991) Bioceramics, 4, p. 113. , edited by W. Bonfied, G. W. Hastings and K. E. Tanner Butterworth-Heineman, London; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., (1995) J. Mat. Sci. Mater. Med., 6, p. 319; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., (1995) J. Biomed. Mater. Res., 29, p. 349; Li, S.H., Liu, Q., Wijn, J.R., Zhou, B.L., De Groot, K., (1997) Biomaterials, 18, p. 389; Li, S.H., Liu, Q., Wijn, J.R., De Groot, K., Zhou, B.L., (1996) J. Mater. Sci. Lett., 15, p. 1882; Golomb, G., Barashi, A., Wagner, D., Nachmias, O., (1993) Clin. Mater., 13, p. 61; Oliveira, J.M., Fernandes, M.H., Correia, R.N., (1992) Bioceramics, 5, p. 7. , edited by T. Yamumuro, T. Kokubu, T. Nakamura and Kobunshi, Konkokai, Tokyo; Oliveira, J.M., Correia, R.N., Fernandes, M.H., (1995) Biomaterials, 16, p. 849
Keywords: Apatite; Bioactivity; Biomaterials; calcium phosphate; cancellous bone; conference paper; Deposition; Film growth; Foamed plastics; glass; Heat treatment; hydroxyapatite; implantation; mineralization; molecular weight; morphology; Nucleation; Phosphate coatings; Phosphate minerals; polyethylene; polymer; polyurethan foam; Polyurethanes; priority journal; Raman spectrometry; Raman spectroscopy; Scanning electron microscopy; X ray diffraction; Zea mays

XPS characterization of surface films formed on surface-modified implant materials after cell culture - Leitão, E.; Barbosa, M.A.; De Groot, K. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1997)
Nitrogen ion-implanted Ti-6AI-4V, Ti-5AI-2.5Fe and 316 L stainless steel and nitrogen or carbon sputter-coated samples were inoculated with rat bone marrow. The interface between the cell layer and the substrata was studied by X-ray photo-electron spectrometry and observed by scanning electron microscopy (SEM). Ca and P were detected on all materials after in vitro cell culture. Titanium appears to be present mainly in the form of TiO 2. Nitrogen ion-implanted Ti-6Al-4V, Ti-5Al-2.5Fe and 316 L stainless steel and nitrogen or carbon sputter-coated samples were inoculated with rat bone marrow. The interface between the cell layer and the substrata was studied by X-ray photo-electron spectrometry and observed by scanning electron microscopy (SEM). Ca and P were detected on all materials after in vitro cell culture. Titanium appears to be present mainly in the form of TiO 2.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018505621839Language of Original Document: EnglishCorrespondence Address: Leitao, E.; INEB-Instituto Engenharia Biomedica, FEUP-Faculdade de Engenharia, Universidade do Porto, Praca Coronel Pacheco 7, 4050 Porto, PortugalReferences: Schmidt, H., Exner, H.E., Rück, D.M., Angert, N., Fink, U., Advances in material science and implant orthopaedic surgery (1995) NATO-ASI Series E: Applied Science, 24, pp. 207-221. , edited by R. Kossowsky and N. Kossowsky;Leitão, E., Sá, C., Silva, R.A., Barbosa, M.A., Ali, H., (1995) Corros. Sci., 37, p. 1861; Howlett, C.R., Zreiqat, H., O'Dell, R., Noorman, J., Evans, P., Dalton, B.A., Mcfarland, C., Steele, J.G., (1994) J. Mater. Sci. Mater. Med., 5, p. 715; Gomi, K., Davies, J.E., (1993) J. Biomedical Mater. Res., 27, p. 429; Gomi, K., De Bruijn, J.D., Ogura, M., Davies, J.D., (1993) Cells and Mater., 3, p. 151; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford Jr., J., Dean, D.D., Boyan, B.D., (1995) J. Biomedical Mater. Res., 29, p. 389; Groessner-Schreiber, B., Tuan, R.S., (1992) J. Cell Sci., 101, p. 209; Davies, J.E., Ottensmeyer, P., Shen, X., Hashimoto, M., Peel, S.A.F., (1991) Proceedings of the Bone-Biomaterial Interface Workshop, p. 214. , December 1990, edited by J. E. Davies Univ. Toronto Press; De Brujin, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., (1993) Cells and Mater., 3, p. 407; Orr, R.D., De Bruijn, J.D., Davies, J.D., (1992) Cells and Mater., 2, p. 241; Harmand, M.-F., Naji, A., Gonfrier, P., (1994) Clin. Mater., 15, p. 281; Mániatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Hanawa, T., Ota, M., (1991) Biomaterials, 12, p. 767; Hanawa, T., (1991) Proceedings of the Bone-Biomaterial Interface Workshop, p. 4961. , December 1990, edited by J. E. Davies Univ. Toronto Press; Hanawa, T., Ota, M., (1992) Appl. Surface Sci., 55, p. 269; Lausmaa, J., Kasemo, B., Mattsson, H., (1990) Appl. Surface Sci., 44, p. 133; Kasemo, B., Lausmaa, J., (1991) Proceedings of the Bone-Biomaterial Interface Workshops, p. 19. , December 1990, edited by J. E. Davies Univ Toronto Press; Sutherland, D.S., Forshaw, P.D., Allen, G.C., Brown, I.T., Williams, K.R., (1993) Biomaterials, 14, p. 893; Sundgren, J.-E., Bodö, P., Lundström, I., (1986) J. Colloid Interface Sci., 110, p. 9; Leitao, E., Barbosa, M.A., De Groot, K., (1995) J. Mater. Sci. Mater. Med., 6, p. 849; Leitão, E., Barbosa, M.A., De Groot, K., J. Mater. Sci. Mater. Med., , in press; Puleo, D.A., Huh, W.W., (1995) J. Appl. Biomater., 6, p. 109; Thompson, G.J., (1995) J. Appl. Biomater., 6, p. 249; Ikeo, N., Iijima, Y., Niimura, N., Sigematsu, M., Tazava, T., Matsumoto, S., Kojima, K., Nagasawa, Y., (1991) Handbook of X-ray Photo-electron Spectroscopy, , JHOL; Armstrong, N.R., Quinn, R.K., (1977) Surface Sci., 67, p. 451; Ong, J.L., Prince, C.W., Lucas, L.C., (1995) J. Biomed. Mater. Res., 29, p. 165; Ducheyne, P., (1992) J. Colloid Interface Sci., 150, p. 404; Wagner, C.D., Bickham, D.M., (1989) NIST-XPS Database, , National Institute of Standards and Technology
Keywords: Animal cell culture; Animalia; article; Bone; bone marrow; Calcium; Carbon; Cell culture; implant; Implants (surgical); Interfaces (materials); Ion implantation; nitrogen; phosphorus; priority journal; Scanning electron microscopy; Stainless steel; Surface films; surface property; Surface treatment; Titanium alloys; Titanium dioxide; X ray spectrometry

Crystallinity and structural changes in HA plasma-sprayed coatings induced by cyclic loading in physiological media - Reis, R.L.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
In this study hydroxyapatite plasma-sprayed Ti-6A1-4V was characterized by X-ray diffraction (XRD) after being cyclically loaded, while immersed in two different testing environments: Hank's balanced salt solution (HBSS) and an isotonic saline solution (0.15m NaCl). An original method was developed to test these systems under cyclic bending, while immersed in the testing solution. The crystallinity of the coating was calculated, before and after testing. Crystallinity changes were related to coating dissolution rates, measured by atomic absorption spectroscopy (AAS) and by a photocolourimetric method using ascorbic acid. Structural changes induced either by the plasma-spraying procedure or due to corrosion-fatigue tests, namely a preferential dissolution of the coating's amorphous phase, were also found in X-ray diffraction patterns. Long-term immersion tests, without any applied load, were carried out for assessing cyclic loading effects. An immersion for 2 years in static conditions was found to be equivalent to a cyclic test of 27.8 h in the same solution, as measured by the changes on the coating structure and by the amount of coating material lost to the solution.In this study hydroxyapatite plasma-sprayed Ti-6Al-4V was characterized by X-ray diffraction (XRD) after being cyclically loaded, while immersed in two different testing environments: Hank's balanced salt solution (HBSS) and an isotonic saline solution (0.15M NaCl). An original method was developed to test these systems under cyclic bending, while immersed in the testing solution. The crystallinity of the coating was calculated, before and after testing. Crystallinity changes were related to coating dissolution rates, measured by atomic absorption spectroscopy (AAS) and by a photocolourimetric method using ascorbic acid. Structural changes induced either by the plasma-spraying procedure or due to corrosion-fatigue tests, namely a preferential dissolution of the coating's amorphous phase, were also found in X-ray diffraction patterns. Long-term immersion tests, without any applied load, were carried out for assessing cyclic loading effects. An immersion for 2 years in static conditions was found to be equivalent to a cyclic test of 27.8 h in the same solution, as measured by the changes on the coating structure and by the amount of coating material lost to the solution.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00122009Language of Original Document: EnglishCorrespondence Address: Reis, R.L.; Dept. of Metallurgical Engineering, FEUP, Univ. of Porto, Rua dos Bragas, 4099 Porto Codex, PortugalReferences: Ji, H., Marquis, P.M., (1993) Biomaterials, 14, p. 64;Pfaff, H.G., Willmann, G., Henne, R., (1993) Proceedings of the 10th European Conference on Biomaterials, p. 110. , Davos, Switzerland, 1993, edited by B. Rahn (European Society for Biomaterials); Brown, S.D., (1984) Thin Solid Films, 119, p. 127; Geesink, R.G.T., (1988), PhD thesis, Univ. Leiden, The NetherlandsVan Blitterswijk, C.A., Grote, J.J., Kuypers, W., Blok-Van Hoek, C.J.G., Daems, W.Th., (1985) Biomaterials, 6, p. 243; Ribeiro, C.C., Barbosa, M.A., (1991) Bioceramics 4, p. 145. , edited by W. Bonfield, G. W. Hastings and K. Tanner (Butterworth-Heinemann London); Ducheyne, P., Healy, K.E., (1988) J. Biomed. Mater. Res., 22, p. 1137; Whitehead, R.Y., Lucas, L.C., Lacefield, W.R., (1993) Clin. Mater., 12, p. 31; De Bruijn, J.D., Davies, J.E., Flach, J.S., De Groot, K., Van Blitterswijk, C.A., (1992) Proceedings of the 4th World Congress on Biomaterials - Workshop on Biomaterials and Tissue Interactions, p. 23. , edited by U. Gross (Berlin); Morita, M., Sasada, T., Hayashi, H., Tsukamoto, Y., (1988) J. Biomed. Mater. Res., 22, p. 529; Brown, S.A., Farsnworth, L.J., Merritt, K., Crowe, T.D., (1988) J. Biomed. Mater. Res., 22, p. 321; Kummer, F., Jaffe, W., (1992) J. Appl. Biomater., 3, p. 211; Reis, R.L., Monteiro, F.J., Garrido, A., (1992) Bioceramics 5, p. 25. , Kyoto, November, 1992, edited by T. Yamamura, T. Kokubo and T. Nakamura (Kobunshi Kankokai, Tokyo); Reis, R.L., Monteiro, F.J., (1993) Bioceramics 6, p. 413. , Philadelphia, USA, 1993, edited by P. Ducheyne and D. Christiansen (Butterworth-Heinemann. New York); Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) J. Mater. Sci. Mater. Med., 5, p. 457; Reis, R.L., Monteiro, F.J., (1995) Proceedings of the NATO/ASI on Materials Science and Implant Orthopaedic Surgery II, p. 163. , Chania, Greesce, June 1994. edited by R. Kossowsky and N. Kossowsky (May, NATO/ASI series E: Applied Sciences, Kluwer Press, Amsterdam); Ji, H., Ponton, C.B., Marquis, P.M., (1992) J. Mater. Sci. Mater. Med., 3, p. 283; Weng, J., Liu, X., Zhang, X., Ma, Z., Ji, X., Zyman, Z., (1993) Biomaterials, 14, p. 578; De Groot, K., Klein, C.A.P.T., Wolke, J.G.C., Blieck-Hogervorst, J.M.A., (1990) Handbook of Bio-active Ceramics, 2, p. 133. , edited by T. Yamamuro, L. L. Hench and J. Wilson (CRC Press, Boca Raton, FL); Delécrin, J., Szumuckler-Moncler, S., Daculsi, G., Rieu, J., Duquet, B., (1991) Bioceramics 4, p. 311. , London, September, 1991, edited by W. Bonfield, G. W. Hastings and K. E. Tanner (Butterworth-Heinemann, London); De Bruijn, J.D., Flach, J.S., Leenders, H., Van der Brink, J., Van Blitterswijk, C., (1992) Bioceramics 5, p. 259. , Kyoto, November, 1992, edited by T. Yamamura, T. Kokubo and T. Nakamura (Kobunshi Kankokai, Tokyo)
Keywords: Absorption spectroscopy; article; ascorbic acid; atomic absorption spectrometry; Atomic absorption spectroscopy; balanced salt solution; Bending (deformation); Calculations; Characterization; Corrosion fatigue tests; crystal structure; Crystallinity; Cyclic bending; Dissolution; Fatigue testing; Hanks balanced salt solution; hydroxyapatite; Hydroxyapatite plasma sprayed coatings; immersion; implant; Isotonic saline solution; loading test; Long term immersion tests; materials testing; Modification; Photocolourimetric method; photometry; Plasma spraying; priority journal; sodium chloride; Sprayed coatings; Titanium alloys; Titanium aluminum vanadium alloys; X ray crystallography; X ray diffraction

Effect of hydroxyapatite thickness on metal ion release from Ti6Al4V substrates - Sousa, S.R.; Barbosa, M.A. (BiomaterialsBIOMATERIALS, 1996)
The electrochemical dissolution behaviour of Ti6Al4V alloy coated with hydroxyapatite (HA) by plasma spraying was studied in Hank's balanced salt solution (HBSS) and compared with that of polished and grit-blasted passivated surfaces. Two different nominal thicknesses of HA (50 and 200 μm) were used. Taking a polished passivated surface as reference, grit blasting of the substrate increased the electrical charge used in the oxidation of Ti6Al4V alloy at constant potential, as a result of increased surface area. However, only HA coatings with a thickness of 200 μm were capable of reducing the charge to values lower than those measured for polished surfaces. Electrochemical impedance spectroscopy has also shown that only 200 μm thick coatings are effective in reducing the oxidation rate of the substrate. Furthermore, in potentiostatic experiments the 50 μm thick coating detached from the substrate, which did not occur with the 200 μm thick coating. However, after 6 months immersion in HBSS, detachment occurred in some regions of both coatings. No titanium, aluminium or vanadium were detected in solution by electrothermal atomic absorption spectroscopy. These data indicate that HA is an effective barrier to metal ion release, even for the thinner coatings, due to formation of metal phosphates or to incorporation of metal ions in the HA structure.The electrochemical dissolution behaviour of Ti6Al4V alloy coated with hydroxyapatite (HA) by plasma spraying was studied in Hank's balanced salt solution (HBSS) and compared with that of polished and grit-blasted passivated surfaces. Two different nominal thicknesses of HA (50 and 200 μm) were used. Taking a polished passivated surface as reference, grit blasting of the substrate increased the electrical charge used in the oxidation of Ti6Al4V alloy at constant potential, as a result of increased surface area. However, only HA coatings with a thickness of 200 μm were capable of reducing the charge to values lower than those measured for polished surfaces. Electrochemical impedance spectroscopy has also shown that only 200 μm thick coatings are effective in reducing the oxidation rate of the substrate. Furthermore, in potentiostatic experiments the 50 μm thick coating detached from the substrate, which did not occur with the 200 μm thick coating. However, after 6 months immersion in HBSS, detachment occurred in some regions of both coatings. No titanium, aluminium or vanadium were detected in solution by electrothermal atomic absorption spectroscopy. These data indicate that HA is an effective barrier to metal ion release, even for the thinner coatings, due to formation of metal phosphates or to incorporation of metal ions in the HA structure.
Cited By (since 1996): 62Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/0142-9612(96)89655-4PubMed ID: 8938233Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; INEB, Praca do Coronel Pacheco 1, 4050 Porto, PortugalChemicals/CAS: Alloys; Biocompatible Materials; Durapatite, 1306-06-5; titanium alloy (TiAl6V4), 12743-70-3; Titanium, 7440-32-6References: Barbosa, M.A., Electrochemical impedance studies on calcium phosphate-metal interfaces (1991) Bioceramics, 4, pp. 325-333. , Bonfield W, Hastings GW, Tanner KE, eds. London: Butterworth-Heinemann;Sousa, S.R., Barbosa, M.A., Electrochemistry of AISI 316L stainless steel in calcium phosphate and protein solutions (1991) J Mater Sci: Mater Med, 2, pp. 19-26; Sousa, S.R., Barbosa, M.A., Corrosion resistance of titanium cp in saline physiological solutions with calcium phosphate and proteins (1993) Clin Mater, 14, pp. 287-294; Li, P., De Groot, K., Calcium phosphate formation within sol-gel prepared titania in vitro and in vivo (1993) J Biomed Mater Res, 27, pp. 1495-1500; Li, P., Kangasniemi, I., De Groot, K., Bonelike hydroxyapatitc induction by a gel-derived titania and a titanium substrate (1994) J Am Ceram Soc, 77, pp. 1307-1312; Ducheyne, P., Healy, K.E., The effect of plasma-sprayed calcium phosphate ceramic coatings on the metal ion release from porous titanium and cobalt-chromium alloys (1988) J Biomed Mater Res, 22, pp. 1137-1163; Weng, J., Liu, X., Zhang, X., Li, X., Thermal decomposition of hydroxyapatite structure induced by titanium and its dioxide (1994) J Mater Sci Lett, 13, pp. 159-161; Castro Ribeiro, C., Barbosa, M.A., Influence of metal ions on the dissolution behaviour of hydroxyapatite (1991) Bioceramics, 4, pp. 145-153. , Bonfield W, Hastings GW, Tanner KE, eds. Butterworth-Heinemann; ASTM G61-86, standard test method for: Conducting cyclic potentiodynamic polarization measurements for localized corrosion susceptibility of iron, nickel, or cobalt based alloys (1989) Annual Book of ASTM Standards, pp. 345-361. , 03.02. Philadelphia, PA: American Society for Testing and Materials; ASTM G 31-72 e1, standard practice for: Laboratory immersion corrosion testing of metals (1989) Annual Book of ASTM Standards, pp. 176-186. , 03.02. Philadelphia, PA: American Society for Testing and Materials; Barbosa, M.A., Surface layers and the reactivity of metallic implants (1992) Biomaterials - Hard Tissue Repair and Replacement, pp. 257-283. , Muster D et al. ed. Amsterdam: Elsevier Science Publishers BV; Rivero, D.P., Fox, J., Skipor, A.K., Urban, R.M., Galante, J.O., Calcium phosphate-coated porous titanium implants for enhanced skeletal fixation (1988) J Biomed Mater Res, 22, pp. 191-201; Oonishi, H., Yamamoto, M., Ishimaru, H., The effect of hydroxyapatite coating on bone growth into porous titanium alloy implants (1989) J Bone Joint Surg, 71 B, pp. 213-216; Bourne, R.B., Rorabeck, C.H., Burkar, B., Kirk, P.G., Ingrowth surfaces - Plasma spray coating to titanium alloy hip replacements (1994) Clin Orthop Rel Res, 298, pp. 37-46; Oonishi, H., Noda, T., Ito, S., Effect of hydroxyapatite coatings on bone growth into porous titanium alloy implants under loaded conditions (1994) J Appl Biomater, 5, pp. 23-37; Moroni, A., Caja, V.L., Egger, E.L., Trinchese, L., Chao, E.Y.S., Histomorphometry of hydroxyapatite coated and uncoated porous titanium bone implants (1994) Biomaterials, 15, pp. 926-930; Bloebaum, R.D., DuPont, J.A., Osteolysis from a press-fit hydroxyapatite-coated implant (1993) J Arthroplasty, 8, pp. 195-202; Bloebaum, R.D., Beeks, D., Dorr, L.D., Savory, C.G., DuPont, J.A., Hofmann, A.A., Complications with hydroxyapatite particulate separation in total hip arthroplasty (1994) Clin Orthop, 298, pp. 19-26; Klein, C.P.A.T., Patka, P., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., Long-term in vivo study of plasma-sprayed coatings on titanium alloys of tetracalcium phosphate, hydroxyapatite and α-tricalcium phosphate (1994) Biomaterials, 15, pp. 146-160; Reis, R.L., Monteiro, F.J., Hastings, G.W., Stability of hydroxyapatite plasma-sprayed coated Ti-6Al-4V under cyclic bending in simulated physiological solutions (1994) J Mater Sci: Mater Med, 5, pp. 457-462; Wang, B.C., Lee, T.M., Chang, E., Yang, C.Y., The shear strength and the failure mode of plasma-sprayed hydroxyapatite coating to bone: The effect of coating thickness (1993) J Biomed Mater Res, 27, pp. 1315-1327; Tranquilli Leali, P., Merolli, A., Palmacci, O., Gabbi, C., Cacchiolo, A., Gonizzi, G., Evaluation of different preparations of plasma-spray hydroxyapatite coating on titanium alloy and duplex stainless steel in the rabbit (1994) J Mater Sci: Mater Med, 5, pp. 345-349
Keywords: Absorption spectroscopy; Alloys; Aluminum; article; Atomic spectroscopy; balanced salt solution; Bioactive coatings; Biocompatible Materials; Biomaterials; Calcium Compounds; Dissolution; Durapatite; Electric charge; Electrochemical dissolution; Electrochemical impedance spectroscopy; electrochemistry; Electrothermal atomic absorption spectroscopy; Hank balanced salt solution; hydroxyapatite; Ion release; Ions; metal ion; Metal ion release; Metal phosphates; Microscopy, Electron, Scanning; Oxidation; Plasma spraying; potentiometry; priority journal; Spectrophotometry, Atomic; Spectroscopy; Substrates; thickness; Thickness effect; Time Factors; Titanium; Titanium alloys; vanadium

Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures - Tomás, H.; Carvalho, G.S.; Fernandes, M.H.; Freire, A.P.; Abrantes, L.M. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
The cytocompatibility of the degradation products of a Co-Cr orthopaedic alloy was investigated with particular focus on the dose-effect of an electrochemically dissolved alloy extract and of the corresponding separate metal ions on human osteogenic bone marrow derived cells. The extract solution contained 15ppm of Co and 8ppm of Cr as analysed by atomic absorption spectroscopy. Stock salt solutions of CoCl 2·6H 2O, CrCl 3·6H 2O and Na 2CrO 4 at corresponding concentrations were also prepared. Several dilutions of the above metallic solutions were tested for a period of 21 days on cells (third subculture) cultured in α-minimal essential medium containing foetal bovine serum and supplemented with antibiotics, dexamethasone ascorbic acid and β-glycerophosphate. The osteoblast response to the presence of metal ions was evaluated by several biochemical parameters: cell viability (MTT reduction by intracellular enzymes), alkaline phosphatase activity (an osteoblast marker) and protein production (both intracellular and extracellular). Co-Cr corrosion products showed opposite effects to their respective metal salts only on day 1. With time the different metal solutions presented a similar pattern of inhibition. These results suggest that impaired bone formation in vitro can occur in the presence of Co-Cr corrosion products. The cytocompatibility of the degradation products of a Co-Cr orthopaedic alloy was investigated with particular focus on the dose-effect of an electrochemically dissolved alloy extract and of the corresponding separate metal ions on human osteogenic bone marrow derived cells. The extract solution contained 15 ppm of Co and 8 ppm of Cr as analyzed by atomic absorption spectroscopy. Stock salt solutions of COCl 2·6H 2O, CrCl 3·6H 2O and Na 2CrO 4 at corresponding concentrations were also prepared. Several dilutions of the above metallic solutions were tested for a period of 21 days on cells (third subculture) cultured in α-minimal essential medium containing foetal bovine serum and supplemented with antibiotics, dexamethasone ascorbic acid and β-glycerophosphate. The osteoblast response to the presence of metal ions was evaluated by several biochemical parameters: cell viability (MTT reduction by intracellular enzymes), alkaline phosphatase activity (an osteoblast marker) and protein production (both intracellular and extracellular). Co-Cr corrosion products showed opposite effects to their respective metal salts only on day 1. With time the different metal solutions presented a similar pattern of inhibition. These results suggest that impaired bone formation in vitro can occur in the presence of Co-Cr corrosion products.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Tomas, H.; Faculdade de Ciencias, Universidade de Lisboa, Campo Grande, C1, Piso 5, 1700 Lisboa, PortugalReferences: Pohler, O.E.M., (1983) Biomaterials in Reconstructive Surgery, p. 158. , C. V. Mosby, St. Louis;Black, J., Oppenheiner, P., Morris, R.O.M., Peduto, A.M., Clark, C.C., (1987) J. Biomed. Mater. Res., 21, p. 1213; Sunderman Jr., F.W., Hopfer, S.M., Swift, T., Rezuke, W.N., Ziebka, L., Highman, P., Edwards, B., Gossling, H.R., (1989) J. Orthop. Res., 7, p. 307; Traisnel, M., Maguer, D., Hildebrand, H.F., (1990) Clin. Mater., 5, p. 309; Moore Jr., R.M., Hamburger, S., Jeng, L.J., Hamilton, P.M., (1991) J. Appl. Biomater., 2, p. 127; Henning, E.F., Raithel, H.J., Schaller, K.H., Dòhler, J.R., (1992) J. Trace Elem. Electrolytes Health Dis., 6, p. 239; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., (1993) J. Biomed. Mater. Res., 27, p. 1007; Albore-Saavedra, J., Vuitch, F., Delgado, R., Wiley, E., Hagler, H., (1994) Amer. Surg. Pathol., 18, p. 83; Buechel, F.F., Drucker, D., Jasty, M., Jiranek, W., Harris, W., (1994) Clin. Orthop. Related Res., 298, p. 202; De Bruijn, J.D., (1993), p. 9. , PhD thesis, LeidenNasser, S., Campbell, P.A., Kilgus, D., Kossovsky, N., Amstutz, H.C., (1990) Clin. Orthop., 261, p. 171; Revell, P.A., Weightman, B., Freeman, M.A.R., Roberts, B.V., (1978) Arch. Orthop. Trauma Surg., 91, p. 167; Vilamitjana-Amedee, J., Bareille, R., Rouais, F., Caplan, A.I., Harmand, M.F., (1993) In Vitro Cell. Dev. Biol., 29 A, p. 699; Bizios, R., (1994) Biotechnol. Bioeng., 43, p. 582; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Arciola, C.R., Granchi, D., Savarino, L., (1994) Clin. Mater., 15, p. 173; Tomás, H., Freire, A.P., Abrantes, L.M., (1994) J. Mater. Sci. Mater. Med., 5, p. 446; Lowry, O.H., Rosebrough, N.J., Farr, A.L., Randall, R.J., (1951) J. Biol. Chem., 193, p. 256; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Berridge, M.V., Tan, A.S., (1993) Arch. Biochem. Biophys., 303, p. 474; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., (1993) Biomaterials, 14, p. 359; Martin, A., Clynes, M., (1993) Cytotechnology, 11, p. 49; Carvalho, G.S., Castanheira, M., Diogo, I., Abreu, A.M., Sousa, J.P., Loon, J.A., Van Blitterswijk, C.A., J. Mater. Sci. Mater. Med., , in press; Gotoh, Y., Hiraiwa, K., Nagayama, M., (1990) Bone and Mineral, 8, p. 239; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Mineral, 14, p. 27
Keywords: Absorption spectroscopy; article; Atomic spectroscopy; Biocompatibility; Bone; Cell culture; Chromium alloys; Cobalt alloys; Corrosion; Corrosion resistance; Cytocompatibility; Enzyme inhibition; human; human cell; Human osteoblasts; Implants (surgical); Orthopaedic alloys; ossification; osteoblast; priority journal; surface property

Granules of osteoapatite and glass-reinforced hydroxyapatite implanted in rabbit tibiae - Afonso, A.; Santos, J.D.; Vasconcelos, M.; Branco, R.; Cavalheiro, J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Granules of a modified hydroxyapatite, glass-reinforced hydroxyapatite composite and commercial hydroxyapatite were implanted in rabbit tibiae. Histological studies were carried out after 1 and 2 months implantation periods using light and fluorescence microscopy. A much higher percentage of bone contact was developed for both the glass-reinforced hydroxyapatite composite and the modified hydroxyapatite when compared to commercial hydroxyapatite (89-91% versus 66%) after 2 months implantation. The mechanism of bone formation and growth around implants is discussed in terms of the influence of elements incorporated into these novel materials which are commonly found in bone tissues, such as Na, K and Mg, and the presence of a soluble β-tricalcium phosphate phase in the microstructure of the composite.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Afonso, A.; Faculty of Dental Medicine, University of Porto, Rua Dr Roberto Frias, 4200 Porto, PortugalChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; magnesium, 7439-95-4; potassium, 7440-09-7; sodium, 7440-23-5References: Ravaglioli, A., Krajewski, A., (1992) Bioceramics-materials, Properties and Applications, p. 100. , Chapman & Hall, London;Cranin, A.N., Ronen, E., Puntoff, R.S.H., Tobim, G., Dibeling, J.B., (1988) J. Biomed. Mater. Res., 22, p. 1165; De Groot, K., Klein, C.P.A.T., (1990) "Handbook of Bioactive Ceramics", Vol. II-Calcium Phosphate and Hydroxylapatite Ceramics, 2, p. 3. , edited by T. Yamamuro CRC Press, Boston; Hollinger, J.O., Schmitz, J.P., Mizgala, J.W., Hassler, C., (1989) J. Biomed. Mater. Res., 23, p. 17; Cavalheiro, J., Branco, R., Vasconcelos, M., (1991) Proceedings of the 4th International Conference on Bioceramics, p. 205. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner, London, UK Butterworth-Heinemann, Oxford; Santos, J.D., Reis, R.L., Knowles, J.C., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Nery, E.B., Legeros, R.Z., Lynch, K.L., Kalbleisch, J., (1988) J. Dent. Res., 67, p. 178; Ellinger, R.F., Nery, E.B., Lynch, K.L., (1986) Int. J. Period. Restor. Dent., 3, p. 223; Legeros, R.Z., Daculsi, G., (1990) "Handbook of Bioactive Ceramics", Vol. II-Calcium Phosphate and Hydroxylapatite Ceramics, 2, p. 17. , edited by T. Yamamuro CRC Press, Boston
Keywords: animal experiment; animal tissue; article; Bone; Bone formation; bone growth; Calcium Compounds; calcium phosphate; Composite materials; Fiber reinforced materials; glass; Glass fibers; Glass reinforced hydroxyapatite; Granular materials; histology; hydroxyapatite; implant; Implants (surgical); Magnesium; Microstructure; Modified hydroxyapatite; nonhuman; Optical microscopy; ossification; Osteoapatite; Oxides; Phosphates; Physiological models; potassium; priority journal; rabbit; Rabbit tibiae; Sodium; tibia; X ray diffraction analysis

In vitro calcium phosphate formation on SiO 2-Na 2O-CaO-P 2O 5 glass reinforced hydroxyapatite composite: A study by XPS analysis - Santos, J.D.; Jha, L.J.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
In-vitro apatite layer formation on the surface of a newly developed glass reinforced hydroxyapatite composite was characterized using X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) equipped with energy dispersive X-ray analysis (EDXA). After 1 week soaking in an acellular simulated body fluid the composite surface was entirely covered by a Ca, P-layer, suggesting a bioactive behaviour. XPS binding energy results revealed that this surface layer was a carbonated and non- stoichiometric apatite with Ca/P ratio of 1.3. This apatite layer was composed of very fine needle-like crystallites. Comparative studies on a commercially available hydroxyapatite showed that a similar apatite layer was also formed on its surface.In-vitro apatite layer formation on the surface of a newly developed glass reinforced hydroxyapatite composite was characterized using X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) equipped with energy dispersive X-ray analysis (EDXA). After 1 week soaking in an acellular simulated body fluid the composite surface was entirely covered by a Ca, P-layer, suggesting a bioactive behaviour. XPS binding energy results revealed that this surface layer was a carbonated and non-stoichiometric apatite with Ca/P ratio of 1.3. This apatite layer was composed of very fine needle-like crystallites. Comparative studies on a commercially available hydroxyapatite showed that a similar apatite layer was also formed on its surface.
Cited By (since 1996): 42Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; FEUP, Rua dos Bragas, 4099-Porto Codex, PortugalChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8References: Ducheyne, P., (1987) J. Biomed. Mater. Res.: Appl. Biomater., 21 (A2), p. 219;Hench, L.L., (1989) J. Biomed. Mater. Res., 23, p. 685; Hench, L.L., (1991) J. Amer. Ceram. Soc., 7, p. 1487; Jarcho, M., (1988) Bioceramics 1, p. 57. , edited by H. Oonishi, H. Aoki and K. Sawai Ishiyaku Euro America, Tokyo; De Groot, K., (1980) Biomaterials, 1, p. 47; Blitterswijk, C.A.V., Koerten, H.K., Grote, J.J., (1986) Biological and Biomechanical Performance of Biomaterials, p. 27. , edited by P. Cristel, A. Meunier and A. J. C. Lee Elsevier Science Publishers, Amsterdam; Ono, K., Yamamuro, T., Nakamura, T., Kokubo, T., Kotoura, Y., (1988) J. Biomed. Mater. Res., 22, p. 869; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Japanese Association of Apatite Science (JAAS), Takayama Press System Centre Co., Inc; Manabe, A., Shigematsu, M., Kobayashi, S., (1987) High Tech Ceramics, p. 63. , edited by P. Vincenzini Elsevier Science Publishers, Amsterdam; Kitsugi, T., Yamamuro, T., Nakamura, T., Kokubo, T., Ono, M., (1987) J. Biomed. Mater. Res., 21, p. 1109; Kokubo, T., Ito, S., Shigematsu, M., Sakka, S., Yamamuro, T., (1985) J. Mater. Sci. Mater. Med., 20, p. 2001; Mestral, F., Drew, R.L.A., (1989) J. Eur. Ceram. Soc., 5, p. 47; Burnie, J., Gilchrist, T., Kobayashi, S., (1983) Ceramics in Surgery, p. 169. , edited by P. Vincenzini Elsevier Science Publishers, Amsterdam; Andersson, O.H., Liu, G., Karlsson, K.H., Niemi, L., Juhanoja, J., (1990) J. Mater. Sci. Mater. Med., 1, p. 219; Knowles, J.C., Rehman, I., Bonfield, W., (1994) Bioceramics 7, p. 85. , edited by O. H. Andersson, R. P. Happonen and A. Yli-Urpo Butterworth Heinemann, Turku, Finland; Santos, J.D., Reis, R.L., Knowles, J.C., Hastings, G.W., Monteiro, F.J., (1994) Biomaterials, 15, p. 5; Santos, J.D., Knowles, J.C., Monteiro, F.J., Hastings, G.W., (1992) Bioceramics 5, p. 35. , edited by T. Yamamuro, T. Kokubo and T. Nakamura Kokunshi Kankokai, Kyoto; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1985) J. Mater. Sci. Mater. Med., 6, p. 448; Wilson, J., Low, S., (1992) J. Appl. Biomater., 3, p. 123; Oonishi, H., Kushitani, S., Yasukawa, E., Hench, L.L., Wilson, J., Tsuji, E., Sugihara, T., (1994) Bioceramics 7, p. 139. , edited by O. H. Andersson, R.-P. Happonen and A. Yli-Urpo, Butterworth Heinemann, Turku, Finland; Neo, M., Nakamura, T., Yamamuro, T., Ohtsuki, C., Kokubo, T., Bando, Y., (1992) J. Biomed. Mater. Res., 26, p. 1419; Hyakuna, K., Yamamuro, T., Kotoura, Y., Kokubo, T., Kushitani, H., (1990) J. Biomed. Mater. Res., 24, p. 471; Kokubo, T., Kushitani, H., Sakka, S., Kitsugi, T., Yamamuro, T., (1990) J. Biomed. Mater. Res., 24, p. 721; Santos, J.D., Jha, L.J., Monteiro, F.J., (1995) Biomaterials, 16, p. 521; Li, P., Ohtsuki, C., Kokubo, T., Nakanishi, K., Soga, N., Nakamura, T., Yamamuro, T., (1993) J. Appl. Biomater., 4, p. 221; Neo, M., Kotani, S., Fujita, Y., Yamamuro, T., Bando, Y., Ohtsuki, C., Kokubo, T., (1992) J. Biomed. Mater. Res., 26, p. 255; Li, P., Yang, Q., Zhang, F., Kokubo, T., (1992) J. Mater. Sci. Mater. Med., 3, p. 452; Kokubo, T., Kushitani, H., Kitsugi, T., Yamamuro, T., (1988) Bioceramics 1, p. 157. , edited by T. Yamamuro, T. Kokubo and T. Nakamura Kokunshi Kankokai, Kyoto; Landis, W.J., Martin, J.R., (1984) J. Vac. Sci. Technol., A2, p. 1108; Andersson, O.H., Kangasniemi, I., (1991) J. Biomed. Mater. Res., 25, p. 1019; Verhoeven, J.A.T., Van Doveren, H., (1982) Surf. Sci., 123, p. 369; Rehman, I., Hench, L.L., Bonfield, W., (1994) Bioceramics 7, p. 123. , edited by O. H. Andersson, R. P. Happonen and A. Yli-Urpo Butterworth Heinemann, Turku, Finland; Turner, N.H., Murday, J.S., Ramaker, D.E., (1980) Anal. Chem., 52, p. 84
Keywords: article; Binding energy; Biocompatibility; Biodegradation; biomaterial; Calcium; calcium phosphate; Characterization; Composite materials; Composition; Energy dispersive x ray analysis; glass; Glass reinforced hydroxyapetite composite; hydroxyapatite; implant; In vitro calcium phosphate formation; Ionic concentration; molecular interaction; Nucleation; Phosphates; phosphorus; priority journal; Scanning electron microscopy; Surfaces; X ray analysis; X ray photoelectron spectroscopy

Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts - Carvalho, G.S.; Castanheira, M.; Diogo, I.; Abreu, A.M.; Sousa, J.P.; Loon, J.A.; Van Blitterswijk, C.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Fibroblasts from normal human skin were cultured for a period of 21 days in the absence or in the presence of metal ions. The effects of stainless steel (SS) corrosion products were compared to the effects of iron, chromium and nickel ions used either separately (Fe, Cr, or Ni solutions) or combined (Fe+Cr+Ni solution). At several periods of time (4, 7, 14 and 21 days) the cell cultures were analysed for the following parameters: (a) metal ion accumulation by atomic absorption spectrometry; (b) cell morphology and viability by the neutral red assay; (c) cell proliferation by DNA assessment, and enzyme activity by both (d) MTT reduction and (e) acid phosphatase activity. Results showed that SS-corrosion products and the corresponding metal ions combined at the same concentrations, Fe+Cr+Ni solution, had opposite effects on fibroblast cultures. In fact, SS-corrosion products caused no apparent effects on cell morphology nor on cell proliferation whereas Fe+Cr+Ni solution stimulated both neutral red uptake and cell proliferation. The enzymatic assays showed that SS-corrosion products caused inhibition of both MTT reduction and acid phosphatase activity in contrast to Fe+Cr+Ni solution which stimulated their activity. Furthermore, in all biological parameters studied, a strong association was observed between the effects of Fe+Cr+Ni solution and Cr alone, suggesting that Cr was the metal ion mostly involved in the stimulatory effects of the combined solution.Fibroblasts from normal human skin were cultured for 21 days in the absence, or presence, of metal ions. The effects of stainless steel (SS) corrosion products were compared to the effects of iron, chromium, and nickel ions used either separately or combined. At different periods of time, the cell cultures were analyzed for the following parameters: metal ion accumulation by atomic absorption spectrometry; cell morphology and viability by the neutral red assay; cell proliferation by DNA assessment; and enzyme activity by both MTT reduction and acid phosphatase activity. Results show that SS-corrosion products and the corresponding metal ions combined at the same concentrations, Fe+Cr+Ni solution, have opposite effects on fibroblast cultures.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; INEB-Instituto Engenharia Biomedica, Portugal Universidade do Minho, Praca Coronel Pacheco, 1, 4000 Porto, PortugalChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; acid phosphatase, 9001-77-8, 9025-88-1; chromium, 16065-83-1, 7440-47-3; DNA, 9007-49-2; iron, 14093-02-8, 53858-86-9, 7439-89-6; neutral red, 553-24-2; nickel, 7440-02-0; stainless steel, 12597-68-1References: Pohler, O.E.M., (1983) Biomaterials in Reconstructive Surgery, p. 158. , C.V. Mosby, St. Louis;Galante, J.O., Lemons, J., Spector, M., Wilson Jr., P.D., Wright, T.M., (1991) J. Orthop. Res., 9, p. 760; Henning, E.F., Raithel, H.J., Schaller, K.H., Döhler, J.R., (1992) J. Trace Elem. Electrolytes Health Dis., 6, p. 239; Maloney, W.J., Smith, R.L., Castro, F., Schurman, J., (1993) J. Bone Joint Surg., 75 A, p. 835; Jorgensen, T.J., Munno, F., Mitchell, T.G., Hungerford, D., (1983) Clin. Orthop., 176, p. 124; Jones, L.C., Hungerford, D.S., (1987) Trans Orthop. Res. Soc., 32, p. 317; Stulberg, B.N., Watson, J.T., Shull, S.L., Merritt, K., Crowe, T.D., Stulberg, S.D., Guidry, C.H., (1987) Trans Orthop. Res. Soc., 33, p. 314; Sunderman Jr., F.W., Hopfer, S.M., Swift, T., Rezuke, W.N., Ziebka, L., Highman, P., Edwards, B., Gossling, H.R., (1989) J. Orthop. Res., 7, p. 307; Merritt, K., Brown, S.A., Sharkey, N.A., (1984) J. Biomed. Mater. Res., 18, p. 991; Brown, S.A., Farnsworth, L.J., Merritt, K., Crowe, T.D., (1988) Biomed. Mater. Res., 22, p. 321; Merritt, K., Crowe, T.D., Brown, S.A., (1989) J. Biomed. Mater. Res., 23, p. 845; Merritt, K., Margevicius, R.W., Brown, S.A., (1992) J. Biomed. Mater. Res., 26, p. 1503; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., (1993) J. Biomed. Mater. Res., 27, p. 1007; Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., (1994) Cytobios, 77, p. 73; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, p. 523; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, p. 56; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., (1992) Advances in Biomaterials, p. 7. , edited by P. J. Doherty et al. Elsevier, Amsterdam; Vrouwenvelder, W.C.A., Groot, C.G., DeGroot, K., (1993) J. Biomed. Mater. Res., 27, p. 465; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., (1993) Biomaterials, 14, p. 359; Martin, A., Clynes, M., (1991) In Vitro Cell. Dev. Biol., 27 A, p. 183; Borenfreund, E., Puerner, J.A., (1983) J. Tissue Culture Methods, 9, p. 7; Hansen, M.B., Nielsen, S.E., Berg, K., (1989) J. Immunol. Methods, 119, p. 203; Rosdy, M., Grisoni, B., Claus, L.C., (1991) Biomaterials, 12, p. 511; Van Sliedregt, A., Radder, A.M., De Groot, K., Van Blitterswijk, C.A., (1992) J. Mater. Sci. Mater. Med., 3, p. 365; Caughman, W.F., Caughman, G.B., Shiflett, R.A., Rueggeberg, F., Schuster, G.S., (1991) Biomaterials, 12, p. 737; Carvalho, G.S., Bravo, I., (1993) J. Mater. Sci. Mater. Med., 4, p. 366; Harmand, M.F., Bordenave, L., Bareille, R., Naji, A., Jeandot, R., Rouais, F., Ducassou, D., (1991) J. Biomater. Sci. Polymer Edn., 2, p. 67; Katz, A., Feldman, M., Eisenbach, L., (1992) J. Immunol. Methods, 149, p. 117; Naji, A., Harmand, M.F., (1990) J. Biomed. Mater. Res., 24, p. 861; Mosmann, T., (1983) J. Immunol. Methods, 65, p. 55; Berridge, M.V., Tan, S., (1993) Arch. Biochem. Biophys., 303, p. 474
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; Absorption spectroscopy; Acid phosphatase; article; atomic absorption spectrometry; Atomic spectroscopy; Bioassay; Cell culture; Cell morphology; cell proliferation; cell structure; cell viability; Chromium; controlled study; Corrosion; Corrosion products; cytology; DNA; Enzymatic assays; Enzyme Activation; enzyme activity; Enzyme inhibition; fibroblast; human; human cell; Ions; Iron; metal; Metal ion accumulation; Metal salts; Metals; neutral red; Nickel; priority journal; Salts; Skin; skin fibroblast; Stainless steel; Steel corrosion

Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O and MgO - Santos, J.D.; Silva, P.L.; Knowles, J.C.; Talal, S.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Commercial hydroxyapatite was reinforced by adding small amounts (2 and 4 wt%) of P 2O 5-based glasses during its sintering process. The composites prepared had a chemical composition closely related to the mineral part of bone tissues in terms of trace elements usually detected, such as Na, K and Mg. X-ray diffraction analysis (XRD) showed that the glass reinforced-HA composites were composed of a HA matrix and variable amounts of tricalcium phosphate phase, depending on sintering temperature and glass composition. These composites were shown to have much higher biaxial bending strength than sintered HA, 107 MPa for Ha/2% of 35P 2O 5-35CAO-10Na 2O-10K 2O-10MgO glass composite and 28 MPa for sintered HA. The presence of β-tricalcium phosphate in the microstructure of the composites is an important factor in the reinforcement process. Commercial hydroxyapatite was reinforced by adding small amounts (2 and 4 wt%) of P 2O 5-based glasses during its sintering process. The composites prepared had a chemical composition closely related to the mineral part of bone tissues in terms of trace elements usually detected, such as Na, K and Mg. X-ray diffraction analysis (XRD) showed that the glass reinforced-HA composites were composed of a HA matrix and variable amounts of tricalcium phosphate phase, depending on sintering temperature and glass composition. These composites were shown to have much higher biaxial bending strength than sintered HA, 107 MPa for Ha/2% of 35P 2O 5-35CaO-10Na 2O-10K 2O-10MgO glass composite and 28 MPa for sintered HA. The presence of β-tricalcium phosphate in the microstructure of the composites is an important factor in the reinforcement process.
Cited By (since 1996): 49Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; Dept. of Metallurgical Engineering, FEUP, University of Porto, Rua dos Bragas, 4099 Porto Codex, PortugalChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; magnesium oxide, 1309-48-4, 1317-74-4References: Barney, V.C., Levin, M.P., Adams, D.F., (1986) J. Perio Dont., 57, p. 764;Legeros, R.Z., (1988) Adv. Dent. Res., 2, p. 164; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, p. 165. , Takayama Press System Center, JAAS, Tokyo; Ducheyne, P., (1987) J. Biomed. Mater. Res. Appl. Biomater., 21, p. 219; Heughbaert, J.C., Bonel, G., (1986) Biological and Biomechanical Performance of Biomaterials, p. 9. , edited by P. Christel, A. Meunier and A. J. C. Lee Elsevier Science Publishers B.V., Amsterdam; Ellis, L.G., Nelson, D.G.A., Featherstone, J.D.B., (1988) J. Biomed. Mater. Res., 22, p. 541; Raemdonck, W.V., Ducheyne, P., Meester, P.D., (1984) Metal and Ceramic Biomaterials, p. 143. , edited by P. Ducheyne and G. W. Hashi CRC Press, Boca Raton, FL; Shors, E.C., Holmes, R.E., (1993) An Introduction to Bioceramics, p. 181. , edited by L. L. Hench and J. Wilson World Scientific, Hong Kong; Rey, C., (1990) Biomaterials, 11, p. 14; Evans, G., Behiri, J., Currey, J., Bonfield, W., (1990) J. Mater. Sci. Mater. Med., 1, p. 38; Rey, C., Frèche, M., Heughebaert, M., Heughebaert, J.C., Lacout, J.L., Vignoles, M., Bioceramics 4, London, 1991, p. 57. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner (Butterworth-Heinemann, London); With, G., Van Dijk, H., Hattu, N., Prijs, K., (1981) J. Mater. Sci., 16, p. 1592; Akao, M., Aoki, H., Kato, K., (1981) J. Mater. Sci., 16, p. 809; Santos, J., Knowles, J., Reis, R., Monteiro, F., Hastings, G., (1994) Biomaterials, 15, p. 5; Soltesz, U., Richter, H., Kienzler, R., (1987) High Technology Ceramics, p. 110. , Elsevier Science Publishers, B.V., Amsterdam; (1971) Determination Micrographique de la Grosseur du Grain Ferritique ou Austénitique des Aciers; Daculsi, G., LeGeros, R.G., Nery, E., Lynch, K., Kerebel, B., (1989) J. Biomed. Mater. Res., 23, p. 883
Keywords: article; Bending strength; Bone; chemical composition; Composite materials; Composition; Composition effects; glass; Glass composition; Glass reinforced hydroxapatite composite; hydroxyapatite; implant; Magnesium Oxide; metal oxide; Microstructure; molecular dynamics; Phosphates; potassium derivative; priority journal; Sintering; Sintering temperature; sodium derivative; Thermal effects; Trace Elements; Tricalcium phosphate phase; X ray diffraction

Sintering effects in a glass reinforced hydroxyapatite - Knowles, J.C.; Talal, S.; Santos, J.D. (BiomaterialsBIOMATERIALS, 1996)
Glass was incorporated into hydroxyapatite (HA) to act as a sintering aid in order to improve the mechanical properties. The glass was added at 2 and 4 wt% and the powders compacted uniaxially. The compacts were sintered at a variety of temperatures (1200, 1250, 1300 and 1350°C) and the effects of the glass addition and the firing temperature were studied to determine their effects on the sintering process. It was found that the glass promoted some phase changes, related to the amount of glass added to the composite. At 1200 and 1250°C, some β-tricaicium phosphate (TCP) was found with the residual being HA. However, at 1300 and 1350°C, both β- and α-TCP were formed. The 4 wt% addition, as expected, promoted higher levels of secondary phases in the composite. The flexural bend strength (FBS) showed high values and also significant differences dependent on the amount of glass added. A 2 wt% addition gave a gradual increase in FBS with temperature. With a 4 wt% addition there was an increase in FBS, but above 1300°C there was a rapid decrease. These effects were mirrored in the linear shrinkage. Both the linear shrinkage and the FBS results were attributed to both the phase changes occurring and also change in grain size with increasing firing temperature.Glass was incorporated into hydroxyapatite (HA) to act as a sintering aid in order to improve the mechanical properties. The glass was added at 2 and 4 wt% and the powders compacted uniaxially. The compacts were sintered at a variety of temperatures (1200, 1250, 1300 and 1350°C) and the effects of the glass addition and the firing temperature were studied to determine their effects on the sintering process. It was found that the glass promoted some phase changes, related to the amount of glass added to the composite. At 1200 and 1250°C, some β- tricalcium phosphate (TCP) was found with the residual being HA. However, at 1300 and 1350°C, both β- and α-TCP were formed. The 4 wt% addition, as expected, promoted higher levels of secondary phases in the composite. The flexural bend strength (FBS) showed high values and also significant differences dependent on the amount of glass added. A 2 wt% addition gave a gradual increase in FBS with temperature. With a 4 wt% addition there was an increase in FBS, but above 1300°C there was a rapid decrease. These effects were mirrored in the linear shrinkage. Both the linear shrinkage and the FBS results were attributed to both the phase changes occurring and also change in grain size with increasing firing temperature.
Cited By (since 1996): 39Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/0142-9612(96)87287-5PubMed ID: 8830972Language of Original Document: EnglishCorrespondence Address: Knowles, J.C.; Eastman Dental Institute, Queen Mary and Westfield College, Mile End Road, London E1 4NS, United KingdomChemicals/CAS: Durapatite, 1306-06-5References: Currey, J.D., (1984) The Mechanical Adaptations of Bones, , Princeton University Press;Brown, W.E., Chow, L., Chemical composition of bone mineral (1976) Ann Res Mater Sci, 6, pp. 213-226; Glimcher, M.J., Recent studies of the mineral phase in bone and its possible linkage to the organic matrix by protein bound phosphate conds (1984) Phil Trans R Soc Land, B304, pp. 479-508; Cook, S.D., Thomas, K.A., Kay, J.F., Jarcho, M., Hydroxyapatite-coated porous titanium for use as an orthopaedic biologic attachment system (1980) Clin Orthop, 230, pp. 303-312; Patka, P., Den Otter, G., De Groot, K., Driessen, A.A., Reconstruction of large bone defects with calcium phosphate ceramics. An experimental study (1985) Neth J Surg, 37, p. 38; Wolford, L.M., Wardrop, R.W., Hartog, J.M., Coralline porous hydroxyapatite as a bone graft substitute in orthognathic surgery (1987) J Oral Maxillofac Surg, 45, pp. 1034-1042; Santos, J.D., Morrey, S., Hastings, G.W., Monteiro, F.J., The production and characterisation of a hydroxyapatite ceramic material (1991) Bioceramics, Vol 4. Proceedings of the 4th International Symposium on Ceramics in Medicine, 4, pp. 71-78. , Bonfield W, Hastings GW, Tanner KE, eds. London: Butterworth Heinemann; Dörre, E., Dawihl, W., Ceramic hip endoprostheses (1980) Mechanical Properties of Biomaterials, pp. 113-127. , Hastings GW, Williams DF, eds. New York: Wiley; Murray, M.G.S., Ponton, C.B., Marquis, P.M., Emulsion processing of hydroxyapatite (1992) Bioceramics, Vol 4. Proceedings of the 4th International Symposium on Ceramics in Medicine, 4, pp. 15-22. , Kyoto: Kobunshi Kankokai; Puajindanetr, S., Best, S.M., Bonfield, W., Characterisation and sintering of precipitated hydroxyapatite (1994) Br Ceram Trans, 93 (3), pp. 96-99; Knowles, J.C., Bonfield, W., Development of a glass reinforced hydroxyapatite with enhanced mechanical properties. The effect of glass composition on mechanical properties and its relationship to phase changes (1993) J Biomed Mater Res, 27, pp. 159-1598; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15 (1), pp. 5-10; Knowles, J.C., Development of hydroxyapatite with enhanced mechanical properties: Effect of high glass additions on mechanical properties and phase stability of sintered hydroxyapatite (1994) Br Ceram Trans, 93 (3), pp. 100-103; Ruys, A.J., Wei, M., Sorrell, C.C., Dickson, M.R., Brandwood, A., Milthorpe, B.K., Sintering effects on the strength of hydroxyapatite (1995) Biomaterials, 16, pp. 409-415; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions. Structure and properties of the composites (1995) J Mater Sci Mater Med, , to be published; Soltesz, U., Ritcher, H., Keinzler, R., (1987) High Tech Ceramics, p. 110. , Vincenzini P, ed. Amsterdam: Elsevier; Laugier, M.T., New formula for indentation toughness in ceramics (1987) J Mater Sci Lett, 6, pp. 355-356; Knowles, J.C., Abrahams, I., Bonfield, W., Effect of reinforcing glass composition on phase transformation and crystallographic parameters in hydroxyapatite (1993) Bioceramics, 6, pp. 191-196. , Ducheyne P, Christiansen D, eds. Butterworth-Heinemann
Keywords: article; Bending strength; Biomaterials; calcium phosphate; Chemistry, Physical; Durapatite; glass; Glass reinforced hydroxyapatite; Grain growth; hydroxyapatite; priority journal; Sintering; Sintering aid; temperature; tensile strength; Tricalcium phosphate; X-Ray Diffraction

Computerized fetal heart rate analysis in labour based on 2-s sampling. Can it proceed with confidence? [1] - Bernardes, J.; Garrido, A.; Chang, A.; Sahota, D.S.; Reed, N.N.; James, D.K.; Mohajer, M.P. (European Journal of Obstetrics Gynecology and Reproductive BiologyEUR. J. OBSTET. GYNECOL. REPROD. BIOL., 1995)
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: EOGRAdoi: 10.1016/0301-2115(95)02215-SPubMed ID: 8674558Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Instituto Engenharia Biomedica, Praca Coronel Pacheco 1, 4000 Porto, Portugal
Keywords: computer analysis; Computers; Female; Fetal monitoring; fetus; fetus heart rate; Heart Rate, Fetal; human; labor; Labor, Obstetric; letter; measurement; Pregnancy; priority journal; sampling; Time Factors

The effect of hydroxyapatite thickness on metal ion release from stainless steel substrates - Sousa, S.R.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
The corrosion behaviour of 350 stainless steel coated with hydroxyapatite, HA, by plasma spraying was studied in Hank's Balanced Salt Solution, HBSS, and compared with that of polished passivated surfaces. Two different nominal thicknesses, 50 μm and 200 μm, corresponding to what one might consider a thin and a thick coating, respectively, were used. Only HA coatings with a thickness of 200 μm were capable of reducing the electrical charge consumed at constant potential to values lower than those measured for polished surfaces. However, no HA detachment occurred for both thicknesses, as opposed to what has been found in a previous work with Ti6A14V alloy coated with 50 μm HA. No iron, chromium or nickel were detected in solution by Atomic Absorption Spectroscopy with electrothermal atomization (ET-AAS). These elements were also absent from the bulk of the HA coating, both after a 6 month immersion period and electrochemical accelerated tests. The data indicate that in spite of the relatively low corrosion resistance of stainless steel as compared to that of titanium alloys, a thin (50 μm) HA coating prevents the release of metal ions, while remaining adherent to the substrate.The corrosion behaviour of 350 stainless steel coated with hydroxyapatite, HA, by plasma spraying was studied in Hank's Balanced Salt Solution, HBSS, and compared with that of polished passivated surfaces. Two different nominal thicknesses, 50 μm and 200 μm, corresponding to what one might consider a thin and a thick coating, respectively, were used. Only HA coatings with a thickness of 200 μm were capable of reducing the electrical charge consumed at constant potential to values lower than those measured for polished surfaces. However, no HA detachment occurred for both thicknesses, as opposed to what has been found in a previous work [1] with Ti6Al4V alloy coated with 50 μm HA. No iron, chromium or nickel were detected in solution by Atomic Absorption Spectroscopy with electrothermal atomization (ET-AAS). These elements were also absent from the bulk of the HA coating, both after a 6 month immersion period and electrochemical accelerated tests. The data indicate that in spite of the relatively low corrosion resistance of stainless steel as compared to that of titanium alloys, a thin (50 μm) HA coating prevents the release of metal ions, while remaining adherent to the substrate.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00134324Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; INEB, Instituto Engenharia Biomedica, Praca do Coronel Pacheco, 1, 4050 Porto, Portugal
Keywords: Absorption spectroscopy; atomic absorption spectrometry; Atomic absorption spectroscopy; Atomic spectroscopy; balanced salt solution; Calcium Compounds; Chromium; comparative study; conference paper; Corrosion; Corrosion behaviour; Electric charge; electrochemistry; Hank balanced salt solution; hydroxyapatite; immersion; Inorganic coatings; Ions; Iron; metal ion; Metal ion release; Nickel; Plasma spraying; priority journal; Stainless steel; Stainless steel substrates; Substrates; thickness; Thickness effect; Titanium; Titanium alloys

In vitro calcification of orthopaedic implant materials - Leitao, E.; Barbosa, M.A.; De Groot, K. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
The formation of an apatite-like layer is achieved by immersing Ti6A14V and TiA12.5Fe substrata in Hank's Balanced Salt Solution (HBSS). The layer was characterized by several techniques, namely X-ray microanalysis, X-ray diffraction and X-ray photoelectron spectroscopy. The results suggest that the layer produced by immersion in HBSS is in the form of an amorphous apatite. The pH and the concentrations of calcium and phosphate were monitored as a function of time. In vitro tests with rat bone marrow were performed in order to mimic the bone/biomaterial interface. They were performed on both immersed and non-immersed samples. The in vitro bone marrow results suggest that the apatite-like layer formed may improve the bone bonding characteristics of the studied titanium alloys.The formation of an apatite-like layer is achieved by immersing Ti6Al4V and TiAl2.5Fe substrata in Hank's Balanced Salt Solution (HBSS). The layer was characterized by several techniques, namely X-ray microanalysis, X-ray diffraction and X-ray photoelectron spectroscopy. The results suggest that the layer produced by immersion in HBSS is in the form of an amorphous apatite. The pH and the concentrations of calcium and phosphate were monitored as a function of time. In vitro tests with rat bone marrow were performed in order to mimic the bone/biomaterial interface. They were performed on both immersed and non-immersed samples. The in vitro bone marrow results suggest that the apatite-like layer formed may improve the bone bonding characteristics of the studied titanium alloys.
Cited By (since 1996): 23Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00134330Language of Original Document: EnglishCorrespondence Address: Leitao, E.; Instituto de Engenharia Biomedica, Faculdade de Engenharia, Universidade do Porto, Praca Coronel Pacheco 1, 4050 Porto, Portugal
Keywords: Amorphous apatite; Amorphous materials; animal cell; Apatite; balanced salt solution; Bone; bone marrow; Calcification; Calcification (biochemistry); Calcium; calcium phosphate; conference paper; Hank balanced salt solution; immersion; implantation; Implants (surgical); metal implantation; Microanalysis; nonhuman; orthopedics; pH; phosphate; Phosphates; priority journal; rat; Spectroscopy; surface property; time; Titanium; Titanium alloys; X ray analysis; X ray diffraction; X ray photoelectron spectroscopy

Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions: Structure and properties of the composites - Santos, J.D.; Reis, R.L.; Monteiro, F.J.; Knowles, J.C.; Hastings, G.W. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
Phosphate- and silicate-based glasses were added to hydroxyapatite in order to improve its mechanical properties and to fabricate composites with different degrees of bioactivity. A strong chemical bonding was obtained between hydroxyapatite and the phosphate-based glasses leading to samples approaching theoretical density, according to density measurements and scanning electron microscopy. Bioglass® additions led to the formation of a complex calcium phosphate silicate which hampered the reinforcement process. The fracture toughness of the hydroxyapatite-glass composites was shown to be within the 1.1-1.2 MPam(1/2) range, which is double that determined for sintered hydroxyapatite. A 2 μm thick apatite layer was observed on the surface of the hydroxyapatite-glass composites after 48 h immersion in a simulated human blood plasma, whereas only a few apatite crystals were detected on sintered hydroxyapatite after 7 days immersion. From the results obtained we anticipate that the composites might show a higher rate of bone bonding, leading to enhanced bioactivity.Phosphate- and silicate-based glasses were added to hydroxyapatite in order to improve its mechanical properties and to fabricate composites with different degrees of bioactivity. A strong chemical bonding was obtained between hydroxyapatite and the phosphate-based glasses leading to samples approaching theoretical density, according to density measurements and scanning electron microscopy. Bioglass (R) additions led to the formation of a complex calcium phosphate silicate which hampered the reinforcement process. The fracture toughness of the hydroxyapatite-glass composites was shown to be within the 1.1-1.2 MPa m 1/2 range, which is double that determined for sintered hydroxyapatite. A 2 μm thick apatite layer was observed on the surface of the hydroxyapatite-glass composites after 48 h immersion in a simulated human blood plasma, whereas only a few apatite crystals were detected on sintered hydroxyapatite after 7 days immersion. From the results obtained we anticipate that the composites might show a higher rate of bone bonding, leading to enhanced bioactivity.
Cited By (since 1996): 41Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00120303Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB-National Inst. Biomedical Engn., Department Metallurgical Engineering, FEUP, University of Porto, Rua dos Bragas 4099-Porto Codex, Portugal
Keywords: Adhesion; article; Bioactivity; Bioglass; Biomaterials; Bone; bone prosthesis; calcium phosphate; chemical binding; Chemical bonds; chemical composition; Chemical structure; Complex calcium phosphate silicate; Composite materials; crystal; density; Density measurement (specific gravity); glass; Human blood plasma; hydroxyapatite; Liquid phase sintering; Mechanical properties; Mechanics; phosphate; Phosphates; plasma; priority journal; Scanning electron microscopy; silicate; Silicates; Sintering; Structure (composition); surface property; thickness

Modifications in the molecular structure of hydroxyapatite induced by titanium ions - Ribeiro, C.C.; Barbosa, M.A.; Machado, A.A.S.C.; Tudor, A.; Davies, M.C. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
The purpose of this study was to contribute to the understanding of the effect of titanium ions released from a metallic substrate on the molecular structure of hydroxyapatite. The effects of pH, time of incubation and concentration of titanium ions were investigated. The solids were analysed by X-ray diffraction, Fourier transform infrared spectroscopy, Fourier transform Raman spectroscopy, energy dispersive X-ray analysis and thermogravimetric analysis. The results clearly indicate the presence of a titanium phosphate, Ti(HPO 4) 2·nH 2O (n = 1-3), which probably has a double layered structure. The formation of this compound is dependent on the titanium concentration and its crystallinity increases with the time of incubation. The purpose of this study was to contribute to the understanding of the effect of titanium ions released from a metallic substrate on the molecular structure of hydroxyapatite. The effects of pH, time of incubation and concentration of titanium ions were investigated. The solids were analysed by X-ray diffraction, Fourier transform infrared spectroscopy, Fourier transform Raman spectroscopy, energy dispersive X-ray analysis and thermogravimetric analysis. The results clearly indicate the presence of a titanium phosphate, Ti(HPO 4) 2·nH 2O (n = 1-3), which probably has a double layered structure. The formation of this compound is dependent on the titanium concentration and its crystallinity increases with the time of incubation.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00134326Language of Original Document: EnglishCorrespondence Address: Ribeiro, C.C.; Instituto de Engenharia Biomedica, Praca do Coronel Pacheco, 1, 4050 Porto, Portugal
Keywords: Calcium Compounds; Chemical structure; Coatings; conference paper; Crystallinity; Crystallization; Dissolution; Energy dispersive x ray analysis; Fourier transform infrared spectroscopy; Fourier transform Raman spectroscopy; hydroxyapatite; Implants (surgical); incubation time; infrared spectroscopy; Ions; metal ion; Molecular Structure; pH; pH effects; phosphate; Phosphates; priority journal; Raman spectrometry; Raman spectroscopy; Thermogravimetric analysis; thermogravimetry; time; Titanium; Titanium compounds; X ray analysis; X ray diffraction

Stainless steel corrosion products cause alterations on mouse spleen cellular populations - Tracana, R.B.; Pereira, M.L.; Abreu, A.M.; Sousa, J.P.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
Stainless steel is a metallic biomaterial commonly used in orthopaedic surgery. In this study we looked at the effects of stainless steel corrosion products on spleen, in order to evaluate their potential immunotoxicological effects. For this purpose stainless steel, type AISI 316L, was electrochemically dissolved in a physiological salt solution. The final solution, containing 490 μg/ml Fe, 224 μg/ml Cr and 150 μg/ml Ni, was injected subcutaneously in mice. After several periods of time (4, 10 and 14 days) spleens were removed and analysed for: (a) their contents in Fe, Cr and Ni, (b) histological alterations, (c) enumeration of cellular populations. Results showed that stainless steel corrosion products accumulated in spleen, caused histological alterations, and induced changes in cellular populations. When compared to chromium and nickel, iron was the metal ion preferentially accumulated in spleen. The increase of the multinucleated giant cell population was accompanied by depletion of lymphocyte populations. This study indicates that stainless steel corrosion products can spread systemically and accumulate in spleen inducing histological and cellular alterations which may give rise to immunotoxicological consequences.Stainless steel is a metallic biomaterial commonly used in orthopaedic surgery. In this study we looked at the effects of stainless steel corrosion products on spleen, in order to evaluate their potential immunotoxicological effects. For this purpose stainless steel, type AISI 316L, was electrochemically dissolved in a physiological salt solution. The final solution, containing 490 μg/ml Fe, 224 μg/ml Cr and 150 μg/ml Ni, was injected subcutaneously in mice. After several periods of time (4, 10 and 14 days) spleens were removed and analysed for: (a) their contents in Fe, Cr and Ni, (b) histological alterations, (c) enumeration of cellular populations. Results showed that stainless steel corrosion products accumulated in spleen, caused histological alterations, and induced changes in cellular populations. When compared to chromium and nickel, iron was the metal ion preferentially accumulated in spleen. The increase of the multinucleated giant cell population was accompanied by depletion of lymphocyte populations. This study indicates that stainless steel corrosion products can spread systematically and accumulate in spleen inducing histological and cellular alterations which may give rise to immunotoxicological consequences.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00121249Language of Original Document: EnglishCorrespondence Address: Tracana, R.B.; Natl. Inst. Biomedical Engineering, INEB, Praca Coronel Pacheco 1, 4000 Porto, Portugal
Keywords: animal cell; animal experiment; animal tissue; Animalia; article; Biocompatibility; biomaterial; cell population; Cells; Chromium; Chronoamperometry; controlled study; Corrosion; Corrosion products; Dissolution; electrochemistry; giant cell; histology; immunology; immunotoxicity; Immunotoxicological effects; Ions; Iron; Lymphocyte; lymphocyte subpopulation; male; mouse; Nickel; nonhuman; orthopedic surgery; priority journal; sodium chloride; Spleen; spleen cell; Stainless steel; Steel corrosion; subcutaneous drug administration; toxicity

Surface modifications of glass-reinforced hydroxyapatite composites - Santos, J.D.; Jha, L.J.; Monteiro, F.J. (BiomaterialsBIOMATERIALS, 1995)
Surface modifications of glass-reinforced hydroxyapatite composites immersed in a simulated physiological solution were studied using X-ray photoelectron spectroscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy. In the first stages of the apatite formation process, calcium and silicon ions were leached out from the surface of the composites. After 12 days of immersion, apatite crystals were detected on the surface indicating bioactive behaviour. Sodium ions attributed to sodium sulphate were also found in the apatite layer. Bound water on the surface also increased with immersion time.Surface modifications of glass-reinforced hydroxyapatite composites immersed in a simulated physiological solution were studied using X-ray photoelectron spectroscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy. In the first stages of the apatite formation process, calcium and silicon ions were leached out from the surface of the composites. After 12 days of immersion, apatite crystals were detected on the surface indicating bioactive behaviour. Sodium ions attributed to sodium sulphate were also found in the apatite layer. Bound water on the surface also increased with immersion time.
Cited By (since 1996): 24Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/0142-9612(95)91124-HPubMed ID: 7492715Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Dept Metallurgical Engineering, FEUP, University of Porto, Rua dos Bragas 4099-Porto Codex, PortugalChemicals/CAS: Biocompatible Materials; Calcium, 7440-70-2; Glass; Hydroxyapatites; Phosphorus, 7723-14-0; Silicon, 7440-21-3; Sodium, 7440-23-5
Keywords: Apatite; article; Bioactive glass; Biocompatible Materials; Biomaterials; Calcium; chemical composition; Composite materials; Electron Probe Microanalysis; glass; Glass reinforced hydroxyapatite composites; Hydrogen-Ion Concentration; hydroxyapatite; Hydroxyapatites; immersion; Ions; Leaching; Microscopy, Electron, Scanning; Phosphates; phosphorus; priority journal; Scanning electron microscopy; Silicon; Sodium; sodium chloride; sodium sulfate; Spectrometry, X-Ray Emission; Spectroscopy; Surface modification; Surface Properties; surface property; Surface treatment; Water; X ray; X ray photoelectron spectroscopy; X ray spectroscopy

Mouse inflammatory response to stainless steel corrosion products - Tracana, R.B.; Sousa, J.P.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1994)
Corrosion occurs regularly following long-term implantation of stainless steel. Little is known about the inflammatory and immunological potential of stainless steel corrosion products. AISI 316L stainless steel was anodically dissolved in a physiologically solution, HBSS, through a chronoamperometric process by imposing an external constant current of 0.5 mA. The solution, containing 245 μg of Fe, 112 μg of Cr, 75 μg of Ni and 13 μg of Mo, was injected in the peritoneal cavity of male C57BL/6 mice. Five animals were used per survival period of time: 4, 16, 24, and 48 h, 1, 2, 4, 8 and 16 weeks. Three control mice per survival period of time were injected with HBSS. For each assay, peritoneal samples were analysed not only for the total number of cells but also for the percentages of macrophages, lymphocytes and polymorphonuclear (PMN) cells, which were estimated by differential counting on Wright-stained cytocentrifuge preparations. Our follow-up study showed that stainless steel corrosion products induced an acute inflammatory response for a period of one week as demonstrated by the influx of PMN cells and macrophages. In contrast neither a chronic inflammation nor an immune response was observed indicating that the stainless steel solution caused a minor tissue response.A follow-up study of the changes to mouse peritoneal cell populations, succeeding intraperitoneal injection of stainless steel corrosion products, in order to assess the inflammatory response to such metals was presented. AISI stainless steel was anodically dissolved in a physiologically solution, Hank's balanced salt solution (HBSS), which was injected in the peritoneal cavity of male mice. Five animals were designated per survival time interval of 4, 16, 24, and 48 h, 1, 2, 4, 8 and 16 weeks. Three control mice per survival period of time were treated with HBSS. For each assay, peritoneal samples were tested for total number of cells and percentages of macrophages, lymphocytes and polymorphonuclear (PMN) cells. The follow-up study revealed that stainless steel corrosion products induced an acute inflammatory response for a duration of one week as shown by the influx of PMN cells and macrophages. In contrast, neither a chronic inflammation nor an immune response was noted suggesting that stainless steel solution caused a minor tissue response.
Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00120337Language of Original Document: EnglishCorrespondence Address: Tracana, R.B.; Nat. Inst. Biomedical Engineering, Praca Coronel Pacheco 14000 Porto, Portugal
Keywords: animal cell; animal experiment; Animalia; article; Assays; Cell Count; Cells; Chromium; Chronoamperometry; controlled study; Corrosion; Dissolution; follow up; immune response; immunology; Inflammation; Inflammatory response; Iron; Lymphocyte; Lymphocytes; macrophage; Macrophages; male; metal implantation; Mice (animal); molybdenum; mouse; Nickel; nonhuman; Peritoneal cavity; Polymorphonuclear; polymorphonuclear cell; priority journal; Stainless steel; time; Tissue; Wright stained cytocentrifuge

Stability of hydroxylapatite plasma-sprayed coated Ti-6Al-4V under cyclic bending in simulated physiological solutions - Reis, R.L.; Monteiro, F.J.; Hastings, G.W. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1994)
The aim of this research was to study the stability of plasma-sprayed coated metal systems and to evaluate their susceptibility to the occurrence of corrosion fatigue. Hydroxylapatite plasma-sprayed coated samples of Ti-6Al-4V were studied under cyclic bending. During fatigue testing samples were immersed in a simulated physiological solution and mechanical and electrochemical degradation were monitored. Applied loads were intended to crack the ceramic coating and not the metal substrate. Electrochemical impedance spectroscopy was used to further characterize the electrochemical behaviour. No increase in tendency to corrode was detected in open-circuit corrosion fatigue testing. It appears as if the coating cracking does not increase metal substrate corrosion susceptibility. The coating integrity has been seriously affected, with marked decrease in thickness, due to the synergistic effect of load and presence of simulated body fluids environment. Impedance results, however, show a general tendency to an increase in corrosion kinetics after corrosion fatigue testing.The aim of this research was to study the stability of plasma-sprayed coated metal systems and to evaluate their susceptibility to the occurrence of corrosion fatigue. Hydroxylapatite plasma-sprayed coated samples of Ti-6Al-4V were studied under cyclic bending. During fatigue testing samples were immersed in a simulated physiological solution and mechanical and electrochemical degradation were monitored. Applied loads were intended to crack the ceramic coating and not the metal substrate. Electrochemical impedance spectroscopy was used to further characterize the electrochemical behaviour. No increase in tendency to corrode was detected in open-circuit corrosion fatigue testing. It appears as if the coating cracking does not increase metal substrate corrosion susceptibility. The coating integrity has been seriously affected, with marked decrease in thickness, due to the synergistic effect of load and presence of simulated body fluids environment. Impedance results, however, show a general tendency to an increase in corrosion kinetics after corrosion fatigue testing.
Cited By (since 1996): 35Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00058983Language of Original Document: EnglishCorrespondence Address: Reis, R.L.; INEB-National Inst. Biomedical Engn., Faculty of Engineering, University of Porto, Rua dos Bragas, 4099 Porto Codex, Portugal
Keywords: article; Bending (deformation); biomaterial; biomechanics; body fluid; Ceramic coatings; ceramics; controlled study; Corrosion; Corrosion fatigue; Corrosion susceptibility; Degradation; Electrochemical impedance spectroscopy; electrochemistry; fatigue; Fatigue testing; hydroxyapatite; impedance; mechanical stress; Physiological solutions; Plasma spraying; priority journal; sodium chloride; Solutions; Spectroscopy; Stability; Substrates; thickness; Titanium; Titanium alloys